The Cardiovascular Health Study: design and rationale. - Fried, L P; Borhani, N O; Enright, P; Furberg, C D; Gardin, J M; Kronmal, R A; Kuller, L H; Manolio, T A; Mittelmark, M B; Newman, A (Ann Epidemiol, 1991)
The Cardiovascular Health Study (CHS) is a population-based, longitudinal study of coronary heart disease and stroke in adults aged 65 years and older. The main objective of the study is to identify factors related to the onset and course of coronary heart disease and stroke. CHS is designed to determine the importance of conventional cardiovascular disease (CVD) risk factors in older adults, and to identify new risk factors in this age group, especially those that may be protective and modifiable. The study design called for enrollment of 1250 men and women in each of four communities: Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Pittsburgh, Pennsylvania. Eligible participants were sampled from Medicare eligibility lists in each area. Extensive physical and laboratory evaluations were performed at baseline to identify the presence and severity of CVD risk factors such as hypertension, hypercholesterolemia and glucose intolerance; subclinical disease such as carotid artery atherosclerosis, left ventricular enlargement, and transient ischemia; and clinically overt CVD. These examinations in CHS permit evaluation of CVD risk factors in older adults, particularly in groups previously under-represented in epidemiologic studies, such as women and the very old. The first of two examination cycles began in June 1989. A second comprehensive examination will be repeated three years later. Periodic interim contacts are scheduled to ascertain and verify the incidence of CVD events, the frequency of recurrent events, and the sequellae of CVD.
Keywords: Aged; Cerebrovascular Disorders; Coronary Disease; Epidemiologic Methods; Female; Health Status; Humans; Longitudinal Studies; Male; Physical Examination; Research Design; Risk Factors; United States

Lipoprotein lipids in older people. Results from the Cardiovascular Health Study. The CHS Collaborative Research Group. - Ettinger, W H; Wahl, P W; Kuller, L H; Bush, T L; Tracy, R P; Manolio, T A; Borhani, N O; Wong, N D; O'Leary, D H (Circulation, 1992)
BACKGROUND: Cardiovascular disease is the leading cause of death and disability in older people. There is little information about the distributions of risk factors in older populations. This article describes the distribution and correlates of lipoprotein lipids in people greater than or equal to 65 years old. METHODS AND RESULTS: Lipoprotein lipid concentrations were measured in 2,106 men (M) and 2,732 women (F) who were participants in the Cardiovascular Health Study, a population-based epidemiological study. Distributions of lipids by age and sex and bivariate and multivariate relations among lipids and other variables were determined in cross-sectional analyses. Mean concentrations of lipids were cholesterol: M, 5.20 +/- 0.93 mmol/l (201 +/- 36 mg/dl) and F, 5.81 +/- 0.98 mmol/l (225 +/- 38 mg/dl); triglyceride (TG): M, 1.58 +/- 0.85 mmol/l (140 +/- 75 mg/dl) and F, 1.57 +/- 0.78 mmol/l (139 +/- 69 mg/dl); high density lipoprotein cholesterol (HDL-C): M, 1.23 +/- 0.33 mmol/l (48 +/- 16 mg/dl), and F, 1.53 +/- 0.41 mmol/l (59 +/- 16 mg/dl); low density lipoprotein cholesterol (LDL-C): M, 3.27 +/- 0.85 mmol/l (127 +/- 33 mg/dl) and F, 3.57 +/- 0.93 mmol/l (138 +/- 36 mg/dl). The total cholesterol to HDL-C ratios were M, 4.49 +/- 1.29 and F, 4.05 +/- 1.22. TG, total cholesterol, and LDL-C concentrations were lower with increasing age, the last more evident in men than in women. TG concentration was positively associated with obesity (in women), central fat patterning, glucose intolerance, use of beta-blockers (in men), and use of estrogens (in women) and negatively associated with age, renal function, alcohol use, and socioeconomic status. In general, HDL-C had opposite relations with these variables, except that estrogen use was associated with higher HDL-C concentrations. LDL-C concentration was associated with far fewer variables than the other lipids but was negatively associated with age in men and women and positively correlated with obesity and central fat patterning and negatively correlated with renal function and estrogen use in women. There were no differences in total cholesterol and LDL-C concentrations among participants with and without prevalent coronary heart disease and stroke, but TG concentration was higher and HDL-C lower in men with both coronary heart disease and stroke and in women with coronary heart disease. CONCLUSIONS: Cholesterol and cholesterol/HDL-C ratio were lower and HDL-C higher than previously reported values in older people, suggesting that lipid risk profiles may be improving in older Americans. TG and HDL-C concentrations, and to a lesser extent LDL-C, were associated with potentially important modifiable factors such as obesity, glucose intolerance, renal function, and medication use.
Keywords: Aged; Aging; Cardiovascular Diseases; Cardiovascular Physiological Phenomena; Cholesterol, HDL; Cholesterol, LDL; Cross-Sectional Studies; Female; Health Status; Humans; Lipids; Lipoproteins; Male; Multivariate Analysis; Triglycerides

Epidemiology of low cholesterol levels in older adults. The Cardiovascular Health Study. - Manolio, T A; Ettinger, W H; Tracy, R P; Kuller, L H; Borhani, N O; Lynch, J C; Fried, L P (Circulation, 1993)
BACKGROUND: Low cholesterol levels have been associated with increased mortality from stroke, cancer, and other noncardiovascular diseases, but the reasons for this association remain unclear. One explanation is that persons with low cholesterol levels have early or occult disease that eventually leads to their deaths. METHODS AND RESULTS: This possibility was explored in 2,091 men and 2,714 women 65-100 years old in the Cardiovascular Health Study, a multicenter observational study of risk factors for heart disease and stroke in older adults. Cholesterol levels < or = 160 mg/dL were present in 11.6% of men and 3.7% of women and increased in prevalence with age. After adjustment for age, total cholesterol levels in this range were associated with a twofold increased prevalence of treated diabetes in men and women and with a twofold increased prevalence of cancer diagnosed in the preceding 5 years in women only. Low cholesterol was also associated with lower levels of hemoglobin, albumin, and factor VII, suggesting a link with hepatic synthetic function. On multivariate analysis, factors most strongly associated with low cholesterol levels in men and women were decreased factor VII levels, decreased albumin, and diabetes. CONCLUSIONS: Cross-sectional associations with low cholesterol levels differ by sex and suggest poorer health by some measures. The observed relations with treated diabetes and impaired hepatic synthetic function should be examined for risk of mortality in longitudinal data from this and other observational studies.
Keywords: Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Cardiovascular Physiological Phenomena; Cholesterol; Female; Health Status; Humans; Longitudinal Studies; Male; Prevalence; Probability; Regression Analysis; Risk Factors

Serum fructosamine as a screening test for diabetes in the elderly: a pilot study. - Cefalu, W T; Ettinger, W H; Bell-Farrow, A D; Rushing, J T (J Am Geriatr Soc, 1993)
OBJECTIVE: To determine the value of serum glycated protein, measured as serum fructosamine, as a screening test for diabetes in the elderly. DESIGN: Cross-sectional pilot study. SETTING: Ambulatory research clinic in university setting. PATIENTS: One hundred fifty-seven consecutive community-dwelling participants in the Cardiovascular Health Study, average age 71.8 + 5 (mean +/- SD, range 65-88 years). MEASUREMENTS: Serum fructosamine levels (first and second generation assay) were obtained. All subjects who did not have a diagnosis of diabetes were given a 75-g glucose tolerance test (GTT). RESULTS: Twenty-six subjects (17%) (10 previously diagnosed, 16 undiagnosed and asymptomatic) had diabetes mellitus, and 38 subjects (24%) had impaired glucose tolerance by history or by the GTT (WHO criteria). Only the 16 asymptomatic diabetics were included in the analysis for the pilot study. There was a significant difference in the fasting fructosamine level between non-diabetics and asymptomatic diabetics for the first generation (2.06 +/- .21 vs 2.53 +/- .49 mMol/L, P < 0.0015) and second generation assay (221 +/- 27 vs 269 +/- 48 mMol/L, P < 0.0012). Receiver operator curves were constructed to evaluate the test characteristics of serum fructosamine. Using a point of > or = 2.3 mMol/L for the first-generation assay, the sensitivity to detect asymptomatic diabetes was 75%, specificity 83%, and positive predictive value 35%. To detect both diabetes and impaired glucose tolerance using a cutpoint of > or = 2.3 mMol/L, the sensitivity was 24%, specificity 95%, and positive predictive value 68%. Employing a cut point of 250 muMol/L for the second generation assay, the sensitivity to detect diabetes was 81%, specificity 87%, and positive predictive value 43%. However, to detect diabetes and glucose intolerance using the second generation assay, the sensitivity was 39% and specificity was 86%. CONCLUSION: This study demonstrated that a single measurement of either first or second generation fructosamine showed promise as a screening test for diabetes, but not impaired glucose tolerance, in older people.
Keywords: Aged; Diabetes Mellitus; Female; Fructosamine; Glucose Tolerance Test; Hexosamines; Humans; Insulin; Male; Pilot Projects; Predictive Value of Tests; Sensitivity and Specificity

Smoking and lung function in elderly men and women. The Cardiovascular Health Study. - Higgins, M W; Enright, P L; Kronmal, R A; Schenker, M B; Anton-Culver, H; Lyles, M (JAMA, 1993)
OBJECTIVE: To investigate relationships between cigarette smoking and pulmonary function in elderly men and women. DESIGN: Cross-sectional analysis of baseline data from a prospective, population-based study of risk factors, preclinical, and overt cardiovascular and pulmonary disease. SETTING: Defined communities in Forsyth County, North Carolina; Pittsburgh, Pa; Sacramento County, California; and Washington County, Maryland. POPULATION: A total of 5201 noninstitutionalized men and women 65 years of age and older. MAIN OUTCOME MEASURES: Pulmonary function; means of forced expiratory volume in 1 second (FEV1) and forced vital capacity and prevalence of low FEV1 levels. RESULTS: Prevalence of cigarette smoking was 10% to 20% and higher in women than men and in blacks than whites. Forced vital capacity and FEV1 levels were related positively to height and white race and negatively to age and waist girth. Age- and height-adjusted FEV1 means were 23% and 18% lower in male and female current smokers, respectively, than in never smokers but not reduced in never smokers currently living with a smoker. Smokers who quit before age 40 years had FEV1 levels similar to never smokers, but FEV1 levels were lower by 7% and 14% in smokers who quit at ages 40 to 60 years and older than 60 years, respectively. Lung function was related inversely to pack-years of cigarette use. Prevalence rates of impaired lung function were highest in current smokers and lowest in never smokers. Regression coefficients for the smoking variables were smaller in persons without cardiovascular or respiratory conditions than in the total cohort. CONCLUSIONS: Cigarette smoking is associated with reduced pulmonary function in elderly men and women. However, smokers who quit, even after age 60 years, have better pulmonary function than continuing smokers.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Anthropometry; Cardiovascular Diseases; Cross-Sectional Studies; European Continental Ancestry Group; Female; Forced Expiratory Volume; Humans; Lung Diseases; Male; Prevalence; Prospective Studies; Reference Values; Respiratory Function Tests; Risk Factors; Smoking; United States; Vital Capacity

Spirometry reference values for women and men 65 to 85 years of age. Cardiovascular health study. - Enright, P L; Kronmal, R A; Higgins, M; Schenker, M; Haponik, E F (Am Rev Respir Dis, 1993)
Pulmonary function was assessed by spirometry in 5,201 ambulatory elderly participants of the Cardiovascular Health Study, sampled from four communities. A stringent quality assurance program exceeded American Thoracic Society (ATS) recommendations for spirometry. Less than 6% of the participants were unable to perform three acceptable spirometry maneuvers. A "healthy" subgroup of 777 women and men 65 to 85 yr of age was identified by excluding smokers and those with lung disease and other factors determined to independently, significantly, and negatively influence the FEV1. Results from black participants were examined separately. Reference equations and normal ranges for FEV1, FVC, and the FEV1/FVC ratio were determined from the healthy group. The results demonstrate differences in predicted values as great as 20% (0.5 to 1 L) for elderly patients when compared with the spirometry reference equations that are most commonly used in the United States.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Female; Forced Expiratory Volume; Humans; Male; Reference Values; Smoking; Spirometry; Vital Capacity

High density lipoprotein cholesterol subfractions in older people. - Ettinger, W H; Verdery, R B; Wahl, P W; Fried, L P (J Gerontol, 1994)
BACKGROUND: High density lipoprotein (HDL) may be an important risk factor for cardiovascular disease in older people. HDL is heterogeneous with several subfractions. This article describes the distribution and correlates of HDL2 cholesterol (C) and HDL3-C in older people. METHODS: HDL subfraction cholesterols were measured in 1,127 females and 825 males > or = 65 years old who participated in the Cardiovascular Health Study. Distributions of HDL subfraction cholesterols and bivariate and multivariate relationships were determined in cross-sectional analyses. RESULTS: Mean (+/- SD) concentrations of HDL subfractions were: HDL3-C (M .98 +/- .25, F 1.2 +/- .29 mmol/l), HDL2-C (M .09 +/- .08, F .13 +/- .09 mmol/l). HDL2-C, but not HDL3-C, was slightly higher with age. Using multivariate analysis, both HDL2-C and HDL3-C (in females) were inversely correlated with triglyceride, body weight, and fasting insulin; HDL3-C was inversely correlated with central fat distribution in women. Both HDL2-C and HDL3-C were lower in participants with prevalent cardiovascular disease. However, only HDL3-C was significantly inversely related to carotid stenosis, as measured by ultrasound. CONCLUSIONS: The slight increase in HDL-C with age appears to be due to an increase in the HDL2-C subfraction. HDL-C subfractions are independently related to triglyceride levels, body weight, and insulin concentrations in older people, all potentially modifiable risk factors. Both HDL2-C and HDL3-C are lower in older people with prevalent cardiovascular disease, although only HDL3-C was correlated with carotid atherosclerosis. These findings are consistent with the hypothesis that HDL subfractions are important risk factors for atherosclerotic cardiovascular disease in the elderly.
Keywords: Aged; Aged, 80 and over; Alcohol Drinking; Body Weight; Carotid Stenosis; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; Cross-Sectional Studies; Drug Therapy; Female; Humans; Insulin; Lipoproteins, HDL; Lipoproteins, HDL2; Lipoproteins, HDL3; Male; Sex Factors; Socioeconomic Factors

A method for using MR to evaluate the effects of cardiovascular disease on the brain: the cardiovascular health study. - Bryan, R N; Manolio, T A; Schertz, L D; Jungreis, C; Poirier, V C; Elster, A D; Kronmal, R A (AJNR Am J Neuroradiol, 1994)
PURPOSE: To do a pilot study for the Cardiovascular Health Study (a population-based, longitudinal study of coronary heart disease and stroke in adults 65 years of age and older designed to identify risk factors related to cerebrovascular disease, particularly stroke): (a) to determine the feasibility of adding brain MR to the full-scale study; (b) to evaluate the reliability of standardized MR image interpretation in a multicenter study; and (c) to compare the prevalence of stroke determined by MR with that by clinical history. METHODS: Protocol-defined MR studies were performed in 100 subjects with clinical histories of stroke and 203 subjects without reported histories of stroke. MR scans were independently evaluated by two trained neuroradiologists for the presence of small (< or = 3 mm) and large (> 3 mm) "infarctlike" lesions. The sizes of the cerebral sulci and lateral ventricles and the extent of white matter disease were graded on a scale of 0 to 9. RESULTS: Eighty percent of the Cardiovascular Health Study participants who were invited to undergo MR studies agreed to do so; 95% of those agreeing to the procedure successfully completed the exams. Intrareader and interreader reliability of infarctlike lesion identification was high for large lesions (kappa, 0.71 and 0.78, respectively) but not for small lesions (kappa, 0.71 and 0.32, respectively). Relaxed intrareader and interreader kappa scores for sulcal and ventricular sizes and extent of white matter disease were greater than 0.8 MR evidence of infarctlike lesions was present in 77% of the participants with histories of stroke but was also present in 23% of the participants without clinical histories of stroke. Seventy-nine percent of the infarctlike lesions were larger than 3 mm. CONCLUSIONS: This preliminary study indicates that a large, prospective, epidemiologic study of elderly subjects using MR scans of the brain for identification of cerebrovascular disease is feasible and that the interpretative results are reproducible, and suggests that MR evidence of stroke is more prevalent than reported clinical history of stroke.
Keywords: Aged; Brain; Cerebral Infarction; Cerebral Ventricles; Cerebrovascular Disorders; Cohort Studies; Coronary Disease; Cross-Sectional Studies; Diagnosis, Differential; Feasibility Studies; Female; Humans; Image Interpretation, Computer-Assisted; Incidence; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mass Screening; Observer Variation; Pilot Projects; Prospective Studies; Risk Factors; United States

Physical disability in older adults: a physiological approach. Cardiovascular Health Study Research Group. - Fried, L P; Ettinger, W H; Lind, B; Newman, A B; Gardin, J (J Clin Epidemiol, 1994)
Measures of physical function have been developed primarily to assess health status, prognosis, and service needs. They are now, increasingly, being used as outcome measures in studies seeking to determine the causes of disability. However, the extent to which these standardized measures, as they currently are constituted, are meaningful for the evaluation of underlying pathophysiology is not defined. To assess evidence for an etiologic rationale for these measures, we evaluated self-report of difficulty in physical function in the Cardiovascular Health Study, a study of 5201 men and women 65 years and older in four U.S. communities. We determined (by factor analysis) that self-reported difficulty with each of 17 tasks of daily life aggregates in four groups; i.e. difficulty in one task is associated with having difficulty in the other tasks in the group. These groups include (1) activities primarily dependent on mobility and exercise tolerance; (2) complex activities heavily dependent on cognition and sensory input; (3) selected basic self-care activities; and (4) upper extremity activities. Groups 2 and 3 are similar, but not identical, to Instrumental Activities of Daily Living (IADL) and Activities of Daily Living (ADL), respectively. We then tested whether these groupings were associated with different underlying impairments. Multiple logistic regression analyses indicate that there are constellations of physiologic and disease characteristics significantly (p < 0.01) associated with difficulty in each of these four groups of activities, among 15 chronic diseases and conditions ascertained. Some diseases are uniquely associated with difficulty in one group of tasks; some overlap, and are associated with 2, 3 or 4 groups of tasks. The associations found with difficulty in performing tasks in groups 2 and 3 were frequently stronger than those with the larger groups of ADL or IADL tasks, suggesting increased specificity of associations found with these new groupings. These results suggest that re-grouping of tasks of daily life may provide a more refined physiologically-based outcome measure for use in evaluating causes of disability. The ability to define risk factors for disability may be enhanced by choosing outcome measures with a demonstrated physiologic rationale.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic Disease; Disabled Persons; Factor Analysis, Statistical; Female; Geriatric Assessment; Humans; Logistic Models; Male; Outcome Assessment (Health Care); Risk Factors; Sex Factors; Socioeconomic Factors; United States

Prevalence and correlates of respiratory symptoms and disease in the elderly. Cardiovascular Health Study. - Enright, P L; Kronmal, R A; Higgins, M W; Schenker, M B; Haponik, E F (Chest, 1994)
Spirometry was performed by 5,201 elderly participants of the Cardiovascular Health Study during their baseline examination and a subset of the ATS/DLD-78 respiratory questionnaire was administered by trained interviewers. In never smokers (46 percent of the cohort), the overall prevalence of chronic cough was 9 percent, chronic phlegm was 13 percent, attacks of wheezing with dyspnea were 8 percent, and grade 3 dyspnea on exertion was 10 percent. The prevalence of lung disease in current smokers (12 percent of the cohort) was 8/7 percent (men/women) with chronic bronchitis and 14/5 percent with emphysema. Overall, 6 percent reported asthma (a physician-confirmed history) and 12 percent reported hay fever. Using a logistic regression model, attacks of wheezing with dyspnea were strongly associated with a lower FEV1, coronary heart disease, heart failure, and a large waist size (in participants without a diagnosis of asthma, chronic bronchitis, or emphysema). Undiagnosed airways obstruction was twice as likely in women and those with lower income, and was associated with current and former smoking, pack-years of smoking, and chronic cough. Dyspnea on exertion (DOE) was three times or more likely if a participant reported heart failure, coronary heart disease, or emphysema; and much more likely if their FEV1 or FVC was substantially reduced. Dyspnea on exertion was also positively associated with older age, chronic bronchitis or asthma, a larger waist or hip size, pack-years of smoking, and less education. We conclude that DOE and attacks of wheezing with dyspnea are commonly associated with cardiovascular disease and a low FEV1 in those over 65 years and that airways obstruction frequently remains undiagnosed in the elderly.
Keywords: Aged; Aged, 80 and over; California; Cohort Studies; Female; Humans; Lung Diseases; Male; Maryland; Multivariate Analysis; North Carolina; Pennsylvania; Prevalence; Prognosis; Respiratory Tract Diseases; Spirometry; Surveys and Questionnaires

Respiratory muscle strength in the elderly. Correlates and reference values. Cardiovascular Health Study Research Group. - Enright, P L; Kronmal, R A; Manolio, T A; Schenker, M B; Hyatt, R E (Am J Respir Crit Care Med, 1994)
Maximal inspiratory pressure (MIP) was assessed in 4,443 ambulatory participants of the Cardiovascular Health Study, 65 yr of age and older, sampled from four communities. Maximal expiratory pressure (MEP) was also measured in 790 participants from a single clinic. Positive predictors of MIP included male sex, FVC, handgrip strength, and higher levels of lean body mass (or low bioelectric resistance). Negative predictors were age, current smoking, self-reported fair to poor general health, and waist size. Both participant and technician learning effects were noted, but there was no independent effect of race, hypertension, cardiovascular disease, or diabetes. A healthy subgroup was identified by excluding current smokers, those with fair to poor general health, or an FEV1 less than 65% of predicted. Mean values determined from the healthy group were 57/116 cm H2O (MIP/MEP) for women, and 83/174 for men. Lower limits of the normal range (fifth percentiles) were 45 to 60% of the mean predicted values. The reference equations derived from this group of healthy 65 to 85-yr-olds may be used by pulmonary function laboratories and respiratory therapists who evaluate the respiratory muscle strength of elderly patients.
Keywords: Aged; Aged, 80 and over; Aging; Body Constitution; Cardiovascular Diseases; Female; Humans; Male; Prospective Studies; Reference Values; Respiratory Function Tests; Respiratory Muscles; Risk Factors; Sex Characteristics; Smoking

Self-reported causes of physical disability in older people: the Cardiovascular Health Study. CHS Collaborative Research Group. - Ettinger, W H; Fried, L P; Harris, T; Shemanski, L; Schulz, R; Robbins, J (J Am Geriatr Soc, 1994)
OBJECTIVE: To determine the major conditions and symptoms reported to cause difficulty in 17 physical tasks of daily life and the criterion validity of self-report of diseases given as the causes of the difficulty in functioning, in community-dwelling older people. DESIGN: Cross sectional analyses of data obtained in an observational cohort study. SETTING: Research clinics in four US communities: Winston-Salem, NC, Hagerstown, MD, Pittsburgh, PA, and Sacramento, CA. PARTICIPANTS: 5201 community-dwelling people > or = 65 years old. RESULTS: Arthritis and other musculoskeletal diseases were given as the primary causes of difficulty in performing physical tasks by 49.0% of the participants reporting difficulty in any task, followed by heart disease (13.7%), injury (12.0%), old age (11.7%), lung disease (6.0%), and stroke (2.9%). The self-reports of diseases that caused disability varied by task. Whereas arthritis was given as a cause of difficulty in most of the 17 different tasks, heart and lung disease were more likely to be reported as causing difficulty with activities requiring high aerobic work capacity such as walking one-half mile or doing heavy housework. Stroke was more likely to be reported as causing difficulty with use of the upper extremities and in performing basic activities of daily living. There was a high degree of consistency (91%) between the diseases and symptoms reported to cause disabilities. The percentage of people who reported a disease as the cause of their difficulty performing a task and had independent confirmation of the diagnosis was 85% in men and 71% in women, and varied according to type of disease and the individual's cognitive status and health status. CONCLUSION: These data suggest that age-related chronic diseases are important causes of disability in older people but that the type of disability is dependent on the underlying disease that causes the disability. Also, self-report of the cause of disability appears to be generally accurate but is influenced by gender, health status, and type of disease.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Arthritis; Cardiovascular Diseases; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Disabled Persons; Female; Health Status; Health Surveys; Heart Diseases; Humans; Lung Diseases; Male; Observer Variation; Reproducibility of Results; Risk Factors; Sex Factors; United States

Smoking, Lung Function, and Atherosclerosis in the 5,000 Elderly Participants of the Cardiovascular Health Study. - Enright, Paul L. (Am J Geriatr Cardiol, 1994)
The Cardiovascular Health Study (CHS) is an observational study of heart disease and stroke designed to evaluate risk factors and noninvasive measures and to describe and predict atherosclerotic events in older adults. Five thousand two hundred one individuals ages 65 or older were recruited from a stratified random sample of Medicare recipients from 4 US communities. This review of cross-sectional data from the CHS baseline examination describes the cigarette smoking habits of elderly persons and the relationships of smoking to lung function (spirometry) and atherosclerosis, as noninvasively measured by the ankle-arm index (AAI) and carotid ultrasonography. Only 10% of the men and 13% of the women were current smokers, and about half were former smokers. Forced expiratory flow (FEV1) was about 20% lower in current smokers when compared with never smokers. Current and former smoking were strongly associated with an increased risk for an abnormal AAI. Common and internal carotid artery walls were thicker and stenosis more common in current smokers and former smokers, when compared with never smokers. Analysis of long-term follow-up morbidity and mortality data from the CHS cohort should provide even stronger evidence of the effects of smoking in the elderly. Vigorous efforts should be made to persuade elderly smokers to quit.

Evidence for inflammation as a cause of hypocholesterolemia in older people. - Ettinger, W H; Harris, T; Verdery, R B; Tracy, R; Kouba, E (J Am Geriatr Soc, 1995)
Keywords: Age Factors; Aged; Analysis of Variance; C-Reactive Protein; Case-Control Studies; Cholesterol; Female; Fibrinogen; Humans; Hypolipoproteinemias; Inflammation; Interleukin-1; Interleukin-6; Male

Hematological and biochemical laboratory values in older Cardiovascular Health Study participants. - Robbins, J; Wahl, P; Savage, P; Enright, P; Powe, N; Lyles, M (J Am Geriatr Soc, 1995)
OBJECTIVE: To define reference hematologic and biochemical lab values in older individuals. DESIGN: Randomly selected, age- and gender-stratified participants. SETTING: Visits by participants to four research clinics. PATIENTS: A total of 5201 participants in the Cardiovascular Health Study, an observational study of older Medicare-eligible individuals living at home. MEASUREMENT: Information about health status, previous illness, and medication use was obtained from participants and/or their MDs. This information was used to define a healthy subset of the population. Blood samples were obtained for Cholesterol, HDL and LDL cholesterol, fasting and 2-hour postload glucose and insulin, fibrinogen, factors VII and VIII, potassium, creatinine, albumin, uric acid, white blood count, hematocrit, hemoglobin, and platelet count. RESULTS: Significant differences were found for age group and/or gender for all mean values. Many tests were significantly different from the generally accepted reference ranges used in clinical laboratories. CONCLUSIONS: In some situations accepted laboratory norms for the general population can not be extrapolated to older adults. There are implications for both research and clinical practice.
Keywords: Age Factors; Aged; Analysis of Variance; California; Cardiovascular Diseases; Cohort Studies; Female; Health Status; Humans; Male; Maryland; Middle Aged; North Carolina; Pennsylvania; Reference Values; Risk Factors; Sex Characteristics

High density lipoprotein cholesterol is associated with serum cortisol in older people. - Varma, V K; Rushing, J T; Ettinger, W H (J Am Geriatr Soc, 1995)
OBJECTIVE: To determine the associations between serum cortisol and HDL cholesterol, other lipoprotein lipids and cardiovascular risk factors, carotid atherosclerosis, and clinical heart disease in older people. DESIGN: A cross-sectional, observational, ancillary study of the Cardiovascular Health Study (CHS). POPULATION: A total of 245 community-dwelling people, 65 to 89 years old, were recruited consecutively for a 2-month period from the CHS cohort in Forsyth County, North Carolina. METHODS: Cortisol was measured by radioimmunoassay in serum collected between 7:00 and 10:00 AM after an overnight fast. Cortisol levels were correlated with lipoprotein lipids, insulin, glucose, body mass index, waist-hip ratio, prevalent coronary heart disease, hypertension, diabetes, and carotid atherosclerosis by B-mode ultrasound. RESULTS: Serum cortisol was correlated negatively (r = -.24) with body mass index and waist-hip ratio (r = -.16) but was not related significantly to fasting insulin or glucose. Cortisol was not associated significantly with triglyceride and low density lipoprotein cholesterol but showed a positive correlation (r = .21) with high density lipoprotein cholesterol. The relationship between cortisol and high density lipoprotein cholesterol persisted after adjustment for gender, body mass index, waist-hip ratio, cigarette and alcohol use, triglyceride level, and diabetes. There was a trend toward a negative correlation between cortisol and measures of carotid atherosclerosis, but no significant relationship was indicated between cortisol and prevalent coronary heart disease, hypertension, or diabetes. CONCLUSION: Endogenous glucocorticoid levels correlated with HDL cholesterol levels and may play a role in the physiologic regulation of high density lipoprotein levels in older people.
Keywords: Aged; Body Constitution; Body Mass Index; Cardiovascular Diseases; Carotid Stenosis; Cholesterol, HDL; Coronary Disease; Cross-Sectional Studies; Diabetes Mellitus; Female; Humans; Hydrocortisone; Hypertension; Male; Prevalence; Risk Factors

Reduced vital capacity in elderly persons with hypertension, coronary heart disease, or left ventricular hypertrophy. The Cardiovascular Health Study. - Enright, P L; Kronmal, R A; Smith, V E; Gardin, J M; Schenker, M B; Manolio, T A (Chest, 1995)
The Cardiovascular Health Study provided the opportunity to determine the association of subclinical and clinical cardiovascular disease with pulmonary function in a population sample of elderly adults. Included were 2,955 women and 2,246 men over age 64 years who were recruited for this observational study from four communities and completed extensive examinations that included spirometry, echocardiograms, and blood pressure. Current smokers, past smokers with >20 pack-years of smoking, and persons with a history of asthma, chronic bronchitis, or emphysema were excluded from this analysis, leaving 2,784 (55%) of the cohort. Systolic hypertension or coronary artery disease was associated with 40- to 100-mL decrements in FEV1, and 50- to 150-mL decrements in FVC, while a history of congestive heart failure was associated with 200 to 300 mL lower FEV1 and FVC values (p < 0.0001), after correcting for age, height, and waist size. Higher left ventricular (LV) mass was also significantly associated with a decrease in FEV1 and FVC in multivariate models. This relationship was strongest with the end-diastolic LV posterior wall thickness component of LV mass. In summary, FEV1 and FVC are reduced in elderly persons with hypertension, ischemic heart disease, higher disease, higher LV mass, and congestive heart failure, though the magnitude of these associations is relatively small unless heart failure supervenes. Substantial decrements in percent predicted FEV1 and FVC should not be attributed to the presence of uncomplicated ischemic heart disease or hypertension alone.
Keywords: Age Factors; Aged; Aged, 80 and over; Coronary Disease; Female; Forced Expiratory Volume; Humans; Hypertension; Hypertrophy, Left Ventricular; Male; Middle Aged; Ventricular Function, Left; Vital Capacity

Asthma and its association with cardiovascular disease in the elderly. The Cardiovascular Health Study Research Group. - Enright, P L; Ward, B J; Tracy, R P; Lasser, E C (J Asthma, 1996)
Cardiovascular disease (CVD) is more prevalent in elderly than in middle-aged patients. Symptoms such as intermittent wheezing with dyspnea may then be due to either CVD or asthma. The objective of this study was to determine the prevalence and correlates of asthma in the elderly and their associations with CVD and CVD risk factors. A community sample of 5201 elderly persons from the Cardiovascular Health Study was asked if they had a physician diagnosis of asthma, and multiple cardiovascular risk and disease variables were measured. Six percent of the participants (309) recalled a history of asthma, and half of these were never smokers. Thirty percent of those with asthma were currently taking a bronchodilator, 14% inhaled steroids, and 10% oral prednisone. Men and women with asthma who were cigarette smokers were more likely to report a concurrent diagnosis of congestive heart failure than smokers without asthma (p = .04). However, when we determined the independent CVD correlates of asthma in this cohort, controlling for smoking status, age, gender, and diagnoses of chronic bronchitis and emphysema, only higher levels of high-density lipoprotein cholesterol (HDL-C) and higher plasma fibrinogen levels were significantly associated with asthma. It was concluded that asthma is as prevalent in the elderly as in middle-aged persons and is associated with higher HDL-C and higher fibrinogen levels, but not with prevalent cardiovascular disease.
Keywords: Aged; Aged, 80 and over; Asthma; Cardiovascular Diseases; Cohort Studies; Female; Humans; Lung; Male; Multivariate Analysis; Prevalence; Risk Factors; Sex Distribution; Smoking

Clinical correlates of white matter findings on cranial magnetic resonance imaging of 3301 elderly people. The Cardiovascular Health Study. - Longstreth, W T; Manolio, T A; Arnold, A; Burke, G L; Bryan, N; Jungreis, C A; Enright, P L; O'Leary, D; Fried, L (Stroke, 1996)
BACKGROUND AND PURPOSE: Our aim was to identify potential risk factors for and clinical manifestations of white matter findings on cranial MRI in elderly people. METHODS: Medicare eligibility lists were used to obtain a representative sample of 5888 community-dwelling people aged 65 years or older. Correlates of white matter findings were sought among 3301 participants who underwent MRI scanning and denied a history of stroke or transient ischemic attack. Participants underwent extensive standardized evaluations at baseline and on follow-up, including standard questionnaires, physical examination, multiple blood tests, electrocardiogram, pulmonary function tests, carotid sonography, and M-mode echocardiography. Neuroradiologists graded white matter findings from 0 (none) to 9 (maximal) without clinical information. RESULTS: Many potential risk factors were related to the white matter grade, but in the multivariate model the factors significantly (all P < .01) and independently associated with increased grade were greater age, clinically silent stroke on MRI, higher systolic blood pressure, lower forced expiratory volume in 1 second (FEV1), and income less than $50,000 per year. If excluded, FEV1 was replaced in the model by female sex, history of smoking, and history of physician-diagnosed hypertension at the baseline examination. Many clinical features were correlated with the white matter grade, especially those indicating impaired cognitive and lower extremity function. CONCLUSIONS: White matter findings were significantly associated with age, silent stroke, hypertension, FEV1, and income. The white matter findings may not be considered benign because they are associated with impaired cognitive and lower extremity function.
Keywords: Age Factors; Aged; Aging; Blood Pressure; Brain; Cardiovascular Diseases; Cerebrovascular Disorders; Cohort Studies; Female; Humans; Ischemic Attack, Transient; Magnetic Resonance Imaging; Male; Multivariate Analysis; Risk Factors; Sex Factors

Lipoprotein levels in elderly patients with asthma. Cardiovascular Health Study Research Group. - Enright, P L; Lasser, E C; Ward, B J; Tracy, R P (J Allergy Clin Immunol, 1996)
Keywords: Aged; Aging; Arteriosclerosis; Asthma; Female; Humans; Lipoproteins; Male; Prospective Studies; Risk Factors; Sex Factors

Prevalence and correlates of snoring and observed apneas in 5,201 older adults. - Enright, P L; Newman, A B; Wahl, P W; Manolio, T A; Haponik, E F; Boyle, P J (Sleep, 1996)
The objectives of this study were to describe the prevalence of snoring, observed apneas, and daytime sleepiness in older men and women, and to describe the relationships of these sleep disturbances to health status and cardiovascular diseases (CVD). A cross-sectional design was employed to study sleep problems, CVD, general health, psychosocial factors, and medication use. The subjects were participants in the Cardiovascular Health Study, which included 5,201 adults, aged 65 and older, who were recruited from a random sample of Medicare enrollees in four U.S. communities. Study measures employed were sleep questions, echocardiography, carotid ultrasound, resting electrocardiogram, cognitive function, cardiopulmonary symptoms and diseases, depression, independent activities of daily living (IADLs), and benzodiazepine use. Thirty-three percent of the men and 19% of the women reported loud snoring, which was less frequent in those over age 75. Snoring was positively associated with younger age, marital status, and alcohol use in men, and obesity, diabetes, and arthritis in women. Snoring was not associated, however, with cardiovascular risk factors or clinical CVD in men or women. Observed apneas were reported much less frequently (13% of men and 4% women) than snoring, and they were associated with alcohol use, chronic bronchitis, and marital status in men. Observed apneas were associated with depression and diabetes in women. In both men and women, daytime sleepiness was associated with poor health, advanced age, and IADL limitations. The conclusions of the study were that loud snoring, observed apneas, and daytime sleepiness are not associated cross-sectionally with hypertension or prevalent CVD in elderly persons.
Keywords: Activities of Daily Living; Age Factors; Aged; Cardiovascular Diseases; Comorbidity; Female; Humans; Incidence; Lung Diseases; Male; Narcolepsy; Prevalence; Random Allocation; Sex Factors; Sleep Apnea Syndromes; Snoring

Spirometry reference values for healthy elderly blacks. The Cardiovascular Health Study Research Group. - Enright, P L; Arnold, A; Manolio, T A; Kuller, L H (Chest, 1996)
Pulmonary function was assessed by spirometry in 497 black and 2,980 white ambulatory elderly male and female participants of the Cardiovascular Health Study. The quality assurance program prompted technicians to exceed American Thoracic Society recommendations for spirometry. A "healthy" subgroup of 235 black and 1,227 white participants age 65 years and older was identified by excluding current and former smoker, and those with self-reported asthma or emphysema, congestive heart failure, and poor-quality results of spirometry tests, since those factors were associated with a lower FEV1. Reference equations and normal ranges for elderly blacks for measurements of FEV1, FVC, and the FEV1/FVC ratio were then determined from the healthy group. These elderly blacks had an FVC about 6% lower than elderly whites, even after correcting for standing height, sitting height (trunk length), and age. The popular use of spirometry reference values from studies of middle-aged white subjects by applying a 12% race correction factor for black patients appears to overestimate predicted values.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; European Continental Ancestry Group; Female; Forced Expiratory Volume; Humans; Male; Reference Values; Spirometry; United States; Vital Capacity

Clinically serious abnormalities found incidentally at MR imaging of the brain: data from the Cardiovascular Health Study. - Yue, N C; Longstreth, W T; Elster, A D; Jungreis, C A; O'Leary, D H; Poirier, V C (Radiology, 1997)
PURPOSE: To determine the prevalence of clinically serious findings unrelated to stroke on cranial magnetic resonance (MR) images in a population of community-dwelling elderly people. MATERIALS AND METHODS: Neuroradiologists reviewed MR images of 3,672 people aged 65 years and older who were enrolled in a longitudinal, population-based study of cardiovascular and cerebrovascular disease. The neuroradiologists alerted MR imaging field centers about potentially serious abnormalities. Clinical information was obtained from clinical examinations performed before MR imaging, hospital discharge summaries, and the field centers at which MR imaging was performed. RESULTS: On 3,672 image sets, 64 (1.74%) clinically serious abnormalities were found. Among the presumptive diagnoses were 19 meningiomas (0.52%), six pituitary adenomas (0.16%), five cavernous malformations (0.14%), eight vascular stenoses (0.22%), four aneurysms (0.11%), two intraventricular masses (0.05%), two subdural fluid collections (0.05%), and two other tumors (0.05%). Only nine participants with these abnormalities required surgery. All but one of the meningiomas were in women, and the prevalence of the tumor decreased with increasing age. CONCLUSION: Physicians should be alert to the possible presence of clinically serious conditions in otherwise asymptomatic elderly individuals.
Keywords: Aged; Aged, 80 and over; Brain; Brain Diseases; Cardiovascular Diseases; Cohort Studies; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male

Correlates of performance-based measures of muscle function in the elderly: the Cardiovascular Health Study. - Hirsch, C H; Fried, L P; Harris, T; Fitzpatrick, A; Enright, P; Schulz, R (J Gerontol A Biol Sci Med Sci, 1997)
BACKGROUND: It is unknown how much age-related changes in muscle performance represent normal aging versus the effects of chronic disease and life style. We examined the correlates of four performance measures-gait speed, timed chair stands (TCS), grip strength, and maximal inspiratory pressure (MIP)-using baseline data from the Cardiovascular Health Study (CHS), a population-based study of risk factors for heart disease and stroke in persons > or = age 65. METHODS: We analyzed data from the 5,201 CHS participants. Variables were arranged into nine categories: Personal Characteristics, Anthropometry, Physical Condition, Reported Functional Status, Subjective Health, Psychological Factors, Symptoms, Cognitive Status, Habits and Lifestyle, and Prevalent Disease. Independent correlates were identified using stepwise linear regression. RESULTS: The regression models explained 17.7-25.4% of the observed variability. Although age significantly correlated with each measure, it explained little of the variability (< or = 5.7%). Anthropometric features plus physical condition explained 14.0-17.4% of the variability for grip strength and MIP, but 2.8-12.9% of the variability for gait speed and the log of TCS. Subjective health and psychological factors explained 1.8-9.4% of the variability in gait speed and the log of TCS, but < or = 1.2% of the variability in grip strength and MIP. Variables for prevalent disease explained < or = 1.3% of the variability in each measure. CONCLUSIONS: After age 64, age explained little of the variability in muscle performance in a large sample of mostly functionally intact, community-dwelling older persons. Complex measures such as gait speed were more associated with subjective factors than were direct measures of strength. Prevalent disease contributed surprisingly little to muscle performance.
Keywords: Aging; Anthropometry; Cardiovascular Physiological Phenomena; Female; Gait; Hand Strength; Health Status; Humans; Male; Middle Aged; Motor Activity; Muscles; Pressure; Regression Analysis; Respiration

Health status of individuals with mild stroke. - Duncan, P W; Samsa, G P; Weinberger, M; Goldstein, L B; Bonito, A; Witter, D M; Enarson, C; Matchar, D (Stroke, 1997)
BACKGROUND AND PURPOSE: Diminished quality of life and limitations in higher levels of physical functioning are often underestimated in stroke and are not fully captured by measures such as the Barthel Index and the Rankin Outcome Scale. This study used additional measures to assess the health status of 304 persons with mild stroke and to compare these individuals with 184 persons with transient ischemic attack and 654 persons without history of stroke/transient ischemic attack but at elevated risk for stroke (asymptomatic group). METHODS: Subjects were recruited from the Academic Medical Center Consortium (inpatients), the Cardiovascular Health Study (population-based sample of community-dwelling persons 65 years and older), and United HealthCare (inpatients and outpatients typically younger than 65 years). Subjects were interviewed by telephone or in person to assess activities of daily living (Barthel Index), depression (Center for Epidemiological Studies Depression Scale), health status (MOS-36), and utility for current health state. RESULTS: Most respondents were independent on all Barthel items. The stroke group was more impaired on the MOS-36 than the asymptomatic group but similar to the group with transient ischemic attack. Health-related quality of life was lowest for persons with stroke. While symptom status and Barthel Index score were the strongest predictors of health status, the Barthel Index showed a consistent ceiling effect when compared with the physical function subscale of the MOS-36. CONCLUSIONS: The consequences of even mild stroke affect all dimensions of health except pain. Standardized assessment of persons with stroke must evaluate across the entire continuum of health-related functions.
Keywords: Age Distribution; Aged; Cerebrovascular Disorders; European Continental Ancestry Group; Female; Health Status; Humans; Ischemic Attack, Transient; Male; Middle Aged; Social Support

Infarctlike lesions in the brain: prevalence and anatomic characteristics at MR imaging of the elderly--data from the Cardiovascular Health Study. - Bryan, R N; Wells, S W; Miller, T J; Elster, A D; Jungreis, C A; Poirier, V C; Lind, B K; Manolio, T A (Radiology, 1997)
PURPOSE: To determine the prevalence and anatomic characteristics of infarctlike lesions seen on cranial magnetic resonance (MR) images. MATERIALS AND METHODS: The study cohort consisted of 5,888 community-living individuals aged 65 years and older enrolled in a longitudinal, population-based study of cardiovascular disease. MR images were obtained from 3,658 participants and evaluated by trained readers. Lesion size, anatomic location, and signal intensity were recorded. Infarctlike lesion was defined as a nonmass, hyperintense region on spin-density- and T2-weighted images and, in cerebral white matter and brain stem, a hypointense region on T1-weighted images. RESULTS: Infarctlike lesions were depicted on MR images of 1,323 (36%) participants. Eighty-five percent (1,128 participants) had lesions 3 mm or larger in maximum dimension, although 70.9% (1,320 of 1,861) of these lesions were 10 mm or less. Lesion prevalence increased with age, especially with lesions 3 mm or larger, which increased from 22.1% (86 of 389) in the 65-69-year age group to 42.9% (88 of 205) in the over-85-year age group (P < .0001). Lesion prevalence was slightly greater in men (497 of 1,527 [32.5%]) than in women (631 of 2,131 [29.6%]), but did not differ between blacks and non-blacks. The deep nuclei were the most commonly affected anatomic sites, with 78.2% (1,451 of 1,856) of lesions. Lesions that involved the cerebrum and posterior fossa accounted for 11.7% (218 of 1,856) and 10.1% (187 of 1,856) of lesions, respectively. CONCLUSION: If the lesions reported in this study indicate cerebrovascular disease, subclinical disease may be more prevalent than clinical disease, and the prevalence of disease may rise with age. Also, infarctlike lesions have a distinctive anatomic profile.
Keywords: Aged; Brain; Cardiovascular Diseases; Cerebral Infarction; Cohort Studies; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Prevalence

Knowledge of risk among patients at increased risk for stroke. - Samsa, G P; Cohen, S J; Goldstein, L B; Bonito, A J; Duncan, P W; Enarson, C; DeFriese, G H; Horner, R D; Matchar, D B (Stroke, 1997)
BACKGROUND AND PURPOSE: Patients who recognize their increased risk for stroke are more likely to engage in (and comply with) stroke prevention practices than those who do not. We describe perceived risk of stroke among a nationally diverse sample of patients at increased risk for stroke and determine whether patients' knowledge of their stroke risk varied according to patients' demographic and clinical characteristics. METHODS: Respondents were recruited from the Academic Medical Center Consortium (n = 621, five academic medical centers, inpatients of varying age); the Cardiovascular Health Study (n = 321, population-based sample of persons aged 65+ years); and United HealthCare (n = 319, five health plans, inpatients and outpatients typically younger than 65 years). The primary outcome was awareness of being at risk for stroke. RESULTS: Only 41% of respondents were aware of their increased risk for stroke (including less than one half of patients with previous minor stroke). Approximately 74% of patients who recalled being told of their increased stroke risk by a physician acknowledged this risk in comparison with 28% of patients who did not recall being informed by a physician. Younger patients, depressed patients, those in poor current health, and those with a history of TIA were most likely to be aware of their stroke risk. CONCLUSIONS: Over one half of patients at increased risk of stroke are unaware of their risk. Healthcare providers play a crucial role in communicating information about risk, and successful communication encourages adoption of stroke prevention practices. Educational messages should be targeted toward patients least likely to be aware of their risk.
Keywords: Adult; Aged; Aged, 80 and over; Awareness; Cerebrovascular Disorders; Female; Humans; Knowledge; Male; Middle Aged; Multivariate Analysis; Risk Factors

Relationship of C-reactive protein to risk of cardiovascular disease in the elderly. Results from the Cardiovascular Health Study and the Rural Health Promotion Project. - Tracy, R P; Lemaitre, R N; Psaty, B M; Ives, D G; Evans, R W; Cushman, M; Meilahn, E N; Kuller, L H (Arterioscler Thromb Vasc Biol, 1997)
Markers of inflammation, such as C-reactive protein (CRP), are related to risk of cardiovascular disease (CVD) events in those with angina, but little is known about individuals without prevalent clinical CVD. We performed a prospective, nested case-control study in the Cardiovascular Health Study (CHS; 5201 healthy elderly men and women). Case subjects (n = 146 men and women with incident CVD events including angina, myocardial infarction, and death) and control subjects (n = 146) were matched on the basis of sex and the presence or absence of significant subclinical CVD at baseline (average follow-up, 2.4 years). In women but not men, the mean CRP level was higher for case subjects than for control subjects (P < or = .05). In general, CRP was higher in those with subclinical disease. Most of the association of CRP with female case subjects versus control subjects was in the subgroup with subclinical disease; 3.33 versus 1.90 mg/L, P < .05, adjusted for age and time of follow-up. Case-control differences were greatest when the time between baseline and the CVD event was shortest. The strongest associations were with myocardial infarction, and there was an overall odds ratio for incident myocardial infarction for men and women with subclinical disease (upper quartile versus lower three quartiles) of 2.67 (confidence interval [CI] = 1.04 to 6.81), with the relationship being stronger in women (4.50 [CI = 0.97 to 20.8]) than in men (1.75 [CI = 0.51 to 5.98]). We performed a similar study in the Rural Health Promotion Project, in which mean values of CRP were higher for female case subjects than for female control subjects, but no differences were apparent for men. Comparing the upper quintile with the lower four, the odds ratio for CVD case subjects was 2.7 (CI = 1.10 to 6.60). In conclusion, CRP was associated with incident events in the elderly, especially in those with subclinical disease at baseline.
Keywords: Aged; Aging; C-Reactive Protein; Cardiovascular Diseases; Case-Control Studies; Female; Humans; Male; Prospective Studies; Sex Factors

Sleep disturbance, psychosocial correlates, and cardiovascular disease in 5201 older adults: the Cardiovascular Health Study. - Newman, A B; Enright, P L; Manolio, T A; Haponik, E F; Wahl, P W (J Am Geriatr Soc, 1997)
OBJECTIVES: To describe the prevalence of self reported sleep disturbances in older men and women and to describe their relationships with health status and cardiovascular disease (CVD). DESIGN: Cross-sectional study of sleep disturbance, CVD, general health, psychosocial factors, physical function, and use of psychotropic medications. SETTING: Participants of the Cardiovascular Health Study, 5201 adults aged 65 and older recruited from a random sample of noninstitutionalized Medicare enrollees in four US communities. MEASURES: Self-reported sleep disturbances and standardized questionnaires for cardiopulmonary symptoms and diseases, depression, social support, activities of daily living, physical activity, cognitive function, and current medications, spirometry, ECG, echocardiography, and carotid ultrasound. RESULTS: Women were twice as likely as men to report difficulty falling asleep (30% vs 14%). Daytime sleepiness, difficulty falling asleep, and frequent awakenings increased in prevalence with age. All symptoms were related strongly to depression. Symptoms of daytime sleepiness were also related strongly to poor health and limitations in activities of daily living in men and women. In multivariate analysis, men taking benzodiazepines were likely to report difficulty falling asleep and daytime sleepiness, whereas women taking benzodiazepines reported difficulty falling asleep and waking up too early. After accounting for these factors, the only cardiovascular disease independently associated with sleep disturbances was angina. Men and women with confirmed angina were 1.6 times more likely to report trouble falling asleep. Independent relationships between sleep disturbances and cardiovascular risk factors such as obesity, hypertension, smoking, and diabetes were relatively weak and inconsistent, though smokers were less likely to report frequent awakenings. CONCLUSIONS: Sleep disturbances are relatively common in older men and women and are associated with poor health, depression, angina, limitations in activities of daily living, and the use of benzodiazepines.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cross-Sectional Studies; Depression; Female; Geriatric Assessment; Health Surveys; Humans; Male; Prevalence; Psychotropic Drugs; Random Allocation; Risk Factors; Sex Factors; Sleep Wake Disorders; Social Support; Surveys and Questionnaires; United States

Sulcal, ventricular, and white matter changes at MR imaging in the aging brain: data from the cardiovascular health study. - Yue, N C; Arnold, A M; Longstreth, W T; Elster, A D; Jungreis, C A; O'Leary, D H; Poirier, V C; Bryan, R N (Radiology, 1997)
PURPOSE: To determine the distribution of changes in sulcal size, ventricular size, and white matter signal intensity depicted on cranial magnetic resonance (MR) images, with stratification according to age, race, and sex. MATERIALS AND METHODS: Ventricular size, sulcal size, and white matter signal intensity changes were graded on cranial MR images of 3,660 community-living, elderly participants in the Cardiovascular Health Study. A healthier subgroup was also defined. Summary statistics for both groups were generated for age, race, and sex. RESULTS: Regression models of the entire imaged cohort showed higher grades of all variables with increasing age, and higher ventricular and sulcal grades in men and in nonblack individuals. White matter grade was greater in women and in black individuals. Regression models of the healthier subgroup showed similar associations, except for a lack of association of sulcal and ventricular size with race. CONCLUSION: Sulcal width, ventricular size, and white matter signal intensity change with age, sex, and race. Knowledge of these changes is important in appropriate interpretation of MR images of the elderly.
Keywords: Aged; Aged, 80 and over; Aging; Brain; Cardiovascular Diseases; Cerebral Ventricles; Cohort Studies; Continental Population Groups; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Reproducibility of Results; Sex Factors

Correlates of daytime sleepiness in 4578 elderly persons: the Cardiovascular Health Study. - Whitney, C W; Enright, P L; Newman, A B; Bonekat, W; Foley, D; Quan, S F (Sleep, 1998)
OBJECTIVES: To describe the prevalence of self-reported daytime sleepiness in older men and women and to describe their relationships with demographic factors, nocturnal complaints, health status, and cardiovascular diseases (CVD). DESIGN: Cross-sectional survey and clinical exam. SETTING: Participants in the Cardiovascular Health Study, 4578 adults aged 65 and older, recruited from a random sample of non-institutionalized Medicare enrollees in four U.S. communities. MEASURES: Daytime sleepiness measured by the Epworth Sleepiness Scale (ESS), magnetic resonance imaging of the brain (MRI), cognitive function tests, and standardized questionnaires for cardiopulmonary symptoms and diseases, depressive symptoms, social support, activities of daily living, physical activity, and current medications. RESULTS: Approximately 20% of the participants reported that they were "usually sleepy in the daytime". Although elderly black men were less likely to report frequent awakenings than those in the other three race and gender groups, they had significantly higher mean ESS scores. The following were independently associated with higher ESS scores in gender-specific models: non-white race, depression, loud snoring, awakening with dyspnea or snorting, frequent nocturnal awakenings, medications used to treat congestive heart failure, non-use of sleeping pills, a sedentary lifestyle, and limitation of activities of daily living in both men and women; additional correlates included hip circumference and current smoking in men, and hayfever in women. The following were not independently associated with ESS in the models: age, education, use of wine or beer to aid sleep, use of tricyclic antidepressants, long- or short-acting benzodiazepines, asthma, angina, myocardial infarction, congestive heart failure itself, forced vital capacity, social support, cognitive function, or MRI evidence of global brain atrophy or white matter abnormality. CONCLUSIONS: Daytime sleepiness is common in the elderly, probably due to nocturnal disturbances such as frequent awakenings and snoring. The occasional use of sleeping pills for insomnia is associated with reduced daytime sleepiness in the elderly, while the use of medications for congestive heart failure is associated with daytime sleepiness. Surprisingly, anatomic abnormalities such as evidence of previous strokes and brain atrophy (as seen on brain MRI scans) were not associated with daytime sleepiness in these non-institutionalized elderly persons.
Keywords: Activities of Daily Living; Age Distribution; Aged; Aged, 80 and over; Brain; Cardiovascular Diseases; Circadian Rhythm; Cognition Disorders; Cohort Studies; Continental Population Groups; Cross-Sectional Studies; Disorders of Excessive Somnolence; Electrocardiography; Female; Health Status; Health Surveys; Humans; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Prevalence; Sex Distribution

Relationship between balance and abnormalities in cerebral magnetic resonance imaging in older adults. - Tell, G S; Lefkowitz, D S; Diehr, P; Elster, A D (Arch Neurol, 1998)
BACKGROUND: Falling is a major cause of disability and morbidity among older adults. Because poor balance is a major reason for frequent falls, assessment of balance and its risk factors are important. In this study, we postulated that cerebral changes identified on magnetic resonance (MR) imaging are related to balance, and that older adults with balance problems would have significantly greater prevalence of such brain abnormalities than older adults without balance problems. DESIGN AND MEASUREMENTS: Several measures of balance were examined in more than 700 community-dwelling older men and women, blacks and whites. Balance measures included dynamic posturography, functional reach, Romberg and 1-foot stand tests, tandem stand, and 1-foot stand. Cerebral MR imaging assessments included ventricular size, sulcal widening, white matter disease, and ischemic infarctions. Cardiovascular disease and hypertension were determined and controlled for in the analyses. RESULTS: A summary of the balance measures was significantly related to each of the 4 MR imaging measures, with those with poorer balance having more disease. The strongest associations with balance were seen for white matter disease and ventricular size. All but the ischemic infarction variable remained significantly associated with balance after adjustments for sex, race, age, cardiovascular disease, and hypertension. CONCLUSION: Cerebral changes identified by MR imaging are associated with poorer balance among older adults.
Keywords: Accidental Falls; Aged; Aging; Cerebral Cortex; Female; Humans; Magnetic Resonance Imaging; Male; Postural Balance; Risk Factors

Utilities for major stroke: results from a survey of preferences among persons at increased risk for stroke. - Samsa, G P; Matchar, D B; Goldstein, L; Bonito, A; Duncan, P W; Lipscomb, J; Enarson, C; Witter, D; Venus, P; Paul, J E; Weinberger, M (Am Heart J, 1998)
BACKGROUND: Patient beliefs, values, and preferences are crucial to decisions involving health care. In a large sample of persons at increased risk for stroke, we examined attitudes toward hypothetical major stroke. METHODS AND RESULTS: Respondents were obtained from the Academic Medical Center Consortium (n = 621), the Cardiovascular Health Study (n = 321 ), and United Health Care (n = 319). Preferences were primarily assessed by using the time trade off (TTO). Although major stroke is generally considered an undesirable event (mean TTO = 0.30), responses were varied: although 45% of respondents considered major stroke to be a worse outcome than death, 15% were willing to trade off little or no survival to avoid a major stroke. CONCLUSIONS: Providers should speak directly with patients about beliefs, values, and preferences. Stroke-related interventions, even those with a high price or less than dramatic clinical benefits, are likely to be cost-effective if they prevent an outcome (major stroke) that is so undesirable.
Keywords: Adult; Age Distribution; Aged; Aged, 80 and over; Attitude to Health; Female; Health Status; Humans; Intracranial Embolism and Thrombosis; Male; Middle Aged; Quality of Life; Sex Distribution; Surveys and Questionnaires; United States

The relationship of fibrinogen and factors VII and VIII to incident cardiovascular disease and death in the elderly: results from the cardiovascular health study. - Tracy, R P; Arnold, A M; Ettinger, W; Fried, L; Meilahn, E; Savage, P (Arterioscler Thromb Vasc Biol, 1999)
Little is known about the prospective associations of fibrinogen, factor VII, or factor VIII with cardiovascular disease (CVD) and mortality in the elderly. At baseline in the Cardiovascular Health Study (5888 white and African American men and women; aged >/=65 years), we measured fibrinogen, factor VIII, and factor VII. We used sex-stratified stepwise Cox survival analysis to determine relative risks (RRs) for CVD events and all-cause mortality (up to 5 years of follow-up), both unadjusted and adjusted for CVD risk factors and subclinical CVD. After adjustment, comparing the fifth quintile to the first, fibrinogen was significantly associated in men with coronary heart disease events (RR=2.1) and stroke or transient ischemic attack (RR=1.3), and also with mortality within 2.5 years of follow-up (RR=5.8) and later (RR=1.7). Factor VIII was significantly associated in men with coronary heart disease events (RR=1.5) and mortality (RR=1.8), and in women with stroke/transient ischemic attack (RR=1.4). For both factors, values were higher in those who died, whether causes were CVD-related or non-CVD-related, but highest in CVD death. Factor VII exhibited associations with incident angina (RR=1.44) in men and with death in women (RR, middle quintile compared with first=0.66). However, in general, factor VII was not consistently associated with CVD events in this population. We conclude that, if confirmed in other studies, the measurement of fibrinogen and/or factor VIII may help identify older individuals at higher risk for CVD events and mortality.
Keywords: Aged; Cardiovascular Diseases; Factor VII; Factor VIII; Female; Fibrinogen; Humans; Male; Multivariate Analysis; Risk Factors

Relationships of cerebral MRI findings to ultrasonographic carotid atherosclerosis in older adults : the Cardiovascular Health Study. CHS Collaborative Research Group. - Manolio, T A; Burke, G L; O'Leary, D H; Evans, G; Beauchamp, N; Knepper, L; Ward, B (Arterioscler Thromb Vasc Biol, 1999)
Cerebral magnetic resonance imaging (MRI) has demonstrated a high prevalence of infarct-like lesions, white matter hyperintensities, and evidence of cerebral atrophy in older adults. While these findings are generally believed to be related to ischemia and atherosclerosis, their relationship to atherosclerosis in the carotid arteries remains to be explored. Study subjects were part of the multicenter Cardiovascular Health Study, a cross-sectional study of 3502 women and men >/=65 years of age undergoing cranial MRI and carotid ultrasonography. MRI infarcts were detected in 1068 participants (29.3%) and measurable carotid plaque in 2745 (75.3%). MRI infarcts, ventricular and sulcal widening, and white matter score were strongly associated with carotid intimal-medial thickness (IMT) and stenosis degree after adjustment for age and sex (all P<0. 01). Associations with plaque characteristics were less strong and less consistent; MRI infarcts were weakly associated only with surface irregularity, and ventricular size was weakly associated only with lesion density (both P<0.04). In contrast, sulcal widening was strongly related to plaque characteristics, with scores being higher in those with heterogeneous and irregular plaque (both P<0. 009). Adjustment for other risk factors, and for carotid IMT/stenosis, removed associations of MRI findings with plaque characteristics except for weak relationships remaining between MRI infarcts and surface irregularity and between sulcal score and heterogeneous plaque (both P<0.03). MRI abnormalities show strong and consistent relationships with increasing carotid IMT and stenosis degree but less strong associations with plaque characteristics, especially after adjusting for IMT and stenosis.
Keywords: Aged; Arteriosclerosis; Brain; Cardiovascular System; Carotid Artery Diseases; Cerebral Infarction; Cohort Studies; Cross-Sectional Studies; Echoencephalography; Female; Health Status; Humans; Magnetic Resonance Imaging; Male; Prevalence

Underdiagnosis and undertreatment of asthma in the elderly. Cardiovascular Health Study Research Group. - Enright, P L; McClelland, R L; Newman, A B; Gottlieb, D J; Lebowitz, M D (Chest, 1999)
OBJECTIVE: To describe the clinical correlates of asthma in a community-based sample of elderly persons. PARTICIPANTS: A community sample of 4,581 persons > or = 65 years old from the Cardiovascular Health Study. MEASUREMENTS: Standardized respiratory, sleep, and quality-of-life (QOL) questions, a medication inventory, spirometry, and ambulatory peak flow. RESULTS: Four percent of the participants reported a current diagnosis of asthma (definite asthma), while another 4% reported at least one attack of wheezing accompanied by chest tightness or dyspnea during the previous 12 months (probable asthma). Smokers and those with congestive heart failure were excluded from the subsequent analyses, leaving 2,527 participants. Of those who had definite asthma, 40% were taking a sympathomimetic bronchodilator, 30% inhaled corticosteroids, 21% theophylline, and 18% oral corticosteroids; 39% were taking no asthma medications. The participants with definite or probable asthma were much more likely than the others to have a family history of asthma, childhood respiratory problems, a history of workplace exposures, dyspnea on exertion, hay fever, chronic bronchitis, nocturnal symptoms, and daytime sleepiness. They were also more likely to report poor general health, symptoms of depression, and limitation of activities of daily living. There was little difference in the morbidity and QOL of participants with recent asthma-like symptoms who had received the diagnosis of asthma versus those who had not. CONCLUSIONS: Asthma in elderly persons is associated with a lower QOL and considerable morbidity when compared with those who do not have asthma symptoms. Asthma is underdiagnosed in this group and is often associated with allergic triggers; inhaled corticosteroids are underutilized.
Keywords: Age Factors; Aged; Aged, 80 and over; Asthma; Female; Humans; Male; Peak Expiratory Flow Rate; Quality of Life; Risk Factors; Spirometry; Vital Capacity

Clinical correlates of ventricular and sulcal size on cranial magnetic resonance imaging of 3,301 elderly people. The Cardiovascular Health Study. Collaborative Research Group. - Longstreth, W T; Arnold, A M; Manolio, T A; Burke, G L; Bryan, N; Jungreis, C A; O'Leary, D; Enright, P L; Fried, L (Neuroepidemiology, 2000)
To identify potential risk factors for and clinical manifestations of ventricular and sulcal enlargement on cranial magnetic resonance imaging (MRI), 3,301 community-dwelling people 65 years or older without a history of stroke or transient ischemic attack underwent extensive standardized evaluations and MRI. In the multivariate model, increased age and white matter grade on MRI were the dominant risk factors for ventricular and sulcal grade. For ventricular grade, other than race, for which non-Blacks had higher grades, models for men and women shared no other factors. For sulcal grades, models for men and women shared variables reflecting cigarette smoking and diabetes. Clinical features were correlated more strongly with ventricular than sulcal grade and more strongly for women than men. Significant age-adjusted correlations between ventricular grade and the Digit-Symbol Substitution Test were found for men and women. Prospective studies will be needed to extend findings of this cross-sectional analysis.
Keywords: Age Distribution; Age Factors; Aged; Aging; Cerebral Ventricles; Continental Population Groups; Cross-Sectional Studies; Diabetes Complications; Female; Humans; Hypertrophy; Linear Models; Magnetic Resonance Imaging; Male; Multivariate Analysis; Risk Factors; Severity of Illness Index; Sex Distribution; Sex Factors; Smoking; Stroke

Coronary artery calcification in older adults with minimal clinical or subclinical cardiovascular disease. - Newman, A B; Naydeck, B; Sutton-Tyrrell, K; Edmundowicz, D; Gottdiener, J; Kuller, L H (J Am Geriatr Soc, 2000)
BACKGROUND: Coronary artery calcification (CAC) reflects the extent of coronary artery atherosclerosis. The extent of coronary artery calcification is not well described in older adults. OBJECTIVE: To determine the extent of CAC in older adults participating in a large population study of cardiovascular disease (CVD), especially those characterized as having minimal clinical or subclinical cardiovascular disease. DESIGN: An observational epidemiologic study. POPULATION: Participants in the Cardiovascular Health Study Cohort, mean age 78 years, who had electron beam computed tomography (EBT) scan of the heart (n = 133); included were 106 persons with no prior evidence of clinical or subclinical CVD. MEASUREMENTS: Total CAC score was measured using cardiac EBT. Cardiovascular disease and risk factors, as well as carotid ultrasound, electrocardiogram, echocardiogram, and ankle-arm index, had been measured previously to define subclinical disease. Previous cerebral magnetic resonance imaging was also evaluated. RESULTS: Overall, the CAC scores were higher in those with clinical cardiovascular disease or evidence of subclinical cardiovascular disease than in those with no evidence of disease. For the 106 participants without evidence of clinical or subclinical disease, the median score was 176, compared with 367 in those with subclinical disease and 923 in those with clinical CVD. Seventeen persons had scores of zero. There was little difference in risk factors across quartiles of CAC in the subgroup of 106 with prior characterization of minimal CVD despite the broad range of CAC scores. There was a higher proportion of those with white matter grade > or = 2 by magnetic resonance imaging among those with higher CAC scores (P = .025). Infarct-like lesions prevalence ranged from 12.5% in the lowest group to 47.1% in the highest CAC group (P = .019). CONCLUSIONS: Older adults with evidence of clinical or subclinical CVD have higher total CAC scores. Though the extent of coronary artery calcification was lower in those with minimal evidence of CVD, the range was broad and not explained by CVD risk factors.
Keywords: Aged; Aging; Analysis of Variance; Calcinosis; Cardiovascular Diseases; Chi-Square Distribution; Coronary Artery Disease; Coronary Disease; Female; Humans; Male; Risk Factors; Statistics, Nonparametric; Tomography, X-Ray Computed

Daytime sleepiness predicts mortality and cardiovascular disease in older adults. The Cardiovascular Health Study Research Group. - Newman, A B; Spiekerman, C F; Enright, P; Lefkowitz, D; Manolio, T; Reynolds, C F; Robbins, J (J Am Geriatr Soc, 2000)
INTRODUCTION: As part of the baseline examination in the Cardiovascular Health Study, sleep disturbance symptoms including snoring and daytime sleepiness, were assessed as potential risk factors or precipitants of cardiovascular disease (CVD). Because of the association of sleep disturbance with poorer health and the possible associations of sleep apnea with CVD, we hypothesized that those with poorer sleep or daytime sleepiness may be at increased risk of mortality or incident CVD. SETTING: Participants (n = 5888) were recruited in 1989, with an additional minority cohort recruited in 1993, in four US communities for a cohort study designed to evaluate risk factors for cardiovascular disease. METHODS: An interview-administered questionnaire regarding health and sleep habits with ongoing ascertainment of total mortality and cardiovascular disease morbidity and mortality, including total CVD morbidity and mortality, incident myocardial infarction, and congestive heart failure. RESULTS: Daytime sleepiness was the only sleep symptom that was significantly associated with mortality in both men and women. The unadjusted hazard ratio was 2.12 (1.66, 2.72) in women and 1.40 (1.12, 1.73) in men. Men who reported difficulty falling asleep also had an increased mortality rate (HR = 1.43 (1.14, 1.80)) which was not seen in women. The risks were attenuated with adjustment for age but remained significant for daytime sleepiness in women (HR = 1.82 (1.42, 2.34)) and for difficulty falling asleep in men. (HR = 1.29 (1.03, 1.63)). Frequent awakenings, early morning awakening, and snoring were not associated with a significantly increased risk of mortality in these older men and women. Crude event rates were evaluated for total incident cardiovascular morbidity and mortality, incident myocardial infarction, and incident congestive heart failure (CHF). Incident CVD rates were higher in both men and women with daytime sleepiness. The aged adjusted HR was 1.35 (95% CI = 1.03, 1.76) in men and was 1.66 (95% CI = 1.28, 2.16) in women. Incident CVD was not higher in those with any other sleep disturbance including snoring. The risk of CVD events associated with daytime sleepiness was attenuated but remained significant in women after adjustment for age. Incident myocardial infarction (MI) rates were also higher in women with daytime sleepiness but were not significantly higher in men. Incident CHF rates were increased in both men and women with daytime sleepiness. In men, the age adjusted HR was 1.49 (95% CI, 1.12- 1.98) and in women, was 2.21 (95% CI, 1.64-2.98). Women reporting both daytime sleepiness and frequent awakening had a hazard ratio of 2.34 (95% CI, 1.66-3.29) for incident CHF compared with those with daytime sleepiness but without frequent awakening. This interaction was not found in men. CONCLUSIONS: In this study, daytime sleepiness was the only sleep disturbance symptom that was associated with mortality, incident CVD morbidity and mortality, MI, and CHF. These findings were stronger in women than men, i.e., the associations persisted for mortality, CVD, and CHF in women after adjustment for age and other factors. Thus, a report of daytime sleepiness identifies older adults at increased risk for total and cardiovascular mortality, and is an independent risk factor in women.
Keywords: Age Factors; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Female; Health Status; Heart Failure; Humans; Incidence; Male; Multivariate Analysis; Myocardial Infarction; Odds Ratio; Risk Factors; Sex Factors; Sleep Apnea Syndromes; Sleep Stages; Sleep Wake Disorders; Snoring; Surveys and Questionnaires; United States

Rates of sensor loss in unattended home polysomnography: the influence of age, gender, obesity, and sleep-disordered breathing. - Kapur, V K; Rapoport, D M; Sanders, M H; Enright, P; Hill, J; Iber, C; Romaniuk, J (Sleep, 2000)
OBJECTIVES: To evaluate study failure and sensor loss in unattended home polysomnography and their relationship to age, gender, obesity, and severity of sleep-disordered breathing (SDB). DESIGN: A cross-sectional analysis of data gathered prospectively for the Sleep Heart Health Study (SHHS). SETTING: Unattended polysomnography was performed in participants' homes by the staff of the sites that are involved in SHHS. PARTICIPANTS: 6,802 individuals who met the inclusion criteria (age >40 years, no history of treatment of sleep apnea, no tracheostomy, no current home oxygen therapy) for SHHS. RESULTS: A total of 6802 participants had 7151 studies performed. 6161 of 6802 initial studies (90.6%) were acceptable. Obesity was associated with a decreased likelihood of a successful initial study. After one or more attempts, 6440 participants (94.7%) had studies that were judged as acceptable. The mean duration of scorable signals for specific channels ranged from 5.7 to 6.8 hours. The magnitudes of the effects of age, gender, BMI, and RDI on specific signal durations were not clinically significant. CONCLUSION: Unattended home PSG as performed for SHHS was usually successful. Participant characteristics had very weak associations with duration of scorable signal. This study suggests that unattended home PSG, when performed with proper protocols and quality controls, has reasonable success rates and signal quality for the evaluation of SDB in clinical and research settings.
Keywords: Age Factors; Cross-Sectional Studies; Electroencephalography; Electromyography; Electrooculography; Equipment Failure; Female; Humans; Male; Middle Aged; Obesity; Polysomnography; Prospective Studies; Severity of Illness Index; Sex Factors; Sleep Apnea Syndromes

Brachial flow-mediated vasodilator responses in population-based research: methods, reproducibility and effects of age, gender and baseline diameter. - Herrington, D M; Fan, L; Drum, M; Riley, W A; Pusser, B E; Crouse, J R; Burke, G L; McBurnie, M A; Morgan, T M; Espeland, M A (J Cardiovasc Risk, 2001)
BACKGROUND: Brachial artery ultrasound has been proposed as an inexpensive, accurate way to assess cardiovascular risk in populations. However, analysis and interpretation of these data are not uniform. METHODS: We analysed the relationship between relative and absolute changes in brachial artery diameter in response to flow-mediated dilation and age, gender and baseline diameter among 4,040 ultrasound examinations from subjects aged 14 to 98 years. RESULTS: Reproducibility studies demonstrated intra- and interreader and intrasubject correlations from 0.67 to 0.84 for repeated measures of per cent change in diameter. Per cent change in diameter after flow stimulus was 3.58 +/- 0.10% (mean +/- standard deviation). Corresponding values for baseline diameter and absolute change in diameter were 4.43 +/- 0.87 mm and 0.15 +/- 0.01 mm, respectively. Baseline diameter and its variance were inversely related to per cent change in diameter (P< 0.001). In contrast, absolute change in diameter was more uniform throughout the range of baseline diameters. Baseline diameter was directly related, and per cent change in diameter inversely related, to age (P < 0.001 for all three measures). Time to maximum vasodilator response increased with age (P < 0.001). Women (n=2,315) had significantly larger per cent change in diameter than men (n=1,725) (P < 0.001). However, after adjustment for age and baseline diameter, per cent and absolute change were 5% smaller in women than men (P < 0.05 for both). In multivariate analysis, age was overwhelmingly the most important determinant of absolute change in diameter (P < 0.001). CONCLUSIONS: Automated analysis of brachial flow-mediated vasodilator responses is both feasible and reproducible in large-scale clinical and population-based research.
Keywords: Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Blood Circulation; Brachial Artery; Female; Humans; Male; Middle Aged; Observer Variation; Population Surveillance; Reproducibility of Results; Sex Factors; Vasodilation; Vasodilator Agents

Coronary artery calcification in older adults to age 99: prevalence and risk factors. - Newman, A B; Naydeck, B L; Sutton-Tyrrell, K; Feldman, A; Edmundowicz, D; Kuller, L H (Circulation, 2001)
BACKGROUND: Coronary artery calcification has been proposed as a noninvasive method to assess cardiovascular disease (CVD) risk. However, the prevalence and risk factors for coronary artery calcification in populations >65 years have not been well studied. METHODS AND RESULTS: Electron beam tomography was performed to assess coronary artery calcium (CAC) in 614 older adults aged, on average, 80 years (range, 67 to 99 years); 367 (60%) were women, and 143 (23%) were black. Calcium scores ranged from 0 to 5459. Median scores were 622 for men and 205 for women. Scores increased by age and were lower in blacks than in whites. Nine percent of subjects (n=57) had no CAC, and 31% (n=190) had a score lower than 100. A history of CVD was associated with calcium score. Age, male sex, white race, CVD, triglyceride level, pack-years of smoking, and asthma, emphysema, or bronchitis (chronic obstructive pulmonary disease) were independently associated with CAC score in the fourth quartile. CONCLUSIONS: A wide range of CAC scores was observed, suggesting adaptation with aging. CAC may have potential to predict CVD in older adults, but this remains to be determined.
Keywords: Age Distribution; Age Factors; Aged; Aged, 80 and over; Black People; Calcinosis; Calcium; Cohort Studies; Comorbidity; Coronary Angiography; Coronary Artery Disease; Coronary Vessels; Demography; Female; Humans; Logistic Models; Male; Predictive Value of Tests; Prevalence; Risk Factors; Sex Distribution; Sex Factors; Tomography, X-Ray Computed; White People

Correlates of peak expiratory flow lability in elderly persons. - Enright, P L; McClelland, R L; Buist, A S; Lebowitz, M D (Chest, 2001)
OBJECTIVE: To determine the correlates of the lability of peak expiratory flow (PEF) in the elderly. METHODS: A community sample of 4,581 persons > or = 65 years old from the Cardiovascular Health Study completed an asthma questionnaire and underwent spirometry. During a follow-up examination of the cohort, 1,836 persons agreed to measure PEF at home twice daily for 2 weeks, and 90% successfully obtained at least 4 days of valid measurements. PEF lability was calculated as the highest daily (PEF maximum - PEF minimum)/mean PEF. RESULTS: Mean PEF measured at home was accurate when compared to PEF determined by spirometry in the clinic. Mean PEF lability was 18% in those with current asthma (n = 165) vs 12% in healthy nonsmokers (upper limit of normal, 29%). Approximately 26% of those with asthma and 14% of the other participants had abnormally high PEF lability (> 29%). After excluding participants with asthma, other independent predictors of high PEF lability included black race, current and former smoking, airway obstruction on spirometry, daytime sleepiness, recent wheezing, chronic cough, emphysema, and wheezing from lying in a supine position. Despite having a lower mean PEF, those reporting congestive heart failure (n = 82) did not have significantly higher PEF lability. CONCLUSIONS: Measurement of PEF lability at home is highly successful in elderly persons. PEF lability > or = 30% is abnormal in the elderly and is associated with asthma.
Keywords: Aged; Aged, 80 and over; Aging; Asthma; Female; Heart Failure; Humans; Male; Monitoring, Ambulatory; Peak Expiratory Flow Rate; Predictive Value of Tests; Pulmonary Disease, Chronic Obstructive; Reference Values; Rhinitis, Allergic, Seasonal; Risk Factors; Signal Processing, Computer-Assisted; Spirometry

Echocardiographic features of the right heart in sleep-disordered breathing: the Framingham Heart Study. - Guidry, U C; Mendes, L A; Evans, J C; Levy, D; O'Connor, G T; Larson, M G; Gottlieb, D J; Benjamin, E J (Am J Respir Crit Care Med, 2001)
The effect of sleep-disordered breathing (SDB) on right heart structure and function is controversial. Studies of patients referred for evaluation of possible sleep apnea have yielded conflicting results, and the impact of SDB on the right heart has not been investigated in the general population. We examined the echocardiographic features of subjects with SDB at the Framingham Heart Study site of the Sleep Heart Health Study. Of 1,001 polysomnography subjects, 90 with SDB defined as a respiratory disturbance index (RDI) score > 90th percentile (mean RDI = 42) were compared with 90 low-RDI subjects (mean RDI = 5) matched for age, sex, and body mass index. Right heart measurements, made without knowledge of clinical status, were compared between groups. The majority of the subjects were male (74%). After multivariable adjustment, right ventricle (RV) wall thickness was significantly greater (p = 0.005) in subjects with SDB (0.78 +/- 0.02 cm) than in the low-RDI subjects (0.68 +/- 0.02 cm). Right atrial dimensions, RV dimensions, and RV systolic function were not found to be significantly different between subjects with SDB and the low-RDI subjects. We conclude that in this community-based study of SDB and right heart echocardiographic features, RV wall thickness was increased in subjects with SDB. Whether the RV hypertrophy observed in persons with SDB is associated with increased morbidity and mortality remains unknown.
Keywords: Adult; Age Factors; Aged; Cohort Studies; Cross-Sectional Studies; Data Interpretation, Statistical; Echocardiography; Female; Forced Expiratory Volume; Humans; Hypertrophy, Right Ventricular; Linear Models; Male; Middle Aged; Obesity; Observer Variation; Polysomnography; Prospective Studies; Sex Factors; Sleep Apnea Syndromes; Ventricular Function, Right; Vital Capacity

Estrogen replacement and brachial artery flow-mediated vasodilation in older women. - Herrington, D M; Espeland, M A; Crouse, J R; Robertson, J; Riley, W A; McBurnie, M A; Burke, G L (Arterioscler Thromb Vasc Biol, 2001)
It remains unclear whether estrogen therapy (with or without progestin) improves endothelial function in older postmenopausal women with or at risk for coronary heart disease. To address this issue, we analyzed brachial artery flow-mediated vasodilation in the Cardiovascular Health Study, a longitudinal study of cardiovascular risk factors in subjects over 65 years of age. At the tenth annual Cardiovascular Health Study examination, 1662 women returned for follow-up. Eighteen percent (n=291) were current users of estrogen replacement, most of whom (75.9%, n=221) took unopposed estrogen. Brachial artery ultrasound examinations measuring vasodilation in response to a flow stimulus (hyperemia) were performed on 1636 women. There were no statistical differences in brachial flow-mediated vasodilator responses between users and nonusers, even after adjustment for potential confounders. Absence of an effect was most notable in women over 80 years old and in those with established cardiovascular disease. However, among women without clinical or subclinical cardiovascular disease or its risk factors, there was a significant association between hormone replacement therapy use and flow-mediated vasodilator responses (P=0.01). Among older postmenopausal women, favorable vascular effects of estrogen may be limited to those who have not yet developed atherosclerotic vascular disease. These data emphasize the importance of ongoing efforts to determine the role of hormone replacement therapy for primary prevention of cardiovascular disease.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Brachial Artery; Cardiovascular Diseases; Drug Therapy, Combination; Estrogen Replacement Therapy; Estrogens; Female; Humans; Longitudinal Studies; Progestins; Risk Factors; Ultrasonography; Vasodilation

Hormone replacement therapy is associated with higher FEV1 in elderly women. - Carlson, C L; Cushman, M; Enright, P L; Cauley, J A; Newman, A B (Am J Respir Crit Care Med, 2001)
Estrogen and progesterone use have been associated with improved pulmonary function in premenopausal women. However, little research has examined the relationship between hormone replacement therapy (HRT) and pulmonary function in postmenopausal women. We examined the relationship of HRT with spirometry in 2,353 women aged 65 yr and older participating in the Cardiovascular Health Study in 1993/1994. Current use of HRT was hypothesized to be associated with higher FEV1, higher FVC, and less pulmonary obstruction (FEV1/FVC < 65%). FEV1 was higher among current HRT users compared to noncurrent users in the following groups: overall (1.82 L versus 1.66 L, p < 0.0001), among women without asthma (1.85 L versus 1.69 L, p < 0.0001), among former smokers (1.76 L versus 1.60 L, p = 0.013), and among never smokers (1.90 L versus 1.72 L, p < 0.0001). Overall, HRT use was associated with a lower prevalence of pulmonary obstruction (OR 0.75 [95% CI 0.55, 0.99]). After controlling for potential confounders, HRT use was significantly associated with higher FEV(1) (p = 0.031) and with a lower prevalence of obstruction (OR 0.67 [95% CI 0.48, 0.95]). We conclude that postmenopausal women who use HRT have higher levels of FEV1 and less obstruction, which could not be explained by their lower rates of smoking and other health factors associated with HRT use.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Estrogen Replacement Therapy; Female; Forced Expiratory Volume; Humans; Longitudinal Studies; Spirometry; Vital Capacity

Importance of heart failure with preserved systolic function in patients > or = 65 years of age. CHS Research Group. Cardiovascular Health Study. - Kitzman, D W; Gardin, J M; Gottdiener, J S; Arnold, A; Boineau, R; Aurigemma, G; Marino, E K; Lyles, M; Cushman, M; Enright, P L (Am J Cardiol, 2001)
Although congestive heart failure (CHF) is a common syndrome among the elderly, there is a relative paucity of population-based data, particularly regarding CHF with normal systolic left ventricular function. A total of 4,842 independent living, community-dwelling subjects aged 66 to 103 years received questionnaires on medical history, family history, personal habits, physical activity, and socioeconomic status, confirmation of pre-existing cardiovascular and cerebrovascular disease, anthropometric measurements, casual seated random-zero blood pressure, forced vital capacity and expiratory volume in 1 second, 12-lead supine electrocardiogram, fasting glucose, creatinine, plasma lipids, carotid artery wall thickness by ultrasonography, and echocardiography-Doppler examinations. Participants with at least 1 confirmed episode of CHF by Cardiovascular Health Study criteria were considered prevalent for CHF. The prevalence of CHF was 8.8% and was associated with increased age, particularly for women, in whom it increased more than twofold from age 65 to 69 years (6.6%) to age > or = 85 years (14%). In multivariate analysis, subjects with CHF were more likely to be older (odds ratio [OR] 1.2 for 5-year difference, men OR 1.1), and more often had a history of myocardial infarction (OR 7.3), atrial fibrillation (OR 3.0), diabetes mellitus (OR 2.1), renal dysfunction (OR 2.0 for creatinine < or = 1.5 mg/ dl), and chronic pulmonary disease (OR 1.8; women only). The echocardiographic correlates of CHF were increased left atrial and ventricular dimensions. Importantly, 55% of subjects with CHF had normal left ventricular systolic function and 80% had either normal or only mildly reduced systolic function. Among subjects with CHF, women had normal systolic function more frequently than men (67% vs 42%; p < 0.001). Thus, CHF is common among community-dwelling elderly. It increases with age and is usually associated with normal systolic LV function, particularly among women. The finding that a large proportion of elderly with CHF have preserved LV systolic function is important because there is a paucity of data to guide management in this dominant subset.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Chi-Square Distribution; Echocardiography, Doppler; Female; Health Status; Heart Failure; Humans; Logistic Models; Longitudinal Studies; Male; Prevalence; Risk Factors; Surveys and Questionnaires; United States; Ventricular Function, Left

Predictors of loss of lung function in the elderly: the Cardiovascular Health Study. - Griffith, K A; Sherrill, D L; Siegel, E M; Manolio, T A; Bonekat, H W; Enright, P L (Am J Respir Crit Care Med, 2001)
Pulmonary function, as measured by spirometry (FEV1 or FVC), is an important independent predictor of morbidity and mortality in elderly persons. In this study we examined the predictors of longitudinal decline in lung function for participants of the Cardiovascular Health Study (CHS). The CHS was started in 1990 as a population-based observational study of cardiovascular disease in elderly persons. Spirometry testing was conducted at baseline, 4 and 7 yr later. The data were analyzed using a random effects model (REM) including an AR(1) error structure. There were 5,242 subjects (57.6% female, mean age 73 yr, 87.5% white and 12.5% African-American) with eligible FEV1 measures representing 89% of the baseline cohort. The REM results showed that African-Americans had significantly lower spirometry levels than whites but that their rate of decline with age was significantly less. Subjects reporting congestive heart failure (CHF), high systolic blood pressure (> 160 mm Hg), or taking beta-blockers had significantly lower spirometry levels; however, the effects of high blood pressure and taking beta-blockers diminished with increasing age. Chronic bronchitis, pneumonia, emphysema, and asthma were associated with reduced spirometry levels. The most notable finding of these analyses was that current smoking (especially for men) was associated with more rapid rates of decline in FVC and FEV1. African-Americans (especially women) had slower rates of decline in FEV1 than did whites. Although participants with current asthma had a mean 0.5 L lower FEV1 at their baseline examination, they did not subsequently experience more rapid declines in FEV1.
Keywords: Age Factors; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Forced Expiratory Volume; Humans; Longitudinal Studies; Lung; Lung Volume Measurements; Male

Weight change in old age and its association with mortality. - Newman, A B; Yanez, D; Harris, T; Duxbury, A; Enright, P L; Fried, L P (J Am Geriatr Soc, 2001)
OBJECTIVES: Previous studies of weight change and mortality in older adults have relied on self-reported weight loss, have not evaluated weight gain, or have had limited information on health status. Our objective was to determine whether 5% weight gain or loss in 3 years was predictive of mortality in a large sample of older adults. DESIGN: Longitudinal observational cohort study. SETTING: Four U.S. communities. PARTICIPANTS: Four thousand seven hundred fourteen community-dwelling older adults, age 65 and older. MEASUREMENTS: Weight gain or loss of 5% in a 3-year period was examined in relationship to baseline health status and interim health events. Risk for subsequent mortality was estimated in those with weight loss or weight gain compared with the group whose weight was stable. RESULTS: Weight changes occurred in 34.6% of women and 27.3% of men, with weight loss being more frequent than gain. Weight loss was associated with older age, black race, higher weight, lower waist circumference, current smoking, stroke, any hospitalization, death of a spouse, activities of daily living disability, lower grip strength, and slower gait speed. Weight loss but not weight gain of 5% or more was associated with an increased risk of mortality that persisted after multivariate adjustment (Hazard ratio (HR) = 1.67, 95% CI = 1.29-2.15) and was similar in those with no serious illness in the period of weight change. Those with weight loss and low baseline weight had the highest crude mortality rate, although the HR for weight loss was similar for all tertiles of baseline weight and for those with or without a special diet, compared with those whose weight was stable. CONCLUSIONS: This study confirms that even modest decline in body weight is an important and independent marker of risk of mortality in older adults.
Keywords: Aged; Analysis of Variance; Body Weight; Chi-Square Distribution; Female; Health Status; Humans; Longitudinal Studies; Male; Mortality; Proportional Hazards Models; Risk Factors; United States; Weight Gain; Weight Loss

Angiotensin II type 1 receptor polymorphisms in the cardiovascular health study: relation to blood pressure, ethnicity, and cardiovascular events. - Hindorff, Lucia A; Heckbert, Susan R; Tracy, Russell; Tang, Zhonghua; Psaty, Bruce M; Edwards, Karen L; Siscovick, David S; Kronmal, Richard A; Nazar-Stewart, Valle (Am J Hypertens, 2002)
BACKGROUND: The angiotensin II type 1 receptor A1166C polymorphism has been associated with increased risks of hypertension and myocardial infarction in several small studies. We examined the association between this polymorphism and new-onset hypertension, blood pressure (BP) control, and incident cardiovascular events in a large population-based cohort of older adults. METHODS: Eight hundred self-identified African Americans and 1,371 randomly selected white participants in the Cardiovascular Health Study were genotyped. The median duration of follow-up was 8.1 years. RESULTS: The A1166C polymorphism was not associated with new-onset hypertension, with BP control, or with incident cardiovascular events in the overall population. In white participants, the CC genotype was associated with higher baseline systolic BP and pulse pressure, compared to the AC or AA genotype. In whites with treated hypertension at baseline, compared to the AA genotype, the CC genotype was associated with increased risks of incident congestive heart failure (hazard ratio = 2.5, 95% confidence interval [CI] 1.3-4.9) and incident ischemic stroke (hazard ratio = 2.6, 95% CI 1.1-6.0). These associations were not observed among white participants without treated hypertension, but the interaction of genotype with treated hypertension on ischemic stroke and heart failure was only marginally significant. CONCLUSIONS: On the whole, in this large cohort of older adults, the A1166C polymorphism was not associated with BP control or incident cardiovascular events. The subgroup findings in treated hypertensives need to be confirmed in additional studies.
Keywords: African Continental Ancestry Group; Aged; Blood Pressure; Cardiovascular Diseases; European Continental Ancestry Group; Female; Gene Frequency; Humans; Hypertension; Male; Polymorphism, Genetic; Receptor, Angiotensin, Type 1; Receptors, Angiotensin; United States

Predictors of sleep-disordered breathing in community-dwelling adults: the Sleep Heart Health Study. - Young, Terry; Shahar, Eyal; Nieto, F Javier; Redline, Susan; Newman, Anne B; Gottlieb, Daniel J; Walsleben, Joyce A; Finn, Laurel; Enright, Paul; Samet, Jonathan M (Arch Intern Med, 2002)
BACKGROUND: Sleep-disordered breathing (SDB) is common, but largely undiagnosed in the general population. Information on demographic patterns of SDB occurrence and its predictive factors in the general population is needed to target high-risk groups that may benefit from diagnosis. METHODS: The sample comprised 5615 community-dwelling men and women aged between 40 and 98 years who were enrolled in the Sleep Heart Health Study. Data were collected by questionnaire, clinical examinations, and in-home polysomnography. Sleep-disordered breathing status was based on the average number of apnea and hypopnea episodes per hour of sleep (apnea-hypopnea index [AHI]). We used multiple logistic regression modeling to estimate cross-sectional associations of selected participant characteristics with SDB defined by an AHI of 15 or greater. RESULTS: Male sex, age, body mass index, neck girth, snoring, and repeated breathing pause frequency were independent, significant correlates of an AHI of 15 or greater. People reporting habitual snoring, loud snoring, and frequent breathing pauses were 3 to 4 times more likely to have an AHI of 15 or greater vs an AHI less than 15, but there were weaker associations for other factors with an AHI of 15 or greater. The odds ratios (95% confidence interval) for an AHI of 15 or greater vs an AHI less than 15 were 1.6 and 1.5, respectively, for 1-SD increments in body mass index and neck girth. As age increased, the magnitude of associations for SDB and body habitus, snoring, and breathing pauses decreased. CONCLUSIONS: A significant proportion of occult SDB in the general population would be missed if screening or case finding were based solely on increased body habitus or male sex. Breathing pauses and obesity may be particularly insensitive for identifying SDB in older people. A better understanding of predictive factors for SDB, particularly in older adults, is needed.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Cohort Studies; Continental Population Groups; Female; Humans; Male; Middle Aged; Obesity; Predictive Value of Tests; Residence Characteristics; Risk Factors; Sex Factors; Sleep Apnea Syndromes; Snoring

Prevalence of renovascular disease in the elderly: a population-based study. - Hansen, Kimberley J; Edwards, Matthew S; Craven, Timothy E; Cherr, Gregory S; Jackson, Sharon A; Appel, Richard G; Burke, Gregory L; Dean, Richard H (J Vasc Surg, 2002)
PURPOSE: The purpose of this investigation was to estimate the population-based prevalence of renovascular disease (RVD), defined as > or = 60% diameter-reducing renal artery stenosis or occlusion, and to define its associations with age, gender, race, and other potential risk factors among participants in the Cardiovascular Health Study (CHS). METHODS: The CHS is a multicenter, longitudinal cohort study of cardiovascular disease risk factors, morbidity, and mortality among free-living adults of more than 65 years of age. As part of an ancillary investigation, participants in the Forsyth County cohort of the CHS were invited to undergo renal duplex sonography (RDS) to define the presence or absence of RVD. RVD was defined as stenosis with a focal renal artery peak systolic velocity exceeding 1.8 m/s in the main renal artery and defined as occlusion when an imaged renal artery lacked a Doppler signal. Demographic and atherosclerotic risk factor data were gathered as part of the baseline CHS examination. Univariable tests of association were performed with chi(2) and Student t tests and logistic regression analysis. Multivariate associations were examined with logistic regression analysis. RESULTS: Eight hundred seventy CHS participants underwent RDS. Of these examinations, 834 (96%) were technically adequate to define the presence or absence of RVD. The RDS study cohort had a mean age of 77.2 +/- 4.9 years and consisted of 63% women and 37% men. Participant race was 76% white and 23% African American. The overall prevalence rate of RVD was 6.8%. Among the 57 patients with RVD, 50 (88%) had unilateral disease and seven (12%) had bilateral disease. Seven cases were seen of renal artery occlusion, including one case with contralateral renal artery stenosis. The mean ages of patients with and without RVD were 78.7 +/- 5.7 years and 77.1 +/- 4.9 years (P =.018). RVD was present in 5.5% of women and 9.1% of men (P =.053). RVD was present in 6.9% of white participants and 6.7% of African American participants (P =.933). Multivariate analysis revealed increasing participant age (P =.028; odds ratio, 1.34; 95% CI, 1.03, 1.73), high-density lipoprotein cholesterol levels of less than 40 mg/dL (P =.003; odds ratio, 2.63; 95% CI, 1.40, 4.93), and increasing systolic blood pressure (P =.007; odds ratio, 1.44; 95% CI, 1.10, 1.87) to be significantly and independently associated with the presence of RVD. CONCLUSION: This investigation provides the first population-based estimate of the prevalence of RVD among free-living, elderly black and white Americans. RVD was present in 6.8% of the study cohort. RVD showed no association with ethnicity. However, its presence was significantly and independently associated with increasing age, low high-density lipoprotein cholesterol levels, and increasing systolic blood pressure.
Keywords: Age Factors; Aged; Aged, 80 and over; Cohort Studies; Ethnic Groups; Female; Humans; Longitudinal Studies; Male; Prevalence; Prospective Studies; Renal Artery; Renal Artery Obstruction; Risk Factors; Sex Factors; Ultrasonography, Doppler, Duplex

Racial differences in coronary artery calcification in older adults. - Newman, Anne B; Naydeck, Barbara L; Whittle, Jeff; Sutton-Tyrrell, Kim; Edmundowicz, Daniel; Kuller, Lewis H (Arterioscler Thromb Vasc Biol, 2002)
Reports on race-related differences in coronary artery calcium (CAC) are just beginning to emerge and have not been well studied in the elderly. This study was undertaken to assess whether such differences exist and the relationship between CAC and cardiovascular risk factors in a cohort of elderly community-dwelling adults. CAC was measured by using electron-beam tomography in 614 adults (aged 67 to 99 years), of whom 59% were women and 23% were black. The median CAC score was lower in blacks than in whites for men (159 versus 787, respectively; P<0.001) and for women (134 versus 233, respectively; P=0.02) after adjustment for age, cardiovascular disease, and risk factors for cardiovascular disease, although this difference was stronger and remained significant among men only. Lower CAC scores were also observed in the subgroup of blacks with a history of myocardial infarction. The lower CAC scores in blacks compared with whites observed in this study is consistent with either a lower prevalence of coronary artery disease or a lower extent of calcification of coronary artery disease.
Keywords: Age Factors; Aged; Calcinosis; Cohort Studies; Coronary Artery Disease; Female; Humans; Logistic Models; Male; Risk Factors; Sex Factors; Tomography, X-Ray Computed

Relationship between coronary artery calcification and other measures of subclinical cardiovascular disease in older adults. - Newman, Anne B; Naydeck, Barbara L; Sutton-Tyrrell, Kim; Edmundowicz, Daniel; O'Leary, Daniel; Kronmal, Richard; Burke, Gregory L; Kuller, Lewis H (Arterioscler Thromb Vasc Biol, 2002)
BACKGROUND: In the Cardiovascular Health Study, subclinical cardiovascular disease (CVD) predicted CVD events in older adults. The extent to which this measure or its components reflect calcified coronary disease is unknown. METHODS AND RESULTS: Coronary artery calcium (CAC) was assessed with electron beam tomography in 414 participants without clinical CVD and examined using cut points (CAC> or =400 and CAC> or =800) and the log(CAC); 274 had subclinical CVD by ankle-arm index, ECG, or carotid ultrasound. Cut points for subclinical disease as previously defined in the Cardiovascular Health Study were examined as well as continuous measures to produce receiver operating characteristic curve curves. A low ankle-arm index was highly specific for a high CAC score. The internal carotid artery intima-media thickness was most strongly correlated with CAC (r=0.30) and was significantly related to both CAC cut points and to the log(CAC) score independently of all other measures. CONCLUSIONS: In these community-dwelling older adults without clinical CVD, internal carotid artery intima-media thickness was most closely related to CAC. However, 17.5% of those with a CAC> or =400 would be missed in the ascertainment of subclinical atherosclerosis using the previously published composite of subclinical atherosclerosis. Prospective follow-up will determine whether the CAC score improves prediction of CVD events over other noninvasive measures.
Keywords: Aged; Aged, 80 and over; Calcinosis; Cardiovascular Diseases; Carotid Stenosis; Cohort Studies; Coronary Artery Disease; Demography; Female; Humans; Male; Prevalence; Risk Factors; Sensitivity and Specificity; Sex Factors; Tomography, X-Ray Computed; Tunica Intima; Tunica Media

Time trends in high blood pressure control and the use of antihypertensive medications in older adults: the Cardiovascular Health Study. - Psaty, Bruce M; Manolio, Teri A; Smith, Nicholas L; Heckbert, Susan R; Gottdiener, John S; Burke, Gregory L; Weissfeld, Joel; Enright, Paul; Lumley, Thomas; Powe, Neil; Furberg, Curt D (Arch Intern Med, 2002)
BACKGROUND: Control of high blood pressure (BP) in older adults is an important part of public health efforts at prevention. OBJECTIVE: To assess recent time trends in the awareness, treatment, and control of high BP and in the use of medications to treat high BP. METHODS: In the Cardiovascular Health Study, 5888 adults 65 years and older were recruited from 4 US centers. At baseline, participants underwent an extensive examination that included the measurement of BP, use of medications, and other risk factors. Participants were followed up with annual visits that assessed BP and medication use from baseline in 1989-1990 through the examination in 1998-1999. The primary outcome measures were control of BP to levels lower than than 140/90 mm Hg and the prevalence of use of various classes of antihypertensive medications. RESULTS: The awareness, treatment, and control of high BP improved during the 1990s. The proportions aware and treated were higher among blacks than whites, though control prevalences were similar. For both groups combined, the control of high BP to lower than 140/90 mm Hg increased from 37% at baseline to 49% in 1999. The 51% whose BP was not controlled generally had isolated mild to moderate elevations in systolic BP. Among treated persons, the improvement in control was achieved in part by a mean increase of 0.2 antihypertensive medications per person over the course of 9 years. Improved control was also achieved by increasing the proportion of the entire Cardiovascular Health Study population that was treated for hypertension, from 34.5% in 1990 to 51.1% in 1999. Time trends in antihypertensive drug use were pronounced. Among those without coronary disease, the use of low-dose diuretics and beta-blockers decreased, while the use of newer agents, such as calcium channel blockers, angiotensin-converting enzyme inhibitors, and alpha-blockers increased. CONCLUSIONS: While control of high BP improved in the 1990s, about half the participants with hypertension had uncontrolled BP, primarily mild to moderate elevations in systolic BP. Low-dose diuretics and beta-blockers--the preferred agents since 1993 according to the recommendations of the Joint National Committee on the Detection, Evaluation and Treatment of High Blood Pressure--remained underused. More widespread use of these agents will be an important intervention to prevent the devastating complications of hypertension, including stroke, myocardial infarction, and heart failure.
Keywords: Age Factors; Aged; Antihypertensive Agents; Awareness; Cohort Studies; Drug Therapy; Female; Health Knowledge, Attitudes, Practice; Humans; Hypertension; Male; Prospective Studies; Time Factors

The 6-min walk test: a quick measure of functional status in elderly adults. - Enright, Paul L; McBurnie, Mary Ann; Bittner, Vera; Tracy, Russell P; McNamara, Robert; Arnold, Alice; Newman, Anne B (Chest, 2003)
OBJECTIVES: To determine the correlates of the total 6-min walk distance (6MWD) in a population sample of adults > or = 68 years old. METHODS: The standardized 6-min walk test (6MWT) was administered to the Cardiovascular Health Study cohort during their seventh annual examination. RESULTS: Of the 3,333 participants with a clinic visit, 2,281 subjects (68%) performed the 6MWT. There were no untoward events. The mean 6MWD was 344 m (SD, 88 m). Independent general correlates of a shorter 6MWD in linear regression models in women and men included the following: older age, higher weight, larger waist, weaker grip strength, symptoms of depression, and decreased mental status. Independent disease or risk factor correlates of a shorter 6MWD included the following: a low ankle BP, use of angiotensin-converting enzyme inhibitors, and arthritis in men and women; higher C-reactive protein, diastolic hypertension, and lower FEV(1) in women; and the use of digitalis in men. Approximately 30% of the variance in 6MWD was explained by the linear regression models. Newly described bivariate associations of a shorter 6MWD included impaired activities of daily living; self-reported poor health; less education; nonwhite race; a history of coronary heart disease, transient ischemic attacks, stroke, or diabetes; and higher levels of C-reactive protein, fibrinogen, or WBC count. CONCLUSIONS: Most community-dwelling elderly persons can quickly and safely perform this functional status test in the outpatient clinic setting. The test may be used clinically to measure the impact of multiple comorbidities, including cardiovascular disease, lung disease, arthritis, diabetes, and cognitive dysfunction and depression, on exercise capacity and endurance in older adults. Expected values should be adjusted for the patient's age, gender, height, and weight.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Exercise Test; Female; Humans; Ischemic Attack, Transient; Linear Models; Male; Mass Screening; Sensitivity and Specificity; Stroke; United States; Walking

Beta2-adrenergic receptor polymorphisms and risk of incident cardiovascular events in the elderly. - Heckbert, Susan R; Hindorff, Lucia A; Edwards, Karen L; Psaty, Bruce M; Lumley, Thomas; Siscovick, David S; Tang, Zhonghua; Durda, J Peter; Kronmal, Richard A; Tracy, Russell P (Circulation, 2003)
BACKGROUND: Genetic polymorphisms at codons 16 and 27 of the beta2-adrenergic receptor have been associated with altered response to sympathetic stimulation. We examined these polymorphisms in relation to cardiovascular event risk in the Cardiovascular Health Study. METHODS AND RESULTS: A total of 808 black and 4441 white participants (mean age, 73 years) were genotyped for the Arg16Gly and Gln27Glu polymorphisms of the beta2-adrenergic receptor. There were 702 incident coronary events, 438 ischemic strokes, and 1136 combined cardiovascular events during 7 to 10 years of follow-up. Allele frequencies differed by race but not by age or hypertension status. Glu27 carriers had a lower risk of coronary events than Gln27 homozygotes (hazard ratio, 0.82; 95% CI, 0.70 to 0.95), and there was a suggestion of decreased risk among Gly16 carriers compared with Arg16 homozygotes (hazard ratio, 0.88; 95% CI, 0.72 to 1.07). There was no association of beta2-adrenergic receptor genotype with ischemic stroke or combined cardiovascular events. CONCLUSIONS: The Glu27 allele of the beta2-adrenergic receptor was associated with a lower risk of incident coronary events in this elderly population.
Keywords: African Continental Ancestry Group; Aged; Alleles; Brain Ischemia; Cardiovascular Diseases; Cohort Studies; Comorbidity; Coronary Disease; European Continental Ancestry Group; Follow-Up Studies; Gene Frequency; Humans; Incidence; Linkage Disequilibrium; Polymorphism, Genetic; Receptors, Adrenergic, beta-2; Risk Assessment; Stroke; United States

Diabetes and sleep disturbances: findings from the Sleep Heart Health Study. - Resnick, Helaine E; Redline, Susan; Shahar, Eyal; Gilpin, Adele; Newman, Anne; Walter, Robert; Ewy, Gordon A; Howard, Barbara V; Punjabi, Naresh M (Diabetes Care, 2003)
OBJECTIVE: To test the hypothesis that diabetes is independently associated with sleep-disordered breathing (SDB), and in particular that diabetes is associated with sleep abnormalities of a central, rather than obstructive, nature. RESEARCH DESIGN AND METHODS: Using baseline data from the Sleep Heart Health Study (SHHS), we related diabetes to 1). the respiratory disturbance index (RDI; number of apneas plus hypopneas per h of sleep); 2). obstructive apnea index (OAI; >or=3 apneas/h of sleep associated with obstruction of the upper airway); 3). percent of sleep time < 90% O(2) saturation; 4). central apnea index (CAI; >or=3 apneas [without respiratory effort]/h sleep); 5). occurrence of a periodic breathing (Cheyne Stokes) pattern; and 6) sleep stages. Initial analyses excluding persons with prevalent cardiovascular disease (CVD) were repeated including these participants. RESULTS: Of the 5874 participants included in this report, 692 (11.8%) reported diabetes or were taking oral hypoglycemic medications or insulin and 1002 had prevalent CVD. Among the 4872 persons without CVD, 470 (9.6%) had diabetes. Diabetic participants had worse CVD risk factor profiles than their nondiabetic counterparts, including higher BMI, waist and neck circumferences, triglycerides, higher prevalence of hypertension, and lower HDL cholesterol (P < 0.001, all). Descriptive analyses indicated differences between diabetic and nondiabetic participants in RDI, sleep stages, sleep time <90% O(2) saturation, CAI, and periodic breathing (P < 0.05, all). However, multivariable regression analyses that adjusted for age, sex, BMI, race, and neck circumference eliminated these differences for all sleep measures except percent time in rapid eye movement (REM) sleep (19.0% among diabetic vs. 20.1% among nondiabetic subjects, P < 0.001) and prevalence of periodic breathing (odds ratio [OR] for diabetic subjects versus nondiabetic subjects 1.80, 95% CI 1.02-3.15). Additionally, adjusted analyses showed diabetes was associated with nonstatistically significant elevations in the odds of an increased central breathing index (OR 1.42, 95% CI 0.80-2.55). Addition to the analysis of the 1002 persons with prevalent CVD (including 222 people with diabetes) did not materially change these results. CONCLUSIONS: These data suggest that diabetes is associated with periodic breathing, a respiratory abnormality associated with abnormalities in the central control of ventilation. Some sleep disturbances may result from diabetes through the deleterious effects of diabetes on central control of respiration. The high prevalence of SDB in diabetes, although largely explained by obesity and other confounders, suggests the presence of a potentially treatable risk factor for CVD in the diabetic population.
Keywords: Aged; Diabetes Mellitus; Female; Humans; Logistic Models; Male; Middle Aged; Multivariate Analysis; Prevalence; Risk Factors; Sleep Apnea Syndromes; Sleep Apnea, Obstructive

Imputation of missing longitudinal data: a comparison of methods. - Engels, Jean Mundahl; Diehr, Paula (J Clin Epidemiol, 2003)
BACKGROUND AND OBJECTIVES: Missing information is inevitable in longitudinal studies, and can result in biased estimates and a loss of power. One approach to this problem is to impute the missing data to yield a more complete data set. Our goal was to compare the performance of 14 methods of imputing missing data on depression, weight, cognitive functioning, and self-rated health in a longitudinal cohort of older adults. METHODS: We identified situations where a person had a known value following one or more missing values, and treated the known value as a "missing value." This "missing value" was imputed using each method and compared to the observed value. Methods were compared on the root mean square error, mean absolute deviation, bias, and relative variance of the estimates. RESULTS: Most imputation methods were biased toward estimating the "missing value" as too healthy, and most estimates had a variance that was too low. Imputed values based on a person's values before and after the "missing value" were superior to other methods, followed by imputations based on a person's values before the "missing value." Imputations that used no information specific to the person, such as using the sample mean, had the worst performance. CONCLUSIONS: We conclude that, in longitudinal studies where the overall trend is for worse health over time and where missing data can be assumed to be primarily related to worse health, missing data in a longitudinal sequence should be imputed from the available longitudinal data for that person.
Keywords: Aged; Analysis of Variance; Bias; Coronary Disease; Data Interpretation, Statistical; Depression; Female; Health Status; Humans; Longitudinal Studies; Male; Research Design; Risk Factors; Stroke; United States

Relationships between renovascular disease, blood pressure, and renal function in the elderly: a population-based study. - Edwards, Matthew S; Hansen, Kimberley J; Craven, Timothy E; Cherr, Gregory S; Bleyer, Anthony J; Burke, Gregory L; Dean, Richard H (Am J Kidney Dis, 2003)
BACKGROUND: The purpose of this study is to examine the associations between renovascular disease (RVD) and cross-sectional measures of blood pressure and renal function among participants in the Cardiovascular Health Study (CHS). METHODS: The CHS is a prospective cohort study of cardiovascular disease among elderly Americans. As part of an ancillary study, participants in the Forsyth County, NC, cohort of the CHS were invited to undergo renal duplex sonography (RDS) to define the presence or absence of RVD (defined as any focal peak systolic velocity > or = 1.8 milliseconds or the absence of a Doppler shifted signal from an imaged artery). Demographic, risk factor, blood pressure, and serum creatinine data were obtained at the time of RDS and from the annual CHS examination. RESULTS: Eight hundred thirty-four CHS participants (including 525 women [63%], 309 men [37%], 194 African Americans [23%], and 635 Caucasians [76%]) with a mean age of 77.2 +/- 4.9 years underwent successful RDS. RVD was present in 57 participants (6.8%). When examined according to the presence or absence of RVD, significant univariate differences were observed in the prevalence of clinical hypertension (72% versus 50%; P = 0.001), systolic blood pressure (145 versus 136 mm Hg; P = 0.001), and renal insufficiency (16% versus 8%; P = 0.041). Multivariate analyses showed significant and independent associations for the presence of RVD with increasing systolic blood pressure (P = 0.034), clinical hypertension (odds ratio, 2.68; 95% confidence interval, 1.44 to 4.99; P = 0.002), increasing serum creatinine level, and renal insufficiency (odds ratio, 2.21; 95% confidence interval, 1.02 to 4.79; P = 0.043). A significant interaction was observed between the presence of RVD and increasing systolic blood pressure in association with increasing serum creatinine levels (P = 0.041). CONCLUSION: These results suggest important population-based associations between RVD and cross-sectional measures of blood pressure and renal function. Furthermore, the observed relationship between RVD and increasing serum creatinine level was influenced strongly by increasing blood pressure.
Keywords: Aged; Blood Pressure; Female; Humans; Hypertension; Kidney; Kidney Diseases; Male; Prospective Studies; Ultrasonography, Doppler, Duplex; Vascular Diseases

"Successful aging": effect of subclinical cardiovascular disease. - Newman, Anne B; Arnold, Alice M; Naydeck, Barbara L; Fried, Linda P; Burke, Gregory L; Enright, Paul; Gottdiener, John; Hirsch, Calvin; O'Leary, Daniel; Tracy, Russell (Arch Intern Med, 2003)
BACKGROUND: Cardiovascular diseases are the primary cause of death in older adults. Among those without clinical disease, high levels of subclinical disease are associated with poor survival. The effect of the extent of subclinical cardiovascular disease on the quality of the remaining years has not been defined. METHODS: In a longitudinal cohort study, 2932 men and women aged 65 years and older were followed up for 8 years to determine the likelihood of maintaining intact health and functioning. Successful aging was defined as remaining free of cardiovascular disease, cancer, and chronic obstructive pulmonary disease and with intact physical and cognitive functioning. RESULTS: Younger age at study entry and a lower extent of subclinical cardiovascular disease were independently associated with the likelihood of maintaining successful aging. In age-stratified summaries, those with subclinical disease had a trajectory of decline similar to subjects 5 years older without subclinical vascular disease. Regression analyses showed that the decline associated with subclinical disease was equivalent to 6.5 (95% confidence interval, 6.4-6.6) years of aging for women and 5.6 (95% confidence interval, 5.4-5.8) years of aging for men. Individual measures of the extent of cardiovascular disease, diabetes mellitus, smoking, and higher C-reactive protein level were also independently predictive of fewer years of successful aging, but none of these factors substantially attenuated the effect of age itself. CONCLUSIONS: There is a graded relationship between the extent of vascular disease measured noninvasively and the likelihood of maintaining intact health and function. Prevention of subclinical vascular disease may increase the quality and the quantity of years in late life.
Keywords: Aged; Aged, 80 and over; Aging; C-Reactive Protein; Cardiovascular Diseases; Female; Health Status; Humans; Longitudinal Studies; Male; Quality of Life; Regression Analysis; Risk Factors

Associations between renovascular disease and prevalent cardiovascular disease in the elderly: a population-based study. - Edwards, Matthew S; Hansen, Kimberley J; Craven, Timothy E; Bleyer, Anthony J; Burke, Gregory L; Levy, Pavel J; Dean, Richard H (Vasc Endovascular Surg, 2004)
Atherosclerotic renovascular disease (RVD) is a suspected contributor to the morbidity and mortality of cardiovascular disease (CVD) through its potential effects on blood pressure and excretory renal function as well as through its associations with other forms of CVD. However, population-based data regarding the associations between the presence of RVD and prevalent CVD are lacking. The Cardiovascular Health Study (CHS) is a prospective, multicenter cohort study of CVD among elderly Americans. As part of an ancillary study, participants in the Forsyth County, North Carolina, cohort of the CHS were invited to undergo renal duplex sonography (RDS) to establish the presence or absence of RVD (defined as any focal peak systolic velocity >/= 1.8 m/second or the absence of a Doppler-shifted signal from an imaged artery). Demographic, risk factor, and prevalent CVD data were obtained from the CHS coordinating center and matched with ancillary study participants. Eight hundred thirty-four CHS participants (including 525 women [63%], 309 men [37%], 194 African-Americans [23%], and 635 Caucasians [76%]) with a mean age of 77.2 +/-4.9 years underwent RDS examination. RVD was present in 57 participants (6.8%). Overall, clinical and/or subclinical manifestations of CVD were present in 603 participants (72.3%) at the time of RDS. Participants with RVD demonstrated a significantly greater prevalence of angina (p = 0.002), previous myocardial infarction (p < 0.001), >/= 25% diameter-reducing internal carotid artery stenosis (p = 0.010), increased carotid intimal medial thickness (p = 0.003), and major electrocardiographic abnormalities (p = 0.013). Following adjustment for demographics and cardiovascular risk factors, the presence of RVD demonstrated a significant and independent association with prevalent coronary artery disease but not with prevalent cerebrovascular or lower extremity vascular disease. These results suggest important population-based associations between RVD and both clinical and subclinical manifestations of CVD, especially coronary artery disease.
Keywords: Aged; Arteriosclerosis; Cardiovascular Diseases; Cohort Studies; Humans; Hypertension, Renovascular; Longitudinal Studies; Male; Multivariate Analysis; Prevalence; Prospective Studies; Renal Artery Obstruction; Ultrasonography; United States

Deep vein thrombosis and pulmonary embolism in two cohorts: the longitudinal investigation of thromboembolism etiology. - Cushman, Mary; Tsai, Albert W; White, Richard H; Heckbert, Susan R; Rosamond, Wayne D; Enright, Paul; Folsom, Aaron R (Am J Med, 2004)
PURPOSE: To determine the incidence of deep vein thrombosis and pulmonary embolism in two cohorts representing regions of the United States. METHODS: The sample comprised 21,680 participants of the Atherosclerosis Risk in Communities study and the Cardiovascular Health Study. Subjects were aged >/=45 years, resided in six communities, and were followed for 7.6 years. All hospitalizations were identified and thromboses were validated by chart review. RESULTS: The age-standardized incidence of first-time venous thromboembolism was 1.92 per 1000 person-years. Rates were higher in men than women, and increased with age in both sexes. There was no antecedent trauma, surgery, immobilization, or diagnosis of cancer for 48% (175/366) of events. The 28-day case-fatality rate was 11% (29/265) after a first venous thromboembolism and 25% (17/67) for cancer-associated thrombosis. The recurrence rate 2 years after a first venous thromboembolism was 7.7% per year (95% confidence interval [CI]: 4.5% to 10.9% per year). Cancer was the only factor independently associated with 28-day fatality (relative risk [RR] = 5.2; 95% CI: 1.4 to 19.9) or recurrent thrombosis (RR = 9.2; 95% CI: 2.0 to 41.7). CONCLUSION: The incidence of venous thromboembolism in this cohort of middle- and older-aged subjects was similar to that observed in more geographically homogeneous samples. Half of cases were idiopathic. Short-term mortality and 2-year recurrence rates were appreciable, especially among subjects with cancer. Based on this study we estimate that 187,000 cases of first-time venous thromboembolism are diagnosed yearly in the United States among those aged 45 years or older.
Keywords: Aged; Case-Control Studies; Cohort Studies; Female; Follow-Up Studies; Humans; Incidence; Male; Middle Aged; Neoplasms; Population Surveillance; Pulmonary Embolism; Recurrence; Risk Factors; Survival Rate; Venous Thrombosis

Mesenteric artery disease in the elderly. - Hansen, Kimberley J; Wilson, David B; Craven, Timothy E; Pearce, Jeffrey D; English, William P; Edwards, Matthew S; Ayerdi, Juan; Burke, Gregory L (J Vasc Surg, 2004)
PURPOSE: The purpose of this study was to estimate the population-based prevalence of mesenteric artery stenosis (MAS) and occlusion among independent elderly Americans. METHOD: As part of an ancillary investigation to the Cardiovascular Health Study (CHS), participants in the Forsyth County, NC cohort had visceral duplex sonography of the celiac arteries and superior mesenteric arteries (SMAs). Critical MAS was defined by celiac peak systolic velocity >or=2.0 m/s and/or SMA peak systolic velocity >or=2.7 m/s. Occlusion of either vessel was defined by lack of a Doppler-shifted signal within the imaged artery. Demographic data, blood pressures, and blood lipid levels were collected as part of the baseline CHS examination. Participants' weights were measured at baseline and before the duplex exam. Univariate tests of association were performed with two-way contingency tables, Student t tests, and Fisher exact tests. Multivariate associations were examined with logistic regression analysis. RESULTS: A total of 553 CHS participants had visceral duplex sonography technically adequate to define the presence or absence of MAS. The study group had a mean age of 77.2 +/- 4.9 years and comprised 63% women and 37% men. Participant race was 76% white and 23% African-American. Ninety-seven participants (17.5%) had MAS. There was no significant difference in age, race, gender, body mass index, blood pressure, cholesterol, or low-density lipoproteins for participants with or without MAS. Forward stepwise variable selection found renal artery stenosis (P =.008; odds ratio [OR], 2.85; 95% confidence interval [CI], 1.31, 6.21) and high-density lipoprotein >40 (P =.02; OR, 3.03; 95% CI, 1.17, 7.81) significantly associated with MAS in a multivariate logistic regression model. Eighty-three of the 97 participants with MAS (15.0% of the cohort) had isolated celiac stenosis. Seven participants (1.3% of the cohort) had combined celiac and SMA stenosis. Five participants (0.9% of the cohort) had isolated SMA stenosis. Two participants (0.4% of the cohort) had celiac occlusion. Considering all participants with MAS, there was no association with weight change. However, SMA stenosis and celiac occlusion demonstrated an independent association with annualized weight loss (P =.028; OR, 1.54; 95% CI, 1.05, 2.26) and with renal artery stenosis (P =.001; OR, 9.48; 95% CI, 2.62, 34.47). CONCLUSION: This investigation provides the first population-based estimate of the prevalence of MAS among independent elderly Americans. MAS existed in 17.5% of the study cohort. The majority had isolated celiac disease. SMA stenosis and celiac artery occlusion demonstrated a significant and independent association with weight loss and concurrent renal artery disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Arteriosclerosis; Celiac Artery; Cohort Studies; Female; Humans; Male; Mesenteric Arteries; Mesenteric Artery, Superior; Mesenteric Vascular Occlusion; Prevalence; Ultrasonography, Doppler, Duplex; Weight Loss

Racial differences in endothelial function in postmenopausal women. - Loehr, Laura R; Espeland, Mark A; Sutton-Tyrrell, Kim; Burke, Gregory L; Crouse, John R; Herrington, David M (Am Heart J, 2004)
OBJECTIVE: Racial differences in cardiovascular mortality among women remain largely unexplained. Preliminary data suggest that African American and Caucasian differences in endothelial function may parallel differential cardiovascular disease (CVD) risk in women. To further study differences in endothelial function between African American and Caucasian women, we analyzed measures of brachial artery flow-mediated dilation (FMD) in women enrolled in the Cardiovascular Health Study (CHS). METHODS AND RESULTS: Brachial artery FMD was measured in the fasting state using established ultrasound techniques in 1330 Caucasian and 297 African American female participants in CHS (mean age 78.4 +/- 4.4 years). General linear models were used to compare FMD between African American and Caucasian women after adjusting for baseline brachial diameter, hypertension, diabetes, smoking, cholesterol, systolic blood pressure, body mass index, waist/hip ratio, age, education, income level; use of angiotensin-converting enzyme inhibitors, beta-blockers, nitroglycerin, estrogens and lipid-lowering drugs; and presence of clinical or subclinical disease. Adjusted absolute change and percent change in brachial artery diameter was significantly reduced in African American women compared with Caucasian women (P <.0001 and P =.0002, respectively). Similar results were found when the women were stratified by history of CVD (- CVD, P =.02; + CVD, P =.001) and CVD or subclinical vascular disease (- disease, P =.01, + disease, P =.03). CONCLUSIONS: In this cohort, brachial artery FMD was lower in African American women compared to Caucasian women, and this difference persisted after adjustment by multivariable analysis. The increased CVD risk in African American women may be related to impaired endothelial function. It remains to be determined whether African American women may uniquely benefit by interventions designed to improve endothelial health.
Keywords: African Continental Ancestry Group; Aged; Brachial Artery; Cohort Studies; Endothelium, Vascular; European Continental Ancestry Group; Female; Humans; Multivariate Analysis; Postmenopause; Risk Factors; Vasodilation

Respiratory muscle strength and the risk of incident cardiovascular events. - van der Palen, J; Rea, T D; Manolio, T A; Lumley, T; Newman, A B; Tracy, R P; Enright, P L; Psaty, B M (Thorax, 2004)
BACKGROUND: Maximal inspiratory pressure (MIP) is a measure of inspiratory muscle strength. The prognostic importance of MIP for cardiovascular events among elderly community dwelling individuals is unknown. Diminished forced vital capacity (FVC) is a risk factor for cardiovascular events which remains largely unexplained. METHODS: MIP was measured at the baseline examination of the Cardiovascular Health Study. Participants had to be free of prevalent congestive heart failure (CHF), myocardial infarction (MI), and stroke. RESULTS: Subjects in the lowest quintile of MIP had a 1.5-fold increased risk of MI (HR 1.48, 95% CI 1.07 to 2.06) and cardiovascular disease (CVD) death (HR 1.54, 95% CI 1.09 to 2.15) after adjustment for non-pulmonary function covariates. There was a potential inverse relationship with stroke (HR 1.36, 95% CI 0.97 to 1.90), but there was little evidence of an association between MIP and CHF (HR 1.22, 95% CI 0.93 to 1.60). The addition of FVC to models attenuated the HR associated with MIP only modestly; similarly, addition of MIP attenuated the HR associated with FVC only modestly. CONCLUSIONS: A reduced MIP is an independent risk factor for MI and CVD death, and a suggestion of an increased risk for stroke. This association with MIP appeared to be mediated through mechanisms other than inflammation.
Keywords: Cardiovascular Diseases; Female; Follow-Up Studies; Forced Expiratory Volume; Humans; Male; Maximal Voluntary Ventilation; Prospective Studies; Respiratory Muscles; Risk Factors; Vital Capacity

Stroke risk factors and loss of high cognitive function. - Elkins, J S; O'Meara, E S; Longstreth, W T; Carlson, M C; Manolio, T A; Johnston, S C (Neurology, 2004)
BACKGROUND: Modifiable stroke risk factors may contribute to age-associated declines in cognitive function. Individuals with high levels of cognitive function after midlife may have less exposure to these stroke risk factors or may be less susceptible to their effects on cognition. METHODS: The Cardiovascular Health Study (CHS)* is a population-based, longitudinal cohort study of 5,888 people age 65 years and older. Participants (n = 4,129) who were free of dementia, stroke, or TIA at the time of baseline cranial MRI were selected for analysis. High cognitive function at baseline was defined by performance at or above midlife norms on the Modified Mini-Mental State Examination (3MS). RESULTS: The odds of having high cognitive function at baseline decreased by quartile of stroke risk (highest vs lowest risk quartile, adjusted odds ratio [OR] 0.68; 95% CI 0.52 to 0.88; p for trend = 0.005). Stroke risk was a predictor of decline on the 3MS in those with typical levels of cognitive function at baseline, even in the absence of incident stroke or TIA (highest vs lowest risk quartile for 3MS decline, adjusted OR 2.11; 95% CI 1.42 to 3.13; p for trend < 0.001). In contrast, stroke risk was not associated with decline on the 3MS in those with high cognitive function at baseline (p = 0.03 for interaction). CONCLUSIONS: In a cohort of older adults without stroke, TIA, or dementia, cognitive function and incident cognitive decline were associated with risk for stroke. Additional studies are needed to determine whether modification of stroke risk factors can reduce the cognitive decline that is often attributed to normal aging.
Keywords: Aged; Aged, 80 and over; Aging; Cognition Disorders; Cohort Studies; Comorbidity; Female; Follow-Up Studies; Higher Nervous Activity; Humans; Incidence; Male; Risk Assessment; Risk Factors; Sampling Studies; Sensitivity and Specificity; Severity of Illness Index; Stroke; United States

Associations between retinal microvascular abnormalities and declining renal function in the elderly population: the Cardiovascular Health Study. - Edwards, Matthew S; Wilson, David B; Craven, Timothy E; Stafford, Jeanette; Fried, Linda F; Wong, Tien Y; Klein, Ronald; Burke, Gregory L; Hansen, Kimberley J (Am J Kidney Dis, 2005)
BACKGROUND: Microvascular abnormalities in the kidney are common histopathologic findings in individuals with chronic kidney disease or renal failure. These abnormalities may represent one manifestation of ongoing systemic microvascular damage. We hypothesized that retinal microvascular abnormalities, when present, would be associated with progressive renal dysfunction in elderly individuals. METHODS: The Cardiovascular Health Study (CHS) is a prospective, multicenter, cohort study initiated in 1989 designed to examine cardiovascular risk factors, morbidity, and mortality in elderly Americans. As part of an ancillary study, CHS participants underwent retinal photography in 1997 and 1998. Retinal microvascular abnormalities were assessed and graded by using standardized measures. Retinal microvascular abnormalities were defined as retinopathy (hard and soft exudates, hemorrhages, or microaneurysms) and/or retinal arteriolar abnormalities (arteriovenous nicking, focal arteriolar narrowing, or lowest quartile arteriole-venule ratio). Associations between these abnormalities and observed 4-year changes in serum creatinine levels and estimated glomerular filtration rates (eGFRs) from study years 5 to 9 (encompassing years 1994 to 2001) were examined by using regression modeling. RESULTS: A total of 1,394 CHS participants had retinal and serum creatinine data. After adjustments for age, race, sex, weight, diabetes, hypertension, angiotensin-converting enzyme inhibitor use, and proteinuria, participants with retinopathy showed a significant increase in serum creatinine level and decline in eGFR compared with those without retinopathy during the 4-year study period (+0.24 mg/dL [+21 micromol/L] versus -0.21 mg/dL [-19 micromol/L] and -0.48 mL/min/1.73 m2 [-0.01 mL/s/1.73 m2] versus +1.74 mL/min/1.73 m2 [+0.03 mL/s/1.73 m2], respectively). Participants with retinopathy also were significantly more likely to have an observed significant deterioration in renal function, defined as a 0.3-mg/dL (27-micromol/L) increase in serum creatinine level or 20% or greater decline in eGFR (odds ratio, 3.20; 95% confidence interval, 1.58 to 6.50; and odds ratio, 2.84; 95% confidence interval, 1.56 to 5.16, respectively). These associations remained in separate stratified analyses of patients with and without diabetes. The presence of retinal arteriolar abnormalities was not associated with deteriorating renal function. CONCLUSION: Retinal microvascular abnormalities defined as retinopathy were significantly associated with renal function deterioration. The observed findings were independent of effects of any associated diabetes or hypertension. These findings suggest that systemic microvascular disease may be associated with progressive renal dysfunction in the elderly population.
Keywords: African Americans; Aged; Aged, 80 and over; Aging; Antihypertensive Agents; Capillaries; Cohort Studies; Comorbidity; Creatinine; Diabetes Mellitus; Disease Progression; European Continental Ancestry Group; Female; Glomerular Filtration Rate; Humans; Hypertension; Kidney; Male; Photography; Prospective Studies; Proteinuria; Retina; Retinal Diseases; Retinal Vessels

Associations of sleep-disordered breathing and cerebral changes on MRI. - Robbins, John; Redline, Susan; Ervin, Ann; Walsleben, Joyce A; Ding, Jingzhong; Nieto, F Javier (J Clin Sleep Med, 2005)
STUDY OBJECTIVES: Population-based studies have demonstrated associations between sleep-disordered breathing (SDB), hypertension, and cardiovascular disease; few large-scale studies have examined associations of SDB with objective measures of cerebrovascular disease. This study tested the significance of associations of SDB with evidence of brain injury or ischemia determined by cerebral magnetic resonance imaging (MRI) studies. DESIGN: Cross-sectional and longitudinal analyses in a nested sample of Cardiovascular Health Study participants in the Sleep Heart Health Study. PARTICIPANTS: The 843 individuals (mean age 77, SD 4.3 years, 58% women) who had MRI studies as part of the Cardiovascular Health Study before and after polysomnography obtained as part of the Sleep Heart Health Study. MEASUREMENTS: A 12-channel polysomnogram was used to derive indexes of sleep-disordered breathing. Repeated MRI measurements provided indexes of infarct (presence and size) and white matter disease. Logistic regression analyses were used to model MRI changes of infarct-like lesions and white matter disease as a function of age, baseline white matter grade, and indexes of central and obstructive sleep-disordered breathing. RESULTS: Individuals who showed progression in white matter disease compared to those who did not were significantly more likely to show a Cheyne-Stokes respiration pattern and to have an increased number of central but not obstructive apneas. CONCLUSIONS: An association between change in white matter grade and measures of central sleep apnea was demonstrated that was consistent with a causal pathway in which central sleep apnea contributes to the progression of white matter disease; alternatively, central sleep apnea may be a marker of subclinical cerebrovascular or cardiovascular disease.
Keywords: Aged; Brain; Cerebral Infarction; Cerebrovascular Circulation; Female; Humans; Magnetic Resonance Imaging; Male; Polysomnography; Severity of Illness Index; Sleep Apnea Syndromes; Sleep Apnea, Obstructive

beta(2)-Adrenergic receptor polymorphisms and determinants of cardiovascular risk: the Cardiovascular Health Study. - Hindorff, Lucia A; Heckbert, Susan R; Psaty, Bruce M; Lumley, Thomas; Siscovick, David S; Herrington, David M; Edwards, Karen L; Tracy, Russell P (Am J Hypertens, 2005)
BACKGROUND: Common Arg16Gly and Gln27Glu polymorphisms of the beta(2)-adrenergic receptor (beta(2)AR) have been associated with hypertension and coronary disease. This analysis of older adults in the Cardiovascular Health Study examined whether these polymorphisms were associated with blood pressure (BP), subclinical atherosclerosis, and, among treated hypertensive individuals, differences in coronary disease risk according to antihypertensive drug class. METHODS: Altogether, 5249 participants (4441 white and 808 African American, median follow-up time 10.2 years) were genotyped for both polymorphisms. Ankle-arm index (AAI), carotid intima-media thickness (IMT), and brachial flow-mediated dilation were measured cross-sectionally. All estimates were adjusted for ethnicity. RESULTS: Relative to Gln27 homozygotes, carrying the Glu27 allele was not associated with new-onset hypertension (hazard ratio [HR] = 1.01, 95% confidence interval [CI] = 0.87 to 1.16), BP control (odds ratio [OR] = 0.97, 95% CI = 0.89 to 1.06), AAI (mean difference 0.0042 +/- 0.0052), carotid IMT (mean difference 0.0044 +/- 0.02 mm), or brachial flow-mediated dilation (mean difference in baseline diameter -0.028 +/- 0.036 mm; the most marked of three measures). Among treated hypertensive individuals, coronary disease risk was similar in Glu27 carriers relative to Gln27 homozygotes in subgroups defined by use of beta-blockers (HR = 1.09, 95% CI = 0.64 to 1.87) or other antihypertensive medications (HR = 1.00, 95% CI = 0.78 to 1.28). Results were similar for the Arg16Gly polymorphism. CONCLUSIONS: The association of beta(2)AR genotype with coronary disease previously reported in this older adult population is not likely to be explained by BP levels, subclinical atherosclerosis, or antihypertensive treatment. Other measures of vascular response, gene-gene or gene-environment interactions, or characteristics developing earlier in life may mediate the association between beta(2)AR genotype and coronary disease and merit further research.
Keywords: African Americans; Antihypertensive Agents; Arteriosclerosis; Coronary Artery Disease; European Continental Ancestry Group; Female; Genotype; Homozygote; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Genetic; Receptors, Adrenergic, beta-2; Risk Factors

Factors associated with incidence and persistence of symptoms of disturbed sleep in an elderly cohort: the Cardiovascular Health Study. - Quan, Stuart F; Katz, Ronit; Olson, Jean; Bonekat, William; Enright, Paul L; Young, Terry; Newman, Anne (Am J Med Sci, 2005)
BACKGROUND: There are limited data pertaining to the factors influencing the incidence and persistence of sleep symptoms in the elderly. The purpose of this study was to determine the incidence and nonremission rates of the following sleep symptoms: trouble falling asleep (TFA), frequent awakenings (FA), and excessive daytime sleepiness (EDS) in the Cardiovascular Health Study (CHS), a prospective multicenter study of cardiovascular disease in a large cohort of elderly adults. Factors influencing these rates were assessed as well. METHODS: 4467 participants in CHS were surveyed for the presence of TFA, FA, and EDS as well as other health problems at their baseline examination and at a follow-up examination 1 to 4 years later. RESULTS: Annualized incidence and nonremission rates were the following: TFA (2.8% and 15.4%), FA (12.3% and 22.7%), and EDS (4.4% and 13.4%). Women were more likely to have incident and persistent TFA. Depression was the primary factor predicting the incidence of all three sleep symptoms. However, other health conditions, including respiratory symptoms and cardiovascular disease, and limitation in activities of daily living were important as well. Depression also was the most important factor associated with persistence of these sleep symptoms. The role of other health conditions in determining nonremission was much more limited. CONCLUSIONS: Incidence of sleep disturbances in the elderly is related to depression, health conditions, and physical functioning. However, persistence of sleep disturbances is best predicted by the presence of depression.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Depression; Female; Health Status; Humans; Incidence; Logistic Models; Male; Odds Ratio; Prevalence; Risk Factors; Sex Factors; Sleep Initiation and Maintenance Disorders; Surveys and Questionnaires

Predictors of heartburn during sleep in a large prospective cohort study. - Fass, Ronnie; Quan, Stuart F; O'Connor, George T; Ervin, Ann; Iber, Conrad (Chest, 2005)
BACKGROUND AND AIMS: Nocturnal gastroesophageal reflux, which may result in nocturnal heartburn, has been demonstrated to be associated with a more severe form of gastroesophageal reflux disease (GERD). The aim of this study was to determine the clinical predictors of heartburn during sleep in a large prospective cohort study. METHODS: Study subjects were members of the parent cohorts from which the Sleep Heart Health Study (SHHS) recruited participants. SHHS is a multicenter, longitudinal, cohort study of the cardiovascular consequences of sleep-disordered breathing. As part of the recruitment process, parent cohort members completed a questionnaire that permitted an assessment of the relationships between heartburn during sleep, and patient demographics, sleep abnormalities, medical history, and social habits in nine community-based parent cohorts across the United States. All variables, significant at the p < 0.05 level, were included as independent variables in multivariate logistic regression models with heartburn during sleep status included as the dependent variable RESULTS: A total of 15,314 subjects completed the questions about heartburn during sleep, and of these, 3,806 subjects (24.9%) reported having this symptom. In four increasingly comprehensive multivariate models, increased body mass index (BMI), carbonated soft drink consumption, snoring and daytime sleepiness (Epworth sleepiness scale score), insomnia, hypertension, asthma, and usage of benzodiazepines were strong predictors of heartburn during sleep. In contrast, college education decreased the risk of reporting heartburn during sleep. CONCLUSIONS: Heartburn during sleep is very common in the general population. Reports of this type of symptom of GERD are strongly associated with increased BMI, carbonated soft drink consumption, snoring and daytime sleepiness, insomnia, hypertension, asthma, and usage of benzodiazepines. Overall, heartburn during sleep may be associated with sleep complaints and excessive daytime sleepiness.
Keywords: Aged; Body Mass Index; Carbonated Beverages; Cohort Studies; Educational Status; Female; Gastroesophageal Reflux; Heartburn; Humans; Male; Middle Aged; Multivariate Analysis; Prospective Studies; Sleep; Surveys and Questionnaires

Renal duplex parameters, blood pressure, and renal function in elderly people. - Pearce, Jeffrey D; Edwards, Matthew S; Craven, Timothy E; English, William P; Mondi, Matthew M; Reavis, Scott W; Hansen, Kimberley J (Am J Kidney Dis, 2005)
BACKGROUND: Changes in renal artery and renal parenchyma perfusion are believed to correlate with severity of hypertension and worsened renal function, but population-based studies of these associations are not available. This study examines relationships between parameters derived from renal duplex sonography (RDS), blood pressure (BP), and excretory renal function in a population-based cohort of elderly Americans. METHODS: Through an ancillary study to the Cardiovascular Health Study, 758 participants (37% men; mean age, 77 years) underwent RDS in which flow velocities and frequency shifts were determined from spectral analysis of Doppler-shifted signals obtained from the renal artery and parenchyma. Associations of these duplex parameters with BP and inverse serum creatinine were examined by using multivariate regression techniques. RESULTS: Main renal artery peak systolic flow velocity (PSV) showed independent associations with BP, with an SD increase in PSV (0.53 m/s) associated with a 3.3-mm Hg increase in systolic BP (SBP) and a 2.4-mm Hg decrease in diastolic BP (DBP). An SD decrease in end-diastolic frequency shift (EDF; 131 kHz) was associated with a 6.0-mm Hg increase in SBP, a 4.2-mm Hg decrease in DBP, and a significant 3.7% decrease in inverse serum creatinine. CONCLUSION: Increases in renal artery PSV and decreases in parenchymal EDF are associated with increased SBP and decreased DBP. Moreover, decreased parenchymal EDF showed significant associations with impaired excretory renal function. These results suggest that renal duplex parameters are associated with renal parenchymal changes caused by hypertension and progressive renal dysfunction in elderly people.
Keywords: African Americans; Aged; Aging; Arteriosclerosis; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Creatinine; Cross-Sectional Studies; Diastole; Disease Progression; European Continental Ancestry Group; Female; Humans; Hypertension, Renovascular; Kidney; Kidney Diseases; Kidney Function Tests; Male; Renal Artery; Renal Artery Obstruction; Renal Circulation; Risk Factors; Sampling Studies; Systole; Ultrasonography, Doppler, Duplex; United States

Renovascular disease and the risk of adverse coronary events in the elderly: a prospective, population-based study. - Edwards, Matthew S; Craven, Timothy E; Burke, Gregory L; Dean, Richard H; Hansen, Kimberley J (Arch Intern Med, 2005)
BACKGROUND: Renovascular disease is a cause of secondary hypertension and renal insufficiency and is suspected to contribute to morbidity and mortality of coronary heart disease. This investigation prospectively examined associations between renovascular disease and adverse coronary events among a population-based sample of elderly Americans. METHODS: The Cardiovascular Health Study is a prospective, multicenter cohort study of cardiovascular disease risk factors, morbidity, and mortality among Americans older than 65 years. Renal duplex sonography was performed on 870 individuals between January 1995 and February 1997. Renovascular disease was defined as any focal peak systolic velocity of 1.8 m/s or greater (renal artery stenosis) or the absence of a Doppler-shifted signal from an imaged artery (renal artery occlusion). Adverse coronary events were defined as hospitalized angina, fatal or nonfatal myocardial infarction, and coronary revascularization. RESULTS: During a mean follow-up of 14 months, 68 participants experienced incident or recurrent adverse coronary events. The presence of renovascular disease demonstrated a significant relationship with adverse coronary events (hazard ratio, 1.96; 95% confidence interval, 1.00-3.83; P = .05) that remained after controlling for the effects of coexisting atherosclerotic risk factors and prevalent cardiovascular disease. The relationship between renovascular disease and adverse coronary events was not dependent on the effects of increased blood pressure. CONCLUSIONS: The presence of renovascular disease was associated with an increase in the risk of adverse coronary events in this sample. The increment in risk was not dependent on the effects of associated atherosclerotic risk factors, other prevalent cardiovascular disease, or increased blood pressure.
Keywords: Age Distribution; Aged; Aged, 80 and over; Analysis of Variance; Cohort Studies; Comorbidity; Coronary Disease; Female; Geriatric Assessment; Heart Function Tests; Humans; Hypertension, Renovascular; Incidence; Kidney Function Tests; Male; Multivariate Analysis; Probability; Prognosis; Prospective Studies; Risk Assessment; Severity of Illness Index; Sex Distribution; Survival Rate; Ultrasonography, Doppler; United States

Risk factors for declining ankle-brachial index in men and women 65 years or older: the Cardiovascular Health Study. - Kennedy, Margaret; Solomon, Cam; Manolio, Teri A; Criqui, Michael H; Newman, Anne B; Polak, Joseph F; Burke, Gregory L; Enright, Paul; Cushman, Mary (Arch Intern Med, 2005)
BACKGROUND: An ankle-brachial index (ABI) of less than 0.9 is a noninvasive measure of lower extremity arterial disease and a predictor of cardiovascular events. Little information is available on longitudinal change in ABI or on risk factors for declining ABI in a community-based population. METHODS: To assess risk factors for ABI decline, we studied 5888 participants in the Cardiovascular Health Study cohort (men and women 65 years or older). We measured ABI in 1992-1993 and again in 1998-1999. At baseline, we excluded individuals with an ABI less than 0.9, ABI greater than 1.4, or confirmed symptomatic lower extremity arterial disease (n = 823). The group with ABI decline included 218 participants with decline greater than 0.15 and to 0.9 or less. The comparison group comprised the remaining 2071 participants with follow-up ABI. RESULTS: The percentage of participants with ABI decline was 9.5% over 6 years of follow-up. The mean +/- SD decline was 0.33 +/- 0.12 in cases of ABI decline and 0.02 +/- 0.13 in non-cases. Independent predictors of ABI decline, reported as odds ratios, were age, 1.96 (95% confidence interval [CI], 1.42-2.71) for 75 to 84 years and 3.79 (95% CI, 1.36-10.5) for those older than 85 years compared with those younger than 75 years; current cigarette use, 1.74 (95% CI, 1.02-2.96); hypertension, 1.64 (95% CI, 1.18-2.28); diabetes, 1.77 (95% CI, 1.14-2.76); higher low-density lipoprotein cholesterol level, 1.60 (95% CI, 1.03-2.51), and lipid-lowering drug use 1.74 (95% CI, 1.05-2.89). CONCLUSION: Worsening lower extremity arterial disease, assessed as ABI decline, occurred in 9.5% of this elderly cohort over 6 years and was associated with modifiable vascular disease risk factors.
Keywords: Aged; Aged, 80 and over; Ankle; Brachial Artery; Cardiovascular Diseases; Female; Humans; Male; Peripheral Vascular Diseases; Risk Assessment; Risk Factors

Vascular events, mortality, and preventive therapy following ischemic stroke in the elderly. - Kaplan, R C; Tirschwell, D L; Longstreth, W T; Manolio, T A; Heckbert, S R; Lefkowitz, D; El-Saed, A; Psaty, B M (Neurology, 2005)
BACKGROUND: The authors studied mortality, vascular events, and preventive therapies following ischemic stroke among adults aged > or =65 years. METHODS: The authors identified 546 subjects with first ischemic stroke during 1989 to 2001 among Cardiovascular Health Study participants. Deaths, recurrent strokes, and coronary heart disease (CHD) events were identified over 3.2 years (median) follow-up. RESULTS: During the first year of follow-up, rates were 105.4/1,000 for recurrent stroke and 59.3/1,000 for CHD. After the first year, the stroke rate was 52.0/1,000 and the CHD rate was 46.5/1,000. Cardioembolic strokes had the highest mortality (185.4/1,000) and recurrence rates (86.6/1,000). Lacunar strokes had the lowest mortality (119.3/1,000) and recurrence rates (43.0/1,000). Age and male sex predicted death and CHD, but not recurrence. Outcomes did not differ by race. Following stroke, 47.8% used aspirin and 13.5% used other antiplatelet agents; 52.6% of patients with atrial fibrillation used warfarin; 31.3% of hyperlipidemic subjects, 57.0% of diabetic patients, and 81.5% of hypertensive patients were drug-treated; and 40.0% of hypertensive patients had blood pressure (BP) <140/90 mm Hg. Older subjects were less likely to use lipid-lowering therapy, women were less likely to have BP <140/90 mm Hg, and low-income subjects were less likely to use diabetes medications. CONCLUSIONS: Recurrent strokes were nearly twice as frequent as coronary heart disease (CHD) events during the first year after initial stroke, but stroke and CHD rates were similar after the first year. Preventive drug therapies were underused, which may reflect clinical uncertainty due to the lack of clinical trials among the elderly. Utilization was lower among the oldest patients, women, and low-income individuals.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Anticoagulants; Antihypertensive Agents; Brain Ischemia; Cohort Studies; Comorbidity; Coronary Artery Disease; Drug Utilization; Female; Humans; Hyperlipidemias; Hypertension; Hypolipidemic Agents; Male; Mortality; Prospective Studies; Recurrence; Sex Factors; Stroke; Treatment Outcome

Blood pressure level and outcomes in adults aged 65 and older with prior ischemic stroke. - Kaplan, Robert C; Tirschwell, David L; Longstreth, W T; Manolio, Teri A; Heckbert, Susan R; LeValley, Aaron J; Lefkowitz, David; El-Saed, Aiman; Psaty, Bruce M (J Am Geriatr Soc, 2006)
OBJECTIVES: To examine the association between blood pressure (BP) levels and long-term stroke outcomes in elderly stroke survivors. DESIGN: Observational study. SETTING: The Cardiovascular Health Study (CHS) of 5,888 community-dwelling adults. PARTICIPANTS: Two hundred fifty-four adults aged 65 and older (mean age 78.6) who sustained a nonfatal first ischemic stroke. MEASUREMENTS: BP levels assessed at prestroke and poststroke CHS visits were examined as predictors of stroke recurrence, coronary heart disease (CHD), combined vascular events (CVEs), and mortality. RESULTS: Higher poststroke BP level, assessed 261.6 days (mean) after stroke, was associated with higher risk of stroke recurrence over 5.4 years (mean) of follow-up. The multivariate-adjusted hazard ratio for stroke recurrence was 1.42 (95% confidence interval (CI) = 1.03-1.99) per standard deviation (SD) of systolic BP (P = .04) and 1.39 (95% CI = 1.01-1.91) per SD of diastolic BP (P = .04). Mortality was significantly greater in patients with low or high poststroke BP than in those with intermediate BP. Poststroke BP was not associated with risk of CHD or CVE, although further analyses suggested that high systolic BP predicted CHD and CVE in younger but not older subjects. Prestroke BP did not predict poststroke outcomes. CONCLUSION: In this observational study of adults aged 65 and older assessed approximately 8 months after stroke, low BP was associated with favorable risk of recurrent stroke, although high and low poststroke BP levels were associated with greater mortality. Long-term antihypertensive trials in older stroke survivors would increase knowledge about the benefits of lowering BP in this population.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Brain Ischemia; Female; Follow-Up Studies; Humans; Male; Outcome Assessment, Health Care; Prospective Studies; Recurrence; Stroke; Survival Rate

Clinical course of mesenteric artery stenosis in elderly americans. - Wilson, David B; Mostafavi, Kian; Craven, Timothy E; Ayerdi, Juan; Edwards, Matthew S; Hansen, Kimberley J (Arch Intern Med, 2006)
BACKGROUND: To examine prospectively the relationship between stenosis or occlusion of the celiac and superior mesenteric arteries and symptoms of chronic intestinal ischemia in free-living elderly patients in the United States. METHODS: As part of an ancillary study to the Cardiovascular Health Study, participants in the Forsyth County (North Carolina) cohort underwent visceral duplex ultrasonography of the celiac and superior mesenteric arteries. Critical mesenteric artery stenosis (MAS) or occlusion was defined by Doppler flow ultrasound-derived criteria. Clinical outcomes were assessed at annual follow-up examinations and review of death certificates. Multivariate associations between the presence of MAS and all-cause mortality and adverse cardiovascular events were analyzed. Participants with MAS were contacted to determine the presence of symptoms consistent with chronic intestinal ischemia. RESULTS: Of 553 participants who underwent visceral duplex ultrasonography, 97 (17.5%) had disease of the celiac or superior mesenteric artery. At a mean follow-up of 6(1/2) years, 20 participants with MAS (20.6%) and 93 without MAS (20.4%) had died (relative risk, 1.01; 95% confidence interval, 0.66-1.55). No deaths were attributed to intestinal infarction. No association existed between the presence of MAS and prevalent cardiovascular disease, all-cause mortality, or adverse cardiovascular events. A questionnaire was completed by 71% of the surviving participants with MAS. No participant reported symptoms or weight loss consistent with chronic intestinal ischemia. CONCLUSIONS: Mesenteric artery stenosis was a common finding in free-living elderly patients. At long-term follow-up, the presence of asymptomatic MAS was not associated with death or adverse cardiovascular events. Participants with asymptomatic MAS by duplex ultrasonographic criteria did not experience intestinal infarction or develop chronic intestinal ischemia.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Comorbidity; Female; Humans; Male; Mesenteric Arteries; Mesenteric Vascular Occlusion; Proportional Hazards Models; Prospective Studies; Radiography; Risk Factors; Surveys and Questionnaires; Ultrasonography

Education and the cognitive decline associated with MRI-defined brain infarct. - Elkins, J S; Longstreth, W T; Manolio, T A; Newman, A B; Bhadelia, R A; Johnston, S C (Neurology, 2006)
OBJECTIVE: To assess whether educational attainment, a correlate of cognitive reserve, predicts the amount of cognitive decline associated with a new brain infarct. METHODS: The Cardiovascular Health Study is a population-based, longitudinal study of people aged 65 years and older. Cognitive function was measured annually using the Modified Mini-Mental State Examination (3MS) and the Digit-Symbol Substitution Test (DSST). The authors tested whether education level modified 1) the cross-sectional association between cognitive performance and MRI-defined infarct and 2) the change in cognitive function associated with an incident infarct at a follow-up MRI. RESULTS: In cross-sectional analysis (n = 3,660), MRI-defined infarct was associated with a greater impact on 3MS performance in the lowest education quartile when compared with others (p for heterogeneity = 0.012). Among those with a follow-up MRI who had no infarct on initial MRI (n = 1,433), education level was not associated with the incidence, size, or location of new brain infarct. However, a new MRI-defined infarct predicted substantially greater decline in 3MS scores in the lowest education group compared with the others (6.3, 95% CI 4.4- to 8.2-point decline vs 1.7, 95% CI 0.7- to 2.7-point decline; p for heterogeneity < 0.001). Higher education was not associated with smaller declines in DSST performance in the setting of MRI-defined infarct. CONCLUSIONS: Education seems to modify an individual's decline on a test of general cognitive function when there is incident brain infarct. These findings are consistent with the hypothesis that cognitive reserve influences the impact of vascular injury in the brain.
Keywords: Cerebral Infarction; Cognition Disorders; Cross-Sectional Studies; Educational Status; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Neuropsychological Tests

Factors associated with geographic variations in stroke incidence among older populations in four US communities. - El-Saed, Aiman; Kuller, Lewis H; Newman, Anne B; Lopez, Oscar; Costantino, Joseph; McTigue, Kathleen; Cushman, Mary; Kronmal, Richard (Stroke, 2006)
BACKGROUND AND PURPOSE: In the Cardiovascular Health Study (CHS), we previously observed lower stroke incidence in Allegheny County, PA compared with the other 3 study sites. The purpose of this study was to study possible reasons for the lower stroke incidence in Allegheny County. METHODS: CHS participants 65 years or older who were stroke-free at baseline (n=5639) were followed between 1989 to 1990 and 2000 for the development of stroke. Risk factors at baseline and their subsequent control were compared among both groups. Site-specific hazard ratios for stroke incidence were calculated using Cox regression models. RESULTS: The unadjusted hazard ratio for total stroke incidence in Forsyth County, NC; Sacramento County, CA; and Washington County, MD combined compared with Allegheny County, PA was 1.74 (95% CI: 1.42, 2.14). After adjustment for age and other traditional risk factors, there was modest reduction of the excess hazard in non-Allegheny sites compared with Allegheny County (hazard ratio=1.52, 95% CI: 1.17, 1.98). Between baseline and the seventh-year visits, control of hypertension, diabetes, lipids, smoking, atrial fibrillation and transient ischemic attack were similar across sites. White matter grade > or = 3 on the baseline brain MRI was less common in Allegheny County (25.8% versus 36.3%, respectively; P<0.001) and accounted for 25% of the excess hazard in non-Allegheny sites compared with Allegheny County. CONCLUSIONS: Site differences in stroke risk factors at baseline and subsequent control only partially explain site differences in stroke incidence. White matter grade as a possible integrated measure of exposure and control of risk factors may help in explaining geographic variations in stroke incidence.
Keywords: Aged; Brain; California; Female; Humans; Incidence; Magnetic Resonance Imaging; Male; Maryland; North Carolina; Pennsylvania; Proportional Hazards Models; Risk Assessment; Risk Factors; Stroke

Genetic Susceptibility to Prostate Cancer: Prostate-specific Antigen and its Interaction with the Androgen Receptor (United States). - Sieh, Weiva; Edwards, Karen L; Fitzpatrick, Annette L; Srinouanprachanh, Sengkeo L; Farin, Fred M; Monks, Stephanie A; Kronmal, Richard A; Eaton, David L (Cancer Causes Control, 2006)
OBJECTIVE: To determine whether directly observed prostate-specific antigen (PSA) promoter diploid haplotype, either alone or in conjunction with androgen receptor (AR) genotype, is associated with prostate cancer risk. METHODS: We conducted a case-control study nested within the US population-based Cardiovascular Health Study cohort. Incident prostate cancers were identified by linkage to cancer registry records for the years 1989-2000. We genotyped 193 cases and 391 controls for the PSA -252 G/A and -158 G/A SNPs and the AR CAG microsatellite, and developed methods to directly determine proximal PSA promoter haplotypes. Exact logistic regression was used to estimate odds ratios and significance levels. RESULTS: No significant associations were observed between PSA diplotype and prostate cancer overall. Short (< 20) AR CAG repeat lengths were associated with modest increases in the risk of prostate cancer (OR, 1.46; 95% CI, 0.97-2.19; p = 0.071) that were significant for advanced disease (OR, 1.82; 95% CI, 1.02-3.26; p = 0.044). Men who possessed two copies of the PSA*2 (-252G/-158G) haplotype and short AR CAG repeat lengths had a 4-fold (95% CI, 1.05-20.75; exact p = 0.040) increased risk of prostate cancer, and a 7-fold (95% CI, 1.25-39.78; exact p = 0.026) increased risk of advanced disease. CONCLUSIONS: We found evidence that the PSA*2*2 diplotype in combination with short AR CAG alleles increases a man's risk of developing prostate cancer. These findings support an etiologic role in prostate cancer of genetic interactions between polymorphisms that increase AR transactivation strength and those that alter the regulatory regions of target genes such as PSA that are responsive to androgen stimulation.
Keywords: Aged; Biomarkers, Tumor; Case-Control Studies; Cohort Studies; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Male; Polymorphism, Genetic; Prostate-Specific Antigen; Prostatic Neoplasms; Receptors, Androgen; United States

Geographic variations in stroke incidence and mortality among older populations in four US communities. - El-Saed, Aiman; Kuller, Lewis H; Newman, Anne B; Lopez, Oscar; Costantino, Joseph; McTigue, Kathleen; Cushman, Mary; Kronmal, Richard (Stroke, 2006)
BACKGROUND AND PURPOSE: Stroke is a leading cause of death and disability in the US. There is limited data on geographic variations in stroke incidence among older US populations who experience the majority of stroke burden. The purpose of this study was to compare stroke incidence and mortality rates in 4 US communities. METHODS: Participants in the Cardiovascular Health Study (CHS) who had no history of stroke at baseline (n=5639) were followed for 10 or 7 years in predominantly white (n=5002) and black (n=637) participants, respectively. Incident stroke was validated by a stroke adjudication committee after ascertainment at annual visits, interim telephone contacts, and review of Medicare hospitalization data. RESULTS: The 2000 US population age and sex standardized total stroke incidence rate for all CHS participants was 17.7 per 1000 person-years (95% CI: 15.9, 19.5). The rate was significantly lower in Allegheny County, Pennsylvania 9.6/1000 person-years (95% CI: 7.7, 11.5) than Forsyth County, North Carolina 19.2/1000 person-years (95% CI: 15.6, 22.8), Sacramento County, California 20.7/1000 person-years (95% CI: 16.9, 24.5), and Washington County, Maryland 19.8/1000 person-years (95% CI: 16.1, 23.5). The lower stroke incidence rate in Allegheny County was consistent in gender, race, and age groups. Though not statistically significant, stroke mortality was also lower in Allegheny County than other 3 sites. The 1-month case fatality rate was similar in the 4 sites for all strokes, and by stroke types. CONCLUSIONS: Understanding geographic variations in stroke incidence may be an important step in improving preventive practices of stroke.
Keywords: Aged; Aged, 80 and over; California; Female; Humans; Incidence; Male; Maryland; North Carolina; Pennsylvania; Stroke

Lipoprotein subclass and particle size differences in Afro-Caribbeans, African Americans, and white Americans: associations with hepatic lipase gene variation. - Miljkovic-Gacic, Iva; Bunker, Clareann H; Ferrell, Robert E; Kammerer, Candace M; Evans, Rhobert W; Patrick, Alan L; Kuller, Lewis H (Metabolism, 2006)
Despite a higher prevalence of coronary heart disease risk factors, men of African origin have less coronary atherosclerosis, as measured by coronary calcification, than whites. In part, this is thought to be because of the less atherogenic lipoprotein profile observed in men of African origin, characterized by lower triglycerides and higher high-density lipoprotein (HDL) cholesterol. We hypothesized that the -514C>T polymorphism in the hepatic lipase gene (LIPC) plays a significant role in determining a less atherogenic lipoprotein profile observed in men of African origin. Previously conducted studies of the LIPC -514C>T polymorphism in African Americans may have been confounded by a higher level of European admixture; in addition, the results from these studies do not necessarily apply to other African populations because gene-environment interactions may differ. Thus, we compared nuclear magnetic resonance spectroscopy-measured lipoprotein subclass patterns and LIPC -514C>T genotypes in population-based samples of older white American (n = 532) and African American (n = 97) men from the Cardiovascular Health Study to those among older, less admixed, Afro-Caribbean men (n = 205) from the Tobago Health Study. Men of African origin had a more favorable lipoprotein profile than whites. In addition, levels of low-density lipoprotein cholesterol, total cholesterol, and triglyceride, and large and small very low-density lipoprotein, small low-density lipoprotein, as well as very low-density lipoprotein particle size, were remarkably lower in Afro-Caribbean men than in either African American or white men. The frequency of the LIPC -514T allele was much higher in Afro-Caribbeans (0.57) and in African Americans (0.49) than in whites (0.20). The -514T allele in both populations of African origin, but not in whites, was associated with elevated large HDL and greater HDL size. Our findings indicate that the higher frequency of the LIPC -514T allele found in men of African origin living in different environments significantly contributes to the more favorable distribution of HDL subclasses compared with whites.
Keywords: Adult; African Americans; Age Factors; Aged; Alleles; Body Mass Index; Cardiovascular Diseases; Caribbean Region; Cohort Studies; DNA; European Continental Ancestry Group; Gene Frequency; Genetic Variation; Humans; Lipase; Lipoproteins; Lipoproteins, HDL; Lipoproteins, LDL; Liver; Longitudinal Studies; Male; Middle Aged; Particle Size; Trinidad and Tobago; United States

New-onset diabetes and risk of all-cause and cardiovascular mortality: the Cardiovascular Health Study. - Smith, Nicholas L; Barzilay, Joshua I; Kronmal, Richard; Lumley, Thomas; Enquobahrie, Daniel; Psaty, Bruce M (Diabetes Care, 2006)
OBJECTIVE: Cardiovascular risk associated with new-onset diabetes is not well characterized. We hypothesized that risk of all-cause and cardiovascular mortality would be similar among participants with and without new-onset diabetes in the first years of follow-up and rise over time for new-onset diabetes. RESEARCH DESIGN AND METHODS: The Cardiovascular Health Study (CHS) is a longitudinal study of cardiovascular risk factors in adults aged > or =65 years. We used CHS participants to define a cohort (n = 282) with new-onset diabetes during 11 years of follow-up. New-onset diabetes was defined by initiation of antidiabetes medication or by fasting plasma glucose >125 mg/dl among CHS participants without diabetes at study entry. Three CHS participants without diabetes were matched for age, sex, and race to each participant with new-onset diabetes at the time of diabetes identification (n = 837). Survival analysis provided adjusted hazard ratios (HRs) for all-cause and cardiovascular mortality. RESULTS: During a median of 5.9 years of follow-up, there were 352 deaths, of which 41% were cardiovascular. In adjusted analyses, new-onset diabetes was associated with an HR of 1.9 (95% CI 1.4-2.5) for all-cause and 2.2 (1.4-3.4) for cardiovascular mortality compared with no diabetes. Mortality risks were elevated within 2 years of onset, especially cardiovascular risk (4.3 [95% CI 1.7-10.8]), and did not increase over time. CONCLUSIONS: Our findings indicate that there may be a mortality differential soon after diabetes onset in older adults and suggest that long-term macrovascular damage from atherosclerosis may not be primarily responsible for increased risk.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Blood Glucose; Cardiovascular Diseases; Diabetes Complications; Diabetes Mellitus; Follow-Up Studies; Humans; Kaplan-Meier Estimate; Risk Factors; Survival Rate; Time Factors

Progression of atherosclerotic renovascular disease: A prospective population-based study. - Pearce, Jeffrey D; Craven, Brandon L; Craven, Timothy E; Piercy, K Todd; Stafford, Jeanette M; Edwards, Matthew S; Hansen, Kimberley J (J Vasc Surg, 2006)
OBJECTIVE: Previous reports from select hypertensive patients suggest that atherosclerotic renovascular disease (RVD) is rapidly progressive and associated with a decline in kidney size and kidney function. This prospective, population-based study estimates the incidence of new RVD and progression of established RVD among elderly, free-living participants in the Cardiovascular Health Study (CHS). METHOD: The CHS is a multicenter, longitudinal cohort study of cardiovascular risk factors, morbidity, and mortality among men and women aged >65 years old. From 1995 through 1996, 834 participants underwent renal duplex sonography (RDS) to define the presence or absence of significant RVD. Between 2002 and 2005, a second RDS study was performed in 119 participants (mean study interval, 8.0 +/- 0.8 years). Significant RVD was defined as hemodynamically significant stenosis (renal artery peak systolic velocity [RA-PSV] exceeding 1.8 m/s) or renal artery occlusion. Prevalent RVD was significant RVD at the first RDS, and incident disease was defined as new significant RVD at the second RDS. Significant change of RVD was defined as a change in RA-PSV of greater than two times the standard deviation of expected change over time, regardless of hemodynamic significance or progression to renal artery occlusion. RESULTS: The second RDS study cohort included 119 CHS participants with 235 kidneys (35% men; mean age, 82.8 +/- 3.4). On follow-up, no prevalent RVD (n = 13 kidneys; 6.0%) progressed to occlusion. Twenty-nine kidneys without RVD at the first RDS demonstrated significant change in PSV at the second RDS; including nine kidneys with new significant RVD (8 new stenoses; 1 new occlusion). Controlling for within-subject correlation, the overall estimated change in RVD among all 235 kidneys was 14.0% (95% confidence interval [CI], 9.2% to 21.4%), with progression to significant RVD in 4.0% (95% CI, 1.9% to 8.2%). Longitudinal increase in diastolic blood pressure and decrease in renal length were significantly associated with progression to new (ie, incident) significant RVD but not prevalent RVD. CONCLUSIONS: This is the first prospective, population-based estimate of incident RVD and progression of prevalent RVD among free-living elderly Americans. In contrast to previous reports among select hypertensive patients, CHS participants with a low rate of clinical hypertension demonstrated a significant change of RVD in only 14.0% of kidneys on follow-up of 8 years (annualized rate, 1.3% per year). Progression to significant RVD was observed in only 4.0% (annualized rate, 0.5% per year), and no prevalent RVD progressed to occlusion.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Blood Flow Velocity; Blood Pressure; Disease Progression; Female; Follow-Up Studies; Humans; Incidence; Male; North Carolina; Population Surveillance; Prognosis; Prospective Studies; Renal Artery Obstruction; Severity of Illness Index; Time Factors; Ultrasonography, Doppler, Duplex

Collaborative meta-analysis of individual participant data from observational studies of Lp-PLA2 and cardiovascular diseases. - Ballantyne, C; Cushman, M; Psaty, B; Furberg, C; Khaw, K T; Sandhu, M; Oldgren, J; Rossi, G P; Maiolino, G; Cesari, M; Lenzini, L; James, S K; et al. (Eur J Cardiovasc Prev Rehabil, 2007)
BACKGROUND: A large number of observational epidemiological studies have reported generally positive associations between circulating mass and activity levels of lipoprotein-associated phospholipase A2 (Lp-PLA2) and the risk of cardiovascular diseases. Few studies have been large enough to provide reliable estimates in different circumstances, such as in different subgroups (e.g., by age group, sex, or smoking status) or at different Lp-PLA2 levels. Moreover, most published studies have related disease risk only to baseline values of Lp-PLA2 markers (which can lead to substantial underestimation of any risk relationships because of within-person variability over time) and have used different approaches to adjustment for possible confounding factors. OBJECTIVES: By combination of data from individual participants from all relevant observational studies in a systematic 'meta-analysis', with correction for regression dilution (using available data on serial measurements of Lp-PLA2), the Lp-PLA2 Studies Collaboration will aim to characterize more precisely than has previously been possible the strength and shape of the age and sex-specific associations of plasma Lp-PLA2 with coronary heart disease (and, where data are sufficient, with other vascular diseases, such as ischaemic stroke). It will also help to determine to what extent such associations are independent of possible confounding factors and to explore potential sources of heterogeneity among studies, such as those related to assay methods and study design. It is anticipated that the present collaboration will serve as a framework to investigate related questions on Lp-PLA2 and cardiovascular outcomes. METHODS: A central database is being established containing data on circulating Lp-PLA2 values, sex and other potential confounding factors, age at baseline Lp-PLA2 measurement, age at event or at last follow-up, major vascular morbidity and cause-specific mortality. Information about any repeat measurements of Lp-PLA2 and potential confounding factors has been sought to allow adjustment for possible confounding and correction for regression dilution. The analyses will involve age-specific regression models. Synthesis of the available observational studies of Lp-PLA2 will yield information on a total of about 15 000 cardiovascular disease endpoints.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Cardiovascular Diseases; Humans; Phospholipases A2

The Emerging Risk Factors Collaboration: analysis of individual data on lipid, inflammatory and other markers in over 1.1 million participants in 104 prospective studies of cardiovascular diseases. - Danesh, J; Erqou, S; Walker, M; Thompson, S G; Tipping, R; Ford, C; Pressel, S; Walldius, G; Jungner, I; Folsom, A R; Chambless, L E; Knuiman, M; et al. (Eur J Epidemiol, 2007)
Many long-term prospective studies have reported on associations of cardiovascular diseases with circulating lipid markers and/or inflammatory markers. Studies have not, however, generally been designed to provide reliable estimates under different circumstances and to correct for within-person variability. The Emerging Risk Factors Collaboration has established a central database on over 1.1 million participants from 104 prospective population-based studies, in which subsets have information on lipid and inflammatory markers, other characteristics, as well as major cardiovascular morbidity and cause-specific mortality. Information on repeat measurements on relevant characteristics has been collected in approximately 340,000 participants to enable estimation of and correction for within-person variability. Re-analysis of individual data will yield up to approximately 69,000 incident fatal or nonfatal first ever major cardiovascular outcomes recorded during about 11.7 million person years at risk. The primary analyses will involve age-specific regression models in people without known baseline cardiovascular disease in relation to fatal or nonfatal first ever coronary heart disease outcomes. This initiative will characterize more precisely and in greater detail than has previously been possible the shape and strength of the age- and sex-specific associations of several lipid and inflammatory markers with incident coronary heart disease outcomes (and, secondarily, with other incident cardiovascular outcomes) under a wide range of circumstances. It will, therefore, help to determine to what extent such associations are independent from possible confounding factors and to what extent such markers (separately and in combination) provide incremental predictive value.
Keywords: Albumins; Biomarkers; Cardiovascular Diseases; Databases, Factual; Far East; Humans; Inflammation; Leukocyte Count; Lipids; Lipoproteins, HDL; Prospective Studies; Risk Factors; Triglycerides

Potential interactions between complementary/alternative products and conventional medicines in a Medicare population. - Elmer, Gary W; Lafferty, William E; Tyree, Patrick T; Lind, Bonnie K (Ann Pharmacother, 2007)
BACKGROUND: Despite the high prevalence of complementary and alternative medicine (CAM) product use among the elderly, little is known about the extent of concurrent CAM-conventional medicine use and the potential for adverse reactions. OBJECTIVE: To determine the prevalence of CAM product use concurrent with conventional medications, prescription and nonprescription, in a Medicare population and assess the risk for adverse interactions. METHODS: Retrospective analysis was performed on Cardiovascular Health Study interview data from 1994, 1995, 1997, and 1999. The prevalence of concurrent combinations of CAM products and conventional drugs was tabulated. The adverse interaction risks were categorized as unknown, theoretical, and significant. RESULTS: Of 5052 participants, the median age was 75, 60.2% were female, 16.6% were African American, and 83.4% were white. The percent using CAM products during the 4 time periods was 6.3%, 6.7%, 12.8%, and 15.1%. The percent using both CAM products and conventional drugs was 6.0%, 6.2%, 11.7%, and 14.4%. Of these, 294 (5.8%) individuals took combinations considered to have a significant risk for an adverse interaction. Combinations with risk were observed on 393 separate interviews. Most (379) involved a risk of bleeding due to use of ginkgo, garlic, or ginseng together with aspirin, warfarin, ticlopidine, or pentoxifylline. An additional 786 observations of combinations were considered to have some, albeit theoretical or uncertain, risk for an adverse interaction. CONCLUSIONS: Concurrent use of CAM products and conventional medicines in a Medicare population was found to be common. Research to define the risks of combining ginkgo and garlic supplements with aspirin should be of high priority.
Keywords: Aged; Complementary Therapies; Drug Interactions; Drug-Related Side Effects and Adverse Reactions; Female; Hemorrhage; Herb-Drug Interactions; Humans; Male; Medicare; Pharmaceutical Preparations; Phytotherapy; Plant Extracts; Plant Preparations; Retrospective Studies; Risk Factors; Washington

Abdominal aortic aneurysms, increasing infrarenal aortic diameter, and risk of total mortality and incident cardiovascular disease events: 10-year follow-up data from the Cardiovascular Health Study. - Freiberg, Matthew S; Arnold, Alice M; Newman, Anne B; Edwards, Matthew S; Kraemer, Kevin L; Kuller, Lewis H (Circulation, 2008)
BACKGROUND: Long-term data describing small abdominal aortic aneurysms (AAAs) and increasing infrarenal aortic diameters and their relationship to future surgical repair, total mortality, and incident cardiovascular disease (CVD) events, particularly among women, are sparse. METHODS AND RESULTS: In 1992 to 1993, 4734 Cardiovascular Health Study participants > or = 65 years old had an abdominal aortic ultrasound evaluation. Of those screened, 416 had an AAA (infrarenal aortic diameter > or = 3.0 cm or an infrarenal/suprarenal ratio > or = 1.2). By 2002, there were 56 surgical AAA repairs and 10 AAA-related deaths. A single ultrasound screening demonstrated that aneurysm dilation > or = 3 cm identified 68% of all AAA repairs over the next 10 years and 6 of the 10 AAA-related deaths in 4% of the total population and that a > or = 2.5-cm dilation identified 91% of all AAA repairs and 9 of the 10 deaths in 10% of the total population. With adjusted Cox proportional hazard models, AAAs were associated with a higher risk of total mortality (hazard ratio 1.44, 95% confidence interval 1.25 to 1.66) and incident CVD events (hazard ratio 1.52, 95% confidence interval 1.25 to 1.85). Compared with diameters < 2.0 cm, infrarenal aortic diameters 2.0 to < 3.0 cm were associated with increased risk of incident CVD events in women and total mortality in men. CONCLUSIONS: This study suggests that a 1-time screening of the abdominal aorta can acceptably identify individuals with a clinically significant AAA. Infrarenal aortic diameters > 2.0 cm are associated with a significantly increased risk of future CVD events and total mortality.
Keywords: Aged; Aged, 80 and over; Aorta, Abdominal; Aortic Aneurysm, Abdominal; Cause of Death; Female; Follow-Up Studies; Humans; Incidence; Intermittent Claudication; Kidney; Male; Prospective Studies; Risk Factors; Sex Distribution; Ultrasonography

Association of gene variants with incident myocardial infarction in the Cardiovascular Health Study. - Shiffman, Dov; O'Meara, Ellen S; Bare, Lance A; Rowland, Charles M; Louie, Judy Z; Arellano, Andre R; Lumley, Thomas; Rice, Kenneth; Iakoubova, Olga; Luke, May M; Young, Bradford A; Malloy, Mary J; et al. (Arterioscler Thromb Vasc Biol, 2008)
OBJECTIVE: We asked whether single nucleotide polymorphisms (SNPs) that had been nominally associated with cardiovascular disease in antecedent studies were also associated with cardiovascular disease in a population-based prospective study of 4522 individuals aged 65 or older. METHODS AND RESULTS: Based on antecedent studies, we prespecified a risk allele and an inheritance model for each of 74 SNPs. We then tested the association of these SNPs with myocardial infarction (MI) in the Cardiovascular Health Study (CHS). The prespecified risk alleles of 8 SNPs were nominally associated (1-sided P<0.05) with increased risk of MI in White CHS participants. The false discovery rate for these 8 was 0.43, suggesting that about 4 of these 8 are likely to be true positives. The 4 of these 8 SNPs that had the strongest evidence for association with cardiovascular disease before testing in CHS (association in 3 antecedent studies) were in KIF6 (CHS HR=1.29; 90%CI 1.1 to 1.52), VAMP8 (HR=1.2; 90%CI 1.02 to 1.41), TAS2R50 (HR=1.13; 90%CI 1 to 1.27), and LPA (HR=1.62; 90%CI 1.09 to 2.42). CONCLUSIONS: Although most of the SNPs investigated were not associated with MI in CHS, evidence from this investigation combined with previous studies suggests that 4 of these SNPs are likely associated with MI.
Keywords: African Americans; Aged; Aged, 80 and over; Coronary Disease; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Male; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Polymorphism, Single Nucleotide; Proportional Hazards Models; United States

Incident physical disability in people with lower extremity peripheral arterial disease: the role of cardiovascular disease. - Brach, Jennifer S; Solomon, Cam; Naydeck, Barbara L; Sutton-Tyrrell, Kim; Enright, Paul L; Jenny, Nancy Swords; Chaves, Paulo M; Newman, Anne B (J Am Geriatr Soc, 2008)
OBJECTIVES: To evaluate the risk of incident physical disability and the decline in gait speed over a 6-year follow-up associated with a low ankle-arm index (AAI) in older adults. DESIGN: Observational cohort study. SETTING: Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Allegheny County, Pennsylvania. PARTICIPANTS: Four thousand seven hundred five older adults, 58% women and 17.6% black, participating in the Cardiovascular Health Study. MEASUREMENTS: AAI was measured in 1992/93 (baseline). Self-reported mobility, activity of daily living (ADL), and instrumental activity of daily living (IADL) disability and gait speed were recorded at baseline and at 1-year intervals over 6 years of follow-up. Mobility disability was defined as any difficulty walking half a mile and ADL and IADL disability was defined as any difficulty with 11 specific ADL and IADL tasks. Individuals with mobility, ADL, or IADL disability at baseline were excluded from the respective incident disability analyses. RESULTS: Lower baseline AAI values were associated with increased risk of mobility disability and ADL/IADL disability. Clinical cardiovascular disease (CVD), diabetes mellitus, and interim CVD events partially explained these associations for mobility disability and clinical CVD and diabetes mellitus partially explained these associations for ADL and IADL disability. Individuals with an AAI less than 0.9 had on average a mean decrease in gait speed of 0.02 m/s per year, or a decline of 0.12 m/s over the 6-year follow-up. Prevalent CVD partly explained this decrease but interim CVD events did not further attenuate it. CONCLUSION: Low AAI serves as marker of future disability risk. Reduction of disability risk in patients with a low AAI should consider cardiovascular comorbidity and the prevention of additional disabling CVD events.
Keywords: Activities of Daily Living; Aged; Cardiovascular Diseases; Cohort Studies; Comorbidity; Disability Evaluation; Female; Gait; Geriatric Assessment; Humans; Lower Extremity; Male; Mobility Limitation; Peripheral Vascular Diseases; Proportional Hazards Models; Risk Assessment; Risk Factors; United States

Inflammatory markers and longitudinal lung function decline in the elderly. - Jiang, Rui; Burke, Gregory L; Enright, Paul L; Newman, Anne B; Margolis, Helene G; Cushman, Mary; Tracy, Russell P; Wang, Yuanjia; Kronmal, Richard A; Barr, R Graham (Am J Epidemiol, 2008)
Longitudinal studies examining associations of the inflammatory markers fibrinogen and C-reactive protein (CRP) with lung function decline are sparse. The authors examined whether elevated fibrinogen and CRP levels were associated with greater longitudinal lung function decline in the elderly. The Cardiovascular Health Study measured fibrinogen and CRP in 5,790 Whites and African Americans from four US communities aged 65 years or older in 1989-1990 or 1992-1993. Spirometry was performed in 1989-1990 and 4, 7, and 16 years later. Fibrinogen and CRP were inversely associated with lung function at baseline after adjustment for multiple potential confounders. In mixed models, the rate of decline in forced expiratory volume in 1 second (FEV(1))/forced vital capacity (FVC) ratio with increasing age was faster among those with higher baseline fibrinogen (-0.032%/year per standard deviation higher fibrinogen (95% confidence interval: -0.057, -0.0074)) but not among those with higher CRP (-0.0037%/year per standard deviation higher CRP (95% confidence interval: -0.013, 0.0056)). Longitudinal analyses for FEV(1) and FVC yielded results in the direction opposite of that hypothesized, possibly because of the high mortality rate and strong inverse association of FEV(1) and FVC but not FEV(1)/FVC with mortality. An alternative approach to missing data yielded similar results. In conclusion, higher levels of fibrinogen, but not CRP, independently predicted greater FEV(1)/FVC decline in the elderly.
Keywords: Aged; C-Reactive Protein; Cross-Sectional Studies; Female; Fibrinogen; Forced Expiratory Volume; Geriatric Assessment; Humans; Logistic Models; Longitudinal Studies; Lung Volume Measurements; Male; Multicenter Studies as Topic; Pulmonary Disease, Chronic Obstructive; Spirometry

Insulin-like growth factors, their binding proteins, and prostate cancer risk: analysis of individual patient data from 12 prospective studies. - Roddam, Andrew W; Allen, Naomi E; Appleby, Paul; Key, Timothy J; Ferrucci, Luigi; Carter, H Ballentine; Metter, E Jeffrey; Chen, Chu; Weiss, Noel S; Fitzpatrick, Annette; Hsing, Ann W; Lacey, James V; et al. (Ann Intern Med, 2008)
BACKGROUND: Some, but not all, published results have shown an association between circulating blood levels of some insulin-like growth factors (IGFs) and their binding proteins (IGFBPs) and the subsequent risk for prostate cancer. PURPOSE: To assess the association between levels of IGFs and IGFBPs and the subsequent risk for prostate cancer. DATA SOURCES: Studies identified in PubMed, Web of Science, and CancerLit. STUDY SELECTION: The principal investigators of all studies that published data on circulating concentrations of sex steroids, IGFs, or IGFBPs and prostate cancer risk using prospectively collected blood samples were invited to collaborate. DATA EXTRACTION: Investigators provided individual participant data on circulating concentrations of IGF-I, IGF-II, IGFBP-II, and IGFBP-III and participant characteristics to a central data set in Oxford, United Kingdom. DATA SYNTHESIS: The study included data on 3700 men with prostate cancer and 5200 control participants. On average, case patients were 61.5 years of age at blood collection and received a diagnosis of prostate cancer 5 years after blood collection. The greater the serum IGF-I concentration, the greater the subsequent risk for prostate cancer (odds ratio [OR] in the highest vs. lowest quintile, 1.38 [95% CI, 1.19 to 1.60]; P < 0.001 for trend). Neither IGF-II nor IGFBP-II concentrations were associated with prostate cancer risk, but statistical power was limited. Insulin-like growth factor I and IGFBP-III were correlated (r = 0.58), and although IGFBP-III concentration seemed to be associated with prostate cancer risk, this was secondary to its association with IGF-I levels. Insulin-like growth factor I concentrations seemed to be more positively associated with low-grade than high-grade disease; otherwise, the association between IGFs and IGFBPs and prostate cancer risk had no statistically significant heterogeneity related to stage or grade of disease, time between blood collection and diagnosis, age and year of diagnosis, prostate-specific antigen level at recruitment, body mass index, smoking, or alcohol intake. LIMITATIONS: Insulin-like growth factor concentrations were measured in only 1 sample for each participant, and the laboratory methods to measure IGFs differed in each study. Not all patients had disease stage or grade information, and the diagnosis of prostate cancer may differ among the studies. CONCLUSION: High circulating IGF-I concentrations are associated with a moderately increased risk for prostate cancer.
Keywords: Aged; Humans; Insulin-Like Growth Factor Binding Protein 2; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor Binding Proteins; Insulin-Like Growth Factor I; Insulin-Like Growth Factor II; Male; Middle Aged; Prospective Studies; Prostatic Neoplasms; Risk Factors; Somatomedins

Metabolic syndrome, endothelial dysfunction, and risk of cardiovascular events: the Northern Manhattan Study (NOMAS). - Suzuki, Takeki; Hirata, Kumiko; Elkind, Mitchell S V; Jin, Zhezhen; Rundek, Tanja; Miyake, Yumiko; Boden-Albala, Bernadette; Di Tullio, Marco R; Sacco, Ralph; Homma, Shunichi (Am Heart J, 2008)
BACKGROUND: Metabolic syndrome (MetS) predisposes to cardiovascular disease. Endothelial dysfunction is thought to be an important factor in the pathogenesis of atherosclerosis. We tested the hypothesis that both MetS and endothelial dysfunction are vascular risk factors and provide additive prognostic values in predicting cardiovascular events in a multiethnic community sample. METHODS: The study population consisted of 819 subjects (467 female, mean age 66.5 +/- 8.8 years, 66% Hispanic) enrolled in the NOMAS. Metabolic syndrome was defined using the revised Adult Treatment Panel III criteria. Brachial artery flow-mediated dilation (FMD) was measured using high-resolution ultrasound. Endothelial dysfunction was defined as FMD <8.44% (lower 3 quartiles). Cox proportional hazards models were used to assess the effect of MetS and endothelial dysfunction on risk of cardiovascular events. RESULTS: During 81 +/- 21 months of follow-up, events occurred in 84 subjects. Metabolic syndrome was independently associated with cardiovascular events in a multivariate model, including cardiovascular risk factors (adjusted hazard ratio 2.08, 95% CI 1.27-3.40). Subjects with both MetS and endothelial dysfunction were at higher risk for cardiovascular events than those with either one of them alone (adjusted hazard ratio 2.60, 95% CI 1.14-5.92). CONCLUSIONS: Metabolic syndrome is associated with incident cardiovascular events. Combined use of MetS and FMD identifies those who are at higher risk of cardiovascular events. Metabolic syndrome and noninvasive FMD testing can be used concurrently for cardiovascular risk prediction.
Keywords: Adult; Aged; Brachial Artery; Endothelium, Vascular; Female; Humans; Kaplan-Meier Estimate; Male; Metabolic Syndrome; Middle Aged; Prognosis; Prospective Studies; Risk Factors; Stroke; Vascular Diseases

Association of genetic variation in serum amyloid-A with cardiovascular disease and interactions with IL6, IL1RN, IL1beta and TNF genes in the Cardiovascular Health Study. - Carty, Cara L; Heagerty, Patrick; Heckbert, Susan R; Enquobahrie, Daniel A; Jarvik, Gail P; Davis, Scott; Tracy, Russell P; Reiner, Alexander P (J Atheroscler Thromb, 2009)
AIM: Since inflammation is an important contributor to atherosclerosis, gene variants mediating inflammation are of interest. We investigated gene variants in acute phase serum amyloid-A (SAA), a sensitive indicator of inflammatory activity, and their associations with cardiovascular disease (CVD) and HDL cholesterol. Interaction of the SAA genes with genetic variants of their regulators, IL-1, IL-6 and TNF-alpha in influencing CVD was also explored. METHODS: SNPs characterizing common variation in the SAA1 and SAA2 genes were genotyped in European-(EA) and African-American (AA) participants (n=3969 and n=719) of the Cardiovascular Health Study. Using linear and Cox proportional hazards regression, we assessed associations of SNPs with baseline carotid artery intima-media thickness (cIMT) and risk of incident myocardial infarction, ischemic stroke, total CVD events or mortality during 14 years of follow-up. RESULTS: No associations between SAA SNPs and outcomes were observed in EA, with the exception of total CVD events; each rs4638289 minor allele was associated with an increased risk in obese individuals, HR=1.2 (95%CI: 0.981.4; p=0.086) and decreased risk among non-obese, HR=0.9 (95%CI: 0.80.99; p=0.026). In AA, we observed modest associations between SAA SNPs and cIMT, potentially modified by HDL. SAA SNPs were also associated with lower HDL in EA and AA. Suggestive gene-gene interaction findings for cIMT in AA and CVD mortality in EA were not significant in subsequent model selection tests. CONCLUSION: Associations of SAA SNPs with cIMT, HDL and total CVD events were identified, unadjusted for multiple testing. These findings should be regarded as hypothesis-generating until confirmed by other studies.
Keywords: Aged; Cardiovascular Diseases; Cholesterol, HDL; Cytokines; Female; Gene Regulatory Networks; Humans; Inflammation Mediators; Interleukin 1 Receptor Antagonist Protein; Interleukin-1beta; Interleukin-6; Male; Polymorphism, Single Nucleotide; Proportional Hazards Models; Serum Amyloid A Protein; Tumor Necrosis Factor-alpha; Tunica Intima

Association of novel genetic Loci with circulating fibrinogen levels: a genome-wide association study in 6 population-based cohorts. - Dehghan, Abbas; Yang, Qiong; Peters, Annette; Basu, Saonli; Bis, Joshua C; Rudnicka, Alicja R; Kavousi, Maryam; Chen, Ming-Huei; Baumert, Jens; Lowe, Gordon D O; McKnight, Barbara; Tang, Weihong; et al. (Circ Cardiovasc Genet, 2009)
BACKGROUND: Fibrinogen is both central to blood coagulation and an acute-phase reactant. We aimed to identify common variants influencing circulation fibrinogen levels. METHODS AND RESULTS: We conducted a genome-wide association analysis on 6 population-based studies, the Rotterdam Study, the Framingham Heart Study, the Cardiovascular Health Study, the Atherosclerosis Risk in Communities Study, the Monitoring of Trends and Determinants in Cardiovascular Disease/KORA Augsburg Study, and the British 1958 Birth Cohort Study, including 22 096 participants of European ancestry. Four loci were marked by 1 or more single-nucleotide polymorphisms that demonstrated genome-wide significance (P<5.0 x 10(-8)). These included a single-nucleotide polymorphism located in the fibrinogen beta chain (FGB) gene and 3 single-nucleotide polymorphisms representing newly identified loci. The high-signal single-nucleotide polymorphisms were rs1800789 in exon 7 of FGB (P=1.8 x 10(-30)), rs2522056 downstream from the interferon regulatory factor 1 (IRF1) gene (P=1.3 x 10(-15)), rs511154 within intron 1 of the propionyl coenzyme A carboxylase (PCCB) gene (P=5.9 x 10(-10)), and rs1539019 on the NLR family pyrin domain containing 3 isoforms (NLRP3) gene (P=1.04 x 10(-8)). CONCLUSIONS: Our findings highlight biological pathways that may be important in regulation of inflammation underlying cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Common variants at ten loci influence QT interval duration in the QTGEN Study. - Newton-Cheh, Christopher; Eijgelsheim, Mark; Rice, Kenneth M; de Bakker, Paul I W; Yin, Xiaoyan; Estrada, Karol; Bis, Joshua C; Marciante, Kristin; Rivadeneira, Fernando; Noseworthy, Peter A; Sotoodehnia, Nona; Smith, Nicholas L; et al. (Nat Genet, 2009)
QT interval duration, reflecting myocardial repolarization on the electrocardiogram, is a heritable risk factor for sudden cardiac death and drug-induced arrhythmias. We conducted a meta-analysis of three genome-wide association studies in 13,685 individuals of European ancestry from the Framingham Heart Study, the Rotterdam Study and the Cardiovascular Health Study, as part of the QTGEN consortium. We observed associations at P < 5 x 10(-8) with variants in NOS1AP, KCNQ1, KCNE1, KCNH2 and SCN5A, known to be involved in myocardial repolarization and mendelian long-QT syndromes. Associations were found at five newly identified loci, including 16q21 near NDRG4 and GINS3, 6q22 near PLN, 1p36 near RNF207, 16p13 near LITAF and 17q12 near LIG3 and RFFL. Collectively, the 14 independent variants at these 10 loci explain 5.4-6.5% of the variation in QT interval. These results, together with an accompanying paper, offer insights into myocardial repolarization and suggest candidate genes that could predispose to sudden cardiac death and drug-induced arrhythmias.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Aged; Arrhythmias, Cardiac; Chromosome Mapping; Death, Sudden, Cardiac; Electroencephalography; ERG1 Potassium Channel; Ether-A-Go-Go Potassium Channels; European Continental Ancestry Group; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Humans; KCNQ1 Potassium Channel; Meta-Analysis as Topic; Muscle Proteins; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Potassium Channels, Voltage-Gated; Risk Factors; Sodium Channels

Genetic variants associated with cardiac structure and function: a meta-analysis and replication of genome-wide association data. - Vasan, Ramachandran S; Glazer, Nicole L; Felix, Janine F; Lieb, Wolfgang; Wild, Philipp S; Felix, Stephan B; Watzinger, Norbert; Larson, Martin G; Smith, Nicholas L; Dehghan, Abbas; Grosshennig, Anika; Schillert, Arne; et al. (JAMA, 2009)
CONTEXT: Echocardiographic measures of left ventricular (LV) structure and function are heritable phenotypes of cardiovascular disease. OBJECTIVE: To identify common genetic variants associated with cardiac structure and function by conducting a meta-analysis of genome-wide association data in 5 population-based cohort studies (stage 1) with replication (stage 2) in 2 other community-based samples. DESIGN, SETTING, AND PARTICIPANTS: Within each of 5 community-based cohorts comprising the EchoGen consortium (stage 1; n = 12 612 individuals of European ancestry; 55% women, aged 26-95 years; examinations between 1978-2008), we estimated the association between approximately 2.5 million single-nucleotide polymorphisms (SNPs; imputed to the HapMap CEU panel) and echocardiographic traits. In stage 2, SNPs significantly associated with traits in stage 1 were tested for association in 2 other cohorts (n = 4094 people of European ancestry). Using a prespecified P value threshold of 5 x 10(-7) to indicate genome-wide significance, we performed an inverse variance-weighted fixed-effects meta-analysis of genome-wide association data from each cohort. MAIN OUTCOME MEASURES: Echocardiographic traits: LV mass, internal dimensions, wall thickness, systolic dysfunction, aortic root, and left atrial size. RESULTS: In stage 1, 16 genetic loci were associated with 5 echocardiographic traits: 1 each with LV internal dimensions and systolic dysfunction, 3 each with LV mass and wall thickness, and 8 with aortic root size. In stage 2, 5 loci replicated (6q22 locus associated with LV diastolic dimensions, explaining <1% of trait variance; 5q23, 12p12, 12q14, and 17p13 associated with aortic root size, explaining 1%-3% of trait variance). CONCLUSIONS: We identified 5 genetic loci harboring common variants that were associated with variation in LV diastolic dimensions and aortic root size, but such findings explained a very small proportion of variance. Further studies are required to replicate these findings, identify the causal variants at or near these loci, characterize their functional significance, and determine whether they are related to overt cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Aorta; Cardiovascular Diseases; Echocardiography; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart Atria; Heart Ventricles; Humans; Male; Middle Aged; Organ Size; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Ventricular Dysfunction, Left; Ventricular Function, Left

Genome-wide association study of blood pressure and hypertension. - Levy, Daniel; Ehret, Georg B; Rice, Kenneth; Verwoert, Germaine C; Launer, Lenore J; Dehghan, Abbas; Glazer, Nicole L; Morrison, Alanna C; Johnson, Andrew D; Aspelund, Thor; Aulchenko, Yurii; Lumley, Thomas; et al. (Nat Genet, 2009)
Blood pressure is a major cardiovascular disease risk factor. To date, few variants associated with interindividual blood pressure variation have been identified and replicated. Here we report results of a genome-wide association study of systolic (SBP) and diastolic (DBP) blood pressure and hypertension in the CHARGE Consortium (n = 29,136), identifying 13 SNPs for SBP, 20 for DBP and 10 for hypertension at P < 4 × 10(-7). The top ten loci for SBP and DBP were incorporated into a risk score; mean BP and prevalence of hypertension increased in relation to the number of risk alleles carried. When ten CHARGE SNPs for each trait were included in a joint meta-analysis with the Global BPgen Consortium (n = 34,433), four CHARGE loci attained genome-wide significance (P < 5 × 10(-8)) for SBP (ATP2B1, CYP17A1, PLEKHA7, SH2B3), six for DBP (ATP2B1, CACNB2, CSK-ULK3, SH2B3, TBX3-TBX5, ULK4) and one for hypertension (ATP2B1). Identifying genes associated with blood pressure advances our understanding of blood pressure regulation and highlights potential drug targets for the prevention or treatment of hypertension.
Keywords: Blood Pressure; Cell Line; Chromosome Mapping; Chromosomes, Human; Diastole; Gene Expression Regulation; Genetic Association Studies; Genome-Wide Association Study; Humans; Hypertension; Liver; Lymphocytes; Meta-Analysis as Topic; Odds Ratio; Phenotype; Prevalence; Risk Assessment; Systole

Insomnia did not predict incident hypertension in older adults in the cardiovascular health study. - Phillips, Barbara; Bůzková, Petra; Enright, Paul (Sleep, 2009)
STUDY OBJECTIVE: We hypothesized that the sleep complaints of insomnia predict incident hypertension, particularly in African Americans. The purpose of this study was to analyze insomnia complaints as predictors of incident hypertension in the Cardiovascular Health Study (CHS), stratifying by gender and allowing for race and sleep variable interaction. DESIGN: This is a prospective cohort study over a 6-year period of follow-up. SETTING: This is a community-based study of participants in Forsyth County, North Carolina; Pittsburgh, Pennsylvania; Sacramento County, California; and Washington County, Maryland. PARTICIPANTS: The study analyzed data from 1419 older individuals (baseline mean age 73.4 +/- 4.4 years) from the Cardiovascular Health Study who were not hypertensive at baseline. INTERVENTIONS: none. MEASUREMENTS: We constructed relative risks of incident hypertension over a 6-year period for insomnia complaints singly and in combination. RESULTS: Difficulty falling asleep, singly or in combination with other sleep complaints, predicted a statistically significant reduction of risk for incident hypertension for non-African American men in 6 years of follow-up. Insomnia complaints did not predict incident hypertension in 6 years of follow-up in women or in African Americans, although there may not have been enough power to show a significant association for African Americans. CONCLUSIONS: Insomnia did not predict hypertension in this older cohort which was free of hypertension at baseline. Difficulty falling asleep was associated with reduced risk of hypertension in non-African American men.
Keywords: African Americans; Aged; Cohort Studies; Comorbidity; European Continental Ancestry Group; Female; Follow-Up Studies; Health Surveys; Humans; Hypertension; Male; Prospective Studies; Risk Factors; Sleep Initiation and Maintenance Disorders; United States

Lipoprotein(a) concentration and the risk of coronary heart disease, stroke, and nonvascular mortality. - Erqou, Sebhat; Kaptoge, Stephen; Perry, Philip L; Di Angelantonio, Emanuele; Thompson, Alexander; White, Ian R; Marcovina, Santica M; Collins, Rory; Thompson, Simon G; Danesh, John (JAMA, 2009)
CONTEXT: Circulating concentration of lipoprotein(a) (Lp[a]), a large glycoprotein attached to a low-density lipoprotein-like particle, may be associated with risk of coronary heart disease (CHD) and stroke. OBJECTIVE: To assess the relationship of Lp(a) concentration with risk of major vascular and nonvascular outcomes. STUDY SELECTION: Long-term prospective studies that recorded Lp(a) concentration and subsequent major vascular morbidity and/or cause-specific mortality published between January 1970 and March 2009 were identified through electronic searches of MEDLINE and other databases, manual searches of reference lists, and discussion with collaborators. DATA EXTRACTION: Individual records were provided for each of 126,634 participants in 36 prospective studies. During 1.3 million person-years of follow-up, 22,076 first-ever fatal or nonfatal vascular disease outcomes or nonvascular deaths were recorded, including 9336 CHD outcomes, 1903 ischemic strokes, 338 hemorrhagic strokes, 751 unclassified strokes, 1091 other vascular deaths, 8114 nonvascular deaths, and 242 deaths of unknown cause. Within-study regression analyses were adjusted for within-person variation and combined using meta-analysis. Analyses excluded participants with known preexisting CHD or stroke at baseline. DATA SYNTHESIS: Lipoprotein(a) concentration was weakly correlated with several conventional vascular risk factors and it was highly consistent within individuals over several years. Associations of Lp(a) with CHD risk were broadly continuous in shape. In the 24 cohort studies, the rates of CHD in the top and bottom thirds of baseline Lp(a) distributions, respectively, were 5.6 (95% confidence interval [CI], 5.4-5.9) per 1000 person-years and 4.4 (95% CI, 4.2-4.6) per 1000 person-years. The risk ratio for CHD, adjusted for age and sex only, was 1.16 (95% CI, 1.11-1.22) per 3.5-fold higher usual Lp(a) concentration (ie, per 1 SD), and it was 1.13 (95% CI, 1.09-1.18) following further adjustment for lipids and other conventional risk factors. The corresponding adjusted risk ratios were 1.10 (95% CI, 1.02-1.18) for ischemic stroke, 1.01 (95% CI, 0.98-1.05) for the aggregate of nonvascular mortality, 1.00 (95% CI, 0.97-1.04) for cancer deaths, and 1.00 (95% CI, 0.95-1.06) for nonvascular deaths other than cancer. CONCLUSION: Under a wide range of circumstances, there are continuous, independent, and modest associations of Lp(a) concentration with risk of CHD and stroke that appear exclusive to vascular outcomes.
Keywords: Cause of Death; Coronary Disease; Humans; Lipoprotein(a); Risk Factors; Stroke

Longitudinal Data with Follow-up Truncated by Death: Match the Analysis Method to Research Aims. - Kurland, Brenda F; Johnson, Laura L; Egleston, Brian L; Diehr, Paula H (Stat Sci, 2009)
Diverse analysis approaches have been proposed to distinguish data missing due to death from nonresponse, and to summarize trajectories of longitudinal data truncated by death. We demonstrate how these analysis approaches arise from factorizations of the distribution of longitudinal data and survival information. Models are illustrated using cognitive functioning data for older adults. For unconditional models, deaths do not occur, deaths are independent of the longitudinal response, or the unconditional longitudinal response is averaged over the survival distribution. Unconditional models, such as random effects models fit to unbalanced data, may implicitly impute data beyond the time of death. Fully conditional models stratify the longitudinal response trajectory by time of death. Fully conditional models are effective for describing individual trajectories, in terms of either aging (age, or years from baseline) or dying (years from death). Causal models (principal stratification) as currently applied are fully conditional models, since group differences at one timepoint are described for a cohort that will survive past a later timepoint. Partly conditional models summarize the longitudinal response in the dynamic cohort of survivors. Partly conditional models are serial cross-sectional snapshots of the response, reflecting the average response in survivors at a given timepoint rather than individual trajectories. Joint models of survival and longitudinal response describe the evolving health status of the entire cohort. Researchers using longitudinal data should consider which method of accommodating deaths is consistent with research aims, and use analysis methods accordingly.

Multiple loci associated with indices of renal function and chronic kidney disease. - Köttgen, Anna; Glazer, Nicole L; Dehghan, Abbas; Hwang, Shih-Jen; Katz, Ronit; Li, Man; Yang, Qiong; Gudnason, Vilmundur; Launer, Lenore J; Harris, Tamara B; Smith, Albert V; Arking, Dan E; et al. (Nat Genet, 2009)
Chronic kidney disease (CKD) has a heritable component and is an important global public health problem because of its high prevalence and morbidity. We conducted genome-wide association studies (GWAS) to identify susceptibility loci for glomerular filtration rate, estimated by serum creatinine (eGFRcrea) and cystatin C (eGFRcys), and CKD (eGFRcrea < 60 ml/min/1.73 m(2)) in European-ancestry participants of four population-based cohorts (ARIC, CHS, FHS, RS; n = 19,877; 2,388 CKD cases), and tested for replication in 21,466 participants (1,932 CKD cases). We identified significant SNP associations (P < 5 × 10(-8)) with CKD at the UMOD locus, with eGFRcrea at UMOD, SHROOM3 and GATM-SPATA5L1, and with eGFRcys at CST and STC1. UMOD encodes the most common protein in human urine, Tamm-Horsfall protein, and rare mutations in UMOD cause mendelian forms of kidney disease. Our findings provide new insights into CKD pathogenesis and underscore the importance of common genetic variants influencing renal function and disease.
Keywords: Chromosome Mapping; Cohort Studies; Genetic Variation; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Meta-Analysis as Topic; Mucoproteins; Netherlands; Polymorphism, Single Nucleotide; Prevalence; Uromodulin

Multiple loci influence erythrocyte phenotypes in the CHARGE Consortium. - Ganesh, Santhi K; Zakai, Neil A; van Rooij, Frank J A; Soranzo, Nicole; Smith, Albert V; Nalls, Michael A; Chen, Ming-Huei; Köttgen, Anna; Glazer, Nicole L; Dehghan, Abbas; Kuhnel, Brigitte; Aspelund, Thor; et al. (Nat Genet, 2009)
Measurements of erythrocytes within the blood are important clinical traits and can indicate various hematological disorders. We report here genome-wide association studies (GWAS) for six erythrocyte traits, including hemoglobin concentration (Hb), hematocrit (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and red blood cell count (RBC). We performed an initial GWAS in cohorts of the CHARGE Consortium totaling 24,167 individuals of European ancestry and replication in additional independent cohorts of the HaemGen Consortium totaling 9,456 individuals. We identified 23 loci significantly associated with these traits in a meta-analysis of the discovery and replication cohorts (combined P values ranging from 5 x 10(-8) to 7 x 10(-86)). Our findings include loci previously associated with these traits (HBS1L-MYB, HFE, TMPRSS6, TFR2, SPTA1) as well as new associations (EPO, TFRC, SH2B3 and 15 other loci). This study has identified new determinants of erythrocyte traits, offering insight into common variants underlying variation in erythrocyte measures.
Keywords: Blood Pressure; Cell Line; Cohort Studies; Endothelial Cells; Erythrocytes; Gene Expression; Genome, Human; Genome-Wide Association Study; Humans; Hypertension; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

NRXN3 is a novel locus for waist circumference: a genome-wide association study from the CHARGE Consortium. - Heard-Costa, Nancy L; Zillikens, M Carola; Monda, Keri L; Johansson, Asa; Harris, Tamara B; Fu, Mao; Haritunians, Talin; Feitosa, Mary F; Aspelund, Thor; Eiriksdottir, Gudny; Garcia, Melissa; Launer, Lenore J; et al. (PLoS Genet, 2009)
Central abdominal fat is a strong risk factor for diabetes and cardiovascular disease. To identify common variants influencing central abdominal fat, we conducted a two-stage genome-wide association analysis for waist circumference (WC). In total, three loci reached genome-wide significance. In stage 1, 31,373 individuals of Caucasian descent from eight cohort studies confirmed the role of FTO and MC4R and identified one novel locus associated with WC in the neurexin 3 gene [NRXN3 (rs10146997, p = 6.4x10(-7))]. The association with NRXN3 was confirmed in stage 2 by combining stage 1 results with those from 38,641 participants in the GIANT consortium (p = 0.009 in GIANT only, p = 5.3x10(-8) for combined analysis, n = 70,014). Mean WC increase per copy of the G allele was 0.0498 z-score units (0.65 cm). This SNP was also associated with body mass index (BMI) [p = 7.4x10(-6), 0.024 z-score units (0.10 kg/m(2)) per copy of the G allele] and the risk of obesity (odds ratio 1.13, 95% CI 1.07-1.19; p = 3.2x10(-5) per copy of the G allele). The NRXN3 gene has been previously implicated in addiction and reward behavior, lending further evidence that common forms of obesity may be a central nervous system-mediated disorder. Our findings establish that common variants in NRXN3 are associated with WC, BMI, and obesity.
Keywords: Aged; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Obesity; Polymorphism, Single Nucleotide; Waist Circumference

N-terminal pro-B-type natriuretic peptide is a major predictor of the development of atrial fibrillation: the Cardiovascular Health Study. - Patton, Kristen K; Ellinor, Patrick T; Heckbert, Susan R; Christenson, Robert H; DeFilippi, Christopher; Gottdiener, John S; Kronmal, Richard A (Circulation, 2009)
BACKGROUND: Atrial fibrillation (AF), the most common cardiac rhythm abnormality, is associated with significant morbidity, mortality, and healthcare expenditures. Elevated B-type natriuretic peptide levels have been associated with the risk of heart failure, AF, and mortality. METHODS AND RESULTS: The relation between N-terminal pro-B-type natriuretic peptide (NT-proBNP) and AF was studied in 5445 Cardiovascular Health Study participants with the use of relative risk regression for predicting prevalent AF and Cox proportional hazards for predicting incident AF. NT-proBNP levels were strongly associated with prevalent AF, with an unadjusted prevalence ratio of 128 for the highest quintile (95% confidence interval, 17.9 to 913.3; P<0.001) and adjusted prevalence ratio of 147 for the highest quintile (95% confidence interval, 20.4 to 1064.3; P<0.001) compared with the lowest. After a median follow-up of 10 years (maximum of 16 years), there were 1126 cases of incident AF (a rate of 2.2 per 100 person-years). NT-proBNP was highly predictive of incident AF, with an unadjusted hazard ratio of 5.2 (95% confidence interval, 4.3 to 6.4; P<0.001) for the development of AF for the highest quintile compared with the lowest; for the same contrast, NT-proBNP remained the strongest predictor of incident AF after adjustment for an extensive number of covariates, including age, sex, medication use, blood pressure, echocardiographic parameters, diabetes mellitus, and heart failure, with an adjusted hazard ratio of 4.0 (95% confidence interval, 3.2 to 5.0; P<0.001). CONCLUSIONS: In a community-based population of older adults, NT-proBNP was a remarkable predictor of incident AF, independent of any other previously described risk factor.
Keywords: Aged; Aged, 80 and over; Atrial Fibrillation; Female; Humans; Immunoassay; Longitudinal Studies; Male; Natriuretic Peptide, Brain; Peptide Fragments; Predictive Value of Tests; Prevalence; Proportional Hazards Models; Risk Factors

Sleep-disordered breathing and frailty in the Cardiovascular Health Study Cohort. - Endeshaw, Yohannes W; Unruh, Mark L; Kutner, Michael; Newman, Anne B; Bliwise, Donald L (Am J Epidemiol, 2009)
Sleep-disordered breathing (SDB) is associated with pathophysiology that may influence the development and progression of frailty. Using data collected in 1995-1996, the authors explored the relation between SDB and components of frailty among 1,042 participants of the Cardiovascular Health Study. Diagnosis of SDB was based on the results of overnight polysomnography, and severe SDB was defined as an apnea-hypopnea index of >30 per hour of sleep. Slow walking speed, low grip strength, exhaustion, low physical activity, and unexplained weight loss were referred to as frailty indicator variables. There were 584 (56%) female and 458 (44%) male participants, and the mean age was 77 (standard deviation, 4) years. There was independent association between severe SDB and 1 or more frailty indicator variables (adjusted odds ratio = 4.85, 95% confidence interval: 1.40, 16.78), slow walking speed (adjusted odds ratio = 2.67, 95% confidence interval: 1.04, 6.84), and low grip strength (adjusted odds ratio = 3.29, 95% confidence interval: 1.36, 7.96) among female study participants. The finding of an independent association between SDB and frailty indicator variables among older women could have important implications in interventions aimed at preventing or delaying the progression of frailty.
Keywords: Activities of Daily Living; Aged; Cardiovascular Diseases; Cardiovascular System; Cohort Studies; Confidence Intervals; Exercise Tolerance; Female; Frail Elderly; Hand Strength; Humans; Logistic Models; Male; Mobility Limitation; Models, Statistical; Motor Activity; Muscle Strength; Odds Ratio; Polysomnography; Psychometrics; Risk Factors; Sleep Apnea, Obstructive; Weight Loss

Systematically missing confounders in individual participant data meta-analysis of observational cohort studies. - Jackson, Dan; White, Ian; Kostis, J B; Wilson, A C; Folsom, A R; Wu, K; Chambless, L; Benderly, M; Goldbourt, U; Willeit, J; Kiechl, S; Yarnell, J W G; et al. (Stat Med, 2009)
One difficulty in performing meta-analyses of observational cohort studies is that the availability of confounders may vary between cohorts, so that some cohorts provide fully adjusted analyses while others only provide partially adjusted analyses. Commonly, analyses of the association between an exposure and disease either are restricted to cohorts with full confounder information, or use all cohorts but do not fully adjust for confounding. We propose using a bivariate random-effects meta-analysis model to use information from all available cohorts while still adjusting for all the potential confounders. Our method uses both the fully adjusted and the partially adjusted estimated effects in the cohorts with full confounder information, together with an estimate of their within-cohort correlation. The method is applied to estimate the association between fibrinogen level and coronary heart disease incidence using data from 154,012 participants in 31 cohorts
Keywords: Cohort Studies; Computer Simulation; Coronary Disease; Data Interpretation, Statistical; Female; Fibrinogen; Humans; Male; Meta-Analysis as Topic; Models, Statistical

Variants in ZFHX3 are associated with atrial fibrillation in individuals of European ancestry. - Benjamin, Emelia J; Rice, Kenneth M; Arking, Dan E; Pfeufer, Arne; van Noord, Charlotte; Smith, Albert V; Schnabel, Renate B; Bis, Joshua C; Boerwinkle, Eric; Sinner, Moritz F; Dehghan, Abbas; Lubitz, Steven A; et al. (Nat Genet, 2009)
We conducted meta-analyses of genome-wide association studies for atrial fibrillation (AF) in participants from five community-based cohorts. Meta-analyses of 896 prevalent (15,768 referents) and 2,517 incident (21,337 referents) AF cases identified a new locus for AF (ZFHX3, rs2106261, risk ratio RR = 1.19; P = 2.3 x 10(-7)). We replicated this association in an independent cohort from the German AF Network (odds ratio = 1.44; P = 1.6 x 10(-11); combined RR = 1.25; combined P = 1.8 x 10(-15)).
Keywords: Atrial Fibrillation; Chromosomes, Human, Pair 16; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Homeodomain Proteins; Humans; Meta-Analysis as Topic; Mutation; Polymorphism, Single Nucleotide; Reproducibility of Results

Association analyses of 249,796 individuals reveal 18 new loci associated with body mass index. - Speliotes, Elizabeth K; Willer, Cristen J; Berndt, Sonja I; Monda, Keri L; Thorleifsson, Gudmar; Jackson, Anne U; Lango Allen, Hana; Lindgren, Cecilia M; Luan, Jian'an; Mägi, Reedik; Randall, Joshua C; Vedantam, Sailaja; et al. (Nat Genet, 2010)
Obesity is globally prevalent and highly heritable, but its underlying genetic factors remain largely elusive. To identify genetic loci for obesity susceptibility, we examined associations between body mass index and ∼ 2.8 million SNPs in up to 123,865 individuals with targeted follow up of 42 SNPs in up to 125,931 additional individuals. We confirmed 14 known obesity susceptibility loci and identified 18 new loci associated with body mass index (P < 5 × 10⁻⁸), one of which includes a copy number variant near GPRC5B. Some loci (at MC4R, POMC, SH2B1 and BDNF) map near key hypothalamic regulators of energy balance, and one of these loci is near GIPR, an incretin receptor. Furthermore, genes in other newly associated loci may provide new insights into human body weight regulation.
Keywords: Body Height; Body Mass Index; Body Size; Body Weight; Chromosome Mapping; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Obesity; Polymorphism, Single Nucleotide

Associations between renal duplex parameters and adverse cardiovascular events in the elderly: a prospective cohort study. - Pearce, Jeffrey D; Craven, Timothy E; Edwards, Matthew S; Corriere, Matthew A; Crutchley, Teresa A; Fleming, Shawn H; Hansen, Kimberley J (Am J Kidney Dis, 2010)
BACKGROUND: Atherosclerotic renovascular disease is associated with an increased risk of cardiovascular disease (CVD) events. This study examines associations between Doppler-derived parameters from the renal artery and renal parenchyma and all-cause mortality and fatal and nonfatal CVD events in a cohort of elderly Americans. STUDY DESIGN: Cohort study. SETTING: A subset of participants from the Cardiovascular Health Study (CHS). Through an ancillary study, 870 (70% recruitment) Forsyth County, NC, CHS participants consented to undergo renal duplex sonography to define the prevalence of renovascular disease in the elderly, resulting in 726 (36% men; mean age, 77 years) technically adequate complete studies included in this investigation. PREDICTOR: Renal duplex sonography-derived Doppler signals from the main renal arteries and renal parenchyma. Spectral analysis from Doppler-shifted frequencies and angle of insonation were used to estimate renal artery peak systolic and end diastolic velocity (both in meters per second). Color Doppler was used to identify the corticomedullary junction. Using a 3-mm Doppler sample, the parenchymal peak systolic and end diastolic frequency shift (both in kilohertz) were obtained. Resistive index was calculated as (1 - [end diastolic frequency shift/peak systolic frequency shift]) using Doppler samples from the hilar arteries of the left or right kidney with the higher main renal artery peak systolic velocity. OUTCOMES & MEASUREMENTS: Proportional hazard regression analysis was used to determine associations between renal duplex sonography-derived Doppler signals and CVD events and all-cause mortality adjusted for accepted cardiovascular risk factors. Index CVD outcomes were defined as coronary events (angina, myocardial infarction, and coronary artery bypass grafting/percutaneous coronary intervention), cerebrovascular events (stroke or transient ischemic attack), and any CVD event (angina, congestive heart failure, myocardial infarction, stroke, transient ischemic attack, and coronary artery bypass grafting [CABG]/percutaneous transluminal coronary intervention [PTCI]). RESULTS: During follow-up, 221 deaths (31%), 229 CVD events (32%), 122 coronary events (17%), and 92 cerebrovascular events (13%) were observed. Renal duplex sonography-derived Doppler signals from the renal parenchyma were associated independently with all-cause mortality and CVD outcomes. In particular, increased parenchymal end diastolic frequency shift was associated significantly with any CVD event (HR, 0.73; 95% CI, 0.62-0.87; P < 0.001). Marginally significant associations were observed between increases in parenchymal end diastolic frequency shift and decreased risk of death (HR, 0.86; 95% CI, 0.73-1.00; P = 0.06) and decreased risk of cerebrovascular events (HR, 0.78; 95% CI, 0.61-1.01; P = 0.06). Parenchymal end diastolic frequency shift was not significantly predictive of coronary events (HR, 0.84; 95% CI, 0.67-1.06; P = 0.1). LIMITATIONS: CHS participants showed a "healthy cohort" effect that may underestimate the rate of CVD events in the general population. CONCLUSION: Renal duplex sonographic Doppler signals from the renal parenchyma showed significant associations with subsequent CVD events after controlling for other significant risk factors. In particular, a standard deviation increase in parenchymal end diastolic frequency shift was associated with 27% risk reduction in any CVD event.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Female; Humans; Kidney Diseases; Male; Renal Artery; Risk Factors; Ultrasonography, Doppler, Duplex

Bayesian methods for meta-analysis of causal relationships estimated using genetic instrumental variables. - Burgess, Stephen; Thompson, Simon G; Burgess, S; Thompson, S G; Andrews, G; Samani, N J; Hall, A; Whincup, P; Morris, R; Lawlor, D A; Davey Smith, G; Timpson, N; et al. (Stat Med, 2010)
Genetic markers can be used as instrumental variables, in an analogous way to randomization in a clinical trial, to estimate the causal relationship between a phenotype and an outcome variable. Our purpose is to extend the existing methods for such Mendelian randomization studies to the context of multiple genetic markers measured in multiple studies, based on the analysis of individual participant data. First, for a single genetic marker in one study, we show that the usual ratio of coefficients approach can be reformulated as a regression with heterogeneous error in the explanatory variable. This can be implemented using a Bayesian approach, which is next extended to include multiple genetic markers. We then propose a hierarchical model for undertaking a meta-analysis of multiple studies, in which it is not necessary that the same genetic markers are measured in each study. This provides an overall estimate of the causal relationship between the phenotype and the outcome, and an assessment of its heterogeneity across studies. As an example, we estimate the causal relationship of blood concentrations of C-reactive protein on fibrinogen levels using data from 11 studies. These methods provide a flexible framework for efficient estimation of causal relationships derived from multiple studies. Issues discussed include weak instrument bias, analysis of binary outcome data such as disease risk, missing genetic data, and the use of haplotypes.
Keywords: Bayes Theorem; Biostatistics; C-Reactive Protein; Fibrinogen; Genetic Markers; Humans; Meta-Analysis as Topic; Models, Statistical; Phenotype; Polymorphism, Single Nucleotide

Biological, clinical and population relevance of 95 loci for blood lipids. - Teslovich, Tanya M; Musunuru, Kiran; Smith, Albert V; Edmondson, Andrew C; Stylianou, Ioannis M; Koseki, Masahiro; Pirruccello, James P; Ripatti, Samuli; Chasman, Daniel I; Willer, Cristen J; Johansen, Christopher T; Fouchier, Sigrid W; et al. (Nature, 2010)
Plasma concentrations of total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides are among the most important risk factors for coronary artery disease (CAD) and are targets for therapeutic intervention. We screened the genome for common variants associated with plasma lipids in >100,000 individuals of European ancestry. Here we report 95 significantly associated loci (P < 5 x 10(-8)), with 59 showing genome-wide significant association with lipid traits for the first time. The newly reported associations include single nucleotide polymorphisms (SNPs) near known lipid regulators (for example, CYP7A1, NPC1L1 and SCARB1) as well as in scores of loci not previously implicated in lipoprotein metabolism. The 95 loci contribute not only to normal variation in lipid traits but also to extreme lipid phenotypes and have an impact on lipid traits in three non-European populations (East Asians, South Asians and African Americans). Our results identify several novel loci associated with plasma lipids that are also associated with CAD. Finally, we validated three of the novel genes-GALNT2, PPP1R3B and TTC39B-with experiments in mouse models. Taken together, our findings provide the foundation to develop a broader biological understanding of lipoprotein metabolism and to identify new therapeutic opportunities for the prevention of CAD.
Keywords: African Americans; Animals; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Europe; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Lipid Metabolism; Lipids; Liver; Male; Mice; N-Acetylgalactosaminyltransferases; Phenotype; Polymorphism, Single Nucleotide; Protein Phosphatase 1; Reproducibility of Results; Triglycerides

Candidate gene association resource (CARe): design, methods, and proof of concept. - Musunuru, Kiran; Lettre, Guillaume; Young, Taylor; Farlow, Deborah N; Pirruccello, James P; Ejebe, Kenechi G; Keating, Brendan J; Yang, Qiong; Chen, Ming-Huei; Lapchyk, Nina; Crenshaw, Andrew; Ziaugra, Liuda; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: The National Heart, Lung, and Blood Institute's Candidate Gene Association Resource (CARe), a planned cross-cohort analysis of genetic variation in cardiovascular, pulmonary, hematologic, and sleep-related traits, comprises >40,000 participants representing 4 ethnic groups in 9 community-based cohorts. The goals of CARe include the discovery of new variants associated with traits using a candidate gene approach and the discovery of new variants using the genome-wide association mapping approach specifically in African Americans. METHODS AND RESULTS: CARe has assembled DNA samples for >40,000 individuals self-identified as European American, African American, Hispanic, or Chinese American, with accompanying data on hundreds of phenotypes that have been standardized and deposited in the CARe Phenotype Database. All participants were genotyped for 7 single-nucleotide polymorphisms (SNPs) selected based on prior association evidence. We performed association analyses relating each of these SNPs to lipid traits, stratified by sex and ethnicity, and adjusted for age and age squared. In at least 2 of the ethnic groups, SNPs near CETP, LIPC, and LPL strongly replicated for association with high-density lipoprotein cholesterol concentrations, PCSK9 with low-density lipoprotein cholesterol levels, and LPL and APOA5 with serum triglycerides. Notably, some SNPs showed varying effect sizes and significance of association in different ethnic groups. CONCLUSIONS: The CARe Pilot Study validates the operational framework for phenotype collection, SNP genotyping, and analytic pipeline of the CARe project and validates the planned candidate gene study of approximately 2000 biological candidate loci in all participants and genome-wide association study in approximately 8000 African American participants. CARe will serve as a valuable resource for the scientific community.
Keywords: African Americans; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Databases, Genetic; European Continental Ancestry Group; Genetic Association Studies; Genotype; Humans; Phenotype; Pilot Projects; Polymorphism, Single Nucleotide; Research Design; Triglycerides

Common genetic determinants of vitamin D insufficiency: a genome-wide association study. - Wang, Thomas J; Zhang, Feng; Richards, J Brent; Kestenbaum, Bryan; van Meurs, Joyce B; Berry, Diane; Kiel, Douglas P; Streeten, Elizabeth A; Ohlsson, Claes; Koller, Daniel L; Peltonen, Leena; Cooper, Jason D; et al. (Lancet, 2010)
BACKGROUND: Vitamin D is crucial for maintenance of musculoskeletal health, and might also have a role in extraskeletal tissues. Determinants of circulating 25-hydroxyvitamin D concentrations include sun exposure and diet, but high heritability suggests that genetic factors could also play a part. We aimed to identify common genetic variants affecting vitamin D concentrations and risk of insufficiency. METHODS: We undertook a genome-wide association study of 25-hydroxyvitamin D concentrations in 33 996 individuals of European descent from 15 cohorts. Five epidemiological cohorts were designated as discovery cohorts (n=16 125), five as in-silico replication cohorts (n=9367), and five as de-novo replication cohorts (n=8504). 25-hydroxyvitamin D concentrations were measured by radioimmunoassay, chemiluminescent assay, ELISA, or mass spectrometry. Vitamin D insufficiency was defined as concentrations lower than 75 nmol/L or 50 nmol/L. We combined results of genome-wide analyses across cohorts using Z-score-weighted meta-analysis. Genotype scores were constructed for confirmed variants. FINDINGS: Variants at three loci reached genome-wide significance in discovery cohorts for association with 25-hydroxyvitamin D concentrations, and were confirmed in replication cohorts: 4p12 (overall p=1.9x10(-109) for rs2282679, in GC); 11q12 (p=2.1x10(-27) for rs12785878, near DHCR7); and 11p15 (p=3.3x10(-20) for rs10741657, near CYP2R1). Variants at an additional locus (20q13, CYP24A1) were genome-wide significant in the pooled sample (p=6.0x10(-10) for rs6013897). Participants with a genotype score (combining the three confirmed variants) in the highest quartile were at increased risk of having 25-hydroxyvitamin D concentrations lower than 75 nmol/L (OR 2.47, 95% CI 2.20-2.78, p=2.3x10(-48)) or lower than 50 nmol/L (1.92, 1.70-2.16, p=1.0x10(-26)) compared with those in the lowest quartile. INTERPRETATION: Variants near genes involved in cholesterol synthesis, hydroxylation, and vitamin D transport affect vitamin D status. Genetic variation at these loci identifies individuals who have substantially raised risk of vitamin D insufficiency. FUNDING: Full funding sources listed at end of paper (see Acknowledgments).
Keywords: Canada; Chromosomes, Human, Pair 11; Chromosomes, Human, Pair 4; Cohort Studies; Dietary Supplements; Europe; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Homozygote; Humans; Immunoassay; International Cooperation; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Seasons; United States; Vitamin D; Vitamin D Deficiency

Common variants in 22 loci are associated with QRS duration and cardiac ventricular conduction. - Sotoodehnia, Nona; Isaacs, Aaron; de Bakker, Paul I W; Dörr, Marcus; Newton-Cheh, Christopher; Nolte, Ilja M; van der Harst, Pim; Müller, Martina; Eijgelsheim, Mark; Alonso, Alvaro; Hicks, Andrew A; Padmanabhan, Sandosh; et al. (Nat Genet, 2010)
The QRS interval, from the beginning of the Q wave to the end of the S wave on an electrocardiogram, reflects ventricular depolarization and conduction time and is a risk factor for mortality, sudden death and heart failure. We performed a genome-wide association meta-analysis in 40,407 individuals of European descent from 14 studies, with further genotyping in 7,170 additional Europeans, and we identified 22 loci associated with QRS duration (P < 5 × 10(-8)). These loci map in or near genes in pathways with established roles in ventricular conduction such as sodium channels, transcription factors and calcium-handling proteins, but also point to previously unidentified biologic processes, such as kinase inhibitors and genes related to tumorigenesis. We demonstrate that SCN10A, a candidate gene at the most significantly associated locus in this study, is expressed in the mouse ventricular conduction system, and treatment with a selective SCN10A blocker prolongs QRS duration. These findings extend our current knowledge of ventricular depolarization and conduction.
Keywords: Animals; Animals, Newborn; Chromosomes, Human; Computational Biology; Electrocardiography; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Mice; Mice, Transgenic; Models, Animal; Myocytes, Cardiac; NAV1.8 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sodium Channels

Common variants in KCNN3 are associated with lone atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Glazer, Nicole L; Pfeufer, Arne; Alonso, Alvaro; Chung, Mina K; Sinner, Moritz F; de Bakker, Paul I W; Mueller, Martina; Lubitz, Steven A; Fox, Ervin; Darbar, Dawood; et al. (Nat Genet, 2010)
Atrial fibrillation (AF) is the most common sustained arrhythmia. Previous studies have identified several genetic loci associated with typical AF. We sought to identify common genetic variants underlying lone AF. This condition affects a subset of individuals without overt heart disease and with an increased heritability of AF. We report a meta-analysis of genome-wide association studies conducted using 1,335 individuals with lone AF (cases) and 12,844 unaffected individuals (referents). Cases were obtained from the German AF Network, Heart and Vascular Health Study, the Atherosclerosis Risk in Communities Study, the Cleveland Clinic and Massachusetts General Hospital. We identified an association on chromosome 1q21 to lone AF (rs13376333, adjusted odds ratio = 1.56; P = 6.3 x 10(-12)), and we replicated this association in two independent cohorts with lone AF (overall combined odds ratio = 1.52, 95% CI 1.40-1.64; P = 1.83 x 10(-21)). rs13376333 is intronic to KCNN3, which encodes a potassium channel protein involved in atrial repolarization.
Keywords: Adolescent; Adult; Aged; Atrial Fibrillation; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Introns; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Small-Conductance Calcium-Activated Potassium Channels; Young Adult

C-reactive protein concentration and risk of coronary heart disease, stroke, and mortality: an individual participant meta-analysis. - Kaptoge, Stephen; Di Angelantonio, Emanuele; Lowe, Gordon; Pepys, Mark B; Thompson, Simon G; Collins, Rory; Danesh, John (Lancet, 2010)
BACKGROUND: Associations of C-reactive protein (CRP) concentration with risk of major diseases can best be assessed by long-term prospective follow-up of large numbers of people. We assessed the associations of CRP concentration with risk of vascular and non-vascular outcomes under different circumstances. METHODS: We meta-analysed individual records of 160 309 people without a history of vascular disease (ie, 1.31 million person-years at risk, 27 769 fatal or non-fatal disease outcomes) from 54 long-term prospective studies. Within-study regression analyses were adjusted for within-person variation in risk factor levels. RESULTS: Log(e) CRP concentration was linearly associated with several conventional risk factors and inflammatory markers, and nearly log-linearly with the risk of ischaemic vascular disease and non-vascular mortality. Risk ratios (RRs) for coronary heart disease per 1-SD higher log(e) CRP concentration (three-fold higher) were 1.63 (95% CI 1.51-1.76) when initially adjusted for age and sex only, and 1.37 (1.27-1.48) when adjusted further for conventional risk factors; 1.44 (1.32-1.57) and 1.27 (1.15-1.40) for ischaemic stroke; 1.71 (1.53-1.91) and 1.55 (1.37-1.76) for vascular mortality; and 1.55 (1.41-1.69) and 1.54 (1.40-1.68) for non-vascular mortality. RRs were largely unchanged after exclusion of smokers or initial follow-up. After further adjustment for fibrinogen, the corresponding RRs were 1.23 (1.07-1.42) for coronary heart disease; 1.32 (1.18-1.49) for ischaemic stroke; 1.34 (1.18-1.52) for vascular mortality; and 1.34 (1.20-1.50) for non-vascular mortality. INTERPRETATION: CRP concentration has continuous associations with the risk of coronary heart disease, ischaemic stroke, vascular mortality, and death from several cancers and lung disease that are each of broadly similar size. The relevance of CRP to such a range of disorders is unclear. Associations with ischaemic vascular disease depend considerably on conventional risk factors and other markers of inflammation. FUNDING: British Heart Foundation, UK Medical Research Council, BUPA Foundation, and GlaxoSmithKline.
Keywords: Alcohol Drinking; Biomarkers; Blood Pressure; Body Mass Index; C-Reactive Protein; Cholesterol; Coronary Disease; Databases, Factual; Diabetes Mellitus; Female; Fibrinogen; Humans; Interleukin-6; Leukocyte Count; Lung Diseases; Male; Middle Aged; Motor Activity; Neoplasms; Regression Analysis; Risk Assessment; Risk Factors; Serum Albumin; Sex Factors; Smoking; Stroke; Triglycerides

Diabetes mellitus, fasting blood glucose concentration, and risk of vascular disease: a collaborative meta-analysis of 102 prospective studies. - Sarwar, N; Gao, P; Seshasai, S R Kondapally; Gobin, R; Kaptoge, S; Di Angelantonio, E; Ingelsson, E; Lawlor, D A; Selvin, E; Stampfer, M; Stehouwer, C D A; Lewington, S; et al. (Lancet, 2010)
BACKGROUND: Uncertainties persist about the magnitude of associations of diabetes mellitus and fasting glucose concentration with risk of coronary heart disease and major stroke subtypes. We aimed to quantify these associations for a wide range of circumstances. METHODS: We undertook a meta-analysis of individual records of diabetes, fasting blood glucose concentration, and other risk factors in people without initial vascular disease from studies in the Emerging Risk Factors Collaboration. We combined within-study regressions that were adjusted for age, sex, smoking, systolic blood pressure, and body-mass index to calculate hazard ratios (HRs) for vascular disease. FINDINGS: Analyses included data for 698 782 people (52 765 non-fatal or fatal vascular outcomes; 8.49 million person-years at risk) from 102 prospective studies. Adjusted HRs with diabetes were: 2.00 (95% CI 1.83-2.19) for coronary heart disease; 2.27 (1.95-2.65) for ischaemic stroke; 1.56 (1.19-2.05) for haemorrhagic stroke; 1.84 (1.59-2.13) for unclassified stroke; and 1.73 (1.51-1.98) for the aggregate of other vascular deaths. HRs did not change appreciably after further adjustment for lipid, inflammatory, or renal markers. HRs for coronary heart disease were higher in women than in men, at 40-59 years than at 70 years and older, and with fatal than with non-fatal disease. At an adult population-wide prevalence of 10%, diabetes was estimated to account for 11% (10-12%) of vascular deaths. Fasting blood glucose concentration was non-linearly related to vascular risk, with no significant associations between 3.90 mmol/L and 5.59 mmol/L. Compared with fasting blood glucose concentrations of 3.90-5.59 mmol/L, HRs for coronary heart disease were: 1.07 (0.97-1.18) for lower than 3.90 mmol/L; 1.11 (1.04-1.18) for 5.60-6.09 mmol/L; and 1.17 (1.08-1.26) for 6.10-6.99 mmol/L. In people without a history of diabetes, information about fasting blood glucose concentration or impaired fasting glucose status did not significantly improve metrics of vascular disease prediction when added to information about several conventional risk factors. INTERPRETATION: Diabetes confers about a two-fold excess risk for a wide range of vascular diseases, independently from other conventional risk factors. In people without diabetes, fasting blood glucose concentration is modestly and non-linearly associated with risk of vascular disease. FUNDING: British Heart Foundation, UK Medical Research Council, and Pfizer.
Keywords: Adult; Aged; Blood Glucose; Coronary Disease; Diabetes Complications; Diabetes Mellitus; Fasting; Female; Humans; Male; Middle Aged; Risk Factors; Stroke

European ancestry as a risk factor for atrial fibrillation in African Americans. - Marcus, Gregory M; Alonso, Alvaro; Peralta, Carmen A; Lettre, Guillaume; Vittinghoff, Eric; Lubitz, Steven A; Fox, Ervin R; Levitzky, Yamini S; Mehra, Reena; Kerr, Kathleen F; Deo, Rajat; Sotoodehnia, Nona; et al. (Circulation, 2010)
BACKGROUND: Despite a higher burden of standard atrial fibrillation (AF) risk factors, African Americans have a lower risk of AF than whites. It is unknown whether the higher risk is due to genetic or environmental factors. Because African Americans have varying degrees of European ancestry, we sought to test the hypothesis that European ancestry is an independent risk factor for AF. METHODS AND RESULTS: We studied whites (n=4543) and African Americans (n=822) in the Cardiovascular Health Study (CHS) and whites (n=10 902) and African Americans (n=3517) in the Atherosclerosis Risk in Communities (ARIC) Study (n=3517). Percent European ancestry in African Americans was estimated with 1747 ancestry informative markers from the Illumina custom ITMAT-Broad-CARe array. Among African Americans without baseline AF, 120 of 804 CHS participants and 181 of 3517 ARIC participants developed incident AF. A meta-analysis from the 2 studies revealed that every 10% increase in European ancestry increased the risk of AF by 13% (hazard ratio, 1.13; 95% confidence interval, 1.03 to 1.23; P=0.007). After adjustment for potential confounders, European ancestry remained a predictor of incident AF in each cohort alone, with a combined estimated hazard ratio for each 10% increase in European ancestry of 1.17 (95% confidence interval, 1.07 to 1.29; P=0.001). A second analysis using 3192 ancestry informative markers from a genome-wide Affymetrix 6.0 array in ARIC African Americans yielded similar results. CONCLUSIONS: European ancestry predicted risk of incident AF. Our study suggests that investigating genetic variants contributing to differential AF risk in individuals of African versus European ancestry will be informative.
Keywords: African Americans; Aged; Atrial Fibrillation; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Risk Factors

Four novel Loci (19q13, 6q24, 12q24, and 5q14) influence the microcirculation in vivo. - Ikram, M Kamran; Sim, Xueling; Xueling, Sim; Jensen, Richard A; Cotch, Mary Frances; Hewitt, Alex W; Ikram, M Arfan; Wang, Jie Jin; Klein, Ronald; Klein, Barbara E K; Breteler, Monique M B; Cheung, Ning; et al. (PLoS Genet, 2010)
There is increasing evidence that the microcirculation plays an important role in the pathogenesis of cardiovascular diseases. Changes in retinal vascular caliber reflect early microvascular disease and predict incident cardiovascular events. We performed a genome-wide association study to identify genetic variants associated with retinal vascular caliber. We analyzed data from four population-based discovery cohorts with 15,358 unrelated Caucasian individuals, who are members of the Cohort for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, and replicated findings in four independent Caucasian cohorts (n  =  6,652). All participants had retinal photography and retinal arteriolar and venular caliber measured from computer software. In the discovery cohorts, 179 single nucleotide polymorphisms (SNP) spread across five loci were significantly associated (p<5.0×10(-8)) with retinal venular caliber, but none showed association with arteriolar caliber. Collectively, these five loci explain 1.0%-3.2% of the variation in retinal venular caliber. Four out of these five loci were confirmed in independent replication samples. In the combined analyses, the top SNPs at each locus were: rs2287921 (19q13; p  =  1.61×10(-25), within the RASIP1 locus), rs225717 (6q24; p = 1.25×10(-16), adjacent to the VTA1 and NMBR loci), rs10774625 (12q24; p  =  2.15×10(-13), in the region of ATXN2,SH2B3 and PTPN11 loci), and rs17421627 (5q14; p = 7.32×10(-16), adjacent to the MEF2C locus). In two independent samples, locus 12q24 was also associated with coronary heart disease and hypertension. Our population-based genome-wide association study demonstrates four novel loci associated with retinal venular caliber, an endophenotype of the microcirculation associated with clinical cardiovascular disease. These data provide further insights into the contribution and biological mechanisms of microcirculatory changes that underlie cardiovascular disease.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Child; Child, Preschool; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 19; Chromosomes, Human, Pair 5; Chromosomes, Human, Pair 6; Cohort Studies; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Microcirculation; Middle Aged; Polymorphism, Single Nucleotide; Retinal Vessels; Young Adult

Genetic ancestry in lung-function predictions. - Kumar, Rajesh; Seibold, Max A; Aldrich, Melinda C; Williams, L Keoki; Reiner, Alex P; Colangelo, Laura; Galanter, Joshua; Gignoux, Christopher; Hu, Donglei; Sen, Saunak; Choudhry, Shweta; Peterson, Edward L; et al. (N Engl J Med, 2010)
BACKGROUND: Self-identified race or ethnic group is used to determine normal reference standards in the prediction of pulmonary function. We conducted a study to determine whether the genetically determined percentage of African ancestry is associated with lung function and whether its use could improve predictions of lung function among persons who identified themselves as African American. METHODS: We assessed the ancestry of 777 participants self-identified as African American in the Coronary Artery Risk Development in Young Adults (CARDIA) study and evaluated the relation between pulmonary function and ancestry by means of linear regression. We performed similar analyses of data for two independent cohorts of subjects identifying themselves as African American: 813 participants in the Health, Aging, and Body Composition (HABC) study and 579 participants in the Cardiovascular Health Study (CHS). We compared the fit of two types of models to lung-function measurements: models based on the covariates used in standard prediction equations and models incorporating ancestry. We also evaluated the effect of the ancestry-based models on the classification of disease severity in two asthma-study populations. RESULTS: African ancestry was inversely related to forced expiratory volume in 1 second (FEV(1)) and forced vital capacity in the CARDIA cohort. These relations were also seen in the HABC and CHS cohorts. In predicting lung function, the ancestry-based model fit the data better than standard models. Ancestry-based models resulted in the reclassification of asthma severity (based on the percentage of the predicted FEV(1)) in 4 to 5% of participants. CONCLUSIONS: Current predictive equations, which rely on self-identified race alone, may misestimate lung function among subjects who identify themselves as African American. Incorporating ancestry into normative equations may improve lung-function estimates and more accurately categorize disease severity. (Funded by the National Institutes of Health and others.)
Keywords: Adolescent; Adult; African Americans; Aged; Aged, 80 and over; Female; Forced Expiratory Volume; Genetic Markers; Genotype; Humans; Linear Models; Male; Middle Aged; Oligonucleotide Array Sequence Analysis; Reference Values; Respiratory Function Tests; Vital Capacity; Young Adult

Genome-wide analysis of genetic loci associated with Alzheimer disease. - Seshadri, Sudha; Fitzpatrick, Annette L; Ikram, M Arfan; DeStefano, Anita L; Gudnason, Vilmundur; Boada, Merce; Bis, Joshua C; Smith, Albert V; Carassquillo, Minerva M; Lambert, Jean Charles; Harold, Denise; Schrijvers, Elisabeth M C; et al. (JAMA, 2010)
CONTEXT: Genome-wide association studies (GWAS) have recently identified CLU, PICALM, and CR1 as novel genes for late-onset Alzheimer disease (AD). OBJECTIVES: To identify and strengthen additional loci associated with AD and confirm these in an independent sample and to examine the contribution of recently identified genes to AD risk prediction in a 3-stage analysis of new and previously published GWAS on more than 35,000 persons (8371 AD cases). DESIGN, SETTING, AND PARTICIPANTS: In stage 1, we identified strong genetic associations (P < 10(-3)) in a sample of 3006 AD cases and 14,642 controls by combining new data from the population-based Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (1367 AD cases [973 incident]) with previously reported results from the Translational Genomics Research Institute and the Mayo AD GWAS. We identified 2708 single-nucleotide polymorphisms (SNPs) with P < 10(-3). In stage 2, we pooled results for these SNPs with the European AD Initiative (2032 cases and 5328 controls) to identify 38 SNPs (10 loci) with P < 10(-5). In stage 3, we combined data for these 10 loci with data from the Genetic and Environmental Risk in AD consortium (3333 cases and 6995 controls) to identify 4 SNPs with P < 1.7x10(-8). These 4 SNPs were replicated in an independent Spanish sample (1140 AD cases and 1209 controls). Genome-wide association analyses were completed in 2007-2008 and the meta-analyses and replication in 2009. MAIN OUTCOME MEASURE: Presence of Alzheimer disease. RESULTS: Two loci were identified to have genome-wide significance for the first time: rs744373 near BIN1 (odds ratio [OR],1.13; 95% confidence interval [CI],1.06-1.21 per copy of the minor allele; P = 1.59x10(-11)) and rs597668 near EXOC3L2/BLOC1S3/MARK4 (OR, 1.18; 95% CI, 1.07-1.29; P = 6.45x10(-9)). Associations of these 2 loci plus the previously identified loci CLU and PICALM with AD were confirmed in the Spanish sample (P < .05). However, although CLU and PICALM were confirmed to be associated with AD in this independent sample, they did not improve the ability of a model that included age, sex, and APOE to predict incident AD (improvement in area under the receiver operating characteristic curve from 0.847 to 0.849 in the Rotterdam Study and 0.702 to 0.705 in the Cardiovascular Health Study). CONCLUSIONS: Two genetic loci for AD were found for the first time to reach genome-wide statistical significance. These findings were replicated in an independent population. Two recently reported associations were also confirmed. These loci did not improve AD risk prediction. While not clinically useful, they may implicate biological pathways useful for future research.
Keywords: Age of Onset; Aged; Alzheimer Disease; Case-Control Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Odds Ratio; Polymorphism, Single Nucleotide

Genome-wide association analysis identifies multiple loci related to resting heart rate. - Eijgelsheim, Mark; Newton-Cheh, Christopher; Sotoodehnia, Nona; de Bakker, Paul I W; Müller, Martina; Morrison, Alanna C; Smith, Albert V; Isaacs, Aaron; Sanna, Serena; Dörr, Marcus; Navarro, Pau; Fuchsberger, Christian; et al. (Hum Mol Genet, 2010)
Higher resting heart rate is associated with increased cardiovascular disease and mortality risk. Though heritable factors play a substantial role in population variation, little is known about specific genetic determinants. This knowledge can impact clinical care by identifying novel factors that influence pathologic heart rate states, modulate heart rate through cardiac structure and function or by improving our understanding of the physiology of heart rate regulation. To identify common genetic variants associated with heart rate, we performed a meta-analysis of 15 genome-wide association studies (GWAS), including 38,991 subjects of European ancestry, estimating the association between age-, sex- and body mass-adjusted RR interval (inverse heart rate) and approximately 2.5 million markers. Results with P < 5 × 10(-8) were considered genome-wide significant. We constructed regression models with multiple markers to assess whether results at less stringent thresholds were likely to be truly associated with RR interval. We identified six novel associations with resting heart rate at six loci: 6q22 near GJA1; 14q12 near MYH7; 12p12 near SOX5, c12orf67, BCAT1, LRMP and CASC1; 6q22 near SLC35F1, PLN and c6orf204; 7q22 near SLC12A9 and UfSp1; and 11q12 near FADS1. Associations at 6q22 400 kb away from GJA1, at 14q12 MYH6 and at 1q32 near CD34 identified in previously published GWAS were confirmed. In aggregate, these variants explain approximately 0.7% of RR interval variance. A multivariant regression model including 20 variants with P < 10(-5) increased the explained variance to 1.6%, suggesting that some loci falling short of genome-wide significance are likely truly associated. Future research is warranted to elucidate underlying mechanisms that may impact clinical care.
Keywords: Adult; Aged; Base Pairing; Cohort Studies; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Heart Rate; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Rest

Genome-wide association identifies multiple ulcerative colitis susceptibility loci. - McGovern, Dermot P B; Gardet, Agnès; Törkvist, Leif; Goyette, Philippe; Essers, Jonah; Taylor, Kent D; Neale, Benjamin M; Ong, Rick T H; Lagacé, Caroline; Li, Chun; Green, Todd; Stevens, Christine R; et al. (Nat Genet, 2010)
Ulcerative colitis is a chronic, relapsing inflammatory condition of the gastrointestinal tract with a complex genetic and environmental etiology. In an effort to identify genetic variation underlying ulcerative colitis risk, we present two distinct genome-wide association studies of ulcerative colitis and their joint analysis with a previously published scan, comprising, in aggregate, 2,693 individuals with ulcerative colitis and 6,791 control subjects. Fifty-nine SNPs from 14 independent loci attained an association significance of P < 10(-5). Seven of these loci exceeded genome-wide significance (P < 5 x 10(-8)). After testing an independent cohort of 2,009 cases of ulcerative colitis and 1,580 controls, we identified 13 loci that were significantly associated with ulcerative colitis (P < 5 x 10(-8)), including the immunoglobulin receptor gene FCGR2A, 5p15, 2p16 and ORMDL3 (orosomucoid1-like 3). We confirmed association with 14 previously identified ulcerative colitis susceptibility loci, and an analysis of acknowledged Crohn's disease loci showed that roughly half of the known Crohn's disease associations are shared with ulcerative colitis. These data implicate approximately 30 loci in ulcerative colitis, thereby providing insight into disease pathogenesis.
Keywords: Colitis, Ulcerative; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Membrane Proteins; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Receptors, IgG

Genome-wide association studies of MRI-defined brain infarcts: meta-analysis from the CHARGE Consortium. - Debette, Stephanie; Bis, Joshua C; Fornage, Myriam; Schmidt, Helena; Ikram, M Arfan; Sigurdsson, Sigurdur; Heiss, Gerardo; Struchalin, Maksim; Smith, Albert V; van der Lugt, Aad; DeCarli, Charles; Lumley, Thomas; et al. (Stroke, 2010)
BACKGROUND AND PURPOSE: Previous studies examining genetic associations with MRI-defined brain infarct have yielded inconsistent findings. We investigated genetic variation underlying covert MRI infarct in persons without histories of transient ischemic attack or stroke. We performed meta-analysis of genome-wide association studies of white participants in 6 studies comprising the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Using 2.2 million genotyped and imputed single nucleotide polymorphisms, each study performed cross-sectional genome-wide association analysis of MRI infarct using age- and sex-adjusted logistic regression models. Study-specific findings were combined in an inverse-variance-weighted meta-analysis, including 9401 participants with mean age 69.7 (19.4% of whom had >or=1 MRI infarct). RESULTS: The most significant association was found with rs2208454 (minor allele frequency, 20%), located in intron 3 of MACRO domain containing 2 gene and in the downstream region of fibronectin leucine-rich transmembrane protein 3 gene. Each copy of the minor allele was associated with lower risk of MRI infarcts (odds ratio, 0.76; 95% confidence interval, 0.68-0.84; P=4.64x10(-7)). Highly suggestive associations (P<1.0x10(-5)) were also found for 22 other single nucleotide polymorphisms in linkage disequilibrium (r(2)>0.64) with rs2208454. The association with rs2208454 did not replicate in independent samples of 1822 white and 644 black participants, although 4 single nucleotide polymorphisms within 200 kb from rs2208454 were associated with MRI infarcts in the black population sample. CONCLUSIONS: This first community-based, genome-wide association study on covert MRI infarcts uncovered novel associations. Although replication of the association with top single nucleotide polymorphisms failed, possibly because of insufficient power, results in the black population sample are encouraging, and further efforts at replication are needed.
Keywords: African Americans; Aged; Brain; Brain Infarction; Cohort Studies; DNA Mutational Analysis; Female; Gene Frequency; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genetic Variation; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Magnetic Resonance Imaging; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies

Genome-wide association studies of serum magnesium, potassium, and sodium concentrations identify six Loci influencing serum magnesium levels. - Meyer, Tamra E; Verwoert, Germaine C; Hwang, Shih-Jen; Glazer, Nicole L; Smith, Albert V; van Rooij, Frank J A; Ehret, Georg B; Boerwinkle, Eric; Felix, Janine F; Leak, Tennille S; Harris, Tamara B; Yang, Qiong; et al. (PLoS Genet, 2010)
Magnesium, potassium, and sodium, cations commonly measured in serum, are involved in many physiological processes including energy metabolism, nerve and muscle function, signal transduction, and fluid and blood pressure regulation. To evaluate the contribution of common genetic variation to normal physiologic variation in serum concentrations of these cations, we conducted genome-wide association studies of serum magnesium, potassium, and sodium concentrations using approximately 2.5 million genotyped and imputed common single nucleotide polymorphisms (SNPs) in 15,366 participants of European descent from the international CHARGE Consortium. Study-specific results were combined using fixed-effects inverse-variance weighted meta-analysis. SNPs demonstrating genome-wide significant (p<5 x 10(-8)) or suggestive associations (p<4 x 10(-7)) were evaluated for replication in an additional 8,463 subjects of European descent. The association of common variants at six genomic regions (in or near MUC1, ATP2B1, DCDC5, TRPM6, SHROOM3, and MDS1) with serum magnesium levels was genome-wide significant when meta-analyzed with the replication dataset. All initially significant SNPs from the CHARGE Consortium showed nominal association with clinically defined hypomagnesemia, two showed association with kidney function, two with bone mineral density, and one of these also associated with fasting glucose levels. Common variants in CNNM2, a magnesium transporter studied only in model systems to date, as well as in CNNM3 and CNNM4, were also associated with magnesium concentrations in this study. We observed no associations with serum sodium or potassium levels exceeding p<4 x 10(-7). Follow-up studies of newly implicated genomic loci may provide additional insights into the regulation and homeostasis of human serum magnesium levels.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Magnesium; Male; Middle Aged; Polymorphism, Single Nucleotide; Potassium; Sodium

Genome-wide association study of PR interval. - Pfeufer, Arne; van Noord, Charlotte; Marciante, Kristin D; Arking, Dan E; Larson, Martin G; Smith, Albert Vernon; Tarasov, Kirill V; Müller, Martina; Sotoodehnia, Nona; Sinner, Moritz F; Verwoert, Germaine C; Li, Man; et al. (Nat Genet, 2010)
The electrocardiographic PR interval (or PQ interval) reflects atrial and atrioventricular nodal conduction, disturbances of which increase risk of atrial fibrillation. We report a meta-analysis of genome-wide association studies for PR interval from seven population-based European studies in the CHARGE Consortium: AGES, ARIC, CHS, FHS, KORA, Rotterdam Study, and SardiNIA (N = 28,517). We identified nine loci associated with PR interval at P < 5 x 10(-8). At the 3p22.2 locus, we observed two independent associations in voltage-gated sodium channel genes, SCN10A and SCN5A. Six of the loci were near cardiac developmental genes, including CAV1-CAV2, NKX2-5 (CSX1), SOX5, WNT11, MEIS1, and TBX5-TBX3, providing pathophysiologically interesting candidate genes. Five of the loci, SCN5A, SCN10A, NKX2-5, CAV1-CAV2, and SOX5, were also associated with atrial fibrillation (N = 5,741 cases, P < 0.0056). This suggests a role for common variation in ion channel and developmental genes in atrial and atrioventricular conduction as well as in susceptibility to atrial fibrillation.
Keywords: Aged; Atrial Fibrillation; Cohort Studies; Electrocardiography; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Meta-Analysis as Topic

Genome-wide meta-analysis increases to 71 the number of confirmed Crohn's disease susceptibility loci. - Franke, Andre; McGovern, Dermot P B; Barrett, Jeffrey C; Wang, Kai; Radford-Smith, Graham L; Ahmad, Tariq; Lees, Charlie W; Balschun, Tobias; Lee, James; Roberts, Rebecca; Anderson, Carl A; Bis, Joshua C; et al. (Nat Genet, 2010)
We undertook a meta-analysis of six Crohn's disease genome-wide association studies (GWAS) comprising 6,333 affected individuals (cases) and 15,056 controls and followed up the top association signals in 15,694 cases, 14,026 controls and 414 parent-offspring trios. We identified 30 new susceptibility loci meeting genome-wide significance (P < 5 × 10⁻⁸). A series of in silico analyses highlighted particular genes within these loci and, together with manual curation, implicated functionally interesting candidate genes including SMAD3, ERAP2, IL10, IL2RA, TYK2, FUT2, DNMT3A, DENND1B, BACH2 and TAGAP. Combined with previously confirmed loci, these results identify 71 distinct loci with genome-wide significant evidence for association with Crohn's disease.
Keywords: Computational Biology; Crohn Disease; Genetic Linkage; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Reproducibility of Results

Hundreds of variants clustered in genomic loci and biological pathways affect human height. - Lango Allen, Hana; Estrada, Karol; Lettre, Guillaume; Berndt, Sonja I; Weedon, Michael N; Rivadeneira, Fernando; Willer, Cristen J; Jackson, Anne U; Vedantam, Sailaja; Raychaudhuri, Soumya; Ferreira, Teresa; Wood, Andrew R; et al. (Nature, 2010)
Most common human traits and diseases have a polygenic pattern of inheritance: DNA sequence variants at many genetic loci influence the phenotype. Genome-wide association (GWA) studies have identified more than 600 variants associated with human traits, but these typically explain small fractions of phenotypic variation, raising questions about the use of further studies. Here, using 183,727 individuals, we show that hundreds of genetic variants, in at least 180 loci, influence adult height, a highly heritable and classic polygenic trait. The large number of loci reveals patterns with important implications for genetic studies of common human diseases and traits. First, the 180 loci are not random, but instead are enriched for genes that are connected in biological pathways (P = 0.016) and that underlie skeletal growth defects (P < 0.001). Second, the likely causal gene is often located near the most strongly associated variant: in 13 of 21 loci containing a known skeletal growth gene, that gene was closest to the associated variant. Third, at least 19 loci have multiple independently associated variants, suggesting that allelic heterogeneity is a frequent feature of polygenic traits, that comprehensive explorations of already-discovered loci should discover additional variants and that an appreciable fraction of associated loci may have been identified. Fourth, associated variants are enriched for likely functional effects on genes, being over-represented among variants that alter amino-acid structure of proteins and expression levels of nearby genes. Our data explain approximately 10% of the phenotypic variation in height, and we estimate that unidentified common variants of similar effect sizes would increase this figure to approximately 16% of phenotypic variation (approximately 20% of heritable variation). Although additional approaches are needed to dissect the genetic architecture of polygenic human traits fully, our findings indicate that GWA studies can identify large numbers of loci that implicate biologically relevant genes and pathways.
Keywords: Body Height; Chromosomes, Human, Pair 3; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Metabolic Networks and Pathways; Multifactorial Inheritance; Phenotype; Polymorphism, Single Nucleotide

Independent susceptibility markers for atrial fibrillation on chromosome 4q25. - Lubitz, Steven A; Sinner, Moritz F; Lunetta, Kathryn L; Makino, Seiko; Pfeufer, Arne; Rahman, Rosanna; Veltman, Caroline E; Barnard, John; Bis, Joshua C; Danik, Stephan P; Sonni, Akshata; Shea, Marisa A; et al. (Circulation, 2010)
BACKGROUND: Genetic variants on chromosome 4q25 are associated with atrial fibrillation (AF). We sought to determine whether there is more than 1 susceptibility signal at this locus. METHODS AND RESULTS: Thirty-four haplotype-tagging single-nucleotide polymorphisms (SNPs) at the 4q25 locus were genotyped in 790 case and 1177 control subjects from Massachusetts General Hospital and tested for association with AF. We replicated SNPs associated with AF after adjustment for the most significantly associated SNP in 5066 case and 30 661 referent subjects from the German Competence Network for Atrial Fibrillation, Atherosclerosis Risk In Communities Study, Cleveland Clinic Lone AF Study, Cardiovascular Health Study, and Rotterdam Study. All subjects were of European ancestry. A multimarker risk score composed of SNPs that tagged distinct AF susceptibility signals was constructed and tested for association with AF, and all results were subjected to meta-analysis. The previously reported SNP, rs2200733, was most significantly associated with AF (minor allele odds ratio 1.80, 95% confidence interval 1.50 to 2.15, P=1.2 x 10(-20)) in the discovery sample. Adjustment for rs2200733 genotype revealed 2 additional susceptibility signals marked by rs17570669 and rs3853445. A graded risk of AF was observed with an increasing number of AF risk alleles at SNPs that tagged these 3 susceptibility signals. CONCLUSIONS: We identified 2 novel AF susceptibility signals on chromosome 4q25. Consideration of multiple susceptibility signals at chromosome 4q25 identifies individuals with an increased risk of AF and may localize regulatory elements at the locus with biological relevance in the pathogenesis of AF.
Keywords: Aged; Aged, 80 and over; Atrial Fibrillation; Chromosome Mapping; Chromosomes, Human, Pair 4; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Meta-analyses of genome-wide association studies identify multiple loci associated with pulmonary function. - Hancock, Dana B; Eijgelsheim, Mark; Wilk, Jemma B; Gharib, Sina A; Loehr, Laura R; Marciante, Kristin D; Franceschini, Nora; van Durme, Yannick M T A; Chen, Ting-Hsu; Barr, R Graham; Schabath, Matthew B; Couper, David J; et al. (Nat Genet, 2010)
Spirometric measures of lung function are heritable traits that reflect respiratory health and predict morbidity and mortality. We meta-analyzed genome-wide association studies for two clinically important lung-function measures: forced expiratory volume in the first second (FEV(1)) and its ratio to forced vital capacity (FEV(1)/FVC), an indicator of airflow obstruction. This meta-analysis included 20,890 participants of European ancestry from four CHARGE Consortium studies: Atherosclerosis Risk in Communities, Cardiovascular Health Study, Framingham Heart Study and Rotterdam Study. We identified eight loci associated with FEV(1)/FVC (HHIP, GPR126, ADAM19, AGER-PPT2, FAM13A, PTCH1, PID1 and HTR4) and one locus associated with FEV(1) (INTS12-GSTCD-NPNT) at or near genome-wide significance (P < 5 x 10(-8)) in the CHARGE Consortium dataset. Our findings may offer insights into pulmonary function and pathogenesis of chronic lung disease.
Keywords: Databases, Genetic; Female; Forced Expiratory Volume; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Lung; Lung Diseases; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Spirometry; Vital Capacity

Meta-analysis identifies 13 new loci associated with waist-hip ratio and reveals sexual dimorphism in the genetic basis of fat distribution. - Heid, Iris M; Jackson, Anne U; Randall, Joshua C; Winkler, Thomas W; Qi, Lu; Steinthorsdottir, Valgerdur; Thorleifsson, Gudmar; Zillikens, M Carola; Speliotes, Elizabeth K; Mägi, Reedik; Workalemahu, Tsegaselassie; White, Charles C; et al. (Nat Genet, 2010)
Waist-hip ratio (WHR) is a measure of body fat distribution and a predictor of metabolic consequences independent of overall adiposity. WHR is heritable, but few genetic variants influencing this trait have been identified. We conducted a meta-analysis of 32 genome-wide association studies for WHR adjusted for body mass index (comprising up to 77,167 participants), following up 16 loci in an additional 29 studies (comprising up to 113,636 subjects). We identified 13 new loci in or near RSPO3, VEGFA, TBX15-WARS2, NFE2L3, GRB14, DNM3-PIGC, ITPR2-SSPN, LY86, HOXC13, ADAMTS9, ZNRF3-KREMEN1, NISCH-STAB1 and CPEB4 (P = 1.9 × 10⁻⁹ to P = 1.8 × 10⁻⁴⁰) and the known signal at LYPLAL1. Seven of these loci exhibited marked sexual dimorphism, all with a stronger effect on WHR in women than men (P for sex difference = 1.9 × 10⁻³ to P = 1.2 × 10⁻¹³). These findings provide evidence for multiple loci that modulate body fat distribution independent of overall adiposity and reveal strong gene-by-sex interactions.
Keywords: Adipose Tissue; Age Factors; Chromosome Mapping; Female; Genome, Human; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Sex Characteristics; Waist-Hip Ratio

Multiple genetic loci influence serum urate levels and their relationship with gout and cardiovascular disease risk factors. - Yang, Qiong; Köttgen, Anna; Dehghan, Abbas; Smith, Albert V; Glazer, Nicole L; Chen, Ming-Huei; Chasman, Daniel I; Aspelund, Thor; Eiriksdottir, Gudny; Harris, Tamara B; Launer, Lenore; Nalls, Michael; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Elevated serum urate levels can lead to gout and are associated with cardiovascular risk factors. We performed a genome-wide association study to search for genetic susceptibility loci for serum urate and gout and investigated the causal nature of the associations of serum urate with gout and selected cardiovascular risk factors and coronary heart disease (CHD). METHODS AND RESULTS: Meta-analyses of genome-wide association studies (GWAS) were performed in 5 population-based cohorts of the Cohorts for Heart and Aging Research in Genome Epidemiology consortium for serum urate and gout in 28 283 white participants. The effect of the most significant single-nucleotide polymorphism at all genome-wide significant loci on serum urate was added to create a genetic urate score. Findings were replicated in the Women's Genome Health Study (n=22 054). Single-nucleotide polymorphisms at 8 genetic loci achieved genome-wide significance with serum urate levels (P=4×10(-8) to 2×10(-242) in SLC22A11, GCKR, R3HDM2-INHBC region, RREB1, PDZK1, SLC2A9, ABCG2, and SLC17A1). Only 2 loci (SLC2A9, ABCG2) showed genome-wide significant association with gout. The genetic urate score was strongly associated with serum urate and gout (odds ratio, 12.4 per 100 μmol/L; P=3×10(-39)) but not with blood pressure, glucose, estimated glomerular filtration rate, chronic kidney disease, or CHD. The lack of association between the genetic score and the latter phenotypes also was observed in the Women's Genome Health Study. CONCLUSIONS: The genetic urate score analysis suggested a causal relationship between serum urate and gout but did not provide evidence for one between serum urate and cardiovascular risk factors and CHD.
Keywords: Cardiovascular Diseases; Coronary Disease; Female; Genetic Loci; Genome-Wide Association Study; Gout; Humans; Male; Risk Factors; Uric Acid

New genetic loci implicated in fasting glucose homeostasis and their impact on type 2 diabetes risk. - Dupuis, Josée; Langenberg, Claudia; Prokopenko, Inga; Saxena, Richa; Soranzo, Nicole; Jackson, Anne U; Wheeler, Eleanor; Glazer, Nicole L; Bouatia-Naji, Nabila; Gloyn, Anna L; Lindgren, Cecilia M; Mägi, Reedik; et al. (Nat Genet, 2010)
Levels of circulating glucose are tightly regulated. To identify new loci influencing glycemic traits, we performed meta-analyses of 21 genome-wide association studies informative for fasting glucose, fasting insulin and indices of beta-cell function (HOMA-B) and insulin resistance (HOMA-IR) in up to 46,186 nondiabetic participants. Follow-up of 25 loci in up to 76,558 additional subjects identified 16 loci associated with fasting glucose and HOMA-B and two loci associated with fasting insulin and HOMA-IR. These include nine loci newly associated with fasting glucose (in or near ADCY5, MADD, ADRA2A, CRY2, FADS1, GLIS3, SLC2A2, PROX1 and C2CD4B) and one influencing fasting insulin and HOMA-IR (near IGF1). We also demonstrated association of ADCY5, PROX1, GCK, GCKR and DGKB-TMEM195 with type 2 diabetes. Within these loci, likely biological candidate genes influence signal transduction, cell proliferation, development, glucose-sensing and circadian regulation. Our results demonstrate that genetic studies of glycemic traits can identify type 2 diabetes risk loci, as well as loci containing gene variants that are associated with a modest elevation in glucose levels but are not associated with overt diabetes.
Keywords: Adolescent; Adult; Alleles; Blood Glucose; Child; Databases, Genetic; Diabetes Mellitus, Type 2; DNA Copy Number Variations; Fasting; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Homeostasis; Humans; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Reproducibility of Results

New loci associated with kidney function and chronic kidney disease. - Köttgen, Anna; Pattaro, Cristian; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Glazer, Nicole L; Parsa, Afshin; Gao, Xiaoyi; Yang, Qiong; Smith, Albert V; O'Connell, Jeffrey R; Li, Man; et al. (Nat Genet, 2010)
Chronic kidney disease (CKD) is a significant public health problem, and recent genetic studies have identified common CKD susceptibility variants. The CKDGen consortium performed a meta-analysis of genome-wide association data in 67,093 individuals of European ancestry from 20 predominantly population-based studies in order to identify new susceptibility loci for reduced renal function as estimated by serum creatinine (eGFRcrea), serum cystatin c (eGFRcys) and CKD (eGFRcrea < 60 ml/min/1.73 m(2); n = 5,807 individuals with CKD (cases)). Follow-up of the 23 new genome-wide-significant loci (P < 5 x 10(-8)) in 22,982 replication samples identified 13 new loci affecting renal function and CKD (in or near LASS2, GCKR, ALMS1, TFDP2, DAB2, SLC34A1, VEGFA, PRKAG2, PIP5K1B, ATXN2, DACH1, UBE2Q2 and SLC7A9) and 7 loci suspected to affect creatinine production and secretion (CPS1, SLC22A2, TMEM60, WDR37, SLC6A13, WDR72 and BCAS3). These results further our understanding of the biologic mechanisms of kidney function by identifying loci that potentially influence nephrogenesis, podocyte function, angiogenesis, solute transport and metabolic functions of the kidney.
Keywords: Cohort Studies; Creatinine; Cystatin C; Diet; Europe; Genetic Markers; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Models, Genetic; Risk Factors

Physical activity predicts gray matter volume in late adulthood: the Cardiovascular Health Study. - Erickson, K I; Raji, C A; Lopez, O L; Becker, J T; Rosano, C; Newman, A B; Gach, H M; Thompson, P M; Ho, A J; Kuller, L H (Neurology, 2010)
OBJECTIVES: Physical activity (PA) has been hypothesized to spare gray matter volume in late adulthood, but longitudinal data testing an association has been lacking. Here we tested whether PA would be associated with greater gray matter volume after a 9-year follow-up, a threshold could be identified for the amount of walking necessary to spare gray matter volume, and greater gray matter volume associated with PA would be associated with a reduced risk for cognitive impairment 13 years after the PA evaluation. METHODS: In 299 adults (mean age 78 years) from the Cardiovascular Health Cognition Study, we examined the association between gray matter volume, PA, and cognitive impairment. Physical activity was quantified as the number of blocks walked over 1 week. High-resolution brain scans were acquired 9 years after the PA assessment on cognitively normal adults. White matter hyperintensities, ventricular grade, and other health variables at baseline were used as covariates. Clinical adjudication for cognitive impairment occurred 13 years after baseline. RESULTS: Walking amounts ranged from 0 to 300 blocks (mean 56.3; SD 69.7). Greater PA predicted greater volumes of frontal, occipital, entorhinal, and hippocampal regions 9 years later. Walking 72 blocks was necessary to detect increased gray matter volume but walking more than 72 blocks did not spare additional volume. Greater gray matter volume with PA reduced the risk for cognitive impairment 2-fold. CONCLUSION: Greater amounts of walking are associated with greater gray matter volume, which is in turn associated with a reduced risk of cognitive impairment.
Keywords: Aged; Aged, 80 and over; Brain; Brain Mapping; Cardiovascular Diseases; Cognition Disorders; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Motor Activity; Neuropsychological Tests; Odds Ratio; Predictive Value of Tests; Surveys and Questionnaires

Sleep disturbances, quality of life, and ethnicity: the Sleep Heart Health Study. - Baldwin, Carol M; Ervin, Ann-Margret; Mays, Mary Z; Robbins, John; Shafazand, Shirin; Walsleben, Joyce; Weaver, Terri (J Clin Sleep Med, 2010)
STUDY OBJECTIVES: To compare health-related quality of life (HR-QOL) across subgroups defined by sleep disturbances and ethnicity. METHODS: Men (47%) and women (53%) Sleep Heart Health Study participants age 40 and older (N = 5237) underwent overnight polysomnography and completed self-report questionnaires on symptoms of sleep disturbances. The physical and mental composite scales (PCS and MCS) of the Medical Outcomes Study 36-item short form survey assessed HR-QOL and were compared to sleep data. RESULTS: Participants self-identified as Caucasian/White (n = 4482, 86%), African American/Black (n = 490, 9%), or Hispanic/Mexican American (n = 265, 5%). The prevalence of obstructive sleep apnea (OSA) was 17%, frequent snoring was 34%, difficulty initiating or maintaining sleep (DIMS; insomnia symptoms) was 30%, and excessive daytime sleepiness (EDS) was 25%. African American participants with frequent snoring, insomnia symptoms, or EDS had significantly poorer physical health compared to Caucasians (p < 0.001). Hispanics with frequent snoring, insomnia symptoms, or EDS had significantly poorer mental health than Caucasian participants (p <0.001). Neither PCS nor MCS scores differed significantly across ethnic subgroups for participants with moderate to severe OSA (respiratory disturbance index > 15, 4% desaturation). CONCLUSIONS: Across ethnic/racial subgroups, sleep disturbances are associated with worse physical and better mental HR-QOL than the U.S. norm, but this relationship may be moderated by comorbid health conditions. This study replicates and extends prior research indicating differences among minority and non-minority participants and highlights the need for future studies of sleep disturbances with larger samples of minorities that control for comorbid health conditions.
Keywords: African Americans; Cohort Studies; Ethnic Groups; European Continental Ancestry Group; Female; Health Status; Heart Diseases; Hispanic Americans; Humans; Longitudinal Studies; Male; Mental Health; Middle Aged; Polysomnography; Prevalence; Quality of Life; Sleep Apnea, Obstructive; Sleep Initiation and Maintenance Disorders; Sleep Wake Disorders; Snoring; Surveys and Questionnaires; United States

Subclinical hypothyroidism and the risk of coronary heart disease and mortality. - Rodondi, Nicolas; den Elzen, Wendy P J; Bauer, Douglas C; Cappola, Anne R; Razvi, Salman; Walsh, John P; Asvold, Bjørn O; Iervasi, Giorgio; Imaizumi, Misa; Collet, Tinh-Hai; Bremner, Alexandra; Maisonneuve, Patrick; et al. (JAMA, 2010)
CONTEXT: Data regarding the association between subclinical hypothyroidism and cardiovascular disease outcomes are conflicting among large prospective cohort studies. This might reflect differences in participants' age, sex, thyroid-stimulating hormone (TSH) levels, or preexisting cardiovascular disease. OBJECTIVE: To assess the risks of coronary heart disease (CHD) and total mortality for adults with subclinical hypothyroidism. DATA SOURCES AND STUDY SELECTION: The databases of MEDLINE and EMBASE (1950 to May 31, 2010) were searched without language restrictions for prospective cohort studies with baseline thyroid function and subsequent CHD events, CHD mortality, and total mortality. The reference lists of retrieved articles also were searched. DATA EXTRACTION: Individual data on 55,287 participants with 542,494 person-years of follow-up between 1972 and 2007 were supplied from 11 prospective cohorts in the United States, Europe, Australia, Brazil, and Japan. The risk of CHD events was examined in 25,977 participants from 7 cohorts with available data. Euthyroidism was defined as a TSH level of 0.50 to 4.49 mIU/L. Subclinical hypothyroidism was defined as a TSH level of 4.5 to 19.9 mIU/L with normal thyroxine concentrations. RESULTS: Among 55,287 adults, 3450 had subclinical hypothyroidism (6.2%) and 51,837 had euthyroidism. During follow-up, 9664 participants died (2168 of CHD), and 4470 participants had CHD events (among 7 studies). The risk of CHD events and CHD mortality increased with higher TSH concentrations. In age- and sex-adjusted analyses, the hazard ratio (HR) for CHD events was 1.00 (95% confidence interval [CI], 0.86-1.18) for a TSH level of 4.5 to 6.9 mIU/L (20.3 vs 20.3/1000 person-years for participants with euthyroidism), 1.17 (95% CI, 0.96-1.43) for a TSH level of 7.0 to 9.9 mIU/L (23.8/1000 person-years), and 1.89 (95% CI, 1.28-2.80) for a TSH level of 10 to 19.9 mIU/L (n = 70 events/235; 38.4/1000 person-years; P <.001 for trend). The corresponding HRs for CHD mortality were 1.09 (95% CI, 0.91-1.30; 5.3 vs 4.9/1000 person-years for participants with euthyroidism), 1.42 (95% CI, 1.03-1.95; 6.9/1000 person-years), and 1.58 (95% CI, 1.10-2.27, n = 28 deaths/333; 7.7/1000 person-years; P = .005 for trend). Total mortality was not increased among participants with subclinical hypothyroidism. Results were similar after further adjustment for traditional cardiovascular risk factors. Risks did not significantly differ by age, sex, or preexisting cardiovascular disease. CONCLUSIONS: Subclinical hypothyroidism is associated with an increased risk of CHD events and CHD mortality in those with higher TSH levels, particularly in those with a TSH concentration of 10 mIU/L or greater.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Coronary Disease; Female; Humans; Hypothyroidism; Male; Middle Aged; Mortality; Prospective Studies; Risk; Thyrotropin; Young Adult

Association of genetic variants and incident coronary heart disease in multiethnic cohorts: the PAGE study. - Franceschini, Nora; Carty, Cara; Bůzková, Petra; Reiner, Alex P; Garrett, Tiana; Lin, Yi; Vöckler, Jens-S; Hindorff, Lucia A; Cole, Shelley A; Boerwinkle, Eric; Lin, Dan-Yu; Bookman, Ebony; et al. (Circ Cardiovasc Genet, 2011)
BACKGROUND: Genome-wide association studies identified several single nucleotide polymorphisms (SNP) associated with prevalent coronary heart disease (CHD), but less is known of associations with incident CHD. The association of 13 published CHD SNPs was examined in 5 ancestry groups of 4 large US prospective cohorts. METHODS AND RESULTS: The analyses included incident coronary events over an average 9.1 to 15.7 follow-up person-years in up to 26 617 white individuals (6626 events), 8018 black individuals (914 events), 1903 Hispanic individuals (113 events), 3669 American Indian individuals (595 events), and 885 Asian/Pacific Islander individuals (66 events). We used Cox proportional hazards models (with additive mode of inheritance) adjusted for age, sex, and ancestry (as needed). Nine loci were statistically associated with incident CHD events in white participants: 9p21 (rs10757278; P=4.7 × 10(-41)), 16q23.1 (rs2549513; P=0.0004), 6p24.1 (rs499818; P=0.0002), 2q36.3 (rs2943634; P=6.7 × 10(-6)), MTHFD1L (rs6922269, P=5.1 × 10(-10)), APOE (rs429358; P=2.7×10(-18)), ZNF627 (rs4804611; P=5.0 × 10(-8)), CXCL12 (rs501120; P=1.4 × 10(-6)) and LPL (rs268; P=2.7 × 10(-17)). The 9p21 region showed significant between-study heterogeneity, with larger effects in individuals age 55 years or younger and in women. Inclusion of coronary revascularization procedures among the incident CHD events introduced heterogeneity. The SNPs were not associated with CHD in black participants, and associations varied in other US minorities. CONCLUSIONS: Prospective analyses of white participants replicated several reported cross-sectional CHD-SNP associations.
Keywords: Aged; Aged, 80 and over; Continental Population Groups; Coronary Disease; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies

Association of genetic variation with systolic and diastolic blood pressure among African Americans: the Candidate Gene Association Resource study. - Fox, Ervin R; Young, J Hunter; Li, Yali; Dreisbach, Albert W; Keating, Brendan J; Musani, Solomon K; Liu, Kiang; Morrison, Alanna C; Ganesh, Santhi; Kutlar, Abdullah; Ramachandran, Vasan S; Polak, Josef F; et al. (Hum Mol Genet, 2011)
The prevalence of hypertension in African Americans (AAs) is higher than in other US groups; yet, few have performed genome-wide association studies (GWASs) in AA. Among people of European descent, GWASs have identified genetic variants at 13 loci that are associated with blood pressure. It is unknown if these variants confer susceptibility in people of African ancestry. Here, we examined genome-wide and candidate gene associations with systolic blood pressure (SBP) and diastolic blood pressure (DBP) using the Candidate Gene Association Resource (CARe) consortium consisting of 8591 AAs. Genotypes included genome-wide single-nucleotide polymorphism (SNP) data utilizing the Affymetrix 6.0 array with imputation to 2.5 million HapMap SNPs and candidate gene SNP data utilizing a 50K cardiovascular gene-centric array (ITMAT-Broad-CARe [IBC] array). For Affymetrix data, the strongest signal for DBP was rs10474346 (P= 3.6 × 10(-8)) located near GPR98 and ARRDC3. For SBP, the strongest signal was rs2258119 in C21orf91 (P= 4.7 × 10(-8)). The top IBC association for SBP was rs2012318 (P= 6.4 × 10(-6)) near SLC25A42 and for DBP was rs2523586 (P= 1.3 × 10(-6)) near HLA-B. None of the top variants replicated in additional AA (n = 11 882) or European-American (n = 69 899) cohorts. We replicated previously reported European-American blood pressure SNPs in our AA samples (SH2B3, P= 0.009; TBX3-TBX5, P= 0.03; and CSK-ULK3, P= 0.0004). These genetic loci represent the best evidence of genetic influences on SBP and DBP in AAs to date. More broadly, this work supports that notion that blood pressure among AAs is a trait with genetic underpinnings but also with significant complexity.
Keywords: Adult; African Americans; Aged; Blood Pressure; Cohort Studies; Diastole; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Hypertension; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Systole

Association of hypertension drug target genes with blood pressure and hypertension in 86,588 individuals. - Johnson, Andrew D; Newton-Cheh, Christopher; Chasman, Daniel I; Ehret, Georg B; Johnson, Toby; Rose, Lynda; Rice, Kenneth; Verwoert, Germaine C; Launer, Lenore J; Gudnason, Vilmundur; Larson, Martin G; Chakravarti, Aravinda; et al. (Hypertension, 2011)
We previously conducted genome-wide association meta-analysis of systolic blood pressure, diastolic blood pressure, and hypertension in 29,136 people from 6 cohort studies in the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. Here we examine associations of these traits with 30 gene regions encoding known antihypertensive drug targets. We find nominal evidence of association of ADRB1, ADRB2, AGT, CACNA1A, CACNA1C, and SLC12A3 polymorphisms with 1 or more BP traits in the Cohorts for Heart and Aging Research in Genomic Epidemiology genome-wide association meta-analysis. We attempted replication of the top meta-analysis single nucleotide polymorphisms for these genes in the Global BPgen Consortium (n=34,433) and the Women's Genome Health Study (n=23,019) and found significant results for rs1801253 in ADRB1 (Arg389Gly), with the Gly allele associated with a lower mean systolic blood pressure (β: 0.57 mm Hg; SE: 0.09 mm Hg; meta-analysis: P=4.7×10(-10)), diastolic blood pressure (β: 0.36 mm Hg; SE: 0.06 mm Hg; meta-analysis: P=9.5×10(-10)), and prevalence of hypertension (β: 0.06 mm Hg; SE: 0.02 mm Hg; meta-analysis: P=3.3×10(-4)). Variation in AGT (rs2004776) was associated with systolic blood pressure (β: 0.42 mm Hg; SE: 0.09 mm Hg; meta-analysis: P=3.8×10(-6)), as well as diastolic blood pressure (P=5.0×10(-8)) and hypertension (P=3.7×10(-7)). A polymorphism in ACE (rs4305) showed modest replication of association with increased hypertension (β: 0.06 mm Hg; SE: 0.01 mm Hg; meta-analysis: P=3.0×10(-5)). Two loci, ADRB1 and AGT, contain single nucleotide polymorphisms that reached a genome-wide significance threshold in meta-analysis for the first time. Our findings suggest that these genes warrant further studies of their genetic effects on blood pressure, including pharmacogenetic interactions.
Keywords: Alleles; Angiotensinogen; Antihypertensive Agents; Blood Pressure; Female; Genetic Predisposition to Disease; Genotype; Humans; Hypertension; Male; Pharmacogenetics; Polymorphism, Single Nucleotide; Receptors, Adrenergic, beta-1

CUBN is a gene locus for albuminuria. - Böger, Carsten A; Chen, Ming-Huei; Tin, Adrienne; Olden, Matthias; Köttgen, Anna; de Boer, Ian H; Fuchsberger, Christian; O'Seaghdha, Conall M; Pattaro, Cristian; Teumer, Alexander; Liu, Ching-Ti; Glazer, Nicole L; et al. (J Am Soc Nephrol, 2011)
Identification of genetic risk factors for albuminuria may alter strategies for early prevention of CKD progression, particularly among patients with diabetes. Little is known about the influence of common genetic variants on albuminuria in both general and diabetic populations. We performed a meta-analysis of data from 63,153 individuals of European ancestry with genotype information from genome-wide association studies (CKDGen Consortium) and from a large candidate gene study (CARe Consortium) to identify susceptibility loci for the quantitative trait urinary albumin-to-creatinine ratio (UACR) and the clinical diagnosis microalbuminuria. We identified an association between a missense variant (I2984V) in the CUBN gene, which encodes cubilin, and both UACR (P = 1.1 × 10(-11)) and microalbuminuria (P = 0.001). We observed similar associations among 6981 African Americans in the CARe Consortium. The associations between this variant and both UACR and microalbuminuria were significant in individuals of European ancestry regardless of diabetes status. Finally, this variant associated with a 41% increased risk for the development of persistent microalbuminuria during 20 years of follow-up among 1304 participants with type 1 diabetes in the prospective DCCT/EDIC Study. In summary, we identified a missense CUBN variant that associates with levels of albuminuria in both the general population and in individuals with diabetes.
Keywords: African Continental Ancestry Group; Albuminuria; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Humans; Mutation, Missense; Receptors, Cell Surface

Depressive symptoms, physical inactivity and risk of cardiovascular mortality in older adults: the Cardiovascular Health Study. - Win, Sithu; Parakh, Kapil; Eze-Nliam, Chete M; Gottdiener, John S; Kop, Willem J; Ziegelstein, Roy C (Heart, 2011)
BACKGROUND: Depressed older individuals have a higher mortality than older persons without depression. Depression is associated with physical inactivity, and low levels of physical activity have been shown in some cohorts to be a partial mediator of the relationship between depression and cardiovascular events and mortality. METHODS: A cohort of 5888 individuals (mean 72.8 ± 5.6 years, 58% female, 16% African-American) from four US communities was followed for an average of 10.3 years. Self-reported depressive symptoms (10-item Center for Epidemiological Studies Depression Scale) were assessed annually and self-reported physical activity was assessed at baseline and at 3 and 7 years. To estimate how much of the increased risk of cardiovascular mortality associated with depressive symptoms was due to physical inactivity, Cox regression with time-varying covariates was used to determine the percentage change in the log HR of depressive symptoms for cardiovascular mortality after adding physical activity variables. RESULTS: At baseline, 20% of participants scored above the cut-off for depressive symptoms. There were 2915 deaths (49.8%), of which 1176 (20.1%) were from cardiovascular causes. Depressive symptoms and physical inactivity each independently increased the risk of cardiovascular mortality and were strongly associated with each other (all p < 0.001). Individuals with both depressive symptoms and physical inactivity had greater cardiovascular mortality than those with either individually (p < 0.001, log rank test). Physical inactivity reduced the log HR of depressive symptoms for cardiovascular mortality by 26% after adjustment. This was similar for persons with (25%) and without (23%) established coronary heart disease. CONCLUSIONS: Physical inactivity accounted for a significant proportion of the risk of cardiovascular mortality due to depressive symptoms in older adults, regardless of coronary heart disease status.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Depression; Epidemiologic Methods; Female; Humans; Male; Motor Activity; Psychiatric Status Rating Scales; United States

Diabetes mellitus, fasting glucose, and risk of cause-specific death. - Rao Kondapally Seshasai, Sreenivasa; Kaptoge, Stephen; Thompson, Alexander; Di Angelantonio, Emanuele; Gao, Pei; Sarwar, Nadeem; Whincup, Peter H; Mukamal, Kenneth J; Gillum, Richard F; Holme, Ingar; Njølstad, Inger; Fletcher, Astrid; et al. (N Engl J Med, 2011)
BACKGROUND: The extent to which diabetes mellitus or hyperglycemia is related to risk of death from cancer or other nonvascular conditions is uncertain. METHODS: We calculated hazard ratios for cause-specific death, according to baseline diabetes status or fasting glucose level, from individual-participant data on 123,205 deaths among 820,900 people in 97 prospective studies. RESULTS: After adjustment for age, sex, smoking status, and body-mass index, hazard ratios among persons with diabetes as compared with persons without diabetes were as follows: 1.80 (95% confidence interval [CI], 1.71 to 1.90) for death from any cause, 1.25 (95% CI, 1.19 to 1.31) for death from cancer, 2.32 (95% CI, 2.11 to 2.56) for death from vascular causes, and 1.73 (95% CI, 1.62 to 1.85) for death from other causes. Diabetes (vs. no diabetes) was moderately associated with death from cancers of the liver, pancreas, ovary, colorectum, lung, bladder, and breast. Aside from cancer and vascular disease, diabetes (vs. no diabetes) was also associated with death from renal disease, liver disease, pneumonia and other infectious diseases, mental disorders, nonhepatic digestive diseases, external causes, intentional self-harm, nervous-system disorders, and chronic obstructive pulmonary disease. Hazard ratios were appreciably reduced after further adjustment for glycemia measures, but not after adjustment for systolic blood pressure, lipid levels, inflammation or renal markers. Fasting glucose levels exceeding 100 mg per deciliter (5.6 mmol per liter), but not levels of 70 to 100 mg per deciliter (3.9 to 5.6 mmol per liter), were associated with death. A 50-year-old with diabetes died, on average, 6 years earlier than a counterpart without diabetes, with about 40% of the difference in survival attributable to excess nonvascular deaths. CONCLUSIONS: In addition to vascular disease, diabetes is associated with substantial premature death from several cancers, infectious diseases, external causes, intentional self-harm, and degenerative disorders, independent of several major risk factors. (Funded by the British Heart Foundation and others.).
Keywords: Blood Glucose; Cause of Death; Diabetes Mellitus; Female; Humans; Hyperglycemia; Life Expectancy; Male; Middle Aged; Risk; Survival Analysis

Enhanced statistical tests for GWAS in admixed populations: assessment using African Americans from CARe and a Breast Cancer Consortium. - Pasaniuc, Bogdan; Zaitlen, Noah; Lettre, Guillaume; Chen, Gary K; Tandon, Arti; Kao, W H Linda; Ruczinski, Ingo; Fornage, Myriam; Siscovick, David S; Zhu, Xiaofeng; Larkin, Emma; Lange, Leslie A; et al. (PLoS Genet, 2011)
While genome-wide association studies (GWAS) have primarily examined populations of European ancestry, more recent studies often involve additional populations, including admixed populations such as African Americans and Latinos. In admixed populations, linkage disequilibrium (LD) exists both at a fine scale in ancestral populations and at a coarse scale (admixture-LD) due to chromosomal segments of distinct ancestry. Disease association statistics in admixed populations have previously considered SNP association (LD mapping) or admixture association (mapping by admixture-LD), but not both. Here, we introduce a new statistical framework for combining SNP and admixture association in case-control studies, as well as methods for local ancestry-aware imputation. We illustrate the gain in statistical power achieved by these methods by analyzing data of 6,209 unrelated African Americans from the CARe project genotyped on the Affymetrix 6.0 chip, in conjunction with both simulated and real phenotypes, as well as by analyzing the FGFR2 locus using breast cancer GWAS data from 5,761 African-American women. We show that, at typed SNPs, our method yields an 8% increase in statistical power for finding disease risk loci compared to the power achieved by standard methods in case-control studies. At imputed SNPs, we observe an 11% increase in statistical power for mapping disease loci when our local ancestry-aware imputation framework and the new scoring statistic are jointly employed. Finally, we show that our method increases statistical power in regions harboring the causal SNP in the case when the causal SNP is untyped and cannot be imputed. Our methods and our publicly available software are broadly applicable to GWAS in admixed populations.
Keywords: African Americans; Algorithms; Breast Neoplasms; Chromosome Mapping; Coronary Disease; Diabetes Mellitus, Type 2; Female; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Receptor, Fibroblast Growth Factor, Type 2; Software

Genetic association for renal traits among participants of African ancestry reveals new loci for renal function. - Liu, Ching-Ti; Garnaas, Maija K; Tin, Adrienne; Köttgen, Anna; Franceschini, Nora; Peralta, Carmen A; de Boer, Ian H; Lu, Xiaoning; Atkinson, Elizabeth; Ding, Jingzhong; Nalls, Michael; Shriner, Daniel; et al. (PLoS Genet, 2011)
Chronic kidney disease (CKD) is an increasing global public health concern, particularly among populations of African ancestry. We performed an interrogation of known renal loci, genome-wide association (GWA), and IBC candidate-gene SNP association analyses in African Americans from the CARe Renal Consortium. In up to 8,110 participants, we performed meta-analyses of GWA and IBC array data for estimated glomerular filtration rate (eGFR), CKD (eGFR <60 mL/min/1.73 m(2)), urinary albumin-to-creatinine ratio (UACR), and microalbuminuria (UACR >30 mg/g) and interrogated the 250 kb flanking region around 24 SNPs previously identified in European Ancestry renal GWAS analyses. Findings were replicated in up to 4,358 African Americans. To assess function, individually identified genes were knocked down in zebrafish embryos by morpholino antisense oligonucleotides. Expression of kidney-specific genes was assessed by in situ hybridization, and glomerular filtration was evaluated by dextran clearance. Overall, 23 of 24 previously identified SNPs had direction-consistent associations with eGFR in African Americans, 2 of which achieved nominal significance (UMOD, PIP5K1B). Interrogation of the flanking regions uncovered 24 new index SNPs in African Americans, 12 of which were replicated (UMOD, ANXA9, GCKR, TFDP2, DAB2, VEGFA, ATXN2, GATM, SLC22A2, TMEM60, SLC6A13, and BCAS3). In addition, we identified 3 suggestive loci at DOK6 (p-value = 5.3×10(-7)) and FNDC1 (p-value = 3.0×10(-7)) for UACR, and KCNQ1 with eGFR (p = 3.6×10(-6)). Morpholino knockdown of kcnq1 in the zebrafish resulted in abnormal kidney development and filtration capacity. We identified several SNPs in association with eGFR in African Ancestry individuals, as well as 3 suggestive loci for UACR and eGFR. Functional genetic studies support a role for kcnq1 in glomerular development in zebrafish.
Keywords: Adaptor Proteins, Vesicular Transport; Adult; African Continental Ancestry Group; Aged; Animals; Female; Gene Knockdown Techniques; Genetic Association Studies; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; KCNQ1 Potassium Channel; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Neoplasm Proteins; Phenotype; Polymorphism, Single Nucleotide; Zebrafish

Genetic determinants of lipid traits in diverse populations from the population architecture using genomics and epidemiology (PAGE) study. - Dumitrescu, Logan; Carty, Cara L; Taylor, Kira; Schumacher, Fredrick R; Hindorff, Lucia A; Ambite, José L; Anderson, Garnet; Best, Lyle G; Brown-Gentry, Kristin; Bůzková, Petra; Carlson, Christopher S; Cochran, Barbara; et al. (PLoS Genet, 2011)
For the past five years, genome-wide association studies (GWAS) have identified hundreds of common variants associated with human diseases and traits, including high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) levels. Approximately 95 loci associated with lipid levels have been identified primarily among populations of European ancestry. The Population Architecture using Genomics and Epidemiology (PAGE) study was established in 2008 to characterize GWAS-identified variants in diverse population-based studies. We genotyped 49 GWAS-identified SNPs associated with one or more lipid traits in at least two PAGE studies and across six racial/ethnic groups. We performed a meta-analysis testing for SNP associations with fasting HDL-C, LDL-C, and ln(TG) levels in self-identified European American (~20,000), African American (~9,000), American Indian (~6,000), Mexican American/Hispanic (~2,500), Japanese/East Asian (~690), and Pacific Islander/Native Hawaiian (~175) adults, regardless of lipid-lowering medication use. We replicated 55 of 60 (92%) SNP associations tested in European Americans at p<0.05. Despite sufficient power, we were unable to replicate ABCA1 rs4149268 and rs1883025, CETP rs1864163, and TTC39B rs471364 previously associated with HDL-C and MAFB rs6102059 previously associated with LDL-C. Based on significance (p<0.05) and consistent direction of effect, a majority of replicated genotype-phentoype associations for HDL-C, LDL-C, and ln(TG) in European Americans generalized to African Americans (48%, 61%, and 57%), American Indians (45%, 64%, and 77%), and Mexican Americans/Hispanics (57%, 56%, and 86%). Overall, 16 associations generalized across all three populations. For the associations that did not generalize, differences in effect sizes, allele frequencies, and linkage disequilibrium offer clues to the next generation of association studies for these traits.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Continental Population Groups; Female; Gene Frequency; Genetics, Population; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Lipid Metabolism; Lipoproteins, HDL; Lipoproteins, LDL; Male; Middle Aged; Molecular Epidemiology; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Triglycerides; Young Adult

Genetic variants in novel pathways influence blood pressure and cardiovascular disease risk. - Ehret, Georg B; Munroe, Patricia B; Rice, Kenneth M; Bochud, Murielle; Johnson, Andrew D; Chasman, Daniel I; Smith, Albert V; Tobin, Martin D; Verwoert, Germaine C; Hwang, Shih-Jen; Pihur, Vasyl; Vollenweider, Peter; et al. (Nature, 2011)
Blood pressure is a heritable trait influenced by several biological pathways and responsive to environmental stimuli. Over one billion people worldwide have hypertension (≥140 mm Hg systolic blood pressure or  ≥90 mm Hg diastolic blood pressure). Even small increments in blood pressure are associated with an increased risk of cardiovascular events. This genome-wide association study of systolic and diastolic blood pressure, which used a multi-stage design in 200,000 individuals of European descent, identified sixteen novel loci: six of these loci contain genes previously known or suspected to regulate blood pressure (GUCY1A3-GUCY1B3, NPR3-C5orf23, ADM, FURIN-FES, GOSR2, GNAS-EDN3); the other ten provide new clues to blood pressure physiology. A genetic risk score based on 29 genome-wide significant variants was associated with hypertension, left ventricular wall thickness, stroke and coronary artery disease, but not kidney disease or kidney function. We also observed associations with blood pressure in East Asian, South Asian and African ancestry individuals. Our findings provide new insights into the genetics and biology of blood pressure, and suggest potential novel therapeutic pathways for cardiovascular disease prevention.
Keywords: Africa; Asia; Blood Pressure; Cardiovascular Diseases; Coronary Artery Disease; Europe; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Kidney Diseases; Polymorphism, Single Nucleotide; Stroke

Genetic variants of the NOTCH3 gene in the elderly and magnetic resonance imaging correlates of age-related cerebral small vessel disease. - Schmidt, Helena; Zeginigg, Marion; Wiltgen, Marco; Freudenberger, Paul; Petrovic, Katja; Cavalieri, Margherita; Gider, Pierre; Enzinger, Christian; Fornage, Myriam; Debette, Stephanie; Rotter, Jerome I; Ikram, Mohammad A; et al. (Brain, 2011)
Cerebral small vessel disease-related brain lesions such as white matter lesions and lacunes are common findings of magnetic resonance imaging in the elderly. These lesions are thought to be major contributors to disability in old age, and risk factors that include age and hypertension have been established. The radiological, histopathologic and clinical phenotypes of age-related cerebral small vessel disease remarkably resemble autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy, which is caused by mutations in NOTCH3. We hypothesized that genetic variations in NOTCH3 also play a role in age-related cerebral small vessel disease. We directly sequenced all 33 exons, the promoter and 3'-untranslated region of NOTCH3 in 195 participants with either coalescent white matter lesions or lacunes and compared the results to 82 randomly selected participants with no focal changes on magnetic resonance images in the Austrian Stroke Prevention Study. We detected nine common and 33 rare single nucleotide polymorphisms, of which 20 were novel. All common single nucleotide polymorphisms were genotyped in the entire cohort (n = 888), and four of them, rs1043994, rs10404382, rs10423702 and rs1043997, were associated significantly with both the presence and progression of white matter lesions. The association was confined to hypertensives, a result which we replicated in the Cohorts for Heart and Ageing Research in Genomic Epidemiology Consortium on an independent sample of 4773 stroke-free hypertensive elderly individuals of European descent (P = 0.04). The 33 rare single nucleotide polymorphisms were scattered over the NOTCH3 gene with three being located in the promoter region, 24 in exons (18 non-synonymous), three in introns and three in the 3'-untranslated region. None of the single nucleotide polymorphisms affected a cysteine residue. Sorting Intolerant From Tolerant, PolyPhen2 analyses and protein structure simulation consistently predicted six of the non-synonymous single nucleotide polymorphisms (H170R, P496L, V1183M, L1518M, D1823N and V1952M) to be functional, with four being exclusively or mainly detected in subjects with severe white matter lesions. In four individuals with rare non-synonymous single nucleotide polymorphisms, we noted anterior temporal lobe hyperintensity, hyperintensity in the external capsule, lacunar infarcts or subcortical lacunar lesions. None of the observed abnormalities were specific to cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy. This is the first comprehensive study investigating (i) the frequency of NOTCH3 variations in community-dwelling elderly and (ii) their effect on cerebral small vessel disease related magnetic resonance imaging phenotypes. We show that the NOTCH3 gene is highly variable with both common and rare single nucleotide polymorphisms spreading across the gene, and that common variants at the NOTCH3 gene increase the risk of age-related white matter lesions in hypertensives. Additional investigations are required to explore the biological mechanisms underlying the observed association.
Keywords: Aged; Aged, 80 and over; Alleles; Brain; Cerebral Small Vessel Diseases; Exons; Female; Follow-Up Studies; Genetic Association Studies; Genotype; Humans; Hypertension; Magnetic Resonance Imaging; Male; Middle Aged; Phenotype; Promoter Regions, Genetic; Prospective Studies; Receptor, Notch3; Receptors, Notch

Genetic variation near IRS1 associates with reduced adiposity and an impaired metabolic profile. - Kilpeläinen, Tuomas O; Zillikens, M Carola; Stančáková, Alena; Finucane, Francis M; Ried, Janina S; Langenberg, Claudia; Zhang, Weihua; Beckmann, Jacques S; Luan, Jian'an; Vandenput, Liesbeth; Styrkarsdottir, Unnur; Zhou, Yanhua; et al. (Nat Genet, 2011)
Genome-wide association studies have identified 32 loci influencing body mass index, but this measure does not distinguish lean from fat mass. To identify adiposity loci, we meta-analyzed associations between ∼2.5 million SNPs and body fat percentage from 36,626 individuals and followed up the 14 most significant (P < 10(-6)) independent loci in 39,576 individuals. We confirmed a previously established adiposity locus in FTO (P = 3 × 10(-26)) and identified two new loci associated with body fat percentage, one near IRS1 (P = 4 × 10(-11)) and one near SPRY2 (P = 3 × 10(-8)). Both loci contain genes with potential links to adipocyte physiology. Notably, the body-fat-decreasing allele near IRS1 is associated with decreased IRS1 expression and with an impaired metabolic profile, including an increased visceral to subcutaneous fat ratio, insulin resistance, dyslipidemia, risk of diabetes and coronary artery disease and decreased adiponectin levels. Our findings provide new insights into adiposity and insulin resistance.
Keywords: Adiponectin; Adiposity; Alleles; Body Fat Distribution; Body Mass Index; Body Weight; Female; Genetic Variation; Genome-Wide Association Study; Humans; Insulin Receptor Substrate Proteins; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Meta-Analysis as Topic; Metabolome; Obesity; Polymorphism, Single Nucleotide; Subcutaneous Fat

Genome-wide association and large-scale follow up identifies 16 new loci influencing lung function. - Soler Artigas, Maria; Loth, Daan W; Wain, Louise V; Gharib, Sina A; Obeidat, Ma'en; Tang, Wenbo; Zhai, Guangju; Zhao, Jing Hua; Smith, Albert Vernon; Huffman, Jennifer E; Albrecht, Eva; Jackson, Catherine M; et al. (Nat Genet, 2011)
Pulmonary function measures reflect respiratory health and are used in the diagnosis of chronic obstructive pulmonary disease. We tested genome-wide association with forced expiratory volume in 1 second and the ratio of forced expiratory volume in 1 second to forced vital capacity in 48,201 individuals of European ancestry with follow up of the top associations in up to an additional 46,411 individuals. We identified new regions showing association (combined P < 5 × 10(-8)) with pulmonary function in or near MFAP2, TGFB2, HDAC4, RARB, MECOM (also known as EVI1), SPATA9, ARMC2, NCR3, ZKSCAN3, CDC123, C10orf11, LRP1, CCDC38, MMP15, CFDP1 and KCNE2. Identification of these 16 new loci may provide insight into the molecular mechanisms regulating pulmonary function and into molecular targets for future therapy to alleviate reduced lung function.
Keywords: Child; European Continental Ancestry Group; Genome-Wide Association Study; Humans; Pulmonary Disease, Chronic Obstructive; Respiratory Function Tests

Genome-wide association studies of cerebral white matter lesion burden: the CHARGE consortium. - Fornage, Myriam; Debette, Stephanie; Bis, Joshua C; Schmidt, Helena; Ikram, M Arfan; Dufouil, Carole; Sigurdsson, Sigurdur; Lumley, Thomas; DeStefano, Anita L; Fazekas, Franz; Vrooman, Henri A; Shibata, Dean K; et al. (Ann Neurol, 2011)
OBJECTIVE: White matter hyperintensities (WMHs) detectable by magnetic resonance imaging are part of the spectrum of vascular injury associated with aging of the brain and are thought to reflect ischemic damage to the small deep cerebral vessels. WMHs are associated with an increased risk of cognitive and motor dysfunction, dementia, depression, and stroke. Despite a significant heritability, few genetic loci influencing WMH burden have been identified. METHODS: We performed a meta-analysis of genome-wide association studies (GWASs) for WMH burden in 9,361 stroke-free individuals of European descent from 7 community-based cohorts. Significant findings were tested for replication in 3,024 individuals from 2 additional cohorts. RESULTS: We identified 6 novel risk-associated single nucleotide polymorphisms (SNPs) in 1 locus on chromosome 17q25 encompassing 6 known genes including WBP2, TRIM65, TRIM47, MRPL38, FBF1, and ACOX1. The most significant association was for rs3744028 (p(discovery) = 4.0 × 10(-9) ; p(replication) = 1.3 × 10(-7) ; p(combined) = 4.0 × 10(-15) ). Other SNPs in this region also reaching genome-wide significance were rs9894383 (p = 5.3 × 10(-9) ), rs11869977 (p = 5.7 × 10(-9) ), rs936393 (p = 6.8 × 10(-9) ), rs3744017 (p = 7.3 × 10(-9) ), and rs1055129 (p = 4.1 × 10(-8) ). Variant alleles at these loci conferred a small increase in WMH burden (4-8% of the overall mean WMH burden in the sample). INTERPRETATION: This large GWAS of WMH burden in community-based cohorts of individuals of European descent identifies a novel locus on chromosome 17. Further characterization of this locus may provide novel insights into the pathogenesis of cerebral WMH.
Keywords: Aged; Aged, 80 and over; Cerebral Cortex; Chromosomes, Human, Pair 17; Cognition Disorders; Cohort Studies; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Movement Disorders; Nerve Fibers, Myelinated; Polymorphism, Single Nucleotide; Residence Characteristics; RNA, Messenger

Genome-wide association study for serum urate concentrations and gout among African Americans identifies genomic risk loci and a novel URAT1 loss-of-function allele. - Tin, Adrienne; Woodward, Owen M; Kao, Wen Hong Linda; Liu, Ching-Ti; Lu, Xiaoning; Nalls, Michael A; Shriner, Daniel; Semmo, Mariam; Akylbekova, Ermeg L; Wyatt, Sharon B; Hwang, Shih-Jen; Yang, Qiong; et al. (Hum Mol Genet, 2011)
Serum urate concentrations are highly heritable and elevated serum urate is a key risk factor for gout. Genome-wide association studies (GWAS) of serum urate in African American (AA) populations are lacking. We conducted a meta-analysis of GWAS of serum urate levels and gout among 5820 AA and a large candidate gene study among 6890 AA and 21 708 participants of European ancestry (EA) within the Candidate Gene Association Resource Consortium. Findings were tested for replication among 1996 independent AA individuals, and evaluated for their association among 28 283 EA participants of the CHARGE Consortium. Functional studies were conducted using (14)C-urate transport assays in mammalian Chinese hamster ovary cells. In the discovery GWAS of serum urate, three loci achieved genome-wide significance (P< 5.0 × 10(-8)): a novel locus near SGK1/SLC2A12 on chromosome 6 (rs9321453, P= 1.0 × 10(-9)), and two loci previously identified in EA participants, SLC2A9 (P= 3.8 × 10(-32)) and SLC22A12 (P= 2.1 × 10(-10)). A novel rare non-synonymous variant of large effect size in SLC22A12, rs12800450 (minor allele frequency 0.01, G65W), was identified and replicated (beta -1.19 mg/dl, P= 2.7 × 10(-16)). (14)C-urate transport assays showed reduced urate transport for the G65W URAT1 mutant. Finally, in analyses of 11 loci previously associated with serum urate in EA individuals, 10 of 11 lead single-nucleotide polymorphisms showed direction-consistent association with urate among AA. In summary, we identified and replicated one novel locus in association with serum urate levels and experimentally characterize the novel G65W variant in URAT1 as a functional allele. Our data support the importance of multi-ethnic GWAS in the identification of novel risk loci as well as functional variants.
Keywords: Adult; African Americans; Aged; Animals; CHO Cells; Cricetinae; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Gout; Humans; Loss of Heterozygosity; Male; Middle Aged; Organic Anion Transporters; Organic Cation Transport Proteins; Polymorphism, Single Nucleotide; Uric Acid; Young Adult

A genome-wide association study identifies novel loci associated with circulating IGF-I and IGFBP-3. - Kaplan, Robert C; Petersen, Ann-Kristin; Chen, Ming-Huei; Teumer, Alexander; Glazer, Nicole L; Döring, Angela; Lam, Carolyn S P; Friedrich, Nele; Newman, Anne; Müller, Martina; Yang, Qiong; Homuth, Georg; et al. (Hum Mol Genet, 2011)
Insulin-like growth factor-I (IGF-I) and insulin-like growth factor-binding protein-3 (IGFBP-3) are involved in cell replication, proliferation, differentiation, protein synthesis, carbohydrate homeostasis and bone metabolism. Circulating IGF-I and IGFBP-3 concentrations predict anthropometric traits and risk of cancer and cardiovascular disease. In a genome-wide association study of 10 280 middle-aged and older men and women from four community-based cohort studies, we confirmed a known association of single nucleotide polymorphisms in the IGFBP3 gene region on chromosome 7p12.3 with IGFBP-3 concentrations using a significance threshold of P < 5 × 10(-8) (P = 3.3 × 10(-101)). Furthermore, the same IGFBP3 gene locus (e.g. rs11977526) that was associated with IGFBP-3 concentrations was also associated with the opposite direction of effect, with IGF-I concentration after adjustment for IGFBP-3 concentration (P = 1.9 × 10(-26)). A novel and independent locus on chromosome 7p12.3 (rs700752) had genome-wide significant associations with higher IGFBP-3 (P = 4.4 × 10(-21)) and higher IGF-I (P = 4.9 × 10(-9)) concentrations; when the two measurements were adjusted for one another, the IGF-I association was attenuated but the IGFBP-3 association was not. Two additional loci demonstrated genome-wide significant associations with IGFBP-3 concentration (rs1065656, chromosome 16p13.3, P = 1.2 × 10(-11), IGFALS, a confirmatory finding; and rs4234798, chromosome 4p16.1, P = 4.5 × 10(-10), SORCS2, a novel finding). Together, the four genome-wide significant loci explained 6.5% of the population variation in IGFBP-3 concentration. Furthermore, we observed a borderline statistically significant association between IGF-I concentration and FOXO3 (rs2153960, chromosome 6q21, P = 5.1 × 10(-7)), a locus associated with longevity. These genetic loci deserve further investigation to elucidate the biological basis for the observed associations and clarify their possible role in IGF-mediated regulation of cell growth and metabolism.
Keywords: Aged; Chromosomes, Human, Pair 7; Cohort Studies; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Polymorphism, Single Nucleotide

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

A genome-wide association study of aging. - Walter, Stefan; Atzmon, Gil; Demerath, Ellen W; Garcia, Melissa E; Kaplan, Robert C; Kumari, Meena; Lunetta, Kathryn L; Milaneschi, Yuri; Tanaka, Toshiko; Tranah, Gregory J; Völker, Uwe; Yu, Lei; et al. (Neurobiol Aging, 2011)
Human longevity and healthy aging show moderate heritability (20%-50%). We conducted a meta-analysis of genome-wide association studies from 9 studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium for 2 outcomes: (1) all-cause mortality, and (2) survival free of major disease or death. No single nucleotide polymorphism (SNP) was a genome-wide significant predictor of either outcome (p < 5 × 10(-8)). We found 14 independent SNPs that predicted risk of death, and 8 SNPs that predicted event-free survival (p < 10(-5)). These SNPs are in or near genes that are highly expressed in the brain (HECW2, HIP1, BIN2, GRIA1), genes involved in neural development and function (KCNQ4, LMO4, GRIA1, NETO1) and autophagy (ATG4C), and genes that are associated with risk of various diseases including cancer and Alzheimer's disease. In addition to considerable overlap between the traits, pathway and network analysis corroborated these findings. These findings indicate that variation in genes involved in neurological processes may be an important factor in regulating aging free of major disease and achieving longevity.
Keywords: Aging; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Longevity

Hospitalization for infection and risk of acute ischemic stroke: the Cardiovascular Health Study. - Elkind, Mitchell S V; Carty, Cara L; O'Meara, Ellen S; Lumley, Thomas; Lefkowitz, David; Kronmal, Richard A; Longstreth, W T (Stroke, 2011)
BACKGROUND AND PURPOSE: Little is known about the acute precipitants of ischemic stroke, although evidence suggests infections contribute to risk. We hypothesized that acute hospitalization for infection is associated with the short-term risk of stroke. METHODS: The case-crossover design was used to compare hospitalization for infection during case periods (90, 30, or 14 days before an incident ischemic stroke) and control periods (equivalent time periods exactly 1 or 2 years before stroke) in the Cardiovascular Health Study, a population-based cohort of 5888 elderly participants from 4 US sites. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated by conditional logistic regression. Confirmatory analyses assessed hazard ratios of stroke from Cox regression models, with hospitalization for infection as a time-varying exposure. RESULTS: During a median follow-up of 12.2 years, 669 incident ischemic strokes were observed in participants without a baseline history of stroke. Hospitalization for infection was more likely during case than control time periods; for 90 days before stroke, OR=3.4 (95% CI, 1.8 to 6.5). The point estimates of risks were higher when we examined shorter intervals: for 30 days, OR=7.3 (95% CI, 1.9 to 40.9), and for 14 days, OR=8.0 (95% CI, 1.7 to 77.3). In survival analyses, risk of stroke was associated with hospitalization for infection in the preceding 90 days, adjusted hazard ratio=2.4 (95% CI, 1.6 to 3.4). CONCLUSIONS: Hospitalization for infection is associated with a short-term increased risk of stroke, with higher risks observed for shorter intervals preceding stroke.
Keywords: Bacterial Infections; Brain Ischemia; Cardiology; Cohort Studies; Cross-Over Studies; Female; Follow-Up Studies; Hospitalization; Humans; Male; Odds Ratio; Proportional Hazards Models; Regression Analysis; Risk; Stroke; Time Factors

Identification of a sudden cardiac death susceptibility locus at 2q24.2 through genome-wide association in European ancestry individuals. - Arking, Dan E; Junttila, M Juhani; Goyette, Philippe; Huertas-Vazquez, Adriana; Eijgelsheim, Mark; Blom, Marieke T; Newton-Cheh, Christopher; Reinier, Kyndaron; Teodorescu, Carmen; Uy-Evanado, Audrey; Carter-Monroe, Naima; Kaikkonen, Kari S; et al. (PLoS Genet, 2011)
Sudden cardiac death (SCD) continues to be one of the leading causes of mortality worldwide, with an annual incidence estimated at 250,000-300,000 in the United States and with the vast majority occurring in the setting of coronary disease. We performed a genome-wide association meta-analysis in 1,283 SCD cases and >20,000 control individuals of European ancestry from 5 studies, with follow-up genotyping in up to 3,119 SCD cases and 11,146 controls from 11 European ancestry studies, and identify the BAZ2B locus as associated with SCD (P = 1.8×10(-10)). The risk allele, while ancestral, has a frequency of ~1.4%, suggesting strong negative selection and increases risk for SCD by 1.92-fold per allele (95% CI 1.57-2.34). We also tested the role of 49 SNPs previously implicated in modulating electrocardiographic traits (QRS, QT, and RR intervals). Consistent with epidemiological studies showing increased risk of SCD with prolonged QRS/QT intervals, the interval-prolonging alleles are in aggregate associated with increased risk for SCD (P = 0.006).
Keywords: Adult; Aged; Alleles; Chromosomes, Human, Pair 2; Death, Sudden, Cardiac; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Myocardial Contraction; Polymorphism, Single Nucleotide

Large-scale candidate gene analysis in whites and African Americans identifies IL6R polymorphism in relation to atrial fibrillation: the National Heart, Lung, and Blood Institute's Candidate Gene Association Resource (CARe) project. - Schnabel, Renate B; Kerr, Kathleen F; Lubitz, Steven A; Alkylbekova, Ermeg L; Marcus, Gregory M; Sinner, Moritz F; Magnani, Jared W; Wolf, Philip A; Deo, Rajat; Lloyd-Jones, Donald M; Lunetta, Kathryn L; Mehra, Reena; et al. (Circ Cardiovasc Genet, 2011)
BACKGROUND: The genetic background of atrial fibrillation (AF) in whites and African Americans is largely unknown. Genes in cardiovascular pathways have not been systematically investigated. METHODS AND RESULTS: We examined a panel of approximately 50,000 common single-nucleotide polymorphisms (SNPs) in 2095 cardiovascular candidate genes and AF in 3 cohorts with participants of European (n=18,524; 2260 cases) or African American descent (n=3662; 263 cases) in the National Heart, Lung, and Blood Institute's Candidate Gene Association Resource. Results in whites were followed up in the German Competence Network for AF (n=906, 468 cases). The top result was assessed in relation to incident ischemic stroke in the Cohorts for Heart and Aging Research in Genomic Epidemiology Stroke Consortium (n=19,602 whites, 1544 incident strokes). SNP rs4845625 in the IL6R gene was associated with AF (relative risk [RR] C allele, 0.90; 95% confidence interval [CI], 0.85-0.95; P=0.0005) in whites but did not reach statistical significance in African Americans (RR, 0.86; 95% CI, 0.72-1.03; P=0.09). The results were comparable in the German AF Network replication, (RR, 0.71; 95% CI, 0.57-0.89; P=0.003). No association between rs4845625 and stroke was observed in whites. The known chromosome 4 locus near PITX2 in whites also was associated with AF in African Americans (rs4611994; hazard ratio, 1.40; 95% CI, 1.16-1.69; P=0.0005). CONCLUSIONS: In a community-based cohort meta-analysis, we identified genetic association in IL6R with AF in whites. Additionally, we demonstrated that the chromosome 4 locus known from recent genome-wide association studies in whites is associated with AF in African Americans.
Keywords: African Americans; Aged; Alleles; Atrial Fibrillation; Chromosomes, Human, Pair 4; Cohort Studies; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors; Stroke; United States

Measures of adiposity and future risk of ischemic stroke and coronary heart disease in older men and women. - Kizer, Jorge R; Biggs, Mary L; Ix, Joachim H; Mukamal, Kenneth J; Zieman, Susan J; de Boer, Ian H; Mozaffarian, Dariush; Barzilay, Joshua I; Strotmeyer, Elsa S; Luchsinger, José A; Elkind, Mitchell S V; Longstreth, W T; et al. (Am J Epidemiol, 2011)
The relation between measures of general and central adiposity and individual cardiovascular endpoints remains understudied in older adults. This study investigated the association of measures of body size and composition with incident ischemic stroke or coronary heart disease (1989-2007) in 3,754 community-dwelling US adults aged 65-100 years. Standardized anthropometry and bioelectric impedance measurements were obtained at baseline. Body mass index at age 50 years (BMI50) was calculated on the basis of recalled weight. Although only waist/hip ratio was significantly associated with ischemic stroke in quintile analysis in women, dichotomized body mass index (BMI) (≥ 30 kg/m²) was the only significant predictor in men. For coronary heart disease, there were significant positive adjusted associations for all adiposity measures, without interaction by sex. This was true for both quintiles and conventional cutpoints for obesity, although BMI-defined overweight (25-29.9 kg/m² was significant at midlife but not at baseline. Strengths of association for extreme quintiles (quintile 5 vs. quintile 1) were broadly comparable, but the highest effect estimates were for waist/hip ratio (hazard ratio = 1.56, 95% confidence interval: 1.25, 1.94) and BMI50 (hazard ratio = 1.71, 95% confidence interval: 1.37, 2.14), both of which remained significant after adjustment for mediators, BMI, or each other. Whether these differences translate to better risk prediction will require meta-analytical approaches, as will determination of prognostic cutpoints.
Keywords: Adiposity; Age Factors; Aged; Aged, 80 and over; Brain Ischemia; Coronary Disease; Female; Humans; Incidence; Male; Middle Aged; Obesity; Prevalence; Retrospective Studies; Risk Factors; Sex Factors; United States

Meta-analysis of genome-wide association studies from the CHARGE consortium identifies common variants associated with carotid intima media thickness and plaque. - Bis, Joshua C; Kavousi, Maryam; Franceschini, Nora; Isaacs, Aaron; Abecasis, Goncalo R; Schminke, Ulf; Post, Wendy S; Smith, Albert V; Cupples, L Adrienne; Markus, Hugh S; Schmidt, Reinhold; Huffman, Jennifer E; et al. (Nat Genet, 2011)
Carotid intima media thickness (cIMT) and plaque determined by ultrasonography are established measures of subclinical atherosclerosis that each predicts future cardiovascular disease events. We conducted a meta-analysis of genome-wide association data in 31,211 participants of European ancestry from nine large studies in the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. We then sought additional evidence to support our findings among 11,273 individuals using data from seven additional studies. In the combined meta-analysis, we identified three genomic regions associated with common carotid intima media thickness and two different regions associated with the presence of carotid plaque (P < 5 × 10(-8)). The associated SNPs mapped in or near genes related to cellular signaling, lipid metabolism and blood pressure homeostasis, and two of the regions were associated with coronary artery disease (P < 0.006) in the Coronary Artery Disease Genome-Wide Replication and Meta-Analysis (CARDIoGRAM) consortium. Our findings may provide new insight into pathways leading to subclinical atherosclerosis and subsequent cardiovascular events.
Keywords: Adult; Aged; Aging; Atherosclerosis; Carotid Intima-Media Thickness; Cohort Studies; Coronary Artery Disease; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Heart; Humans; Middle Aged; Phenotype; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Risk Factors

Meta-analysis of genome-wide association studies in >80 000 subjects identifies multiple loci for C-reactive protein levels. - Dehghan, Abbas; Dupuis, Josée; Barbalic, Maja; Bis, Joshua C; Eiriksdottir, Gudny; Lu, Chen; Pellikka, Niina; Wallaschofski, Henri; Kettunen, Johannes; Henneman, Peter; Baumert, Jens; Strachan, David P; et al. (Circulation, 2011)
BACKGROUND: C-reactive protein (CRP) is a heritable marker of chronic inflammation that is strongly associated with cardiovascular disease. We sought to identify genetic variants that are associated with CRP levels. METHODS AND RESULTS: We performed a genome-wide association analysis of CRP in 66 185 participants from 15 population-based studies. We sought replication for the genome-wide significant and suggestive loci in a replication panel comprising 16 540 individuals from 10 independent studies. We found 18 genome-wide significant loci, and we provided evidence of replication for 8 of them. Our results confirm 7 previously known loci and introduce 11 novel loci that are implicated in pathways related to the metabolic syndrome (APOC1, HNF1A, LEPR, GCKR, HNF4A, and PTPN2) or the immune system (CRP, IL6R, NLRP3, IL1F10, and IRF1) or that reside in regions previously not known to play a role in chronic inflammation (PPP1R3B, SALL1, PABPC4, ASCL1, RORA, and BCL7B). We found a significant interaction of body mass index with LEPR (P<2.9×10(-6)). A weighted genetic risk score that was developed to summarize the effect of risk alleles was strongly associated with CRP levels and explained ≈5% of the trait variance; however, there was no evidence for these genetic variants explaining the association of CRP with coronary heart disease. CONCLUSIONS: We identified 18 loci that were associated with CRP levels. Our study highlights immune response and metabolic regulatory pathways involved in the regulation of chronic inflammation.
Keywords: Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Risk Factors; Vasculitis

Neighborhood disadvantage and ischemic stroke: the Cardiovascular Health Study (CHS). - Brown, Arleen F; Liang, Li-Jung; Vassar, Stefanie D; Stein-Merkin, Sharon; Longstreth, W T; Ovbiagele, Bruce; Yan, Tingjian; Escarce, José J (Stroke, 2011)
BACKGROUND AND PURPOSE: Neighborhood characteristics may influence the risk of stroke and contribute to socioeconomic disparities in stroke incidence. The objectives of this study were to examine the relationship between neighborhood socioeconomic status and incident ischemic stroke and examine potential mediators of these associations. METHODS: We analyzed data from 3834 whites and 785 blacks enrolled in the Cardiovascular Health Study, a multicenter, population-based, longitudinal study of adults ages≥65 years from 4 US counties. The primary outcome was adjudicated incident ischemic stroke. Neighborhood socioeconomic status was measured using a composite of 6 census tract variables. Race-stratified multilevel Cox proportional hazard models were constructed adjusted for sociodemographic, behavioral, and biological risk factors. RESULTS: Among whites, in models adjusted for sociodemographic characteristics, stroke hazard was significantly higher among residents of neighborhoods in the lowest compared with the highest neighborhood socioeconomic status quartile (hazard ratio, 1.32; 95% CI, 1.01-1.72) with greater attenuation of the hazard ratio after adjustment for biological risk factors (hazard ratio, 1.16; 0.88-1.52) than for behavioral risk factors (hazard ratio, 1.30; 0.99-1.70). Among blacks, we found no significant associations between neighborhood socioeconomic status and ischemic stroke. CONCLUSIONS: Higher risk of incident ischemic stroke was observed in the most disadvantaged neighborhoods among whites, but not among blacks. The relationship between neighborhood socioeconomic status and stroke among whites appears to be mediated more strongly by biological than behavioral risk factors.
Keywords: Aged; Aged, 80 and over; Brain Ischemia; Female; Health Status Disparities; Humans; Incidence; Longitudinal Studies; Male; Poverty; Residence Characteristics; Risk; Risk Factors; Social Class; Social Environment; Socioeconomic Factors; Stroke; Urban Population

New gene functions in megakaryopoiesis and platelet formation. - Gieger, Christian; Radhakrishnan, Aparna; Cvejic, Ana; Tang, Weihong; Porcu, Eleonora; Pistis, Giorgio; Serbanovic-Canic, Jovana; Elling, Ulrich; Goodall, Alison H; Labrune, Yann; Lopez, Lorna M; Mägi, Reedik; et al. (Nature, 2011)
Platelets are the second most abundant cell type in blood and are essential for maintaining haemostasis. Their count and volume are tightly controlled within narrow physiological ranges, but there is only limited understanding of the molecular processes controlling both traits. Here we carried out a high-powered meta-analysis of genome-wide association studies (GWAS) in up to 66,867 individuals of European ancestry, followed by extensive biological and functional assessment. We identified 68 genomic loci reliably associated with platelet count and volume mapping to established and putative novel regulators of megakaryopoiesis and platelet formation. These genes show megakaryocyte-specific gene expression patterns and extensive network connectivity. Using gene silencing in Danio rerio and Drosophila melanogaster, we identified 11 of the genes as novel regulators of blood cell formation. Taken together, our findings advance understanding of novel gene functions controlling fate-determining events during megakaryopoiesis and platelet formation, providing a new example of successful translation of GWAS to function.
Keywords: Animals; Blood Platelets; Cell Size; Drosophila melanogaster; Drosophila Proteins; Europe; Gene Expression Profiling; Gene Silencing; Genome, Human; Genome-Wide Association Study; Hematopoiesis; Humans; Megakaryocytes; Platelet Count; Protein Interaction Maps; Transcription, Genetic; Zebrafish; Zebrafish Proteins

Separate and combined associations of body-mass index and abdominal adiposity with cardiovascular disease: collaborative analysis of 58 prospective studies. - Wormser, David; Kaptoge, Stephen; Di Angelantonio, Emanuele; Wood, Angela M; Pennells, Lisa; Thompson, Alex; Sarwar, Nadeem; Kizer, Jorge R; Lawlor, Debbie A; Nordestgaard, Børge G; Ridker, Paul; Salomaa, Veikko; et al. (Lancet, 2011)
BACKGROUND: Guidelines differ about the value of assessment of adiposity measures for cardiovascular disease risk prediction when information is available for other risk factors. We studied the separate and combined associations of body-mass index (BMI), waist circumference, and waist-to-hip ratio with risk of first-onset cardiovascular disease. METHODS: We used individual records from 58 cohorts to calculate hazard ratios (HRs) per 1 SD higher baseline values (4.56 kg/m(2) higher BMI, 12.6 cm higher waist circumference, and 0.083 higher waist-to-hip ratio) and measures of risk discrimination and reclassification. Serial adiposity assessments were used to calculate regression dilution ratios. RESULTS: Individual records were available for 221,934 people in 17 countries (14,297 incident cardiovascular disease outcomes; 1.87 million person-years at risk). Serial adiposity assessments were made in up to 63,821 people (mean interval 5.7 years [SD 3.9]). In people with BMI of 20 kg/m(2) or higher, HRs for cardiovascular disease were 1.23 (95% CI 1.17-1.29) with BMI, 1.27 (1.20-1.33) with waist circumference, and 1.25 (1.19-1.31) with waist-to-hip ratio, after adjustment for age, sex, and smoking status. After further adjustment for baseline systolic blood pressure, history of diabetes, and total and HDL cholesterol, corresponding HRs were 1.07 (1.03-1.11) with BMI, 1.10 (1.05-1.14) with waist circumference, and 1.12 (1.08-1.15) with waist-to-hip ratio. Addition of information on BMI, waist circumference, or waist-to-hip ratio to a cardiovascular disease risk prediction model containing conventional risk factors did not importantly improve risk discrimination (C-index changes of -0.0001, -0.0001, and 0.0008, respectively), nor classification of participants to categories of predicted 10-year risk (net reclassification improvement -0.19%, -0.05%, and -0.05%, respectively). Findings were similar when adiposity measures were considered in combination. Reproducibility was greater for BMI (regression dilution ratio 0.95, 95% CI 0.93-0.97) than for waist circumference (0.86, 0.83-0.89) or waist-to-hip ratio (0.63, 0.57-0.70). INTERPRETATION: BMI, waist circumference, and waist-to-hip ratio, whether assessed singly or in combination, do not importantly improve cardiovascular disease risk prediction in people in developed countries when additional information is available for systolic blood pressure, history of diabetes, and lipids. FUNDING: British Heart Foundation and UK Medical Research Council.
Keywords: Age Factors; Blood Pressure; Body Mass Index; Cardiovascular Diseases; Cholesterol; Cholesterol, HDL; Diabetes Mellitus; Female; Humans; Male; Middle Aged; Obesity, Abdominal; Proportional Hazards Models; Prospective Studies; Risk Assessment; Sex Factors; Smoking; Systole; Waist Circumference; Waist-Hip Ratio

Surrogate screening models for the low physical activity criterion of frailty. - Eckel, Sandrah P; Bandeen-Roche, Karen; Chaves, Paulo H M; Fried, Linda P; Louis, Thomas A (Aging Clin Exp Res, 2011)
BACKGROUND AND AIMS: Low physical activity, one of five criteria in a validated clinical phenotype of frailty, is assessed by a standardized, semiquantitative questionnaire on up to 20 leisure time activities. Because of the time demanded to collect the interview data, it has been challenging to translate to studies other than the Cardiovascular Health Study (CHS), for which it was developed. Considering subsets of activities, we identified and evaluated streamlined surrogate assessment methods and compared them to one implemented in the Women's Health and Aging Study (WHAS). METHODS: Using data on men and women ages 65 and older from the CHS, we applied logistic regression models to rank activities by "relative influence" in predicting low physical activity.We considered subsets of the most influential activities as inputs to potential surrogate models (logistic regressions). We evaluated predictive accuracy and predictive validity using the area under receiver operating characteristic curves and assessed criterion validity using proportional hazards models relating frailty status (defined using the surrogate) to mortality. RESULTS: Walking for exercise and moderately strenuous household chores were highly influential for both genders. Women required fewer activities than men for accurate classification. The WHAS model (8 CHS activities) was an effective surrogate, but a surrogate using 6 activities (walking, chores, gardening, general exercise, mowing and golfing) was also highly predictive. CONCLUSIONS: We recommend a 6 activity questionnaire to assess physical activity for men and women. If efficiency is essential and the study involves only women, fewer activities can be included.
Keywords: Activities of Daily Living; Aged; Cohort Studies; Exercise; Female; Follow-Up Studies; Frail Elderly; Geriatric Assessment; Humans; Leisure Activities; Logistic Models; Male; Motor Activity; Prospective Studies; Surveys and Questionnaires; Women's Health

Trajectory of cognitive decline as a predictor of psychosis in early Alzheimer disease in the cardiovascular health study. - Emanuel, James E; Lopez, Oscar L; Houck, Patricia R; Becker, James T; Weamer, Elise A; Demichele-Sweet, Mary Ann A; Kuller, Lewis; Sweet, Robert A (Am J Geriatr Psychiatry, 2011)
OBJECTIVE: To compare the trajectories of cognitive decline between groups with, and without, the later development of psychotic symptoms during Alzheimer disease (AD) or mild cognitive impairment (MCI). DESIGN: : The authors examined cognitive function in a new analysis of an existing data set, the Cardiovascular Health Study, an epidemiologic, longitudinal follow-up study. Our analyses examined 9 years of follow-up data. SETTING: Community. PARTICIPANTS: The authors examined subjects who were without dementia at study entry, received a diagnosis of AD or MCI during follow-up, and had been rated on the Neuropsychiatric Inventory for the presence of psychosis; 362 participants for the modified Mini-Mental State Examination (3MS) analysis and 350 participants for the digit symbol substitution test (DSST) analysis had sufficient follow-up data and apolipoprotein-∊ (APOE) genotyping. MEASUREMENTS: The 3MS and DSST were administered annually and analyzed using mixed-effects models including APOE4 status. RESULTS: : Mean 3MS and DSST scores did not differ between AD with psychosis (AD + P) and without psychosis groups at baseline. The 3MS and DSST scores decreased more rapidly in subjects who ultimately developed psychosis. CONCLUSIONS: Individuals who ultimately develop psychosis have more rapid cognitive deterioration during the earliest phases of AD than individuals with AD not developing psychosis. The genetic and other neurobiologic factors leading to the expression of AD + P may exert their effects by acceleration of the neurodegenerative process.
Keywords: Aged; Alzheimer Disease; Chi-Square Distribution; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Psychiatric Status Rating Scales; Psychotic Disorders; Time Factors

Vitamin D, parathyroid hormone, and sudden cardiac death: results from the Cardiovascular Health Study. - Deo, Rajat; Katz, Ronit; Shlipak, Michael G; Sotoodehnia, Nona; Psaty, Bruce M; Sarnak, Mark J; Fried, Linda F; Chonchol, Michel; de Boer, Ian H; Enquobahrie, Daniel; Siscovick, David; Kestenbaum, Bryan (Hypertension, 2011)
Recent studies have demonstrated greater risks of cardiovascular events and mortality among persons who have lower 25-hydroxyvitamin D (25-OHD) and higher parathyroid hormone (PTH) levels. We sought to evaluate the association between markers of mineral metabolism and sudden cardiac death (SCD) among the 2312 participants from the Cardiovascular Health Study who were free of clinical cardiovascular disease at baseline. We estimated associations of baseline 25-OHD and PTH concentrations individually and in combination with SCD using Cox proportional hazards models after adjustment for demographics, cardiovascular risk factors, and kidney function. During a median follow-up of 14 years, there were 73 adjudicated SCD events. The annual incidence of SCD was greater among subjects who had lower 25-OHD concentrations, 2 events per 1000 for 25-OHD ≥20 ng/mL and 4 events per 1000 for 25-OHD <20 ng/mL. Similarly, SCD incidence was greater among subjects who had higher PTH concentrations, 2 events per 1000 for PTH <65 pg/mL and 4 events per 1000 for PTH ≥65 pg/mL. Multivariate adjustment attenuated associations of 25-OHD and PTH with SCD. Finally, 267 participants (11.7% of the cohort) had high PTH and low 25-OHD concentrations. This combination was associated with a >2-fold risk of SCD after adjustment (hazard ratio: 2.19 [95% CI: 1.17-4.10]; P=0.017) compared with participants with normal levels of PTH and 25-OHD. The combination of lower 25-OHD and higher PTH concentrations appears to be associated independently with SCD risk among older adults without cardiovascular disease.
Keywords: Aged; Cardiovascular Diseases; Comorbidity; Death, Sudden, Cardiac; Diabetes Mellitus; Female; Follow-Up Studies; Humans; Hypertension; Incidence; Kidney; Male; Middle Aged; Minerals; Parathyroid Hormone; Proportional Hazards Models; Risk Factors; Socioeconomic Factors; United States; Vitamin D

Assessment of gene-by-sex interaction effect on bone mineral density. - Liu, Ching-Ti; Estrada, Karol; Yerges-Armstrong, Laura M; Amin, Najaf; Evangelou, Evangelos; Li, Guo; Minster, Ryan L; Carless, Melanie A; Kammerer, Candace M; Oei, Ling; Zhou, Yanhua; Alonso, Nerea; et al. (J Bone Miner Res, 2012)
Sexual dimorphism in various bone phenotypes, including bone mineral density (BMD), is widely observed; however, the extent to which genes explain these sex differences is unclear. To identify variants with different effects by sex, we examined gene-by-sex autosomal interactions genome-wide, and performed expression quantitative trait loci (eQTL) analysis and bioinformatics network analysis. We conducted an autosomal genome-wide meta-analysis of gene-by-sex interaction on lumbar spine (LS) and femoral neck (FN) BMD in 25,353 individuals from 8 cohorts. In a second stage, we followed up the 12 top single-nucleotide polymorphisms (SNPs; p < 1 × 10(-5) ) in an additional set of 24,763 individuals. Gene-by-sex interaction and sex-specific effects were examined in these 12 SNPs. We detected one novel genome-wide significant interaction associated with LS-BMD at the Chr3p26.1-p25.1 locus, near the GRM7 gene (male effect = 0.02 and p = 3.0 × 10(-5) ; female effect = -0.007 and p = 3.3 × 10(-2) ), and 11 suggestive loci associated with either FN- or LS-BMD in discovery cohorts. However, there was no evidence for genome-wide significant (p < 5 × 10(-8) ) gene-by-sex interaction in the joint analysis of discovery and replication cohorts. Despite the large collaborative effort, no genome-wide significant evidence for gene-by-sex interaction was found to influence BMD variation in this screen of autosomal markers. If they exist, gene-by-sex interactions for BMD probably have weak effects, accounting for less than 0.08% of the variation in these traits per implicated SNP. © 2012 American Society for Bone and Mineral Research.
Keywords: Bone Density; Cohort Studies; Female; Genes; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Sex Characteristics

Association between chromosome 9p21 variants and the ankle-brachial index identified by a meta-analysis of 21 genome-wide association studies. - Murabito, Joanne M; White, Charles C; Kavousi, Maryam; Sun, Yan V; Feitosa, Mary F; Nambi, Vijay; Lamina, Claudia; Schillert, Arne; Coassin, Stefan; Bis, Joshua C; Broer, Linda; Crawford, Dana C; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Genetic determinants of peripheral arterial disease (PAD) remain largely unknown. To identify genetic variants associated with the ankle-brachial index (ABI), a noninvasive measure of PAD, we conducted a meta-analysis of genome-wide association study data from 21 population-based cohorts. METHODS AND RESULTS: Continuous ABI and PAD (ABI ≤0.9) phenotypes adjusted for age and sex were examined. Each study conducted genotyping and imputed data to the ≈2.5 million single nucleotide polymorphisms (SNPs) in HapMap. Linear and logistic regression models were used to test each SNP for association with ABI and PAD using additive genetic models. Study-specific data were combined using fixed effects inverse variance weighted meta-analyses. There were a total of 41 692 participants of European ancestry (≈60% women, mean ABI 1.02 to 1.19), including 3409 participants with PAD and with genome-wide association study data available. In the discovery meta-analysis, rs10757269 on chromosome 9 near CDKN2B had the strongest association with ABI (β=-0.006, P=2.46×10(-8)). We sought replication of the 6 strongest SNP associations in 5 population-based studies and 3 clinical samples (n=16 717). The association for rs10757269 strengthened in the combined discovery and replication analysis (P=2.65×10(-9)). No other SNP associations for ABI or PAD achieved genome-wide significance. However, 2 previously reported candidate genes for PAD and 1 SNP associated with coronary artery disease were associated with ABI: DAB21P (rs13290547, P=3.6×10(-5)), CYBA (rs3794624, P=6.3×10(-5)), and rs1122608 (LDLR, P=0.0026). CONCLUSIONS: Genome-wide association studies in more than 40 000 individuals identified 1 genome wide significant association on chromosome 9p21 with ABI. Two candidate genes for PAD and 1 SNP for coronary artery disease are associated with ABI.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alleles; Ankle Brachial Index; Chromosomes, Human, Pair 9; Cohort Studies; Cyclin-Dependent Kinase Inhibitor p15; Female; Genome-Wide Association Study; Genotype; HapMap Project; Humans; Logistic Models; Male; Middle Aged; Peripheral Vascular Diseases; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Sex Factors

Classification algorithms for predicting sleepiness and sleep apnea severity. - Eiseman, Nathaniel A; Westover, M Brandon; Mietus, Joseph E; Thomas, Robert J; Bianchi, Matt T (J Sleep Res, 2012)
Identifying predictors of subjective sleepiness and severity of sleep apnea are important yet challenging goals in sleep medicine. Classification algorithms may provide insights, especially when large data sets are available. We analyzed polysomnography and clinical features available from the Sleep Heart Health Study. The Epworth Sleepiness Scale and the apnea-hypopnea index were the targets of three classifiers: k-nearest neighbor, naive Bayes and support vector machine algorithms. Classification was based on up to 26 features including demographics, polysomnogram, and electrocardiogram (spectrogram). Naive Bayes was best for predicting abnormal Epworth class (0-10 versus 11-24), although prediction was weak: polysomnogram features had 16.7% sensitivity and 88.8% specificity; spectrogram features had 5.3% sensitivity and 96.5% specificity. The support vector machine performed similarly to naive Bayes for predicting sleep apnea class (0-5 versus >5): 59.0% sensitivity and 74.5% specificity using clinical features and 43.4% sensitivity and 83.5% specificity using spectrographic features compared with the naive Bayes classifier, which had 57.5% sensitivity and 73.7% specificity (clinical), and 39.0% sensitivity and 82.7% specificity (spectrogram). Mutual information analysis confirmed the minimal dependency of the Epworth score on any feature, while the apnea-hypopnea index showed modest dependency on body mass index, arousal index, oxygenation and spectrogram features. Apnea classification was modestly accurate, using either clinical or spectrogram features, and showed lower sensitivity and higher specificity than common sleep apnea screening tools. Thus, clinical prediction of sleep apnea may be feasible with easily obtained demographic and electrocardiographic analysis, but the utility of the Epworth is questioned by its minimal relation to clinical, electrocardiographic, or polysomnographic features.
Keywords: Adult; Algorithms; Disorders of Excessive Somnolence; Electrocardiography; Humans; Polysomnography; Prognosis; Psychometrics; Sensitivity and Specificity; Severity of Illness Index; Sleep Apnea, Obstructive; Sleep Stages

Comparison of risk prediction using the CKD-EPI equation and the MDRD study equation for estimated glomerular filtration rate. - Matsushita, Kunihiro; Mahmoodi, Bakhtawar K; Woodward, Mark; Emberson, Jonathan R; Jafar, Tazeen H; Jee, Sun Ha; Polkinghorne, Kevan R; Shankar, Anoop; Smith, David H; Tonelli, Marcello; Warnock, David G; Wen, Chi-Pang; et al. (JAMA, 2012)
CONTEXT: The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation more accurately estimates glomerular filtration rate (GFR) than the Modification of Diet in Renal Disease (MDRD) Study equation using the same variables, especially at higher GFR, but definitive evidence of its risk implications in diverse settings is lacking. OBJECTIVE: To evaluate risk implications of estimated GFR using the CKD-EPI equation compared with the MDRD Study equation in populations with a broad range of demographic and clinical characteristics. DESIGN, SETTING, AND PARTICIPANTS: A meta-analysis of data from 1.1 million adults (aged ≥ 18 years) from 25 general population cohorts, 7 high-risk cohorts (of vascular disease), and 13 CKD cohorts. Data transfer and analyses were conducted between March 2011 and March 2012. MAIN OUTCOME MEASURES: All-cause mortality (84,482 deaths from 40 cohorts), cardiovascular mortality (22,176 events from 28 cohorts), and end-stage renal disease (ESRD) (7644 events from 21 cohorts) during 9.4 million person-years of follow-up; the median of mean follow-up time across cohorts was 7.4 years (interquartile range, 4.2-10.5 years). RESULTS: Estimated GFR was classified into 6 categories (≥90, 60-89, 45-59, 30-44, 15-29, and <15 mL/min/1.73 m(2)) by both equations. Compared with the MDRD Study equation, 24.4% and 0.6% of participants from general population cohorts were reclassified to a higher and lower estimated GFR category, respectively, by the CKD-EPI equation, and the prevalence of CKD stages 3 to 5 (estimated GFR <60 mL/min/1.73 m(2)) was reduced from 8.7% to 6.3%. In estimated GFR of 45 to 59 mL/min/1.73 m(2) by the MDRD Study equation, 34.7% of participants were reclassified to estimated GFR of 60 to 89 mL/min/1.73 m(2) by the CKD-EPI equation and had lower incidence rates (per 1000 person-years) for the outcomes of interest (9.9 vs 34.5 for all-cause mortality, 2.7 vs 13.0 for cardiovascular mortality, and 0.5 vs 0.8 for ESRD) compared with those not reclassified. The corresponding adjusted hazard ratios were 0.80 (95% CI, 0.74-0.86) for all-cause mortality, 0.73 (95% CI, 0.65-0.82) for cardiovascular mortality, and 0.49 (95% CI, 0.27-0.88) for ESRD. Similar findings were observed in other estimated GFR categories by the MDRD Study equation. Net reclassification improvement based on estimated GFR categories was significantly positive for all outcomes (range, 0.06-0.13; all P < .001). Net reclassification improvement was similarly positive in most subgroups defined by age (<65 years and ≥65 years), sex, race/ethnicity (white, Asian, and black), and presence or absence of diabetes and hypertension. The results in the high-risk and CKD cohorts were largely consistent with the general population cohorts. CONCLUSION: The CKD-EPI equation classified fewer individuals as having CKD and more accurately categorized the risk for mortality and ESRD than did the MDRD Study equation across a broad range of populations.
Keywords: African Continental Ancestry Group; Aged; Algorithms; Asian Continental Ancestry Group; Cardiovascular Diseases; Cohort Studies; Decision Support Techniques; European Continental Ancestry Group; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Models, Theoretical; Risk Assessment; Sex Factors

Effect of Alzheimer's disease risk genes on trajectories of cognitive function in the Cardiovascular Health Study. - Sweet, Robert A; Seltman, Howard; Emanuel, James E; Lopez, Oscar L; Becker, James T; Bis, Joshua C; Weamer, Elise A; Demichele-Sweet, Mary Ann A; Kuller, Lewis H (Am J Psychiatry, 2012)
OBJECTIVE: The trajectory of cognitive decline in patients with late-onset Alzheimer's disease varies widely. Genetic variations in CLU, PICALM, and CR1 are associated with Alzheimer's disease, but it is unknown whether they exert their effects by altering cognitive trajectory in elderly individuals at risk for the disease. METHOD: The authors developed a Bayesian model to fit cognitive trajectories in a cohort of elderly subjects and test for genetic effects. They first validated the model's ability to detect the previously established effects of APOE ε4 alleles on age at cognitive decline and of psychosis on the rate of cognitive decline in 802 subjects from the Cardiovascular Health Cognition Study who did not have dementia at study entry and developed incident dementia during follow-up. The authors then evaluated the effects of CLU, PICALM, and CR1 on age and rate of decline in 1,831 subjects who did not have dementia at study entry and then did or did not develop incident dementia by study's end. RESULTS: The model generated robust fits to the observed cognitive trajectory data, and validation analysis supported the model's utility. CLU and CR1 were associated with more rapid cognitive decline. PICALM was associated with an earlier age at midpoint of cognitive decline. Associations remained after accounting for the effects of APOE and demographic factors. CONCLUSIONS: Evaluation of cognitive trajectories provides a powerful approach to dissecting genetic effects on the processes leading to cognitive deterioration and Alzheimer's disease.
Keywords: Age of Onset; Aged; Alleles; Alzheimer Disease; Apolipoprotein E4; Bayes Theorem; Clusterin; Cohort Studies; Dementia; Disease Progression; Female; Genetic Predisposition to Disease; Humans; Male; Models, Psychological; Monomeric Clathrin Assembly Proteins; Polymorphism, Single Nucleotide; Receptors, Complement 3b; Risk Factors

Eight genetic loci associated with variation in lipoprotein-associated phospholipase A2 mass and activity and coronary heart disease: meta-analysis of genome-wide association studies from five community-based studies. - Grallert, Harald; Dupuis, Josée; Bis, Joshua C; Dehghan, Abbas; Barbalic, Maja; Baumert, Jens; Lu, Chen; Smith, Nicholas L; Uitterlinden, André G; Roberts, Robert; Khuseyinova, Natalie; Schnabel, Renate B; et al. (Eur Heart J, 2012)
AIMS: Lipoprotein-associated phospholipase A2 (Lp-PLA2) generates proinflammatory and proatherogenic compounds in the arterial vascular wall and is a potential therapeutic target in coronary heart disease (CHD). We searched for genetic loci related to Lp-PLA2 mass or activity by a genome-wide association study as part of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. METHODS AND RESULTS: In meta-analyses of findings from five population-based studies, comprising 13 664 subjects, variants at two loci (PLA2G7, CETP) were associated with Lp-PLA2 mass. The strongest signal was at rs1805017 in PLA2G7 [P = 2.4 × 10(-23), log Lp-PLA2 difference per allele (beta): 0.043]. Variants at six loci were associated with Lp-PLA2 activity (PLA2G7, APOC1, CELSR2, LDL, ZNF259, SCARB1), among which the strongest signals were at rs4420638, near the APOE-APOC1-APOC4-APOC2 cluster [P = 4.9 × 10(-30); log Lp-PLA2 difference per allele (beta): -0.054]. There were no significant gene-environment interactions between these eight polymorphisms associated with Lp-PLA2 mass or activity and age, sex, body mass index, or smoking status. Four of the polymorphisms (in APOC1, CELSR2, SCARB1, ZNF259), but not PLA2G7, were significantly associated with CHD in a second study. CONCLUSION: Levels of Lp-PLA2 mass and activity were associated with PLA2G7, the gene coding for this protein. Lipoprotein-associated phospholipase A2 activity was also strongly associated with genetic variants related to low-density lipoprotein cholesterol levels.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Coronary Artery Disease; Coronary Disease; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Phospholipases A2; Polymorphism, Single Nucleotide

Evaluation of the metabochip genotyping array in African Americans and implications for fine mapping of GWAS-identified loci: the PAGE study. - Buyske, Steven; Wu, Ying; Carty, Cara L; Cheng, Iona; Assimes, Themistocles L; Dumitrescu, Logan; Hindorff, Lucia A; Mitchell, Sabrina; Ambite, Jose Luis; Boerwinkle, Eric; Bůzková, Petra; Carlson, Chris S; et al. (PLoS One, 2012)
The Metabochip is a custom genotyping array designed for replication and fine mapping of metabolic, cardiovascular, and anthropometric trait loci and includes low frequency variation content identified from the 1000 Genomes Project. It has 196,725 SNPs concentrated in 257 genomic regions. We evaluated the Metabochip in 5,863 African Americans; 89% of all SNPs passed rigorous quality control with a call rate of 99.9%. Two examples illustrate the value of fine mapping with the Metabochip in African-ancestry populations. At CELSR2/PSRC1/SORT1, we found the strongest associated SNP for LDL-C to be rs12740374 (p = 3.5 × 10(-11)), a SNP indistinguishable from multiple SNPs in European ancestry samples due to high correlation. Its distinct signal supports functional studies elsewhere suggesting a causal role in LDL-C. At CETP we found rs17231520, with risk allele frequency 0.07 in African Americans, to be associated with HDL-C (p = 7.2 × 10(-36)). This variant is very rare in Europeans and not tagged in common GWAS arrays, but was identified as associated with HDL-C in African Americans in a single-gene study. Our results, one narrowing the risk interval and the other revealing an associated variant not found in Europeans, demonstrate the advantages of high-density genotyping of common and rare variation for fine mapping of trait loci in African American samples.
Keywords: African Americans; Cardiovascular Diseases; Cholesterol Ester Transfer Proteins; Cholesterol, HDL; Cholesterol, LDL; Chromosomes, Human; Cohort Studies; Gene Frequency; Genome-Wide Association Study; Genotype; Humans; Metabolic Diseases; Polymorphism, Single Nucleotide; Quantitative Trait Loci

FTO genotype is associated with phenotypic variability of body mass index. - Yang, Jian; Loos, Ruth J F; Powell, Joseph E; Medland, Sarah E; Speliotes, Elizabeth K; Chasman, Daniel I; Rose, Lynda M; Thorleifsson, Gudmar; Steinthorsdottir, Valgerdur; Mägi, Reedik; Waite, Lindsay; Smith, Albert Vernon; et al. (Nature, 2012)
There is evidence across several species for genetic control of phenotypic variation of complex traits, such that the variance among phenotypes is genotype dependent. Understanding genetic control of variability is important in evolutionary biology, agricultural selection programmes and human medicine, yet for complex traits, no individual genetic variants associated with variance, as opposed to the mean, have been identified. Here we perform a meta-analysis of genome-wide association studies of phenotypic variation using ∼170,000 samples on height and body mass index (BMI) in human populations. We report evidence that the single nucleotide polymorphism (SNP) rs7202116 at the FTO gene locus, which is known to be associated with obesity (as measured by mean BMI for each rs7202116 genotype), is also associated with phenotypic variability. We show that the results are not due to scale effects or other artefacts, and find no other experiment-wise significant evidence for effects on variability, either at loci other than FTO for BMI or at any locus for height. The difference in variance for BMI among individuals with opposite homozygous genotypes at the FTO locus is approximately 7%, corresponding to a difference of ∼0.5 kilograms in the standard deviation of weight. Our results indicate that genetic variants can be discovered that are associated with variability, and that between-person variability in obesity can partly be explained by the genotype at the FTO locus. The results are consistent with reported FTO by environment interactions for BMI, possibly mediated by DNA methylation. Our BMI results for other SNPs and our height results for all SNPs suggest that most genetic variants, including those that influence mean height or mean BMI, are not associated with phenotypic variance, or that their effects on variability are too small to detect even with samples sizes greater than 100,000.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Body Height; Body Mass Index; Co-Repressor Proteins; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteins; Repressor Proteins

Genetic determinants of the ankle-brachial index: a meta-analysis of a cardiovascular candidate gene 50K SNP panel in the candidate gene association resource (CARe) consortium. - Wassel, Christina L; Lamina, Claudia; Nambi, Vijay; Coassin, Stefan; Mukamal, Kenneth J; Ganesh, Santhi K; Jacobs, David R; Franceschini, Nora; Papanicolaou, George J; Gibson, Quince; Yanek, Lisa R; van der Harst, Pim; et al. (Atherosclerosis, 2012)
BACKGROUND: Candidate gene association studies for peripheral artery disease (PAD), including subclinical disease assessed with the ankle-brachial index (ABI), have been limited by the modest number of genes examined. We conducted a two stage meta-analysis of ∼50,000 SNPs across ∼2100 candidate genes to identify genetic variants for ABI. METHODS AND RESULTS: We studied subjects of European ancestry from 8 studies (n=21,547, 55% women, mean age 44-73 years) and African American ancestry from 5 studies (n=7267, 60% women, mean age 41-73 years) involved in the candidate gene association resource (CARe) consortium. In each ethnic group, additive genetic models were used (with each additional copy of the minor allele corresponding to the given beta) to test each SNP for association with continuous ABI (excluding ABI>1.40) and PAD (defined as ABI<0.90) using linear or logistic regression with adjustment for known PAD risk factors and population stratification. We then conducted a fixed-effects inverse-variance weighted meta-analyses considering a p<2×10(-6) to denote statistical significance. RESULTS: In the European ancestry discovery meta-analyses, rs2171209 in SYTL3 (β=-0.007, p=6.02×10(-7)) and rs290481 in TCF7L2 (β=-0.008, p=7.01×10(-7)) were significantly associated with ABI. None of the SNP associations for PAD were significant, though a SNP in CYP2B6 (p=4.99×10(-5)) was among the strongest associations. These 3 genes are linked to key PAD risk factors (lipoprotein(a), type 2 diabetes, and smoking behavior, respectively). We sought replication in 6 population-based and 3 clinical samples (n=15,440) for rs290481 and rs2171209. However, in the replication stage (rs2171209, p=0.75; rs290481, p=0.19) and in the combined discovery and replication analysis the SNP-ABI associations were no longer significant (rs2171209, p=1.14×10(-3); rs290481, p=8.88×10(-5)). In African Americans, none of the SNP associations for ABI or PAD achieved an experiment-wide level of significance. CONCLUSIONS: Genetic determinants of ABI and PAD remain elusive. Follow-up of these preliminary findings may uncover important biology given the known gene-risk factor associations. New and more powerful approaches to PAD gene discovery are warranted.
Keywords: Adult; African Americans; Aged; Ankle Brachial Index; Aryl Hydrocarbon Hydroxylases; Cytochrome P-450 CYP2B6; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Oxidoreductases, N-Demethylating; Peripheral Arterial Disease; Polymorphism, Single Nucleotide; Risk Factors; Transcription Factor 7-Like 2 Protein

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Genome-wide association study for circulating levels of PAI-1 provides novel insights into its regulation. - Huang, Jie; Sabater-Lleal, Maria; Asselbergs, Folkert W; Tregouet, David; Shin, So-Youn; Ding, Jingzhong; Baumert, Jens; Oudot-Mellakh, Tiphaine; Folkersen, Lasse; Johnson, Andrew D; Smith, Nicholas L; Williams, Scott M; et al. (Blood, 2012)
We conducted a genome-wide association study to identify novel associations between genetic variants and circulating plasminogen activator inhibitor-1 (PAI-1) concentration, and examined functional implications of variants and genes that were discovered. A discovery meta-analysis was performed in 19 599 subjects, followed by replication analysis of genome-wide significant (P < 5 × 10(-8)) single nucleotide polymorphisms (SNPs) in 10 796 independent samples. We further examined associations with type 2 diabetes and coronary artery disease, assessed the functional significance of the SNPs for gene expression in human tissues, and conducted RNA-silencing experiments for one novel association. We confirmed the association of the 4G/5G proxy SNP rs2227631 in the promoter region of SERPINE1 (7q22.1) and discovered genome-wide significant associations at 3 additional loci: chromosome 7q22.1 close to SERPINE1 (rs6976053, discovery P = 3.4 × 10(-10)); chromosome 11p15.2 within ARNTL (rs6486122, discovery P = 3.0 × 10(-8)); and chromosome 3p25.2 within PPARG (rs11128603, discovery P = 2.9 × 10(-8)). Replication was achieved for the 7q22.1 and 11p15.2 loci. There was nominal association with type 2 diabetes and coronary artery disease at ARNTL (P < .05). Functional studies identified MUC3 as a candidate gene for the second association signal on 7q22.1. In summary, SNPs in SERPINE1 and ARNTL and an SNP associated with the expression of MUC3 were robustly associated with circulating levels of PAI-1.
Keywords: Adaptor Proteins, Signal Transducing; ARNTL Transcription Factors; ATPases Associated with Diverse Cellular Activities; Cell Line; Cell Line, Tumor; Cohort Studies; Coronary Artery Disease; Diabetes Mellitus, Type 2; Gene Expression Profiling; Gene Expression Regulation; Gene Frequency; Genome-Wide Association Study; Genotype; Humans; LIM Domain Proteins; Meta-Analysis as Topic; Monocytes; Mucin-3; Plasminogen Activator Inhibitor 1; Polymorphism, Single Nucleotide; PPAR gamma; Proteasome Endopeptidase Complex; RNA Interference; Transcription Factors

Genome-wide joint meta-analysis of SNP and SNP-by-smoking interaction identifies novel loci for pulmonary function. - Hancock, Dana B; Soler Artigas, Maria; Gharib, Sina A; Henry, Amanda; Manichaikul, Ani; Ramasamy, Adaikalavan; Loth, Daan W; Imboden, Medea; Koch, Beate; McArdle, Wendy L; Smith, Albert V; Smolonska, Joanna; et al. (PLoS Genet, 2012)
Genome-wide association studies have identified numerous genetic loci for spirometic measures of pulmonary function, forced expiratory volume in one second (FEV(1)), and its ratio to forced vital capacity (FEV(1)/FVC). Given that cigarette smoking adversely affects pulmonary function, we conducted genome-wide joint meta-analyses (JMA) of single nucleotide polymorphism (SNP) and SNP-by-smoking (ever-smoking or pack-years) associations on FEV(1) and FEV(1)/FVC across 19 studies (total N = 50,047). We identified three novel loci not previously associated with pulmonary function. SNPs in or near DNER (smallest P(JMA = )5.00×10(-11)), HLA-DQB1 and HLA-DQA2 (smallest P(JMA = )4.35×10(-9)), and KCNJ2 and SOX9 (smallest P(JMA = )1.28×10(-8)) were associated with FEV(1)/FVC or FEV(1) in meta-analysis models including SNP main effects, smoking main effects, and SNP-by-smoking (ever-smoking or pack-years) interaction. The HLA region has been widely implicated for autoimmune and lung phenotypes, unlike the other novel loci, which have not been widely implicated. We evaluated DNER, KCNJ2, and SOX9 and found them to be expressed in human lung tissue. DNER and SOX9 further showed evidence of differential expression in human airway epithelium in smokers compared to non-smokers. Our findings demonstrated that joint testing of SNP and SNP-by-environment interaction identified novel loci associated with complex traits that are missed when considering only the genetic main effects.
Keywords: Forced Expiratory Volume; Gene Expression; Genome, Human; Genome-Wide Association Study; HLA-DQ Antigens; HLA-DQ beta-Chains; Humans; Lung; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Potassium Channels, Inwardly Rectifying; Pulmonary Disease, Chronic Obstructive; Receptors, Cell Surface; Smoking; SOX9 Transcription Factor; Vital Capacity

Genome-wide meta-analyses of smoking behaviors in African Americans. - David, S P; Hamidovic, A; Chen, G K; Bergen, A W; Wessel, J; Kasberger, J L; Brown, W M; Petruzella, S; Thacker, E L; Kim, Y; Nalls, M A; Tranah, G J; et al. (Transl Psychiatry, 2012)
The identification and exploration of genetic loci that influence smoking behaviors have been conducted primarily in populations of the European ancestry. Here we report results of the first genome-wide association study meta-analysis of smoking behavior in African Americans in the Study of Tobacco in Minority Populations Genetics Consortium (n = 32,389). We identified one non-coding single-nucleotide polymorphism (SNP; rs2036527[A]) on chromosome 15q25.1 associated with smoking quantity (cigarettes per day), which exceeded genome-wide significance (β = 0.040, s.e. = 0.007, P = 1.84 × 10(-8)). This variant is present in the 5'-distal enhancer region of the CHRNA5 gene and defines the primary index signal reported in studies of the European ancestry. No other SNP reached genome-wide significance for smoking initiation (SI, ever vs never smoking), age of SI, or smoking cessation (SC, former vs current smoking). Informative associations that approached genome-wide significance included three modestly correlated variants, at 15q25.1 within PSMA4, CHRNA5 and CHRNA3 for smoking quantity, which are associated with a second signal previously reported in studies in European ancestry populations, and a signal represented by three SNPs in the SPOCK2 gene on chr10q22.1. The association at 15q25.1 confirms this region as an important susceptibility locus for smoking quantity in men and women of African ancestry. Larger studies will be needed to validate the suggestive loci that did not reach genome-wide significance and further elucidate the contribution of genetic variation to disparities in cigarette consumption, SC and smoking-attributable disease between African Americans and European Americans.
Keywords: Adult; African Americans; Aged; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 15; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteoglycans; Receptors, Nicotinic; Smoking; Statistics as Topic

Genome-wide meta-analysis identifies 56 bone mineral density loci and reveals 14 loci associated with risk of fracture. - Estrada, Karol; Styrkarsdottir, Unnur; Evangelou, Evangelos; Hsu, Yi-Hsiang; Duncan, Emma L; Ntzani, Evangelia E; Oei, Ling; Albagha, Omar M E; Amin, Najaf; Kemp, John P; Koller, Daniel L; Li, Guo; et al. (Nat Genet, 2012)
Bone mineral density (BMD) is the most widely used predictor of fracture risk. We performed the largest meta-analysis to date on lumbar spine and femoral neck BMD, including 17 genome-wide association studies and 32,961 individuals of European and east Asian ancestry. We tested the top BMD-associated markers for replication in 50,933 independent subjects and for association with risk of low-trauma fracture in 31,016 individuals with a history of fracture (cases) and 102,444 controls. We identified 56 loci (32 new) associated with BMD at genome-wide significance (P < 5 × 10(-8)). Several of these factors cluster within the RANK-RANKL-OPG, mesenchymal stem cell differentiation, endochondral ossification and Wnt signaling pathways. However, we also discovered loci that were localized to genes not known to have a role in bone biology. Fourteen BMD-associated loci were also associated with fracture risk (P < 5 × 10(-4), Bonferroni corrected), of which six reached P < 5 × 10(-8), including at 18p11.21 (FAM210A), 7q21.3 (SLC25A13), 11q13.2 (LRP5), 4q22.1 (MEPE), 2p16.2 (SPTBN1) and 10q21.1 (DKK1). These findings shed light on the genetic architecture and pathophysiological mechanisms underlying BMD variation and fracture susceptibility.
Keywords: Bone Density; Computational Biology; European Continental Ancestry Group; Extracellular Matrix Proteins; Female; Femur Neck; Fractures, Bone; Gene Expression Profiling; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Glycoproteins; Humans; Intercellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-5; Lumbar Vertebrae; Male; Mitochondrial Membrane Transport Proteins; Osteoporosis; Phosphoproteins; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Spectrin

Genome-wide meta-analysis points to CTC1 and ZNF676 as genes regulating telomere homeostasis in humans. - Mangino, Massimo; Hwang, Shih-Jen; Spector, Timothy D; Hunt, Steven C; Kimura, Masayuki; Fitzpatrick, Annette L; Christiansen, Lene; Petersen, Inge; Elbers, Clara C; Harris, Tamara; Chen, Wei; Srinivasan, Sathanur R; et al. (Hum Mol Genet, 2012)
Leukocyte telomere length (LTL) is associated with a number of common age-related diseases and is a heritable trait. Previous genome-wide association studies (GWASs) identified two loci on chromosomes 3q26.2 (TERC) and 10q24.33 (OBFC1) that are associated with the inter-individual LTL variation. We performed a meta-analysis of 9190 individuals from six independent GWAS and validated our findings in 2226 individuals from four additional studies. We confirmed previously reported associations with OBFC1 (rs9419958 P = 9.1 × 10(-11)) and with the telomerase RNA component TERC (rs1317082, P = 1.1 × 10(-8)). We also identified two novel genomic regions associated with LTL variation that map near a conserved telomere maintenance complex component 1 (CTC1; rs3027234, P = 3.6 × 10(-8)) on chromosome17p13.1 and zinc finger protein 676 (ZNF676; rs412658, P = 3.3 × 10(-8)) on 19p12. The minor allele of rs3027234 was associated with both shorter LTL and lower expression of CTC1. Our findings are consistent with the recent observations that point mutations in CTC1 cause short telomeres in both Arabidopsis and humans affected by a rare Mendelian syndrome. Overall, our results provide novel insights into the genetic architecture of inter-individual LTL variation in the general population.
Keywords: Genome-Wide Association Study; Humans; Kruppel-Like Transcription Factors; Telomere; Telomere Homeostasis; Telomere-Binding Proteins

Hemodynamic fluid shear stress response genes and carotid intima-media thickness: a candidate gene association analysis in the cardiovascular health study. - Suchy-Dicey, Astrid M; Enquobahrie, Daniel A; Heckbert, Susan R; Rotter, Jerome I; Psaty, Bruce M; McKnight, Barbara (Int J Mol Epidemiol Genet, 2012)
OBJECTIVE: This study examined whether carotid artery intimal-medial thickness (cIMT) is associated with genetic variations (SNPs) in a hemodynamics-responsive gene pathway. METHODS: Subjects were Cardiovascular Health Study participants free of cardiovascular events at baseline (N=3388). Genotype was measured using Illumina 370CNV HumanHap chip. Carotid IMT was measured using ultrasound. Estimated mean differences in cIMT per additional minor allele for 366 SNPs in MAP2K5, MAPK7, MEF2A/C, and KLF2 were adjusted for sex, age, clinic, and medication use. SNP-SNP interactions were examined using logic regression for 71 tagSNPs. RESULTS: None of the associations was significant after correction for multiple comparisons; smallest P-value=0.065 for MAP2K5 and common cIMT. The best-performing logic regression tree combined two SNPs in MAP2K5-rs745212 and rs12905175- and common cIMT; this association was not significant, corrected P-value=0.062. CONCLUSION: There was not strong evidence of association between genetic variants in a hemodynamics-responsive gene pathway and atherosclerosis among older adults.

Impact of ancestry and common genetic variants on QT interval in African Americans. - Smith, J Gustav; Avery, Christy L; Evans, Daniel S; Nalls, Michael A; Meng, Yan A; Smith, Erin N; Palmer, Cameron; Tanaka, Toshiko; Mehra, Reena; Butler, Anne M; Young, Taylor; Buxbaum, Sarah G; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Ethnic differences in cardiac arrhythmia incidence have been reported, with a particularly high incidence of sudden cardiac death and low incidence of atrial fibrillation in individuals of African ancestry. We tested the hypotheses that African ancestry and common genetic variants are associated with prolonged duration of cardiac repolarization, a central pathophysiological determinant of arrhythmia, as measured by the electrocardiographic QT interval. METHODS AND RESULTS: First, individual estimates of African and European ancestry were inferred from genome-wide single-nucleotide polymorphism (SNP) data in 7 population-based cohorts of African Americans (n=12,097) and regressed on measured QT interval from ECGs. Second, imputation was performed for 2.8 million SNPs, and a genome-wide association study of QT interval was performed in 10 cohorts (n=13,105). There was no evidence of association between genetic ancestry and QT interval (P=0.94). Genome-wide significant associations (P<2.5 × 10(-8)) were identified with SNPs at 2 loci, upstream of the genes NOS1AP (rs12143842, P=2 × 10(-15)) and ATP1B1 (rs1320976, P=2 × 10(-10)). The most significant SNP in NOS1AP was the same as the strongest SNP previously associated with QT interval in individuals of European ancestry. Low probability values (P<10(-5)) were observed for SNPs at several other loci previously identified in genome-wide association studies in individuals of European ancestry, including KCNQ1, KCNH2, LITAF, and PLN. CONCLUSIONS: We observed no difference in duration of cardiac repolarization with global genetic indices of African American ancestry. In addition, our genome-wide association study extends the association of polymorphisms at several loci associated with repolarization in individuals of European ancestry to include individuals of African ancestry.
Keywords: Adult; African Americans; Aged; Electrocardiography; European Continental Ancestry Group; Female; Genealogy and Heraldry; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Large-scale association analyses identify new loci influencing glycemic traits and provide insight into the underlying biological pathways. - Scott, Robert A; Lagou, Vasiliki; Welch, Ryan P; Wheeler, Eleanor; Montasser, May E; Luan, Jian'an; Mägi, Reedik; Strawbridge, Rona J; Rehnberg, Emil; Gustafsson, Stefan; Kanoni, Stavroula; Rasmussen-Torvik, Laura J; et al. (Nat Genet, 2012)
Through genome-wide association meta-analyses of up to 133,010 individuals of European ancestry without diabetes, including individuals newly genotyped using the Metabochip, we have increased the number of confirmed loci influencing glycemic traits to 53, of which 33 also increase type 2 diabetes risk (q < 0.05). Loci influencing fasting insulin concentration showed association with lipid levels and fat distribution, suggesting impact on insulin resistance. Gene-based analyses identified further biologically plausible loci, suggesting that additional loci beyond those reaching genome-wide significance are likely to represent real associations. This conclusion is supported by an excess of directionally consistent and nominally significant signals between discovery and follow-up studies. Functional analysis of these newly discovered loci will further improve our understanding of glycemic control.
Keywords: Adult; Animals; Blood Glucose; Fasting; Female; Gene Frequency; Genome-Wide Association Study; Humans; Insulin; Male; Metabolic Networks and Pathways; Mice; Osmolar Concentration; Quantitative Trait Loci

Large-scale international validation of the ADO index in subjects with COPD: an individual subject data analysis of 10 cohorts. - Puhan, Milo A; Hansel, Nadia N; Sobradillo, Patricia; Enright, Paul; Lange, Peter; Hickson, Demarc; Menezes, Ana M; ter Riet, Gerben; Held, Ulrike; Domingo-Salvany, Antonia; Mosenifar, Zab; Antó, Josep M; et al. (BMJ Open, 2012)
BACKGROUND: Little evidence on the validity of simple and widely applicable tools to predict mortality in patients with chronic obstructive pulmonary disease (COPD) exists. OBJECTIVE: To conduct a large international study to validate the ADO index that uses age, dyspnoea and FEV(1) to predict 3-year mortality and to update it in order to make prediction of mortality in COPD patients as generalisable as possible. DESIGN: Individual subject data analysis of 10 European and American cohorts (n=13 914). SETTING: Population-based, primary, secondary and tertiary care. PATIENTS: COPD GOLD stages I-IV. MEASUREMENTS: We validated the original ADO index. We then obtained an updated ADO index in half of our cohorts to improve its predictive accuracy, which in turn was validated comprehensively in the remaining cohorts using discrimination, calibration and decision curve analysis and a number of sensitivity analyses. RESULTS: 1350 (9.7%) of all subjects with COPD (60% male, mean age 61 years, mean FEV(1) 66% predicted) had died at 3 years. The original ADO index showed high discrimination but poor calibration (p<0.001 for difference between predicted and observed risk). The updated ADO index (scores from 0 to 14) preserved excellent discrimination (area under curve 0.81, 95% CI 0.80 to 0.82) but showed much improved calibration with predicted 3-year risks from 0.7% (95% CI 0.6% to 0.9%, score of 0) to 64.5% (61.2% to 67.7%, score of 14). The ADO index showed higher net benefit in subjects at low-to-moderate risk of 3-year mortality than FEV(1) alone. INTERPRETATION: The updated 15-point ADO index accurately predicts 3-year mortality across the COPD severity spectrum and can be used to inform patients about their prognosis, clinical trial study design or benefit harm assessment of medical interventions.

Lipid-related markers and cardiovascular disease prediction. - Di Angelantonio, Emanuele; Gao, Pei; Pennells, Lisa; Kaptoge, Stephen; Caslake, Muriel; Thompson, Alexander; Butterworth, Adam S; Sarwar, Nadeem; Wormser, David; Saleheen, Danish; Ballantyne, Christie M; Psaty, Bruce M; et al. (JAMA, 2012)
CONTEXT: The value of assessing various emerging lipid-related markers for prediction of first cardiovascular events is debated. OBJECTIVE: To determine whether adding information on apolipoprotein B and apolipoprotein A-I, lipoprotein(a), or lipoprotein-associated phospholipase A2 to total cholesterol and high-density lipoprotein cholesterol (HDL-C) improves cardiovascular disease (CVD) risk prediction. DESIGN, SETTING, AND PARTICIPANTS: Individual records were available for 165,544 participants without baseline CVD in 37 prospective cohorts (calendar years of recruitment: 1968-2007) with up to 15,126 incident fatal or nonfatal CVD outcomes (10,132 CHD and 4994 stroke outcomes) during a median follow-up of 10.4 years (interquartile range, 7.6-14 years). MAIN OUTCOME MEASURES: Discrimination of CVD outcomes and reclassification of participants across predicted 10-year risk categories of low (<10%), intermediate (10%-<20%), and high (≥20%) risk. RESULTS: The addition of information on various lipid-related markers to total cholesterol, HDL-C, and other conventional risk factors yielded improvement in the model's discrimination: C-index change, 0.0006 (95% CI, 0.0002-0.0009) for the combination of apolipoprotein B and A-I; 0.0016 (95% CI, 0.0009-0.0023) for lipoprotein(a); and 0.0018 (95% CI, 0.0010-0.0026) for lipoprotein-associated phospholipase A2 mass. Net reclassification improvements were less than 1% with the addition of each of these markers to risk scores containing conventional risk factors. We estimated that for 100,000 adults aged 40 years or older, 15,436 would be initially classified at intermediate risk using conventional risk factors alone. Additional testing with a combination of apolipoprotein B and A-I would reclassify 1.1%; lipoprotein(a), 4.1%; and lipoprotein-associated phospholipase A2 mass, 2.7% of people to a 20% or higher predicted CVD risk category and, therefore, in need of statin treatment under Adult Treatment Panel III guidelines. CONCLUSION: In a study of individuals without known CVD, the addition of information on the combination of apolipoprotein B and A-I, lipoprotein(a), or lipoprotein-associated phospholipase A2 mass to risk scores containing total cholesterol and HDL-C led to slight improvement in CVD prediction.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Cholesterol, HDL; Cohort Studies; Female; Humans; Lipoproteins; Male; Middle Aged; Risk Assessment

Markers of cholesterol metabolism in the brain show stronger associations with cerebrovascular disease than Alzheimer's disease. - Hughes, Timothy M; Kuller, Lewis H; Lopez, Oscar L; Becker, James T; Evans, Rhobert W; Sutton-Tyrrell, Kim; Rosano, Caterina (J Alzheimers Dis, 2012)
Cholesterol metabolism is believed to play a role in the development of Alzheimer's disease (AD). Oxysterol metabolites of cholesterol, 24S-hydroxycholesterol (24-OHC, a brain-derived oxysterol) and 27-hydroxycholesterol (27-OHC, a peripherally derived oxysterol) cross the blood brain barrier and have been associated with AD. We investigated whether oxysterols were associated with markers of cerebrovascular disease prior to the onset of cognitive impairment. Oxysterols were quantified in 105 participants (average age: 80 ± 4 years) from the Pittsburgh Cardiovascular Health Study Cognition Study who remained cognitively normal at blood draw in 2002, had MRI in 1992 and 1998, and annual cognitive assessment for incident AD and mild cognitive impairment made by consensus conference between 1998 and 2010. Higher plasma levels of 24-OHC were associated with age, gender, the presence of high grade white matter hyperintensities, and brain infarcts on prior MRI. Participants with higher plasma 24-OHC and a greater ratio of 24-OHC/27-OHC were also more likely to develop incident cognitive impairment over 8 years of follow-up. Higher levels of 24-OHC suggest increased cholesterol metabolism occurring in the brains of participants with cerebrovascular disease prior to the onset of cognitive impairment. Measurement of oxysterols may provide information about cholesterol metabolism and brain disease over the cognitive impairment process.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Brain; Cerebrovascular Disorders; Cognition Disorders; Cohort Studies; Female; Humans; Hydroxycholesterols; Magnetic Resonance Imaging; Male; Retrospective Studies

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Polymerase gamma; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Meta-analysis identifies six new susceptibility loci for atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Albert, Christine M; Glazer, Nicole L; Ritchie, Marylyn D; Smith, Albert V; Arking, Dan E; Müller-Nurasyid, Martina; Krijthe, Bouwe P; Lubitz, Steven A; Bis, Joshua C; Chung, Mina K; et al. (Nat Genet, 2012)
Atrial fibrillation is a highly prevalent arrhythmia and a major risk factor for stroke, heart failure and death. We conducted a genome-wide association study (GWAS) in individuals of European ancestry, including 6,707 with and 52,426 without atrial fibrillation. Six new atrial fibrillation susceptibility loci were identified and replicated in an additional sample of individuals of European ancestry, including 5,381 subjects with and 10,030 subjects without atrial fibrillation (P < 5 × 10(-8)). Four of the loci identified in Europeans were further replicated in silico in a GWAS of Japanese individuals, including 843 individuals with and 3,350 individuals without atrial fibrillation. The identified loci implicate candidate genes that encode transcription factors related to cardiopulmonary development, cardiac-expressed ion channels and cell signaling molecules.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Atrial Fibrillation; Child; Child, Preschool; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Infant; Infant, Newborn; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

Modification of the association between ambient air pollution and lung function by frailty status among older adults in the Cardiovascular Health Study. - Eckel, Sandrah P; Louis, Thomas A; Chaves, Paulo H M; Fried, Linda P; Margolis, And Helene G (Am J Epidemiol, 2012)
The susceptibility of older adults to the health effects of air pollution is well-recognized. Advanced age may act as a partial surrogate for conditions associated with aging. The authors investigated whether gerontologic frailty (a clinical health status metric) modified the association between ambient level of ozone or particulate matter with an aerodynamic diameter less than 10 µm and lung function in 3,382 older adults using 7 years of follow-up data (1990-1997) from the Cardiovascular Health Study and its Environmental Factors Ancillary Study. Monthly average pollution and annual frailty assessments were related to up to 3 repeated measurements of lung function using cumulative summaries of pollution and frailty histories that accounted for duration as well as concentration. Frailty history was found to modify long-term associations of pollutants with forced vital capacity. For example, the decrease in forced vital capacity associated with a 70-ppb/month greater cumulative sum of monthly average ozone exposure was 12.3 mL (95% confidence interval: 10.4, 14.2) for a woman who had spent the prior 7 years prefrail or frail as compared with 4.7 mL (95% confidence interval: 3.8, 5.6) for a similar woman who was robust during all 7 years (interaction P < 0.001).
Keywords: Aged; Air Pollution; Cardiovascular Diseases; Female; Forced Expiratory Volume; Frail Elderly; Geriatric Assessment; Humans; Male; Prospective Studies; Respiratory Function Tests; Sex Factors; Smoking; Time Factors; United States; Vital Capacity

Novel loci associated with PR interval in a genome-wide association study of 10 African American cohorts. - Butler, Anne M; Yin, Xiaoyan; Evans, Daniel S; Nalls, Michael A; Smith, Erin N; Tanaka, Toshiko; Li, Guo; Buxbaum, Sarah G; Whitsel, Eric A; Alonso, Alvaro; Arking, Dan E; Benjamin, Emelia J; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: The PR interval, as measured by the resting, standard 12-lead ECG, reflects the duration of atrial/atrioventricular nodal depolarization. Substantial evidence exists for a genetic contribution to PR, including genome-wide association studies that have identified common genetic variants at 9 loci influencing PR in populations of European and Asian descent. However, few studies have examined loci associated with PR in African Americans. METHODS AND RESULTS: We present results from the largest genome-wide association study to date of PR in 13 415 adults of African descent from 10 cohorts. We tested for association between PR (ms) and ≈2.8 million genotyped and imputed single-nucleotide polymorphisms. Imputation was performed using HapMap 2 YRI and CEU panels. Study-specific results, adjusted for global ancestry and clinical correlates of PR, were meta-analyzed using the inverse variance method. Variation in genome-wide test statistic distributions was noted within studies (λ range: 0.9-1.1), although not after genomic control correction was applied to the overall meta-analysis (λ: 1.008). In addition to generalizing previously reported associations with MEIS1, SCN5A, ARHGAP24, CAV1, and TBX5 to African American populations at the genome-wide significance level (P<5.0 × 10(-8)), we also identified a novel locus: ITGA9, located in a region previously implicated in SCN5A expression. The 3p21 region harboring SCN5A also contained 2 additional independent secondary signals influencing PR (P<5.0 × 10(-8)). CONCLUSIONS: This study demonstrates the ability to map novel loci in African Americans as well as the generalizability of loci associated with PR across populations of African, European, and Asian descent.
Keywords: Adult; African Americans; Cohort Studies; Electrocardiography; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide

Novel loci for adiponectin levels and their influence on type 2 diabetes and metabolic traits: a multi-ethnic meta-analysis of 45,891 individuals. - Dastani, Zari; Hivert, Marie-France; Timpson, Nicholas; Perry, John R B; Yuan, Xin; Scott, Robert A; Henneman, Peter; Heid, Iris M; Kizer, Jorge R; Lyytikäinen, Leo-Pekka; Fuchsberger, Christian; Tanaka, Toshiko; et al. (PLoS Genet, 2012)
Circulating levels of adiponectin, a hormone produced predominantly by adipocytes, are highly heritable and are inversely associated with type 2 diabetes mellitus (T2D) and other metabolic traits. We conducted a meta-analysis of genome-wide association studies in 39,883 individuals of European ancestry to identify genes associated with metabolic disease. We identified 8 novel loci associated with adiponectin levels and confirmed 2 previously reported loci (P = 4.5×10(-8)-1.2×10(-43)). Using a novel method to combine data across ethnicities (N = 4,232 African Americans, N = 1,776 Asians, and N = 29,347 Europeans), we identified two additional novel loci. Expression analyses of 436 human adipocyte samples revealed that mRNA levels of 18 genes at candidate regions were associated with adiponectin concentrations after accounting for multiple testing (p<3×10(-4)). We next developed a multi-SNP genotypic risk score to test the association of adiponectin decreasing risk alleles on metabolic traits and diseases using consortia-level meta-analytic data. This risk score was associated with increased risk of T2D (p = 4.3×10(-3), n = 22,044), increased triglycerides (p = 2.6×10(-14), n = 93,440), increased waist-to-hip ratio (p = 1.8×10(-5), n = 77,167), increased glucose two hours post oral glucose tolerance testing (p = 4.4×10(-3), n = 15,234), increased fasting insulin (p = 0.015, n = 48,238), but with lower in HDL-cholesterol concentrations (p = 4.5×10(-13), n = 96,748) and decreased BMI (p = 1.4×10(-4), n = 121,335). These findings identify novel genetic determinants of adiponectin levels, which, taken together, influence risk of T2D and markers of insulin resistance.
Keywords: Adiponectin; African Americans; Asian Continental Ancestry Group; Cholesterol, HDL; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Tolerance Test; Humans; Insulin Resistance; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Waist-Hip Ratio

Probabilistic sleep architecture models in patients with and without sleep apnea. - Bianchi, Matt T; Eiseman, Nathaniel A; Cash, Sydney S; Mietus, Joseph; Peng, Chung-Kang; Thomas, Robert J (J Sleep Res, 2012)
Sleep fragmentation of any cause is disruptive to the rejuvenating value of sleep. However, methods to quantify sleep architecture remain limited. We have previously shown that human sleep-wake stage distributions exhibit multi-exponential dynamics, which are fragmented by obstructive sleep apnea (OSA), suggesting that Markov models may be a useful method to quantify architecture in health and disease. Sleep stage data were obtained from two subsets of the Sleep Heart Health Study database: control subjects with no medications, no OSA, no medical co-morbidities and no sleepiness (n = 374); and subjects with severe OSA (n = 338). Sleep architecture was simplified into three stages: wake after sleep onset (WASO); non-rapid eye movement (NREM) sleep; and rapid eye movement (REM) sleep. The connectivity and transition rates among eight 'generator' states of a first-order continuous-time Markov model were inferred from the observed ('phenotypic') distributions: three exponentials each of NREM sleep and WASO; and two exponentials of REM sleep. Ultradian REM cycling was accomplished by imposing time-variation to REM state entry rates. Fragmentation in subjects with severe OSA involved faster transition probabilities as well as additional state transition paths within the model. The Markov models exhibit two important features of human sleep architecture: multi-exponential stage dynamics (accounting for observed bout distributions); and probabilistic transitions (an inherent source of variability). In addition, the model quantifies the fragmentation associated with severe OSA. Markov sleep models may prove important for quantifying sleep disruption to provide objective metrics to correlate with endpoints ranging from sleepiness to cardiovascular morbidity.
Keywords: Cohort Studies; Computer Simulation; Humans; Models, Theoretical; Polysomnography; Probability; Sleep Apnea Syndromes; Sleep Stages; Sleep, REM; Time Factors

Subclinical hyperthyroidism and the risk of coronary heart disease and mortality. - Collet, Tinh-Hai; Gussekloo, Jacobijn; Bauer, Douglas C; den Elzen, Wendy P J; Cappola, Anne R; Balmer, Philippe; Iervasi, Giorgio; Asvold, Bjørn O; Sgarbi, José A; Völzke, Henry; Gencer, Bariş; Maciel, Rui M B; et al. (Arch Intern Med, 2012)
BACKGROUND: Data from prospective cohort studies regarding the association between subclinical hyperthyroidism and cardiovascular outcomes are conflicting.We aimed to assess the risks of total and coronary heart disease (CHD) mortality, CHD events, and atrial fibrillation (AF) associated with endogenous subclinical hyperthyroidism among all available large prospective cohorts. METHODS: Individual data on 52 674 participants were pooled from 10 cohorts. Coronary heart disease events were analyzed in 22 437 participants from 6 cohorts with available data, and incident AF was analyzed in 8711 participants from 5 cohorts. Euthyroidism was defined as thyrotropin level between 0.45 and 4.49 mIU/L and endogenous subclinical hyperthyroidism as thyrotropin level lower than 0.45 mIU/L with normal free thyroxine levels, after excluding those receiving thyroid-altering medications. RESULTS: Of 52 674 participants, 2188 (4.2%) had subclinical hyperthyroidism. During follow-up, 8527 participants died (including 1896 from CHD), 3653 of 22 437 had CHD events, and 785 of 8711 developed AF. In age- and sex-adjusted analyses, subclinical hyperthyroidism was associated with increased total mortality (hazard ratio[HR], 1.24, 95% CI, 1.06-1.46), CHD mortality (HR,1.29; 95% CI, 1.02-1.62), CHD events (HR, 1.21; 95%CI, 0.99-1.46), and AF (HR, 1.68; 95% CI, 1.16-2.43).Risks did not differ significantly by age, sex, or preexisting cardiovascular disease and were similar after further adjustment for cardiovascular risk factors, with attributable risk of 14.5% for total mortality to 41.5% forAF in those with subclinical hyperthyroidism. Risks for CHD mortality and AF (but not other outcomes) were higher for thyrotropin level lower than 0.10 mIU/L compared with thyrotropin level between 0.10 and 0.44 mIU/L(for both, P value for trend, .03). CONCLUSION: Endogenous subclinical hyperthyroidism is associated with increased risks of total, CHD mortality, and incident AF, with highest risks of CHD mortality and AF when thyrotropin level is lower than 0.10 mIU/L.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Atrial Fibrillation; Cause of Death; Cohort Studies; Coronary Artery Disease; Female; Humans; Hyperthyroidism; Male; Middle Aged; Prognosis; Prospective Studies; Risk Assessment; Severity of Illness Index; Sex Distribution; Survival Analysis; Switzerland; Thyroid Function Tests; Thyrotropin; Young Adult

Subclinical thyroid dysfunction and the risk of heart failure events: an individual participant data analysis from 6 prospective cohorts. - Gencer, Bariş; Collet, Tinh-Hai; Virgini, Vanessa; Bauer, Douglas C; Gussekloo, Jacobijn; Cappola, Anne R; Nanchen, David; den Elzen, Wendy P J; Balmer, Philippe; Luben, Robert N; Iacoviello, Massimo; Triggiani, Vincenzo; et al. (Circulation, 2012)
BACKGROUND: American College of Cardiology/American Heart Association guidelines for the diagnosis and management of heart failure recommend investigating exacerbating conditions such as thyroid dysfunction, but without specifying the impact of different thyroid-stimulation hormone (TSH) levels. Limited prospective data exist on the association between subclinical thyroid dysfunction and heart failure events. METHODS AND RESULTS: We performed a pooled analysis of individual participant data using all available prospective cohorts with thyroid function tests and subsequent follow-up of heart failure events. Individual data on 25 390 participants with 216 248 person-years of follow-up were supplied from 6 prospective cohorts in the United States and Europe. Euthyroidism was defined as TSH of 0.45 to 4.49 mIU/L, subclinical hypothyroidism as TSH of 4.5 to 19.9 mIU/L, and subclinical hyperthyroidism as TSH <0.45 mIU/L, the last two with normal free thyroxine levels. Among 25 390 participants, 2068 (8.1%) had subclinical hypothyroidism and 648 (2.6%) had subclinical hyperthyroidism. In age- and sex-adjusted analyses, risks of heart failure events were increased with both higher and lower TSH levels (P for quadratic pattern <0.01); the hazard ratio was 1.01 (95% confidence interval, 0.81-1.26) for TSH of 4.5 to 6.9 mIU/L, 1.65 (95% confidence interval, 0.84-3.23) for TSH of 7.0 to 9.9 mIU/L, 1.86 (95% confidence interval, 1.27-2.72) for TSH of 10.0 to 19.9 mIU/L (P for trend <0.01) and 1.31 (95% confidence interval, 0.88-1.95) for TSH of 0.10 to 0.44 mIU/L and 1.94 (95% confidence interval, 1.01-3.72) for TSH <0.10 mIU/L (P for trend=0.047). Risks remained similar after adjustment for cardiovascular risk factors. CONCLUSION: Risks of heart failure events were increased with both higher and lower TSH levels, particularly for TSH ≥10 and <0.10 mIU/L.
Keywords: Adult; Aged; Aged, 80 and over; Comorbidity; Female; Follow-Up Studies; Heart Failure; Humans; Hypothyroidism; Male; Middle Aged; Prospective Studies; Risk; Risk Factors; Sensitivity and Specificity; Thyrotropin; Thyroxine

Variation in the lysyl oxidase (LOX) gene is associated with keratoconus in family-based and case-control studies. - Bykhovskaya, Yelena; Li, Xiaohui; Epifantseva, Irina; Haritunians, Talin; Siscovick, David; Aldave, Anthony; Szczotka-Flynn, Loretta; Iyengar, Sudha K; Taylor, Kent D; Rotter, Jerome I; Rabinowitz, Yaron S (Invest Ophthalmol Vis Sci, 2012)
PURPOSE: Keratoconus is a bilateral noninflammatory progressive corneal disorder with complex genetic inheritance and a common cause for cornea transplantation in young adults. A genomewide linkage scan in keratoconus families identified a locus at 5q23.2, overlapping the gene coding for the lysyl oxidase (LOX). LOX encodes an enzyme responsible for collagen cross-linking in a variety of tissues including the cornea. Corneal collagen cross-linking with long-wave ultraviolet light and riboflavin is a promising new treatment for keratoconus. To determine whether LOX is a genetic determinant of the pathogenesis of keratoconus, we analyzed association results of LOX polymorphisms in two independent case-control samples and in keratoconus families. METHODS: Association results were analyzed of single-nucleotide polymorphisms (SNPs) in the LOX gene from a Genome-Wide Association Study (GWAS) investigation in two independent panels of patients with keratoconus and controls and in keratoconus families. RESULTS: Evidence of association was found at SNPs rs10519694 and rs2956540 located in intron 4 of LOX in the GWAS discovery case-control panel with P values of 2.3×10(-3) and 7×10(-3), respectively. The same two SNPs were found to be associated with keratoconus by family-based association testing with P values of 2.7×10(-3) and 7.7×10(-4), respectively. Meta P values of 4.0×10(-5) and 4.0×10(-7) were calculated for SNPs rs10519694 and rs2956540 by analyzing case-control and family samples simultaneously. Sequencing of LOX exons in a subset of keratoconus patients identified two polymorphisms, rs1800449 and rs2288393, located in LOX transcripts I and II, associated with keratoconus in case-control and family samples with a meta P value of 0.02. CONCLUSIONS: Results provided strong genetic evidence that LOX variants lead to increased susceptibility to developing of keratoconus.
Keywords: Case-Control Studies; Cornea; Corneal Topography; DNA; Family; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Keratoconus; Polymorphism, Genetic; Protein-Lysine 6-Oxidase

Common carotid intima-media thickness does not add to Framingham risk score in individuals with diabetes mellitus: the USE-IMT initiative. - den Ruijter, H M; Peters, S A E; Groenewegen, K A; Anderson, T J; Britton, A R; Dekker, J M; Engstrom, G; Eijkemans, M J; Evans, G W; de Graaf, J; Grobbee, D E; Hedblad, B; et al. (Diabetologia, 2013)
AIMS/HYPOTHESIS: The aim of this work was to investigate whether measurement of the mean common carotid intima-media thickness (CIMT) improves cardiovascular risk prediction in individuals with diabetes. METHODS: We performed a subanalysis among 4,220 individuals with diabetes in a large ongoing individual participant data meta-analysis involving 56,194 subjects from 17 population-based cohorts worldwide. We first refitted the risk factors of the Framingham heart risk score on the individuals without previous cardiovascular disease (baseline model) and then expanded this model with the mean common CIMT (CIMT model). The absolute 10 year risk for developing a myocardial infarction or stroke was estimated from both models. In individuals with diabetes we compared discrimination and calibration of the two models. Reclassification of individuals with diabetes was based on allocation to another cardiovascular risk category when mean common CIMT was added. RESULTS: During a median follow-up of 8.7 years, 684 first-time cardiovascular events occurred among the population with diabetes. The C statistic was 0.67 for the Framingham model and 0.68 for the CIMT model. The absolute 10 year risk for developing a myocardial infarction or stroke was 16% in both models. There was no net reclassification improvement with the addition of mean common CIMT (1.7%; 95% CI -1.8, 3.8). There were no differences in the results between men and women. CONCLUSIONS/INTERPRETATION: There is no improvement in risk prediction in individuals with diabetes when measurement of the mean common CIMT is added to the Framingham risk score. Therefore, this measurement is not recommended for improving individual cardiovascular risk stratification in individuals with diabetes.
Keywords: Cardiovascular Diseases; Carotid Intima-Media Thickness; Diabetes Mellitus; Humans; Myocardial Infarction; Risk Factors; Stroke

Common genetic loci influencing plasma homocysteine concentrations and their effect on risk of coronary artery disease. - van Meurs, Joyce B J; Paré, Guillaume; Schwartz, Stephen M; Hazra, Aditi; Tanaka, Toshiko; Vermeulen, Sita H; Cotlarciuc, Ioana; Yuan, Xin; Mälarstig, Anders; Bandinelli, Stefania; Bis, Joshua C; Blom, Henk; et al. (Am J Clin Nutr, 2013)
BACKGROUND: The strong observational association between total homocysteine (tHcy) concentrations and risk of coronary artery disease (CAD) and the null associations in the homocysteine-lowering trials have prompted the need to identify genetic variants associated with homocysteine concentrations and risk of CAD. OBJECTIVE: We tested whether common genetic polymorphisms associated with variation in tHcy are also associated with CAD. DESIGN: We conducted a meta-analysis of genome-wide association studies (GWAS) on tHcy concentrations in 44,147 individuals of European descent. Polymorphisms associated with tHcy (P < 10(⁻⁸) were tested for association with CAD in 31,400 cases and 92,927 controls. RESULTS: Common variants at 13 loci, explaining 5.9% of the variation in tHcy, were associated with tHcy concentrations, including 6 novel loci in or near MMACHC (2.1 × 10⁻⁹), SLC17A3 (1.0 × 10⁻⁸), GTPB10 (1.7 × 10⁻⁸), CUBN (7.5 × 10⁻¹⁰), HNF1A (1.2 × 10⁻¹²)), and FUT2 (6.6 × 10⁻⁹), and variants previously reported at or near the MTHFR, MTR, CPS1, MUT, NOX4, DPEP1, and CBS genes. Individuals within the highest 10% of the genotype risk score (GRS) had 3-μmol/L higher mean tHcy concentrations than did those within the lowest 10% of the GRS (P = 1 × 10⁻³⁶). The GRS was not associated with risk of CAD (OR: 1.01; 95% CI: 0.98, 1.04; P = 0.49). CONCLUSIONS: We identified several novel loci that influence plasma tHcy concentrations. Overall, common genetic variants that influence plasma tHcy concentrations are not associated with risk of CAD in white populations, which further refutes the causal relevance of moderately elevated tHcy concentrations and tHcy-related pathways for CAD.
Keywords: Coronary Artery Disease; Genes; Genetic Loci; Genetic Predisposition to Disease; Genotype; Homocysteine; Humans; Polymorphism, Genetic; Risk Factors

Common genetic variation near the connexin-43 gene is associated with resting heart rate in African Americans: a genome-wide association study of 13,372 participants. - Deo, R; Nalls, M A; Avery, C L; Smith, J G; Evans, D S; Keller, M F; Butler, A M; Buxbaum, S G; Li, G; Miguel Quibrera, P; Smith, E N; Tanaka, T; et al. (Heart Rhythm, 2013)
BACKGROUND: Genome-wide association studies have identified several genetic loci associated with variation in resting heart rate in European and Asian populations. No study has evaluated genetic variants associated with heart rate in African Americans. OBJECTIVE: To identify novel genetic variants associated with resting heart rate in African Americans. METHODS: Ten cohort studies participating in the Candidate-gene Association Resource and Continental Origins and Genetic Epidemiology Network consortia performed genome-wide genotyping of single nucleotide polymorphisms (SNPs) and imputed 2,954,965 SNPs using HapMap YRI and CEU panels in 13,372 participants of African ancestry. Each study measured the RR interval (ms) from 10-second resting 12-lead electrocardiograms and estimated RR-SNP associations using covariate-adjusted linear regression. Random-effects meta-analysis was used to combine cohort-specific measures of association and identify genome-wide significant loci (P≤2.5×10(-8)). RESULTS: Fourteen SNPs on chromosome 6q22 exceeded the genome-wide significance threshold. The most significant association was for rs9320841 (+13 ms per minor allele; P = 4.98×10(-15)). This SNP was approximately 350 kb downstream of GJA1, a locus previously identified as harboring SNPs associated with heart rate in Europeans. Adjustment for rs9320841 also attenuated the association between the remaining 13 SNPs in this region and heart rate. In addition, SNPs in MYH6, which have been identified in European genome-wide association study, were associated with similar changes in the resting heart rate as this population of African Americans. CONCLUSIONS: An intergenic region downstream of GJA1 (the gene encoding connexin 43, the major protein of the human myocardial gap junction) and an intragenic region within MYH6 are associated with variation in resting heart rate in African Americans as well as in populations of European and Asian origin.
Keywords: Adult; African Americans; Aged; Arrhythmias, Cardiac; Connexin 43; Electrocardiography; Female; Genetic Variation; Genome-Wide Association Study; Genotype; Heart Rate; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Rest; United States

Common variants associated with plasma triglycerides and risk for coronary artery disease. - Do, Ron; Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Gao, Chi; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; et al. (Nat Genet, 2013)
Triglycerides are transported in plasma by specific triglyceride-rich lipoproteins; in epidemiological studies, increased triglyceride levels correlate with higher risk for coronary artery disease (CAD). However, it is unclear whether this association reflects causal processes. We used 185 common variants recently mapped for plasma lipids (P < 5 × 10(-8) for each) to examine the role of triglycerides in risk for CAD. First, we highlight loci associated with both low-density lipoprotein cholesterol (LDL-C) and triglyceride levels, and we show that the direction and magnitude of the associations with both traits are factors in determining CAD risk. Second, we consider loci with only a strong association with triglycerides and show that these loci are also associated with CAD. Finally, in a model accounting for effects on LDL-C and/or high-density lipoprotein cholesterol (HDL-C) levels, the strength of a polymorphism's effect on triglyceride levels is correlated with the magnitude of its effect on CAD risk. These results suggest that triglyceride-rich lipoproteins causally influence risk for CAD.
Keywords: Biological Transport; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Humans; Polymorphism, Single Nucleotide; Risk Factors; Triglycerides

Common variants in Mendelian kidney disease genes and their association with renal function. - Parsa, Afshin; Fuchsberger, Christian; Köttgen, Anna; O'Seaghdha, Conall M; Pattaro, Cristian; de Andrade, Mariza; Chasman, Daniel I; Teumer, Alexander; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; et al. (J Am Soc Nephrol, 2013)
Many common genetic variants identified by genome-wide association studies for complex traits map to genes previously linked to rare inherited Mendelian disorders. A systematic analysis of common single-nucleotide polymorphisms (SNPs) in genes responsible for Mendelian diseases with kidney phenotypes has not been performed. We thus developed a comprehensive database of genes for Mendelian kidney conditions and evaluated the association between common genetic variants within these genes and kidney function in the general population. Using the Online Mendelian Inheritance in Man database, we identified 731 unique disease entries related to specific renal search terms and confirmed a kidney phenotype in 218 of these entries, corresponding to mutations in 258 genes. We interrogated common SNPs (minor allele frequency >5%) within these genes for association with the estimated GFR in 74,354 European-ancestry participants from the CKDGen Consortium. However, the top four candidate SNPs (rs6433115 at LRP2, rs1050700 at TSC1, rs249942 at PALB2, and rs9827843 at ROBO2) did not achieve significance in a stage 2 meta-analysis performed in 56,246 additional independent individuals, indicating that these common SNPs are not associated with estimated GFR. The effect of less common or rare variants in these genes on kidney function in the general population and disease-specific cohorts requires further research.
Keywords: Databases, Genetic; European Continental Ancestry Group; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Kidney; Mendelian Randomization Analysis; Phenotype; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic

Discovery and refinement of loci associated with lipid levels. - Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; Beckmann, Jacques S; Bragg-Gresham, Jennifer L; et al. (Nat Genet, 2013)
Levels of low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides and total cholesterol are heritable, modifiable risk factors for coronary artery disease. To identify new loci and refine known loci influencing these lipids, we examined 188,577 individuals using genome-wide and custom genotyping arrays. We identify and annotate 157 loci associated with lipid levels at P < 5 × 10(-8), including 62 loci not previously associated with lipid levels in humans. Using dense genotyping in individuals of European, East Asian, South Asian and African ancestry, we narrow association signals in 12 loci. We find that loci associated with blood lipid levels are often associated with cardiovascular and metabolic traits, including coronary artery disease, type 2 diabetes, blood pressure, waist-hip ratio and body mass index. Our results demonstrate the value of using genetic data from individuals of diverse ancestry and provide insights into the biological mechanisms regulating blood lipids to guide future genetic, biological and therapeutic research.
Keywords: African Continental Ancestry Group; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Lipids; Triglycerides

Effects of respiratory and non-respiratory factors on disability among older adults with airway obstruction: the Cardiovascular Health Study. - Locke, Emily; Thielke, Stephen; Diehr, Paula; Wilsdon, Anthony G; Barr, R Graham; Hansel, Nadia; Kapur, Vishesh K; Krishnan, Jerry; Enright, Paul; Heckbert, Susan R; Kronmal, Richard A; Fan, Vincent S (COPD, 2013)
BACKGROUND: High rates of disability associated with chronic airway obstruction may be caused by impaired pulmonary function, pulmonary symptoms, other chronic diseases, or systemic inflammation. METHODS: We analyzed data from the Cardiovascular Health Study, a longitudinal cohort of 5888 older adults. Categories of lung function (normal; restricted; borderline, mild-moderate, and severe obstruction) were delineated by baseline spirometry (without bronchodilator). Disability-free years were calculated as total years alive and without self-report of difficulty performing &γτ;1 Instrumental Activities of Daily Living over 6 years of follow-up. Using linear regression, we compared disability-free years by lung disease category, adjusting for demographic factors, body mass index, smoking, cognition, and other chronic co-morbidities. Among participants with airflow obstruction, we examined the association of respiratory factors (FEV1 and dyspnea) and non-respiratory factors (ischemic heart disease, congestive heart failure, diabetes, muscle weakness, osteoporosis, depression and cognitive impairment) on disability-free years. RESULTS: The average disability free years were 4.0 out of a possible 6 years. Severe obstruction was associated with 1 fewer disability-free year compared to normal spirometry in the adjusted model. For the 1,048 participants with airway obstruction, both respiratory factors (FEV1 and dyspnea) and non-respiratory factors (heart disease, coronary artery disease, diabetes, depression, osteoporosis, cognitive function, and weakness) were associated with decreased disability-free years. CONCLUSIONS: Severe obstruction is associated with greater disability compared to patients with normal spirometery. Both respiratory and non-respiratory factors contribute to disability in older adults with abnormal spirometry.
Keywords: Activities of Daily Living; Aged; Cognition Disorders; Cohort Studies; Comorbidity; Depression; Diabetes Mellitus; Disease Progression; Dyspnea; Female; Heart Failure; Humans; Linear Models; Longitudinal Studies; Male; Muscle Weakness; Myocardial Ischemia; Osteoporosis; Pulmonary Disease, Chronic Obstructive; Severity of Illness Index; Spirometry

Exploring psychosocial pathways between neighbourhood characteristics and stroke in older adults: the cardiovascular health study. - Yan, Tingjian; Escarce, José J; Liang, Li-Jung; Longstreth, W T; Merkin, Sharon Stein; Ovbiagele, Bruce; Vassar, Stefanie D; Seeman, Teresa; Sarkisian, Catherine; Brown, Arleen F (Age Ageing, 2013)
OBJECTIVES: to investigate whether psychosocial pathways mediate the association between neighbourhood socioeconomic disadvantage and stroke. METHODS: prospective cohort study with a follow-up of 11.5 years. SETTING: the Cardiovascular Health Study, a longitudinal population-based cohort study of older adults ≥65 years. MEASUREMENTS: the primary outcome was adjudicated incident ischaemic stroke. Neighbourhood socioeconomic status (NSES) was measured using a composite of six census-tract variables. Psychosocial factors were assessed with standard measures for depression, social support and social networks. RESULTS: of the 3,834 white participants with no prior stroke, 548 had an incident ischaemic stroke over the 11.5-year follow-up. Among whites, the incident stroke hazard ratio (HR) associated with living in the lowest relative to highest NSES quartile was 1.32 (95% CI = 1.01-1.73), in models adjusted for individual SES. Additional adjustment for psychosocial factors had a minimal effect on hazard of incident stroke (HR = 1.31, CI = 1.00-1.71). Associations between NSES and stroke incidence were not found among African-Americans (n = 785) in either partially or fully adjusted models. CONCLUSIONS: psychosocial factors played a minimal role in mediating the effect of NSES on stroke incidence among white older adults.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Aging; Brain Ischemia; Depression; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Linear Models; Logistic Models; Male; Middle Aged; Proportional Hazards Models; Prospective Studies; Residence Characteristics; Risk Assessment; Risk Factors; Social Support; Socioeconomic Factors; Stroke; Time Factors; United States; Vulnerable Populations

Fine Mapping and Identification of BMI Loci in African Americans. - Gong, Jian; Schumacher, Fredrick; Lim, Unhee; Hindorff, Lucia A; Haessler, Jeff; Buyske, Steven; Carlson, Christopher S; Rosse, Stephanie; Bůzková, Petra; Fornage, Myriam; Gross, Myron; Pankratz, Nathan; et al. (Am J Hum Genet, 2013)
Genome-wide association studies (GWASs) primarily performed in European-ancestry (EA) populations have identified numerous loci associated with body mass index (BMI). However, it is still unclear whether these GWAS loci can be generalized to other ethnic groups, such as African Americans (AAs). Furthermore, the putative functional variant or variants in these loci mostly remain under investigation. The overall lower linkage disequilibrium in AA compared to EA populations provides the opportunity to narrow in or fine-map these BMI-related loci. Therefore, we used the Metabochip to densely genotype and evaluate 21 BMI GWAS loci identified in EA studies in 29,151 AAs from the Population Architecture using Genomics and Epidemiology (PAGE) study. Eight of the 21 loci (SEC16B, TMEM18, ETV5, GNPDA2, TFAP2B, BDNF, FTO, and MC4R) were found to be associated with BMI in AAs at 5.8 × 10(-5). Within seven out of these eight loci, we found that, on average, a substantially smaller number of variants was correlated (r(2) > 0.5) with the most significant SNP in AA than in EA populations (16 versus 55). Conditional analyses revealed GNPDA2 harboring a potential additional independent signal. Moreover, Metabochip-wide discovery analyses revealed two BMI-related loci, BRE (rs116612809, p = 3.6 × 10(-8)) and DHX34 (rs4802349, p = 1.2 × 10(-7)), which were significant when adjustment was made for the total number of SNPs tested across the chip. These results demonstrate that fine mapping in AAs is a powerful approach for both narrowing in on the underlying causal variants in known loci and discovering BMI-related loci.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Body Mass Index; Female; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Young Adult

Generalization and dilution of association results from European GWAS in populations of non-European ancestry: the PAGE study. - Carlson, Christopher S; Matise, Tara C; North, Kari E; Haiman, Christopher A; Fesinmeyer, Megan D; Buyske, Steven; Schumacher, Fredrick R; Peters, Ulrike; Franceschini, Nora; Ritchie, Marylyn D; Duggan, David J; Spencer, Kylee L; et al. (PLoS Biol, 2013)
The vast majority of genome-wide association study (GWAS) findings reported to date are from populations with European Ancestry (EA), and it is not yet clear how broadly the genetic associations described will generalize to populations of diverse ancestry. The Population Architecture Using Genomics and Epidemiology (PAGE) study is a consortium of multi-ancestry, population-based studies formed with the objective of refining our understanding of the genetic architecture of common traits emerging from GWAS. In the present analysis of five common diseases and traits, including body mass index, type 2 diabetes, and lipid levels, we compare direction and magnitude of effects for GWAS-identified variants in multiple non-EA populations against EA findings. We demonstrate that, in all populations analyzed, a significant majority of GWAS-identified variants have allelic associations in the same direction as in EA, with none showing a statistically significant effect in the opposite direction, after adjustment for multiple testing. However, 25% of tagSNPs identified in EA GWAS have significantly different effect sizes in at least one non-EA population, and these differential effects were most frequent in African Americans where all differential effects were diluted toward the null. We demonstrate that differential LD between tagSNPs and functional variants within populations contributes significantly to dilute effect sizes in this population. Although most variants identified from GWAS in EA populations generalize to all non-EA populations assessed, genetic models derived from GWAS findings in EA may generate spurious results in non-EA populations due to differential effect sizes. Regardless of the origin of the differential effects, caution should be exercised in applying any genetic risk prediction model based on tagSNPs outside of the ancestry group in which it was derived. Models based directly on functional variation may generalize more robustly, but the identification of functional variants remains challenging.
Keywords: African Americans; Asian Americans; Body Mass Index; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Hispanic Americans; Humans; Indians, North American; Lipids; Metagenomics; Oceanic Ancestry Group; Polymorphism, Single Nucleotide

Genetic loci for retinal arteriolar microcirculation. - Sim, Xueling; Jensen, Richard A; Ikram, M Kamran; Cotch, Mary Frances; Li, Xiaohui; Macgregor, Stuart; Xie, Jing; Smith, Albert Vernon; Boerwinkle, Eric; Mitchell, Paul; Klein, Ronald; Klein, Barbara E K; et al. (PLoS One, 2013)
Narrow arterioles in the retina have been shown to predict hypertension as well as other vascular diseases, likely through an increase in the peripheral resistance of the microcirculatory flow. In this study, we performed a genome-wide association study in 18,722 unrelated individuals of European ancestry from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium and the Blue Mountain Eye Study, to identify genetic determinants associated with variations in retinal arteriolar caliber. Retinal vascular calibers were measured on digitized retinal photographs using a standardized protocol. One variant (rs2194025 on chromosome 5q14 near the myocyte enhancer factor 2C MEF2C gene) was associated with retinal arteriolar caliber in the meta-analysis of the discovery cohorts at genome-wide significance of P-value <5×10(-8). This variant was replicated in an additional 3,939 individuals of European ancestry from the Australian Twins Study and Multi-Ethnic Study of Atherosclerosis (rs2194025, P-value = 2.11×10(-12) in combined meta-analysis of discovery and replication cohorts). In independent studies of modest sample sizes, no significant association was found between this variant and clinical outcomes including coronary artery disease, stroke, myocardial infarction or hypertension. In conclusion, we found one novel loci which underlie genetic variation in microvasculature which may be relevant to vascular disease. The relevance of these findings to clinical outcomes remains to be determined.
Keywords: Aged; Aged, 80 and over; Arterioles; Chromosomes, Human, Pair 5; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Male; MEF2 Transcription Factors; Microcirculation; Middle Aged; Models, Genetic; Retinal Vessels

Genome-wide and gene-centric analyses of circulating myeloperoxidase levels in the charge and care consortia. - Reiner, Alexander P; Hartiala, Jaana; Zeller, Tanja; Bis, Joshua C; Dupuis, Josée; Fornage, Myriam; Baumert, Jens; Kleber, Marcus E; Wild, Philipp S; Baldus, Stephan; Bielinski, Suzette J; Fontes, João D; et al. (Hum Mol Genet, 2013)
Increased systemic levels of myeloperoxidase (MPO) are associated with the risk of coronary artery disease (CAD). To identify the genetic factors that are associated with circulating MPO levels, we carried out a genome-wide association study (GWAS) and a gene-centric analysis in subjects of European ancestry and African Americans (AAs). A locus on chromosome 1q31.1 containing the complement factor H (CFH) gene was strongly associated with serum MPO levels in 9305 subjects of European ancestry (lead SNP rs800292; P = 4.89 × 10(-41)) and in 1690 AA subjects (rs505102; P = 1.05 × 10(-8)). Gene-centric analyses in 8335 subjects of European ancestry additionally identified two rare MPO coding sequence variants that were associated with serum MPO levels (rs28730837, P = 5.21 × 10(-12); rs35897051, P = 3.32 × 10(-8)). A GWAS for plasma MPO levels in 9260 European ancestry subjects identified a chromosome 17q22 region near MPO that was significantly associated (lead SNP rs6503905; P = 2.94 × 10(-12)), but the CFH locus did not exhibit evidence of association with plasma MPO levels. Functional analyses revealed that rs800292 was associated with levels of complement proteins in serum. Variants at chromosome 17q22 also had pleiotropic cis effects on gene expression. In a case-control analysis of ∼80 000 subjects from CARDIoGRAM, none of the identified single-nucleotide polymorphisms (SNPs) were associated with CAD. These results suggest that distinct genetic factors regulate serum and plasma MPO levels, which may have relevance for various acute and chronic inflammatory disorders. The clinical implications for CAD and a better understanding of the functional basis for the association of CFH and MPO variants with circulating MPO levels require further study.
Keywords: Adult; African Americans; Aged; Case-Control Studies; Complement Factor H; Coronary Artery Disease; European Continental Ancestry Group; Female; Gene Expression Regulation, Enzymologic; Genetic Association Studies; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Peroxidase; Polymorphism, Single Nucleotide; Young Adult

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Genome-wide association of body fat distribution in African ancestry populations suggests new loci. - Liu, Ching-Ti; Monda, Keri L; Taylor, Kira C; Lange, Leslie; Demerath, Ellen W; Palmas, Walter; Wojczynski, Mary K; Ellis, Jaclyn C; Vitolins, Mara Z; Liu, Simin; Papanicolaou, George J; Irvin, Marguerite R; et al. (PLoS Genet, 2013)
Central obesity, measured by waist circumference (WC) or waist-hip ratio (WHR), is a marker of body fat distribution. Although obesity disproportionately affects minority populations, few studies have conducted genome-wide association study (GWAS) of fat distribution among those of predominantly African ancestry (AA). We performed GWAS of WC and WHR, adjusted and unadjusted for BMI, in up to 33,591 and 27,350 AA individuals, respectively. We identified loci associated with fat distribution in AA individuals using meta-analyses of GWA results for WC and WHR (stage 1). Overall, 25 SNPs with single genomic control (GC)-corrected p-values<5.0 × 10(-6) were followed-up (stage 2) in AA with WC and with WHR. Additionally, we interrogated genomic regions of previously identified European ancestry (EA) WHR loci among AA. In joint analysis of association results including both Stage 1 and 2 cohorts, 2 SNPs demonstrated association, rs2075064 at LHX2, p = 2.24×10(-8) for WC-adjusted-for-BMI, and rs6931262 at RREB1, p = 2.48×10(-8) for WHR-adjusted-for-BMI. However, neither signal was genome-wide significant after double GC-correction (LHX2: p = 6.5 × 10(-8); RREB1: p = 5.7 × 10(-8)). Six of fourteen previously reported loci for waist in EA populations were significant (p<0.05 divided by the number of independent SNPs within the region) in AA studied here (TBX15-WARS2, GRB14, ADAMTS9, LY86, RSPO3, ITPR2-SSPN). Further, we observed associations with metabolic traits: rs13389219 at GRB14 associated with HDL-cholesterol, triglycerides, and fasting insulin, and rs13060013 at ADAMTS9 with HDL-cholesterol and fasting insulin. Finally, we observed nominal evidence for sexual dimorphism, with stronger results in AA women at the GRB14 locus (p for interaction = 0.02). In conclusion, we identified two suggestive loci associated with fat distribution in AA populations in addition to confirming 6 loci previously identified in populations of EA. These findings reinforce the concept that there are fat distribution loci that are independent of generalized adiposity.
Keywords: Adiposity; African Continental Ancestry Group; Body Fat Distribution; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Obesity; Polymorphism, Single Nucleotide; Waist-Hip Ratio

A genome-wide association study of depressive symptoms. - Hek, Karin; Demirkan, Ayse; Lahti, Jari; Terracciano, Antonio; Teumer, Alexander; Cornelis, Marilyn C; Amin, Najaf; Bakshis, Erin; Baumert, Jens; Ding, Jingzhong; Liu, Yongmei; Marciante, Kristin; et al. (Biol Psychiatry, 2013)
BACKGROUND: Depression is a heritable trait that exists on a continuum of varying severity and duration. Yet, the search for genetic variants associated with depression has had few successes. We exploit the entire continuum of depression to find common variants for depressive symptoms. METHODS: In this genome-wide association study, we combined the results of 17 population-based studies assessing depressive symptoms with the Center for Epidemiological Studies Depression Scale. Replication of the independent top hits (p<1×10(-5)) was performed in five studies assessing depressive symptoms with other instruments. In addition, we performed a combined meta-analysis of all 22 discovery and replication studies. RESULTS: The discovery sample comprised 34,549 individuals (mean age of 66.5) and no loci reached genome-wide significance (lowest p = 1.05×10(-7)). Seven independent single nucleotide polymorphisms were considered for replication. In the replication set (n = 16,709), we found suggestive association of one single nucleotide polymorphism with depressive symptoms (rs161645, 5q21, p = 9.19×10(-3)). This 5q21 region reached genome-wide significance (p = 4.78×10(-8)) in the overall meta-analysis combining discovery and replication studies (n = 51,258). CONCLUSIONS: The results suggest that only a large sample comprising more than 50,000 subjects may be sufficiently powered to detect genes for depressive symptoms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human, Pair 5; Depression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

A genome-wide association study of early menopause and the combined impact of identified variants. - Perry, John R B; Corre, Tanguy; Esko, Tõnu; Chasman, Daniel I; Fischer, Krista; Franceschini, Nora; He, Chunyan; Kutalik, Zoltán; Mangino, Massimo; Rose, Lynda M; Vernon Smith, Albert; Stolk, Lisette; et al. (Hum Mol Genet, 2013)
Early menopause (EM) affects up to 10% of the female population, reducing reproductive lifespan considerably. Currently, it constitutes the leading cause of infertility in the western world, affecting mainly those women who postpone their first pregnancy beyond the age of 30 years. The genetic aetiology of EM is largely unknown in the majority of cases. We have undertaken a meta-analysis of genome-wide association studies (GWASs) in 3493 EM cases and 13 598 controls from 10 independent studies. No novel genetic variants were discovered, but the 17 variants previously associated with normal age at natural menopause as a quantitative trait (QT) were also associated with EM and primary ovarian insufficiency (POI). Thus, EM has a genetic aetiology which overlaps variation in normal age at menopause and is at least partly explained by the additive effects of the same polygenic variants. The combined effect of the common variants captured by the single nucleotide polymorphism arrays was estimated to account for ∼30% of the variance in EM. The association between the combined 17 variants and the risk of EM was greater than the best validated non-genetic risk factor, smoking.
Keywords: Case-Control Studies; Female; Gene Frequency; Genome-Wide Association Study; Humans; Menopause, Premature; Polymorphism, Single Nucleotide; Primary Ovarian Insufficiency; Quantitative Trait Loci; Risk

Genome-wide association study of retinopathy in individuals without diabetes. - Jensen, Richard A; Sim, Xueling; Li, Xiaohui; Cotch, Mary Frances; Ikram, M Kamran; Holliday, Elizabeth G; Eiriksdottir, Gudny; Harris, Tamara B; Jonasson, Fridbert; Klein, Barbara E K; Launer, Lenore J; Smith, Albert Vernon; et al. (PLoS One, 2013)
BACKGROUND: Mild retinopathy (microaneurysms or dot-blot hemorrhages) is observed in persons without diabetes or hypertension and may reflect microvascular disease in other organs. We conducted a genome-wide association study (GWAS) of mild retinopathy in persons without diabetes. METHODS: A working group agreed on phenotype harmonization, covariate selection and analytic plans for within-cohort GWAS. An inverse-variance weighted fixed effects meta-analysis was performed with GWAS results from six cohorts of 19,411 Caucasians. The primary analysis included individuals without diabetes and secondary analyses were stratified by hypertension status. We also singled out the results from single nucleotide polymorphisms (SNPs) previously shown to be associated with diabetes and hypertension, the two most common causes of retinopathy. RESULTS: No SNPs reached genome-wide significance in the primary analysis or the secondary analysis of participants with hypertension. SNP, rs12155400, in the histone deacetylase 9 gene (HDAC9) on chromosome 7, was associated with retinopathy in analysis of participants without hypertension, -1.3±0.23 (beta ± standard error), p = 6.6×10(-9). Evidence suggests this was a false positive finding. The minor allele frequency was low (∼2%), the quality of the imputation was moderate (r(2) ∼0.7), and no other common variants in the HDAC9 gene were associated with the outcome. SNPs found to be associated with diabetes and hypertension in other GWAS were not associated with retinopathy in persons without diabetes or in subgroups with or without hypertension. CONCLUSIONS: This GWAS of retinopathy in individuals without diabetes showed little evidence of genetic associations. Further studies are needed to identify genes associated with these signs in order to help unravel novel pathways and determinants of microvascular diseases.
Keywords: Aged; Aged, 80 and over; Female; Genome-Wide Association Study; Genotype; Histone Deacetylases; Humans; Hypertension; Male; Polymorphism, Single Nucleotide; Repressor Proteins; Retinal Diseases

Genome-wide meta-analysis identifies 11 new loci for anthropometric traits and provides insights into genetic architecture. - Berndt, Sonja I; Gustafsson, Stefan; Mägi, Reedik; Ganna, Andrea; Wheeler, Eleanor; Feitosa, Mary F; Justice, Anne E; Monda, Keri L; Croteau-Chonka, Damien C; Day, Felix R; Esko, Tõnu; Fall, Tove; et al. (Nat Genet, 2013)
Approaches exploiting trait distribution extremes may be used to identify loci associated with common traits, but it is unknown whether these loci are generalizable to the broader population. In a genome-wide search for loci associated with the upper versus the lower 5th percentiles of body mass index, height and waist-to-hip ratio, as well as clinical classes of obesity, including up to 263,407 individuals of European ancestry, we identified 4 new loci (IGFBP4, H6PD, RSRC1 and PPP2R2A) influencing height detected in the distribution tails and 7 new loci (HNF4G, RPTOR, GNAT2, MRPS33P4, ADCY9, HS6ST3 and ZZZ3) for clinical classes of obesity. Further, we find a large overlap in genetic structure and the distribution of variants between traits based on extremes and the general population and little etiological heterogeneity between obesity subgroups.
Keywords: Anthropometry; Body Height; Body Mass Index; Case-Control Studies; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Meta-Analysis as Topic; Obesity; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Waist-Hip Ratio

Genome-wide meta-analysis of observational studies shows common genetic variants associated with macronutrient intake. - Tanaka, Toshiko; Ngwa, Julius S; van Rooij, Frank J A; Zillikens, M Carola; Wojczynski, Mary K; Frazier-Wood, Alexis C; Houston, Denise K; Kanoni, Stavroula; Lemaitre, Rozenn N; Luan, Jian'an; Mikkilä, Vera; Renstrom, Frida; et al. (Am J Clin Nutr, 2013)
BACKGROUND: Macronutrient intake varies substantially between individuals, and there is evidence that this variation is partly accounted for by genetic variants. OBJECTIVE: The objective of the study was to identify common genetic variants that are associated with macronutrient intake. DESIGN: We performed 2-stage genome-wide association (GWA) meta-analysis of macronutrient intake in populations of European descent. Macronutrients were assessed by using food-frequency questionnaires and analyzed as percentages of total energy consumption from total fat, protein, and carbohydrate. From the discovery GWA (n = 38,360), 35 independent loci associated with macronutrient intake at P < 5 × 10(-6) were identified and taken forward to replication in 3 additional cohorts (n = 33,533) from the DietGen Consortium. For one locus, fat mass obesity-associated protein (FTO), cohorts with Illumina MetaboChip genotype data (n = 7724) provided additional replication data. RESULTS: A variant in the chromosome 19 locus (rs838145) was associated with higher carbohydrate (β ± SE: 0.25 ± 0.04%; P = 1.68 × 10(-8)) and lower fat (β ± SE: -0.21 ± 0.04%; P = 1.57 × 10(-9)) consumption. A candidate gene in this region, fibroblast growth factor 21 (FGF21), encodes a fibroblast growth factor involved in glucose and lipid metabolism. The variants in this locus were associated with circulating FGF21 protein concentrations (P < 0.05) but not mRNA concentrations in blood or brain. The body mass index (BMI)-increasing allele of the FTO variant (rs1421085) was associated with higher protein intake (β ± SE: 0.10 ± 0.02%; P = 9.96 × 10(-10)), independent of BMI (after adjustment for BMI, β ± SE: 0.08 ± 0.02%; P = 3.15 × 10(-7)). CONCLUSION: Our results indicate that variants in genes involved in nutrient metabolism and obesity are associated with macronutrient consumption in humans. Trials related to this study were registered at clinicaltrials.gov as NCT00005131 (Atherosclerosis Risk in Communities), NCT00005133 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetic and Environmental Determinants of Triglycerides), NCT01331512 (InCHIANTI Study), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Alleles; Atherosclerosis; Body Mass Index; Dietary Carbohydrates; Dietary Fats; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Fibroblast Growth Factors; Follow-Up Studies; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Life Style; Obesity; Polymorphism, Single Nucleotide; Prospective Studies; Quantitative Trait Loci; Surveys and Questionnaires

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD. - Hansel, Nadia N; Ruczinski, Ingo; Rafaels, Nicholas; Sin, Don D; Daley, Denise; Malinina, Alla; Huang, Lili; Sandford, Andrew; Murray, Tanda; Kim, Yoonhee; Vergara, Candelaria; Heckbert, Susan R; et al. (Hum Genet, 2013)
Accelerated lung function decline is a key COPD phenotype; however, its genetic control remains largely unknown. We performed a genome-wide association study using the Illumina Human660W-Quad v.1_A BeadChip. Generalized estimation equations were used to assess genetic contributions to lung function decline over a 5-year period in 4,048 European American Lung Health Study participants with largely mild COPD. Genotype imputation was performed using reference HapMap II data. To validate regions meeting genome-wide significance, replication of top SNPs was attempted in independent cohorts. Three genes (TMEM26, ANK3 and FOXA1) within the regions of interest were selected for tissue expression studies using immunohistochemistry. Two intergenic SNPs (rs10761570, rs7911302) on chromosome 10 and one SNP on chromosome 14 (rs177852) met genome-wide significance after Bonferroni. Further support for the chromosome 10 region was obtained by imputation, the most significantly associated imputed SNPs (rs10761571, rs7896712) being flanked by observed markers rs10761570 and rs7911302. Results were not replicated in four general population cohorts or a smaller cohort of subjects with moderate to severe COPD; however, we show novel expression of genes near regions of significantly associated SNPS, including TMEM26 and FOXA1 in airway epithelium and lung parenchyma, and ANK3 in alveolar macrophages. Levels of expression were associated with lung function and COPD status. We identified two novel regions associated with lung function decline in mild COPD. Genes within these regions were expressed in relevant lung cells and their expression related to airflow limitation suggesting they may represent novel candidate genes for COPD susceptibility.
Keywords: Adult; Ankyrins; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 14; Cohort Studies; Female; Genome-Wide Association Study; Hepatocyte Nuclear Factor 3-alpha; Humans; Linkage Disequilibrium; Lung; Male; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive

Identification of heart rate-associated loci and their effects on cardiac conduction and rhythm disorders. - den Hoed, Marcel; Eijgelsheim, Mark; Esko, Tõnu; Brundel, Bianca J J M; Peal, David S; Evans, David M; Nolte, Ilja M; Segrè, Ayellet V; Holm, Hilma; Handsaker, Robert E; Westra, Harm-Jan; Johnson, Toby; et al. (Nat Genet, 2013)
Elevated resting heart rate is associated with greater risk of cardiovascular disease and mortality. In a 2-stage meta-analysis of genome-wide association studies in up to 181,171 individuals, we identified 14 new loci associated with heart rate and confirmed associations with all 7 previously established loci. Experimental downregulation of gene expression in Drosophila melanogaster and Danio rerio identified 20 genes at 11 loci that are relevant for heart rate regulation and highlight a role for genes involved in signal transmission, embryonic cardiac development and the pathophysiology of dilated cardiomyopathy, congenital heart failure and/or sudden cardiac death. In addition, genetic susceptibility to increased heart rate is associated with altered cardiac conduction and reduced risk of sick sinus syndrome, and both heart rate-increasing and heart rate-decreasing variants associate with risk of atrial fibrillation. Our findings provide fresh insights into the mechanisms regulating heart rate and identify new therapeutic targets.
Keywords: Animals; Arrhythmias, Cardiac; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Heart Rate; Humans; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Insights into the genetic architecture of early stage age-related macular degeneration: a genome-wide association study meta-analysis. - Holliday, Elizabeth G; Smith, Albert V; Cornes, Belinda K; Buitendijk, Gabriëlle H S; Jensen, Richard A; Sim, Xueling; Aspelund, Thor; Aung, Tin; Baird, Paul N; Boerwinkle, Eric; Cheng, Ching Yu; van Duijn, Cornelia M; et al. (PLoS One, 2013)
Genetic factors explain a majority of risk variance for age-related macular degeneration (AMD). While genome-wide association studies (GWAS) for late AMD implicate genes in complement, inflammatory and lipid pathways, the genetic architecture of early AMD has been relatively under studied. We conducted a GWAS meta-analysis of early AMD, including 4,089 individuals with prevalent signs of early AMD (soft drusen and/or retinal pigment epithelial changes) and 20,453 individuals without these signs. For various published late AMD risk loci, we also compared effect sizes between early and late AMD using an additional 484 individuals with prevalent late AMD. GWAS meta-analysis confirmed previously reported association of variants at the complement factor H (CFH) (peak P = 1.5×10(-31)) and age-related maculopathy susceptibility 2 (ARMS2) (P = 4.3×10(-24)) loci, and suggested Apolipoprotein E (ApoE) polymorphisms (rs2075650; P = 1.1×10(-6)) associated with early AMD. Other possible loci that did not reach GWAS significance included variants in the zinc finger protein gene GLI3 (rs2049622; P = 8.9×10(-6)) and upstream of GLI2 (rs6721654; P = 6.5×10(-6)), encoding retinal Sonic hedgehog signalling regulators, and in the tyrosinase (TYR) gene (rs621313; P = 3.5×10(-6)), involved in melanin biosynthesis. For a range of published, late AMD risk loci, estimated effect sizes were significantly lower for early than late AMD. This study confirms the involvement of multiple established AMD risk variants in early AMD, but suggests weaker genetic effects on the risk of early AMD relative to late AMD. Several biological processes were suggested to be potentially specific for early AMD, including pathways regulating RPE cell melanin content and signalling pathways potentially involved in retinal regeneration, generating hypotheses for further investigation.
Keywords: Apolipoproteins E; Complement Factor H; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Kruppel-Like Transcription Factors; Macular Degeneration; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Proteins; Risk Factors; Zinc Finger Protein Gli3

Investigation of gene-by-sex interactions for lipid traits in diverse populations from the population architecture using genomics and epidemiology study. - Taylor, Kira C; Carty, Cara L; Dumitrescu, Logan; Bůzková, Petra; Cole, Shelley A; Hindorff, Lucia; Schumacher, Fred R; Wilkens, Lynne R; Shohet, Ralph V; Quibrera, P Miguel; Johnson, Karen C; Henderson, Brian E; et al. (BMC Genet, 2013)
BACKGROUND: High-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) levels are influenced by both genes and the environment. Genome-wide association studies (GWAS) have identified ~100 common genetic variants associated with HDL-C, LDL-C, and/or TG levels, mostly in populations of European descent, but little is known about the modifiers of these associations. Here, we investigated whether GWAS-identified SNPs for lipid traits exhibited heterogeneity by sex in the Population Architecture using Genomics and Epidemiology (PAGE) study. RESULTS: A sex-stratified meta-analysis was performed for 49 GWAS-identified SNPs for fasting HDL-C, LDL-C, and ln(TG) levels among adults self-identified as European American (25,013). Heterogeneity by sex was established when phet < 0.001. There was evidence for heterogeneity by sex for two SNPs for ln(TG) in the APOA1/C3/A4/A5/BUD13 gene cluster: rs28927680 (p(het) = 7.4 x 10(-7)) and rs3135506 (p(het) = 4.3 x 10(-4)one SNP in PLTP for HDL levels (rs7679; p(het) = 9.9 x 10(-4)), and one in HMGCR for LDL levels (rs12654264; p(het) = 3.1 x 10(-5)). We replicated heterogeneity by sex in five of seventeen loci previously reported by genome-wide studies (binomial p = 0.0009). We also present results for other racial/ethnic groups in the supplementary materials, to provide a resource for future meta-analyses. CONCLUSIONS: We provide further evidence for sex-specific effects of SNPs in the APOA1/C3/A4/A5/BUD13 gene cluster, PLTP, and HMGCR on fasting triglyceride levels in European Americans from the PAGE study. Our findings emphasize the need for considering context-specific effects when interpreting genetic associations emerging from GWAS, and also highlight the difficulties in replicating interaction effects across studies and across racial/ethnic groups.
Keywords: Female; Genetic Heterogeneity; Genome, Human; Genome-Wide Association Study; Humans; Lipids; Male; Polymorphism, Single Nucleotide; Population Groups

Ischemic stroke is associated with the ABO locus: the EuroCLOT study. - Williams, Frances M K; Carter, Angela M; Hysi, Pirro G; Surdulescu, Gabriela; Hodgkiss, Dylan; Soranzo, Nicole; Traylor, Matthew; Bevan, Steve; Dichgans, Martin; Rothwell, Peter M W; Sudlow, Cathie; Farrall, Martin; et al. (Ann Neurol, 2013)
OBJECTIVE: End-stage coagulation and the structure/function of fibrin are implicated in the pathogenesis of ischemic stroke. We explored whether genetic variants associated with end-stage coagulation in healthy volunteers account for the genetic predisposition to ischemic stroke and examined their influence on stroke subtype. METHODS: Common genetic variants identified through genome-wide association studies of coagulation factors and fibrin structure/function in healthy twins (n = 2,100, Stage 1) were examined in ischemic stroke (n = 4,200 cases) using 2 independent samples of European ancestry (Stage 2). A third clinical collection having stroke subtyping (total 8,900 cases, 55,000 controls) was used for replication (Stage 3). RESULTS: Stage 1 identified 524 single nucleotide polymorphisms (SNPs) from 23 linkage disequilibrium blocks having significant association (p < 5 × 10(-8)) with 1 or more coagulation/fibrin phenotypes. The most striking associations included SNP rs5985 with factor XIII activity (p = 2.6 × 10(-186)), rs10665 with FVII (p = 2.4 × 10(-47)), and rs505922 in the ABO gene with both von Willebrand factor (p = 4.7 × 10(-57)) and factor VIII (p = 1.2 × 10(-36)). In Stage 2, the 23 independent SNPs were examined in stroke cases/noncases using MOnica Risk, Genetics, Archiving and Monograph (MORGAM) and Wellcome Trust Case Control Consortium 2 collections. SNP rs505922 was nominally associated with ischemic stroke (odds ratio = 0.94, 95% confidence interval = 0.88-0.99, p = 0.023). Independent replication in Meta-Stroke confirmed the rs505922 association with stroke, beta (standard error, SE) = 0.066 (0.02), p = 0.001, a finding specific to large-vessel and cardioembolic stroke (p = 0.001 and p = < 0.001, respectively) but not seen with small-vessel stroke (p = 0.811). INTERPRETATION: ABO gene variants are associated with large-vessel and cardioembolic stroke but not small-vessel disease. This work sheds light on the different pathogenic mechanisms underpinning stroke subtype.
Keywords: ABO Blood-Group System; Adolescent; Adult; Aged; Aged, 80 and over; Blood Coagulation; Brain Ischemia; Cohort Studies; Europe; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Stroke; Young Adult

A meta-analysis identifies new loci associated with body mass index in individuals of African ancestry. - Monda, Keri L; Chen, Gary K; Taylor, Kira C; Palmer, Cameron; Edwards, Todd L; Lange, Leslie A; Ng, Maggie C Y; Adeyemo, Adebowale A; Allison, Matthew A; Bielak, Lawrence F; Chen, Guanjie; Graff, Mariaelisa; et al. (Nat Genet, 2013)
Genome-wide association studies (GWAS) have identified 36 loci associated with body mass index (BMI), predominantly in populations of European ancestry. We conducted a meta-analysis to examine the association of >3.2 million SNPs with BMI in 39,144 men and women of African ancestry and followed up the most significant associations in an additional 32,268 individuals of African ancestry. We identified one new locus at 5q33 (GALNT10, rs7708584, P = 3.4 × 10(-11)) and another at 7p15 when we included data from the GIANT consortium (MIR148A-NFE2L3, rs10261878, P = 1.2 × 10(-10)). We also found suggestive evidence of an association at a third locus at 6q16 in the African-ancestry sample (KLHL32, rs974417, P = 6.9 × 10(-8)). Thirty-two of the 36 previously established BMI variants showed directionally consistent effect estimates in our GWAS (binomial P = 9.7 × 10(-7)), five of which reached genome-wide significance. These findings provide strong support for shared BMI loci across populations, as well as for the utility of studying ancestrally diverse populations.
Keywords: African Americans; Body Mass Index; Case-Control Studies; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Obesity; Polymorphism, Single Nucleotide

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Meta-analysis of genome-wide association studies identifies six new Loci for serum calcium concentrations. - O'Seaghdha, Conall M; Wu, Hongsheng; Yang, Qiong; Kapur, Karen; Guessous, Idris; Zuber, Annie Mercier; Köttgen, Anna; Stoudmann, Candice; Teumer, Alexander; Kutalik, Zoltán; Mangino, Massimo; Dehghan, Abbas; et al. (PLoS Genet, 2013)
Calcium is vital to the normal functioning of multiple organ systems and its serum concentration is tightly regulated. Apart from CASR, the genes associated with serum calcium are largely unknown. We conducted a genome-wide association meta-analysis of 39,400 individuals from 17 population-based cohorts and investigated the 14 most strongly associated loci in ≤ 21,679 additional individuals. Seven loci (six new regions) in association with serum calcium were identified and replicated. Rs1570669 near CYP24A1 (P = 9.1E-12), rs10491003 upstream of GATA3 (P = 4.8E-09) and rs7481584 in CARS (P = 1.2E-10) implicate regions involved in Mendelian calcemic disorders: Rs1550532 in DGKD (P = 8.2E-11), also associated with bone density, and rs7336933 near DGKH/KIAA0564 (P = 9.1E-10) are near genes that encode distinct isoforms of diacylglycerol kinase. Rs780094 is in GCKR. We characterized the expression of these genes in gut, kidney, and bone, and demonstrate modulation of gene expression in bone in response to dietary calcium in mice. Our results shed new light on the genetics of calcium homeostasis.
Keywords: Animals; Bone and Bones; Bone Density; Calcium; European Continental Ancestry Group; Gene Expression Regulation; Genome-Wide Association Study; Homeostasis; Humans; Kidney; Mice; Polymorphism, Single Nucleotide

A meta-analysis of thyroid-related traits reveals novel loci and gender-specific differences in the regulation of thyroid function. - Porcu, Eleonora; Medici, Marco; Pistis, Giorgio; Volpato, Claudia B; Wilson, Scott G; Cappola, Anne R; Bos, Steffan D; Deelen, Joris; den Heijer, Martin; Freathy, Rachel M; Lahti, Jari; Liu, Chunyu; et al. (PLoS Genet, 2013)
Thyroid hormone is essential for normal metabolism and development, and overt abnormalities in thyroid function lead to common endocrine disorders affecting approximately 10% of individuals over their life span. In addition, even mild alterations in thyroid function are associated with weight changes, atrial fibrillation, osteoporosis, and psychiatric disorders. To identify novel variants underlying thyroid function, we performed a large meta-analysis of genome-wide association studies for serum levels of the highly heritable thyroid function markers TSH and FT4, in up to 26,420 and 17,520 euthyroid subjects, respectively. Here we report 26 independent associations, including several novel loci for TSH (PDE10A, VEGFA, IGFBP5, NFIA, SOX9, PRDM11, FGF7, INSR, ABO, MIR1179, NRG1, MBIP, ITPK1, SASH1, GLIS3) and FT4 (LHX3, FOXE1, AADAT, NETO1/FBXO15, LPCAT2/CAPNS2). Notably, only limited overlap was detected between TSH and FT4 associated signals, in spite of the feedback regulation of their circulating levels by the hypothalamic-pituitary-thyroid axis. Five of the reported loci (PDE8B, PDE10A, MAF/LOC440389, NETO1/FBXO15, and LPCAT2/CAPNS2) show strong gender-specific differences, which offer clues for the known sexual dimorphism in thyroid function and related pathologies. Importantly, the TSH-associated loci contribute not only to variation within the normal range, but also to TSH values outside the reference range, suggesting that they may be involved in thyroid dysfunction. Overall, our findings explain, respectively, 5.64% and 2.30% of total TSH and FT4 trait variance, and they improve the current knowledge of the regulation of hypothalamic-pituitary-thyroid axis function and the consequences of genetic variation for hypo- or hyperthyroidism.
Keywords: Female; Genome-Wide Association Study; Humans; Hyperthyroidism; Hypothyroidism; Male; Phenotype; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Sex Characteristics; Signal Transduction; Thyroid Gland; Thyrotropin; Thyroxine

Multiethnic meta-analysis of genome-wide association studies in >100 000 subjects identifies 23 fibrinogen-associated Loci but no strong evidence of a causal association between circulating fibrinogen and cardiovascular disease. - Sabater-Lleal, Maria; Huang, Jie; Chasman, Daniel; Naitza, Silvia; Dehghan, Abbas; Johnson, Andrew D; Teumer, Alexander; Reiner, Alex P; Folkersen, Lasse; Basu, Saonli; Rudnicka, Alicja R; Trompet, Stella; et al. (Circulation, 2013)
BACKGROUND: Estimates of the heritability of plasma fibrinogen concentration, an established predictor of cardiovascular disease, range from 34% to 50%. Genetic variants so far identified by genome-wide association studies explain only a small proportion (<2%) of its variation. METHODS AND RESULTS: We conducted a meta-analysis of 28 genome-wide association studies including >90 000 subjects of European ancestry, the first genome-wide association meta-analysis of fibrinogen levels in 7 studies in blacks totaling 8289 samples, and a genome-wide association study in Hispanics totaling 1366 samples. Evaluation for association of single-nucleotide polymorphisms with clinical outcomes included a total of 40 695 cases and 85 582 controls for coronary artery disease, 4752 cases and 24 030 controls for stroke, and 3208 cases and 46 167 controls for venous thromboembolism. Overall, we identified 24 genome-wide significant (P<5×10(-8)) independent signals in 23 loci, including 15 novel associations, together accounting for 3.7% of plasma fibrinogen variation. Gene-set enrichment analysis highlighted key roles in fibrinogen regulation for the 3 structural fibrinogen genes and pathways related to inflammation, adipocytokines, and thyrotrophin-releasing hormone signaling. Whereas lead single-nucleotide polymorphisms in a few loci were significantly associated with coronary artery disease, the combined effect of all 24 fibrinogen-associated lead single-nucleotide polymorphisms was not significant for coronary artery disease, stroke, or venous thromboembolism. CONCLUSIONS: We identify 23 robustly associated fibrinogen loci, 15 of which are new. Clinical outcome analysis of these loci does not support a causal relationship between circulating levels of fibrinogen and coronary artery disease, stroke, or venous thromboembolism.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Cardiovascular Diseases; Coronary Artery Disease; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Hispanic Americans; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Risk Factors; Stroke; Venous Thromboembolism; Young Adult

Neighborhood socioeconomic disadvantage and mortality after stroke. - Brown, Arleen F; Liang, Li-Jung; Vassar, Stefanie D; Merkin, Sharon Stein; Longstreth, W T; Ovbiagele, Bruce; Yan, Tingjian; Escarce, José J (Neurology, 2013)
OBJECTIVE: Residence in a socioeconomically disadvantaged community is associated with mortality, but the mechanisms are not well understood. We examined whether socioeconomic features of the residential neighborhood contribute to poststroke mortality and whether neighborhood influences are mediated by traditional behavioral and biologic risk factors. METHODS: We used data from the Cardiovascular Health Study, a multicenter, population-based, longitudinal study of adults ≥65 years. Residential neighborhood disadvantage was measured using neighborhood socioeconomic status (NSES), a composite of 6 census tract variables representing income, education, employment, and wealth. Multilevel Cox proportional hazard models were constructed to determine the association of NSES to mortality after an incident stroke, adjusted for sociodemographic characteristics, stroke type, and behavioral and biologic risk factors. RESULTS: Among the 3,834 participants with no prior stroke at baseline, 806 had a stroke over a mean 11.5 years of follow-up, with 168 (20%) deaths 30 days after stroke and 276 (34%) deaths at 1 year. In models adjusted for demographic characteristics, stroke type, and behavioral and biologic risk factors, mortality hazard 1 year after stroke was significantly higher among residents of neighborhoods with the lowest NSES than those in the highest NSES neighborhoods (hazard ratio 1.77, 95% confidence interval 1.17-2.68). CONCLUSION: Living in a socioeconomically disadvantaged neighborhood is associated with higher mortality hazard at 1 year following an incident stroke. Further work is needed to understand the structural and social characteristics of neighborhoods that may contribute to mortality in the year after a stroke and the pathways through which these characteristics operate.
Keywords: Aged; Female; Humans; Incidence; Kaplan-Meier Estimate; Male; Proportional Hazards Models; Residence Characteristics; Risk Factors; Socioeconomic Factors; Stroke; Vulnerable Populations

No evidence of interaction between known lipid-associated genetic variants and smoking in the multi-ethnic PAGE population. - Dumitrescu, Logan; Carty, Cara L; Franceschini, Nora; Hindorff, Lucia A; Cole, Shelley A; Bůzková, Petra; Schumacher, Fredrick R; Eaton, Charles B; Goodloe, Robert J; Duggan, David J; Haessler, Jeff; Cochran, Barbara; et al. (Hum Genet, 2013)
Genome-wide association studies (GWAS) have identified many variants that influence high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and/or triglycerides. However, environmental modifiers, such as smoking, of these known genotype-phenotype associations are just recently emerging in the literature. We have tested for interactions between smoking and 49 GWAS-identified variants in over 41,000 racially/ethnically diverse samples with lipid levels from the Population Architecture Using Genomics and Epidemiology (PAGE) study. Despite their biological plausibility, we were unable to detect significant SNP × smoking interactions.
Keywords: Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Ethnic Groups; Female; Gene Frequency; Gene-Environment Interaction; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Male; Polymorphism, Single Nucleotide; Prevalence; Smoking; Triglycerides; Young Adult

Obesity is associated with a lower resting oxygen saturation in the ambulatory elderly: results from the cardiovascular health study. - Kapur, Vishesh K; Wilsdon, Anthony G; Au, David; Avdalovic, Mark; Enright, Paul; Fan, Vincent S; Hansel, Nadia N; Heckbert, Susan R; Jiang, Rui; Krishnan, Jerry A; Mukamal, Kenneth; Yende, Sachin; et al. (Respir Care, 2013)
BACKGROUND: The contribution of obesity to hypoxemia has not been reported in a community-based study. Our hypothesis was that increasing obesity would be independently associated with lower SpO2 in an ambulatory elderly population. METHODS: The Cardiovascular Health Study ascertained resting SpO2 in 2,252 subjects over age 64. We used multiple linear regression to estimate the association of body mass index (BMI) with SpO2 and to adjust for potentially confounding factors. Covariates including age, sex, race, smoking, airway obstruction (based on spirometry), self reported diagnosis of emphysema, asthma, heart failure, and left ventricular function (by echocardiography) were evaluated. RESULTS: Among 2,252 subjects the mean and median SpO2 were 97.6% and 98.0% respectively; 5% of subjects had SpO2 values below 95%. BMI was negatively correlated with SpO2 (Spearman R = -0.27, P < .001). The mean difference in SpO2 between the lowest and highest BMI categories (< 25 kg/m(2) and ≥ 35 kg/m(2)) was 1.33% (95% CI 0.89-1.78%). In multivariable linear regression analysis, SpO2 was significantly inversely associated with BMI (1.4% per 10 units of BMI, 95% CI 1.2-1.6, for whites/others, and 0.87% per 10 units of BMI, 95% CI 0.47-1.27, for African Americans). CONCLUSIONS: We found a narrow distribution of SpO2 values in a community-based sample of ambulatory elderly. Obesity was a strong independent contributor to a low SpO2, with effects comparable to or greater than other factors clinically associated with lower SpO2.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Body Mass Index; European Continental Ancestry Group; Female; Humans; Male; Obesity; Oximetry; Oxygen; Smoking; Waist Circumference

Post-genome-wide association study challenges for lipid traits: describing age as a modifier of gene-lipid associations in the Population Architecture using Genomics and Epidemiology (PAGE) study. - Dumitrescu, Logan; Carty, Cara L; Franceschini, Nora; Hindorff, Lucia A; Cole, Shelley A; Bůzková, Petra; Schumacher, Fredrick R; Eaton, Charles B; Goodloe, Robert J; Duggan, David J; Haessler, Jeff; Cochran, Barbara; et al. (Ann Hum Genet, 2013)
Numerous common genetic variants that influence plasma high-density lipoprotein cholesterol, low-density lipoprotein cholesterol (LDL-C), and triglyceride distributions have been identified via genome-wide association studies (GWAS). However, whether or not these associations are age-dependent has largely been overlooked. We conducted an association study and meta-analysis in more than 22,000 European Americans between 49 previously identified GWAS variants and the three lipid traits, stratified by age (males: <50 or ≥50 years of age; females: pre- or postmenopausal). For each variant, a test of heterogeneity was performed between the two age strata and significant Phet values were used as evidence of age-specific genetic effects. We identified seven associations in females and eight in males that displayed suggestive heterogeneity by age (Phet < 0.05). The association between rs174547 (FADS1) and LDL-C in males displayed the most evidence for heterogeneity between age groups (Phet = 1.74E-03, I(2) = 89.8), with a significant association in older males (P = 1.39E-06) but not younger males (P = 0.99). However, none of the suggestive modifying effects survived adjustment for multiple testing, highlighting the challenges of identifying modifiers of modest SNP-trait associations despite large sample sizes.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Genetic Association Studies; Genome-Wide Association Study; Humans; Lipids; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors

The QT interval and risk of incident atrial fibrillation. - Mandyam, Mala C; Soliman, Elsayed Z; Alonso, Alvaro; Dewland, Thomas A; Heckbert, Susan R; Vittinghoff, Eric; Cummings, Steven R; Ellinor, Patrick T; Chaitman, Bernard R; Stocke, Karen; Applegate, William B; Arking, Dan E; et al. (Heart Rhythm, 2013)
BACKGROUND: Abnormal atrial repolarization is important in the development of atrial fibrillation (AF), but no direct measurement is available in clinical medicine. OBJECTIVE: To determine whether the QT interval, a marker of ventricular repolarization, could be used to predict incident AF. METHODS: We examined a prolonged QT interval corrected by using the Framingham formula (QT(Fram)) as a predictor of incident AF in the Atherosclerosis Risk in Communities (ARIC) study. The Cardiovascular Health Study (CHS) and Health, Aging, and Body Composition (ABC) study were used for validation. Secondary predictors included QT duration as a continuous variable, a short QT interval, and QT intervals corrected by using other formulas. RESULTS: Among 14,538 ARIC study participants, a prolonged QT(Fram) predicted a roughly 2-fold increased risk of AF (hazard ratio [HR] 2.05; 95% confidence interval [CI] 1.42-2.96; P < .001). No substantive attenuation was observed after adjustment for age, race, sex, study center, body mass index, hypertension, diabetes, coronary disease, and heart failure. The findings were validated in Cardiovascular Health Study and Health, Aging, and Body Composition study and were similar across various QT correction methods. Also in the ARIC study, each 10-ms increase in QT(Fram) was associated with an increased unadjusted (HR 1.14; 95% CI 1.10-1.17; P < .001) and adjusted (HR 1.11; 95% CI 1.07-1.14; P < .001) risk of AF. Findings regarding a short QT interval were inconsistent across cohorts. CONCLUSIONS: A prolonged QT interval is associated with an increased risk of incident AF.
Keywords: Aged; Atrial Fibrillation; Cohort Studies; Electrocardiography; Female; Humans; Incidence; Long QT Syndrome; Male; Middle Aged; Risk Factors

Risk of venous thromboembolism associated with single and combined effects of Factor V Leiden, Prothrombin 20210A and Methylenetethraydrofolate reductase C677T: a meta-analysis involving over 11,000 cases and 21,000 controls. - Simone, Benedetto; De Stefano, Valerio; Leoncini, Emanuele; Zacho, Jeppe; Martinelli, Ida; Emmerich, Joseph; Rossi, Elena; Folsom, Aaron R; Almawi, Wassim Y; Scarabin, Pierre Y; den Heijer, Martin; Cushman, Mary; et al. (Eur J Epidemiol, 2013)
Genetic and environmental factors interact in determining the risk of venous thromboembolism (VTE). The risk associated with the polymorphic variants G1691A of factor V (Factor V Leiden, FVL), G20210A of prothrombin (PT20210A) and C677T of methylentetrahydrofolate reductase (C677T MTHFR) genes has been investigated in many studies. We performed a pooled analysis of case-control and cohort studies investigating in adults the association between each variant and VTE, published on Pubmed, Embase or Google through January 2010. Authors of eligible papers, were invited to provide all available individual data for the pooling. The Odds Ratio (OR) for first VTE associated with each variant, individually and combined with the others, were calculated with a random effect model, in heterozygotes and homozygotes (dominant model for FVL and PT20210A; recessive for C677T MTHFR). We analysed 31 databases, including 11,239 cases and 21,521 controls. No significant association with VTE was found for homozygous C677T MTHFR (OR: 1.38; 95 % confidence intervals [CI]: 0.98-1.93), whereas the risk was increased in carriers of either heterozygous FVL or PT20210 (OR = 4.22; 95 % CI: 3.35-5.32; and OR = 2.79;95 % CI: 2.25-3.46, respectively), in double heterozygotes (OR = 3.42; 95 %CI 1.64-7.13), and in homozygous FVL or PT20210A (OR = 11.45; 95 %CI: 6.79-19.29; and OR: 6.74 (CI 95 % 2.19-20.72), respectively). The stratified analyses showed a stronger effect of FVL on individuals ≤ 45 years (p value for interaction = 0.036) and of PT20210A in women using oral contraceptives (p-value for interaction = 0.045). In this large pooled analysis, inclusive of large studies like MEGA, no effect was found for C677T MTHFR on VTE; FVL and PT20210A were confirmed to be moderate risk factors. Notably, double carriers of the two genetic variants produced an impact on VTE risk significantly increased but weaker than previously thought.
Keywords: Case-Control Studies; Factor V; Genetic Predisposition to Disease; Humans; Methylenetetrahydrofolate Reductase (NADPH2); Prothrombin; Risk Factors; Venous Thromboembolism

Sex-stratified genome-wide association studies including 270,000 individuals show sexual dimorphism in genetic loci for anthropometric traits. - Randall, Joshua C; Winkler, Thomas W; Kutalik, Zoltán; Berndt, Sonja I; Jackson, Anne U; Monda, Keri L; Kilpeläinen, Tuomas O; Esko, Tõnu; Mägi, Reedik; Li, Shengxu; Workalemahu, Tsegaselassie; Feitosa, Mary F; et al. (PLoS Genet, 2013)
Given the anthropometric differences between men and women and previous evidence of sex-difference in genetic effects, we conducted a genome-wide search for sexually dimorphic associations with height, weight, body mass index, waist circumference, hip circumference, and waist-to-hip-ratio (133,723 individuals) and took forward 348 SNPs into follow-up (additional 137,052 individuals) in a total of 94 studies. Seven loci displayed significant sex-difference (FDR<5%), including four previously established (near GRB14/COBLL1, LYPLAL1/SLC30A10, VEGFA, ADAMTS9) and three novel anthropometric trait loci (near MAP3K1, HSD17B4, PPARG), all of which were genome-wide significant in women (P<5×10(-8)), but not in men. Sex-differences were apparent only for waist phenotypes, not for height, weight, BMI, or hip circumference. Moreover, we found no evidence for genetic effects with opposite directions in men versus women. The PPARG locus is of specific interest due to its role in diabetes genetics and therapy. Our results demonstrate the value of sex-specific GWAS to unravel the sexually dimorphic genetic underpinning of complex traits.
Keywords: Anthropometry; Body Height; Body Mass Index; Body Weight; Body Weights and Measures; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Sex Characteristics; Waist Circumference; Waist-Hip Ratio

Simple risk model predicts incidence of atrial fibrillation in a racially and geographically diverse population: the CHARGE-AF consortium. - Alonso, Alvaro; Krijthe, Bouwe P; Aspelund, Thor; Stepas, Katherine A; Pencina, Michael J; Moser, Carlee B; Sinner, Moritz F; Sotoodehnia, Nona; Fontes, João D; Janssens, A Cecile J W; Kronmal, Richard A; Magnani, Jared W; et al. (J Am Heart Assoc, 2013)
BACKGROUND: Tools for the prediction of atrial fibrillation (AF) may identify high-risk individuals more likely to benefit from preventive interventions and serve as a benchmark to test novel putative risk factors. METHODS AND RESULTS: Individual-level data from 3 large cohorts in the United States (Atherosclerosis Risk in Communities [ARIC] study, the Cardiovascular Health Study [CHS], and the Framingham Heart Study [FHS]), including 18 556 men and women aged 46 to 94 years (19% African Americans, 81% whites) were pooled to derive predictive models for AF using clinical variables. Validation of the derived models was performed in 7672 participants from the Age, Gene and Environment-Reykjavik study (AGES) and the Rotterdam Study (RS). The analysis included 1186 incident AF cases in the derivation cohorts and 585 in the validation cohorts. A simple 5-year predictive model including the variables age, race, height, weight, systolic and diastolic blood pressure, current smoking, use of antihypertensive medication, diabetes, and history of myocardial infarction and heart failure had good discrimination (C-statistic, 0.765; 95% CI, 0.748 to 0.781). Addition of variables from the electrocardiogram did not improve the overall model discrimination (C-statistic, 0.767; 95% CI, 0.750 to 0.783; categorical net reclassification improvement, -0.0032; 95% CI, -0.0178 to 0.0113). In the validation cohorts, discrimination was acceptable (AGES C-statistic, 0.664; 95% CI, 0.632 to 0.697 and RS C-statistic, 0.705; 95% CI, 0.664 to 0.747) and calibration was adequate. CONCLUSION: A risk model including variables readily available in primary care settings adequately predicted AF in diverse populations from the United States and Europe.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Atrial Fibrillation; Cohort Studies; Diabetes Mellitus; European Continental Ancestry Group; Female; Heart Failure; Humans; Hypertension; Iceland; Incidence; Male; Middle Aged; Myocardial Infarction; Netherlands; Proportional Hazards Models; Risk Assessment; Smoking; United States

Soluble CD14: genomewide association analysis and relationship to cardiovascular risk and mortality in older adults. - Reiner, Alex P; Lange, Ethan M; Jenny, Nancy S; Chaves, Paulo H M; Ellis, Jaclyn; Li, Jin; Walston, Jeremy; Lange, Leslie A; Cushman, Mary; Tracy, Russell P (Arterioscler Thromb Vasc Biol, 2013)
OBJECTIVE: CD14 is a glycosylphosphotidylinositol-anchored membrane glycoprotein expressed on neutrophils and monocytes/macrophages that also circulates as a soluble form (sCD14). Despite the well-recognized role of CD14 in inflammation, relatively little is known about the genetic determinants of sCD14 or the relationship of sCD14 to vascular- and aging-related phenotypes. METHODS AND RESULTS: We measured baseline levels of sCD14 in >5000 European-American and black adults aged 65 years and older from the Cardiovascular Health Study, who were well characterized at baseline for atherosclerotic risk factors and subclinical cardiovascular disease, and who have been followed for clinical cardiovascular disease and mortality outcomes up to 20 years. At baseline, sCD14 generally showed strong positive correlations with traditional cardio-metabolic risk factors and with subclinical measures of vascular disease such as carotid wall thickness and ankle-brachial index (independently of traditional cardiovascular disease risk factors), and was also inversely correlated with body mass index. In genomewide association analyses of sCD14, we (1) confirmed the importance of the CD14 locus on chromosome 5q21 in European-American; (2) identified a novel African ancestry-specific allele of CD14 associated with lower sCD14 in blacks; and (3) identified a putative novel association in European-American of a nonsynonymous variant of PIGC, which encodes an enzyme required for the first step in glycosylphosphotidylinositol anchor biosynthesis. Finally, we show that, like other acute phase inflammatory biomarkers, sCD14 predicts incident cardiovascular disease, and strongly and independently predicts all-cause mortality in older adults. CONCLUSIONS: CD14 independently predicts risk mortality in older adults.
Keywords: African Americans; Age Factors; Aged; Biomarkers; Cardiovascular Diseases; Chromosomes, Human, Pair 5; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Haplotypes; Hexosyltransferases; Humans; Incidence; Inflammation Mediators; Linear Models; Lipopolysaccharide Receptors; Logistic Models; Male; Membrane Proteins; Multivariate Analysis; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

A systematic mapping approach of 16q12.2/FTO and BMI in more than 20,000 African Americans narrows in on the underlying functional variation: results from the Population Architecture using Genomics and Epidemiology (PAGE) study. - Peters, Ulrike; North, Kari E; Sethupathy, Praveen; Buyske, Steve; Haessler, Jeff; Jiao, Shuo; Fesinmeyer, Megan D; Jackson, Rebecca D; Kuller, Lew H; Rajkovic, Aleksandar; Lim, Unhee; Cheng, Iona; et al. (PLoS Genet, 2013)
Genetic variants in intron 1 of the fat mass- and obesity-associated (FTO) gene have been consistently associated with body mass index (BMI) in Europeans. However, follow-up studies in African Americans (AA) have shown no support for some of the most consistently BMI-associated FTO index single nucleotide polymorphisms (SNPs). This is most likely explained by different race-specific linkage disequilibrium (LD) patterns and lower correlation overall in AA, which provides the opportunity to fine-map this region and narrow in on the functional variant. To comprehensively explore the 16q12.2/FTO locus and to search for second independent signals in the broader region, we fine-mapped a 646-kb region, encompassing the large FTO gene and the flanking gene RPGRIP1L by investigating a total of 3,756 variants (1,529 genotyped and 2,227 imputed variants) in 20,488 AAs across five studies. We observed associations between BMI and variants in the known FTO intron 1 locus: the SNP with the most significant p-value, rs56137030 (8.3 × 10(-6)) had not been highlighted in previous studies. While rs56137030was correlated at r(2)>0.5 with 103 SNPs in Europeans (including the GWAS index SNPs), this number was reduced to 28 SNPs in AA. Among rs56137030 and the 28 correlated SNPs, six were located within candidate intronic regulatory elements, including rs1421085, for which we predicted allele-specific binding affinity for the transcription factor CUX1, which has recently been implicated in the regulation of FTO. We did not find strong evidence for a second independent signal in the broader region. In summary, this large fine-mapping study in AA has substantially reduced the number of common alleles that are likely to be functional candidates of the known FTO locus. Importantly our study demonstrated that comprehensive fine-mapping in AA provides a powerful approach to narrow in on the functional candidate(s) underlying the initial GWAS findings in European populations.
Keywords: Adaptor Proteins, Signal Transducing; Adult; African Americans; Aged; Aged, 80 and over; Alleles; Body Mass Index; Chromosome Mapping; Continental Population Groups; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Metagenomics; Middle Aged; Obesity; Proteins

Trans-ethnic fine-mapping of lipid loci identifies population-specific signals and allelic heterogeneity that increases the trait variance explained. - Wu, Ying; Waite, Lindsay L; Jackson, Anne U; Sheu, Wayne H-H; Buyske, Steven; Absher, Devin; Arnett, Donna K; Boerwinkle, Eric; Bonnycastle, Lori L; Carty, Cara L; Cheng, Iona; Cochran, Barbara; et al. (PLoS Genet, 2013)
Genome-wide association studies (GWAS) have identified ~100 loci associated with blood lipid levels, but much of the trait heritability remains unexplained, and at most loci the identities of the trait-influencing variants remain unknown. We conducted a trans-ethnic fine-mapping study at 18, 22, and 18 GWAS loci on the Metabochip for their association with triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C), respectively, in individuals of African American (n = 6,832), East Asian (n = 9,449), and European (n = 10,829) ancestry. We aimed to identify the variants with strongest association at each locus, identify additional and population-specific signals, refine association signals, and assess the relative significance of previously described functional variants. Among the 58 loci, 33 exhibited evidence of association at P<1 × 10(-4) in at least one ancestry group. Sequential conditional analyses revealed that ten, nine, and four loci in African Americans, Europeans, and East Asians, respectively, exhibited two or more signals. At these loci, accounting for all signals led to a 1.3- to 1.8-fold increase in the explained phenotypic variance compared to the strongest signals. Distinct signals across ancestry groups were identified at PCSK9 and APOA5. Trans-ethnic analyses narrowed the signals to smaller sets of variants at GCKR, PPP1R3B, ABO, LCAT, and ABCA1. Of 27 variants reported previously to have functional effects, 74% exhibited the strongest association at the respective signal. In conclusion, trans-ethnic high-density genotyping and analysis confirm the presence of allelic heterogeneity, allow the identification of population-specific variants, and limit the number of candidate SNPs for functional studies.
Keywords: African Americans; Apolipoproteins A; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Genome-Wide Association Study; Humans; Lipoproteins, HDL; Lipoproteins, LDL; Proprotein Convertases; Serine Endopeptidases; Triglycerides

Association Between 6-Minute Walk Test and All-Cause Mortality, Coronary Heart Disease-Specific Mortality, and Incident Coronary Heart Disease. - Yazdanyar, Ali; Aziz, Michael M; Enright, Paul L; Edmundowicz, Daniel; Boudreau, Robert; Sutton-Tyrell, Kim; Kuller, Lewis; Newman, Anne B (J Aging Health, 2014)
OBJECTIVE: To examine the association between 6-min walk test (6 MWT) performance and all-cause mortality, coronary heart disease mortality, and incident coronary heart disease in older adults. METHOD: We conducted a time-to-event analysis of 1,665 Cardiovascular Health Study participants without prevalent cardiovascular disease with a 6 MWT. RESULTS: During a mean follow-up of 8 years, there were 305 incident coronary heart disease events, and 504 deaths of which 100 were coronary heart disease-related deaths. The 6 MWT performance in the shortest two distance quintiles was associated with increased risk of all-cause mortality (290-338 m: hazard ratio [HR] = 1.7; 95% confidence interval [CI] = [1.2, 2.5]; <290 m: HR = 2.1; 95% CI = [1.4, 3.0]). The adjusted risk of coronary heart disease mortality incident events among those with a 6 MWT < 290 m was not significant. DISCUSSION: Performance on the 6 MWT is independently associated with all-cause mortality and is of prognostic utility in community-dwelling older adults.

Association between alcohol and cardiovascular disease: Mendelian randomisation analysis based on individual participant data. - Holmes, Michael V; Dale, Caroline E; Zuccolo, Luisa; Silverwood, Richard J; Guo, Yiran; Ye, Zheng; Prieto-Merino, David; Dehghan, Abbas; Trompet, Stella; Wong, Andrew; Cavadino, Alana; Drogan, Dagmar; et al. (BMJ, 2014)
OBJECTIVE: To use the rs1229984 variant in the alcohol dehydrogenase 1B gene (ADH1B) as an instrument to investigate the causal role of alcohol in cardiovascular disease. DESIGN: Mendelian randomisation meta-analysis of 56 epidemiological studies. PARTICIPANTS: 261 991 individuals of European descent, including 20 259 coronary heart disease cases and 10 164 stroke events. Data were available on ADH1B rs1229984 variant, alcohol phenotypes, and cardiovascular biomarkers. MAIN OUTCOME MEASURES: Odds ratio for coronary heart disease and stroke associated with the ADH1B variant in all individuals and by categories of alcohol consumption. RESULTS: Carriers of the A-allele of ADH1B rs1229984 consumed 17.2% fewer units of alcohol per week (95% confidence interval 15.6% to 18.9%), had a lower prevalence of binge drinking (odds ratio 0.78 (95% CI 0.73 to 0.84)), and had higher abstention (odds ratio 1.27 (1.21 to 1.34)) than non-carriers. Rs1229984 A-allele carriers had lower systolic blood pressure (-0.88 (-1.19 to -0.56) mm Hg), interleukin-6 levels (-5.2% (-7.8 to -2.4%)), waist circumference (-0.3 (-0.6 to -0.1) cm), and body mass index (-0.17 (-0.24 to -0.10) kg/m(2)). Rs1229984 A-allele carriers had lower odds of coronary heart disease (odds ratio 0.90 (0.84 to 0.96)). The protective association of the ADH1B rs1229984 A-allele variant remained the same across all categories of alcohol consumption (P=0.83 for heterogeneity). Although no association of rs1229984 was identified with the combined subtypes of stroke, carriers of the A-allele had lower odds of ischaemic stroke (odds ratio 0.83 (0.72 to 0.95)). CONCLUSIONS: Individuals with a genetic variant associated with non-drinking and lower alcohol consumption had a more favourable cardiovascular profile and a reduced risk of coronary heart disease than those without the genetic variant. This suggests that reduction of alcohol consumption, even for light to moderate drinkers, is beneficial for cardiovascular health.
Keywords: Adult; Aged; Alcohol Dehydrogenase; Alcohol Drinking; Biomarkers; Coronary Disease; Female; Genetic Markers; Genotype; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Models, Statistical; Polymorphism, Single Nucleotide; Stroke

Association of low-frequency and rare coding-sequence variants with blood lipids and coronary heart disease in 56,000 whites and blacks. - Peloso, Gina M; Auer, Paul L; Bis, Joshua C; Voorman, Arend; Morrison, Alanna C; Stitziel, Nathan O; Brody, Jennifer A; Khetarpal, Sumeet A; Crosby, Jacy R; Fornage, Myriam; Isaacs, Aaron; Jakobsdottir, Johanna; et al. (Am J Hum Genet, 2014)
Low-frequency coding DNA sequence variants in the proprotein convertase subtilisin/kexin type 9 gene (PCSK9) lower plasma low-density lipoprotein cholesterol (LDL-C), protect against risk of coronary heart disease (CHD), and have prompted the development of a new class of therapeutics. It is uncertain whether the PCSK9 example represents a paradigm or an isolated exception. We used the "Exome Array" to genotype >200,000 low-frequency and rare coding sequence variants across the genome in 56,538 individuals (42,208 European ancestry [EA] and 14,330 African ancestry [AA]) and tested these variants for association with LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. Although we did not identify new genes associated with LDL-C, we did identify four low-frequency (frequencies between 0.1% and 2%) variants (ANGPTL8 rs145464906 [c.361C>T; p.Gln121*], PAFAH1B2 rs186808413 [c.482C>T; p.Ser161Leu], COL18A1 rs114139997 [c.331G>A; p.Gly111Arg], and PCSK7 rs142953140 [c.1511G>A; p.Arg504His]) with large effects on HDL-C and/or triglycerides. None of these four variants was associated with risk for CHD, suggesting that examples of low-frequency coding variants with robust effects on both lipids and CHD will be limited.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Adult; African Continental Ancestry Group; Aged; Alleles; Animals; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Association Studies; Genetic Code; Genetic Variation; Humans; Linear Models; Male; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Middle Aged; Phenotype; Sequence Analysis, DNA; Subtilisins; Triglycerides

B-type natriuretic peptide and C-reactive protein in the prediction of atrial fibrillation risk: the CHARGE-AF Consortium of community-based cohort studies. - Sinner, Moritz F; Stepas, Katherine A; Moser, Carlee B; Krijthe, Bouwe P; Aspelund, Thor; Sotoodehnia, Nona; Fontes, João D; Janssens, A Cecile J W; Kronmal, Richard A; Magnani, Jared W; Witteman, Jacqueline C; Chamberlain, Alanna M; et al. (Europace, 2014)
AIMS: B-type natriuretic peptide (BNP) and C-reactive protein (CRP) predict atrial fibrillation (AF) risk. However, their risk stratification abilities in the broad community remain uncertain. We sought to improve risk stratification for AF using biomarker information. METHODS AND RESULTS: We ascertained AF incidence in 18 556 Whites and African Americans from the Atherosclerosis Risk in Communities Study (ARIC, n=10 675), Cardiovascular Health Study (CHS, n = 5043), and Framingham Heart Study (FHS, n = 2838), followed for 5 years (prediction horizon). We added BNP (ARIC/CHS: N-terminal pro-B-type natriuretic peptide; FHS: BNP), CRP, or both to a previously reported AF risk score, and assessed model calibration and predictive ability [C-statistic, integrated discrimination improvement (IDI), and net reclassification improvement (NRI)]. We replicated models in two independent European cohorts: Age, Gene/Environment Susceptibility Reykjavik Study (AGES), n = 4467; Rotterdam Study (RS), n = 3203. B-type natriuretic peptide and CRP were significantly associated with AF incidence (n = 1186): hazard ratio per 1-SD ln-transformed biomarker 1.66 [95% confidence interval (CI), 1.56-1.76], P < 0.0001 and 1.18 (95% CI, 1.11-1.25), P < 0.0001, respectively. Model calibration was sufficient (BNP, χ(2) = 17.0; CRP, χ(2) = 10.5; BNP and CRP, χ(2) = 13.1). B-type natriuretic peptide improved the C-statistic from 0.765 to 0.790, yielded an IDI of 0.027 (95% CI, 0.022-0.032), a relative IDI of 41.5%, and a continuous NRI of 0.389 (95% CI, 0.322-0.455). The predictive ability of CRP was limited (C-statistic increment 0.003). B-type natriuretic peptide consistently improved prediction in AGES and RS. CONCLUSION: B-type natriuretic peptide, not CRP, substantially improved AF risk prediction beyond clinical factors in an independently replicated, heterogeneous population. B-type natriuretic peptide may serve as a benchmark to evaluate novel putative AF risk biomarkers.
Keywords: Aged; Atrial Fibrillation; Biomarkers; C-Reactive Protein; Europe; Female; Humans; Incidence; Male; Natriuretic Peptide, Brain; Peptide Fragments; Predictive Value of Tests; Risk Assessment; Risk Factors; United States

Common carotid intima-media thickness measurements do not improve cardiovascular risk prediction in individuals with elevated blood pressure: the USE-IMT collaboration. - Bots, Michiel L; Groenewegen, Karlijn A; Anderson, Todd J; Britton, Annie R; Dekker, Jacqueline M; Engström, Gunnar; Evans, Greg W; de Graaf, Jacqueline; Grobbee, Diederick E; Hedblad, Bo; Hofman, Albert; Holewijn, Suzanne; et al. (Hypertension, 2014)
Carotid intima-media thickness (CIMT) is a marker of cardiovascular risk. It is unclear whether measurement of mean common CIMT improves 10-year risk prediction of first-time myocardial infarction or stroke in individuals with elevated blood pressure. We performed an analysis among individuals with elevated blood pressure (i.e., a systolic blood pressure ≥140 mm Hg and a diastolic blood pressure ≥ 90 mm Hg) in USE-IMT, a large ongoing individual participant data meta-analysis. We refitted the risk factors of the Framingham Risk Score on asymptomatic individuals (baseline model) and expanded this model with mean common CIMT (CIMT model) measurements. From both models, 10-year risks to develop a myocardial infarction or stroke were estimated. In individuals with elevated blood pressure, we compared discrimination and calibration of the 2 models and calculated the net reclassification improvement (NRI). We included 17 254 individuals with elevated blood pressure from 16 studies. During a median follow-up of 9.9 years, 2014 first-time myocardial infarctions or strokes occurred. The C-statistics of the baseline and CIMT models were similar (0.73). NRI with the addition of mean common CIMT was small and not significant (1.4%; 95% confidence intervals, -1.1 to 3.7). In those at intermediate risk (n=5008, 10-year absolute risk of 10% to 20%), the NRI was 5.6% (95% confidence intervals, 1.6-10.4). There is no added value of measurement of mean common CIMT in individuals with elevated blood pressure for improving cardiovascular risk prediction. For those at intermediate risk, the addition of mean common CIMT to an existing cardiovascular risk score is small but statistically significant.
Keywords: Adult; Aged; Antihypertensive Agents; Blood Pressure; Cardiovascular Diseases; Carotid Artery, Common; Carotid Intima-Media Thickness; Cohort Studies; Female; Humans; Hypertension; Male; Meta-Analysis as Topic; Middle Aged; Risk Assessment; Risk Factors

Common variation in fatty acid metabolic genes and risk of incident sudden cardiac arrest. - Lemaitre, Rozenn N; Johnson, Catherine O; Hesselson, Stephanie; Sotoodehnia, Nona; Sotoodhenia, Nona; McKnight, Barbara; Sitlani, Colleen M; Rea, Thomas D; King, Irena B; Kwok, Pui-Yan; Mak, Angel; Li, Guo; et al. (Heart Rhythm, 2014)
BACKGROUND: There is limited information on genetic factors associated with sudden cardiac arrest (SCA). OBJECTIVE: To assess the association of common variation in genes in fatty acid pathways with SCA risk. METHODS: We selected 85 candidate genes and 1155 single nucleotide polymorphisms (SNPs) tagging common variation in each gene. We investigated the SNP associations with SCA in a population-based case-control study. Cases (n = 2160) were from a repository of SCA in the greater Seattle area. Controls (n = 2615), frequency-matched on age and sex, were from the same area. We used linear logistic regression to examine SNP associations with SCA. We performed permutation-based p-min tests to account for multiple comparisons within each gene. The SNP associations with a corrected P value of <.05 were then examined in a meta-analysis of these SNP associations in 9 replication studies totaling 2129 SCA cases and 23,833 noncases. RESULTS: Eight SNPs in or near 8 genes were associated with SCA risk in the discovery study, one of which was nominally significant in the replication phase (rs7737692, minor allele frequency 36%, near the LPCAT1 gene). For each copy of the minor allele, rs7737692 was associated with 13% lower SCA risk (95% confidence interval -21% to -5%) in the discovery phase and 9% lower SCA risk (95% confidence interval -16% to -1%) in the replication phase. CONCLUSIONS: While none of the associations reached significance with Bonferroni correction, a common genetic variant near LPCAT1, a gene involved in the remodeling of phospholipids, was nominally associated with incident SCA risk. Further study is needed to validate this observation.
Keywords: 1-Acylglycerophosphocholine O-Acyltransferase; Aged; Algorithms; Alleles; Case-Control Studies; Death, Sudden, Cardiac; Fatty Acids; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Male; Polymorphism, Single Nucleotide; Risk Factors

Disability and recovery of independent function in obstructive lung disease: the cardiovascular health study. - Fan, Vincent S; Locke, Emily R; Diehr, Paula; Wilsdon, Anthony; Enright, Paul; Yende, Sachin; Avdalovic, Mark; Barr, Graham; Kapur, Vishesh K; Thomas, Rachel; Krishnan, Jerry A; Lovasi, Gina; et al. (Respiration, 2014)
BACKGROUND: Chronic obstructive lung disease frequently leads to disability. Older patients may experience transitions between states of disability and independence over time. OBJECTIVE: To identify factors associated with transition between states of disability and independent function in obstructive lung disease. METHODS: We analyzed data on 4,394 participants in the Cardiovascular Health Study who completed prebronchodilator spirometry. We calculated the 1-year probability of developing and resolving impairment in ≥1 instrumental activity of daily living (IADL) or ≥1 activity of daily living (ADL) using transition probability analysis. We identified factors associated with resolving disability using relative risk (RR) regression. RESULTS: The prevalence of IADL impairment was higher with moderate (23.9%) and severe (36.9%) airflow obstruction compared to normal spirometry (22.5%; p < 0.001). Among participants with severe airflow obstruction, 23.5% recovered independence in IADLs and 40.5% recovered independence in ADLs. In the adjusted analyses, airflow obstruction predicted the development of IADL, but not ADL impairment. Participants with severe airflow obstruction were less likely to resolve IADL impairment [RR 0.67 and 95% confidence interval (CI) 0.49-0.94]. Compared to the most active individuals (i.e. who walked ≥28 blocks per week), walking less was associated with a decreased likelihood of resolving IADL impairment (7-27 blocks: RR 0.81 and 95% CI 0.69-0.86 and <7 blocks: RR 0.73 and 95% CI 0.61-0.86). Increased strength (RR 1.16 and 95% CI 1.05-1.29) was associated with resolving IADL impairment. CONCLUSIONS: Disability is common in older people, especially in those with severe airflow obstruction. Increased physical activity and muscle strength are associated with recovery. Research is needed on interventions to improve these factors among patients with obstructive lung disease and disability.
Keywords: Activities of Daily Living; Aged; Cardiac Rehabilitation; Cardiovascular Diseases; Disability Evaluation; Exercise Test; Female; Humans; Independent Living; Longitudinal Studies; Male; Motor Activity; Muscle Strength; Outcome Assessment (Health Care); Pulmonary Disease, Chronic Obstructive; Recovery of Function; Risk Assessment; Severity of Illness Index; Spirometry; United States

Drug-gene interactions and the search for missing heritability: a cross-sectional pharmacogenomics study of the QT interval. - Avery, C L; Sitlani, C M; Arking, D E; Arnett, D K; Bis, J C; Boerwinkle, E; Buckley, B M; Ida Chen, Y-D; de Craen, A J M; Eijgelsheim, M; Enquobahrie, D; Evans, D S; et al. (Pharmacogenomics J, 2014)
Variability in response to drug use is common and heritable, suggesting that genome-wide pharmacogenomics studies may help explain the 'missing heritability' of complex traits. Here, we describe four independent analyses in 33 781 participants of European ancestry from 10 cohorts that were designed to identify genetic variants modifying the effects of drugs on QT interval duration (QT). Each analysis cross-sectionally examined four therapeutic classes: thiazide diuretics (prevalence of use=13.0%), tri/tetracyclic antidepressants (2.6%), sulfonylurea hypoglycemic agents (2.9%) and QT-prolonging drugs as classified by the University of Arizona Center for Education and Research on Therapeutics (4.4%). Drug-gene interactions were estimated using covariable-adjusted linear regression and results were combined with fixed-effects meta-analysis. Although drug-single-nucleotide polymorphism (SNP) interactions were biologically plausible and variables were well-measured, findings from the four cross-sectional meta-analyses were null (Pinteraction>5.0 × 10(-8)). Simulations suggested that additional efforts, including longitudinal modeling to increase statistical power, are likely needed to identify potentially important pharmacogenomic effects.
Keywords: Computer Simulation; Cross-Sectional Studies; Drug-Related Side Effects and Adverse Reactions; Electrocardiography; European Continental Ancestry Group; Gene-Environment Interaction; Genome-Wide Association Study; Humans; Linear Models; Long QT Syndrome; Markov Chains; Pharmacogenetics; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Effects of long-term averaging of quantitative blood pressure traits on the detection of genetic associations. - Ganesh, Santhi K; Chasman, Daniel I; Larson, Martin G; Guo, Xiuqing; Verwoert, Germain; Bis, Joshua C; Gu, Xiangjun; Smith, Albert V; Yang, Min-Lee; Zhang, Yan; Ehret, Georg; Rose, Lynda M; et al. (Am J Hum Genet, 2014)
Blood pressure (BP) is a heritable, quantitative trait with intraindividual variability and susceptibility to measurement error. Genetic studies of BP generally use single-visit measurements and thus cannot remove variability occurring over months or years. We leveraged the idea that averaging BP measured across time would improve phenotypic accuracy and thereby increase statistical power to detect genetic associations. We studied systolic BP (SBP), diastolic BP (DBP), mean arterial pressure (MAP), and pulse pressure (PP) averaged over multiple years in 46,629 individuals of European ancestry. We identified 39 trait-variant associations across 19 independent loci (p < 5 × 10(-8)); five associations (in four loci) uniquely identified by our LTA analyses included those of SBP and MAP at 2p23 (rs1275988, near KCNK3), DBP at 2q11.2 (rs7599598, in FER1L5), and PP at 6p21 (rs10948071, near CRIP3) and 7p13 (rs2949837, near IGFBP3). Replication analyses conducted in cohorts with single-visit BP data showed positive replication of associations and a nominal association (p < 0.05). We estimated a 20% gain in statistical power with long-term average (LTA) as compared to single-visit BP association studies. Using LTA analysis, we identified genetic loci influencing BP. LTA might be one way of increasing the power of genetic associations for continuous traits in extant samples for other phenotypes that are measured serially over time.
Keywords: Blood Pressure; Genome-Wide Association Study; Humans; Longitudinal Studies; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

FTO genetic variants, dietary intake and body mass index: insights from 177,330 individuals. - Qi, Qibin; Kilpeläinen, Tuomas O; Downer, Mary K; Tanaka, Toshiko; Smith, Caren E; Sluijs, Ivonne; Sonestedt, Emily; Chu, Audrey Y; Renstrom, Frida; Lin, Xiaochen; Ängquist, Lars H; Huang, Jinyan; et al. (Hum Mol Genet, 2014)
FTO is the strongest known genetic susceptibility locus for obesity. Experimental studies in animals suggest the potential roles of FTO in regulating food intake. The interactive relation among FTO variants, dietary intake and body mass index (BMI) is complex and results from previous often small-scale studies in humans are highly inconsistent. We performed large-scale analyses based on data from 177,330 adults (154 439 Whites, 5776 African Americans and 17 115 Asians) from 40 studies to examine: (i) the association between the FTO-rs9939609 variant (or a proxy single-nucleotide polymorphism) and total energy and macronutrient intake and (ii) the interaction between the FTO variant and dietary intake on BMI. The minor allele (A-allele) of the FTO-rs9939609 variant was associated with higher BMI in Whites (effect per allele = 0.34 [0.31, 0.37] kg/m(2), P = 1.9 × 10(-105)), and all participants (0.30 [0.30, 0.35] kg/m(2), P = 3.6 × 10(-107)). The BMI-increasing allele of the FTO variant showed a significant association with higher dietary protein intake (effect per allele = 0.08 [0.06, 0.10] %, P = 2.4 × 10(-16)), and relative weak associations with lower total energy intake (-6.4 [-10.1, -2.6] kcal/day, P = 0.001) and lower dietary carbohydrate intake (-0.07 [-0.11, -0.02] %, P = 0.004). The associations with protein (P = 7.5 × 10(-9)) and total energy (P = 0.002) were attenuated but remained significant after adjustment for BMI. We did not find significant interactions between the FTO variant and dietary intake of total energy, protein, carbohydrate or fat on BMI. Our findings suggest a positive association between the BMI-increasing allele of FTO variant and higher dietary protein intake and offer insight into potential link between FTO, dietary protein intake and adiposity.
Keywords: Adult; African Americans; Aged; Alleles; Asian Continental Ancestry Group; Body Mass Index; Dietary Carbohydrates; Dietary Fats; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Female; Gene Frequency; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins

Gene expression in thiazide diuretic or statin users in relation to incident type 2 diabetes. - Suchy-Dicey, Astrid; Heckbert, Susan R; Smith, Nicholas L; McKnight, Barbara; Rotter, Jerome I; Chen, Yd Ida; Psaty, Bruce M; Enquobahrie, Daniel A (Int J Mol Epidemiol Genet, 2014)
Thiazide diuretics and statins are used to improve cardiovascular outcomes, but may also cause type 2 diabetes (T2DM), although mechanisms are unknown. Gene expression studies may facilitate understanding of these associations. Participants from ongoing population-based studies were sampled for these longitudinal studies of peripheral blood microarray gene expression, and followed to incident diabetes. All sampled subjects were statin or thiazide users. Those who developed diabetes during follow-up comprised cases (44 thiazide users; 19 statin users), and were matched to drug-using controls who did not develop diabetes on several factors. Supervised normalization, surrogate variable analyses removed technical bias and confounding. Differentially-expressed genes were those with a false discovery rate Q-value<0.05. Among thiazide users, diabetes cases had significantly different expression of CCL14 (down-regulated 6%, Q-value=0.0257), compared with controls. Among statin users, diabetes cases had marginal but insignificantly different expression of ZNF532 (up-regulated 15%, Q-value=0.0584), CXORF21 (up-regulated 11%, Q-value=0.0584), and ZNHIT3 (up-regulated 19%, Q-value=0.0959), compared with controls. These genes comprise potential targets for future expression or mechanistic research on medication-related diabetes development.

Gene-age interactions in blood pressure regulation: a large-scale investigation with the CHARGE, Global BPgen, and ICBP Consortia. - Simino, Jeannette; Shi, Gang; Bis, Joshua C; Chasman, Daniel I; Ehret, Georg B; Gu, Xiangjun; Guo, Xiuqing; Hwang, Shih-Jen; Sijbrands, Eric; Smith, Albert V; Verwoert, Germaine C; Bragg-Gresham, Jennifer L; et al. (Am J Hum Genet, 2014)
Although age-dependent effects on blood pressure (BP) have been reported, they have not been systematically investigated in large-scale genome-wide association studies (GWASs). We leveraged the infrastructure of three well-established consortia (CHARGE, GBPgen, and ICBP) and a nonstandard approach (age stratification and metaregression) to conduct a genome-wide search of common variants with age-dependent effects on systolic (SBP), diastolic (DBP), mean arterial (MAP), and pulse (PP) pressure. In a two-staged design using 99,241 individuals of European ancestry, we identified 20 genome-wide significant (p ≤ 5 × 10(-8)) loci by using joint tests of the SNP main effect and SNP-age interaction. Nine of the significant loci demonstrated nominal evidence of age-dependent effects on BP by tests of the interactions alone. Index SNPs in the EHBP1L1 (DBP and MAP), CASZ1 (SBP and MAP), and GOSR2 (PP) loci exhibited the largest age interactions, with opposite directions of effect in the young versus the old. The changes in the genetic effects over time were small but nonnegligible (up to 1.58 mm Hg over 60 years). The EHBP1L1 locus was discovered through gene-age interactions only in whites but had DBP main effects replicated (p = 8.3 × 10(-4)) in 8,682 Asians from Singapore, indicating potential interethnic heterogeneity. A secondary analysis revealed 22 loci with evidence of age-specific effects (e.g., only in 20 to 29-year-olds). Age can be used to select samples with larger genetic effect sizes and more homogenous phenotypes, which may increase statistical power. Age-dependent effects identified through novel statistical approaches can provide insight into the biology and temporal regulation underlying BP associations.
Keywords: Adolescent; Adult; Age Factors; Aged; Blood Pressure; Cohort Studies; Humans; Middle Aged; Young Adult

Gene-centric meta-analyses for central adiposity traits in up to 57 412 individuals of European descent confirm known loci and reveal several novel associations. - Yoneyama, Sachiko; Guo, Yiran; Lanktree, Matthew B; Barnes, Michael R; Elbers, Clara C; Karczewski, Konrad J; Padmanabhan, Sandosh; Bauer, Florianne; Baumert, Jens; Beitelshees, Amber; Berenson, Gerald S; Boer, Jolanda M A; et al. (Hum Mol Genet, 2014)
Waist circumference (WC) and waist-to-hip ratio (WHR) are surrogate measures of central adiposity that are associated with adverse cardiovascular events, type 2 diabetes and cancer independent of body mass index (BMI). WC and WHR are highly heritable with multiple susceptibility loci identified to date. We assessed the association between SNPs and BMI-adjusted WC and WHR and unadjusted WC in up to 57 412 individuals of European descent from 22 cohorts collaborating with the NHLBI's Candidate Gene Association Resource (CARe) project. The study population consisted of women and men aged 20-80 years. Study participants were genotyped using the ITMAT/Broad/CARE array, which includes ∼50 000 cosmopolitan tagged SNPs across ∼2100 cardiovascular-related genes. Each trait was modeled as a function of age, study site and principal components to control for population stratification, and we conducted a fixed-effects meta-analysis. No new loci for WC were observed. For WHR analyses, three novel loci were significantly associated (P < 2.4 × 10(-6)). Previously unreported rs2811337-G near TMCC1 was associated with increased WHR (β ± SE, 0.048 ± 0.008, P = 7.7 × 10(-9)) as was rs7302703-G in HOXC10 (β = 0.044 ± 0.008, P = 2.9 × 10(-7)) and rs936108-C in PEMT (β = 0.035 ± 0.007, P = 1.9 × 10(-6)). Sex-stratified analyses revealed two additional novel signals among females only, rs12076073-A in SHC1 (β = 0.10 ± 0.02, P = 1.9 × 10(-6)) and rs1037575-A in ATBDB4 (β = 0.046 ± 0.01, P = 2.2 × 10(-6)), supporting an already established sexual dimorphism of central adiposity-related genetic variants. Functional analysis using ENCODE and eQTL databases revealed that several of these loci are in regulatory regions or regions with differential expression in adipose tissue.
Keywords: Adiposity; Adult; Aged; Aged, 80 and over; Body Mass Index; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Waist Circumference; Waist-Hip Ratio; Young Adult

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genetic diversity is a predictor of mortality in humans. - Bihlmeyer, Nathan A; Brody, Jennifer A; Smith, Albert Vernon; Lunetta, Kathryn L; Nalls, Mike; Smith, Jennifer A; Tanaka, Toshiko; Davies, Gail; Yu, Lei; Mirza, Saira Saeed; Teumer, Alexander; Coresh, Josef; et al. (BMC Genet, 2014)
BACKGROUND: It has been well-established, both by population genetics theory and direct observation in many organisms, that increased genetic diversity provides a survival advantage. However, given the limitations of both sample size and genome-wide metrics, this hypothesis has not been comprehensively tested in human populations. Moreover, the presence of numerous segregating small effect alleles that influence traits that directly impact health directly raises the question as to whether global measures of genomic variation are themselves associated with human health and disease. RESULTS: We performed a meta-analysis of 17 cohorts followed prospectively, with a combined sample size of 46,716 individuals, including a total of 15,234 deaths. We find a significant association between increased heterozygosity and survival (P = 0.03). We estimate that within a single population, every standard deviation of heterozygosity an individual has over the mean decreases that person's risk of death by 1.57%. CONCLUSIONS: This effect was consistent between European and African ancestry cohorts, men and women, and major causes of death (cancer and cardiovascular disease), demonstrating the broad positive impact of genomic diversity on human survival.
Keywords: Genome-Wide Association Study; Heterozygote; Humans; Mortality; Polymorphism, Single Nucleotide; Proportional Hazards Models

Gene-wide analysis detects two new susceptibility genes for Alzheimer's disease. - Escott-Price, Valentina; Bellenguez, Céline; Wang, Li-San; Choi, Seung-Hoan; Harold, Denise; Jones, Lesley; Holmans, Peter; Gerrish, Amy; Vedernikov, Alexey; Richards, Alexander; DeStefano, Anita L; Lambert, Jean-Charles; et al. (PLoS One, 2014)
BACKGROUND: Alzheimer's disease is a common debilitating dementia with known heritability, for which 20 late onset susceptibility loci have been identified, but more remain to be discovered. This study sought to identify new susceptibility genes, using an alternative gene-wide analytical approach which tests for patterns of association within genes, in the powerful genome-wide association dataset of the International Genomics of Alzheimer's Project Consortium, comprising over 7 m genotypes from 25,580 Alzheimer's cases and 48,466 controls. PRINCIPAL FINDINGS: In addition to earlier reported genes, we detected genome-wide significant loci on chromosomes 8 (TP53INP1, p = 1.4×10-6) and 14 (IGHV1-67 p = 7.9×10-8) which indexed novel susceptibility loci. SIGNIFICANCE: The additional genes identified in this study, have an array of functions previously implicated in Alzheimer's disease, including aspects of energy metabolism, protein degradation and the immune system and add further weight to these pathways as potential therapeutic targets in Alzheimer's disease.
Keywords: Alzheimer Disease; Carrier Proteins; Case-Control Studies; Genome-Wide Association Study; Heat-Shock Proteins; Humans; Polymorphism, Single Nucleotide; Receptors, Antigen, B-Cell

Genome-wide association analysis identifies six new loci associated with forced vital capacity. - Loth, Daan W; Soler Artigas, Maria; Gharib, Sina A; Wain, Louise V; Franceschini, Nora; Koch, Beate; Pottinger, Tess D; Smith, Albert Vernon; Duan, Qing; Oldmeadow, Chris; Lee, Mi Kyeong; Strachan, David P; et al. (Nat Genet, 2014)
Forced vital capacity (FVC), a spirometric measure of pulmonary function, reflects lung volume and is used to diagnose and monitor lung diseases. We performed genome-wide association study meta-analysis of FVC in 52,253 individuals from 26 studies and followed up the top associations in 32,917 additional individuals of European ancestry. We found six new regions associated at genome-wide significance (P < 5 × 10(-8)) with FVC in or near EFEMP1, BMP6, MIR129-2-HSD17B12, PRDM11, WWOX and KCNJ2. Two loci previously associated with spirometric measures (GSTCD and PTCH1) were related to FVC. Newly implicated regions were followed up in samples from African-American, Korean, Chinese and Hispanic individuals. We detected transcripts for all six newly implicated genes in human lung tissue. The new loci may inform mechanisms involved in lung development and the pathogenesis of restrictive lung disease.
Keywords: Cohort Studies; Databases, Genetic; Follow-Up Studies; Forced Expiratory Volume; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Lung Diseases; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Prognosis; Quantitative Trait Loci; Respiratory Function Tests; Spirometry; Vital Capacity

Genome-wide association study for circulating tissue plasminogen activator levels and functional follow-up implicates endothelial STXBP5 and STX2. - Huang, Jie; Huffman, Jennifer E; Yamakuchi, Munekazu; Yamkauchi, Munekazu; Trompet, Stella; Asselbergs, Folkert W; Sabater-Lleal, Maria; Trégouët, David-Alexandre; Chen, Wei-Min; Smith, Nicholas L; Kleber, Marcus E; Shin, So-Youn; et al. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: Tissue plasminogen activator (tPA), a serine protease, catalyzes the conversion of plasminogen to plasmin, the major enzyme responsible for endogenous fibrinolysis. In some populations, elevated plasma levels of tPA have been associated with myocardial infarction and other cardiovascular diseases. We conducted a meta-analysis of genome-wide association studies to identify novel correlates of circulating levels of tPA. APPROACH AND RESULTS: Fourteen cohort studies with tPA measures (N=26 929) contributed to the meta-analysis. Three loci were significantly associated with circulating tPA levels (P<5.0×10(-8)). The first locus is on 6q24.3, with the lead single nucleotide polymorphism (SNP; rs9399599; P=2.9×10(-14)) within STXBP5. The second locus is on 8p11.21. The lead SNP (rs3136739; P=1.3×10(-9)) is intronic to POLB and <200 kb away from the tPA encoding the gene PLAT. We identified a nonsynonymous SNP (rs2020921) in modest linkage disequilibrium with rs3136739 (r(2)=0.50) within exon 5 of PLAT (P=2.0×10(-8)). The third locus is on 12q24.33, with the lead SNP (rs7301826; P=1.0×10(-9)) within intron 7 of STX2. We further found evidence for the association of lead SNPs in STXBP5 and STX2 with expression levels of the respective transcripts. In in vitro cell studies, silencing STXBP5 decreased the release of tPA from vascular endothelial cells, whereas silencing STX2 increased the tPA release. Through an in silico lookup, we found no associations of the 3 lead SNPs with coronary artery disease or stroke. CONCLUSIONS: We identified 3 loci associated with circulating tPA levels, the PLAT region, STXBP5, and STX2. Our functional studies implicate a novel role for STXBP5 and STX2 in regulating tPA release.
Keywords: Aged; Cells, Cultured; Coronary Artery Disease; Endothelial Cells; Europe; Female; Gene Expression Regulation; Gene Silencing; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; R-SNARE Proteins; Risk Factors; Stroke; Syntaxin 1; Tissue Plasminogen Activator; Transfection; United States; Up-Regulation

Genome-wide association study of L-arginine and dimethylarginines reveals novel metabolic pathway for symmetric dimethylarginine. - Lüneburg, Nicole; Lieb, Wolfgang; Zeller, Tanja; Chen, Ming-Huei; Maas, Renke; Carter, Angela M; Xanthakis, Vanessa; Glazer, Nicole L; Schwedhelm, Edzard; Seshadri, Sudha; Ikram, Mohammad Arfan; Longstreth, William T; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Dimethylarginines (DMA) interfere with nitric oxide formation by inhibiting nitric oxide synthase (asymmetrical DMA [ADMA]) and l-arginine uptake into the cell (ADMA and symmetrical DMA [SDMA]). In prospective clinical studies, ADMA has been characterized as a cardiovascular risk marker, whereas SDMA is a novel marker for renal function and associated with all-cause mortality after ischemic stroke. The aim of the current study was to characterize the environmental and genetic contributions to interindividual variability of these biomarkers. METHODS AND RESULTS: This study comprised a genome-wide association analysis of 3 well-characterized population-based cohorts (Framingham Heart Study [FHS; n=2992], Gutenberg Health Study [GHS; n=4354], and Multinational Monitoring of Trends and Determinants in Cardiovascular Disease Study [MONICA]/Cooperative Health Research in the Augsburg Area, Augsburg, Bavaria, Germany [KORA] F3 [n=581]) and identified replicated loci (DDAH1, MED23, Arg1, and AGXT2) associated with the interindividual variability in ADMA, l-arginine, and SDMA. Experimental in silico and in vitro studies confirmed functional significance of the identified AGXT2 variants. Clinical outcome analysis in 384 patients of the Leeds stroke study demonstrated an association between increased plasma levels of SDMA, AGXT2 variants, and various cardiometabolic risk factors. AGXT2 variants were not associated with poststroke survival in the Leeds study or were they associated with incident stroke in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. CONCLUSIONS: These genome-wide association study support the importance of DDAH1 and MED23/Arg1 in regulating ADMA and l-arginine metabolism, respectively, and identify a novel regulatory renal pathway for SDMA by AGXT2. AGXT2 variants might explain part of the pathogenic link between SDMA, renal function, and outcome. An association between AGXT2 variants and stroke is unclear and warrants further investigation.
Keywords: Adult; Aged; Amidohydrolases; Arginine; Binding Sites; Cohort Studies; Female; Genetic Loci; Genome-Wide Association Study; Genotype; HEK293 Cells; Humans; Male; Mediator Complex; Middle Aged; Polymorphism, Single Nucleotide; Protein Structure, Tertiary; Risk Factors; Stroke; Substrate Specificity; Transaminases

Glycated hemoglobin measurement and prediction of cardiovascular disease. - Di Angelantonio, Emanuele; Gao, Pei; Khan, Hassan; Butterworth, Adam S; Wormser, David; Kaptoge, Stephen; Kondapally Seshasai, Sreenivasa Rao; Thompson, Alex; Sarwar, Nadeem; Willeit, Peter; Ridker, Paul M; Barr, Elizabeth L M; et al. (JAMA, 2014)
IMPORTANCE: The value of measuring levels of glycated hemoglobin (HbA1c) for the prediction of first cardiovascular events is uncertain. OBJECTIVE: To determine whether adding information on HbA1c values to conventional cardiovascular risk factors is associated with improvement in prediction of cardiovascular disease (CVD) risk. DESIGN, SETTING, AND PARTICIPANTS: Analysis of individual-participant data available from 73 prospective studies involving 294,998 participants without a known history of diabetes mellitus or CVD at the baseline assessment. MAIN OUTCOMES AND MEASURES: Measures of risk discrimination for CVD outcomes (eg, C-index) and reclassification (eg, net reclassification improvement) of participants across predicted 10-year risk categories of low (<5%), intermediate (5% to <7.5%), and high (≥ 7.5%) risk. RESULTS: During a median follow-up of 9.9 (interquartile range, 7.6-13.2) years, 20,840 incident fatal and nonfatal CVD outcomes (13,237 coronary heart disease and 7603 stroke outcomes) were recorded. In analyses adjusted for several conventional cardiovascular risk factors, there was an approximately J-shaped association between HbA1c values and CVD risk. The association between HbA1c values and CVD risk changed only slightly after adjustment for total cholesterol and triglyceride concentrations or estimated glomerular filtration rate, but this association attenuated somewhat after adjustment for concentrations of high-density lipoprotein cholesterol and C-reactive protein. The C-index for a CVD risk prediction model containing conventional cardiovascular risk factors alone was 0.7434 (95% CI, 0.7350 to 0.7517). The addition of information on HbA1c was associated with a C-index change of 0.0018 (0.0003 to 0.0033) and a net reclassification improvement of 0.42 (-0.63 to 1.48) for the categories of predicted 10-year CVD risk. The improvement provided by HbA1c assessment in prediction of CVD risk was equal to or better than estimated improvements for measurement of fasting, random, or postload plasma glucose levels. CONCLUSIONS AND RELEVANCE: In a study of individuals without known CVD or diabetes, additional assessment of HbA1c values in the context of CVD risk assessment provided little incremental benefit for prediction of CVD risk.
Keywords: Aged; C-Reactive Protein; Cholesterol, HDL; Coronary Disease; Diabetes Mellitus; Female; Glycated Hemoglobin A; Humans; Male; Middle Aged; Predictive Value of Tests; Prospective Studies; Risk Assessment; Stroke

Identification of novel genetic Loci associated with thyroid peroxidase antibodies and clinical thyroid disease. - Medici, Marco; Porcu, Eleonora; Pistis, Giorgio; Teumer, Alexander; Brown, Suzanne J; Jensen, Richard A; Rawal, Rajesh; Roef, Greet L; Plantinga, Theo S; Vermeulen, Sita H; Lahti, Jari; Simmonds, Matthew J; et al. (PLoS Genet, 2014)
Autoimmune thyroid diseases (AITD) are common, affecting 2-5% of the general population. Individuals with positive thyroid peroxidase antibodies (TPOAbs) have an increased risk of autoimmune hypothyroidism (Hashimoto's thyroiditis), as well as autoimmune hyperthyroidism (Graves' disease). As the possible causative genes of TPOAbs and AITD remain largely unknown, we performed GWAS meta-analyses in 18,297 individuals for TPOAb-positivity (1769 TPOAb-positives and 16,528 TPOAb-negatives) and in 12,353 individuals for TPOAb serum levels, with replication in 8,990 individuals. Significant associations (P<5×10(-8)) were detected at TPO-rs11675434, ATXN2-rs653178, and BACH2-rs10944479 for TPOAb-positivity, and at TPO-rs11675434, MAGI3-rs1230666, and KALRN-rs2010099 for TPOAb levels. Individual and combined effects (genetic risk scores) of these variants on (subclinical) hypo- and hyperthyroidism, goiter and thyroid cancer were studied. Individuals with a high genetic risk score had, besides an increased risk of TPOAb-positivity (OR: 2.18, 95% CI 1.68-2.81, P = 8.1×10(-8)), a higher risk of increased thyroid-stimulating hormone levels (OR: 1.51, 95% CI 1.26-1.82, P = 2.9×10(-6)), as well as a decreased risk of goiter (OR: 0.77, 95% CI 0.66-0.89, P = 6.5×10(-4)). The MAGI3 and BACH2 variants were associated with an increased risk of hyperthyroidism, which was replicated in an independent cohort of patients with Graves' disease (OR: 1.37, 95% CI 1.22-1.54, P = 1.2×10(-7) and OR: 1.25, 95% CI 1.12-1.39, P = 6.2×10(-5)). The MAGI3 variant was also associated with an increased risk of hypothyroidism (OR: 1.57, 95% CI 1.18-2.10, P = 1.9×10(-3)). This first GWAS meta-analysis for TPOAbs identified five newly associated loci, three of which were also associated with clinical thyroid disease. With these markers we identified a large subgroup in the general population with a substantially increased risk of TPOAbs. The results provide insight into why individuals with thyroid autoimmunity do or do not eventually develop thyroid disease, and these markers may therefore predict which TPOAb-positives are particularly at risk of developing clinical thyroid dysfunction.
Keywords: Autoantibodies; Genetic Loci; Genome-Wide Association Study; Graves Disease; Hashimoto Disease; Humans; Iodide Peroxidase; Risk Factors; Thyroiditis, Autoimmune; Thyrotropin

Integrating genetic, transcriptional, and functional analyses to identify 5 novel genes for atrial fibrillation. - Sinner, Moritz F; Tucker, Nathan R; Lunetta, Kathryn L; Ozaki, Kouichi; Smith, J Gustav; Trompet, Stella; Bis, Joshua C; Lin, Honghuang; Chung, Mina K; Nielsen, Jonas B; Lubitz, Steven A; Krijthe, Bouwe P; et al. (Circulation, 2014)
BACKGROUND: Atrial fibrillation (AF) affects >30 million individuals worldwide and is associated with an increased risk of stroke, heart failure, and death. AF is highly heritable, yet the genetic basis for the arrhythmia remains incompletely understood. METHODS AND RESULTS: To identify new AF-related genes, we used a multifaceted approach, combining large-scale genotyping in 2 ethnically distinct populations, cis-eQTL (expression quantitative trait loci) mapping, and functional validation. Four novel loci were identified in individuals of European descent near the genes NEURL (rs12415501; relative risk [RR]=1.18; 95% confidence interval [CI], 1.13-1.23; P=6.5×10(-16)), GJA1 (rs13216675; RR=1.10; 95% CI, 1.06-1.14; P=2.2×10(-8)), TBX5 (rs10507248; RR=1.12; 95% CI, 1.08-1.16; P=5.7×10(-11)), and CAND2 (rs4642101; RR=1.10; 95% CI, 1.06-1.14; P=9.8×10(-9)). In Japanese, novel loci were identified near NEURL (rs6584555; RR=1.32; 95% CI, 1.26-1.39; P=2.0×10(-25)) and CUX2 (rs6490029; RR=1.12; 95% CI, 1.08-1.16; P=3.9×10(-9)). The top single-nucleotide polymorphisms or their proxies were identified as cis-eQTLs for the genes CAND2 (P=2.6×10(-19)), GJA1 (P=2.66×10(-6)), and TBX5 (P=1.36×10(-5)). Knockdown of the zebrafish orthologs of NEURL and CAND2 resulted in prolongation of the atrial action potential duration (17% and 45%, respectively). CONCLUSIONS: We have identified 5 novel loci for AF. Our results expand the diversity of genetic pathways implicated in AF and provide novel molecular targets for future biological and pharmacological investigation.
Keywords: Aged; Animals; Atrial Fibrillation; Chromosome Mapping; Connexin 43; Europe; Female; Gene Knockdown Techniques; Genetic Loci; Genetic Predisposition to Disease; Genotype; Homeodomain Proteins; Humans; Japan; Male; Middle Aged; Muscle Proteins; Nuclear Proteins; Quantitative Trait Loci; Repressor Proteins; T-Box Domain Proteins; Transcription Factors; Ubiquitin-Protein Ligases; Zebrafish; Zebrafish Proteins

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans. - Ellis, Jaclyn; Lange, Ethan M; Li, Jin; Dupuis, Josée; Baumert, Jens; Walston, Jeremy D; Keating, Brendan J; Durda, Peter; Fox, Ervin R; Palmer, Cameron D; Meng, Yan A; Young, Taylor; et al. (Hum Genet, 2014)
C-reactive protein (CRP) is a heritable biomarker of systemic inflammation and a predictor of cardiovascular disease (CVD). Large-scale genetic association studies for CRP have largely focused on individuals of European descent. We sought to uncover novel genetic variants for CRP in a multiethnic sample using the ITMAT Broad-CARe (IBC) array, a custom 50,000 SNP gene-centric array having dense coverage of over 2,000 candidate CVD genes. We performed analyses on 7,570 African Americans (AA) from the Candidate gene Association Resource (CARe) study and race-combined meta-analyses that included 29,939 additional individuals of European descent from CARe, the Women's Health Initiative (WHI) and KORA studies. We observed array-wide significance (p < 2.2 × 10(-6)) for four loci in AA, three of which have been reported previously in individuals of European descent (IL6R, p = 2.0 × 10(-6); CRP, p = 4.2 × 10(-71); APOE, p = 1.6 × 10(-6)). The fourth significant locus, CD36 (p = 1.6 × 10(-6)), was observed at a functional variant (rs3211938) that is extremely rare in individuals of European descent. We replicated the CD36 finding (p = 1.8 × 10(-5)) in an independent sample of 8,041 AA women from WHI; a meta-analysis combining the CARe and WHI AA results at rs3211938 reached genome-wide significance (p = 1.5 × 10(-10)). In the race-combined meta-analyses, 13 loci reached significance, including ten (CRP, TOMM40/APOE/APOC1, HNF1A, LEPR, GCKR, IL6R, IL1RN, NLRP3, HNF4A and BAZ1B/BCL7B) previously associated with CRP, and one (ARNTL) previously reported to be nominally associated with CRP. Two novel loci were also detected (RPS6KB1, p = 2.0 × 10(-6); CD36, p = 1.4 × 10(-6)). These results highlight both shared and unique genetic risk factors for CRP in AA compared to populations of European descent.
Keywords: Adult; African Americans; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; CD36 Antigens; Female; Genetic Loci; Genetic Predisposition to Disease; Genetics, Population; Genome-Wide Association Study; Humans; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Large-scale meta-analysis of genome-wide association data identifies six new risk loci for Parkinson's disease. - Nalls, Mike A; Pankratz, Nathan; Lill, Christina M; Do, Chuong B; Hernandez, Dena G; Saad, Mohamad; DeStefano, Anita L; Kara, Eleanna; Bras, Jose; Sharma, Manu; Schulte, Claudia; Keller, Margaux F; et al. (Nat Genet, 2014)
We conducted a meta-analysis of Parkinson's disease genome-wide association studies using a common set of 7,893,274 variants across 13,708 cases and 95,282 controls. Twenty-six loci were identified as having genome-wide significant association; these and 6 additional previously reported loci were then tested in an independent set of 5,353 cases and 5,551 controls. Of the 32 tested SNPs, 24 replicated, including 6 newly identified loci. Conditional analyses within loci showed that four loci, including GBA, GAK-DGKQ, SNCA and the HLA region, contain a secondary independent risk variant. In total, we identified and replicated 28 independent risk variants for Parkinson's disease across 24 loci. Although the effect of each individual locus was small, risk profile analysis showed substantial cumulative risk in a comparison of the highest and lowest quintiles of genetic risk (odds ratio (OR) = 3.31, 95% confidence interval (CI) = 2.55-4.30; P = 2 × 10(-16)). We also show six risk loci associated with proximal gene expression or DNA methylation.
Keywords: Case-Control Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Parkinson Disease; Polymorphism, Single Nucleotide; Risk Factors

Loss-of-function mutations in APOC3, triglycerides, and coronary disease. - Crosby, Jacy; Peloso, Gina M; Auer, Paul L; Crosslin, David R; Stitziel, Nathan O; Lange, Leslie A; Lu, Yingchang; Tang, Zheng-Zheng; Zhang, He; Hindy, George; Masca, Nicholas; Stirrups, Kathleen; et al. (N Engl J Med, 2014)
BACKGROUND: Plasma triglyceride levels are heritable and are correlated with the risk of coronary heart disease. Sequencing of the protein-coding regions of the human genome (the exome) has the potential to identify rare mutations that have a large effect on phenotype. METHODS: We sequenced the protein-coding regions of 18,666 genes in each of 3734 participants of European or African ancestry in the Exome Sequencing Project. We conducted tests to determine whether rare mutations in coding sequence, individually or in aggregate within a gene, were associated with plasma triglyceride levels. For mutations associated with triglyceride levels, we subsequently evaluated their association with the risk of coronary heart disease in 110,970 persons. RESULTS: An aggregate of rare mutations in the gene encoding apolipoprotein C3 (APOC3) was associated with lower plasma triglyceride levels. Among the four mutations that drove this result, three were loss-of-function mutations: a nonsense mutation (R19X) and two splice-site mutations (IVS2+1G→A and IVS3+1G→T). The fourth was a missense mutation (A43T). Approximately 1 in 150 persons in the study was a heterozygous carrier of at least one of these four mutations. Triglyceride levels in the carriers were 39% lower than levels in noncarriers (P<1×10(-20)), and circulating levels of APOC3 in carriers were 46% lower than levels in noncarriers (P=8×10(-10)). The risk of coronary heart disease among 498 carriers of any rare APOC3 mutation was 40% lower than the risk among 110,472 noncarriers (odds ratio, 0.60; 95% confidence interval, 0.47 to 0.75; P=4×10(-6)). CONCLUSIONS: Rare mutations that disrupt APOC3 function were associated with lower levels of plasma triglycerides and APOC3. Carriers of these mutations were found to have a reduced risk of coronary heart disease. (Funded by the National Heart, Lung, and Blood Institute and others.).
Keywords: African Continental Ancestry Group; Apolipoprotein C-III; Coronary Disease; European Continental Ancestry Group; Exome; Genotype; Heterozygote; Humans; Liver; Mutation; Risk Factors; Sequence Analysis, DNA; Triglycerides

A low-frequency variant in MAPK14 provides mechanistic evidence of a link with myeloperoxidase: a prognostic cardiovascular risk marker. - Waterworth, Dawn M; Li, Li; Scott, Robert; Warren, Liling; Gillson, Christopher; Aponte, Jennifer; Sarov-Blat, Lea; Sprecher, Dennis; Dupuis, Josée; Reiner, Alex; Psaty, Bruce M; Tracy, Russell P; et al. (J Am Heart Assoc, 2014)
BACKGROUND: Genetics can be used to predict drug effects and generate hypotheses around alternative indications. To support Losmapimod, a p38 mitogen-activated protein kinase inhibitor in development for acute coronary syndrome, we characterized gene variation in MAPK11/14 genes by exome sequencing and follow-up genotyping or imputation in participants well-phenotyped for cardiovascular and metabolic traits. METHODS AND RESULTS: Investigation of genetic variation in MAPK11 and MAPK14 genes using additive genetic models in linear or logistic regression with cardiovascular, metabolic, and biomarker phenotypes highlighted an association of RS2859144 in MAPK14 with myeloperoxidase in a dyslipidemic population (Genetic Epidemiology of Metabolic Syndrome Study), P=2.3×10(-6)). This variant (or proxy) was consistently associated with myeloperoxidase in the Framingham Heart Study and Cardiovascular Health Study studies (replication meta-P=0.003), leading to a meta-P value of 9.96×10(-7) in the 3 dyslipidemic groups. The variant or its proxy was then profiled in additional population-based cohorts (up to a total of 58 930 subjects) including Cohorte Lausannoise, Ely, Fenland, European Prospective Investigation of Cancer, London Life Sciences Prospective Population Study, and the Genetics of Obesity Associations study obesity case-control for up to 40 cardiovascular and metabolic traits. Overall analysis identified the same single nucleotide polymorphisms to be nominally associated consistently with glomerular filtration rate (P=0.002) and risk of obesity (body mass index ≥30 kg/m(2), P=0.004). CONCLUSIONS: As myeloperoxidase is a prognostic marker of coronary events, the MAPK14 variant may provide a mechanistic link between p38 map kinase and these events, providing information consistent with current indication of Losmapimod for acute coronary syndrome. If replicated, the association with glomerular filtration rate, along with previous biological findings, also provides support for kidney diseases as alternative indications.
Keywords: Adult; Aged; Cardiovascular Diseases; Dyslipidemias; Exome; Female; Genotype; Humans; Linear Models; Logistic Models; Male; Metabolic Syndrome X; Middle Aged; Mitogen-Activated Protein Kinase 11; Mitogen-Activated Protein Kinase 14; Obesity; Peroxidase; Polymorphism, Single Nucleotide; Prognosis; Risk Factors; Sequence Analysis, DNA

Meta-analysis of genome-wide association studies in African Americans provides insights into the genetic architecture of type 2 diabetes. - Ng, Maggie C Y; Shriner, Daniel; Chen, Brian H; Li, Jiang; Chen, Wei-Min; Guo, Xiuqing; Liu, Jiankang; Bielinski, Suzette J; Yanek, Lisa R; Nalls, Michael A; Comeau, Mary E; Rasmussen-Torvik, Laura J; et al. (PLoS Genet, 2014)
Type 2 diabetes (T2D) is more prevalent in African Americans than in Europeans. However, little is known about the genetic risk in African Americans despite the recent identification of more than 70 T2D loci primarily by genome-wide association studies (GWAS) in individuals of European ancestry. In order to investigate the genetic architecture of T2D in African Americans, the MEta-analysis of type 2 DIabetes in African Americans (MEDIA) Consortium examined 17 GWAS on T2D comprising 8,284 cases and 15,543 controls in African Americans in stage 1 analysis. Single nucleotide polymorphisms (SNPs) association analysis was conducted in each study under the additive model after adjustment for age, sex, study site, and principal components. Meta-analysis of approximately 2.6 million genotyped and imputed SNPs in all studies was conducted using an inverse variance-weighted fixed effect model. Replications were performed to follow up 21 loci in up to 6,061 cases and 5,483 controls in African Americans, and 8,130 cases and 38,987 controls of European ancestry. We identified three known loci (TCF7L2, HMGA2 and KCNQ1) and two novel loci (HLA-B and INS-IGF2) at genome-wide significance (4.15 × 10(-94)<P<5 × 10(-8), odds ratio (OR)  = 1.09 to 1.36). Fine-mapping revealed that 88 of 158 previously identified T2D or glucose homeostasis loci demonstrated nominal to highly significant association (2.2 × 10(-23) < locus-wide P<0.05). These novel and previously identified loci yielded a sibling relative risk of 1.19, explaining 17.5% of the phenotypic variance of T2D on the liability scale in African Americans. Overall, this study identified two novel susceptibility loci for T2D in African Americans. A substantial number of previously reported loci are transferable to African Americans after accounting for linkage disequilibrium, enabling fine mapping of causal variants in trans-ethnic meta-analysis studies.
Keywords: African Americans; Diabetes Mellitus, Type 2; Genome-Wide Association Study; HLA-B27 Antigen; HMGA2 Protein; Humans; KCNQ1 Potassium Channel; Mutant Chimeric Proteins; Polymorphism, Single Nucleotide; Transcription Factor 7-Like 2 Protein

Meta-analysis of loci associated with age at natural menopause in African-American women. - Chen, Christina T L; Liu, Ching-Ti; Chen, Gary K; Andrews, Jeanette S; Arnold, Alice M; Dreyfus, Jill; Franceschini, Nora; Garcia, Melissa E; Kerr, Kathleen F; Li, Guo; Lohman, Kurt K; Musani, Solomon K; et al. (Hum Mol Genet, 2014)
Age at menopause marks the end of a woman's reproductive life and its timing associates with risks for cancer, cardiovascular and bone disorders. GWAS and candidate gene studies conducted in women of European ancestry have identified 27 loci associated with age at menopause. The relevance of these loci to women of African ancestry has not been previously studied. We therefore sought to uncover additional menopause loci and investigate the relevance of European menopause loci by performing a GWAS meta-analysis in 6510 women with African ancestry derived from 11 studies across the USA. We did not identify any additional loci significantly associated with age at menopause in African Americans. We replicated the associations between six loci and age at menopause (P-value < 0.05): AMHR2, RHBLD2, PRIM1, HK3/UMC1, BRSK1/TMEM150B and MCM8. In addition, associations of 14 loci are directionally consistent with previous reports. We provide evidence that genetic variants influencing reproductive traits identified in European populations are also important in women of African ancestry residing in USA.
Keywords: African Americans; Age Factors; Chromosomes, Human; European Continental Ancestry Group; Female; Genetic Loci; Genetic Variation; Genome-Wide Association Study; Humans; Menopause; United States

No evidence for genome-wide interactions on plasma fibrinogen by smoking, alcohol consumption and body mass index: results from meta-analyses of 80,607 subjects. - Baumert, Jens; Huang, Jie; McKnight, Barbara; Sabater-Lleal, Maria; Steri, Maristella; Chu, Audrey Y; Trompet, Stella; Lopez, Lorna M; Fornage, Myriam; Teumer, Alexander; Tang, Weihong; Rudnicka, Alicja R; et al. (PLoS One, 2014)
Plasma fibrinogen is an acute phase protein playing an important role in the blood coagulation cascade having strong associations with smoking, alcohol consumption and body mass index (BMI). Genome-wide association studies (GWAS) have identified a variety of gene regions associated with elevated plasma fibrinogen concentrations. However, little is yet known about how associations between environmental factors and fibrinogen might be modified by genetic variation. Therefore, we conducted large-scale meta-analyses of genome-wide interaction studies to identify possible interactions of genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentration. The present study included 80,607 subjects of European ancestry from 22 studies. Genome-wide interaction analyses were performed separately in each study for about 2.6 million single nucleotide polymorphisms (SNPs) across the 22 autosomal chromosomes. For each SNP and risk factor, we performed a linear regression under an additive genetic model including an interaction term between SNP and risk factor. Interaction estimates were meta-analysed using a fixed-effects model. No genome-wide significant interaction with smoking status, alcohol consumption or BMI was observed in the meta-analyses. The most suggestive interaction was found for smoking and rs10519203, located in the LOC123688 region on chromosome 15, with a p value of 6.2 × 10(-8). This large genome-wide interaction study including 80,607 participants found no strong evidence of interaction between genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentrations. Further studies are needed to yield deeper insight in the interplay between environmental factors and gene variants on the regulation of fibrinogen concentrations.
Keywords: Alcohol Drinking; Body Mass Index; Fibrinogen; Gene-Environment Interaction; Genomics; Humans; Smoking

Novel genetic markers associate with atrial fibrillation risk in Europeans and Japanese. - Lubitz, Steven A; Lunetta, Kathryn L; Lin, Honghuang; Arking, Dan E; Trompet, Stella; Li, Guo; Krijthe, Bouwe P; Chasman, Daniel I; Barnard, John; Kleber, Marcus E; Dörr, Marcus; Ozaki, Kouichi; et al. (J Am Coll Cardiol, 2014)
OBJECTIVES: This study sought to identify nonredundant atrial fibrillation (AF) genetic susceptibility signals and examine their cumulative relations with AF risk. BACKGROUND: AF-associated loci span broad genomic regions that may contain multiple susceptibility signals. Whether multiple signals exist at AF loci has not been systematically explored. METHODS: We performed association testing conditioned on the most significant, independently associated genetic markers at 9 established AF loci using 2 complementary techniques in 64,683 individuals of European ancestry (3,869 incident and 3,302 prevalent AF cases). Genetic risk scores were created and tested for association with AF in Europeans and an independent sample of 11,309 individuals of Japanese ancestry (7,916 prevalent AF cases). RESULTS: We observed at least 4 distinct AF susceptibility signals on chromosome 4q25 upstream of PITX2, but not at the remaining 8 AF loci. A multilocus score comprised 12 genetic markers demonstrated an estimated 5-fold gradient in AF risk. We observed a similar spectrum of risk associated with these markers in Japanese. Regions containing AF signals on chromosome 4q25 displayed a greater degree of evolutionary conservation than the remainder of the locus, suggesting that they may tag regulatory elements. CONCLUSIONS: The chromosome 4q25 AF locus is architecturally complex and harbors at least 4 AF susceptibility signals in individuals of European ancestry. Similar polygenic AF susceptibility exists between Europeans and Japanese. Future work is necessary to identify causal variants, determine mechanisms by which associated loci predispose to AF, and explore whether AF susceptibility signals classify individuals at risk for AF and related morbidity.
Keywords: Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Atrial Fibrillation; Chromosome Mapping; Chromosomes, Human, Pair 4; Europe; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Homeodomain Proteins; Humans; Japan; Male; Middle Aged; Polymorphism, Single Nucleotide; Transcription Factors

Pharmacogenetic meta-analysis of genome-wide association studies of LDL cholesterol response to statins. - Postmus, Iris; Trompet, Stella; Deshmukh, Harshal A; Barnes, Michael R; Li, Xiaohui; Warren, Helen R; Chasman, Daniel I; Zhou, Kaixin; Arsenault, Benoit J; Donnelly, Louise A; Wiggins, Kerri L; Avery, Christy L; et al. (Nat Commun, 2014)
Statins effectively lower LDL cholesterol levels in large studies and the observed interindividual response variability may be partially explained by genetic variation. Here we perform a pharmacogenetic meta-analysis of genome-wide association studies (GWAS) in studies addressing the LDL cholesterol response to statins, including up to 18,596 statin-treated subjects. We validate the most promising signals in a further 22,318 statin recipients and identify two loci, SORT1/CELSR2/PSRC1 and SLCO1B1, not previously identified in GWAS. Moreover, we confirm the previously described associations with APOE and LPA. Our findings advance the understanding of the pharmacogenetic architecture of statin response.
Keywords: Cholesterol, LDL; Genome-Wide Association Study; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pharmacogenetics; Polymorphism, Single Nucleotide

Predicting stroke through genetic risk functions: the CHARGE Risk Score Project. - Ibrahim-Verbaas, Carla A; Fornage, Myriam; Bis, Joshua C; Choi, Seung Hoan; Psaty, Bruce M; Meigs, James B; Rao, Madhu; Nalls, Mike; Fontes, João D; O'Donnell, Christopher J; Kathiresan, Sekar; Ehret, Georg B; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Beyond the Framingham Stroke Risk Score, prediction of future stroke may improve with a genetic risk score (GRS) based on single-nucleotide polymorphisms associated with stroke and its risk factors. METHODS: The study includes 4 population-based cohorts with 2047 first incident strokes from 22,720 initially stroke-free European origin participants aged ≥55 years, who were followed for up to 20 years. GRSs were constructed with 324 single-nucleotide polymorphisms implicated in stroke and 9 risk factors. The association of the GRS to first incident stroke was tested using Cox regression; the GRS predictive properties were assessed with area under the curve statistics comparing the GRS with age and sex, Framingham Stroke Risk Score models, and reclassification statistics. These analyses were performed per cohort and in a meta-analysis of pooled data. Replication was sought in a case-control study of ischemic stroke. RESULTS: In the meta-analysis, adding the GRS to the Framingham Stroke Risk Score, age and sex model resulted in a significant improvement in discrimination (all stroke: Δjoint area under the curve=0.016, P=2.3×10(-6); ischemic stroke: Δjoint area under the curve=0.021, P=3.7×10(-7)), although the overall area under the curve remained low. In all the studies, there was a highly significantly improved net reclassification index (P<10(-4)). CONCLUSIONS: The single-nucleotide polymorphisms associated with stroke and its risk factors result only in a small improvement in prediction of future stroke compared with the classical epidemiological risk factors for stroke.
Keywords: Age Factors; Aged; Aged, 80 and over; Area Under Curve; Case-Control Studies; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; ROC Curve; Sex Factors; Stroke

Regular fish consumption and age-related brain gray matter loss. - Raji, Cyrus A; Erickson, Kirk I; Lopez, Oscar L; Kuller, Lewis H; Gach, H Michael; Thompson, Paul M; Riverol, Mario; Becker, James T (Am J Prev Med, 2014)
BACKGROUND: Brain health may be affected by modifiable lifestyle factors; consuming fish and antioxidative omega-3 fatty acids may reduce brain structural abnormality risk. PURPOSE: To determine whether dietary fish consumption is related to brain structural integrity among cognitively normal elders. METHODS: Data were analyzed from 260 cognitively normal individuals from the Cardiovascular Health Study with information on fish consumption from the National Cancer Institute Food Frequency Questionnaire and brain magnetic resonance imaging (MRI). The relationship between fish consumption data collected in 1989-1990 and brain structural MRI obtained in 1998-1999 was assessed using voxel-based morphometry in multiple regression analyses in 2012. Covariates were age, gender, race, education, white matter lesions, MRI-identified infarcts, waist-hip ratio, and physical activity as assessed by the number of city blocks walked in 1 week. Volumetric changes were further modeled with omega-3 fatty acid estimates to better understand the mechanistic link between fish consumption, brain health, and Alzheimer disease. RESULTS: Weekly consumption of baked or broiled fish was positively associated with gray matter volumes in the hippocampus, precuneus, posterior cingulate, and orbital frontal cortex even after adjusting for covariates. These results did not change when including omega-3 fatty acid estimates in the analysis. CONCLUSIONS: Dietary consumption of baked or broiled fish is related to larger gray matter volumes independent of omega-3 fatty acid content. These findings suggest that a confluence of lifestyle factors influence brain health, adding to the growing body of evidence that prevention strategies for late-life brain health need to begin decades earlier.
Keywords: Aged; Aged, 80 and over; Animals; Brain; Cross-Sectional Studies; Diet; Fatty Acids, Omega-3; Female; Fishes; Gray Matter; Humans; Life Style; Magnetic Resonance Imaging; Male; Regression Analysis; Surveys and Questionnaires

Sequence analysis of six blood pressure candidate regions in 4,178 individuals: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) targeted sequencing study. - Morrison, Alanna C; Bis, Joshua C; Hwang, Shih-Jen; Ehret, Georg B; Lumley, Thomas; Rice, Kenneth; Muzny, Donna; Gibbs, Richard A; Boerwinkle, Eric; Psaty, Bruce M; Chakravarti, Aravinda; Levy, Daniel (PLoS One, 2014)
BACKGROUND: Genome-wide association studies (GWAS) identified multiple loci for blood pressure (BP) and hypertension. Six genes--ATP2B1, CACNB2, CYP17A1, JAG1, PLEKHA7, and SH2B3--were evaluated for sequence variation with large effects on systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP), and mean arterial pressure (MAP). METHODS AND RESULTS: Targeted genomic sequence was determined in 4,178 European ancestry participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Common variants (≥50 minor allele copies) were evaluated individually and rare variants (minor allele frequency, MAF≤1%) were aggregated by locus. 464 common variants were identified across the 6 genes. An upstream CYP17A1 variant, rs11191416 (MAF = 0.09), was the most significant association for SBP (P = 0.0005); however the association was attenuated (P = 0.0469) after conditioning on the GWAS index single nucleotide polymorphism (SNP). A PLEKHA7 intronic variant was the strongest DBP association (rs12806040, MAF = 0.007, P = 0.0006) and was not in LD (r² = 0.01) with the GWAS SNP. A CACNB2 intronic SNP, rs1571787, was the most significant association with PP (MAF = 0.27, P = 0.0003), but was not independent from the GWAS SNP (r² = 0.34). Three variants (rs6163 and rs743572 in the CYP17A1 region and rs112467382 in PLEKHA7) were associated with BP traits (P<0.001). Rare variation, aggregately assessed in the 6 regions, was not significantly associated with BP measures. CONCLUSION: Six targeted gene regions, previously identified by GWAS, did not harbor novel variation with large effects on BP in this sample.
Keywords: Aging; Blood Pressure; Cohort Studies; Heart; Humans; Sequence Analysis

Sequencing of SCN5A identifies rare and common variants associated with cardiac conduction: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. - Magnani, Jared W; Brody, Jennifer A; Prins, Bram P; Arking, Dan E; Lin, Honghuang; Yin, Xiaoyan; Liu, Ching-Ti; Morrison, Alanna C; Zhang, Feng; Spector, Tim D; Alonso, Alvaro; Bis, Joshua C; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: The cardiac sodium channel SCN5A regulates atrioventricular and ventricular conduction. Genetic variants in this gene are associated with PR and QRS intervals. We sought to characterize further the contribution of rare and common coding variation in SCN5A to cardiac conduction. METHODS AND RESULTS: In Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study, we performed targeted exonic sequencing of SCN5A (n=3699, European ancestry individuals) and identified 4 common (minor allele frequency >1%) and 157 rare variants. Common and rare SCN5A coding variants were examined for association with PR and QRS intervals through meta-analysis of European ancestry participants from CHARGE, National Heart, Lung, and Blood Institute's Exome Sequencing Project (n=607), and the UK10K (n=1275) and by examining Exome Sequencing Project African ancestry participants (n=972). Rare coding SCN5A variants in aggregate were associated with PR interval in European and African ancestry participants (P=1.3×10(-3)). Three common variants were associated with PR and QRS interval duration among European ancestry participants and one among African ancestry participants. These included 2 well-known missense variants: rs1805124 (H558R) was associated with PR and QRS shortening in European ancestry participants (P=6.25×10(-4) and P=5.2×10(-3), respectively) and rs7626962 (S1102Y) was associated with PR shortening in those of African ancestry (P=2.82×10(-3)). Among European ancestry participants, 2 novel synonymous variants, rs1805126 and rs6599230, were associated with cardiac conduction. Our top signal, rs1805126 was associated with PR and QRS lengthening (P=3.35×10(-7) and P=2.69×10(-4), respectively) and rs6599230 was associated with PR shortening (P=2.67×10(-5)). CONCLUSIONS: By sequencing SCN5A, we identified novel common and rare coding variants associated with cardiac conduction.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Conduction System; Heart Diseases; Humans; Male; Middle Aged; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Shared genetic susceptibility to ischemic stroke and coronary artery disease: a genome-wide analysis of common variants. - Dichgans, Martin; Malik, Rainer; König, Inke R; Rosand, Jonathan; Clarke, Robert; Gretarsdottir, Solveig; Thorleifsson, Gudmar; Mitchell, Braxton D; Assimes, Themistocles L; Levi, Christopher; O'Donnell, Christopher J; Fornage, Myriam; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Ischemic stroke (IS) and coronary artery disease (CAD) share several risk factors and each has a substantial heritability. We conducted a genome-wide analysis to evaluate the extent of shared genetic determination of the two diseases. METHODS: Genome-wide association data were obtained from the METASTROKE, Coronary Artery Disease Genome-wide Replication and Meta-analysis (CARDIoGRAM), and Coronary Artery Disease (C4D) Genetics consortia. We first analyzed common variants reaching a nominal threshold of significance (P<0.01) for CAD for their association with IS and vice versa. We then examined specific overlap across phenotypes for variants that reached a high threshold of significance. Finally, we conducted a joint meta-analysis on the combined phenotype of IS or CAD. Corresponding analyses were performed restricted to the 2167 individuals with the ischemic large artery stroke (LAS) subtype. RESULTS: Common variants associated with CAD at P<0.01 were associated with a significant excess risk for IS and for LAS and vice versa. Among the 42 known genome-wide significant loci for CAD, 3 and 5 loci were significantly associated with IS and LAS, respectively. In the joint meta-analyses, 15 loci passed genome-wide significance (P<5×10(-8)) for the combined phenotype of IS or CAD and 17 loci passed genome-wide significance for LAS or CAD. Because these loci had prior evidence for genome-wide significance for CAD, we specifically analyzed the respective signals for IS and LAS and found evidence for association at chr12q24/SH2B3 (PIS=1.62×10(-7)) and ABO (PIS=2.6×10(-4)), as well as at HDAC9 (PLAS=2.32×10(-12)), 9p21 (PLAS=3.70×10(-6)), RAI1-PEMT-RASD1 (PLAS=2.69×10(-5)), EDNRA (PLAS=7.29×10(-4)), and CYP17A1-CNNM2-NT5C2 (PLAS=4.9×10(-4)). CONCLUSIONS: Our results demonstrate substantial overlap in the genetic risk of IS and particularly the LAS subtype with CAD.
Keywords: Brain Ischemia; Coronary Artery Disease; Data Interpretation, Statistical; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide; Reproducibility of Results; Risk Factors; Stroke

Targeted sequencing in candidate genes for atrial fibrillation: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study. - Lin, Honghuang; Sinner, Moritz F; Brody, Jennifer A; Arking, Dan E; Lunetta, Kathryn L; Rienstra, Michiel; Lubitz, Steven A; Magnani, Jared W; Sotoodehnia, Nona; McKnight, Barbara; McManus, David D; Boerwinkle, Eric; et al. (Heart Rhythm, 2014)
BACKGROUND: Genome-wide association studies (GWAS) have identified common genetic variants that predispose to atrial fibrillation (AF). It is unclear whether rare and low-frequency variants in genes implicated by such GWAS confer additional risk of AF. OBJECTIVE: To study the association of genetic variants with AF at GWAS top loci. METHODS: In the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study, we selected and sequenced 77 target gene regions from GWAS loci of complex diseases or traits, including 4 genes hypothesized to be related to AF (PRRX1, CAV1, CAV2, and ZFHX3). Sequencing was performed in participants with (n = 948) and without (n = 3330) AF from the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Massachusetts General Hospital. RESULTS: One common variant (rs11265611; P = 1.70 × 10(-6)) intronic to IL6R (interleukin-6 receptor gene) was significantly associated with AF after Bonferroni correction (odds ratio 0.70; 95% confidence interval 0.58-0.85). The variant was not genotyped or imputed by prior GWAS, but it is in linkage disequilibrium (r(2) = .69) with the single-nucleotide polymorphism, with the strongest association with AF so far at this locus (rs4845625). In the rare variant joint analysis, damaging variants within the PRRX1 region showed significant association with AF after Bonferroni correction (P = .01). CONCLUSIONS: We identified 1 common single-nucleotide polymorphism and 1 gene region that were significantly associated with AF. Future sequencing efforts with larger sample sizes and more comprehensive genome coverage are anticipated to identify additional AF-related variants.
Keywords: Aged; Atrial Fibrillation; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeodomain Proteins; Humans; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Interleukin-6

Thyroid antibody status, subclinical hypothyroidism, and the risk of coronary heart disease: an individual participant data analysis. - Collet, Tinh-Hai; Bauer, Douglas C; Cappola, Anne R; Asvold, Bjørn O; Weiler, Stefan; Vittinghoff, Eric; Gussekloo, Jacobijn; Bremner, Alexandra; den Elzen, Wendy P J; Maciel, Rui M B; Vanderpump, Mark P J; Cornuz, Jacques; et al. (J Clin Endocrinol Metab, 2014)
CONTEXT: Subclinical hypothyroidism has been associated with increased risk of coronary heart disease (CHD), particularly with thyrotropin levels of 10.0 mIU/L or greater. The measurement of thyroid antibodies helps predict the progression to overt hypothyroidism, but it is unclear whether thyroid autoimmunity independently affects CHD risk. OBJECTIVE: The objective of the study was to compare the CHD risk of subclinical hypothyroidism with and without thyroid peroxidase antibodies (TPOAbs). DATA SOURCES AND STUDY SELECTION: A MEDLINE and EMBASE search from 1950 to 2011 was conducted for prospective cohorts, reporting baseline thyroid function, antibodies, and CHD outcomes. DATA EXTRACTION: Individual data of 38 274 participants from six cohorts for CHD mortality followed up for 460 333 person-years and 33 394 participants from four cohorts for CHD events. DATA SYNTHESIS: Among 38 274 adults (median age 55 y, 63% women), 1691 (4.4%) had subclinical hypothyroidism, of whom 775 (45.8%) had positive TPOAbs. During follow-up, 1436 participants died of CHD and 3285 had CHD events. Compared with euthyroid individuals, age- and gender-adjusted risks of CHD mortality in subclinical hypothyroidism were similar among individuals with and without TPOAbs [hazard ratio (HR) 1.15, 95% confidence interval (CI) 0.87-1.53 vs HR 1.26, CI 1.01-1.58, P for interaction = .62], as were risks of CHD events (HR 1.16, CI 0.87-1.56 vs HR 1.26, CI 1.02-1.56, P for interaction = .65). Risks of CHD mortality and events increased with higher thyrotropin, but within each stratum, risks did not differ by TPOAb status. CONCLUSIONS: CHD risk associated with subclinical hypothyroidism did not differ by TPOAb status, suggesting that biomarkers of thyroid autoimmunity do not add independent prognostic information for CHD outcomes.
Keywords: Adult; Aged; Aged, 80 and over; Autoantibodies; Coronary Disease; Female; Humans; Hypothyroidism; Incidence; Male; Middle Aged; Prevalence; Prognosis; Risk Factors; Seroepidemiologic Studies; Severity of Illness Index; Young Adult

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Association between hospitalization for pneumonia and subsequent risk of cardiovascular disease. - Corrales-Medina, Vicente F; Alvarez, Karina N; Weissfeld, Lisa A; Angus, Derek C; Chirinos, Julio A; Chang, Chung-Chou H; Newman, Anne; Loehr, Laura; Folsom, Aaron R; Elkind, Mitchell S; Lyles, Mary F; Kronmal, Richard A; et al. (JAMA, 2015)
IMPORTANCE: The risk of cardiovascular disease (CVD) after infection is poorly understood. OBJECTIVE: To determine whether hospitalization for pneumonia is associated with an increased short-term and long-term risk of CVD. DESIGN, SETTINGS, AND PARTICIPANTS: We examined 2 community-based cohorts: the Cardiovascular Health Study (CHS, n = 5888; enrollment age, ≥65 years; enrollment period, 1989-1994) and the Atherosclerosis Risk in Communities study (ARIC, n = 15,792; enrollment age, 45-64 years; enrollment period, 1987-1989). Participants were followed up through December 31, 2010. We matched each participant hospitalized with pneumonia to 2 controls. Pneumonia cases and controls were followed for occurrence of CVD over 10 years after matching. We estimated hazard ratios (HRs) for CVD at different time intervals, adjusting for demographics, CVD risk factors, subclinical CVD, comorbidities, and functional status. EXPOSURES: Hospitalization for pneumonia. MAIN OUTCOMES AND MEASURES: Incident CVD (myocardial infarction, stroke, and fatal coronary heart disease). RESULTS: Of 591 pneumonia cases in CHS, 206 had CVD events over 10 years after pneumonia hospitalization. CVD risk after pneumonia was highest in the first year. CVD occurred in 54 cases and 6 controls in the first 30 days (HR, 4.07; 95% CI, 2.86-5.27); 11 cases and 9 controls between 31 and 90 days (HR, 2.94; 95% CI, 2.18-3.70); and 22 cases and 55 controls between 91 days and 1 year (HR, 2.10; 95% CI, 1.59-2.60). Additional CVD risk remained elevated into the tenth year, when 4 cases and 12 controls developed CVD (HR, 1.86; 95% CI, 1.18-2.55). In ARIC, of 680 pneumonia cases, 112 had CVD over 10 years after hospitalization. CVD occurred in 4 cases and 3 controls in the first 30 days (HR, 2.38; 95% CI, 1.12-3.63); 4 cases and 0 controls between 31 and 90 days (HR, 2.40; 95% CI, 1.23-3.47); 11 cases and 8 controls between 91 days and 1 year (HR, 2.19; 95% CI, 1.20-3.19); and 8 cases and 7 controls during the second year (HR, 1.88; 95% CI, 1.10-2.66). After the second year, the HRs were no longer statistically significant. CONCLUSIONS AND RELEVANCE: Hospitalization for pneumonia was associated with increased short-term and long-term risk of CVD, suggesting that pneumonia may be a risk factor for CVD.
Keywords: Aged; Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Comorbidity; Female; Hospitalization; Humans; Male; Middle Aged; Pneumonia; Risk Factors

Association between left atrial abnormality on ECG and vascular brain injury on MRI in the Cardiovascular Health Study. - Kamel, Hooman; Bartz, Traci M; Longstreth, W T; Okin, Peter M; Thacker, Evan L; Patton, Kristen K; Stein, Phyllis K; Gottesman, Rebecca F; Heckbert, Susan R; Kronmal, Richard A; Elkind, Mitchell S V; Soliman, Elsayed Z (Stroke, 2015)
BACKGROUND AND PURPOSE: Emerging evidence suggests that atrial disease is associated with vascular brain injury in the absence of atrial fibrillation. METHODS: The Cardiovascular Health Study prospectively enrolled community-dwelling adults aged ≥65 years. Among participants who underwent MRI, we examined associations of ECG left atrial abnormality with brain infarcts and leukoaraiosis. P-wave terminal force in lead V1 was the primary measure of left atrial abnormality; P-wave area and duration were secondary predictors. We excluded participants with atrial fibrillation before or on their index ECG. Primary outcomes were incident infarcts and worsening leukoaraiosis from initial to follow-up scan ≈5 years later. Secondary outcomes were prevalent infarcts and degree of leukoaraiosis on initial MRI. Relative risk (RR) and linear regression models were adjusted for vascular risk factors. RESULTS: Among 3129 participants with ≥1 scan, each SD increase in P-wave terminal force in lead V1 was associated with a 0.05-point (95% confidence interval [CI], 0.0003-0.10) higher baseline white matter grade on a 10-point scale. P-wave terminal force in lead V1 was associated with prevalent infarcts of any type (RR per SD, 1.09; 95% CI, 1.04-1.16) and more so with prevalent nonlacunar infarcts (RR per SD, 1.22; 95% CI, 1.08-1.38). Among 1839 participants with 2 scans, P-wave terminal force in lead V1 was associated with worsening leukoaraiosis (RR per SD, 1.09; 95% CI, 1.01-1.18), but not with incident infarcts (RR per SD, 1.06; 95% CI, 0.93-1.20). Sensitivity analyses adjusting for incident atrial fibrillation found similar results. P-wave area and duration were not associated with outcomes. CONCLUSIONS: ECG left atrial abnormality is associated with vascular brain injury in the absence of documented atrial fibrillation.
Keywords: Aged; Atrial Fibrillation; Brain; Brain Infarction; Cardiovascular Diseases; Cerebrovascular Trauma; Electrocardiography; Female; Heart Atria; Heart Diseases; Humans; Linear Models; Magnetic Resonance Imaging; Male; Middle Aged; Predictive Value of Tests; Prospective Studies; Regression Analysis; Risk Factors; Treatment Outcome

Association of Cardiometabolic Multimorbidity With Mortality. - Di Angelantonio, Emanuele; Kaptoge, Stephen; Wormser, David; Willeit, Peter; Butterworth, Adam S; Bansal, Narinder; O'Keeffe, Linda M; Gao, Pei; Wood, Angela M; Burgess, Stephen; Freitag, Daniel F; Pennells, Lisa; et al. (JAMA, 2015)
IMPORTANCE: The prevalence of cardiometabolic multimorbidity is increasing. OBJECTIVE: To estimate reductions in life expectancy associated with cardiometabolic multimorbidity. DESIGN, SETTING, AND PARTICIPANTS: Age- and sex-adjusted mortality rates and hazard ratios (HRs) were calculated using individual participant data from the Emerging Risk Factors Collaboration (689,300 participants; 91 cohorts; years of baseline surveys: 1960-2007; latest mortality follow-up: April 2013; 128,843 deaths). The HRs from the Emerging Risk Factors Collaboration were compared with those from the UK Biobank (499,808 participants; years of baseline surveys: 2006-2010; latest mortality follow-up: November 2013; 7995 deaths). Cumulative survival was estimated by applying calculated age-specific HRs for mortality to contemporary US age-specific death rates. EXPOSURES: A history of 2 or more of the following: diabetes mellitus, stroke, myocardial infarction (MI). MAIN OUTCOMES AND MEASURES: All-cause mortality and estimated reductions in life expectancy. RESULTS: In participants in the Emerging Risk Factors Collaboration without a history of diabetes, stroke, or MI at baseline (reference group), the all-cause mortality rate adjusted to the age of 60 years was 6.8 per 1000 person-years. Mortality rates per 1000 person-years were 15.6 in participants with a history of diabetes, 16.1 in those with stroke, 16.8 in those with MI, 32.0 in those with both diabetes and MI, 32.5 in those with both diabetes and stroke, 32.8 in those with both stroke and MI, and 59.5 in those with diabetes, stroke, and MI. Compared with the reference group, the HRs for all-cause mortality were 1.9 (95% CI, 1.8-2.0) in participants with a history of diabetes, 2.1 (95% CI, 2.0-2.2) in those with stroke, 2.0 (95% CI, 1.9-2.2) in those with MI, 3.7 (95% CI, 3.3-4.1) in those with both diabetes and MI, 3.8 (95% CI, 3.5-4.2) in those with both diabetes and stroke, 3.5 (95% CI, 3.1-4.0) in those with both stroke and MI, and 6.9 (95% CI, 5.7-8.3) in those with diabetes, stroke, and MI. The HRs from the Emerging Risk Factors Collaboration were similar to those from the more recently recruited UK Biobank. The HRs were little changed after further adjustment for markers of established intermediate pathways (eg, levels of lipids and blood pressure) and lifestyle factors (eg, smoking, diet). At the age of 60 years, a history of any 2 of these conditions was associated with 12 years of reduced life expectancy and a history of all 3 of these conditions was associated with 15 years of reduced life expectancy. CONCLUSIONS AND RELEVANCE: Mortality associated with a history of diabetes, stroke, or MI was similar for each condition. Because any combination of these conditions was associated with multiplicative mortality risk, life expectancy was substantially lower in people with multimorbidity.
Keywords: Adult; Aged; Comorbidity; Diabetes Mellitus; Female; Humans; Life Expectancy; Male; Middle Aged; Mortality; Myocardial Infarction; Risk Factors; Stroke

Consumption of meat is associated with higher fasting glucose and insulin concentrations regardless of glucose and insulin genetic risk scores: a meta-analysis of 50,345 Caucasians. - Fretts, Amanda M; Follis, Jack L; Nettleton, Jennifer A; Lemaitre, Rozenn N; Ngwa, Julius S; Wojczynski, Mary K; Kalafati, Ioanna Panagiota; Varga, Tibor V; Frazier-Wood, Alexis C; Houston, Denise K; Lahti, Jari; Ericson, Ulrika; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Recent studies suggest that meat intake is associated with diabetes-related phenotypes. However, whether the associations of meat intake and glucose and insulin homeostasis are modified by genes related to glucose and insulin is unknown. OBJECTIVE: We investigated the associations of meat intake and the interaction of meat with genotype on fasting glucose and insulin concentrations in Caucasians free of diabetes mellitus. DESIGN: Fourteen studies that are part of the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium participated in the analysis. Data were provided for up to 50,345 participants. Using linear regression within studies and a fixed-effects meta-analysis across studies, we examined 1) the associations of processed meat and unprocessed red meat intake with fasting glucose and insulin concentrations; and 2) the interactions of processed meat and unprocessed red meat with genetic risk score related to fasting glucose or insulin resistance on fasting glucose and insulin concentrations. RESULTS: Processed meat was associated with higher fasting glucose, and unprocessed red meat was associated with both higher fasting glucose and fasting insulin concentrations after adjustment for potential confounders [not including body mass index (BMI)]. For every additional 50-g serving of processed meat per day, fasting glucose was 0.021 mmol/L (95% CI: 0.011, 0.030 mmol/L) higher. Every additional 100-g serving of unprocessed red meat per day was associated with a 0.037-mmol/L (95% CI: 0.023, 0.051-mmol/L) higher fasting glucose concentration and a 0.049-ln-pmol/L (95% CI: 0.035, 0.063-ln-pmol/L) higher fasting insulin concentration. After additional adjustment for BMI, observed associations were attenuated and no longer statistically significant. The association of processed meat and fasting insulin did not reach statistical significance after correction for multiple comparisons. Observed associations were not modified by genetic loci known to influence fasting glucose or insulin resistance. CONCLUSION: The association of higher fasting glucose and insulin concentrations with meat consumption was not modified by an index of glucose- and insulin-related single-nucleotide polymorphisms. Six of the participating studies are registered at clinicaltrials.gov as NCT0000513 (Atherosclerosis Risk in Communities), NCT00149435 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetics of Lipid Lowering Drugs and Diet Network), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Blood Glucose; Cohort Studies; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hyperglycemia; Hyperinsulinism; Insulin; Insulin Resistance; Insulin-Secreting Cells; Meat; Meat Products; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

DCAF4, a novel gene associated with leucocyte telomere length. - Mangino, Massimo; Christiansen, Lene; Stone, Rivka; Hunt, Steven C; Horvath, Kent; Eisenberg, Dan T A; Kimura, Masayuki; Petersen, Inge; Kark, Jeremy D; Herbig, Utz; Reiner, Alex P; Benetos, Athanase; et al. (J Med Genet, 2015)
BACKGROUND: Leucocyte telomere length (LTL), which is fashioned by multiple genes, has been linked to a host of human diseases, including sporadic melanoma. A number of genes associated with LTL have already been identified through genome-wide association studies. The main aim of this study was to establish whether DCAF4 (DDB1 and CUL4-associated factor 4) is associated with LTL. In addition, using ingenuity pathway analysis (IPA), we examined whether LTL-associated genes in the general population might partially explain the inherently longer LTL in patients with sporadic melanoma, the risk for which is increased with ultraviolet radiation (UVR). RESULTS: Genome-wide association (GWA) meta-analysis and de novo genotyping of 20 022 individuals revealed a novel association (p=6.4×10(-10)) between LTL and rs2535913, which lies within DCAF4. Notably, eQTL analysis showed that rs2535913 is associated with decline in DCAF4 expressions in both lymphoblastoid cells and sun-exposed skin (p=4.1×10(-3) and 2×10(-3), respectively). Moreover, IPA revealed that LTL-associated genes, derived from GWA meta-analysis (N=9190), are over-represented among genes engaged in melanoma pathways. Meeting increasingly stringent p value thresholds (p<0.05, <0.01, <0.005, <0.001) in the LTL-GWA meta-analysis, these genes were jointly over-represented for melanoma at p values ranging from 1.97×10(-169) to 3.42×10(-24). CONCLUSIONS: We uncovered a new locus associated with LTL in the general population. We also provided preliminary findings that suggest a link of LTL through genetic mechanisms with UVR and melanoma in the general population.
Keywords: Alleles; Carrier Proteins; Gene Expression Regulation; Genome-Wide Association Study; Humans; Leukocytes; Melanoma; Risk Factors; Telomere; Telomere Homeostasis

Drug-Gene Interactions of Antihypertensive Medications and Risk of Incident Cardiovascular Disease: A Pharmacogenomics Study from the CHARGE Consortium. - Bis, Joshua C; Sitlani, Colleen; Irvin, Ryan; Avery, Christy L; Smith, Albert Vernon; Sun, Fangui; Evans, Daniel S; Musani, Solomon K; Li, Xiaohui; Trompet, Stella; Krijthe, Bouwe P; Harris, Tamara B; et al. (PLoS One, 2015)
BACKGROUND: Hypertension is a major risk factor for a spectrum of cardiovascular diseases (CVD), including myocardial infarction, sudden death, and stroke. In the US, over 65 million people have high blood pressure and a large proportion of these individuals are prescribed antihypertensive medications. Although large long-term clinical trials conducted in the last several decades have identified a number of effective antihypertensive treatments that reduce the risk of future clinical complications, responses to therapy and protection from cardiovascular events vary among individuals. METHODS: Using a genome-wide association study among 21,267 participants with pharmaceutically treated hypertension, we explored the hypothesis that genetic variants might influence or modify the effectiveness of common antihypertensive therapies on the risk of major cardiovascular outcomes. The classes of drug treatments included angiotensin-converting enzyme inhibitors, beta-blockers, calcium channel blockers, and diuretics. In the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, each study performed array-based genome-wide genotyping, imputed to HapMap Phase II reference panels, and used additive genetic models in proportional hazards or logistic regression models to evaluate drug-gene interactions for each of four therapeutic drug classes. We used meta-analysis to combine study-specific interaction estimates for approximately 2 million single nucleotide polymorphisms (SNPs) in a discovery analysis among 15,375 European Ancestry participants (3,527 CVD cases) with targeted follow-up in a case-only study of 1,751 European Ancestry GenHAT participants as well as among 4,141 African-Americans (1,267 CVD cases). RESULTS: Although drug-SNP interactions were biologically plausible, exposures and outcomes were well measured, and power was sufficient to detect modest interactions, we did not identify any statistically significant interactions from the four antihypertensive therapy meta-analyses (Pinteraction > 5.0×10-8). Similarly, findings were null for meta-analyses restricted to 66 SNPs with significant main effects on coronary artery disease or blood pressure from large published genome-wide association studies (Pinteraction ≥ 0.01). Our results suggest that there are no major pharmacogenetic influences of common SNPs on the relationship between blood pressure medications and the risk of incident CVD.
Keywords: African Americans; Aged; Antihypertensive Agents; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Treatment Outcome

Exome sequencing identifies rare LDLR and APOA5 alleles conferring risk for myocardial infarction. - Do, Ron; Stitziel, Nathan O; Won, Hong-Hee; Jørgensen, Anders Berg; Duga, Stefano; Angelica Merlini, Pier; Kiezun, Adam; Farrall, Martin; Goel, Anuj; Zuk, Or; Guella, Illaria; Asselta, Rosanna; et al. (Nature, 2015)
Myocardial infarction (MI), a leading cause of death around the world, displays a complex pattern of inheritance. When MI occurs early in life, genetic inheritance is a major component to risk. Previously, rare mutations in low-density lipoprotein (LDL) genes have been shown to contribute to MI risk in individual families, whereas common variants at more than 45 loci have been associated with MI risk in the population. Here we evaluate how rare mutations contribute to early-onset MI risk in the population. We sequenced the protein-coding regions of 9,793 genomes from patients with MI at an early age (≤50 years in males and ≤60 years in females) along with MI-free controls. We identified two genes in which rare coding-sequence mutations were more frequent in MI cases versus controls at exome-wide significance. At low-density lipoprotein receptor (LDLR), carriers of rare non-synonymous mutations were at 4.2-fold increased risk for MI; carriers of null alleles at LDLR were at even higher risk (13-fold difference). Approximately 2% of early MI cases harbour a rare, damaging mutation in LDLR; this estimate is similar to one made more than 40 years ago using an analysis of total cholesterol. Among controls, about 1 in 217 carried an LDLR coding-sequence mutation and had plasma LDL cholesterol > 190 mg dl(-1). At apolipoprotein A-V (APOA5), carriers of rare non-synonymous mutations were at 2.2-fold increased risk for MI. When compared with non-carriers, LDLR mutation carriers had higher plasma LDL cholesterol, whereas APOA5 mutation carriers had higher plasma triglycerides. Recent evidence has connected MI risk with coding-sequence mutations at two genes functionally related to APOA5, namely lipoprotein lipase and apolipoprotein C-III (refs 18, 19). Combined, these observations suggest that, as well as LDL cholesterol, disordered metabolism of triglyceride-rich lipoproteins contributes to MI risk.
Keywords: Age Factors; Age of Onset; Alleles; Apolipoproteins A; Case-Control Studies; Cholesterol, LDL; Coronary Artery Disease; Exome; Female; Genetic Predisposition to Disease; Genetics, Population; Heterozygote; Humans; Male; Middle Aged; Mutation; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Receptors, LDL; Triglycerides; United States

Gene × dietary pattern interactions in obesity: analysis of up to 68 317 adults of European ancestry. - Nettleton, Jennifer A; Follis, Jack L; Ngwa, Julius S; Smith, Caren E; Ahmad, Shafqat; Tanaka, Toshiko; Wojczynski, Mary K; Voortman, Trudy; Lemaitre, Rozenn N; Kristiansson, Kati; Nuotio, Marja-Liisa; Houston, Denise K; et al. (Hum Mol Genet, 2015)
Obesity is highly heritable. Genetic variants showing robust associations with obesity traits have been identified through genome-wide association studies. We investigated whether a composite score representing healthy diet modifies associations of these variants with obesity traits. Totally, 32 body mass index (BMI)- and 14 waist-hip ratio (WHR)-associated single nucleotide polymorphisms were genotyped, and genetic risk scores (GRS) were calculated in 18 cohorts of European ancestry (n = 68 317). Diet score was calculated based on self-reported intakes of whole grains, fish, fruits, vegetables, nuts/seeds (favorable) and red/processed meats, sweets, sugar-sweetened beverages and fried potatoes (unfavorable). Multivariable adjusted, linear regression within each cohort followed by inverse variance-weighted, fixed-effects meta-analysis was used to characterize: (a) associations of each GRS with BMI and BMI-adjusted WHR and (b) diet score modification of genetic associations with BMI and BMI-adjusted WHR. Nominally significant interactions (P = 0.006-0.04) were observed between the diet score and WHR-GRS (but not BMI-GRS), two WHR loci (GRB14 rs10195252; LYPLAL1 rs4846567) and two BMI loci (LRRN6C rs10968576; MTIF3 rs4771122), for the respective BMI-adjusted WHR or BMI outcomes. Although the magnitudes of these select interactions were small, our data indicated that associations between genetic predisposition and obesity traits were stronger with a healthier diet. Our findings generate interesting hypotheses; however, experimental and functional studies are needed to determine their clinical relevance.
Keywords: Adult; Body Mass Index; Case-Control Studies; Diet, Western; Epistasis, Genetic; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Obesity; Polymorphism, Single Nucleotide

Genetic contributions to variation in general cognitive function: a meta-analysis of genome-wide association studies in the CHARGE consortium (N=53949). - Davies, G; Armstrong, N; Bis, J C; Bressler, J; Chouraki, V; Giddaluru, S; Hofer, E; Ibrahim-Verbaas, C A; Kirin, M; Lahti, J; van der Lee, S J; Le Hellard, S; et al. (Mol Psychiatry, 2015)
General cognitive function is substantially heritable across the human life course from adolescence to old age. We investigated the genetic contribution to variation in this important, health- and well-being-related trait in middle-aged and older adults. We conducted a meta-analysis of genome-wide association studies of 31 cohorts (N=53,949) in which the participants had undertaken multiple, diverse cognitive tests. A general cognitive function phenotype was tested for, and created in each cohort by principal component analysis. We report 13 genome-wide significant single-nucleotide polymorphism (SNP) associations in three genomic regions, 6q16.1, 14q12 and 19q13.32 (best SNP and closest gene, respectively: rs10457441, P=3.93 × 10(-9), MIR2113; rs17522122, P=2.55 × 10(-8), AKAP6; rs10119, P=5.67 × 10(-9), APOE/TOMM40). We report one gene-based significant association with the HMGN1 gene located on chromosome 21 (P=1 × 10(-6)). These genes have previously been associated with neuropsychiatric phenotypes. Meta-analysis results are consistent with a polygenic model of inheritance. To estimate SNP-based heritability, the genome-wide complex trait analysis procedure was applied to two large cohorts, the Atherosclerosis Risk in Communities Study (N=6617) and the Health and Retirement Study (N=5976). The proportion of phenotypic variation accounted for by all genotyped common SNPs was 29% (s.e.=5%) and 28% (s.e.=7%), respectively. Using polygenic prediction analysis, ~1.2% of the variance in general cognitive function was predicted in the Generation Scotland cohort (N=5487; P=1.5 × 10(-17)). In hypothesis-driven tests, there was significant association between general cognitive function and four genes previously associated with Alzheimer's disease: TOMM40, APOE, ABCG1 and MEF2C.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognition Disorders; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; HMGN1 Protein; Humans; Male; Middle Aged; Neuropsychological Tests; Phenotype; Polymorphism, Single Nucleotide; Scotland

Genome-wide meta-analysis identifies six novel loci associated with habitual coffee consumption. - Cornelis, M C; Byrne, E M; Esko, T; Nalls, M A; Ganna, A; Paynter, N; Monda, K L; Amin, N; Fischer, K; Renstrom, F; Ngwa, J S; Huikari, V; et al. (Mol Psychiatry, 2015)
Coffee, a major dietary source of caffeine, is among the most widely consumed beverages in the world and has received considerable attention regarding health risks and benefits. We conducted a genome-wide (GW) meta-analysis of predominately regular-type coffee consumption (cups per day) among up to 91,462 coffee consumers of European ancestry with top single-nucleotide polymorphisms (SNPs) followed-up in ~30 062 and 7964 coffee consumers of European and African-American ancestry, respectively. Studies from both stages were combined in a trans-ethnic meta-analysis. Confirmed loci were examined for putative functional and biological relevance. Eight loci, including six novel loci, met GW significance (log10Bayes factor (BF)>5.64) with per-allele effect sizes of 0.03-0.14 cups per day. Six are located in or near genes potentially involved in pharmacokinetics (ABCG2, AHR, POR and CYP1A2) and pharmacodynamics (BDNF and SLC6A4) of caffeine. Two map to GCKR and MLXIPL genes related to metabolic traits but lacking known roles in coffee consumption. Enhancer and promoter histone marks populate the regions of many confirmed loci and several potential regulatory SNPs are highly correlated with the lead SNP of each. SNP alleles near GCKR, MLXIPL, BDNF and CYP1A2 that were associated with higher coffee consumption have previously been associated with smoking initiation, higher adiposity and fasting insulin and glucose but lower blood pressure and favorable lipid, inflammatory and liver enzyme profiles (P<5 × 10(-8)).Our genetic findings among European and African-American adults reinforce the role of caffeine in mediating habitual coffee consumption and may point to molecular mechanisms underlying inter-individual variability in pharmacological and health effects of coffee.
Keywords: Adaptor Proteins, Signal Transducing; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Brain-Derived Neurotrophic Factor; Coffea; Cytochrome P-450 CYP1A2; Food Habits; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide

Genome-wide studies of verbal declarative memory in nondemented older people: the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Debette, Stephanie; Ibrahim Verbaas, Carla A; Bressler, Jan; Schuur, Maaike; Smith, Albert; Bis, Joshua C; Davies, Gail; Wolf, Christiane; Gudnason, Vilmundur; Chibnik, Lori B; Yang, Qiong; DeStefano, Anita L; et al. (Biol Psychiatry, 2015)
BACKGROUND: Memory performance in older persons can reflect genetic influences on cognitive function and dementing processes. We aimed to identify genetic contributions to verbal declarative memory in a community setting. METHODS: We conducted genome-wide association studies for paragraph or word list delayed recall in 19 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, comprising 29,076 dementia- and stroke-free individuals of European descent, aged ≥45 years. Replication of suggestive associations (p < 5 × 10(-6)) was sought in 10,617 participants of European descent, 3811 African-Americans, and 1561 young adults. RESULTS: rs4420638, near APOE, was associated with poorer delayed recall performance in discovery (p = 5.57 × 10(-10)) and replication cohorts (p = 5.65 × 10(-8)). This association was stronger for paragraph than word list delayed recall and in the oldest persons. Two associations with specific tests, in subsets of the total sample, reached genome-wide significance in combined analyses of discovery and replication (rs11074779 [HS3ST4], p = 3.11 × 10(-8), and rs6813517 [SPOCK3], p = 2.58 × 10(-8)) near genes involved in immune response. A genetic score combining 58 independent suggestive memory risk variants was associated with increasing Alzheimer disease pathology in 725 autopsy samples. Association of memory risk loci with gene expression in 138 human hippocampus samples showed cis-associations with WDR48 and CLDN5, both related to ubiquitin metabolism. CONCLUSIONS: This largest study to date exploring the genetics of memory function in ~40,000 older individuals revealed genome-wide associations and suggested an involvement of immune and ubiquitin pathways.
Keywords: Aged; Aged, 80 and over; Aging; Apolipoproteins E; Claudin-5; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Proteins; Proteoglycans; Regression Analysis; Sulfotransferases; Verbal Learning

GWAS of longevity in CHARGE consortium confirms APOE and FOXO3 candidacy. - Broer, Linda; Buchman, Aron S; Deelen, Joris; Evans, Daniel S; Faul, Jessica D; Lunetta, Kathryn L; Sebastiani, Paola; Smith, Jennifer A; Smith, Albert V; Tanaka, Toshiko; Yu, Lei; Arnold, Alice M; et al. (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: The genetic contribution to longevity in humans has been estimated to range from 15% to 25%. Only two genes, APOE and FOXO3, have shown association with longevity in multiple independent studies. METHODS: We conducted a meta-analysis of genome-wide association studies including 6,036 longevity cases, age ≥90 years, and 3,757 controls that died between ages 55 and 80 years. We additionally attempted to replicate earlier identified single nucleotide polymorphism (SNP) associations with longevity. RESULTS: In our meta-analysis, we found suggestive evidence for the association of SNPs near CADM2 (odds ratio [OR] = 0.81; p value = 9.66 × 10(-7)) and GRIK2 (odds ratio = 1.24; p value = 5.09 × 10(-8)) with longevity. When attempting to replicate findings earlier identified in genome-wide association studies, only the APOE locus consistently replicated. In an additional look-up of the candidate gene FOXO3, we found that an earlier identified variant shows a highly significant association with longevity when including published data with our meta-analysis (odds ratio = 1.17; p value = 1.85×10(-10)). CONCLUSIONS: We did not identify new genome-wide significant associations with longevity and did not replicate earlier findings except for APOE and FOXO3. Our inability to find new associations with survival to ages ≥90 years because longevity represents multiple complex traits with heterogeneous genetic underpinnings, or alternatively, that longevity may be regulated by rare variants that are not captured by standard genome-wide genotyping and imputation of common variants.
Keywords: Aged; Aged, 80 and over; Apolipoproteins E; Cell Adhesion Molecules; Cohort Studies; Female; Forkhead Box Protein O3; Forkhead Transcription Factors; Genome-Wide Association Study; Humans; Longevity; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Kainic Acid

Habitual sleep duration is associated with BMI and macronutrient intake and may be modified by CLOCK genetic variants. - Dashti, Hassan S; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Cade, Brian E; Gottlieb, Daniel J; Hruby, Adela; Jacques, Paul F; Lamon-Fava, Stefania; Richardson, Kris; Saxena, Richa; Scheer, Frank A J L; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Short sleep duration has been associated with greater risks of obesity, hypertension, diabetes, and cardiovascular disease. Also, common genetic variants in the human Circadian Locomotor Output Cycles Kaput (CLOCK) show associations with ghrelin and total energy intake. OBJECTIVES: We examined associations between habitual sleep duration, body mass index (BMI), and macronutrient intake and assessed whether CLOCK variants modify these associations. DESIGN: We conducted inverse-variance weighted, fixed-effect meta-analyses of results of adjusted associations of sleep duration and BMI and macronutrient intake as percentages of total energy as well as interactions with CLOCK variants from 9 cohort studies including up to 14,906 participants of European descent from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. RESULTS: We observed a significant association between sleep duration and lower BMI (β ± SE = 0.16 ± 0.04, P < 0.0001) in the overall sample; however, associations between sleep duration and relative macronutrient intake were evident in age- and sex-stratified analyses only. We observed a significant association between sleep duration and lower saturated fatty acid intake in younger (aged 20-64 y) adults (men: 0.11 ± 0.06%, P = 0.03; women: 0.10 ± 0.05%, P = 0.04) and with lower carbohydrate (-0.31 ± 0.12%, P < 0.01), higher total fat (0.18 ± 0.09%, P = 0.05), and higher PUFA (0.05 ± 0.02%, P = 0.02) intakes in older (aged 65-80 y) women. In addition, the following 2 nominally significant interactions were observed: between sleep duration and rs12649507 on PUFA intake and between sleep duration and rs6858749 on protein intake. CONCLUSIONS: Our results indicate that longer habitual sleep duration is associated with lower BMI and age- and sex-specific favorable dietary behaviors. Differences in the relative intake of specific macronutrients associated with short sleep duration could, at least in part, explain previously reported associations between short sleep duration and chronic metabolic abnormalities. In addition, the influence of obesity-associated CLOCK variants on the association between sleep duration and macronutrient intake suggests that longer habitual sleep duration could ameliorate the genetic predisposition to obesity via a favorable dietary profile.
Keywords: Adult; Body Mass Index; CLOCK Proteins; Cohort Studies; Cross-Sectional Studies; Diet; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Fatty Acids, Unsaturated; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Sleep; Young Adult

HMG-coenzyme A reductase inhibition, type 2 diabetes, and bodyweight: evidence from genetic analysis and randomised trials. - Swerdlow, Daniel I; Preiss, David; Kuchenbaecker, Karoline B; Holmes, Michael V; Engmann, Jorgen E L; Shah, Tina; Sofat, Reecha; Stender, Stefan; Johnson, Paul C D; Scott, Robert A; Leusink, Maarten; Verweij, Niek; et al. (Lancet, 2015)
BACKGROUND: Statins increase the risk of new-onset type 2 diabetes mellitus. We aimed to assess whether this increase in risk is a consequence of inhibition of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), the intended drug target. METHODS: We used single nucleotide polymorphisms in the HMGCR gene, rs17238484 (for the main analysis) and rs12916 (for a subsidiary analysis) as proxies for HMGCR inhibition by statins. We examined associations of these variants with plasma lipid, glucose, and insulin concentrations; bodyweight; waist circumference; and prevalent and incident type 2 diabetes. Study-specific effect estimates per copy of each LDL-lowering allele were pooled by meta-analysis. These findings were compared with a meta-analysis of new-onset type 2 diabetes and bodyweight change data from randomised trials of statin drugs. The effects of statins in each randomised trial were assessed using meta-analysis. FINDINGS: Data were available for up to 223 463 individuals from 43 genetic studies. Each additional rs17238484-G allele was associated with a mean 0·06 mmol/L (95% CI 0·05-0·07) lower LDL cholesterol and higher body weight (0·30 kg, 0·18-0·43), waist circumference (0·32 cm, 0·16-0·47), plasma insulin concentration (1·62%, 0·53-2·72), and plasma glucose concentration (0·23%, 0·02-0·44). The rs12916 SNP had similar effects on LDL cholesterol, bodyweight, and waist circumference. The rs17238484-G allele seemed to be associated with higher risk of type 2 diabetes (odds ratio [OR] per allele 1·02, 95% CI 1·00-1·05); the rs12916-T allele association was consistent (1·06, 1·03-1·09). In 129 170 individuals in randomised trials, statins lowered LDL cholesterol by 0·92 mmol/L (95% CI 0·18-1·67) at 1-year of follow-up, increased bodyweight by 0·24 kg (95% CI 0·10-0·38 in all trials; 0·33 kg, 95% CI 0·24-0·42 in placebo or standard care controlled trials and -0·15 kg, 95% CI -0·39 to 0·08 in intensive-dose vs moderate-dose trials) at a mean of 4·2 years (range 1·9-6·7) of follow-up, and increased the odds of new-onset type 2 diabetes (OR 1·12, 95% CI 1·06-1·18 in all trials; 1·11, 95% CI 1·03-1·20 in placebo or standard care controlled trials and 1·12, 95% CI 1·04-1·22 in intensive-dose vs moderate dose trials). INTERPRETATION: The increased risk of type 2 diabetes noted with statins is at least partially explained by HMGCR inhibition. FUNDING: The funding sources are cited at the end of the paper.
Keywords: Aged; Body Mass Index; Body Weight; Cholesterol, HDL; Cholesterol, LDL; Diabetes Mellitus, Type 2; Female; Genetic Testing; Humans; Hydroxymethylglutaryl CoA Reductases; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Randomized Controlled Trials as Topic; Risk Factors

Integrative pathway genomics of lung function and airflow obstruction. - Gharib, Sina A; Loth, Daan W; Soler Artigas, Maria; Birkland, Timothy P; Wilk, Jemma B; Wain, Louise V; Brody, Jennifer A; Obeidat, Ma'en; Hancock, Dana B; Tang, Wenbo; Rawal, Rajesh; Boezen, H Marike; et al. (Hum Mol Genet, 2015)
Chronic respiratory disorders are important contributors to the global burden of disease. Genome-wide association studies (GWASs) of lung function measures have identified several trait-associated loci, but explain only a modest portion of the phenotypic variability. We postulated that integrating pathway-based methods with GWASs of pulmonary function and airflow obstruction would identify a broader repertoire of genes and processes influencing these traits. We performed two independent GWASs of lung function and applied gene set enrichment analysis to one of the studies and validated the results using the second GWAS. We identified 131 significantly enriched gene sets associated with lung function and clustered them into larger biological modules involved in diverse processes including development, immunity, cell signaling, proliferation and arachidonic acid. We found that enrichment of gene sets was not driven by GWAS-significant variants or loci, but instead by those with less stringent association P-values. Next, we applied pathway enrichment analysis to a meta-analyzed GWAS of airflow obstruction. We identified several biologic modules that functionally overlapped with those associated with pulmonary function. However, differences were also noted, including enrichment of extracellular matrix (ECM) processes specifically in the airflow obstruction study. Network analysis of the ECM module implicated a candidate gene, matrix metalloproteinase 10 (MMP10), as a putative disease target. We used a knockout mouse model to functionally validate MMP10's role in influencing lung's susceptibility to cigarette smoke-induced emphysema. By integrating pathway analysis with population-based genomics, we unraveled biologic processes underlying pulmonary function traits and identified a candidate gene for obstructive lung disease.
Keywords: Airway Obstruction; Animals; Cell Proliferation; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Immune System; Lung; Male; Metabolic Networks and Pathways; Mice; Phenotype; Polymorphism, Single Nucleotide; Signal Transduction

Intermediate and long-term risk of new-onset heart failure after hospitalization for pneumonia in elderly adults. - Corrales-Medina, Vicente F; Taljaard, Monica; Yende, Sachin; Kronmal, Richard; Dwivedi, Girish; Newman, Anne B; Elkind, Mitchell S V; Lyles, Mary F; Chirinos, Julio A (Am Heart J, 2015)
BACKGROUND: Pneumonia is associated with high risk of heart failure (HF) in the short term (30 days) postinfection. Whether this association persists beyond this period is unknown. METHODS: We studied 5,613 elderly (≥65 years) adults enrolled in the Cardiovascular Health Study between 1989 and 1994 at 4 US communities. Participants had no clinical diagnosis of HF at enrollment, and they were followed up through December 2010. Hospitalizations for pneumonia were identified using validated International Classification of Disease Ninth Revision codes. A centralized committee adjudicated new-onset HF events. Using Cox regression, we estimated adjusted hazard ratios (HRs) of new-onset HF at different time intervals after hospitalization for pneumonia. RESULTS: A total of 652 participants hospitalized for pneumonia during follow-up were still alive and free of clinical diagnosis of HF by day 30 posthospitalization. Relative to the time of their hospitalization, new-onset HF occurred in 22 cases between 31 and 90 days (HR 6.9, 95% CI 4.46-10.63, P < .001), 14 cases between 91 days and 6 months (HR 3.2, 95% CI 1.88-5.50, P < .001), 20 cases between 6 months and 1 year (HR 2.6, 95% CI 1.64-4.04, P < .001), 76 cases between 1 and 5 years (HR 1.7, 95% CI 1.30-2.12, P < .001), and 71 cases after 5 years (HR 2.0, 95% CI 1.56-2.58, P < .001). Results were robust to sensitivity analyses using stringent definitions of pneumonia and extreme assumptions for potential informative censoring. CONCLUSION: Hospitalization for pneumonia is associated with increased risk of new-onset HF in the intermediate and long term. Studies should characterize the mechanisms of this association in order to prevent HF in elderly pneumonia survivors.
Keywords: Aged; Disease Progression; Female; Follow-Up Studies; Forecasting; Heart Failure; Hospitalization; Humans; Incidence; Inpatients; Male; Patient Readmission; Pneumonia; Proportional Hazards Models; Retrospective Studies; Risk Assessment; Risk Factors; Time Factors

Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: African Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide

Mendelian randomization of blood lipids for coronary heart disease. - Holmes, Michael V; Asselbergs, Folkert W; Palmer, Tom M; Drenos, Fotios; Lanktree, Matthew B; Nelson, Christopher P; Dale, Caroline E; Padmanabhan, Sandosh; Finan, Chris; Swerdlow, Daniel I; Tragante, Vinicius; van Iperen, Erik P A; et al. (Eur Heart J, 2015)
AIMS: To investigate the causal role of high-density lipoprotein cholesterol (HDL-C) and triglycerides in coronary heart disease (CHD) using multiple instrumental variables for Mendelian randomization. METHODS AND RESULTS: We developed weighted allele scores based on single nucleotide polymorphisms (SNPs) with established associations with HDL-C, triglycerides, and low-density lipoprotein cholesterol (LDL-C). For each trait, we constructed two scores. The first was unrestricted, including all independent SNPs associated with the lipid trait identified from a prior meta-analysis (threshold P < 2 × 10(-6)); and the second a restricted score, filtered to remove any SNPs also associated with either of the other two lipid traits at P ≤ 0.01. Mendelian randomization meta-analyses were conducted in 17 studies including 62,199 participants and 12,099 CHD events. Both the unrestricted and restricted allele scores for LDL-C (42 and 19 SNPs, respectively) associated with CHD. For HDL-C, the unrestricted allele score (48 SNPs) was associated with CHD (OR: 0.53; 95% CI: 0.40, 0.70), per 1 mmol/L higher HDL-C, but neither the restricted allele score (19 SNPs; OR: 0.91; 95% CI: 0.42, 1.98) nor the unrestricted HDL-C allele score adjusted for triglycerides, LDL-C, or statin use (OR: 0.81; 95% CI: 0.44, 1.46) showed a robust association. For triglycerides, the unrestricted allele score (67 SNPs) and the restricted allele score (27 SNPs) were both associated with CHD (OR: 1.62; 95% CI: 1.24, 2.11 and 1.61; 95% CI: 1.00, 2.59, respectively) per 1-log unit increment. However, the unrestricted triglyceride score adjusted for HDL-C, LDL-C, and statin use gave an OR for CHD of 1.01 (95% CI: 0.59, 1.75). CONCLUSION: The genetic findings support a causal effect of triglycerides on CHD risk, but a causal role for HDL-C, though possible, remains less certain.
Keywords: Case-Control Studies; Cholesterol, HDL; Coronary Artery Disease; Female; Gene Frequency; Genotype; Genotyping Techniques; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Polymorphism, Single Nucleotide; Risk Assessment; Triglycerides

Meta-analysis of 65,734 individuals identifies TSPAN15 and SLC44A2 as two susceptibility loci for venous thromboembolism. - Germain, Marine; Chasman, Daniel I; de Haan, Hugoline; Tang, Weihong; Lindström, Sara; Weng, Lu-Chen; de Andrade, Mariza; de Visser, Marieke C H; Wiggins, Kerri L; Suchon, Pierre; Saut, Noémie; Smadja, David M; et al. (Am J Hum Genet, 2015)
Venous thromboembolism (VTE), the third leading cause of cardiovascular mortality, is a complex thrombotic disorder with environmental and genetic determinants. Although several genetic variants have been found associated with VTE, they explain a minor proportion of VTE risk in cases. We undertook a meta-analysis of genome-wide association studies (GWASs) to identify additional VTE susceptibility genes. Twelve GWASs totaling 7,507 VTE case subjects and 52,632 control subjects formed our discovery stage where 6,751,884 SNPs were tested for association with VTE. Nine loci reached the genome-wide significance level of 5 × 10(-8) including six already known to associate with VTE (ABO, F2, F5, F11, FGG, and PROCR) and three unsuspected loci. SNPs mapping to these latter were selected for replication in three independent case-control studies totaling 3,009 VTE-affected individuals and 2,586 control subjects. This strategy led to the identification and replication of two VTE-associated loci, TSPAN15 and SLC44A2, with lead risk alleles associated with odds ratio for disease of 1.31 (p = 1.67 × 10(-16)) and 1.21 (p = 2.75 × 10(-15)), respectively. The lead SNP at the TSPAN15 locus is the intronic rs78707713 and the lead SLC44A2 SNP is the non-synonymous rs2288904 previously shown to associate with transfusion-related acute lung injury. We further showed that these two variants did not associate with known hemostatic plasma markers. TSPAN15 and SLC44A2 do not belong to conventional pathways for thrombosis and have not been associated to other cardiovascular diseases nor related quantitative biomarkers. Our findings uncovered unexpected actors of VTE etiology and pave the way for novel mechanistic concepts of VTE pathophysiology.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Membrane Glycoproteins; Membrane Transport Proteins; Odds Ratio; Tetraspanins; Venous Thromboembolism

Meta-Analysis of Genome-Wide Association Studies Identifies Genetic Risk Factors for Stroke in African Americans. - Carty, Cara L; Keene, Keith L; Cheng, Yu-Ching; Meschia, James F; Chen, Wei-Min; Nalls, Mike; Bis, Joshua C; Kittner, Steven J; Rich, Stephen S; Tajuddin, Salman; Zonderman, Alan B; Evans, Michele K; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: The majority of genome-wide association studies (GWAS) of stroke have focused on European-ancestry populations; however, none has been conducted in African Americans, despite the disproportionately high burden of stroke in this population. The Consortium of Minority Population Genome-Wide Association Studies of Stroke (COMPASS) was established to identify stroke susceptibility loci in minority populations. METHODS: Using METAL, we conducted meta-analyses of GWAS in 14 746 African Americans (1365 ischemic and 1592 total stroke cases) from COMPASS, and tested genetic variants with P<10(-6) for validation in METASTROKE, a consortium of ischemic stroke genetic studies in European-ancestry populations. We also evaluated stroke loci previously identified in European-ancestry populations. RESULTS: The 15q21.3 locus linked with lipid levels and hypertension was associated with total stroke (rs4471613; P=3.9×10(-8)) in African Americans. Nominal associations (P<10(-6)) for total or ischemic stroke were observed for 18 variants in or near genes implicated in cell cycle/mRNA presplicing (PTPRG, CDC5L), platelet function (HPS4), blood-brain barrier permeability (CLDN17), immune response (ELTD1, WDFY4, and IL1F10-IL1RN), and histone modification (HDAC9). Two of these loci achieved nominal significance in METASTROKE: 5q35.2 (P=0.03), and 1p31.1 (P=0.018). Four of 7 previously reported ischemic stroke loci (PITX2, HDAC9, CDKN2A/CDKN2B, and ZFHX3) were nominally associated (P<0.05) with stroke in COMPASS. CONCLUSIONS: We identified a novel genetic variant associated with total stroke in African Americans and found that ischemic stroke loci identified in European-ancestry populations may also be relevant for African Americans. Our findings support investigation of diverse populations to identify and characterize genetic risk factors, and the importance of shared genetic risk across populations.
Keywords: African Americans; Case-Control Studies; Cohort Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors; Stroke

A Meta-analysis of the Association of Estimated GFR, Albuminuria, Diabetes Mellitus, and Hypertension With Acute Kidney Injury. - James, Matthew T; Grams, Morgan E; Woodward, Mark; Elley, C Raina; Green, Jamie A; Wheeler, David C; de Jong, Paul; Gansevoort, Ron T; Levey, Andrew S; Warnock, David G; Sarnak, Mark J (Am J Kidney Dis, 2015)
BACKGROUND: Diabetes mellitus and hypertension are risk factors for acute kidney injury (AKI). Whether estimated glomerular filtration rate (eGFR) and urine albumin-creatinine ratio (ACR) remain risk factors for AKI in the presence and absence of these conditions is uncertain. STUDY DESIGN: Meta-analysis of cohort studies. SETTING & POPULATION: 8 general-population (1,285,045 participants) and 5 chronic kidney disease (CKD; 79,519 participants) cohorts. SELECTION CRITERIA FOR STUDIES: Cohorts participating in the CKD Prognosis Consortium. PREDICTORS: Diabetes and hypertension status, eGFR by the 2009 CKD Epidemiology Collaboration creatinine equation, urine ACR, and interactions. OUTCOME: Hospitalization with AKI, using Cox proportional hazards models to estimate HRs of AKI and random-effects meta-analysis to pool results. RESULTS: During a mean follow-up of 4 years, there were 16,480 episodes of AKI in the general-population and 2,087 episodes in the CKD cohorts. Low eGFRs and high ACRs were associated with higher risks of AKI in individuals with or without diabetes and with or without hypertension. When compared to a common reference of eGFR of 80mL/min/1.73m(2) in nondiabetic patients, HRs for AKI were generally higher in diabetic patients at any level of eGFR. The same was true for diabetic patients at all levels of ACR compared with nondiabetic patients. The risk gradient for AKI with lower eGFRs was greater in those without diabetes than with diabetes, but similar with higher ACRs in those without versus with diabetes. Those with hypertension had a higher risk of AKI at eGFRs>60mL/min/1.73m(2) than those without hypertension. However, risk gradients for AKI with both lower eGFRs and higher ACRs were greater for those without than with hypertension. LIMITATIONS: AKI identified by diagnostic code. CONCLUSIONS: Lower eGFRs and higher ACRs are associated with higher risks of AKI among individuals with or without either diabetes or hypertension.
Keywords: Acute Kidney Injury; Adult; Aged; Comorbidity; Diabetes Mellitus; Disease Progression; Female; Glomerular Filtration Rate; Humans; Hypertension; Incidence; Kidney Failure, Chronic; Male; Middle Aged; Prognosis; Renal Insufficiency, Chronic

Multiethnic genome-wide association study of cerebral white matter hyperintensities on MRI. - Verhaaren, Benjamin F J; Debette, Stephanie; Bis, Joshua C; Smith, Jennifer A; Ikram, M Kamran; Adams, Hieab H; Beecham, Ashley H; Rajan, Kumar B; Lopez, Lorna M; Barral, Sandra; van Buchem, Mark A; van der Grond, Jeroen; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: The burden of cerebral white matter hyperintensities (WMH) is associated with an increased risk of stroke, dementia, and death. WMH are highly heritable, but their genetic underpinnings are incompletely characterized. To identify novel genetic variants influencing WMH burden, we conducted a meta-analysis of multiethnic genome-wide association studies. METHODS AND RESULTS: We included 21 079 middle-aged to elderly individuals from 29 population-based cohorts, who were free of dementia and stroke and were of European (n=17 936), African (n=1943), Hispanic (n=795), and Asian (n=405) descent. WMH burden was quantified on MRI either by a validated automated segmentation method or a validated visual grading scale. Genotype data in each study were imputed to the 1000 Genomes reference. Within each ethnic group, we investigated the relationship between each single-nucleotide polymorphism and WMH burden using a linear regression model adjusted for age, sex, intracranial volume, and principal components of ancestry. A meta-analysis was conducted for each ethnicity separately and for the combined sample. In the European descent samples, we confirmed a previously known locus on chr17q25 (P=2.7×10(-19)) and identified novel loci on chr10q24 (P=1.6×10(-9)) and chr2p21 (P=4.4×10(-8)). In the multiethnic meta-analysis, we identified 2 additional loci, on chr1q22 (P=2.0×10(-8)) and chr2p16 (P=1.5×10(-8)). The novel loci contained genes that have been implicated in Alzheimer disease (chr2p21 and chr10q24), intracerebral hemorrhage (chr1q22), neuroinflammatory diseases (chr2p21), and glioma (chr10q24 and chr2p16). CONCLUSIONS: We identified 4 novel genetic loci that implicate inflammatory and glial proliferative pathways in the development of WMH in addition to previously proposed ischemic mechanisms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human; Continental Population Groups; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Models, Genetic; Stroke; White Matter

Novel loci associated with usual sleep duration: the CHARGE Consortium Genome-Wide Association Study. - Gottlieb, D J; Hek, K; Chen, T-H; Watson, N F; Eiriksdottir, G; Byrne, E M; Cornelis, M; Warby, S C; Bandinelli, S; Cherkas, L; Evans, D S; Grabe, H J; et al. (Mol Psychiatry, 2015)
Usual sleep duration is a heritable trait correlated with psychiatric morbidity, cardiometabolic disease and mortality, although little is known about the genetic variants influencing this trait. A genome-wide association study (GWAS) of usual sleep duration was conducted using 18 population-based cohorts totaling 47 180 individuals of European ancestry. Genome-wide significant association was identified at two loci. The strongest is located on chromosome 2, in an intergenic region 35- to 80-kb upstream from the thyroid-specific transcription factor PAX8 (lowest P=1.1 × 10(-9)). This finding was replicated in an African-American sample of 4771 individuals (lowest P=9.3 × 10(-4)). The strongest combined association was at rs1823125 (P=1.5 × 10(-10), minor allele frequency 0.26 in the discovery sample, 0.12 in the replication sample), with each copy of the minor allele associated with a sleep duration 3.1 min longer per night. The alleles associated with longer sleep duration were associated in previous GWAS with a more favorable metabolic profile and a lower risk of attention deficit hyperactivity disorder. Understanding the mechanisms underlying these associations may help elucidate biological mechanisms influencing sleep duration and its association with psychiatric, metabolic and cardiovascular disease.
Keywords: Adult; African Americans; Aged; Dyssomnias; European Continental Ancestry Group; Female; Genetic Association Studies; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Self Report; Sleep

Physical activity, body mass index, and brain atrophy in Alzheimer's disease. - Boyle, Christina P; Raji, Cyrus A; Erickson, Kirk I; Lopez, Oscar L; Becker, James T; Gach, H Michael; Longstreth, W T; Teverovskiy, Leonid; Kuller, Lewis H; Carmichael, Owen T; Thompson, Paul M (Neurobiol Aging, 2015)
The purpose of this study was to use a novel imaging biomarker to assess associations between physical activity (PA), body mass index (BMI), and brain structure in normal aging, mild cognitive impairment, and Alzheimer's dementia. We studied 963 participants (mean age: 74.1 ± 4.4 years) from the multisite Cardiovascular Health Study including healthy controls (n = 724), Alzheimer's dementia patients (n = 104), and people with mild cognitive impairment (n = 135). Volumetric brain images were processed using tensor-based morphometry to analyze regional brain volumes. We regressed the local brain tissue volume on reported PA and computed BMI, and performed conjunction analyses using both variables. Covariates included age, sex, and study site. PA was independently associated with greater whole brain and regional brain volumes and reduced ventricular dilation. People with higher BMI had lower whole brain and regional brain volumes. A PA-BMI conjunction analysis showed brain preservation with PA and volume loss with increased BMI in overlapping brain regions. In one of the largest voxel-based cross-sectional studies to date, PA and lower BMI may be beneficial to the brain across the spectrum of aging and neurodegeneration.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Atrophy; Biomarkers; Body Mass Index; Brain; Cognitive Dysfunction; Cross-Sectional Studies; Diffusion Magnetic Resonance Imaging; Female; Humans; Magnetic Resonance Imaging; Male; Motor Activity; Neuroimaging

Potassium and glucose measures in older adults: the Cardiovascular Health Study. - Chatterjee, Ranee; Biggs, Mary L; de Boer, Ian H; Brancati, Frederick L; Svetkey, Laura P; Barzilay, Joshua; Djoussé, Luc; Ix, Joachim H; Kizer, Jorge R; Siscovick, David S; Mozaffarian, Dariush; Edelman, David; et al. (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: We sought to determine the impacts of serum and dietary potassium measures on glucose metabolism and diabetes risk in older adults. METHODS: Among participants of the Cardiovascular Health Study, a community-based cohort of older American adults, we examined a) cross-sectional associations between potassium and measures of insulin sensitivity and secretion estimated from oral glucose tolerance tests and b) longitudinal associations of serum and dietary potassium with diabetes risk. RESULTS: Among 4,754 participants aged ≥65 years at baseline, there were 445 cases of incident diabetes during a median follow-up of 12 years. In multivariate models, baseline serum and dietary potassium were both associated with lower insulin sensitivity and greater insulin secretion. Compared with those with a serum potassium ≥4.5 mEq/L, participants with a serum potassium <4.0mEq/L had an adjusted mean difference in Matsuda insulin sensitivity index of -0.18 (-0.39, 0.02). Compared with those in the highest quartile, participants in the lowest quartile of dietary potassium intake had a corresponding adjusted mean difference in Matsuda insulin sensitivity index of -0.61 (-0.94, -0.29). In multivariate models, neither serum nor dietary potassium intake was associated with long-term diabetes risk. CONCLUSIONS: Although we did not identify serum and dietary potassium as risk factors for incident diabetes in older adults, results from cross-sectional analyses suggest that both may be associated with increased insulin resistance. This relationship with insulin resistance needs to be confirmed, and its importance on diabetes risk, cardiovascular risk, and conditions specific to older adults should be determined as well.
Keywords: Aged; Blood Glucose; Cohort Studies; Cross-Sectional Studies; Diabetes Mellitus; Female; Humans; Insulin; Insulin Resistance; Longitudinal Studies; Male; Multivariate Analysis; Potassium; Potassium, Dietary; Risk Factors; United States

Race/Ethnic Differences in the Associations of the Framingham Risk Factors with Carotid IMT and Cardiovascular Events. - Gijsberts, Crystel M; Groenewegen, Karlijn A; Hoefer, Imo E; Eijkemans, Marinus J C; Asselbergs, Folkert W; Anderson, Todd J; Britton, Annie R; Dekker, Jacqueline M; Engström, Gunnar; Evans, Greg W; de Graaf, Jacqueline; Grobbee, Diederick E; et al. (PLoS One, 2015)
BACKGROUND: Clinical manifestations and outcomes of atherosclerotic disease differ between ethnic groups. In addition, the prevalence of risk factors is substantially different. Primary prevention programs are based on data derived from almost exclusively White people. We investigated how race/ethnic differences modify the associations of established risk factors with atherosclerosis and cardiovascular events. METHODS: We used data from an ongoing individual participant meta-analysis involving 17 population-based cohorts worldwide. We selected 60,211 participants without cardiovascular disease at baseline with available data on ethnicity (White, Black, Asian or Hispanic). We generated a multivariable linear regression model containing risk factors and ethnicity predicting mean common carotid intima-media thickness (CIMT) and a multivariable Cox regression model predicting myocardial infarction or stroke. For each risk factor we assessed how the association with the preclinical and clinical measures of cardiovascular atherosclerotic disease was affected by ethnicity. RESULTS: Ethnicity appeared to significantly modify the associations between risk factors and CIMT and cardiovascular events. The association between age and CIMT was weaker in Blacks and Hispanics. Systolic blood pressure associated more strongly with CIMT in Asians. HDL cholesterol and smoking associated less with CIMT in Blacks. Furthermore, the association of age and total cholesterol levels with the occurrence of cardiovascular events differed between Blacks and Whites. CONCLUSION: The magnitude of associations between risk factors and the presence of atherosclerotic disease differs between race/ethnic groups. These subtle, yet significant differences provide insight in the etiology of cardiovascular disease among race/ethnic groups. These insights aid the race/ethnic-specific implementation of primary prevention.
Keywords: Adult; Age Distribution; Aged; Carotid Artery Diseases; Carotid Intima-Media Thickness; Cholesterol, HDL; Cholesterol, LDL; Comorbidity; Continental Population Groups; Diabetes Mellitus; Dyslipidemias; Ethnic Groups; Female; Follow-Up Studies; Global Health; Humans; Hypertension; Incidence; Linear Models; Male; Middle Aged; Myocardial Infarction; Prevalence; Proportional Hazards Models; Risk Factors; Smoking; Stroke

Subclinical Hypothyroidism and the Risk of Stroke Events and Fatal Stroke: An Individual Participant Data Analysis. - Chaker, Layal; Baumgartner, Christine; den Elzen, Wendy P J; Ikram, M Arfan; Blum, Manuel R; Collet, Tinh-Hai; Bakker, Stephan J L; Dehghan, Abbas; Drechsler, Christiane; Luben, Robert N; Hofman, Albert; Portegies, Marileen L P; et al. (J Clin Endocrinol Metab, 2015)
OBJECTIVE: The objective was to determine the risk of stroke associated with subclinical hypothyroidism. DATA SOURCES AND STUDY SELECTION: Published prospective cohort studies were identified through a systematic search through November 2013 without restrictions in several databases. Unpublished studies were identified through the Thyroid Studies Collaboration. We collected individual participant data on thyroid function and stroke outcome. Euthyroidism was defined as TSH levels of 0.45-4.49 mIU/L, and subclinical hypothyroidism was defined as TSH levels of 4.5-19.9 mIU/L with normal T4 levels. DATA EXTRACTION AND SYNTHESIS: We collected individual participant data on 47 573 adults (3451 subclinical hypothyroidism) from 17 cohorts and followed up from 1972-2014 (489 192 person-years). Age- and sex-adjusted pooled hazard ratios (HRs) for participants with subclinical hypothyroidism compared to euthyroidism were 1.05 (95% confidence interval [CI], 0.91-1.21) for stroke events (combined fatal and nonfatal stroke) and 1.07 (95% CI, 0.80-1.42) for fatal stroke. Stratified by age, the HR for stroke events was 3.32 (95% CI, 1.25-8.80) for individuals aged 18-49 years. There was an increased risk of fatal stroke in the age groups 18-49 and 50-64 years, with a HR of 4.22 (95% CI, 1.08-16.55) and 2.86 (95% CI, 1.31-6.26), respectively (p trend 0.04). We found no increased risk for those 65-79 years old (HR, 1.00; 95% CI, 0.86-1.18) or ≥ 80 years old (HR, 1.31; 95% CI, 0.79-2.18). There was a pattern of increased risk of fatal stroke with higher TSH concentrations. CONCLUSIONS: Although no overall effect of subclinical hypothyroidism on stroke could be demonstrated, an increased risk in subjects younger than 65 years and those with higher TSH concentrations was observed.
Keywords: Adult; Asymptomatic Diseases; Female; Humans; Hypothyroidism; Incidence; Male; Risk Factors; Stroke; Thyrotropin

Subclinical thyroid dysfunction and fracture risk: a meta-analysis. - Blum, Manuel R; Bauer, Douglas C; Collet, Tinh-Hai; Fink, Howard A; Cappola, Anne R; da Costa, Bruno R; Wirth, Christina D; Peeters, Robin P; Asvold, Bjørn O; den Elzen, Wendy P J; Luben, Robert N; Imaizumi, Misa; et al. (JAMA, 2015)
IMPORTANCE: Associations between subclinical thyroid dysfunction and fractures are unclear and clinical trials are lacking. OBJECTIVE: To assess the association of subclinical thyroid dysfunction with hip, nonspine, spine, or any fractures. DATA SOURCES AND STUDY SELECTION: The databases of MEDLINE and EMBASE (inception to March 26, 2015) were searched without language restrictions for prospective cohort studies with thyroid function data and subsequent fractures. DATA EXTRACTION: Individual participant data were obtained from 13 prospective cohorts in the United States, Europe, Australia, and Japan. Levels of thyroid function were defined as euthyroidism (thyroid-stimulating hormone [TSH], 0.45-4.49 mIU/L), subclinical hyperthyroidism (TSH <0.45 mIU/L), and subclinical hypothyroidism (TSH ≥4.50-19.99 mIU/L) with normal thyroxine concentrations. MAIN OUTCOME AND MEASURES: The primary outcome was hip fracture. Any fractures, nonspine fractures, and clinical spine fractures were secondary outcomes. RESULTS: Among 70,298 participants, 4092 (5.8%) had subclinical hypothyroidism and 2219 (3.2%) had subclinical hyperthyroidism. During 762,401 person-years of follow-up, hip fracture occurred in 2975 participants (4.6%; 12 studies), any fracture in 2528 participants (9.0%; 8 studies), nonspine fracture in 2018 participants (8.4%; 8 studies), and spine fracture in 296 participants (1.3%; 6 studies). In age- and sex-adjusted analyses, the hazard ratio (HR) for subclinical hyperthyroidism vs euthyroidism was 1.36 for hip fracture (95% CI, 1.13-1.64; 146 events in 2082 participants vs 2534 in 56,471); for any fracture, HR was 1.28 (95% CI, 1.06-1.53; 121 events in 888 participants vs 2203 in 25,901); for nonspine fracture, HR was 1.16 (95% CI, 0.95-1.41; 107 events in 946 participants vs 1745 in 21,722); and for spine fracture, HR was 1.51 (95% CI, 0.93-2.45; 17 events in 732 participants vs 255 in 20,328). Lower TSH was associated with higher fracture rates: for TSH of less than 0.10 mIU/L, HR was 1.61 for hip fracture (95% CI, 1.21-2.15; 47 events in 510 participants); for any fracture, HR was 1.98 (95% CI, 1.41-2.78; 44 events in 212 participants); for nonspine fracture, HR was 1.61 (95% CI, 0.96-2.71; 32 events in 185 participants); and for spine fracture, HR was 3.57 (95% CI, 1.88-6.78; 8 events in 162 participants). Risks were similar after adjustment for other fracture risk factors. Endogenous subclinical hyperthyroidism (excluding thyroid medication users) was associated with HRs of 1.52 (95% CI, 1.19-1.93) for hip fracture, 1.42 (95% CI, 1.16-1.74) for any fracture, and 1.74 (95% CI, 1.01-2.99) for spine fracture. No association was found between subclinical hypothyroidism and fracture risk. CONCLUSIONS AND RELEVANCE: Subclinical hyperthyroidism was associated with an increased risk of hip and other fractures, particularly among those with TSH levels of less than 0.10 mIU/L and those with endogenous subclinical hyperthyroidism. Further study is needed to determine whether treating subclinical hyperthyroidism can prevent fractures.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Female; Fractures, Bone; Hip Fractures; Humans; Hyperthyroidism; Hypothyroidism; Male; Middle Aged; Risk Factors; Spinal Fractures; Thyrotropin; Young Adult

Thyroid function within the normal range and risk of coronary heart disease: an individual participant data analysis of 14 cohorts. - Asvold, Bjørn O; Vatten, Lars J; Bjøro, Trine; Bauer, Douglas C; Bremner, Alexandra; Cappola, Anne R; Ceresini, Graziano; den Elzen, Wendy P J; Ferrucci, Luigi; Franco, Oscar H; Franklyn, Jayne A; Gussekloo, Jacobijn; et al. (JAMA Intern Med, 2015)
IMPORTANCE: Some experts suggest that serum thyrotropin levels in the upper part of the current reference range should be considered abnormal, an approach that would reclassify many individuals as having mild hypothyroidism. Health hazards associated with such thyrotropin levels are poorly documented, but conflicting evidence suggests that thyrotropin levels in the upper part of the reference range may be associated with an increased risk of coronary heart disease (CHD). OBJECTIVE: To assess the association between differences in thyroid function within the reference range and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: Individual participant data analysis of 14 cohorts with baseline examinations between July 1972 and April 2002 and with median follow-up ranging from 3.3 to 20.0 years. Participants included 55,412 individuals with serum thyrotropin levels of 0.45 to 4.49 mIU/L and no previously known thyroid or cardiovascular disease at baseline. EXPOSURES: Thyroid function as expressed by serum thyrotropin levels at baseline. MAIN OUTCOMES AND MEASURES: Hazard ratios (HRs) of CHD mortality and CHD events according to thyrotropin levels after adjustment for age, sex, and smoking status. RESULTS: Among 55,412 individuals, 1813 people (3.3%) died of CHD during 643,183 person-years of follow-up. In 10 cohorts with information on both nonfatal and fatal CHD events, 4666 of 48,875 individuals (9.5%) experienced a first-time CHD event during 533,408 person-years of follow-up. For each 1-mIU/L higher thyrotropin level, the HR was 0.97 (95% CI, 0.90-1.04) for CHD mortality and 1.00 (95% CI, 0.97-1.03) for a first-time CHD event. Similarly, in analyses by categories of thyrotropin, the HRs of CHD mortality (0.94 [95% CI, 0.74-1.20]) and CHD events (0.97 [95% CI, 0.83-1.13]) were similar among participants with the highest (3.50-4.49 mIU/L) compared with the lowest (0.45-1.49 mIU/L) thyrotropin levels. Subgroup analyses by sex and age group yielded similar results. CONCLUSIONS AND RELEVANCE: Thyrotropin levels within the reference range are not associated with risk of CHD events or CHD mortality. This finding suggests that differences in thyroid function within the population reference range do not influence the risk of CHD. Increased CHD risk does not appear to be a reason for lowering the upper thyrotropin reference limit.
Keywords: Cohort Studies; Coronary Disease; Humans; Hypothyroidism; Thyrotropin

Voxel Level Survival Analysis of Grey Matter Volume and Incident Mild Cognitive Impairment or Alzheimer's Disease. - Zeifman, Lubov E; Eddy, William F; Lopez, Oscar L; Kuller, Lewis H; Raji, Cyrus; Thompson, Paul M; Becker, James T (J Alzheimers Dis, 2015)
The purpose of this study was to identify, at the voxel level, brain regions associated with the time to develop mild cognitive impairment (MCI) or Alzheimer's disease (AD) from normal cognition. We analyzed incident MCI (n = 58) or AD (n = 151) in 292 cognitively normal participants in the Cardiovascular Health Study-Cognition Study (mean age = 79.2 ± 3.6 years). We used segmented, modulated grey matter maps from 3D (spoiled gradient echo) MRI scans obtained in 1998/99 (with clinical follow-up through 2012) that were smoothed with a 3-D 4 mm Gaussian filter. We fit approximately 1.92 million voxel-level Cox proportional hazard models to examine the grey matter volume effect on time to event, adjusting for age, sex, and diabetes. We used the significance threshold of p <  0.005 with contiguity threshold of at least 68 voxels (false detection probability <2.5×10 -8). Areas within the mesial temporal lobe (MTL), anterior temporal lobe, hippocampus, and posterior cingulate gyrus were associated with time to MCI or AD. The presence of white matter lesions (a marker of small vessel disease in the brain) was associated with the volumes of the MTL and precuneus; MRI-identified infarcts also predicted MTL volume. These findings are important because we identified critical brain regions that predict a person's increased likelihood of developing MCI or AD over a decade prior to the onset of clinical symptoms; these critical brain regions were themselves affected by the presence of vascular disease.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Chi-Square Distribution; Disease Progression; Female; Gray Matter; Humans; Incidence; Magnetic Resonance Imaging; Male; Mild Cognitive Impairment; Neuropsychological Tests; Psychiatric Status Rating Scales; Survival Analysis

-3 Polyunsaturated Fatty Acid Biomarkers and Coronary Heart Disease: Pooling Project of 19 Cohort Studies - Del Gobbo, L. C.; Imamura, F.; Aslibekyan, S.; Marklund, M.; Virtanen, J. K.; Wennberg, M.; Yakoob, M. Y.; Chiuve, S. E.; Dela Cruz, L.; Frazier-Wood, A. C.; Fretts, A. M.; Guallar, E.; et al. (JAMA Intern Med, 2016)
-3 polyunsaturated fatty acids for primary prevention of coronary heart disease (CHD) remains controversial. Most prior longitudinal studies evaluated self-reported consumption rather than biomarkers.\ -3) for incident CHD.\ A global consortium of 19 studies identified by November 2014.\ -3 biomarkers and ascertained CHD.\ -6 levels, and FADS desaturase genes.\ Incident total CHD, fatal CHD, and nonfatal myocardial infarction (MI).\ -3 biomarkers ALA, DPA, and DHA were associated with a lower risk of fatal CHD, with relative risks (RRs) of 0.91 (95% CI, 0.84-0.98) for ALA, 0.90 (95% CI, 0.85-0.96) for DPA, and 0.90 (95% CI, 0.84-0.96) for DHA. Although DPA was associated with a lower risk of total CHD (RR, 0.94; 95% CI, 0.90-0.99), ALA (RR, 1.00; 95% CI, 0.95-1.05), EPA (RR, 0.94; 95% CI, 0.87-1.02), and DHA (RR, 0.95; 95% CI, 0.91-1.00) were not. Significant associations with nonfatal MI were not evident. Associations appeared generally stronger in phospholipids and total plasma. Restricted cubic splines did not identify evidence of nonlinearity in dose responses.\ -3 fatty acids are associated with a modestly lower incidence of fatal CHD.

52 Genetic Loci Influencing Myocardial Mass. - van der Harst, Pim; van Setten, Jessica; Verweij, Niek; Vogler, Georg; Franke, Lude; Maurano, Matthew T; Wang, Xinchen; Mateo Leach, Irene; Eijgelsheim, Mark; Sotoodehnia, Nona; Hayward, Caroline; Sorice, Rossella; et al. (J Am Coll Cardiol, 2016)
BACKGROUND: Myocardial mass is a key determinant of cardiac muscle function and hypertrophy. Myocardial depolarization leading to cardiac muscle contraction is reflected by the amplitude and duration of the QRS complex on the electrocardiogram (ECG). Abnormal QRS amplitude or duration reflect changes in myocardial mass and conduction, and are associated with increased risk of heart failure and death. OBJECTIVES: This meta-analysis sought to gain insights into the genetic determinants of myocardial mass. METHODS: We carried out a genome-wide association meta-analysis of 4 QRS traits in up to 73,518 individuals of European ancestry, followed by extensive biological and functional assessment. RESULTS: We identified 52 genomic loci, of which 32 are novel, that are reliably associated with 1 or more QRS phenotypes at p < 1 × 10(-8). These loci are enriched in regions of open chromatin, histone modifications, and transcription factor binding, suggesting that they represent regions of the genome that are actively transcribed in the human heart. Pathway analyses provided evidence that these loci play a role in cardiac hypertrophy. We further highlighted 67 candidate genes at the identified loci that are preferentially expressed in cardiac tissue and associated with cardiac abnormalities in Drosophila melanogaster and Mus musculus. We validated the regulatory function of a novel variant in the SCN5A/SCN10A locus in vitro and in vivo. CONCLUSIONS: Taken together, our findings provide new insights into genes and biological pathways controlling myocardial mass and may help identify novel therapeutic targets.

Common variants in DRD2 are associated with sleep duration: the CARe consortium. - Cade, Brian E; Gottlieb, Daniel J; Lauderdale, Diane S; Bennett, David A; Buchman, Aron S; Buxbaum, Sarah G; De Jager, Philip L; Evans, Daniel S; Fulop, Tibor; Gharib, Sina A; Johnson, W Craig; Kim, Hyun; et al. (Hum Mol Genet, 2016)
Sleep duration is implicated in the etiologies of chronic diseases and premature mortality. However, the genetic basis for sleep duration is poorly defined. We sought to identify novel genetic components influencing sleep duration in a multi-ethnic sample. Meta-analyses were conducted of genetic associations with self-reported, habitual sleep duration from seven Candidate Gene Association Resource (CARe) cohorts of over 25 000 individuals of African, Asian, European and Hispanic American ancestry. All individuals were genotyped for ∼50 000 SNPs from 2000 candidate heart, lung, blood and sleep genes. African-Americans had additional genome-wide genotypes. Four cohorts provided replication. A SNP (rs17601612) in the dopamine D2 receptor gene (DRD2) was significantly associated with sleep duration (P = 9.8 × 10(-7)). Conditional analysis identified a second DRD2 signal with opposite effects on sleep duration. In exploratory analysis, suggestive association was observed for rs17601612 with polysomnographically determined sleep latency (P = 0.002). The lead DRD2 signal was recently identified in a schizophrenia GWAS, and a genetic risk score of 11 additional schizophrenia GWAS loci genotyped on the IBC array was also associated with longer sleep duration (P = 0.03). These findings support a role for DRD2 in influencing sleep duration. Our work motivates future pharmocogenetics research on alerting agents such as caffeine and modafinil that interact with the dopaminergic pathway and further investigation of genetic overlap between sleep and neuro-psychiatric traits.
Keywords: Cohort Studies; Ethnic Groups; Humans; Polymorphism, Single Nucleotide; Polysomnography; Receptors, Dopamine D2; Sleep; Time Factors

Diagnostic Yield and Clinical Utility of Sequencing Familial Hypercholesterolemia Genes in Patients With Severe Hypercholesterolemia. - Khera, Amit V; Won, Hong-Hee; Peloso, Gina M; Lawson, Kim S; Bartz, Traci M; Deng, Xuan; van Leeuwen, Elisabeth M; Natarajan, Pradeep; Emdin, Connor A; Bick, Alexander G; Morrison, Alanna C; Brody, Jennifer A; et al. (J Am Coll Cardiol, 2016)
BACKGROUND: Approximately 7% of American adults have severe hypercholesterolemia (untreated low-density lipoprotein [LDL] cholesterol ≥190 mg/dl), which may be due to familial hypercholesterolemia (FH). Lifelong LDL cholesterol elevations in FH mutation carriers may confer coronary artery disease (CAD) risk beyond that captured by a single LDL cholesterol measurement. OBJECTIVES: This study assessed the prevalence of an FH mutation among those with severe hypercholesterolemia and determined whether CAD risk varies according to mutation status beyond the observed LDL cholesterol level. METHODS: Three genes causative for FH (LDLR, APOB, and PCSK9) were sequenced in 26,025 participants from 7 case-control studies (5,540 CAD case subjects, 8,577 CAD-free control subjects) and 5 prospective cohort studies (11,908 participants). FH mutations included loss-of-function variants in LDLR, missense mutations in LDLR predicted to be damaging, and variants linked to FH in ClinVar, a clinical genetics database. RESULTS: Among 20,485 CAD-free control and prospective cohort participants, 1,386 (6.7%) had LDL cholesterol ≥190 mg/dl; of these, only 24 (1.7%) carried an FH mutation. Within any stratum of observed LDL cholesterol, risk of CAD was higher among FH mutation carriers than noncarriers. Compared with a reference group with LDL cholesterol <130 mg/dl and no mutation, participants with LDL cholesterol ≥190 mg/dl and no FH mutation had a 6-fold higher risk for CAD (odds ratio: 6.0; 95% confidence interval: 5.2 to 6.9), whereas those with both LDL cholesterol ≥190 mg/dl and an FH mutation demonstrated a 22-fold increased risk (odds ratio: 22.3; 95% confidence interval: 10.7 to 53.2). In an analysis of participants with serial lipid measurements over many years, FH mutation carriers had higher cumulative exposure to LDL cholesterol than noncarriers. CONCLUSIONS: Among participants with LDL cholesterol ≥190 mg/dl, gene sequencing identified an FH mutation in <2%. However, for any observed LDL cholesterol, FH mutation carriers had substantially increased risk for CAD.

Discovery of Genetic Variation on Chromosome 5q22 Associated with Mortality in Heart Failure. - Smith, J Gustav; Felix, Janine F; Morrison, Alanna C; Kalogeropoulos, Andreas; Trompet, Stella; Wilk, Jemma B; Gidlöf, Olof; Wang, Xinchen; Morley, Michael; Mendelson, Michael; Joehanes, Roby; Ligthart, Symen; et al. (PLoS Genet, 2016)
Failure of the human heart to maintain sufficient output of blood for the demands of the body, heart failure, is a common condition with high mortality even with modern therapeutic alternatives. To identify molecular determinants of mortality in patients with new-onset heart failure, we performed a meta-analysis of genome-wide association studies and follow-up genotyping in independent populations. We identified and replicated an association for a genetic variant on chromosome 5q22 with 36% increased risk of death in subjects with heart failure (rs9885413, P = 2.7x10-9). We provide evidence from reporter gene assays, computational predictions and epigenomic marks that this polymorphism increases activity of an enhancer region active in multiple human tissues. The polymorphism was further reproducibly associated with a DNA methylation signature in whole blood (P = 4.5x10-40) that also associated with allergic sensitization and expression in blood of the cytokine TSLP (P = 1.1x10-4). Knockdown of the transcription factor predicted to bind the enhancer region (NHLH1) in a human cell line (HEK293) expressing NHLH1 resulted in lower TSLP expression. In addition, we observed evidence of recent positive selection acting on the risk allele in populations of African descent. Our findings provide novel genetic leads to factors that influence mortality in patients with heart failure.

A DNA methylation biomarker of alcohol consumption. - Liu, C; Marioni, R E; Hedman, Å K; Pfeiffer, L; Tsai, P-C; Reynolds, L M; Just, A C; Duan, Q; Boer, C G; Tanaka, T; Elks, C E; Aslibekyan, S; et al. (Mol Psychiatry, 2016)
The lack of reliable measures of alcohol intake is a major obstacle to the diagnosis and treatment of alcohol-related diseases. Epigenetic modifications such as DNA methylation may provide novel biomarkers of alcohol use. To examine this possibility, we performed an epigenome-wide association study of methylation of cytosine-phosphate-guanine dinucleotide (CpG) sites in relation to alcohol intake in 13 population-based cohorts (ntotal=13 317; 54% women; mean age across cohorts 42-76 years) using whole blood (9643 European and 2423 African ancestries) or monocyte-derived DNA (588 European, 263 African and 400 Hispanic ancestry) samples. We performed meta-analysis and variable selection in whole-blood samples of people of European ancestry (n=6926) and identified 144 CpGs that provided substantial discrimination (area under the curve=0.90-0.99) for current heavy alcohol intake (⩾42 g per day in men and ⩾28 g per day in women) in four replication cohorts. The ancestry-stratified meta-analysis in whole blood identified 328 (9643 European ancestry samples) and 165 (2423 African ancestry samples) alcohol-related CpGs at Bonferroni-adjusted P<1 × 10(-7). Analysis of the monocyte-derived DNA (n=1251) identified 62 alcohol-related CpGs at P<1 × 10(-7). In whole-blood samples of people of European ancestry, we detected differential methylation in two neurotransmitter receptor genes, the γ-Aminobutyric acid-A receptor delta and γ-aminobutyric acid B receptor subunit 1; their differential methylation was associated with expression levels of a number of genes involved in immune function. In conclusion, we have identified a robust alcohol-related DNA methylation signature and shown the potential utility of DNA methylation as a clinically useful diagnostic test to detect current heavy alcohol consumption.Molecular Psychiatry advance online publication, 15 November 2016; doi:10.1038/mp.2016.192.

DNA methylation signatures of chronic low-grade inflammation are associated with complex diseases. - Ligthart, Symen; Marzi, Carola; Aslibekyan, Stella; Mendelson, Michael M; Conneely, Karen N; Tanaka, Toshiko; Colicino, Elena; Waite, Lindsay L; Joehanes, Roby; Guan, Weihua; Brody, Jennifer A; Elks, Cathy; et al. (Genome Biol, 2016)
BACKGROUND: Chronic low-grade inflammation reflects a subclinical immune response implicated in the pathogenesis of complex diseases. Identifying genetic loci where DNA methylation is associated with chronic low-grade inflammation may reveal novel pathways or therapeutic targets for inflammation. RESULTS: We performed a meta-analysis of epigenome-wide association studies (EWAS) of serum C-reactive protein (CRP), which is a sensitive marker of low-grade inflammation, in a large European population (n = 8863) and trans-ethnic replication in African Americans (n = 4111). We found differential methylation at 218 CpG sites to be associated with CRP (P < 1.15 × 10(-7)) in the discovery panel of European ancestry and replicated (P < 2.29 × 10(-4)) 58 CpG sites (45 unique loci) among African Americans. To further characterize the molecular and clinical relevance of the findings, we examined the association with gene expression, genetic sequence variants, and clinical outcomes. DNA methylation at nine (16%) CpG sites was associated with whole blood gene expression in cis (P < 8.47 × 10(-5)), ten (17%) CpG sites were associated with a nearby genetic variant (P < 2.50 × 10(-3)), and 51 (88%) were also associated with at least one related cardiometabolic entity (P < 9.58 × 10(-5)). An additive weighted score of replicated CpG sites accounted for up to 6% inter-individual variation (R2) of age-adjusted and sex-adjusted CRP, independent of known CRP-related genetic variants. CONCLUSION: We have completed an EWAS of chronic low-grade inflammation and identified many novel genetic loci underlying inflammation that may serve as targets for the development of novel therapeutic interventions for inflammation.

Epigenetic Signatures of Cigarette Smoking. - Joehanes, Roby; Just, Allan C; Marioni, Riccardo E; Pilling, Luke C; Reynolds, Lindsay M; Mandaviya, Pooja R; Guan, Weihua; Xu, Tao; Elks, Cathy E; Aslibekyan, Stella; Moreno-Macias, Hortensia; Smith, Jennifer A; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: DNA methylation leaves a long-term signature of smoking exposure and is one potential mechanism by which tobacco exposure predisposes to adverse health outcomes, such as cancers, osteoporosis, lung, and cardiovascular disorders. METHODS AND RESULTS: To comprehensively determine the association between cigarette smoking and DNA methylation, we conducted a meta-analysis of genome-wide DNA methylation assessed using the Illumina BeadChip 450K array on 15 907 blood-derived DNA samples from participants in 16 cohorts (including 2433 current, 6518 former, and 6956 never smokers). Comparing current versus never smokers, 2623 cytosine-phosphate-guanine sites (CpGs), annotated to 1405 genes, were statistically significantly differentially methylated at Bonferroni threshold of P<1×10(-7) (18 760 CpGs at false discovery rate <0.05). Genes annotated to these CpGs were enriched for associations with several smoking-related traits in genome-wide studies including pulmonary function, cancers, inflammatory diseases, and heart disease. Comparing former versus never smokers, 185 of the CpGs that differed between current and never smokers were significant P<1×10(-7) (2623 CpGs at false discovery rate <0.05), indicating a pattern of persistent altered methylation, with attenuation, after smoking cessation. Transcriptomic integration identified effects on gene expression at many differentially methylated CpGs. CONCLUSIONS: Cigarette smoking has a broad impact on genome-wide methylation that, at many loci, persists many years after smoking cessation. Many of the differentially methylated genes were novel genes with respect to biological effects of smoking and might represent therapeutic targets for prevention or treatment of tobacco-related diseases. Methylation at these sites could also serve as sensitive and stable biomarkers of lifetime exposure to tobacco smoke.

Exome Genotyping Identifies Pleiotropic Variants Associated with Red Blood Cell Traits. - Chami, Nathalie; Chen, Ming-Huei; Slater, Andrew J; Eicher, John D; Evangelou, Evangelos; Tajuddin, Salman M; Love-Gregory, Latisha; Kacprowski, Tim; Schick, Ursula M; Nomura, Akihiro; Giri, Ayush; Lessard, Samuel; et al. (Am J Hum Genet, 2016)
Red blood cell (RBC) traits are important heritable clinical biomarkers and modifiers of disease severity. To identify coding genetic variants associated with these traits, we conducted meta-analyses of seven RBC phenotypes in 130,273 multi-ethnic individuals from studies genotyped on an exome array. After conditional analyses and replication in 27,480 independent individuals, we identified 16 new RBC variants. We found low-frequency missense variants in MAP1A (rs55707100, minor allele frequency [MAF] = 3.3%, p = 2 × 10(-10) for hemoglobin [HGB]) and HNF4A (rs1800961, MAF = 2.4%, p < 3 × 10(-8) for hematocrit [HCT] and HGB). In African Americans, we identified a nonsense variant in CD36 associated with higher RBC distribution width (rs3211938, MAF = 8.7%, p = 7 × 10(-11)) and showed that it is associated with lower CD36 expression and strong allelic imbalance in ex vivo differentiated human erythroblasts. We also identified a rare missense variant in ALAS2 (rs201062903, MAF = 0.2%) associated with lower mean corpuscular volume and mean corpuscular hemoglobin (p < 8 × 10(-9)). Mendelian mutations in ALAS2 are a cause of sideroblastic anemia and erythropoietic protoporphyria. Gene-based testing highlighted three rare missense variants in PKLR, a gene mutated in Mendelian non-spherocytic hemolytic anemia, associated with HGB and HCT (SKAT p < 8 × 10(-7)). These rare, low-frequency, and common RBC variants showed pleiotropy, being also associated with platelet, white blood cell, and lipid traits. Our association results and functional annotation suggest the involvement of new genes in human erythropoiesis. We also confirm that rare and low-frequency variants play a role in the architecture of complex human traits, although their phenotypic effect is generally smaller than originally anticipated.

Fine-mapping, novel loci identification, and SNP association transferability in a genome-wide association study of QRS duration in African Americans. - Evans, Daniel S; Avery, Christy L; Nalls, Mike A; Li, Guo; Barnard, John; Smith, Erin N; Tanaka, Toshiko; Butler, Anne M; Buxbaum, Sarah G; Alonso, Alvaro; Arking, Dan E; Berenson, Gerald S; et al. (Hum Mol Genet, 2016)
The electrocardiographic QRS duration, a measure of ventricular depolarization and conduction, is associated with cardiovascular mortality. While single nucleotide polymorphisms (SNPs) associated with QRS duration have been identified at 22 loci in populations of European descent, the genetic architecture of QRS duration in non-European populations is largely unknown. We therefore performed a genome-wide association study (GWAS) meta-analysis of QRS duration in 13,031 African Americans from ten cohorts and a transethnic GWAS meta-analysis with additional results from populations of European descent. In the African American GWAS, a single genome-wide significant SNP association was identified (rs3922844, P = 4 × 10(-14)) in intron 16 of SCN5A, a voltage-gated cardiac sodium channel gene. The QRS-prolonging rs3922844 C allele was also associated with decreased SCN5A RNA expression in human atrial tissue (P = 1.1 × 10(-4)). High density genotyping revealed that the SCN5A association region in African Americans was confined to intron 16. Transethnic GWAS meta-analysis identified novel SNP associations on chromosome 18 in MYL12A (rs1662342, P = 4.9 × 10(-8)) and chromosome 1 near CD1E and SPTA1 (rs7547997, P = 7.9 × 10(-9)). The 22 QRS loci previously identified in populations of European descent were enriched for significant SNP associations with QRS duration in African Americans (P = 9.9 × 10(-7)), and index SNP associations in or near SCN5A, SCN10A, CDKN1A, NFIA, HAND1, TBX5 and SETBP1 replicated in African Americans. In summary, rs3922844 was associated with QRS duration and SCN5A expression, two novel QRS loci were identified using transethnic meta-analysis, and a significant proportion of QRS-SNP associations discovered in populations of European descent were transferable to African Americans when adequate power was achieved.

Gait Speed Predicts Incident Disability: A Pooled Analysis. - Perera, Subashan; Patel, Kushang V; Rosano, Caterina; Rubin, Susan M; Satterfield, Suzanne; Harris, Tamara; Ensrud, Kristine; Orwoll, Eric; Lee, Christine G; Chandler, Julie M; Newman, Anne B; Cauley, Jane A; et al. (J Gerontol A Biol Sci Med Sci, 2016)
BACKGROUND: Functional independence with aging is an important goal for individuals and society. Simple prognostic indicators can inform health promotion and care planning, but evidence is limited by heterogeneity in measures of function. METHODS: We performed a pooled analysis of data from seven studies of 27,220 community-dwelling older adults aged 65 or older with baseline gait speed, followed for disability and mortality. Outcomes were incident inability or dependence on another person in bathing or dressing; and difficulty walking ¼ - ½ mile or climbing 10 steps within 3 years. RESULTS: Participants with faster baseline gait had lower rates of incident disability. In subgroups (defined by 0.2 m/s-wide intervals from <0.4 to ≥ 1.4 m/s) with increasingly greater gait speed, 3-year rates of bathing or dressing dependence trended from 10% to 1% in men, and from 15% to 1% in women, while mobility difficulty trended from 47% to 4% in men and 40% to 6% in women. The age-adjusted relative risk ratio per 0.1 m/s greater speed for bathing or dressing dependence in men was 0.68 (0.57-0.81) and in women: 0.74 (0.66-0.82); for mobility difficulty, men: 0.75 (0.68-0.82), women: 0.73 (0.67-0.80). Results were similar for combined disability and mortality. Effects were largely consistent across subgroups based on age, gender, race, body mass index, prior hospitalization, and selected chronic conditions. In the presence of multiple other risk factors for disability, gait speed significantly increased the area under the receiver operator characteristic curve. CONCLUSION: In older adults, gait speed predicts 3 year incidence of bathing or dressing dependence, mobility difficulty, and a composite outcome of disability and mortality.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cohort Studies; Disability Evaluation; Disabled Persons; Female; Gait; Geriatric Assessment; Humans; Independent Living; Male; Mobility Limitation; Predictive Value of Tests; Prognosis; Psychomotor Performance; Risk Assessment; Risk Factors; ROC Curve; Survival Analysis; United States

{Gene-gene Interaction Analyses for Atrial Fibrillation - Lin, H.; Mueller-Nurasyid, M.; Smith, A. V.; Arking, D. E.; Barnard, J.; Bartz, T. M.; Lunetta, K. L.; Lohman, K.; Kleber, M. E.; Lubitz, S. A.; Geelhoed, B.; Trompet, S.; et al. (Sci Rep, 2016)
{Atrial fibrillation (AF) is a heritable disease that affects more than thirty million individuals worldwide. Extensive efforts have been devoted to the study of genetic determinants of AF. The objective of our study is to examine the effect of gene-gene interaction on AF susceptibility. We performed a large-scale association analysis of gene-gene interactions with AF in 8,173 AF cases, and 65,237 AF-free referents collected from 15 studies for discovery. We examined putative interactions between genome-wide SNPs and 17 known AF-related SNPs. The top interactions were then tested for association in an independent cohort for replication, which included more than 2,363 AF cases and 114,746 AF-free referents. One interaction, between rs7164883 at the HCN4 locus and rs4980345 at the SLC28A1 locus, was found to be significantly associated with AF in the discovery cohorts (interaction OR = 1.44, 95% CI: 1.27-1.65

{Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function - Pattaro, C.; Teumer, A.; Gorski, M.; Chu, A. Y.; Li, M.; Mijatovic, V.; Garnaas, M.; Tin, A.; Sorice, R.; Li, Y.; Taliun, D.; Olden, M.; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.

Genetic Variants Associated with Circulating Parathyroid Hormone. - Robinson-Cohen, Cassianne; Lutsey, Pamela L; Kleber, Marcus E; Nielson, Carrie M; Mitchell, Braxton D; Bis, Joshua C; Eny, Karen M; Portas, Laura; Eriksson, Joel; Lorentzon, Mattias; Koller, Daniel L; Milaneschi, Yuri; et al. (J Am Soc Nephrol, 2016)
Parathyroid hormone (PTH) is a primary calcium regulatory hormone. Elevated serum PTH concentrations in primary and secondary hyperparathyroidism have been associated with bone disease, hypertension, and in some studies, cardiovascular mortality. Genetic causes of variation in circulating PTH concentrations are incompletely understood. We performed a genome-wide association study of serum PTH concentrations among 29,155 participants of European ancestry from 13 cohort studies (n=22,653 and n=6502 in discovery and replication analyses, respectively). We evaluated the association of single nucleotide polymorphisms (SNPs) with natural log-transformed PTH concentration adjusted for age, sex, season, study site, and principal components of ancestry. We discovered associations of SNPs from five independent regions with serum PTH concentration, including the strongest association with rs6127099 upstream of CYP24A1 (P=4.2 × 10(-53)), a gene that encodes the primary catabolic enzyme for 1,25-dihydroxyvitamin D and 25-dihydroxyvitamin D. Each additional copy of the minor allele at this SNP associated with 7% higher serum PTH concentration. The other SNPs associated with serum PTH concentration included rs4074995 within RGS14 (P=6.6 × 10(-17)), rs219779 adjacent to CLDN14 (P=3.5 × 10(-16)), rs4443100 near RTDR1 (P=8.7 × 10(-9)), and rs73186030 near CASR (P=4.8 × 10(-8)). Of these five SNPs, rs6127099, rs4074995, and rs219779 replicated. Thus, common genetic variants located near genes involved in vitamin D metabolism and calcium and renal phosphate transport associated with differences in circulating PTH concentrations. Future studies could identify the causal variants at these loci, and the clinical and functional relevance of these variants should be pursued.

Genetic variants in RBFOX3 are associated with sleep latency. - Amin, Najaf; Allebrandt, Karla V; van der Spek, Ashley; Müller-Myhsok, Bertram; Hek, Karin; Teder-Laving, Maris; Hayward, Caroline; Esko, Tõnu; van Mill, Josine G; Mbarek, Hamdi; Watson, Nathaniel F; Melville, Scott A; et al. (Eur J Hum Genet, 2016)
Time to fall asleep (sleep latency) is a major determinant of sleep quality. Chronic, long sleep latency is a major characteristic of sleep-onset insomnia and/or delayed sleep phase syndrome. In this study we aimed to discover common polymorphisms that contribute to the genetics of sleep latency. We performed a meta-analysis of genome-wide association studies (GWAS) including 2 572 737 single nucleotide polymorphisms (SNPs) established in seven European cohorts including 4242 individuals. We found a cluster of three highly correlated variants (rs9900428, rs9907432 and rs7211029) in the RNA-binding protein fox-1 homolog 3 gene (RBFOX3) associated with sleep latency (P-values=5.77 × 10(-08), 6.59 × 10(-)(08) and 9.17 × 10(-)(08)). These SNPs were replicated in up to 12 independent populations including 30 377 individuals (P-values=1.5 × 10(-)(02), 7.0 × 10(-)(03) and 2.5 × 10(-)(03); combined meta-analysis P-values=5.5 × 10(-07), 5.4 × 10(-07) and 1.0 × 10(-07)). A functional prediction of RBFOX3 based on co-expression with other genes shows that this gene is predominantly expressed in brain (P-value=1.4 × 10(-316)) and the central nervous system (P-value=7.5 × 10(-)(321)). The predicted function of RBFOX3 based on co-expression analysis with other genes shows that this gene is significantly involved in the release cycle of neurotransmitters including gamma-aminobutyric acid and various monoamines (P-values<2.9 × 10(-11)) that are crucial in triggering the onset of sleep. To conclude, in this first large-scale GWAS of sleep latency we report a novel association of variants in RBFOX3 gene. Further, a functional prediction of RBFOX3 supports the involvement of RBFOX3 with sleep latency.

{The genetics of blood pressure regulation and its target organs from association studies in 342,415 individuals - Ehret, G. B.; Ferreira, T.; Chasman, D. I.; Jackson, A. U.; Schmidt, E. M.; Johnson, T.; Thorleifsson, G.; Luan, J.; Donnelly, L. A.; Kanoni, S.; Petersen, A. K.; Pihur, V.; et al. (Nat Genet, 2016)
To dissect the genetic architecture of blood pressure and assess effects on target organ damage, we analyzed 128,272 SNPs from targeted and genome-wide arrays in 201,529 individuals of European ancestry, and genotypes from an additional 140,886 individuals were used for validation. We identified 66 blood pressure-associated loci, of which 17 were new; 15 harbored multiple distinct association signals. The 66 index SNPs were enriched for cis-regulatory elements, particularly in vascular endothelial cells, consistent with a primary role in blood pressure control through modulation of vascular tone across multiple tissues. The 66 index SNPs combined in a risk score showed comparable effects in 64,421 individuals of non-European descent. The 66-SNP blood pressure risk score was significantly associated with target organ damage in multiple tissues but with minor effects in the kidney. Our findings expand current knowledge of blood pressure-related pathways and highlight tissues beyond the classical renal system in blood pressure regulation.

Genome-Wide Association Analysis of Young-Onset Stroke Identifies a Locus on Chromosome 10q25 Near HABP2. - Cheng, Yu-Ching; Stanne, Tara M; Giese, Anne-Katrin; Ho, Weang Kee; Traylor, Matthew; Amouyel, Philippe; Holliday, Elizabeth G; Malik, Rainer; Xu, Huichun; Kittner, Steven J; Cole, John W; O'Connell, Jeffrey R; et al. (Stroke, 2016)
BACKGROUND AND PURPOSE: Although a genetic contribution to ischemic stroke is well recognized, only a handful of stroke loci have been identified by large-scale genetic association studies to date. Hypothesizing that genetic effects might be stronger for early- versus late-onset stroke, we conducted a 2-stage meta-analysis of genome-wide association studies, focusing on stroke cases with an age of onset <60 years. METHODS: The discovery stage of our genome-wide association studies included 4505 cases and 21 968 controls of European, South-Asian, and African ancestry, drawn from 6 studies. In Stage 2, we selected the lead genetic variants at loci with association P<5×10(-6) and performed in silico association analyses in an independent sample of ≤1003 cases and 7745 controls. RESULTS: One stroke susceptibility locus at 10q25 reached genome-wide significance in the combined analysis of all samples from the discovery and follow-up stages (rs11196288; odds ratio =1.41; P=9.5×10(-9)). The associated locus is in an intergenic region between TCF7L2 and HABP2. In a further analysis in an independent sample, we found that 2 single nucleotide polymorphisms in high linkage disequilibrium with rs11196288 were significantly associated with total plasma factor VII-activating protease levels, a product of HABP2. CONCLUSIONS: HABP2, which encodes an extracellular serine protease involved in coagulation, fibrinolysis, and inflammatory pathways, may be a genetic susceptibility locus for early-onset stroke.
Keywords: Adult; African Continental Ancestry Group; Age of Onset; Aged; Asian Continental Ancestry Group; Brain Ischemia; Chromosomes, Human, Pair 10; Computer Simulation; DNA, Intergenic; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Serine Endopeptidases; Stroke

Genome-Wide Association Study for Incident Myocardial Infarction and Coronary Heart Disease in Prospective Cohort Studies: The CHARGE Consortium. - Dehghan, Abbas; Bis, Joshua C; White, Charles C; Smith, Albert Vernon; Morrison, Alanna C; Cupples, L Adrienne; Trompet, Stella; Chasman, Daniel I; Lumley, Thomas; Völker, Uwe; Buckley, Brendan M; Ding, Jingzhong; et al. (PLoS One, 2016)
BACKGROUND: Data are limited on genome-wide association studies (GWAS) for incident coronary heart disease (CHD). Moreover, it is not known whether genetic variants identified to date also associate with risk of CHD in a prospective setting. METHODS: We performed a two-stage GWAS analysis of incident myocardial infarction (MI) and CHD in a total of 64,297 individuals (including 3898 MI cases, 5465 CHD cases). SNPs that passed an arbitrary threshold of 5×10-6 in Stage I were taken to Stage II for further discovery. Furthermore, in an analysis of prognosis, we studied whether known SNPs from former GWAS were associated with total mortality in individuals who experienced MI during follow-up. RESULTS: In Stage I 15 loci passed the threshold of 5×10-6; 8 loci for MI and 8 loci for CHD, for which one locus overlapped and none were reported in previous GWAS meta-analyses. We took 60 SNPs representing these 15 loci to Stage II of discovery. Four SNPs near QKI showed nominally significant association with MI (p-value<8.8×10-3) and three exceeded the genome-wide significance threshold when Stage I and Stage II results were combined (top SNP rs6941513: p = 6.2×10-9). Despite excellent power, the 9p21 locus SNP (rs1333049) was only modestly associated with MI (HR = 1.09, p-value = 0.02) and marginally with CHD (HR = 1.06, p-value = 0.08). Among an inception cohort of those who experienced MI during follow-up, the risk allele of rs1333049 was associated with a decreased risk of subsequent mortality (HR = 0.90, p-value = 3.2×10-3). CONCLUSIONS: QKI represents a novel locus that may serve as a predictor of incident CHD in prospective studies. The association of the 9p21 locus both with increased risk of first myocardial infarction and longer survival after MI highlights the importance of study design in investigating genetic determinants of complex disorders.
Keywords: Aged; Cohort Studies; Cooperative Behavior; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies

A genome-wide association study meta-analysis of clinical fracture in 10,012 African American women. - Taylor, Kira C; Evans, Daniel S; Edwards, Digna R Velez; Edwards, Todd L; Sofer, Tamar; Li, Guo; Liu, Youfang; Franceschini, Nora; Jackson, Rebecca D; Giri, Ayush; Donneyong, Macarius; Psaty, Bruce; et al. (Bone Rep, 2016)
BACKGROUND: Osteoporosis is a major public health problem associated with excess disability and mortality. It is estimated that 50-70% of the variation in osteoporotic fracture risk is attributable to genetic factors. The purpose of this hypothesis-generating study was to identify possible genetic determinants of fracture among African American (AA) women in a GWAS meta-analysis. METHODS: Data on clinical fractures (all fractures except fingers, toes, face, skull or sternum) were analyzed among AA female participants in the Women's Health Initiative (WHI) (N = 8155), Cardiovascular Health Study (CHS) (N = 504), BioVU (N = 704), Health ABC (N = 651), and the Johnston County Osteoarthritis Project (JoCoOA) (N = 291). Affymetrix (WHI) and Illumina (Health ABC, JoCoOA, BioVU, CHS) GWAS panels were used for genotyping, and a 1:1 ratio of YRI:CEU HapMap haplotypes was used as an imputation reference panel. We used Cox proportional hazard models or logistic regression to evaluate the association of ~ 2.5 million SNPs with fracture risk, adjusting for ancestry, age, and geographic region where applicable. We conducted a fixed-effects, inverse variance-weighted meta-analysis. Genome-wide significance was set at P < 5 × 10- 8. RESULTS: One SNP, rs12775980 in an intron of SVIL on chromosome 10p11.2, reached genome-wide significance (P = 4.0 × 10- 8). Although this SNP has a low minor allele frequency (0.03), there was no evidence for heterogeneity of effects across the studies (I2 = 0). This locus was not reported in any previous osteoporosis-related GWA studies. We also interrogated previously reported GWA-significant loci associated with fracture or bone mineral density in our data. One locus (SMOC1) generalized, but overall there was not substantial evidence of generalization. Possible reasons for the lack of generalization are discussed. CONCLUSION: This GWAS meta-analysis of fractures in African American women identified a potentially novel locus in the supervillin gene, which encodes a platelet-associated factor and was previously associated with platelet thrombus formation in African Americans. If validated in other populations of African descent, these findings suggest potential new mechanisms involved in fracture that may be particularly important among African Americans.

Genomewide meta-analysis identifies loci associated with IGF-I and IGFBP-3 levels with impact on age-related traits. - Teumer, Alexander; Qi, Qibin; Nethander, Maria; Aschard, Hugues; Bandinelli, Stefania; Beekman, Marian; Berndt, Sonja I; Bidlingmaier, Martin; Broer, Linda; Cappola, Anne; Ceda, Gian Paolo; Chanock, Stephen; et al. (Aging Cell, 2016)
The growth hormone/insulin-like growth factor (IGF) axis can be manipulated in animal models to promote longevity, and IGF-related proteins including IGF-I and IGF-binding protein-3 (IGFBP-3) have also been implicated in risk of human diseases including cardiovascular diseases, diabetes, and cancer. Through genomewide association study of up to 30 884 adults of European ancestry from 21 studies, we confirmed and extended the list of previously identified loci associated with circulating IGF-I and IGFBP-3 concentrations (IGF1, IGFBP3, GCKR, TNS3, GHSR, FOXO3, ASXL2, NUBP2/IGFALS, SORCS2, and CELSR2). Significant sex interactions, which were characterized by different genotype-phenotype associations between men and women, were found only for associations of IGFBP-3 concentrations with SNPs at the loci IGFBP3 and SORCS2. Analyses of SNPs, gene expression, and protein levels suggested that interplay between IGFBP3 and genes within the NUBP2 locus (IGFALS and HAGH) may affect circulating IGF-I and IGFBP-3 concentrations. The IGF-I-decreasing allele of SNP rs934073, which is an eQTL of ASXL2, was associated with lower adiposity and higher likelihood of survival beyond 90 years. The known longevity-associated variant rs2153960 (FOXO3) was observed to be a genomewide significant SNP for IGF-I concentrations. Bioinformatics analysis suggested enrichment of putative regulatory elements among these IGF-I- and IGFBP-3-associated loci, particularly of rs646776 at CELSR2. In conclusion, this study identified several loci associated with circulating IGF-I and IGFBP-3 concentrations and provides clues to the potential role of the IGF axis in mediating effects of known (FOXO3) and novel (ASXL2) longevity-associated loci.

GWAS analysis of handgrip and lower body strength in older adults in the CHARGE consortium. - Matteini, Amy M; Tanaka, Toshiko; Karasik, David; Atzmon, Gil; Chou, Wen-Chi; Eicher, John D; Johnson, Andrew D; Arnold, Alice M; Callisaya, Michele L; Davies, Gail; Evans, Daniel S; Holtfreter, Birte; et al. (Aging Cell, 2016)
Decline in muscle strength with aging is an important predictor of health trajectory in the elderly. Several factors, including genetics, are proposed contributors to variability in muscle strength. To identify genetic contributors to muscle strength, a meta-analysis of genomewide association studies of handgrip was conducted. Grip strength was measured using a handheld dynamometer in 27 581 individuals of European descent over 65 years of age from 14 cohort studies. Genomewide association analysis was conducted on ~2.7 million imputed and genotyped variants (SNPs). Replication of the most significant findings was conducted using data from 6393 individuals from three cohorts. GWAS of lower body strength was also characterized in a subset of cohorts. Two genomewide significant (P-value< 5 × 10(-8) ) and 39 suggestive (P-value< 5 × 10(-5) ) associations were observed from meta-analysis of the discovery cohorts. After meta-analysis with replication cohorts, genomewide significant association was observed for rs752045 on chromosome 8 (β = 0.47, SE = 0.08, P-value = 5.20 × 10(-10) ). This SNP is mapped to an intergenic region and is located within an accessible chromatin region (DNase hypersensitivity site) in skeletal muscle myotubes differentiated from the human skeletal muscle myoblasts cell line. This locus alters a binding motif of the CCAAT/enhancer-binding protein-β (CEBPB) that is implicated in muscle repair mechanisms. GWAS of lower body strength did not yield significant results. A common genetic variant in a chromosomal region that regulates myotube differentiation and muscle repair may contribute to variability in grip strength in the elderly. Further studies are needed to uncover the mechanisms that link this genetic variant with muscle strength.

GWAS for executive function and processing speed suggests involvement of the CADM2 gene. - Ibrahim-Verbaas, C A; Bressler, J; Debette, S; Schuur, M; Smith, A V; Bis, J C; Davies, G; Trompet, S; Smith, J A; Wolf, C; Chibnik, L B; Liu, Y; et al. (Mol Psychiatry, 2016)
To identify common variants contributing to normal variation in two specific domains of cognitive functioning, we conducted a genome-wide association study (GWAS) of executive functioning and information processing speed in non-demented older adults from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) consortium. Neuropsychological testing was available for 5429-32,070 subjects of European ancestry aged 45 years or older, free of dementia and clinical stroke at the time of cognitive testing from 20 cohorts in the discovery phase. We analyzed performance on the Trail Making Test parts A and B, the Letter Digit Substitution Test (LDST), the Digit Symbol Substitution Task (DSST), semantic and phonemic fluency tests, and the Stroop Color and Word Test. Replication was sought in 1311-21860 subjects from 20 independent cohorts. A significant association was observed in the discovery cohorts for the single-nucleotide polymorphism (SNP) rs17518584 (discovery P-value=3.12 × 10(-8)) and in the joint discovery and replication meta-analysis (P-value=3.28 × 10(-9) after adjustment for age, gender and education) in an intron of the gene cell adhesion molecule 2 (CADM2) for performance on the LDST/DSST. Rs17518584 is located about 170 kb upstream of the transcription start site of the major transcript for the CADM2 gene, but is within an intron of a variant transcript that includes an alternative first exon. The variant is associated with expression of CADM2 in the cingulate cortex (P-value=4 × 10(-4)). The protein encoded by CADM2 is involved in glutamate signaling (P-value=7.22 × 10(-15)), gamma-aminobutyric acid (GABA) transport (P-value=1.36 × 10(-11)) and neuron cell-cell adhesion (P-value=1.48 × 10(-13)). Our findings suggest that genetic variation in the CADM2 gene is associated with individual differences in information processing speed.

Inflammatory markers and extent and progression of early atherosclerosis: Meta-analysis of individual-participant-data from 20 prospective studies of the PROG-IMT collaboration. - Willeit, Peter; Thompson, Simon G; Agewall, Stefan; Bergström, Göran; Bickel, Horst; Catapano, Alberico L; Chien, Kuo-Liong; de Groot, Eric; Empana, Jean-Philippe; Etgen, Thorleif; Franco, Oscar H; Iglseder, Bernhard; et al. (Eur J Prev Cardiol, 2016)
BACKGROUND: Large-scale epidemiological evidence on the role of inflammation in early atherosclerosis, assessed by carotid ultrasound, is lacking. We aimed to quantify cross-sectional and longitudinal associations of inflammatory markers with common-carotid-artery intima-media thickness (CCA-IMT) in the general population. METHODS: Information on high-sensitivity C-reactive protein, fibrinogen, leucocyte count and CCA-IMT was available in 20 prospective cohort studies of the PROG-IMT collaboration involving 49,097 participants free of pre-existing cardiovascular disease. Estimates of associations were calculated within each study and then combined using random-effects meta-analyses. RESULTS: Mean baseline CCA-IMT amounted to 0.74 mm (SD = 0.18) and mean CCA-IMT progression over a mean of 3.9 years to 0.011 mm/year (SD = 0.039). Cross-sectional analyses showed positive linear associations between inflammatory markers and baseline CCA-IMT. After adjustment for traditional cardiovascular risk factors, mean differences in baseline CCA-IMT per one-SD higher inflammatory marker were: 0.0082 mm for high-sensitivity C-reactive protein (p < 0.001); 0.0072 mm for fibrinogen (p < 0.001); and 0.0025 mm for leucocyte count (p = 0.033). 'Inflammatory load', defined as the number of elevated inflammatory markers (i.e. in upper two quintiles), showed a positive linear association with baseline CCA-IMT (p < 0.001). Longitudinal associations of baseline inflammatory markers and changes therein with CCA-IMT progression were null or at most weak. Participants with the highest 'inflammatory load' had a greater CCA-IMT progression (p = 0.015). CONCLUSION: Inflammation was independently associated with CCA-IMT cross-sectionally. The lack of clear associations with CCA-IMT progression may be explained by imprecision in its assessment within a limited time period. Our findings for 'inflammatory load' suggest important combined effects of the three inflammatory markers on early atherosclerosis.

KLB is associated with alcohol drinking, and its gene product β-Klotho is necessary for FGF21 regulation of alcohol preference. - Schumann, Gunter; Liu, Chunyu; O'Reilly, Paul; Gao, He; Song, Parkyong; Xu, Bing; Ruggeri, Barbara; Amin, Najaf; Jia, Tianye; Preis, Sarah; Segura Lepe, Marcelo; Akira, Shizuo; et al. (Proc Natl Acad Sci U S A, 2016)
Excessive alcohol consumption is a major public health problem worldwide. Although drinking habits are known to be inherited, few genes have been identified that are robustly linked to alcohol drinking. We conducted a genome-wide association metaanalysis and replication study among >105,000 individuals of European ancestry and identified β-Klotho (KLB) as a locus associated with alcohol consumption (rs11940694; P = 9.2 × 10(-12)). β-Klotho is an obligate coreceptor for the hormone FGF21, which is secreted from the liver and implicated in macronutrient preference in humans. We show that brain-specific β-Klotho KO mice have an increased alcohol preference and that FGF21 inhibits alcohol drinking by acting on the brain. These data suggest that a liver-brain endocrine axis may play an important role in the regulation of alcohol drinking behavior and provide a unique pharmacologic target for reducing alcohol consumption.

Large-Scale Exome-wide Association Analysis Identifies Loci for White Blood Cell Traits and Pleiotropy with Immune-Mediated Diseases. - Tajuddin, Salman M; Schick, Ursula M; Eicher, John D; Chami, Nathalie; Giri, Ayush; Brody, Jennifer A; Hill, W David; Kacprowski, Tim; Li, Jin; Lyytikäinen, Leo-Pekka; Manichaikul, Ani; Mihailov, Evelin; et al. (Am J Hum Genet, 2016)
White blood cells play diverse roles in innate and adaptive immunity. Genetic association analyses of phenotypic variation in circulating white blood cell (WBC) counts from large samples of otherwise healthy individuals can provide insights into genes and biologic pathways involved in production, differentiation, or clearance of particular WBC lineages (myeloid, lymphoid) and also potentially inform the genetic basis of autoimmune, allergic, and blood diseases. We performed an exome array-based meta-analysis of total WBC and subtype counts (neutrophils, monocytes, lymphocytes, basophils, and eosinophils) in a multi-ancestry discovery and replication sample of ∼157,622 individuals from 25 studies. We identified 16 common variants (8 of which were coding variants) associated with one or more WBC traits, the majority of which are pleiotropically associated with autoimmune diseases. Based on functional annotation, these loci included genes encoding surface markers of myeloid, lymphoid, or hematopoietic stem cell differentiation (CD69, CD33, CD87), transcription factors regulating lineage specification during hematopoiesis (ASXL1, IRF8, IKZF1, JMJD1C, ETS2-PSMG1), and molecules involved in neutrophil clearance/apoptosis (C10orf54, LTA), adhesion (TNXB), or centrosome and microtubule structure/function (KIF9, TUBD1). Together with recent reports of somatic ASXL1 mutations among individuals with idiopathic cytopenias or clonal hematopoiesis of undetermined significance, the identification of a common regulatory 3' UTR variant of ASXL1 suggests that both germline and somatic ASXL1 mutations contribute to lower blood counts in otherwise asymptomatic individuals. These association results shed light on genetic mechanisms that regulate circulating WBC counts and suggest a prominent shared genetic architecture with inflammatory and autoimmune diseases.

Large-scale pharmacogenomic study of sulfonylureas and the QT, JT and QRS intervals: CHARGE Pharmacogenomics Working Group. - Floyd, J S; Sitlani, C M; Avery, C L; Noordam, R; Li, X; Smith, A V; Gogarten, S M; Li, J; Broer, L; Evans, D S; Trompet, S; Brody, J A; et al. (Pharmacogenomics J, 2016)
Sulfonylureas, a commonly used class of medication used to treat type 2 diabetes, have been associated with an increased risk of cardiovascular disease. Their effects on QT interval duration and related electrocardiographic phenotypes are potential mechanisms for this adverse effect. In 11 ethnically diverse cohorts that included 71 857 European, African-American and Hispanic/Latino ancestry individuals with repeated measures of medication use and electrocardiogram (ECG) measurements, we conducted a pharmacogenomic genome-wide association study of sulfonylurea use and three ECG phenotypes: QT, JT and QRS intervals. In ancestry-specific meta-analyses, eight novel pharmacogenomic loci met the threshold for genome-wide significance (P<5 × 10(-8)), and a pharmacokinetic variant in CYP2C9 (rs1057910) that has been associated with sulfonylurea-related treatment effects and other adverse drug reactions in previous studies was replicated. Additional research is needed to replicate the novel findings and to understand their biological basis.The Pharmacogenomics Journal advance online publication, 13 December 2016; doi:10.1038/tpj.2016.90.

Longitudinal Relationships between Caloric Expenditure and Gray Matter in the Cardiovascular Health Study. - Raji, Cyrus A; Merrill, David A; Eyre, Harris; Mallam, Sravya; Torosyan, Nare; Erickson, Kirk I; Lopez, Oscar L; Becker, James T; Carmichael, Owen T; Gach, H Michael; Thompson, Paul M; Longstreth, W T; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Physical activity (PA) can be neuroprotective and reduce the risk for Alzheimer's disease (AD). In assessing physical activity, caloric expenditure is a proxy marker reflecting the sum total of multiple physical activity types conducted by an individual. OBJECTIVE: To assess caloric expenditure, as a proxy marker of PA, as a predictive measure of gray matter (GM) volumes in the normal and cognitively impaired elderly persons. METHODS: All subjects in this study were recruited from the Institutional Review Board approved Cardiovascular Health Study (CHS), a multisite population-based longitudinal study in persons aged 65 and older. We analyzed a sub-sample of CHS participants 876 subjects (mean age 78.3, 57.5% F, 42.5% M) who had i) energy output assessed as kilocalories (kcal) per week using the standardized Minnesota Leisure-Time Activities questionnaire, ii) cognitive assessments for clinical classification of normal cognition, mild cognitive impairment (MCI), and AD, and iii) volumetric MR imaging of the brain. Voxel-based morphometry modeled the relationship between kcal/week and GM volumes while accounting for standard covariates including head size, age, sex, white matter hyperintensity lesions, MCI or AD status, and site. Multiple comparisons were controlled using a False Discovery Rate of 5 percent. RESULTS: Higher energy output, from a variety of physical activity types, was associated with larger GM volumes in frontal, temporal, and parietal lobes, as well as hippocampus, thalamus, and basal ganglia. High levels of caloric expenditure moderated neurodegeneration-associated volume loss in the precuneus, posterior cingulate, and cerebellar vermis. CONCLUSION: Increasing energy output from a variety of physical activities is related to larger gray matter volumes in the elderly, regardless of cognitive status.

Meta-analysis identifies common and rare variants influencing blood pressure and overlapping with metabolic trait loci. - Liu, Chunyu; Kraja, Aldi T; Smith, Jennifer A; Brody, Jennifer A; Franceschini, Nora; Bis, Joshua C; Rice, Kenneth; Morrison, Alanna C; Lu, Yingchang; Weiss, Stefan; Guo, Xiuqing; Palmas, Walter; et al. (Nat Genet, 2016)
Meta-analyses of association results for blood pressure using exome-centric single-variant and gene-based tests identified 31 new loci in a discovery stage among 146,562 individuals, with follow-up and meta-analysis in 180,726 additional individuals (total n = 327,288). These blood pressure-associated loci are enriched for known variants for cardiometabolic traits. Associations were also observed for the aggregation of rare and low-frequency missense variants in three genes, NPR1, DBH, and PTPMT1. In addition, blood pressure associations at 39 previously reported loci were confirmed. The identified variants implicate biological pathways related to cardiometabolic traits, vascular function, and development. Several new variants are inferred to have roles in transcription or as hubs in protein-protein interaction networks. Genetic risk scores constructed from the identified variants were strongly associated with coronary disease and myocardial infarction. This large collection of blood pressure-associated loci suggests new therapeutic strategies for hypertension, emphasizing a link with cardiometabolic risk.

A meta-analysis of 120 246 individuals identifies 18 new loci for fibrinogen concentration. - de Vries, Paul S; Chasman, Daniel I; Sabater-Lleal, Maria; Chen, Ming-Huei; Huffman, Jennifer E; Steri, Maristella; Tang, Weihong; Teumer, Alexander; Marioni, Riccardo E; Grossmann, Vera; Hottenga, Jouke J; Trompet, Stella; et al. (Hum Mol Genet, 2016)
Genome-wide association studies have previously identified 23 genetic loci associated with circulating fibrinogen concentration. These studies used HapMap imputation and did not examine the X-chromosome. 1000 Genomes imputation provides better coverage of uncommon variants, and includes indels. We conducted a genome-wide association analysis of 34 studies imputed to the 1000 Genomes Project reference panel and including ∼120 000 participants of European ancestry (95 806 participants with data on the X-chromosome). Approximately 10.7 million single-nucleotide polymorphisms and 1.2 million indels were examined. We identified 41 genome-wide significant fibrinogen loci; of which, 18 were newly identified. There were no genome-wide significant signals on the X-chromosome. The lead variants of five significant loci were indels. We further identified six additional independent signals, including three rare variants, at two previously characterized loci: FGB and IRF1. Together the 41 loci explain 3% of the variance in plasma fibrinogen concentration.

Meta-analysis of 49 549 individuals imputed with the 1000 Genomes Project reveals an exonic damaging variant in ANGPTL4 determining fasting TG levels. - van Leeuwen, Elisabeth M; Sabo, Aniko; Bis, Joshua C; Huffman, Jennifer E; Manichaikul, Ani; Smith, Albert V; Feitosa, Mary F; Demissie, Serkalem; Joshi, Peter K; Duan, Qing; Marten, Jonathan; van Klinken, Jan B; et al. (J Med Genet, 2016)
BACKGROUND: So far, more than 170 loci have been associated with circulating lipid levels through genome-wide association studies (GWAS). These associations are largely driven by common variants, their function is often not known, and many are likely to be markers for the causal variants. In this study we aimed to identify more new rare and low-frequency functional variants associated with circulating lipid levels. METHODS: We used the 1000 Genomes Project as a reference panel for the imputations of GWAS data from ∼60 000 individuals in the discovery stage and ∼90 000 samples in the replication stage. RESULTS: Our study resulted in the identification of five new associations with circulating lipid levels at four loci. All four loci are within genes that can be linked biologically to lipid metabolism. One of the variants, rs116843064, is a damaging missense variant within the ANGPTL4 gene. CONCLUSIONS: This study illustrates that GWAS with high-scale imputation may still help us unravel the biological mechanism behind circulating lipid levels.

Meta-analysis of genome-wide association studies of HDL cholesterol response to statins. - Postmus, Iris; Warren, Helen R; Trompet, Stella; Arsenault, Benoit J; Avery, Christy L; Bis, Joshua C; Chasman, Daniel I; de Keyser, Catherine E; Deshmukh, Harshal A; Evans, Daniel S; Feng, QiPing; Li, Xiaohui; et al. (J Med Genet, 2016)
BACKGROUND: In addition to lowering low density lipoprotein cholesterol (LDL-C), statin therapy also raises high density lipoprotein cholesterol (HDL-C) levels. Inter-individual variation in HDL-C response to statins may be partially explained by genetic variation. METHODS AND RESULTS: We performed a meta-analysis of genome-wide association studies (GWAS) to identify variants with an effect on statin-induced high density lipoprotein cholesterol (HDL-C) changes. The 123 most promising signals with p<1×10(-4) from the 16 769 statin-treated participants in the first analysis stage were followed up in an independent group of 10 951 statin-treated individuals, providing a total sample size of 27 720 individuals. The only associations of genome-wide significance (p<5×10(-8)) were between minor alleles at the CETP locus and greater HDL-C response to statin treatment. CONCLUSIONS: Based on results from this study that included a relatively large sample size, we suggest that CETP may be the only detectable locus with common genetic variants that influence HDL-C response to statins substantially in individuals of European descent. Although CETP is known to be associated with HDL-C, we provide evidence that this pharmacogenetic effect is independent of its association with baseline HDL-C levels.

Natriuretic peptides and integrated risk assessment for cardiovascular disease: an individual-participant-data meta-analysis. - Willeit, Peter; Kaptoge, Stephen; Welsh, Paul; Butterworth, Adam; Chowdhury, Rajiv; Spackman, Sarah; Pennells, Lisa; Gao, Pei; Burgess, Stephen; Freitag, Daniel; Sweeting, Michael; Wood, Angela; et al. (Lancet Diabetes Endocrinol, 2016)
BACKGROUND: Guidelines for primary prevention of cardiovascular diseases focus on prediction of coronary heart disease and stroke. We assessed whether or not measurement of N-terminal-pro-B-type natriuretic peptide (NT-proBNP) concentration could enable a more integrated approach than at present by predicting heart failure and enhancing coronary heart disease and stroke risk assessment. METHODS: In this individual-participant-data meta-analysis, we generated and harmonised individual-participant data from relevant prospective studies via both de-novo NT-proBNP concentration measurement of stored samples and collection of data from studies identified through a systematic search of the literature (PubMed, Scientific Citation Index Expanded, and Embase) for articles published up to Sept 4, 2014, using search terms related to natriuretic peptide family members and the primary outcomes, with no language restrictions. We calculated risk ratios and measures of risk discrimination and reclassification across predicted 10 year risk categories (ie, <5%, 5% to <7·5%, and ≥7·5%), adding assessment of NT-proBNP concentration to that of conventional risk factors (ie, age, sex, smoking status, systolic blood pressure, history of diabetes, and total and HDL cholesterol concentrations). Primary outcomes were the combination of coronary heart disease and stroke, and the combination of coronary heart disease, stroke, and heart failure. FINDINGS: We recorded 5500 coronary heart disease, 4002 stroke, and 2212 heart failure outcomes among 95 617 participants without a history of cardiovascular disease in 40 prospective studies. Risk ratios (for a comparison of the top third vs bottom third of NT-proBNP concentrations, adjusted for conventional risk factors) were 1·76 (95% CI 1·56-1·98) for the combination of coronary heart disease and stroke and 2·00 (1·77-2·26) for the combination of coronary heart disease, stroke, and heart failure. Addition of information about NT-proBNP concentration to a model containing conventional risk factors was associated with a C-index increase of 0·012 (0·010-0·014) and a net reclassification improvement of 0·027 (0·019-0·036) for the combination of coronary heart disease and stroke and a C-index increase of 0·019 (0·016-0·022) and a net reclassification improvement of 0·028 (0·019-0·038) for the combination of coronary heart disease, stroke, and heart failure. INTERPRETATION: In people without baseline cardiovascular disease, NT-proBNP concentration assessment strongly predicted first-onset heart failure and augmented coronary heart disease and stroke prediction, suggesting that NT-proBNP concentration assessment could be used to integrate heart failure into cardiovascular disease primary prevention. FUNDING: British Heart Foundation, Austrian Science Fund, UK Medical Research Council, National Institute for Health Research, European Research Council, and European Commission Framework Programme 7.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Female; Humans; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Prospective Studies; Risk Assessment

Neighborhood Characteristics are Associated with Racial and Gender Variation in Walking among Older Adults: the Cardiovascular Health Study. - Yan, Tingjian; Liang, Li-Jung; Vassar, Stefanie; Katz, Monica Cheung; Escarce, José J; Longstreth, W T Jr; Merkin, Sharon Stein; Brown, Arleen F (Ethn Dis, 2016)
OBJECTIVE: To examine variation by race and gender in the association between neighborhood socioeconomic status and walking among community-dwelling older adults. DESIGN: Cross-sectional. SETTING: Cardiovascular Health Study, a longitudinal population-based cohort. PARTICIPANTS: 4,849 adults, aged > 65 years. MEASUREMENTS: Participants reported the number of city blocks walked in the prior week. Neighborhood socioeconomic status (NSES) was measured at the level of the census tract. Negative binominal regression models were constructed to test the association between NSES and blocks walked. In the fully adjusted models, we included two-way and three-way interaction terms among race, gender, and NSES. RESULTS: In adjusted analyses, among White residents in the lowest NSES quartile (most disadvantaged), men walked 64% more than women (P<.001), while in the highest NSES (most advantaged), men walked 43% more than women (P<.001). Among African American residents in the lowest NSES quartile, men walked 196% more blocks than women (P<.001). CONCLUSIONS: Female gender is more strongly associated with walking for African Americans than for Whites in low SES neighborhoods but had a similar association with walking for both African Americans and Whites in high SES neighborhoods.

A novel Alzheimer disease locus located near the gene encoding tau protein. - Jun, G; Ibrahim-Verbaas, C A; Vronskaya, M; Lambert, J-C; Chung, J; Naj, A C; Kunkle, B W; Wang, L-S; Bis, J C; Bellenguez, C; Harold, D; Lunetta, K L; et al. (Mol Psychiatry, 2016)
APOE ɛ4, the most significant genetic risk factor for Alzheimer disease (AD), may mask effects of other loci. We re-analyzed genome-wide association study (GWAS) data from the International Genomics of Alzheimer's Project (IGAP) Consortium in APOE ɛ4+ (10 352 cases and 9207 controls) and APOE ɛ4- (7184 cases and 26 968 controls) subgroups as well as in the total sample testing for interaction between a single-nucleotide polymorphism (SNP) and APOE ɛ4 status. Suggestive associations (P<1 × 10(-4)) in stage 1 were evaluated in an independent sample (stage 2) containing 4203 subjects (APOE ɛ4+: 1250 cases and 536 controls; APOE ɛ4-: 718 cases and 1699 controls). Among APOE ɛ4- subjects, novel genome-wide significant (GWS) association was observed with 17 SNPs (all between KANSL1 and LRRC37A on chromosome 17 near MAPT) in a meta-analysis of the stage 1 and stage 2 data sets (best SNP, rs2732703, P=5·8 × 10(-9)). Conditional analysis revealed that rs2732703 accounted for association signals in the entire 100-kilobase region that includes MAPT. Except for previously identified AD loci showing stronger association in APOE ɛ4+ subjects (CR1 and CLU) or APOE ɛ4- subjects (MS4A6A/MS4A4A/MS4A6E), no other SNPs were significantly associated with AD in a specific APOE genotype subgroup. In addition, the finding in the stage 1 sample that AD risk is significantly influenced by the interaction of APOE with rs1595014 in TMEM106B (P=1·6 × 10(-7)) is noteworthy, because TMEM106B variants have previously been associated with risk of frontotemporal dementia. Expression quantitative trait locus analysis revealed that rs113986870, one of the GWS SNPs near rs2732703, is significantly associated with four KANSL1 probes that target transcription of the first translated exon and an untranslated exon in hippocampus (P ⩽ 1.3 × 10(-8)), frontal cortex (P ⩽ 1.3 × 10(-9)) and temporal cortex (P⩽1.2 × 10(-11)). Rs113986870 is also strongly associated with a MAPT probe that targets transcription of alternatively spliced exon 3 in frontal cortex (P=9.2 × 10(-6)) and temporal cortex (P=2.6 × 10(-6)). Our APOE-stratified GWAS is the first to show GWS association for AD with SNPs in the chromosome 17q21.31 region. Replication of this finding in independent samples is needed to verify that SNPs in this region have significantly stronger effects on AD risk in persons lacking APOE ɛ4 compared with persons carrying this allele, and if this is found to hold, further examination of this region and studies aimed at deciphering the mechanism(s) are warranted.
Keywords: Alzheimer Disease; Apolipoprotein E4; Chromosomes, Human, Pair 17; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; tau Proteins

{Novel genetic loci underlying human intracranial volume identified through genome-wide association - Adams, H. H.; Hibar, D. P.; Chouraki, V.; Stein, J. L.; Nyquist, P. A.; Renter?a, M. E.; Trompet, S.; Arias-Vasquez, A.; Seshadri, S.; Desrivi?res, S.; Beecham, A. H.; Jahanshad, N.; et al. (Nat Neurosci, 2016)
Intracranial volume reflects the maximally attained brain size during development, and remains stable with loss of tissue in late life. It is highly heritable, but the underlying genes remain largely undetermined. In a genome-wide association study of 32,438 adults, we discovered five previously unknown loci for intracranial volume and confirmed two known signals. Four of the loci were also associated with adult human stature, but these remained associated with intracranial volume after adjusting for height. We found a high genetic correlation with child head circumference (Ïgenetic = 0.748), which indicates a similar genetic background and allowed us to identify four additional loci through meta-analysis (Ncombined = 37,345). Variants for intracranial volume were also related to childhood and adult cognitive function, and Parkinson's disease, and were enriched near genes involved in growth pathways, including PI3K-AKT signaling. These findings identify the biological underpinnings of intracranial volume and their link to physiological and pathological traits.

Platelet-Related Variants Identified by Exomechip Meta-analysis in 157,293 Individuals. - Eicher, John D; Chami, Nathalie; Kacprowski, Tim; Nomura, Akihiro; Chen, Ming-Huei; Yanek, Lisa R; Tajuddin, Salman M; Schick, Ursula M; Slater, Andrew J; Pankratz, Nathan; Polfus, Linda; Schurmann, Claudia; et al. (Am J Hum Genet, 2016)
Platelet production, maintenance, and clearance are tightly controlled processes indicative of platelets' important roles in hemostasis and thrombosis. Platelets are common targets for primary and secondary prevention of several conditions. They are monitored clinically by complete blood counts, specifically with measurements of platelet count (PLT) and mean platelet volume (MPV). Identifying genetic effects on PLT and MPV can provide mechanistic insights into platelet biology and their role in disease. Therefore, we formed the Blood Cell Consortium (BCX) to perform a large-scale meta-analysis of Exomechip association results for PLT and MPV in 157,293 and 57,617 individuals, respectively. Using the low-frequency/rare coding variant-enriched Exomechip genotyping array, we sought to identify genetic variants associated with PLT and MPV. In addition to confirming 47 known PLT and 20 known MPV associations, we identified 32 PLT and 18 MPV associations not previously observed in the literature across the allele frequency spectrum, including rare large effect (FCER1A), low-frequency (IQGAP2, MAP1A, LY75), and common (ZMIZ2, SMG6, PEAR1, ARFGAP3/PACSIN2) variants. Several variants associated with PLT/MPV (PEAR1, MRVI1, PTGES3) were also associated with platelet reactivity. In concurrent BCX analyses, there was overlap of platelet-associated variants with red (MAP1A, TMPRSS6, ZMIZ2) and white (PEAR1, ZMIZ2, LY75) blood cell traits, suggesting common regulatory pathways with shared genetic architecture among these hematopoietic lineages. Our large-scale Exomechip analyses identified previously undocumented associations with platelet traits and further indicate that several complex quantitative hematological, lipid, and cardiovascular traits share genetic factors.

Predicting Heart Failure With Preserved and Reduced Ejection Fraction: The International Collaboration on Heart Failure Subtypes. - Ho, Jennifer E; Enserro, Danielle; Brouwers, Frank P; Kizer, Jorge R; Shah, Sanjiv J; Psaty, Bruce M; Bartz, Traci M; Santhanakrishnan, Rajalakshmi; Lee, Douglas S; Chan, Cheeling; Liu, Kiang; Blaha, Michael J; et al. (Circ Heart Fail, 2016)
BACKGROUND: Heart failure (HF) is a prevalent and deadly disease, and preventive strategies focused on at-risk individuals are needed. Current HF prediction models have not examined HF subtypes. We sought to develop and validate risk prediction models for HF with preserved and reduced ejection fraction (HFpEF, HFrEF). METHODS AND RESULTS: Of 28,820 participants from 4 community-based cohorts, 982 developed incident HFpEF and 909 HFrEF during a median follow-up of 12 years. Three cohorts were combined, and a 2:1 random split was used for derivation and internal validation, with the fourth cohort as external validation. Models accounted for multiple competing risks (death, other HF subtype, and unclassified HF). The HFpEF-specific model included age, sex, systolic blood pressure, body mass index, antihypertensive treatment, and previous myocardial infarction; it had good discrimination in derivation (c-statistic 0.80; 95% confidence interval [CI], 0.78-0.82) and validation samples (internal: 0.79; 95% CI, 0.77-0.82 and external: 0.76; 95% CI: 0.71-0.80). The HFrEF-specific model additionally included smoking, left ventricular hypertrophy, left bundle branch block, and diabetes mellitus; it had good discrimination in derivation (c-statistic 0.82; 95% CI, 0.80-0.84) and validation samples (internal: 0.80; 95% CI, 0.78-0.83 and external: 0.76; 95% CI, 0.71-0.80). Age was more strongly associated with HFpEF, and male sex, left ventricular hypertrophy, bundle branch block, previous myocardial infarction, and smoking with HFrEF (P value for each comparison ≤0.02). CONCLUSIONS: We describe and validate risk prediction models for HF subtypes and show good discrimination in a large sample. Some risk factors differed between HFpEF and HFrEF, supporting the notion of pathogenetic differences among HF subtypes.

A principal component meta-analysis on multiple anthropometric traits identifies novel loci for body shape. - Ried, Janina S; Jeff M, Janina; Chu, Audrey Y; Bragg-Gresham, Jennifer L; van Dongen, Jenny; Huffman, Jennifer E; Ahluwalia, Tarunveer S; Cadby, Gemma; Eklund, Niina; Eriksson, Joel; Esko, Tõnu; Feitosa, Mary F; et al. (Nat Commun, 2016)
Large consortia have revealed hundreds of genetic loci associated with anthropometric traits, one trait at a time. We examined whether genetic variants affect body shape as a composite phenotype that is represented by a combination of anthropometric traits. We developed an approach that calculates averaged PCs (AvPCs) representing body shape derived from six anthropometric traits (body mass index, height, weight, waist and hip circumference, waist-to-hip ratio). The first four AvPCs explain >99% of the variability, are heritable, and associate with cardiometabolic outcomes. We performed genome-wide association analyses for each body shape composite phenotype across 65 studies and meta-analysed summary statistics. We identify six novel loci: LEMD2 and CD47 for AvPC1, RPS6KA5/C14orf159 and GANAB for AvPC3, and ARL15 and ANP32 for AvPC4. Our findings highlight the value of using multiple traits to define complex phenotypes for discovery, which are not captured by single-trait analyses, and may shed light onto new pathways.
Keywords: Anthropometry; Body Size; Genome-Wide Association Study; Genotype; Humans; Models, Genetic; Principal Component Analysis

Rare Exome Sequence Variants in CLCN6 Reduce Blood Pressure Levels and Hypertension Risk. - Yu, Bing; Pulit, Sara L; Hwang, Shih-Jen; Brody, Jennifer A; Amin, Najaf; Auer, Paul L; Bis, Joshua C; Boerwinkle, Eric; Burke, Gregory L; Chakravarti, Aravinda; Correa, Adolfo; Dreisbach, Albert W; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: Rare genetic variants influence blood pressure (BP). METHODS AND RESULTS: Whole-exome sequencing was performed on DNA samples from 17 956 individuals of European ancestry and African ancestry (14 497, first-stage discovery and 3459, second-stage discovery) to examine the effect of rare variants on hypertension and 4 BP traits: systolic BP, diastolic BP, pulse pressure, and mean arterial pressure. Tests of ≈170 000 common variants (minor allele frequency, ≥1%; statistical significance, P≤2.9×10(-7)) and gene-based tests of rare variants (minor allele frequency, <1%; ≈17 000 genes; statistical significance, P≤1.5×10(-6)) were evaluated for each trait and ancestry, followed by multiethnic meta-analyses. In the first-stage discovery, rare coding variants (splicing, stop-gain, stop-loss, nonsynonymous variants, or indels) in CLCN6 were associated with lower diastolic BP (cumulative minor allele frequency, 1.3%; β=-3.20; P=4.1×10(-6)) and were independent of a nearby common variant (rs17367504) previously associated with BP. CLCN6 rare variants were also associated with lower systolic BP (β=-4.11; P=2.8×10(-4)), mean arterial pressure (β=-3.50; P=8.9×10(-6)), and reduced hypertension risk (odds ratio, 0.72; P=0.017). Meta-analysis of the 2-stage discovery samples showed that CLCN6 was associated with lower diastolic BP at exome-wide significance (cumulative minor allele frequency, 1.1%; β=-3.30; P=5.0×10(-7)). CONCLUSIONS: These findings implicate the effect of rare coding variants in CLCN6 in BP variation and offer new insights into BP regulation.

Rare Functional Variant in TM2D3 is Associated with Late-Onset Alzheimer's Disease. - Jakobsdottir, Johanna; van der Lee, Sven J; Bis, Joshua C; Chouraki, Vincent; Li-Kroeger, David; Yamamoto, Shinya; Grove, Megan L; Naj, Adam; Vronskaya, Maria; Salazar, Jose L; DeStefano, Anita L; Brody, Jennifer A; et al. (PLoS Genet, 2016)
We performed an exome-wide association analysis in 1393 late-onset Alzheimer's disease (LOAD) cases and 8141 controls from the CHARGE consortium. We found that a rare variant (P155L) in TM2D3 was enriched in Icelanders (~0.5% versus <0.05% in other European populations). In 433 LOAD cases and 3903 controls from the Icelandic AGES sub-study, P155L was associated with increased risk and earlier onset of LOAD [odds ratio (95% CI) = 7.5 (3.5-15.9), p = 6.6x10-9]. Mutation in the Drosophila TM2D3 homolog, almondex, causes a phenotype similar to loss of Notch/Presenilin signaling. Human TM2D3 is capable of rescuing these phenotypes, but this activity is abolished by P155L, establishing it as a functionally damaging allele. Our results establish a rare TM2D3 variant in association with LOAD susceptibility, and together with prior work suggests possible links to the β-amyloid cascade.

SOS2 and ACP1 Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2016)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (nStage1: 111,666; nStage2: 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (PPM1J, EDEM3, ACP1, SPEG, EYA4, CYP1A1, and ATXN2L; PStage1<3.7×10(-7)), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, SOS2 (P=5.4×10(-8) by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of acp1- and sos2-knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.

Subclinical Cardiovascular Disease and Death, Dementia, and Coronary Heart Disease in Patients 80+ Years. - Kuller, Lewis H; Lopez, Oscar L; Mackey, Rachel H; Rosano, Caterina; Edmundowicz, Daniel; Becker, James T; Newman, Anne B (J Am Coll Cardiol, 2016)
BACKGROUND: The successful prevention and treatment of coronary heart disease (CHD) and stroke has resulted in a substantial increase in longevity, with subsequent growth in the population of older people at risk for dementia. OBJECTIVES: The authors evaluated the relationship of coronary and other peripheral atherosclerosis to risk of death, dementia, and CHD in the very elderly. Because the extent of vascular disease differs substantially between men and women, sex- and race-specific analyses were included, with a specific focus on women with low coronary artery calcium (CAC) Agatston scores. METHODS: We evaluated the relationship between measures of subclinical cardiovascular disease (CAC, carotid intimal medial thickness, stenosis, and ankle brachial index) and risk of dementia, CHD, and total mortality in 532 participants of the Cardiovascular Health Study-Cognition Study from 1998/1999 (mean age, 80 years) to 2012/2013 (mean age, 93 years). RESULTS: Thirty-six percent of participants had CAC scores >400. Women and African-Americans had lower CAC scores. Few men had low CAC scores. CAC score and number of coronary calcifications were directly related to age-adjusted total mortality and CHD. The age-specific incidence of dementia was higher than for CHD. Only about 25% of deaths were caused by CHD and 16% by dementia. Approximately 64% of those who died had a prior diagnosis of dementia. White women with low CAC scores had a significantly decreased incidence of dementia. CONCLUSIONS: In subjects 80+ years of age, there is a greater incidence of dementia than of CHD. CAC, as a marker of atherosclerosis, is a determinant of mortality, and risk of CHD and myocardial infarction. White women with low CAC scores had a significantly decreased risk of dementia. A very important unanswered question, especially in the very elderly, is whether prevention of atherosclerosis and its complications is associated with less Alzheimer disease pathology and dementia. (Cardiovascular Health Study [CHS]; NCT00005133).
Keywords: Age Factors; Aged, 80 and over; Cause of Death; Coronary Artery Disease; Dementia; Female; Humans; Incidence; Male; Pennsylvania; Retrospective Studies; Risk Factors; Survival Rate

Targeted Sequencing of Genome Wide Significant Loci Associated with Bone Mineral Density (BMD) Reveals Significant Novel and Rare Variants: The Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study. - Hsu, Yi-Hsiang; Li, Guo; Liu, Ching-Ti; Brody, Jennifer A; Karasik, David; Chou, Wen-Chi; Demissie, Serkalem; Nandakumar, Kannabiran; Zhou, Yanhua; Cheng, Chia-Ho; Gill, Richard; Gibbs, Richard A; et al. (Hum Mol Genet, 2016)
BACKGROUND: Bone mineral density (BMD) is a heritable phenotype that predicts fracture risk. We performed fine-mapping by targeted sequencing at WLS, MEF2C, ARHGAP1/F2 and JAG1 loci prioritized by eQTL and bioinformatic approaches among 56 BMD loci from our previous GWAS meta-analysis. METHODS AND RESULTS: Targeted sequencing was conducted in 1,291 Caucasians from the Framingham Heart Study (n=925) and Cardiovascular Health Study (n=366), including 206 women and men with extreme low femoral neck (FN) BMD. A total of 4,964 sequence variants (SNVs) were observed and 80% were rare with MAF <1%. The associations between previously identified SNPs in these loci and BMD, while nominally significant in sequenced participants, were no longer significant after multiple testing corrections. Conditional analyses did not find protein-coding variants that may be responsible for GWAS signals. On the other hand, in the sequenced subjects, we identified novel associations in WLS, ARHGAP1, and 5' of MEF2C (p-values < 8x10(-5); false discovery rate (FDR) q-values < 0.01) that were much more strongly associated with BMD compared to the GWAS SNPs. These associated SNVs are less-common; independent from previous GWAS signals in the same loci; and located in gene regulatory elements. CONCLUSIONS: Our findings suggest that protein-coding variants in selected GWAS loci did not contribute to GWAS signals. By performing targeted sequencing in GWAS loci, we identified less-common and rare non-coding SNVs associated with BMD independently from GWAS common SNPs, suggesting both common and less-common variants may associate with disease risks and phenotypes in the same loci.

Thyroid Function Within the Reference Range and the Risk of Stroke: An Individual Participant Data Analysis. - Chaker, Layal; Baumgartner, Christine; den Elzen, Wendy P J; Collet, Tinh-Hai; Ikram, M Arfan; Blum, Manuel R; Dehghan, Abbas; Drechsler, Christiane; Luben, Robert N; Portegies, Marileen L P; Iervasi, Giorgio; Medici, Marco; et al. (J Clin Endocrinol Metab, 2016)
CONTEXT: The currently applied reference ranges for thyroid function are under debate. Despite evidence that thyroid function within the reference range is related with several cardiovascular disorders, its association with the risk of stroke has not been evaluated previously. DESIGN AND SETTING: We identified studies through a systematic literature search and the Thyroid Studies Collaboration, a collaboration of prospective cohort studies. Studies measuring baseline TSH, free T4, and stroke outcomes were included, and we collected individual participant data from each study, including thyroid function measurements and incident all stroke (combined fatal and nonfatal) and fatal stroke. The applied reference range for TSH levels was between 0.45 and 4.49 mIU/L. RESULTS: We collected individual participant data on 43 598 adults with TSH within the reference range from 17 cohorts, with a median follow-up of 11.6 years (interquartile range 5.1-13.9), including 449 908 person-years. Age- and sex-adjusted pooled hazard ratio for TSH was 0.78 (95% confidence interval [CI] 0.65-0.95 across the reference range of TSH) for all stroke and 0.83 (95% CI 0.62-1.09) for fatal stroke. For the free T4 analyses, the hazard ratio was 1.08 (95% CI 0.99-1.15 per SD increase) for all stroke and 1.10 (95% CI 1.04-1.19) for fatal stroke. This was independent of cardiovascular risk factors including systolic blood pressure, total cholesterol, smoking, and prevalent diabetes. CONCLUSION: Higher levels of TSH within the reference range may decrease the risk of stroke, highlighting the need for further research focusing on the clinical consequences associated with differences within the reference range of thyroid function.

Trans-ethnic Meta-analysis and Functional Annotation Illuminates the Genetic Architecture of Fasting Glucose and Insulin. - Liu, Ching-Ti; Raghavan, Sridharan; Maruthur, Nisa; Kabagambe, Edmond Kato; Hong, Jaeyoung; Ng, Maggie C Y; Hivert, Marie-France; Lu, Yingchang; An, Ping; Bentley, Amy R; Drolet, Anne M; Gaulton, Kyle J; et al. (Am J Hum Genet, 2016)
Knowledge of the genetic basis of the type 2 diabetes (T2D)-related quantitative traits fasting glucose (FG) and insulin (FI) in African ancestry (AA) individuals has been limited. In non-diabetic subjects of AA (n = 20,209) and European ancestry (EA; n = 57,292), we performed trans-ethnic (AA+EA) fine-mapping of 54 established EA FG or FI loci with detailed functional annotation, assessed their relevance in AA individuals, and sought previously undescribed loci through trans-ethnic (AA+EA) meta-analysis. We narrowed credible sets of variants driving association signals for 22/54 EA-associated loci; 18/22 credible sets overlapped with active islet-specific enhancers or transcription factor (TF) binding sites, and 21/22 contained at least one TF motif. Of the 54 EA-associated loci, 23 were shared between EA and AA. Replication with an additional 10,096 AA individuals identified two previously undescribed FI loci, chrX FAM133A (rs213676) and chr5 PELO (rs6450057). Trans-ethnic analyses with regulatory annotation illuminate the genetic architecture of glycemic traits and suggest gene regulation as a target to advance precision medicine for T2D. Our approach to utilize state-of-the-art functional annotation and implement trans-ethnic association analysis for discovery and fine-mapping offers a framework for further follow-up and characterization of GWAS signals of complex trait loci.

Twenty-eight genetic loci associated with ST-T-wave amplitudes of the electrocardiogram. - Verweij, Niek; Mateo Leach, Irene; Isaacs, Aaron; Arking, Dan E; Bis, Joshua C; Pers, Tune H; van den Berg, Marten E; Lyytikäinen, Leo-Pekka; Barnett, Phil; Wang, Xinchen; Soliman, Elsayed Z; van Duijn, Cornelia M; et al. (Hum Mol Genet, 2016)
The ST-segment and adjacent T-wave (ST-T wave) amplitudes of the electrocardiogram are quantitative characteristics of cardiac repolarization. Repolarization abnormalities have been linked to ventricular arrhythmias and sudden cardiac death. We performed the first genome-wide association meta-analysis of ST-T-wave amplitudes in up to 37 977 individuals identifying 71 robust genotype-phenotype associations clustered within 28 independent loci. Fifty-four genes were prioritized as candidates underlying the phenotypes, including genes with established roles in the cardiac repolarization phase (SCN5A/SCN10A, KCND3, KCNB1, NOS1AP and HEY2) and others with as yet undefined cardiac function. These associations may provide insights in the spatiotemporal contribution of genetic variation influencing cardiac repolarization and provide novel leads for future functional follow-up.
Keywords: Adaptor Proteins, Signal Transducing; Arrhythmias, Cardiac; Basic Helix-Loop-Helix Transcription Factors; Brugada Syndrome; Cardiac Conduction System Disease; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Conduction System; Humans; Male; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Repressor Proteins; Shab Potassium Channels; Shal Potassium Channels

Whole Exome Sequencing in Atrial Fibrillation. - Lubitz, Steven A; Brody, Jennifer A; Bihlmeyer, Nathan A; Roselli, Carolina; Weng, Lu-Chen; Christophersen, Ingrid E; Alonso, Alvaro; Boerwinkle, Eric; Gibbs, Richard A; Bis, Joshua C; Cupples, L Adrienne; Mohler, Peter J; et al. (PLoS Genet, 2016)
Atrial fibrillation (AF) is a morbid and heritable arrhythmia. Over 35 genes have been reported to underlie AF, most of which were described in small candidate gene association studies. Replication remains lacking for most, and therefore the contribution of coding variation to AF susceptibility remains poorly understood. We examined whole exome sequencing data in a large community-based sample of 1,734 individuals with and 9,423 without AF from the Framingham Heart Study, Cardiovascular Health Study, Atherosclerosis Risk in Communities Study, and NHLBI-GO Exome Sequencing Project and meta-analyzed the results. We also examined whether genetic variation was enriched in suspected AF genes (N = 37) in AF cases versus controls. The mean age ranged from 59 to 73 years; 8,656 (78%) were of European ancestry. None of the 99,404 common variants evaluated was significantly associated after adjusting for multiple testing. Among the most significantly associated variants was a common (allele frequency = 86%) missense variant in SYNPO2L (rs3812629, p.Pro707Leu, [odds ratio 1.27, 95% confidence interval 1.13-1.43, P = 6.6x10-5]) which lies at a known AF susceptibility locus and is in linkage disequilibrium with a top marker from prior analyses at the locus. We did not observe significant associations between rare variants and AF in gene-based tests. Individuals with AF did not display any statistically significant enrichment for common or rare coding variation in previously implicated AF genes. In conclusion, we did not observe associations between coding genetic variants and AF, suggesting that large-effect coding variation is not the predominant mechanism underlying AF. A coding variant in SYNPO2L requires further evaluation to determine whether it is causally related to AF. Efforts to identify biologically meaningful coding variation underlying AF may require large sample sizes or populations enriched for large genetic effects.

Whole-Exome Sequencing Identifies Loci Associated with Blood Cell Traits and Reveals a Role for Alternative GFI1B Splice Variants in Human Hematopoiesis. - Polfus, Linda M; Khajuria, Rajiv K; Schick, Ursula M; Pankratz, Nathan; Pazoki, Raha; Brody, Jennifer A; Chen, Ming-Huei; Auer, Paul L; Floyd, James S; Huang, Jie; Lange, Leslie; van Rooij, Frank J A; et al. (Am J Hum Genet, 2016)

740 adults from 20 prospective cohort studies - Wu, J. H. Y.; Marklund, M.; Imamura, F.; Tintle, N.; Ardisson Korat, A. V.; de Goede, J.; Zhou, X.; Yang, W. S.; de Oliveira Otto, M. C.; ger, J.; Qureshi, W.; Virtanen, J. K.; et al. (Lancet Diabetes Endocrinol, 2017)
The metabolic effects of omega-6 polyunsaturated fatty acids (PUFAs) remain contentious, and little evidence is available regarding their potential role in primary prevention of type 2 diabetes. We aimed to assess the associations of linoleic acid and arachidonic acid biomarkers with incident type 2 diabetes.\ We did a pooled analysis of new, harmonised, individual-level analyses for the biomarkers linoleic acid and its metabolite arachidonic acid and incident type 2 diabetes. We analysed data from 20 prospective cohort studies from ten countries (Iceland, the Netherlands, the USA, Taiwan, the UK, Germany, Finland, Australia, Sweden, and France), with biomarkers sampled between 1970 and 2010. Participants included in the analyses were aged 18 years or older and had data available for linoleic acid and arachidonic acid biomarkers at baseline. We excluded participants with type 2 diabetes at baseline. The main outcome was the association between omega-6 PUFA biomarkers and incident type 2 diabetes. We assessed the relative risk of type 2 diabetes prospectively for each cohort and lipid compartment separately using a prespecified analytic plan for exposures, covariates, effect modifiers, and analysis, and the findings were then pooled using inverse-variance weighted meta-analysis.\ 13).\ Findings suggest that linoleic acid has long-term benefits for the prevention of type 2 diabetes and that arachidonic acid is not harmful.\ Funders are shown in the appendix.

Association Between Telomere Length and Risk of Cancer and Non-Neoplastic Diseases: A Mendelian Randomization Study. - Haycock, Philip C; Burgess, Stephen; Nounu, Aayah; Zheng, Jie; Okoli, George N; Bowden, Jack; Wade, Kaitlin Hazel; Timpson, Nicholas J; Evans, David M; Willeit, Peter; Aviv, Abraham; Gaunt, Tom R; et al. (JAMA Oncol, 2017)
Importance: The causal direction and magnitude of the association between telomere length and incidence of cancer and non-neoplastic diseases is uncertain owing to the susceptibility of observational studies to confounding and reverse causation. Objective: To conduct a Mendelian randomization study, using germline genetic variants as instrumental variables, to appraise the causal relevance of telomere length for risk of cancer and non-neoplastic diseases. Data Sources: Genomewide association studies (GWAS) published up to January 15, 2015. Study Selection: GWAS of noncommunicable diseases that assayed germline genetic variation and did not select cohort or control participants on the basis of preexisting diseases. Of 163 GWAS of noncommunicable diseases identified, summary data from 103 were available. Data Extraction and Synthesis: Summary association statistics for single nucleotide polymorphisms (SNPs) that are strongly associated with telomere length in the general population. Main Outcomes and Measures: Odds ratios (ORs) and 95% confidence intervals (CIs) for disease per standard deviation (SD) higher telomere length due to germline genetic variation. Results: Summary data were available for 35 cancers and 48 non-neoplastic diseases, corresponding to 420 081 cases (median cases, 2526 per disease) and 1 093 105 controls (median, 6789 per disease). Increased telomere length due to germline genetic variation was generally associated with increased risk for site-specific cancers. The strongest associations (ORs [95% CIs] per 1-SD change in genetically increased telomere length) were observed for glioma, 5.27 (3.15-8.81); serous low-malignant-potential ovarian cancer, 4.35 (2.39-7.94); lung adenocarcinoma, 3.19 (2.40-4.22); neuroblastoma, 2.98 (1.92-4.62); bladder cancer, 2.19 (1.32-3.66); melanoma, 1.87 (1.55-2.26); testicular cancer, 1.76 (1.02-3.04); kidney cancer, 1.55 (1.08-2.23); and endometrial cancer, 1.31 (1.07-1.61). Associations were stronger for rarer cancers and at tissue sites with lower rates of stem cell division. There was generally little evidence of association between genetically increased telomere length and risk of psychiatric, autoimmune, inflammatory, diabetic, and other non-neoplastic diseases, except for coronary heart disease (OR, 0.78 [95% CI, 0.67-0.90]), abdominal aortic aneurysm (OR, 0.63 [95% CI, 0.49-0.81]), celiac disease (OR, 0.42 [95% CI, 0.28-0.61]) and interstitial lung disease (OR, 0.09 [95% CI, 0.05-0.15]). Conclusions and Relevance: It is likely that longer telomeres increase risk for several cancers but reduce risk for some non-neoplastic diseases, including cardiovascular diseases.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Germ-Line Mutation; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Neoplasms; Polymorphism, Single Nucleotide; Risk Assessment; Telomere; Telomere Homeostasis

Association of Coronary Artery Calcium Score vs Age With Cardiovascular Risk in Older Adults: An Analysis of Pooled Population-Based Studies. - Yano, Yuichiro; O'Donnell, Christopher J; Kuller, Lewis; Kavousi, Maryam; Erbel, Raimund; Ning, Hongyan; D'Agostino, Ralph; Newman, Anne B; Nasir, Khurram; Hofman, Albert; Lehmann, Nils; Dhana, Klodian; et al. (JAMA Cardiol, 2017)
Importance: Besides age, other discriminators of atherosclerotic cardiovascular disease (ASCVD) risk are needed in older adults. Objectives: To examine the predictive ability of coronary artery calcium (CAC) score vs age for incident ASCVD and how risk prediction changes by adding CAC score and removing only age from prediction models. Design, Setting, and Participants: We conducted an analysis of pooled US population-based studies, including the Framingham Heart Study, the Multi-Ethnic Study of Atherosclerosis, and the Cardiovascular Health Study. Results were compared with 2 European cohorts, the Rotterdam Study and the Heinz Nixdorf Recall Study. Participants underwent CAC scoring between 1998 and 2006 using cardiac computed tomography. The participants included adults older than 60 years without known ASCVD at baseline. Exposures: Coronary artery calcium scores. Main Outcomes and Measures: Incident ASCVD events including coronary heart disease (CHD) and stroke. Results: The study included 4778 participants from 3 US cohorts, with a mean age of 70.1 years; 2582 (54.0%) were women, and 2431 (50.9%) were nonwhite. Over 11 years of follow-up (44 152 person-years), 405 CHD and 228 stroke events occurred. Coronary artery calcium score (vs age) had a greater association with incident CHD (C statistic, 0.733 vs 0.690; C statistics difference, 0.043; 95% CI of difference, 0.009-0.075) and modestly improved prediction of incident stroke (C statistic, 0.695 vs 0.670; C statistics difference, 0.025; 95% CI of difference, -0.015 to 0.064). Adding CAC score to models including traditional cardiovascular risk factors, with only age being removed, provided improved discrimination for incident CHD (C statistic, 0.735 vs 0.703; C statistics difference, 0.032; 95% CI of difference, 0.002-0.062) but not for stroke. Coronary artery calcium score was more likely than age to provide higher category-free net reclassification improvement among participants who experienced an ASCVD event (0.390; 95% CI, 0.312-0.467 vs 0.08; 95% CI -0.001 to 0.181) and to result in more accurate reclassification of risk for ASCVD events among these individuals. The findings were similar in the 2 European cohorts (n = 4990). Conclusions and Relevance: Coronary artery calcium may be an alternative marker besides age to better discriminate between lower and higher CHD risk in older adults. Whether CAC score can assist in guiding the decision to initiate statin treatment for primary prevention in older adults requires further investigation.

Automatic identification of variables in epidemiological datasets using logic regression. - Lorenz, Matthias W; Abdi, Negin Ashtiani; Scheckenbach, Frank; Pflug, Anja; Bülbül, Alpaslan; Catapano, Alberico L; Agewall, Stefan; Ezhov, Marat; Bots, Michiel L; Kiechl, Stefan; Orth, Andreas (BMC Med Inform Decis Mak, 2017)
BACKGROUND: For an individual participant data (IPD) meta-analysis, multiple datasets must be transformed in a consistent format, e.g. using uniform variable names. When large numbers of datasets have to be processed, this can be a time-consuming and error-prone task. Automated or semi-automated identification of variables can help to reduce the workload and improve the data quality. For semi-automation high sensitivity in the recognition of matching variables is particularly important, because it allows creating software which for a target variable presents a choice of source variables, from which a user can choose the matching one, with only low risk of having missed a correct source variable. METHODS: For each variable in a set of target variables, a number of simple rules were manually created. With logic regression, an optimal Boolean combination of these rules was searched for every target variable, using a random subset of a large database of epidemiological and clinical cohort data (construction subset). In a second subset of this database (validation subset), this optimal combination rules were validated. RESULTS: In the construction sample, 41 target variables were allocated on average with a positive predictive value (PPV) of 34%, and a negative predictive value (NPV) of 95%. In the validation sample, PPV was 33%, whereas NPV remained at 94%. In the construction sample, PPV was 50% or less in 63% of all variables, in the validation sample in 71% of all variables. CONCLUSIONS: We demonstrated that the application of logic regression in a complex data management task in large epidemiological IPD meta-analyses is feasible. However, the performance of the algorithm is poor, which may require backup strategies.

Bivariate Genome-Wide Association Study of Depressive Symptoms with Type 2 Diabetes and Quantitative Glycemic Traits. - Haljas, Kadri; Amare, Azmeraw T; Alizadeh, Behrooz Z; Hsu, Yi-Hsiang; Mosley, Thomas; Newman, Anne; Murabito, Joanne; Tiemeier, Henning; Tanaka, Toshiko; van Duijn, Cornelia; Ding, Jingzhong; Llewellyn, David J; et al. (Psychosom Med, 2017)
OBJECTIVE: Shared genetic background may explain phenotypic associations between depression and Type-2-Diabetes (T2D). We aimed to study, on a genome-wide level, if genetic correlation and pleiotropic loci exist between depressive symptoms and T2D or glycemic traits. METHODS: We estimated SNP-based heritability and analyzed genetic correlation between depressive symptoms and T2D and glycemic traits with the LD Score Regression (LDSC) by combining summary statistics of previously conducted meta-analyses for depressive symptoms by CHARGE consortium (N = 51,258), T2D by Diagram consortium (N = 34,840 patients and 114,981 controls), fasting glucose, fasting insulin, HOMA-β, and HOMA-IR by MAGIC consortium (N = 58,074). Finally, we investigated pleiotropic loci using a bivariate GWAS approach with summary statistics from GWAS meta-analyses and reported loci with genome-wide significant bivariate association p-value (p < 5x10). Biological annotation and function of significant pleiotropic SNPs were assessed in several databases. RESULTS: The SNP-based heritability ranged from 0.04 to 0.10 in each individual trait. In the LDSC analyses, depressive symptoms showed no significant genetic correlation with T2D or glycemic traits (p > 0.37). Yet, we identified pleiotropic genetic variations for depressive symptoms and T2D (in the IGF2BP2, CDKAL1, CDKN2B-AS, and PLEKHA1 genes), and fasting glucose (in the MADD, CDKN2B-AS, PEX16, and MTNR1B genes). CONCLUSIONS: We found no significant overall genetic correlations between depressive symptoms, T2D or glycemic traits suggesting major differences in underlying biology of these traits. Yet, several potential pleiotropic loci were identified between depressive symptoms, T2D and fasting glucose suggesting that previously established phenotypic associations may be partly explained by genetic variation in these specific loci.

The complex genetics of gait speed: genome-wide meta-analysis approach. - Ben-Avraham, Dan; Karasik, David; Verghese, Joe; Lunetta, Kathryn L; Smith, Jennifer A; Eicher, John D; Vered, Rotem; Deelen, Joris; Arnold, Alice M; Buchman, Aron S; Tanaka, Toshiko; Faul, Jessica D; et al. (Aging (Albany NY), 2017)
Emerging evidence suggests that the basis for variation in late-life mobility is attributable, in part, to genetic factors, which may become increasingly important with age. Our objective was to systematically assess the contribution of genetic variation to gait speed in older individuals. We conducted a meta-analysis of gait speed GWASs in 31,478 older adults from 17 cohorts of the CHARGE consortium, and validated our results in 2,588 older adults from 4 independent studies. We followed our initial discoveries with network and eQTL analysis of candidate signals in tissues. The meta-analysis resulted in a list of 536 suggestive genome wide significant SNPs in or near 69 genes. Further interrogation with Pathway Analysis placed gait speed as a polygenic complex trait in five major networks. Subsequent eQTL analysis revealed several SNPs significantly associated with the expression of PRSS16, WDSUB1 and PTPRT, which in addition to the meta-analysis and pathway suggested that genetic effects on gait speed may occur through synaptic function and neuronal development pathways. No genome-wide significant signals for gait speed were identified from this moderately large sample of older adults, suggesting that more refined physical function phenotypes will be needed to identify the genetic basis of gait speed in aging.

Dairy consumption, systolic blood pressure, and risk of hypertension: Mendelian randomization study. - Ding, Ming; Huang, Tao; Bergholdt, Helle Km; Nordestgaard, Børge G; Ellervik, Christina; Qi, Lu (BMJ, 2017)
Objective To examine whether previous observed inverse associations of dairy intake with systolic blood pressure and risk of hypertension were causal.Design Mendelian randomization study using the single nucleotide polymorphism rs4988235 related to lactase persistence as an instrumental variable.Setting CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium.Participants Data from 22 studies with 171 213 participants, and an additional 10 published prospective studies with 26 119 participants included in the observational analysis.Main outcome measures The instrumental variable estimation was conducted using the ratio of coefficients approach. Using meta-analysis, an additional eight published randomized clinical trials on the association of dairy consumption with systolic blood pressure were summarized.Results Compared with the CC genotype (CC is associated with complete lactase deficiency), the CT/TT genotype (TT is associated with lactose persistence, and CT is associated with certain lactase deficiency) of LCT-13910 (lactase persistence gene) rs4988235 was associated with higher dairy consumption (0.23 (about 55 g/day), 95% confidence interval 0.17 to 0.29) serving/day; P<0.001) and was not associated with systolic blood pressure (0.31, 95% confidence interval -0.05 to 0.68 mm Hg; P=0.09) or risk of hypertension (odds ratio 1.01, 95% confidence interval 0.97 to 1.05; P=0.27). Using LCT-13910 rs4988235 as the instrumental variable, genetically determined dairy consumption was not associated with systolic blood pressure (β=1.35, 95% confidence interval -0.28 to 2.97 mm Hg for each serving/day) or risk of hypertension (odds ratio 1.04, 0.88 to 1.24). Moreover, meta-analysis of the published clinical trials showed that higher dairy intake has no significant effect on change in systolic blood pressure for interventions over one month to 12 months (intervention compared with control groups: β=-0.21, 95% confidence interval -0.98 to 0.57 mm Hg). In observational analysis, each serving/day increase in dairy consumption was associated with -0.11 (95% confidence interval -0.20 to -0.02 mm Hg; P=0.02) lower systolic blood pressure but not risk of hypertension (odds ratio 0.98, 0.97 to 1.00; P=0.11).Conclusion The weak inverse association between dairy intake and systolic blood pressure in observational studies was not supported by a comprehensive instrumental variable analysis and systematic review of existing clinical trials.
Keywords: Blood Pressure; Dairy Products; Feeding Behavior; Genetic Predisposition to Disease; Humans; Hypertension; Lactase; Mendelian Randomization Analysis; Observational Studies as Topic; Polymorphism, Single Nucleotide; Randomized Controlled Trials as Topic

Disability Trajectories Before and After Stroke and Myocardial Infarction: The Cardiovascular Health Study. - Dhamoon, Mandip S; Longstreth, W T; Bartz, Traci M; Kaplan, Robert C; Elkind, Mitchell S V (JAMA Neurol, 2017)
Importance: Ischemic strokes may accelerate long-term functional decline apart from their acute effects on neurologic function. Objective: To test whether the increase in long-term disability is steeper after than before the event for ischemic stroke but not myocardial infarction (MI). Design, Settings, and Participants: In the population-based, prospective cohort Cardiovascular Health Study (1989-2013), longitudinal follow-up was conducted for a mean (SD) of 13 (6.2) years. Follow-up data were used until September 1, 2013; data analysis was performed from August 1, 2013, to June 1, 2016. Models based on generalized estimating equations adjusted for baseline covariates and included a test for different slopes of disability before and after the event. Participants included 5888 Medicare-eligible individuals 65 years or older who were not institutionalized, expected to reside in the area for 3 or more years, and able to provide informed consent. Exclusions were needing a wheelchair, receiving hospice care, and undergoing radiotherapy or chemotherapy. Exposures: Ischemic stroke and MI. Main Outcomes and Measures: Annual assessments with a disability scale (measuring activities of daily living [ADLs] and instrumental ADLs). The number of ADLs and instrumental ADLs (range, 0-12) that the participant could not perform was analyzed continuously. Results: The mean (SD) age of the entire cohort (n = 5888) was 72.8 (5.6) years; 2495 (42.4%) were male. During follow-up, 382 (6.5%) participants had ischemic stroke and 395 (6.7%) had MI with 1 or more disability assessment after the event. There was a mean of 3.7 (2.4) visits before stroke and 3.7 (2.3) visits after stroke; there was a mean of 3.8 (2.5) visits before MI and 3.8 (2.4) visits after MI. The increase in disability near the time of the event was greater for stroke (0.88 points on the disability scale; 95% CI, 0.57 to 1.20; P < .001) than MI (0.20 points on the disability scale; 95% CI, 0.06 to 0.35; P = .006). The annual increase in disability before stroke (0.06 points per year; 95% CI, 0.002 to 0.12; P = .04) more than tripled after stroke (0.15 additional points per year; 95% CI, 0.004 to 0.30; P = .04). The annual increase in disability before MI (0.04 points per year; 95% CI, 0.004 to 0.08; P = .03) did not change significantly after MI (0.02 additional points per year; 95% CI, -0.07 to 0.11; P = .69). Conclusions and Relevance: In this large, population-based study, a trajectory of increasing disability became significantly steeper after stroke but not after MI. Thus, in addition to the acute brain injury and consequent impairment, ischemic stroke may also be associated with potentially treatable long-term adverse effects on the brain that lead to accelerated functional decline.
Keywords: Activities of Daily Living; Aged; Brain Ischemia; Cohort Studies; Disabled Persons; Disease Progression; Female; Humans; Male; Myocardial Infarction; Prospective Studies; Stroke

Discovery and fine-mapping of adiposity loci using high density imputation of genome-wide association studies in individuals of African ancestry: African ancestry anthropometry genetics consortium. - Ng, Maggie C Y; Graff, Mariaelisa; Lu, Yingchang; Justice, Anne E; Mudgal, Poorva; Liu, Ching-Ti; Young, Kristin; Yanek, Lisa R; Feitosa, Mary F; Wojczynski, Mary K; Rand, Kristin; Brody, Jennifer A; et al. (PLoS Genet, 2017)
Genome-wide association studies (GWAS) have identified >300 loci associated with measures of adiposity including body mass index (BMI) and waist-to-hip ratio (adjusted for BMI, WHRadjBMI), but few have been identified through screening of the African ancestry genomes. We performed large scale meta-analyses and replications in up to 52,895 individuals for BMI and up to 23,095 individuals for WHRadjBMI from the African Ancestry Anthropometry Genetics Consortium (AAAGC) using 1000 Genomes phase 1 imputed GWAS to improve coverage of both common and low frequency variants in the low linkage disequilibrium African ancestry genomes. In the sex-combined analyses, we identified one novel locus (TCF7L2/HABP2) for WHRadjBMI and eight previously established loci at P < 5×10-8: seven for BMI, and one for WHRadjBMI in African ancestry individuals. An additional novel locus (SPRYD7/DLEU2) was identified for WHRadjBMI when combined with European GWAS. In the sex-stratified analyses, we identified three novel loci for BMI (INTS10/LPL and MLC1 in men, IRX4/IRX2 in women) and four for WHRadjBMI (SSX2IP, CASC8, PDE3B and ZDHHC1/HSD11B2 in women) in individuals of African ancestry or both African and European ancestry. For four of the novel variants, the minor allele frequency was low (<5%). In the trans-ethnic fine mapping of 47 BMI loci and 27 WHRadjBMI loci that were locus-wide significant (P < 0.05 adjusted for effective number of variants per locus) from the African ancestry sex-combined and sex-stratified analyses, 26 BMI loci and 17 WHRadjBMI loci contained ≤ 20 variants in the credible sets that jointly account for 99% posterior probability of driving the associations. The lead variants in 13 of these loci had a high probability of being causal. As compared to our previous HapMap imputed GWAS for BMI and WHRadjBMI including up to 71,412 and 27,350 African ancestry individuals, respectively, our results suggest that 1000 Genomes imputation showed modest improvement in identifying GWAS loci including low frequency variants. Trans-ethnic meta-analyses further improved fine mapping of putative causal variants in loci shared between the African and European ancestry populations.

Discovery of novel heart rate-associated loci using the Exome Chip. - van den Berg, Marten E; Warren, Helen R; Cabrera, Claudia P; Verweij, Niek; Mifsud, Borbala; Haessler, Jeffrey; Bihlmeyer, Nathan A; Fu, Yi-Ping; Weiss, Stefan; Lin, Henry J; Grarup, Niels; Li-Gao, Ruifang; et al. (Hum Mol Genet, 2017)
Background Resting heart rate is a heritable trait, and an increase in heart rate is associated with increased mortality risk. GWAS analyses have found loci associated with resting heart rate, at the time of our study these loci explained 0.9% of the variation.Aim To discover new genetic loci associated with heart rate from Exome Chip meta-analyses.Methods Heart rate was measured from either elecrtrocardiograms or pulse recordings. We meta-analysed heart rate association results from 104,452 European-ancestry individuals from 30 cohorts, genotyped using the Exome Chip. Twenty-four variants were selected for follow-up in an independent dataset (UK Biobank, N = 134,251). Conditional and gene-based testing was undertaken, and variants were investigated with bioinformatics methods.Results We discovered five novel heart rate loci, and one new independent low-frequency non-synonymous variant in an established heart rate locus (KIAA1755). Lead variants in four of the novel loci are non-synonymous variants in the genes C10orf71, DALDR3, TESK2, SEC31B. The variant at SEC31B is significantly associated with SEC31B expression in heart and tibial nerve tissue. Further candidate genes were detected from long range regulatory chromatin interactions in heart tissue (SCD, SLF2, MAPK8). We observed significant enrichment in DNase I hypersensitive sites in fetal heart and lung. Moreover, enrichment was seen for the first time in human neuronal progenitor cells (derived from embryonic stem cells) and fetal muscle samples by including our novel variants.Conclusion Our findings advance the knowledge of the genetic architecture of heart rate, and indicate new candidate genes for follow-up functional studies.

Exome-wide association study of plasma lipids in >300,000 individuals. - Liu, Dajiang J; Peloso, Gina M; Yu, Haojie; Butterworth, Adam S; Wang, Xiao; Mahajan, Anubha; Saleheen, Danish; Emdin, Connor; Alam, Dewan; Alves, Alexessander Couto; Amouyel, Philippe; Di Angelantonio, Emanuele; et al. (Nat Genet, 2017)
We screened variants on an exome-focused genotyping array in >300,000 participants (replication in >280,000 participants) and identified 444 independent variants in 250 loci significantly associated with total cholesterol (TC), high-density-lipoprotein cholesterol (HDL-C), low-density-lipoprotein cholesterol (LDL-C), and/or triglycerides (TG). At two loci (JAK2 and A1CF), experimental analysis in mice showed lipid changes consistent with the human data. We also found that: (i) beta-thalassemia trait carriers displayed lower TC and were protected from coronary artery disease (CAD); (ii) excluding the CETP locus, there was not a predictable relationship between plasma HDL-C and risk for age-related macular degeneration; (iii) only some mechanisms of lowering LDL-C appeared to increase risk for type 2 diabetes (T2D); and (iv) TG-lowering alleles involved in hepatic production of TG-rich lipoproteins (TM6SF2 and PNPLA3) tracked with higher liver fat, higher risk for T2D, and lower risk for CAD, whereas TG-lowering alleles involved in peripheral lipolysis (LPL and ANGPTL4) had no effect on liver fat but decreased risks for both T2D and CAD.
Keywords: Coronary Artery Disease; Diabetes Mellitus, Type 2; Exome; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Lipids; Macular Degeneration; Phenotype; Risk Factors

Fifteen Genetic Loci Associated With the Electrocardiographic P Wave. - Christophersen, Ingrid E; Magnani, Jared W; Yin, Xiaoyan; Barnard, John; Weng, Lu-Chen; Arking, Dan E; Niemeijer, Maartje N; Lubitz, Steven A; Avery, Christy L; Duan, Qing; Felix, Stephan B; Bis, Joshua C; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: The P wave on an ECG is a measure of atrial electric function, and its characteristics may serve as predictors for atrial arrhythmias. Increased mean P-wave duration and P-wave terminal force traditionally have been used as markers for left atrial enlargement, and both have been associated with increased risk of atrial fibrillation. Here, we explore the genetic basis of P-wave morphology through meta-analysis of genome-wide association study results for P-wave duration and P-wave terminal force from 12 cohort studies. METHODS AND RESULTS: We included 44 456 individuals, of which 6778 (16%) were of African ancestry. Genotyping, imputation, and genome-wide association study were performed at each study site. Summary-level results were meta-analyzed centrally using inverse-variance weighting. In meta-analyses of P-wave duration, we identified 6 significant (P<5×10-8) novel loci and replicated a prior association with SCN10A. We identified 3 loci at SCN5A, TBX5, and CAV1/CAV2 that were jointly associated with the PR interval, PR segment, and P-wave duration. We identified 6 novel loci in meta-analysis of P-wave terminal force. Four of the identified genetic loci were significantly associated with gene expression in 329 left atrial samples. Finally, we observed that some of the loci associated with the P wave were linked to overall atrial conduction, whereas others identified distinct phases of atrial conduction. CONCLUSIONS: We have identified 6 novel genetic loci associated with P-wave duration and 6 novel loci associated with P-wave terminal force. Future studies of these loci may aid in identifying new targets for drugs that may modify atrial conduction or treat atrial arrhythmias.
Keywords: Arrhythmias, Cardiac; Caveolin 1; Caveolin 2; Electrocardiography; Genetic Loci; Genome-Wide Association Study; Genotype; Heart Atria; Humans; NAV1.5 Voltage-Gated Sodium Channel; NAV1.8 Voltage-Gated Sodium Channel; T-Box Domain Proteins

Generalization and fine mapping of European ancestry-based central adiposity variants in African ancestry populations. - Yoneyama, S; Yao, J; Guo, X; Fernandez-Rhodes, L; Lim, U; Boston, J; Bůžková, P; Carlson, C S; Cheng, I; Cochran, B; Cooper, R; Ehret, G; et al. (Int J Obes (Lond), 2017)
BACKGROUND/OBJECTIVES: Central adiposity measures such as waist circumference (WC) and waist-to-hip ratio (WHR) are associated with cardiometabolic disorders independently of body mass index (BMI) and are gaining clinically utility. Several studies report genetic variants associated with central adiposity, but most utilize only European ancestry populations. Understanding whether the genetic associations discovered among mainly European descendants are shared with African ancestry populations will help elucidate the biological underpinnings of abdominal fat deposition. SUBJECTS/METHODS: To identify the underlying functional genetic determinants of body fat distribution, we conducted an array-wide association meta-analysis among persons of African ancestry across seven studies/consortia participating in the Population Architecture using Genomics and Epidemiology (PAGE) consortium. We used the Metabochip array, designed for fine-mapping cardiovascular-associated loci, to explore novel array-wide associations with WC and WHR among 15 945 African descendants using all and sex-stratified groups. We further interrogated 17 known WHR regions for African ancestry-specific variants. RESULTS: Of the 17 WHR loci, eight single-nucleotide polymorphisms (SNPs) located in four loci were replicated in the sex-combined or sex-stratified meta-analyses. Two of these eight independently associated with WHR after conditioning on the known variant in European descendants (rs12096179 in TBX15-WARS2 and rs2059092 in ADAMTS9). In the fine-mapping assessment, the putative functional region was reduced across all four loci but to varying degrees (average 40% drop in number of putative SNPs and 20% drop in genomic region). Similar to previous studies, the significant SNPs in the female-stratified analysis were stronger than the significant SNPs from the sex-combined analysis. No novel associations were detected in the array-wide analyses. CONCLUSIONS: Of 17 previously identified loci, four loci replicated in the African ancestry populations of this study. Utilizing different linkage disequilibrium patterns observed between European and African ancestries, we narrowed the suggestive region containing causative variants for all four loci.

Genetic Interactions with Age, Sex, Body Mass Index, and Hypertension in Relation to Atrial Fibrillation: The AFGen Consortium. - Weng, Lu-Chen; Lunetta, Kathryn L; Müller-Nurasyid, Martina; Smith, Albert Vernon; Thériault, Sébastien; Weeke, Peter E; Barnard, John; Bis, Joshua C; Lyytikäinen, Leo-Pekka; Kleber, Marcus E; Martinsson, Andreas; Lin, Henry J; et al. (Sci Rep, 2017)
It is unclear whether genetic markers interact with risk factors to influence atrial fibrillation (AF) risk. We performed genome-wide interaction analyses between genetic variants and age, sex, hypertension, and body mass index in the AFGen Consortium. Study-specific results were combined using meta-analysis (88,383 individuals of European descent, including 7,292 with AF). Variants with nominal interaction associations in the discovery analysis were tested for association in four independent studies (131,441 individuals, including 5,722 with AF). In the discovery analysis, the AF risk associated with the minor rs6817105 allele (at the PITX2 locus) was greater among subjects ≤ 65 years of age than among those > 65 years (interaction p-value = 4.0 × 10-5). The interaction p-value exceeded genome-wide significance in combined discovery and replication analyses (interaction p-value = 1.7 × 10-8). We observed one genome-wide significant interaction with body mass index and several suggestive interactions with age, sex, and body mass index in the discovery analysis. However, none was replicated in the independent sample. Our findings suggest that the pathogenesis of AF may differ according to age in individuals of European descent, but we did not observe evidence of statistically significant genetic interactions with sex, body mass index, or hypertension on AF risk.

Genetic loci associated with chronic obstructive pulmonary disease overlap with loci for lung function and pulmonary fibrosis. - Hobbs, Brian D; de Jong, Kim; Lamontagne, Maxime; Bossé, Yohan; Shrine, Nick; Artigas, Maria Soler; Wain, Louise V; Hall, Ian P; Jackson, Victoria E; Wyss, Annah B; London, Stephanie J; North, Kari E; et al. (Nat Genet, 2017)
Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality worldwide. We performed a genetic association study in 15,256 cases and 47,936 controls, with replication of select top results (P < 5 × 10(-6)) in 9,498 cases and 9,748 controls. In the combined meta-analysis, we identified 22 loci associated at genome-wide significance, including 13 new associations with COPD. Nine of these 13 loci have been associated with lung function in general population samples, while 4 (EEFSEC, DSP, MTCL1, and SFTPD) are new. We noted two loci shared with pulmonary fibrosis (FAM13A and DSP) but that had opposite risk alleles for COPD. None of our loci overlapped with genome-wide associations for asthma, although one locus has been implicated in joint susceptibility to asthma and obesity. We also identified genetic correlation between COPD and asthma. Our findings highlight new loci associated with COPD, demonstrate the importance of specific loci associated with lung function to COPD, and identify potential regions of genetic overlap between COPD and other respiratory diseases.

Genetic loci associated with heart rate variability and their effects on cardiac disease risk. - Nolte, Ilja M; Munoz, M Loretto; Tragante, Vinicius; Amare, Azmeraw T; Jansen, Rick; Vaez, Ahmad; von der Heyde, Benedikt; Avery, Christy L; Bis, Joshua C; Dierckx, Bram; van Dongen, Jenny; Gogarten, Stephanie M; et al. (Nat Commun, 2017)
Reduced cardiac vagal control reflected in low heart rate variability (HRV) is associated with greater risks for cardiac morbidity and mortality. In two-stage meta-analyses of genome-wide association studies for three HRV traits in up to 53,174 individuals of European ancestry, we detect 17 genome-wide significant SNPs in eight loci. HRV SNPs tag non-synonymous SNPs (in NDUFA11 and KIAA1755), expression quantitative trait loci (eQTLs) (influencing GNG11, RGS6 and NEO1), or are located in genes preferentially expressed in the sinoatrial node (GNG11, RGS6 and HCN4). Genetic risk scores account for 0.9 to 2.6% of the HRV variance. Significant genetic correlation is found for HRV with heart rate (-0.74<rg<-0.55) and blood pressure (-0.35<rg<-0.20). These findings provide clinically relevant biological insight into heritable variation in vagal heart rhythm regulation, with a key role for genetic variants (GNG11, RGS6) that influence G-protein heterotrimer action in GIRK-channel induced pacemaker membrane hyperpolarization.

{Genetic Risk Prediction of Atrial Fibrillation - Lubitz, S. A.; Yin, X.; Lin, H. J.; Kolek, M.; Smith, J. G.; Trompet, S.; Rienstra, M.; Rost, N. S.; Teixeira, P. L.; Almgren, P.; Anderson, C. D.; Chen, L. Y.; et al. (Circulation, 2017)
Atrial fibrillation (AF) has a substantial genetic basis. Identification of individuals at greatest AF risk could minimize the incidence of cardioembolic stroke.\ To determine whether genetic data can stratify risk for development of AF, we examined associations between AF genetic risk scores and incident AF in 5 prospective studies comprising 18 919 individuals of European ancestry. We examined associations between AF genetic risk scores and ischemic stroke in a separate study of 509 ischemic stroke cases (202 cardioembolic [40%]) and 3028 referents. Scores were based on 11 to 719 common variants (≥5%) associated with AF at P values ranging from <1×10-3 to <1×10-8 in a prior independent genetic association study.\ Incident AF occurred in 1032 individuals (5.5%). AF genetic risk scores were associated with new-onset AF after adjustment for clinical risk factors. The pooled hazard ratio for incident AF for the highest versus lowest quartile of genetic risk scores ranged from 1.28 (719 variants; 95% confidence interval, 1.13-1.46; P=1.5×10-4) to 1.67 (25 variants; 95% confidence interval, 1.47-1.90; P=9.3×10-15). Discrimination of combined clinical and genetic risk scores varied across studies and scores (maximum C statistic, 0.629-0.811; maximum ΔC statistic from clinical score alone, 0.009-0.017). AF genetic risk was associated with stroke in age- and sex-adjusted models. For example, individuals in the highest versus lowest quartile of a 127-variant score had a 2.49-fold increased odds of cardioembolic stroke (95% confidence interval, 1.39-4.58; P=2.7×10-3). The effect persisted after the exclusion of individuals (n=70) with known AF (odds ratio, 2.25; 95% confidence interval, 1.20-4.40; P=0.01).\ Comprehensive AF genetic risk scores were associated with incident AF beyond associations for clinical AF risk factors but offered small improvements in discrimination. AF genetic risk was also associated with cardioembolic stroke in age- and sex-adjusted analyses. Efforts are warranted to determine whether AF genetic risk may improve identification of subclinical AF or help distinguish between stroke mechanisms.

{Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk - Warren, H. R.; Evangelou, E.; Cabrera, C. P.; Gao, H.; Ren, M.; Mifsud, B.; Ntalla, I.; Surendran, P.; Liu, C.; Cook, J. P.; Kraja, A. T.; Drenos, F.; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.

Genome-wide association meta-analysis of fish and EPA+DHA consumption in 17 US and European cohorts. - Mozaffarian, Dariush; Dashti, Hassan S; Wojczynski, Mary K; Chu, Audrey Y; Nettleton, Jennifer A; Männistö, Satu; Kristiansson, Kati; Reedik, Mägi; Lahti, Jari; Houston, Denise K; Cornelis, Marilyn C; van Rooij, Frank J A; et al. (PLoS One, 2017)
BACKGROUND: Regular fish and omega-3 consumption may have several health benefits and are recommended by major dietary guidelines. Yet, their intakes remain remarkably variable both within and across populations, which could partly owe to genetic influences. OBJECTIVE: To identify common genetic variants that influence fish and dietary eicosapentaenoic acid plus docosahexaenoic acid (EPA+DHA) consumption. DESIGN: We conducted genome-wide association (GWA) meta-analysis of fish (n = 86,467) and EPA+DHA (n = 62,265) consumption in 17 cohorts of European descent from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium Nutrition Working Group. Results from cohort-specific GWA analyses (additive model) for fish and EPA+DHA consumption were adjusted for age, sex, energy intake, and population stratification, and meta-analyzed separately using fixed-effect meta-analysis with inverse variance weights (METAL software). Additionally, heritability was estimated in 2 cohorts. RESULTS: Heritability estimates for fish and EPA+DHA consumption ranged from 0.13-0.24 and 0.12-0.22, respectively. A significant GWA for fish intake was observed for rs9502823 on chromosome 6: each copy of the minor allele (FreqA = 0.015) was associated with 0.029 servings/day (~1 serving/month) lower fish consumption (P = 1.96x10-8). No significant association was observed for EPA+DHA, although rs7206790 in the obesity-associated FTO gene was among top hits (P = 8.18x10-7). Post-hoc calculations demonstrated 95% statistical power to detect a genetic variant associated with effect size of 0.05% for fish and 0.08% for EPA+DHA. CONCLUSIONS: These novel findings suggest that non-genetic personal and environmental factors are principal determinants of the remarkable variation in fish consumption, representing modifiable targets for increasing intakes among all individuals. Genes underlying the signal at rs72838923 and mechanisms for the association warrant further investigation.
Keywords: Adult; Aged; Cohort Studies; Docosahexaenoic Acids; Eicosapentaenoic Acid; Europe; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Seafood; United States

A genome-wide interaction analysis of tricyclic/tetracyclic antidepressants and RR and QT intervals: a pharmacogenomics study from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. - Noordam, Raymond; Sitlani, Colleen M; Avery, Christy L; Stewart, James D; Gogarten, Stephanie M; Wiggins, Kerri L; Trompet, Stella; Warren, Helen R; Sun, Fangui; Evans, Daniel S; Li, Xiaohui; Li, Jin; et al. (J Med Genet, 2017)
BACKGROUND: Increased heart rate and a prolonged QT interval are important risk factors for cardiovascular morbidity and mortality, and can be influenced by the use of various medications, including tricyclic/tetracyclic antidepressants (TCAs). We aim to identify genetic loci that modify the association between TCA use and RR and QT intervals. METHODS AND RESULTS: We conducted race/ethnic-specific genome-wide interaction analyses (with HapMap phase II imputed reference panel imputation) of TCAs and resting RR and QT intervals in cohorts of European (n=45 706; n=1417 TCA users), African (n=10 235; n=296 TCA users) and Hispanic/Latino (n=13 808; n=147 TCA users) ancestry, adjusted for clinical covariates. Among the populations of European ancestry, two genome-wide significant loci were identified for RR interval: rs6737205 in BRE (β=56.3, pinteraction=3.9e(-9)) and rs9830388 in UBE2E2 (β=25.2, pinteraction=1.7e(-8)). In Hispanic/Latino cohorts, rs2291477 in TGFBR3 significantly modified the association between TCAs and QT intervals (β=9.3, pinteraction=2.55e(-8)). In the meta-analyses of the other ethnicities, these loci either were excluded from the meta-analyses (as part of quality control), or their effects did not reach the level of nominal statistical significance (pinteraction>0.05). No new variants were identified in these ethnicities. No additional loci were identified after inverse-variance-weighted meta-analysis of the three ancestries. CONCLUSIONS: Among Europeans, TCA interactions with variants in BRE and UBE2E2 were identified in relation to RR intervals. Among Hispanic/Latinos, variants in TGFBR3 modified the relation between TCAs and QT intervals. Future studies are required to confirm our results.

Genome-Wide Interactions with Dairy Intake for Body Mass Index in Adults of European Descent. - Smith, Caren E; Follis, Jack L; Dashti, Hassan S; Tanaka, Toshiko; Graff, Mariaelisa; Fretts, Amanda M; Kilpeläinen, Tuomas O; Wojczynski, Mary K; Richardson, Kris; Nalls, Mike A; Schulz, Christina-Alexandra; Liu, Yongmei; et al. (Mol Nutr Food Res, 2017)
SCOPE: Body weight responds variably to the intake of dairy foods. Genetic variation may contribute to inter-individual variability in associations between body weight and dairy consumption. METHODS AND RESULTS: A genome-wide interaction study to discover genetic variants that account for variation in BMI in the context of low-fat, high-fat and total dairy intake in cross-sectional analysis was conducted. Data from nine discovery studies (up to 25 513 European descent individuals) were meta-analyzed. Twenty-six genetic variants reached the selected significance threshold (p-interaction <10-7) , and six independent variants (LINC01512-rs7751666, PALM2/AKAP2-rs914359, ACTA2-rs1388, PPP1R12A-rs7961195, LINC00333-rs9635058, AC098847.1-rs1791355) were evaluated meta-analytically for replication of interaction in up to 17 675 individuals. Variant rs9635058 (128 kb 3' of LINC00333) was replicated (p-interaction = 0.004). In the discovery cohorts, rs9635058 interacted with dairy (p-interaction = 7.36 × 10-8) such that each serving of low-fat dairy was associated with 0.225 kg m-2 lower BMI per each additional copy of the effect allele (A). A second genetic variant (ACTA2-rs1388) approached interaction replication significance for low-fat dairy exposure. CONCLUSION: Body weight responses to dairy intake may be modified by genotype, in that greater dairy intake may protect a genetic subgroup from higher body weight.

Genome-wide meta-analysis associates HLA-DQA1/DRB1 and LPA and lifestyle factors with human longevity. - Joshi, Peter K; Pirastu, Nicola; Kentistou, Katherine A; Fischer, Krista; Hofer, Edith; Schraut, Katharina E; Clark, David W; Nutile, Teresa; Barnes, Catriona L K; Timmers, Paul R H J; Shen, Xia; Gandin, Ilaria; et al. (Nat Commun, 2017)
Genomic analysis of longevity offers the potential to illuminate the biology of human aging. Here, using genome-wide association meta-analysis of 606,059 parents' survival, we discover two regions associated with longevity (HLA-DQA1/DRB1 and LPA). We also validate previous suggestions that APOE, CHRNA3/5, CDKN2A/B, SH2B3 and FOXO3A influence longevity. Next we show that giving up smoking, educational attainment, openness to new experience and high-density lipoprotein (HDL) cholesterol levels are most positively genetically correlated with lifespan while susceptibility to coronary artery disease (CAD), cigarettes smoked per day, lung cancer, insulin resistance and body fat are most negatively correlated. We suggest that the effect of education on lifespan is principally mediated through smoking while the effect of obesity appears to act via CAD. Using instrumental variables, we suggest that an increase of one body mass index unit reduces lifespan by 7 months while 1 year of education adds 11 months to expected lifespan.Variability in human longevity is genetically influenced. Using genetic data of parental lifespan, the authors identify associations at HLA-DQA/DRB1 and LPA and find that genetic variants that increase educational attainment have a positive effect on lifespan whereas increasing BMI negatively affects lifespan.

{Genome-wide meta-analysis of 241,258 adults accounting for smoking behaviour identifies novel loci for obesity traits - Justice, A. E.; Winkler, T. W.; Feitosa, M. F.; Graff, M.; Fisher, V. A.; Young, K.; Barata, L.; Deng, X.; Czajkowski, J.; Hadley, D.; Ngwa, J. S.; Ahluwalia, T. S.; et al. (Nat Commun, 2017)
Few genome-wide association studies (GWAS) account for environmental exposures, like smoking, potentially impacting the overall trait variance when investigating the genetic contribution to obesity-related traits. Here, we use GWAS data from 51,080 current smokers and 190,178 nonsmokers (87% European descent) to identify loci influencing BMI and central adiposity, measured as waist circumference and waist-to-hip ratio both adjusted for BMI. We identify 23 novel genetic loci, and 9 loci with convincing evidence of gene-smoking interaction (GxSMK) on obesity-related traits. We show consistent direction of effect for all identified loci and significance for 18 novel and for 5 interaction loci in an independent study sample. These loci highlight novel biological functions, including response to oxidative stress, addictive behaviour, and regulatory functions emphasizing the importance of accounting for environment in genetic analyses. Our results suggest that tobacco smoking may alter the genetic susceptibility to overall adiposity and body fat distribution.

Genome-wide Trans-ethnic Meta-analysis Identifies Seven Genetic Loci Influencing Erythrocyte Traits and a Role for RBPMS in Erythropoiesis. - van Rooij, Frank J A; Qayyum, Rehan; Smith, Albert V; Zhou, Yi; Trompet, Stella; Tanaka, Toshiko; Keller, Margaux F; Chang, Li-Ching; Schmidt, Helena; Yang, Min-Lee; Chen, Ming-Huei; Hayes, James; et al. (Am J Hum Genet, 2017)
Genome-wide association studies (GWASs) have identified loci for erythrocyte traits in primarily European ancestry populations. We conducted GWAS meta-analyses of six erythrocyte traits in 71,638 individuals from European, East Asian, and African ancestries using a Bayesian approach to account for heterogeneity in allelic effects and variation in the structure of linkage disequilibrium between ethnicities. We identified seven loci for erythrocyte traits including a locus (RBPMS/GTF2E2) associated with mean corpuscular hemoglobin and mean corpuscular volume. Statistical fine-mapping at this locus pointed to RBPMS at this locus and excluded nearby GTF2E2. Using zebrafish morpholino to evaluate loss of function, we observed a strong in vivo erythropoietic effect for RBPMS but not for GTF2E2, supporting the statistical fine-mapping at this locus and demonstrating that RBPMS is a regulator of erythropoiesis. Our findings show the utility of trans-ethnic GWASs for discovery and characterization of genetic loci influencing hematologic traits.

Impact of common genetic determinants of Hemoglobin A1c on type 2 diabetes risk and diagnosis in ancestrally diverse populations: A transethnic genome-wide meta-analysis. - Wheeler, Eleanor; Leong, Aaron; Liu, Ching-Ti; Hivert, Marie-France; Strawbridge, Rona J; Podmore, Clara; Li, Man; Yao, Jie; Sim, Xueling; Hong, Jaeyoung; Chu, Audrey Y; Zhang, Weihua; et al. (PLoS Med, 2017)
BACKGROUND: Glycated hemoglobin (HbA1c) is used to diagnose type 2 diabetes (T2D) and assess glycemic control in patients with diabetes. Previous genome-wide association studies (GWAS) have identified 18 HbA1c-associated genetic variants. These variants proved to be classifiable by their likely biological action as erythrocytic (also associated with erythrocyte traits) or glycemic (associated with other glucose-related traits). In this study, we tested the hypotheses that, in a very large scale GWAS, we would identify more genetic variants associated with HbA1c and that HbA1c variants implicated in erythrocytic biology would affect the diagnostic accuracy of HbA1c. We therefore expanded the number of HbA1c-associated loci and tested the effect of genetic risk-scores comprised of erythrocytic or glycemic variants on incident diabetes prediction and on prevalent diabetes screening performance. Throughout this multiancestry study, we kept a focus on interancestry differences in HbA1c genetics performance that might influence race-ancestry differences in health outcomes. METHODS & FINDINGS: Using genome-wide association meta-analyses in up to 159,940 individuals from 82 cohorts of European, African, East Asian, and South Asian ancestry, we identified 60 common genetic variants associated with HbA1c. We classified variants as implicated in glycemic, erythrocytic, or unclassified biology and tested whether additive genetic scores of erythrocytic variants (GS-E) or glycemic variants (GS-G) were associated with higher T2D incidence in multiethnic longitudinal cohorts (N = 33,241). Nineteen glycemic and 22 erythrocytic variants were associated with HbA1c at genome-wide significance. GS-G was associated with higher T2D risk (incidence OR = 1.05, 95% CI 1.04-1.06, per HbA1c-raising allele, p = 3 × 10-29); whereas GS-E was not (OR = 1.00, 95% CI 0.99-1.01, p = 0.60). In Europeans and Asians, erythrocytic variants in aggregate had only modest effects on the diagnostic accuracy of HbA1c. Yet, in African Americans, the X-linked G6PD G202A variant (T-allele frequency 11%) was associated with an absolute decrease in HbA1c of 0.81%-units (95% CI 0.66-0.96) per allele in hemizygous men, and 0.68%-units (95% CI 0.38-0.97) in homozygous women. The G6PD variant may cause approximately 2% (N = 0.65 million, 95% CI 0.55-0.74) of African American adults with T2D to remain undiagnosed when screened with HbA1c. Limitations include the smaller sample sizes for non-European ancestries and the inability to classify approximately one-third of the variants. Further studies in large multiethnic cohorts with HbA1c, glycemic, and erythrocytic traits are required to better determine the biological action of the unclassified variants. CONCLUSIONS: As G6PD deficiency can be clinically silent until illness strikes, we recommend investigation of the possible benefits of screening for the G6PD genotype along with using HbA1c to diagnose T2D in populations of African ancestry or groups where G6PD deficiency is common. Screening with direct glucose measurements, or genetically-informed HbA1c diagnostic thresholds in people with G6PD deficiency, may be required to avoid missed or delayed diagnoses.
Keywords: Diabetes Mellitus, Type 2; Genetic Variation; Genome-Wide Association Study; Glycated Hemoglobin A; Humans; Phenotype; Risk

Large meta-analysis of genome-wide association studies identifies five loci for lean body mass. - Zillikens, M Carola; Demissie, Serkalem; Hsu, Yi-Hsiang; Yerges-Armstrong, Laura M; Chou, Wen-Chi; Stolk, Lisette; Livshits, Gregory; Broer, Linda; Johnson, Toby; Koller, Daniel L; Kutalik, Zoltán; Luan, Jian'an; et al. (Nat Commun, 2017)
Lean body mass, consisting mostly of skeletal muscle, is important for healthy aging. We performed a genome-wide association study for whole body (20 cohorts of European ancestry with n = 38,292) and appendicular (arms and legs) lean body mass (n = 28,330) measured using dual energy X-ray absorptiometry or bioelectrical impedance analysis, adjusted for sex, age, height, and fat mass. Twenty-one single-nucleotide polymorphisms were significantly associated with lean body mass either genome wide (p < 5 × 10-8) or suggestively genome wide (p < 2.3 × 10-6). Replication in 63,475 (47,227 of European ancestry) individuals from 33 cohorts for whole body lean body mass and in 45,090 (42,360 of European ancestry) subjects from 25 cohorts for appendicular lean body mass was successful for five single-nucleotide polymorphisms in/near HSD17B11, VCAN, ADAMTSL3, IRS1, and FTO for total lean body mass and for three single-nucleotide polymorphisms in/near VCAN, ADAMTSL3, and IRS1 for appendicular lean body mass. Our findings provide new insight into the genetics of lean body mass.Lean body mass is a highly heritable trait and is associated with various health conditions. Here, Kiel and colleagues perform a meta-analysis of genome-wide association studies for whole body lean body mass and find five novel genetic loci to be significantly associated.

Large-scale analyses of common and rare variants identify 12 new loci associated with atrial fibrillation. - Christophersen, Ingrid E; Rienstra, Michiel; Roselli, Carolina; Yin, Xiaoyan; Geelhoed, Bastiaan; Barnard, John; Lin, Honghuang; Arking, Dan E; Smith, Albert V; Albert, Christine M; Chaffin, Mark; Tucker, Nathan R; et al. (Nat Genet, 2017)
Atrial fibrillation affects more than 33 million people worldwide and increases the risk of stroke, heart failure, and death. Fourteen genetic loci have been associated with atrial fibrillation in European and Asian ancestry groups. To further define the genetic basis of atrial fibrillation, we performed large-scale, trans-ancestry meta-analyses of common and rare variant association studies. The genome-wide association studies (GWAS) included 17,931 individuals with atrial fibrillation and 115,142 referents; the exome-wide association studies (ExWAS) and rare variant association studies (RVAS) involved 22,346 cases and 132,086 referents. We identified 12 new genetic loci that exceeded genome-wide significance, implicating genes involved in cardiac electrical and structural remodeling. Our results nearly double the number of known genetic loci for atrial fibrillation, provide insights into the molecular basis of atrial fibrillation, and may facilitate the identification of new potential targets for drug discovery.

Large-Scale Cognitive GWAS Meta-Analysis Reveals Tissue-Specific Neural Expression and Potential Nootropic Drug Targets. - Lam, Max; Trampush, Joey W; Yu, Jin; Knowles, Emma; Davies, Gail; Liewald, David C; Starr, John M; Djurovic, Srdjan; Melle, Ingrid; Sundet, Kjetil; Christoforou, Andrea; Reinvang, Ivar; et al. (Cell Rep, 2017)
Here, we present a large (n = 107,207) genome-wide association study (GWAS) of general cognitive ability ("g"), further enhanced by combining results with a large-scale GWAS of educational attainment. We identified 70 independent genomic loci associated with general cognitive ability. Results showed significant enrichment for genes causing Mendelian disorders with an intellectual disability phenotype. Competitive pathway analysis implicated the biological processes of neurogenesis and synaptic regulation, as well as the gene targets of two pharmacologic agents: cinnarizine, a T-type calcium channel blocker, and LY97241, a potassium channel inhibitor. Transcriptome-wide and epigenome-wide analysis revealed that the implicated loci were enriched for genes expressed across all brain regions (most strongly in the cerebellum). Enrichment was exclusive to genes expressed in neurons but not oligodendrocytes or astrocytes. Finally, we report genetic correlations between cognitive ability and disparate phenotypes including psychiatric disorders, several autoimmune disorders, longevity, and maternal age at first birth.

Large-scale genome-wide analysis identifies genetic variants associated with cardiac structure and function. - Wild, Philipp S; Felix, Janine F; Schillert, Arne; Teumer, Alexander; Chen, Ming-Huei; Leening, Maarten J G; Völker, Uwe; Großmann, Vera; Brody, Jennifer A; Irvin, Marguerite R; Shah, Sanjiv J; Pramana, Setia; et al. (J Clin Invest, 2017)
BACKGROUND: Understanding the genetic architecture of cardiac structure and function may help to prevent and treat heart disease. This investigation sought to identify common genetic variations associated with inter-individual variability in cardiac structure and function. METHODS: A GWAS meta-analysis of echocardiographic traits was performed, including 46,533 individuals from 30 studies (EchoGen consortium). The analysis included 16 traits of left ventricular (LV) structure, and systolic and diastolic function. RESULTS: The discovery analysis included 21 cohorts for structural and systolic function traits (n = 32,212) and 17 cohorts for diastolic function traits (n = 21,852). Replication was performed in 5 cohorts (n = 14,321) and 6 cohorts (n = 16,308), respectively. Besides 5 previously reported loci, the combined meta-analysis identified 10 additional genome-wide significant SNPs: rs12541595 near MTSS1 and rs10774625 in ATXN2 for LV end-diastolic internal dimension; rs806322 near KCNRG, rs4765663 in CACNA1C, rs6702619 near PALMD, rs7127129 in TMEM16A, rs11207426 near FGGY, rs17608766 in GOSR2, and rs17696696 in CFDP1 for aortic root diameter; and rs12440869 in IQCH for Doppler transmitral A-wave peak velocity. Findings were in part validated in other cohorts and in GWAS of related disease traits. The genetic loci showed associations with putative signaling pathways, and with gene expression in whole blood, monocytes, and myocardial tissue. CONCLUSION: The additional genetic loci identified in this large meta-analysis of cardiac structure and function provide insights into the underlying genetic architecture of cardiac structure and warrant follow-up in future functional studies. FUNDING: For detailed information per study, see Acknowledgments.

Large-scale GWAS identifies multiple loci for hand grip strength providing biological insights into muscular fitness. - Willems, Sara M; Wright, Daniel J; Day, Felix R; Trajanoska, Katerina; Joshi, Peter K; Morris, John A; Matteini, Amy M; Garton, Fleur C; Grarup, Niels; Oskolkov, Nikolay; Thalamuthu, Anbupalam; Mangino, Massimo; et al. (Nat Commun, 2017)
Hand grip strength is a widely used proxy of muscular fitness, a marker of frailty, and predictor of a range of morbidities and all-cause mortality. To investigate the genetic determinants of variation in grip strength, we perform a large-scale genetic discovery analysis in a combined sample of 195,180 individuals and identify 16 loci associated with grip strength (P<5 × 10) in combined analyses. A number of these loci contain genes implicated in structure and function of skeletal muscle fibres (ACTG1), neuronal maintenance and signal transduction (PEX14, TGFA, SYT1), or monogenic syndromes with involvement of psychomotor impairment (PEX14, LRPPRC and KANSL1). Mendelian randomization analyses are consistent with a causal effect of higher genetically predicted grip strength on lower fracture risk. In conclusion, our findings provide new biological insight into the mechanistic underpinnings of grip strength and the causal role of muscular strength in age-related morbidities and mortality.

Measures of chronic kidney disease and risk of incident peripheral artery disease: a collaborative meta-analysis of individual participant data. - Matsushita, Kunihiro; Ballew, Shoshana H; Coresh, Josef; Arima, Hisatomi; Arnlöv, Johan; Cirillo, Massimo; Ebert, Natalie; Hiramoto, Jade S; Kimm, Heejin; Shlipak, Michael G; Visseren, Frank L J; Gansevoort, Ron T; et al. (Lancet Diabetes Endocrinol, 2017)
BACKGROUND: Some evidence suggests that chronic kidney disease is a risk factor for lower-extremity peripheral artery disease. We aimed to quantify the independent and joint associations of two measures of chronic kidney disease (estimated glomerular filtration rate [eGFR] and albuminuria) with the incidence of peripheral artery disease. METHODS: In this collaborative meta-analysis of international cohorts included in the Chronic Kidney Disease Prognosis Consortium (baseline measurements obtained between 1972 and 2014) with baseline measurements of eGFR and albuminuria, at least 1000 participants (this criterion not applied to cohorts exclusively enrolling patients with chronic kidney disease), and at least 50 peripheral artery disease events, we analysed adult participants without peripheral artery disease at baseline at the individual patient level with Cox proportional hazards models to quantify associations of creatinine-based eGFR, urine albumin-to-creatinine ratio (ACR), and dipstick proteinuria with the incidence of peripheral artery disease (including hospitalisation with a diagnosis of peripheral artery disease, intermittent claudication, leg revascularisation, and leg amputation). We assessed discrimination improvement through c-statistics. FINDINGS: We analysed 817 084 individuals without a history of peripheral artery disease at baseline from 21 cohorts. 18 261 cases of peripheral artery disease were recorded during follow-up across cohorts (median follow-up was 7·4 years [IQR 5·7-8·9], range 2·0-15·8 years across cohorts). Both chronic kidney disease measures were independently associated with the incidence of peripheral artery disease. Compared with an eGFR of 95 mL/min per 1·73 m2, adjusted hazard ratios (HRs) for incident study-specific peripheral artery disease was 1·22 (95% CI 1·14-1·30) at an eGFR of 45 mL/min per 1·73 m2 and 2·06 (1·70-2·48) at an eGFR of 15 mL/min per 1·73 m2. Compared with an ACR of 5 mg/g, the adjusted HR for incident study-specific peripheral artery disease was 1·50 (1·41-1·59) at an ACR of 30 mg/g and 2·28 (2·12-2·44) at an ACR of 300 mg/g. The adjusted HR at an ACR of 300 mg/g versus 5 mg/g was 3·68 (95% CI 3·00-4·52) for leg amputation. eGFR and albuminuria contributed multiplicatively (eg, adjusted HR 5·76 [4·90-6·77] for incident peripheral artery disease and 10·61 [5·70-19·77] for amputation in eGFR <30 mL/min per 1·73 m2 plus ACR ≥300 mg/g or dipstick proteinuria 2+ or higher vs eGFR ≥90 mL/min per 1·73 m2 plus ACR <10 mg/g or dipstick proteinuria negative). Both eGFR and ACR significantly improved peripheral artery disease risk discrimination beyond traditional predictors, with a substantial improvement prediction of amputation with ACR (difference in c-statistic 0·058, 95% CI 0·045-0·070). Patterns were consistent across clinical subgroups. INTERPRETATION: Even mild-to-moderate chronic kidney disease conferred increased risk of incident peripheral artery disease, with a strong association between albuminuria and amputation. Clinical attention should be paid to the development of peripheral artery disease symptoms and signs in people with any stage of chronic kidney disease. FUNDING: American Heart Association, US National Kidney Foundation, and US National Institute of Diabetes and Digestive and Kidney Diseases.

New Blood Pressure-Associated Loci Identified in Meta-Analyses of 475 000 Individuals. - Kraja, Aldi T; Cook, James P; Warren, Helen R; Surendran, Praveen; Liu, Chunyu; Evangelou, Evangelos; Manning, Alisa K; Grarup, Niels; Drenos, Fotios; Sim, Xueling; Smith, Albert Vernon; Amin, Najaf; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: Genome-wide association studies have recently identified >400 loci that harbor DNA sequence variants that influence blood pressure (BP). Our earlier studies identified and validated 56 single nucleotide variants (SNVs) associated with BP from meta-analyses of exome chip genotype data. An additional 100 variants yielded suggestive evidence of association. METHODS AND RESULTS: Here, we augment the sample with 140 886 European individuals from the UK Biobank, in whom 77 of the 100 suggestive SNVs were available for association analysis with systolic BP or diastolic BP or pulse pressure. We performed 2 meta-analyses, one in individuals of European, South Asian, African, and Hispanic descent (pan-ancestry, ≈475 000), and the other in the subset of individuals of European descent (≈423 000). Twenty-one SNVs were genome-wide significant (P<5×10-8) for BP, of which 4 are new BP loci: rs9678851 (missense, SLC4A1AP), rs7437940 (AFAP1), rs13303 (missense, STAB1), and rs1055144 (7p15.2). In addition, we identified a potentially independent novel BP-associated SNV, rs3416322 (missense, SYNPO2L) at a known locus, uncorrelated with the previously reported SNVs. Two SNVs are associated with expression levels of nearby genes, and SNVs at 3 loci are associated with other traits. One SNV with a minor allele frequency <0.01, (rs3025380 at DBH) was genome-wide significant. CONCLUSIONS: We report 4 novel loci associated with BP regulation, and 1 independent variant at an established BP locus. This analysis highlights several candidate genes with variation that alter protein function or gene expression for potential follow-up.

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near HSPB7, TNXB, LRP12, LOC283335, SEPT9, and AKT2, and provide new replication evidence for a further 2 signals in EBF2 and NFKBIA Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

{Novel genetic loci associated with hippocampal volume - Hibar, D. P.; Adams, H. H. H.; Jahanshad, N.; Chauhan, G.; Stein, J. L.; Hofer, E.; Renteria, M. E.; Bis, J. C.; Arias-Vasquez, A.; Ikram, M. K.; Desrivi?res, S.; Vernooij, M. W.; et al. (Nat Commun, 2017)
The hippocampal formation is a brain structure integrally involved in episodic memory, spatial navigation, cognition and stress responsiveness. Structural abnormalities in hippocampal volume and shape are found in several common neuropsychiatric disorders. To identify the genetic underpinnings of hippocampal structure here we perform a genome-wide association study (GWAS) of 33,536 individuals and discover six independent loci significantly associated with hippocampal volume, four of them novel. Of the novel loci, three lie within genes (ASTN2, DPP4 and MAST4) and one is found 200 kb upstream of SHH. A hippocampal subfield analysis shows that a locus within the MSRB3 gene shows evidence of a localized effect along the dentate gyrus, subiculum, CA1 and fissure. Further, we show that genetic variants associated with decreased hippocampal volume are also associated with increased risk for Alzheimer's disease (rg=-0.155). Our findings suggest novel biological pathways through which human genetic variation influences hippocampal volume and risk for neuropsychiatric illness.

PCSK9 Loss-of-Function Variants, Low-Density Lipoprotein Cholesterol, and Risk of Coronary Heart Disease and Stroke: Data From 9 Studies of Blacks and Whites. - Kent, Shia T; Rosenson, Robert S; Avery, Christy L; Chen, Yii-der I; Correa, Adolfo; Cummings, Steven R; Cupples, L Adrienne; Cushman, Mary; Evans, Daniel S; Gudnason, Vilmundur; Harris, Tamara B; Howard, George; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: PCSK9 loss-of-function (LOF) variants allow for the examination of the effects of lifetime reduced low-density lipoprotein cholesterol (LDL-C) on cardiovascular events. We examined the association of PCSK9 LOF variants with LDL-C and incident coronary heart disease and stroke through a meta-analysis of data from 8 observational cohorts and 1 randomized trial of statin therapy. METHODS AND RESULTS: These 9 studies together included 17 459 blacks with 403 (2.3%) having at least 1 Y142X or C679X variant and 31 306 whites with 955 (3.1%) having at least 1 R46L variant. Unadjusted odds ratios for associations between PCSK9 LOF variants and incident coronary heart disease (851 events in blacks and 2662 events in whites) and stroke (523 events in blacks and 1660 events in whites) were calculated using pooled Mantel-Haenszel estimates with continuity correction factors. Pooling results across studies using fixed-effects inverse-variance-weighted models, PCSK9 LOF variants were associated with 35 mg/dL (95% confidence interval [CI], 32-39) lower LDL-C in blacks and 13 mg/dL (95% CI, 11-16) lower LDL-C in whites. PCSK9 LOF variants were associated with a pooled odds ratio for coronary heart disease of 0.51 (95% CI, 0.28-0.92) in blacks and 0.82 (95% CI, 0.63-1.06) in whites. PCSK9 LOF variants were not associated with incident stroke (odds ratio, 0.84; 95% CI, 0.48-1.47 in blacks and odds ratio, 1.06; 95% CI, 0.80-1.41 in whites). CONCLUSIONS: PCSK9 LOF variants were associated with lower LDL-C and coronary heart disease incidence. PCSK9 LOF variants were not associated with stroke risk.

Pharmacogenomics study of thiazide diuretics and QT interval in multi-ethnic populations: the cohorts for heart and aging research in genomic epidemiology. - Seyerle, A A; Sitlani, C M; Noordam, R; Gogarten, S M; Li, J; Li, X; Evans, D S; Sun, F; Laaksonen, M A; Isaacs, A; Kristiansson, K; Highland, H M; et al. (Pharmacogenomics J, 2017)
Thiazide diuretics, commonly used antihypertensives, may cause QT interval (QT) prolongation, a risk factor for highly fatal and difficult to predict ventricular arrhythmias. We examined whether common single-nucleotide polymorphisms (SNPs) modified the association between thiazide use and QT or its component parts (QRS interval, JT interval) by performing ancestry-specific, trans-ethnic and cross-phenotype genome-wide analyses of European (66%), African American (15%) and Hispanic (19%) populations (N=78 199), leveraging longitudinal data, incorporating corrected standard errors to account for underestimation of interaction estimate variances and evaluating evidence for pathway enrichment. Although no loci achieved genome-wide significance (P<5 × 10(-8)), we found suggestive evidence (P<5 × 10(-6)) for SNPs modifying the thiazide-QT association at 22 loci, including ion transport loci (for example, NELL1, KCNQ3). The biologic plausibility of our suggestive results and simulations demonstrating modest power to detect interaction effects at genome-wide significant levels indicate that larger studies and innovative statistical methods are warranted in future efforts evaluating thiazide-SNP interactions.The Pharmacogenomics Journal advance online publication, 18 July 2017; doi:10.1038/tpj.2017.10.

Physical activity predicts reduced plasma β amyloid in the Cardiovascular Health Study. - Stillman, Chelsea M; Lopez, Oscar L; Becker, James T; Kuller, Lewis H; Mehta, Pankaj D; Tracy, Russell P; Erickson, Kirk I (Ann Clin Transl Neurol, 2017)
OBJECTIVE: Higher levels of physical activity (PA) reduce the risk of cognitive impairment, but the underlying mechanisms are unclear. Using longitudinal data from the Cardiovascular Health Study, we examined whether PA predicted plasma Aβ levels and risk for cognitive decline 9-13 years later. METHODS: Linear and logistic regressions (controlling for APOE status, age, gender, body mass index, cardiovascular disease, brain white matter lesions, and cystatin C levels) tested associations between PA, Aβ, and cognitive impairment in a sample of 149 cognitively normal older adults (mean age 83 years). RESULTS: More PA at baseline predicted lower levels of Aβ 9-13 years later. Higher Aβ levels at year 9 predicted greater risk for cognitive impairment at year 13. Levels of Aβ at year 9 mediated the relationship between PA and cognitive impairment. INTERPRETATION: Greater PA may reduce plasma levels of a neurotoxic peptide at an age when the risk for cognitive impairment is especially high.

Predictors and outcomes of heart failure with mid-range ejection fraction. - Bhambhani, Vijeta; Kizer, Jorge R; Lima, João A C; van der Harst, Pim; Bahrami, Hossein; Nayor, Matthew; de Filippi, Christopher R; Enserro, Danielle; Blaha, Michael J; Cushman, Mary; Wang, Thomas J; Gansevoort, Ron T; et al. (Eur J Heart Fail, 2017)
AIMS: While heart failure with preserved (HFpEF) and reduced ejection fraction (HFrEF) are well described, determinants and outcomes of heart failure with mid-range ejection fraction (HFmrEF) remain unclear. We sought to examine clinical and biochemical predictors of incident HFmrEF in the community. METHODS AND RESULTS: We pooled data from four community-based longitudinal cohorts, with ascertainment of new heart failure (HF) classified into HFmrEF [ejection fraction (EF) 41-49%], HFpEF (EF ≥50%), and HFrEF (EF ≤40%). Predictors of incident HF subtypes were assessed using multivariable Cox models. Among 28 820 participants free of HF followed for a median of 12 years, there were 200 new HFmrEF cases, compared with 811 HFpEF and 1048 HFrEF. Clinical predictors of HFmrEF included age, male sex, systolic blood pressure, diabetes mellitus, and prior myocardial infarction (multivariable adjusted P ≤ 0.003 for all). Biomarkers that predicted HFmrEF included natriuretic peptides, cystatin-C, and high-sensitivity troponin (P ≤ 0.0004 for all). Natriuretic peptides were stronger predictors of HFrEF [hazard ratio (HR) 2.00 per 1 standard deviation increase, 95% confidence interval (CI) 1.81-2.20] than of HFmrEF (HR 1.51, 95% CI 1.20-1.90, P = 0.01 for difference), and did not differ in their association with incident HFmrEF and HFpEF (HR 1.56, 95% CI 1.41-1.73, P = 0.68 for difference). All-cause mortality following the onset of HFmrEF was worse than that of HFpEF (50 vs. 39 events per 1000 person-years, P = 0.02), but comparable to that of HFrEF (46 events per 1000 person-years, P = 0.78). CONCLUSIONS: We found overlap in predictors of incident HFmrEF with other HF subtypes. In contrast, mortality risk after HFmrEF was worse than HFpEF, and similar to HFrEF.

Predictors of incident epilepsy in older adults: The Cardiovascular Health Study. - Choi, Hyunmi; Pack, Alison; Elkind, Mitchell S V; Longstreth, W T; Ton, Thanh G N; Onchiri, Frankline (Neurology, 2017)
OBJECTIVE: To determine the prevalence, incidence, and predictors of epilepsy among older adults in the Cardiovascular Health Study (CHS). METHODS: We analyzed data prospectively collected in CHS and merged with data from outpatient Medicare administrative claims. We identified cases with epilepsy using self-report, antiepileptic medication, hospitalization discharge ICD-9 codes, and outpatient Medicare ICD-9 codes. We used Cox proportional hazards regression to identify factors independently associated with incident epilepsy. RESULTS: At baseline, 42% of the 5,888 participants were men and 84% were white. At enrollment, 3.7% (215 of 5,888) met the criteria for prevalent epilepsy. During 14 years of follow-up totaling 48,651 person-years, 120 participants met the criteria for incident epilepsy, yielding an incidence rate of 2.47 per 1,000 person-years. The period prevalence of epilepsy by the end of follow-up was 5.7% (335 of 5,888). Epilepsy incidence rates were significantly higher among blacks than nonblacks: 4.44 vs 2.17 per 1,000 person-years (p < 0.001). In multivariable analyses, risk of incident epilepsy was significantly higher among blacks compared to nonblacks (hazard ratio [HR] 4.04, 95% confidence interval [CI] 1.99-8.17), those 75 to 79 compared to those 65 to 69 years of age (HR 2.07, 95% CI 1.21-3.55), and those with history of stroke (HR 3.49, 95% CI 1.37-8.88). CONCLUSIONS: Epilepsy in older adults in the United States was common. Blacks, the very old, and those with history of stroke have a higher risk of incident epilepsy. The association with race remains unexplained.

Rare coding variants in PLCG2, ABI3, and TREM2 implicate microglial-mediated innate immunity in Alzheimer's disease. - Sims, Rebecca; van der Lee, Sven J; Naj, Adam C; Bellenguez, Céline; Badarinarayan, Nandini; Jakobsdottir, Johanna; Kunkle, Brian W; Boland, Anne; Raybould, Rachel; Bis, Joshua C; Martin, Eden R; Grenier-Boley, Benjamin; et al. (Nat Genet, 2017)
We identified rare coding variants associated with Alzheimer's disease in a three-stage case-control study of 85,133 subjects. In stage 1, we genotyped 34,174 samples using a whole-exome microarray. In stage 2, we tested associated variants (P < 1 × 10-4) in 35,962 independent samples using de novo genotyping and imputed genotypes. In stage 3, we used an additional 14,997 samples to test the most significant stage 2 associations (P < 5 × 10-8) using imputed genotypes. We observed three new genome-wide significant nonsynonymous variants associated with Alzheimer's disease: a protective variant in PLCG2 (rs72824905: p.Pro522Arg, P = 5.38 × 10-10, odds ratio (OR) = 0.68, minor allele frequency (MAF)cases = 0.0059, MAFcontrols = 0.0093), a risk variant in ABI3 (rs616338: p.Ser209Phe, P = 4.56 × 10-10, OR = 1.43, MAFcases = 0.011, MAFcontrols = 0.008), and a new genome-wide significant variant in TREM2 (rs143332484: p.Arg62His, P = 1.55 × 10-14, OR = 1.67, MAFcases = 0.0143, MAFcontrols = 0.0089), a known susceptibility gene for Alzheimer's disease. These protein-altering changes are in genes highly expressed in microglia and highlight an immune-related protein-protein interaction network enriched for previously identified risk genes in Alzheimer's disease. These genetic findings provide additional evidence that the microglia-mediated innate immune response contributes directly to the development of Alzheimer's disease.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Amino Acid Sequence; Case-Control Studies; Exome; Gene Expression Profiling; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Immunity, Innate; Linkage Disequilibrium; Membrane Glycoproteins; Microglia; Odds Ratio; Phospholipase C gamma; Polymorphism, Single Nucleotide; Protein Interaction Maps; Receptors, Immunologic; Sequence Homology, Amino Acid

Rare coding variants pinpoint genes that control human hematological traits. - Mousas, Abdou; Ntritsos, Georgios; Chen, Ming-Huei; Song, Ci; Huffman, Jennifer E; Tzoulaki, Ioanna; Elliott, Paul; Psaty, Bruce M; Auer, Paul L; Johnson, Andrew D; Evangelou, Evangelos; Lettre, Guillaume; et al. (PLoS Genet, 2017)
The identification of rare coding or splice site variants remains the most straightforward strategy to link genes with human phenotypes. Here, we analyzed the association between 137,086 rare (minor allele frequency (MAF) <1%) coding or splice site variants and 15 hematological traits in up to 308,572 participants. We found 56 such rare coding or splice site variants at P<5x10-8, including 31 that are associated with a blood-cell phenotype for the first time. All but one of these 31 new independent variants map to loci previously implicated in hematopoiesis by genome-wide association studies (GWAS). This includes a rare splice acceptor variant (rs146597587, MAF = 0.5%) in interleukin 33 (IL33) associated with reduced eosinophil count (P = 2.4x10-23), and lower risk of asthma (P = 2.6x10-7, odds ratio [95% confidence interval] = 0.56 [0.45-0.70]) and allergic rhinitis (P = 4.2x10-4, odds ratio = 0.55 [0.39-0.76]). The single new locus identified in our study is defined by a rare p.Arg172Gly missense variant (rs145535174, MAF = 0.05%) in plasminogen (PLG) associated with increased platelet count (P = 6.8x10-9), and decreased D-dimer concentration (P = 0.018) and platelet reactivity (P<0.03). Finally, our results indicate that searching for rare coding or splice site variants in very large sample sizes can help prioritize causal genes at many GWAS loci associated with complex human diseases and traits.
Keywords: Asthma; Databases, Genetic; Endometriosis; Female; Fibrin Fibrinogen Degradation Products; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Humans; Interleukin-33; Linear Models; Logistic Models; Male; Mutation, Missense; Phenotype; Plasminogen; Platelet Count; Polymorphism, Single Nucleotide; Principal Component Analysis; Protein Splicing; Rhinitis, Allergic; Sequence Analysis, DNA

Relationship Between Physical Activity, Body Mass Index, and Risk of Heart Failure. - Pandey, Ambarish; LaMonte, Michael; Klein, Liviu; Ayers, Colby; Psaty, Bruce M; Eaton, Charles B; Allen, Norrina B; de Lemos, James A; Carnethon, Mercedes; Greenland, Philip; Berry, Jarett D (J Am Coll Cardiol, 2017)
BACKGROUND: Lower leisure-time physical activity (LTPA) and higher body mass index (BMI) are independently associated with risk of heart failure (HF). However, it is unclear if this relationship is consistent for both heart failure with preserved ejection fraction (HFpEF) and heart failure with reduced ejection fraction (HFrEF). OBJECTIVES: This study sought to quantify dose-response associations between LTPA, BMI, and the risk of different HF subtypes. METHODS: Individual-level data from 3 cohort studies (WHI [Women's Health Initiative], MESA [Multi-Ethnic Study of Atherosclerosis], and CHS [Cardiovascular Health Study]) were pooled and participants were stratified into guideline-recommended categories of LTPA and BMI. Associations between LTPA, BMI, and risk of overall HF, HFpEF (ejection fraction ≥45%), and HFrEF (ejection fraction <45%) were assessed by using multivariable adjusted Cox models and restricted cubic splines. RESULTS: The study included 51,451 participants with 3,180 HF events (1,252 HFpEF, 914 HFrEF, and 1,014 unclassified HF). In the adjusted analysis, there was a dose-dependent association between higher LTPA levels, lower BMI, and overall HF risk. Among HF subtypes, LTPA in any dose range was not associated with HFrEF risk. In contrast, lower levels of LTPA (<500 MET-min/week) were not associated with HFpEF risk, and dose-dependent associations with lower HFpEF risk were observed at higher levels. Compared with no LTPA, higher than twice the guideline-recommended minimum LTPA levels (>1,000 MET-min/week) were associated with an 19% lower risk of HFpEF (hazard ratio: 0.81; 95% confidence interval: 0.68 to 0.97). The dose-response relationship for BMI with HFpEF risk was also more consistent than with HFrEF risk, such that increasing BMI above the normal range (≥25 kg/m(2)) was associated with a greater increase in risk of HFpEF than HFrEF. CONCLUSIONS: Our study findings show strong, dose-dependent associations between LTPA levels, BMI, and risk of overall HF. Among HF subtypes, higher LTPA levels and lower BMI were more consistently associated with lower risk of HFpEF compared with HFrEF.

Single-trait and multi-trait genome-wide association analyses identify novel loci for blood pressure in African-ancestry populations. - Liang, Jingjing; Le, Thu H; Edwards, Digna R Velez; Tayo, Bamidele O; Gaulton, Kyle J; Smith, Jennifer A; Lu, Yingchang; Jensen, Richard A; Chen, Guanjie; Yanek, Lisa R; Schwander, Karen; Tajuddin, Salman M; et al. (PLoS Genet, 2017)
Hypertension is a leading cause of global disease, mortality, and disability. While individuals of African descent suffer a disproportionate burden of hypertension and its complications, they have been underrepresented in genetic studies. To identify novel susceptibility loci for blood pressure and hypertension in people of African ancestry, we performed both single and multiple-trait genome-wide association analyses. We analyzed 21 genome-wide association studies comprised of 31,968 individuals of African ancestry, and validated our results with additional 54,395 individuals from multi-ethnic studies. These analyses identified nine loci with eleven independent variants which reached genome-wide significance (P < 1.25×10-8) for either systolic and diastolic blood pressure, hypertension, or for combined traits. Single-trait analyses identified two loci (TARID/TCF21 and LLPH/TMBIM4) and multiple-trait analyses identified one novel locus (FRMD3) for blood pressure. At these three loci, as well as at GRP20/CDH17, associated variants had alleles common only in African-ancestry populations. Functional annotation showed enrichment for genes expressed in immune and kidney cells, as well as in heart and vascular cells/tissues. Experiments driven by these findings and using angiotensin-II induced hypertension in mice showed altered kidney mRNA expression of six genes, suggesting their potential role in hypertension. Our study provides new evidence for genes related to hypertension susceptibility, and the need to study African-ancestry populations in order to identify biologic factors contributing to hypertension.
Keywords: African Americans; Animals; Basic Helix-Loop-Helix Transcription Factors; Blood Pressure; Cadherins; Case-Control Studies; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Membrane Proteins; Mice; Multifactorial Inheritance; Polymorphism, Single Nucleotide

Systems biology approach to late-onset Alzheimer's disease genome-wide association study identifies novel candidate genes validated using brain expression data and Caenorhabditis elegans experiments. - Mukherjee, Shubhabrata; Russell, Joshua C; Carr, Daniel T; Burgess, Jeremy D; Allen, Mariet; Serie, Daniel J; Boehme, Kevin L; Kauwe, John S K; Naj, Adam C; Fardo, David W; Dickson, Dennis W; Montine, Thomas J; et al. (Alzheimers Dement, 2017)
INTRODUCTION: We sought to determine whether a systems biology approach may identify novel late-onset Alzheimer's disease (LOAD) loci. METHODS: We performed gene-wide association analyses and integrated results with human protein-protein interaction data using network analyses. We performed functional validation on novel genes using a transgenic Caenorhabditis elegans Aβ proteotoxicity model and evaluated novel genes using brain expression data from people with LOAD and other neurodegenerative conditions. RESULTS: We identified 13 novel candidate LOAD genes outside chromosome 19. Of those, RNA interference knockdowns of the C. elegans orthologs of UBC, NDUFS3, EGR1, and ATP5H were associated with Aβ toxicity, and NDUFS3, SLC25A11, ATP5H, and APP were differentially expressed in the temporal cortex. DISCUSSION: Network analyses identified novel LOAD candidate genes. We demonstrated a functional role for four of these in a C. elegans model and found enrichment of differentially expressed genes in the temporal cortex.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Animals, Genetically Modified; Antigens, Neoplasm; Caenorhabditis elegans; Disease Models, Animal; Early Growth Response Protein 1; Female; Gene Expression Regulation; Genome-Wide Association Study; Heparin-binding EGF-like Growth Factor; Humans; Male; Membrane Transport Proteins; Mitochondrial ADP, ATP Translocases; NADH Dehydrogenase; Polymorphism, Single Nucleotide; Protein Interaction Maps; RNA Interference; Systems Biology; Temporal Lobe

Thyroid Function Within the Normal Range, Subclinical Hypothyroidism, and the Risk of Atrial Fibrillation. - Baumgartner, Christine; da Costa, Bruno R; Collet, Tinh-Hai; Feller, Martin; Floriani, Carmen; Bauer, Douglas C; Cappola, Anne R; Heckbert, Susan R; Ceresini, Graziano; Gussekloo, Jacobijn; den Elzen, Wendy P J; Peeters, Robin P; et al. (Circulation, 2017)
BACKGROUND: Atrial fibrillation (AF) is a highly prevalent disorder leading to heart failure, stroke, and death. Enhanced understanding of modifiable risk factors may yield opportunities for prevention. The risk of AF is increased in subclinical hyperthyroidism, but it is uncertain whether variations in thyroid function within the normal range or subclinical hypothyroidism are also associated with AF. METHODS: We conducted a systematic review and obtained individual participant data from prospective cohort studies that measured thyroid function at baseline and assessed incident AF. Studies were identified from MEDLINE and EMBASE databases from inception to July 27, 2016. The euthyroid state was defined as thyroid-stimulating hormone (TSH) 0.45 to 4.49 mIU/L, and subclinical hypothyroidism as TSH 4.5 to 19.9 mIU/L with free thyroxine (fT4) levels within reference range. The association of TSH levels in the euthyroid and subclinical hypothyroid range with incident AF was examined by using Cox proportional hazards models. In euthyroid participants, we additionally examined the association between fT4 levels and incident AF. RESULTS: Of 30 085 participants from 11 cohorts (278 955 person-years of follow-up), 1958 (6.5%) had subclinical hypothyroidism and 2574 individuals (8.6%) developed AF during follow-up. TSH at baseline was not significantly associated with incident AF in euthyroid participants or those with subclinical hypothyroidism. Higher fT4 levels at baseline in euthyroid individuals were associated with increased AF risk in age- and sex-adjusted analyses (hazard ratio, 1.45; 95% confidence interval, 1.26-1.66, for the highest quartile versus the lowest quartile of fT4; P for trend ≤0.001 across quartiles). Estimates did not substantially differ after further adjustment for preexisting cardiovascular disease. CONCLUSIONS: In euthyroid individuals, higher circulating fT4 levels, but not TSH levels, are associated with increased risk of incident AF.
Keywords: Adult; Aged; Aged, 80 and over; Asymptomatic Diseases; Atrial Fibrillation; Biomarkers; Chi-Square Distribution; Female; Humans; Hypothyroidism; Incidence; Male; Middle Aged; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Assessment; Risk Factors; Thyroid Function Tests; Thyroid Gland; Thyrotropin; Thyroxine; Time Factors; Young Adult

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci. - Fernandez-Rhodes, Lindsay; Gong, Jian; Haessler, Jeffrey; Franceschini, Nora; Graff, Mariaelisa; Nishimura, Katherine K; Wang, Yujie; Highland, Heather M; Yoneyama, Sachiko; Bush, William S; Goodloe, Robert; Ritchie, Marylyn D; et al. (Hum Genet, 2017)
Most body mass index (BMI) genetic loci have been identified in studies of primarily European ancestries. The effect of these loci in other racial/ethnic groups is less clear. Thus, we aimed to characterize the generalizability of 170 established BMI variants, or their proxies, to diverse US populations and trans-ethnically fine-map 36 BMI loci using a sample of >102,000 adults of African, Hispanic/Latino, Asian, European and American Indian/Alaskan Native descent from the Population Architecture using Genomics and Epidemiology Study. We performed linear regression of the natural log of BMI (18.5-70 kg/m(2)) on the additive single nucleotide polymorphisms (SNPs) at BMI loci on the MetaboChip (Illumina, Inc.), adjusting for age, sex, population stratification, study site, or relatedness. We then performed fixed-effect meta-analyses and a Bayesian trans-ethnic meta-analysis to empirically cluster by allele frequency differences. Finally, we approximated conditional and joint associations to test for the presence of secondary signals. We noted directional consistency with the previously reported risk alleles beyond what would have been expected by chance (binomial p < 0.05). Nearly, a quarter of the previously described BMI index SNPs and 29 of 36 densely-genotyped BMI loci on the MetaboChip replicated/generalized in trans-ethnic analyses. We observed multiple signals at nine loci, including the description of seven loci with novel multiple signals. This study supports the generalization of most common genetic loci to diverse ancestral populations and emphasizes the importance of dense multiethnic genomic data in refining the functional variation at genetic loci of interest and describing several loci with multiple underlying genetic variants.
Keywords: Body Mass Index; Ethnic Groups; Genetics, Population; Humans; Obesity

Assessment of the genetic and clinical determinants of fracture risk: genome wide association and mendelian randomisation study. - Trajanoska, Katerina; Morris, John A; Oei, Ling; Zheng, Hou-Feng; Evans, David M; Kiel, Douglas P; Ohlsson, Claes; Richards, J Brent; Rivadeneira, Fernando (BMJ, 2018)
OBJECTIVES: To identify the genetic determinants of fracture risk and assess the role of 15 clinical risk factors on osteoporotic fracture risk. DESIGN: Meta-analysis of genome wide association studies (GWAS) and a two-sample mendelian randomisation approach. SETTING: 25 cohorts from Europe, United States, east Asia, and Australia with genome wide genotyping and fracture data. PARTICIPANTS: A discovery set of 37 857 fracture cases and 227 116 controls; with replication in up to 147 200 fracture cases and 150 085 controls. Fracture cases were defined as individuals (>18 years old) who had fractures at any skeletal site confirmed by medical, radiological, or questionnaire reports. Instrumental variable analyses were performed to estimate effects of 15 selected clinical risk factors for fracture in a two-sample mendelian randomisation framework, using the largest previously published GWAS meta-analysis of each risk factor. RESULTS: Of 15 fracture associated loci identified, all were also associated with bone mineral density and mapped to genes clustering in pathways known to be critical to bone biology (eg, , , and ) or novel pathways (, , and ). Mendelian randomisation analyses showed a clear effect of bone mineral density on fracture risk. One standard deviation decrease in genetically determined bone mineral density of the femoral neck was associated with a 55% increase in fracture risk (odds ratio 1.55 (95% confidence interval 1.48 to 1.63; P=1.5×10). Hand grip strength was inversely associated with fracture risk, but this result was not significant after multiple testing correction. The remaining clinical risk factors (including vitamin D levels) showed no evidence for an effect on fracture. CONCLUSIONS: This large scale GWAS meta-analysis for fracture identified 15 genetic determinants of fracture, all of which also influenced bone mineral density. Among the clinical risk factors for fracture assessed, only bone mineral density showed a major causal effect on fracture. Genetic predisposition to lower levels of vitamin D and estimated calcium intake from dairy sources were not associated with fracture risk.

Association between subclinical thyroid dysfunction and change in bone mineral density in prospective cohorts. - Segna, D; Bauer, D C; Feller, M; Schneider, C; Fink, H A; Aubert, C E; Collet, T-H; da Costa, B R; Fischer, K; Peeters, R P; Cappola, A R; Blum, M R; et al. (J Intern Med, 2018)
BACKGROUND: Subclinical hyperthyroidism (SHyper) has been associated with increased risk of hip and other fractures, but the linking mechanisms remain unclear. OBJECTIVE: To investigate the association between subclinical thyroid dysfunction and bone loss. METHODS: Individual participant data analysis was performed after a systematic literature search in MEDLINE/EMBASE (1946-2016). Two reviewers independently screened and selected prospective cohorts providing baseline thyroid status and serial bone mineral density (BMD) measurements. We classified thyroid status as euthyroidism (thyroid-stimulating hormone [TSH] 0.45-4.49 mIU/L), SHyper (TSH < 0.45 mIU/L) and subclinical hypothyroidism (SHypo, TSH ≥ 4.50-19.99 mIU/L) both with normal free thyroxine levels. Our primary outcome was annualized percentage BMD change (%ΔBMD) from serial dual X-ray absorptiometry scans of the femoral neck, total hip and lumbar spine, obtained from multivariable regression in a random-effects two-step approach. RESULTS: Amongst 5458 individuals (median age 72 years, 49.1% women) from six prospective cohorts, 451 (8.3%) had SHypo and 284 (5.2%) had SHyper. During 36 569 person-years of follow-up, those with SHyper had a greater annual bone loss at the femoral neck versus euthyroidism: %ΔBMD = -0.18 (95% CI: -0.34, -0.02; I2 = 0%), with a nonstatistically significant pattern at the total hip: %ΔBMD = -0.14 (95% CI: -0.38, 0.10; I2 = 53%), but not at the lumbar spine: %ΔBMD = 0.03 (95% CI: -0.30, 0.36; I2 = 25%); especially participants with TSH < 0.10 mIU/L showed an increased bone loss in the femoral neck (%Δ BMD = -0.59; [95% CI: -0.99, -0.19]) and total hip region (%ΔBMD = -0.46 [95% CI: -1.05, -0.13]). In contrast, SHypo was not associated with bone loss at any site. CONCLUSION: Amongst adults, SHyper was associated with increased femoral neck bone loss, potentially contributing to the increased fracture risk.
Keywords: Aged; Asymptomatic Diseases; Bone Density; Female; Fractures, Bone; Humans; Hyperthyroidism; Hypothyroidism; Male; Risk Factors

Association of Cardiovascular Biomarkers With Incident Heart Failure With Preserved and Reduced Ejection Fraction. - de Boer, Rudolf A; Nayor, Matthew; deFilippi, Christopher R; Enserro, Danielle; Bhambhani, Vijeta; Kizer, Jorge R; Blaha, Michael J; Brouwers, Frank P; Cushman, Mary; Lima, João A C; Bahrami, Hossein; van der Harst, Pim; et al. (JAMA Cardiol, 2018)
Importance: Nearly half of all patients with heart failure have preserved ejection fraction (HFpEF) as opposed to reduced ejection fraction (HFrEF), yet associations of biomarkers with future heart failure subtype are incompletely understood. Objective: To evaluate the associations of 12 cardiovascular biomarkers with incident HFpEF vs HFrEF among adults from the general population. Design, Setting, and Participants: This study included 4 longitudinal community-based cohorts: the Cardiovascular Health Study (1989-1990; 1992-1993 for supplemental African-American cohort), the Framingham Heart Study (1995-1998), the Multi-Ethnic Study of Atherosclerosis (2000-2002), and the Prevention of Renal and Vascular End-stage Disease study (1997-1998). Each cohort had prospective ascertainment of incident HFpEF and HFrEF. Data analysis was performed from June 25, 2015, to November 9, 2017. Exposures: The following biomarkers were examined: N-terminal pro B-type natriuretic peptide or brain natriuretic peptide, high-sensitivity troponin T or I, C-reactive protein (CRP), urinary albumin to creatinine ratio (UACR), renin to aldosterone ratio, D-dimer, fibrinogen, soluble suppressor of tumorigenicity, galectin-3, cystatin C, plasminogen activator inhibitor 1, and interleukin 6. Main Outcomes and Measures: Development of incident HFpEF and incident HFrEF. Results: Among the 22 756 participants in these 4 cohorts (12 087 women and 10 669 men; mean [SD] age, 60 [13] years) in the study, during a median follow-up of 12 years, 633 participants developed incident HFpEF, and 841 developed HFrEF. In models adjusted for clinical risk factors of heart failure, 2 biomarkers were significantly associated with incident HFpEF: UACR (hazard ratio [HR], 1.33; 95% CI, 1.20-1.48; P < .001) and natriuretic peptides (HR, 1.27; 95% CI, 1.16-1.40; P < .001), with suggestive associations for high-sensitivity troponin (HR, 1.11; 95% CI, 1.03-1.19; P = .008), plasminogen activator inhibitor 1 (HR, 1.22; 95% CI, 1.03-1.45; P = .02), and fibrinogen (HR, 1.12; 95% CI, 1.03-1.22; P = .01). By contrast, 6 biomarkers were associated with incident HFrEF: natriuretic peptides (HR, 1.54; 95% CI, 1.41-1.68; P < .001), UACR (HR, 1.21; 95% CI, 1.11-1.32; P < .001), high-sensitivity troponin (HR, 1.37; 95% CI, 1.29-1.46; P < .001), cystatin C (HR, 1.19; 95% CI, 1.11-1.27; P < .001), D-dimer (HR, 1.22; 95% CI, 1.11-1.35; P < .001), and CRP (HR, 1.19; 95% CI, 1.11-1.28; P < .001). When directly compared, natriuretic peptides, high-sensitivity troponin, and CRP were more strongly associated with HFrEF compared with HFpEF. Conclusions and Relevance: Biomarkers of renal dysfunction, endothelial dysfunction, and inflammation were associated with incident HFrEF. By contrast, only natriuretic peptides and UACR were associated with HFpEF. These findings highlight the need for future studies focused on identifying novel biomarkers of the risk of HFpEF.

Atrial Cardiopathy and the Risk of Ischemic Stroke in the CHS (Cardiovascular Health Study). - Kamel, Hooman; Bartz, Traci M; Elkind, Mitchell S V; Okin, Peter M; Thacker, Evan L; Patton, Kristen K; Stein, Phyllis K; deFilippi, Christopher R; Gottesman, Rebecca F; Heckbert, Susan R; Kronmal, Richard A; Soliman, Elsayed Z; et al. (Stroke, 2018)
BACKGROUND AND PURPOSE: Emerging evidence suggests that an underlying atrial cardiopathy may result in thromboembolism before atrial fibrillation (AF) develops. We examined the association between various markers of atrial cardiopathy and the risk of ischemic stroke. METHODS: The CHS (Cardiovascular Health Study) prospectively enrolled community-dwelling adults ≥65 years of age. For this study, we excluded participants diagnosed with stroke or AF before baseline. Exposures were several markers of atrial cardiopathy: baseline P-wave terminal force in ECG lead V, left atrial dimension on echocardiogram, and N terminal pro B type natriuretic peptide (NT-proBNP), as well as incident AF. Incident AF was ascertained from 12-lead electrocardiograms at annual study visits for the first decade after study enrollment and from inpatient and outpatient Medicare data throughout follow-up. The primary outcome was incident ischemic stroke. We used Cox proportional hazards models that included all 4 atrial cardiopathy markers along with adjustment for demographic characteristics and established vascular risk factors. RESULTS: Among 3723 participants who were free of stroke and AF at baseline and who had data on all atrial cardiopathy markers, 585 participants (15.7%) experienced an incident ischemic stroke during a median 12.9 years of follow-up. When all atrial cardiopathy markers were combined in 1 Cox model, we found significant associations with stroke for P-wave terminal force in ECG lead V (hazard ratio per 1000 μV*ms 1.04; 95% confidence interval, 1.001-1.08), log-transformed NT-proBNP (hazard ratio per doubling of NT-proBNP, 1.09; 95% confidence interval, 1.03-1.16), and incident AF (hazard ratio, 2.04; 95% confidence interval, 1.67-2.48) but not left atrial dimension (hazard ratio per cm, 0.96; 95% confidence interval, 0.84-1.10). CONCLUSIONS: In addition to clinically apparent AF, other evidence of abnormal atrial substrate is associated with subsequent ischemic stroke. This finding is consistent with the hypothesis that thromboembolism from the left atrium may occur in the setting of several different manifestations of atrial disease.

Common and Rare Coding Genetic Variation Underlying the Electrocardiographic PR Interval. - Lin, Honghuang; van Setten, Jessica; Smith, Albert V; Bihlmeyer, Nathan A; Warren, Helen R; Brody, Jennifer A; Radmanesh, Farid; Hall, Leanne; Grarup, Niels; Müller-Nurasyid, Martina; Boutin, Thibaud; Verweij, Niek; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Electrical conduction from the cardiac sinoatrial node to the ventricles is critical for normal heart function. Genome-wide association studies have identified more than a dozen common genetic loci that are associated with PR interval. However, it is unclear whether rare and low-frequency variants also contribute to PR interval heritability. METHODS: We performed large-scale meta-analyses of the PR interval that included 83 367 participants of European ancestry and 9436 of African ancestry. We examined both common and rare variants associated with the PR interval. RESULTS: We identified 31 genetic loci that were significantly associated with PR interval after Bonferroni correction (<1.2×10), including 11 novel loci that have not been reported previously. Many of these loci are involved in heart morphogenesis. In gene-based analysis, we found that multiple rare variants at (=5.9×10) and (=1.1×10) were associated with PR interval. locus also was implicated in the common variant analysis, whereas was a novel locus. CONCLUSIONS: We identified common variants at 11 novel loci and rare variants within 2 gene regions that were significantly associated with PR interval. Our findings provide novel insights to the current understanding of atrioventricular conduction, which is critical for cardiac activity and an important determinant of health.

Common Coding Variants in Are Associated With the Nav1.8 Late Current and Cardiac Conduction. - Macri, Vincenzo; Brody, Jennifer A; Arking, Dan E; Hucker, William J; Yin, Xiaoyan; Lin, Honghuang; Mills, Robert W; Sinner, Moritz F; Lubitz, Steven A; Liu, Ching-Ti; Morrison, Alanna C; Alonso, Alvaro; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Genetic variants at the / locus are strongly associated with electrocardiographic PR and QRS intervals. While is the canonical cardiac sodium channel gene, the role of in cardiac conduction is less well characterized. METHODS: We sequenced the locus in 3699 European-ancestry individuals to identify variants associated with cardiac conduction, and replicated our findings in 21,000 individuals of European ancestry. We examined association with expression in human atrial tissue. We explored the biophysical effect of variation on channel function using cellular electrophysiology. RESULTS: We identified 2 intronic single nucleotide polymorphisms in high linkage disequilibrium (  =0.86) with each other to be the strongest signals for PR (rs10428132, β=-4.74, =1.52×10) and QRS intervals (rs6599251, QRS β=-0.73; =1.2×10), respectively. Although these variants were not associated with or expression in human atrial tissue (n=490), they were in high linkage disequilibrium (  ≥0.72) with a common missense variant, rs6795970 (V1073A). In total, we identified 7 missense variants, 4 of which (I962V, P1045T, V1073A, and L1092P) were associated with cardiac conduction. These 4 missense variants cluster in the cytoplasmic linker of the second and third domains of the SCN10A protein and together form 6 common haplotypes. Using cellular electrophysiology, we found that haplotypes associated with shorter PR intervals had a significantly larger percentage of late current compared with wild-type (I962V+V1073A+L1092P, 20.2±3.3%, =0.03, and I962V+V1073A, 22.4±0.8%, =0.0004 versus wild-type 11.7±1.6%), and the haplotype associated with the longest PR interval had a significantly smaller late current percentage (P1045T, 6.4±1.2%, =0.03). CONCLUSIONS: Our findings suggest an association between genetic variation in , the late sodium current, and alterations in cardiac conduction.

A comprehensive evaluation of the genetic architecture of sudden cardiac arrest. - Ashar, Foram N; Mitchell, Rebecca N; Albert, Christine M; Newton-Cheh, Christopher; Brody, Jennifer A; Müller-Nurasyid, Martina; Moes, Anna; Meitinger, Thomas; Mak, Angel; Huikuri, Heikki; Junttila, M Juhani; Goyette, Philippe; et al. (Eur Heart J, 2018)
Aims: Sudden cardiac arrest (SCA) accounts for 10% of adult mortality in Western populations. We aim to identify potential loci associated with SCA and to identify risk factors causally associated with SCA. Methods and results: We carried out a large genome-wide association study (GWAS) for SCA (n = 3939 cases, 25 989 non-cases) to examine common variation genome-wide and in candidate arrhythmia genes. We also exploited Mendelian randomization (MR) methods using cross-trait multi-variant genetic risk score associations (GRSA) to assess causal relationships of 18 risk factors with SCA. No variants were associated with SCA at genome-wide significance, nor were common variants in candidate arrhythmia genes associated with SCA at nominal significance. Using cross-trait GRSA, we established genetic correlation between SCA and (i) coronary artery disease (CAD) and traditional CAD risk factors (blood pressure, lipids, and diabetes), (ii) height and BMI, and (iii) electrical instability traits (QT and atrial fibrillation), suggesting aetiologic roles for these traits in SCA risk. Conclusions: Our findings show that a comprehensive approach to the genetic architecture of SCA can shed light on the determinants of a complex life-threatening condition with multiple influencing factors in the general population. The results of this genetic analysis, both positive and negative findings, have implications for evaluating the genetic architecture of patients with a family history of SCA, and for efforts to prevent SCA in high-risk populations and the general community.

{Dairy Consumption and Body Mass Index Among Adults: Mendelian Randomization Analysis of 184802 Individuals from 25 Studies - Huang, T.; Ding, M.; Bergholdt, H. K. M.; Wang, T.; Heianza, Y.; Sun, D.; Frazier-Wood, A. C.; Aslibekyan, S.; North, K. E.; Voortman, T.; Graff, M.; Smith, C. E.; et al. (Clin Chem, 2018)
Associations between dairy intake and body mass index (BMI) have been inconsistently observed in epidemiological studies, and the causal relationship remains ill defined.\ We performed Mendelian randomization (MR) analysis using an established dairy intake-associated genetic polymorphism located upstream of the lactase gene (LCT-13910 C/T, rs4988235) as an instrumental variable (IV). Linear regression models were fitted to analyze associations between (a) dairy intake and BMI, (b) rs4988235 and dairy intake, and (c) rs4988235 and BMI in each study. The causal effect of dairy intake on BMI was quantified by IV estimators among 184802 participants from 25 studies.\ Higher dairy intake was associated with higher BMI (β = 0.03 kg/m2 per serving/day; 95% CI, 0.00-0.06; P = 0.04), whereas the LCT genotype with 1 or 2 T allele was significantly associated with 0.20 (95% CI, 0.14-0.25) serving/day higher dairy intake (P = 3.15 × 10-12) and 0.12 (95% CI, 0.06-0.17) kg/m2 higher BMI (P = 2.11 × 10-5). MR analysis showed that the genetically determined higher dairy intake was significantly associated with higher BMI (β = 0.60 kg/m2 per serving/day; 95% CI, 0.27-0.92; P = 3.0 × 10-4).\ The present study provides strong evidence to support a causal effect of higher dairy intake on increased BMI among adults.

DNA methylation age is associated with an altered hemostatic profile in a multi-ethnic meta-analysis. - Ward-Caviness, Cavin K; Huffman, Jennifer E; Evertt, Karl; Germain, Marine; van Dongen, Jenny; Hill, W David; Jhun, Min A; Brody, Jennifer A; Ghanbari, Mohsen; Du, Lei; Roetker, Nicholas S; de Vries, Paul S; et al. (Blood, 2018)
Many hemostatic factors are associated with age and age-related diseases, however much remains unknown about the biological mechanisms linking aging and hemostatic factors. DNA methylation is a novel means by which to assess epigenetic aging, which is a measure of age and the aging processes as determined by altered epigenetic states. We used a meta-analysis approach to examine the association between measures of epigenetic aging and hemostatic factors, as well as a clotting time measure. For fibrinogen, we used European and African-ancestry participants who were meta-analyzed separately and combined via a random effects meta-analysis. All other measures only included participants of European-ancestry. We found that 1-year higher extrinsic epigenetic age as compared to chronological age was associated with higher fibrinogen (0.004 g/L per year; 95% CI: 0.001, 0.007; P = 0.01) and plasminogen activator inhibitor 1 (PAI-1; 0.13 U/mL per year; 95% CI: 0.07, 0.20; P = 6.6x10-5) concentrations as well as lower activated partial thromboplastin time, a measure of clotting time. We replicated PAI-1 associations using an independent cohort. To further elucidate potential functional mechanisms we associated epigenetic aging with expression levels of the PAI-1 protein encoding gene (SERPINE1) and the three fibrinogen subunit-encoding genes (FGA, FGG, and FGB), in both peripheral blood and aorta intima-media samples. We observed associations between accelerated epigenetic aging and transcription of FGG in both tissues. Collectively, our results indicate that accelerated epigenetic aging is associated with a pro-coagulation hemostatic profile, and that epigenetic aging may regulate hemostasis in part via gene transcription.

Equalization of four cardiovascular risk algorithms after systematic recalibration: individual-participant meta-analysis of 86 prospective studies. - Pennells, Lisa; Kaptoge, Stephen; Wood, Angela; Sweeting, Mike; Zhao, Xiaohui; White, Ian; Burgess, Stephen; Willeit, Peter; Bolton, Thomas; Moons, Karel G M; van der Schouw, Yvonne T; Selmer, Randi; et al. (Eur Heart J, 2018)
Aims: There is debate about the optimum algorithm for cardiovascular disease (CVD) risk estimation. We conducted head-to-head comparisons of four algorithms recommended by primary prevention guidelines, before and after 'recalibration', a method that adapts risk algorithms to take account of differences in the risk characteristics of the populations being studied. Methods and results: Using individual-participant data on 360 737 participants without CVD at baseline in 86 prospective studies from 22 countries, we compared the Framingham risk score (FRS), Systematic COronary Risk Evaluation (SCORE), pooled cohort equations (PCE), and Reynolds risk score (RRS). We calculated measures of risk discrimination and calibration, and modelled clinical implications of initiating statin therapy in people judged to be at 'high' 10 year CVD risk. Original risk algorithms were recalibrated using the risk factor profile and CVD incidence of target populations. The four algorithms had similar risk discrimination. Before recalibration, FRS, SCORE, and PCE over-predicted CVD risk on average by 10%, 52%, and 41%, respectively, whereas RRS under-predicted by 10%. Original versions of algorithms classified 29-39% of individuals aged ≥40 years as high risk. By contrast, recalibration reduced this proportion to 22-24% for every algorithm. We estimated that to prevent one CVD event, it would be necessary to initiate statin therapy in 44-51 such individuals using original algorithms, in contrast to 37-39 individuals with recalibrated algorithms. Conclusion: Before recalibration, the clinical performance of four widely used CVD risk algorithms varied substantially. By contrast, simple recalibration nearly equalized their performance and improved modelled targeting of preventive action to clinical need.

Exome Chip Analysis Identifies Low-Frequency and Rare Variants in for White Matter Hyperintensities on Brain Magnetic Resonance Imaging. - Jian, Xueqiu; Satizabal, Claudia L; Smith, Albert V; Wittfeld, Katharina; Bis, Joshua C; Smith, Jennifer A; Hsu, Fang-Chi; Nho, Kwangsik; Hofer, Edith; Hagenaars, Saskia P; Nyquist, Paul A; Mishra, Aniket; et al. (Stroke, 2018)
BACKGROUND AND PURPOSE: White matter hyperintensities (WMH) on brain magnetic resonance imaging are typical signs of cerebral small vessel disease and may indicate various preclinical, age-related neurological disorders, such as stroke. Though WMH are highly heritable, known common variants explain a small proportion of the WMH variance. The contribution of low-frequency/rare coding variants to WMH burden has not been explored. METHODS: In the discovery sample we recruited 20 719 stroke/dementia-free adults from 13 population-based cohort studies within the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, among which 17 790 were of European ancestry and 2929 of African ancestry. We genotyped these participants at ≈250 000 mostly exonic variants with Illumina HumanExome BeadChip arrays. We performed ethnicity-specific linear regression on rank-normalized WMH in each study separately, which were then combined in meta-analyses to test for association with single variants and genes aggregating the effects of putatively functional low-frequency/rare variants. We then sought replication of the top findings in 1192 adults (European ancestry) with whole exome/genome sequencing data from 2 independent studies. RESULTS: At 17q25, we confirmed the association of multiple common variants in , , and (<6×10). We also identified a novel association with 2 low-frequency nonsynonymous variants in (lead, rs34136221; =4.5×10) partially independent of known common signal (=1.4×10). We further identified a locus at 2q33 containing common variants in , , and (lead, rs2351524; =1.9×10). Although our novel findings were not replicated because of limited power and possible differences in study design, meta-analysis of the discovery and replication samples yielded stronger association for the 2 low-frequency variants (=2.8×10). CONCLUSIONS: Both common and low-frequency/rare functional variants influence WMH. Larger replication and experimental follow-up are essential to confirm our findings and uncover the biological causal mechanisms of age-related WMH.

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.

ExomeChip-Wide Analysis of 95 626 Individuals Identifies 10 Novel Loci Associated With QT and JT Intervals. - Bihlmeyer, Nathan A; Brody, Jennifer A; Smith, Albert Vernon; Warren, Helen R; Lin, Honghuang; Isaacs, Aaron; Liu, Ching-Ti; Marten, Jonathan; Radmanesh, Farid; Hall, Leanne M; Grarup, Niels; Mei, Hao; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: QT interval, measured through a standard ECG, captures the time it takes for the cardiac ventricles to depolarize and repolarize. JT interval is the component of the QT interval that reflects ventricular repolarization alone. Prolonged QT interval has been linked to higher risk of sudden cardiac arrest. METHODS AND RESULTS: We performed an ExomeChip-wide analysis for both QT and JT intervals, including 209 449 variants, both common and rare, in 17 341 genes from the Illumina Infinium HumanExome BeadChip. We identified 10 loci that modulate QT and JT interval duration that have not been previously reported in the literature using single-variant statistical models in a meta-analysis of 95 626 individuals from 23 cohorts (comprised 83 884 European ancestry individuals, 9610 blacks, 1382 Hispanics, and 750 Asians). This brings the total number of ventricular repolarization associated loci to 45. In addition, our approach of using coding variants has highlighted the role of 17 specific genes for involvement in ventricular repolarization, 7 of which are in novel loci. CONCLUSIONS: Our analyses show a role for myocyte internal structure and interconnections in modulating QT interval duration, adding to previous known roles of potassium, sodium, and calcium ion regulation, as well as autonomic control. We anticipate that these discoveries will open new paths to the goal of making novel remedies for the prevention of lethal ventricular arrhythmias and sudden cardiac arrest.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genetic Variants Associated with Circulating Fibroblast Growth Factor 23. - Robinson-Cohen, Cassianne; Bartz, Traci M; Lai, Dongbing; Ikizler, T Alp; Peacock, Munro; Imel, Erik A; Michos, Erin D; Foroud, Tatiana M; Åkesson, Kristina; Taylor, Kent D; Malmgren, Linnea; Matsushita, Kunihiro; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Fibroblast growth factor 23 (FGF23), a bone-derived hormone that regulates phosphorus and vitamin D metabolism, contributes to the pathogenesis of mineral and bone disorders in CKD and is an emerging cardiovascular risk factor. Central elements of FGF23 regulation remain incompletely understood; genetic variation may help explain interindividual differences. METHODS: We performed a meta-analysis of genome-wide association studies of circulating FGF23 concentrations among 16,624 participants of European ancestry from seven cohort studies, excluding participants with eGFR<30 ml/min per 1.73 m to focus on FGF23 under normal conditions. We evaluated the association of single-nucleotide polymorphisms (SNPs) with natural log-transformed FGF23 concentration, adjusted for age, sex, study site, and principal components of ancestry. A second model additionally adjusted for BMI and eGFR. RESULTS: We discovered 154 SNPs from five independent regions associated with FGF23 concentration. The SNP with the strongest association, rs17216707 (=3.0×10), lies upstream of , which encodes the primary catabolic enzyme for 1,25-dihydroxyvitamin D and 25-hydroxyvitamin D. Each additional copy of the T allele at this locus is associated with 5% higher FGF23 concentration. Another locus strongly associated with variations in FGF23 concentration is rs11741640, within and upstream of (a gene involved in renal phosphate transport). Additional adjustment for BMI and eGFR did not materially alter the magnitude of these associations. Another top locus (within , the ABO blood group transferase gene) was no longer statistically significant at the genome-wide level. CONCLUSIONS: Common genetic variants located near genes involved in vitamin D metabolism and renal phosphate transport are associated with differences in circulating FGF23 concentrations.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide analyses identify a role for SLC17A4 and AADAT in thyroid hormone regulation. - Teumer, Alexander; Chaker, Layal; Groeneweg, Stefan; Li, Yong; Di Munno, Celia; Barbieri, Caterina; Schultheiss, Ulla T; Traglia, Michela; Ahluwalia, Tarunveer S; Akiyama, Masato; Appel, Emil Vincent R; Arking, Dan E; et al. (Nat Commun, 2018)
Thyroid dysfunction is an important public health problem, which affects 10% of the general population and increases the risk of cardiovascular morbidity and mortality. Many aspects of thyroid hormone regulation have only partly been elucidated, including its transport, metabolism, and genetic determinants. Here we report a large meta-analysis of genome-wide association studies for thyroid function and dysfunction, testing 8 million genetic variants in up to 72,167 individuals. One-hundred-and-nine independent genetic variants are associated with these traits. A genetic risk score, calculated to assess their combined effects on clinical end points, shows significant associations with increased risk of both overt (Graves' disease) and subclinical thyroid disease, as well as clinical complications. By functional follow-up on selected signals, we identify a novel thyroid hormone transporter (SLC17A4) and a metabolizing enzyme (AADAT). Together, these results provide new knowledge about thyroid hormone physiology and disease, opening new possibilities for therapeutic targets.

Genome-wide association study in 79,366 European-ancestry individuals informs the genetic architecture of 25-hydroxyvitamin D levels. - Jiang, Xia; O'Reilly, Paul F; Aschard, Hugues; Hsu, Yi-Hsiang; Richards, J Brent; Dupuis, Josée; Ingelsson, Erik; Karasik, David; Pilz, Stefan; Berry, Diane; Kestenbaum, Bryan; Zheng, Jusheng; et al. (Nat Commun, 2018)
Vitamin D is a steroid hormone precursor that is associated with a range of human traits and diseases. Previous GWAS of serum 25-hydroxyvitamin D concentrations have identified four genome-wide significant loci (GC, NADSYN1/DHCR7, CYP2R1, CYP24A1). In this study, we expand the previous SUNLIGHT Consortium GWAS discovery sample size from 16,125 to 79,366 (all European descent). This larger GWAS yields two additional loci harboring genome-wide significant variants (P = 4.7×10 at rs8018720 in SEC23A, and P = 1.9×10 at rs10745742 in AMDHD1). The overall estimate of heritability of 25-hydroxyvitamin D serum concentrations attributable to GWAS common SNPs is 7.5%, with statistically significant loci explaining 38% of this total. Further investigation identifies signal enrichment in immune and hematopoietic tissues, and clustering with autoimmune diseases in cell-type-specific analysis. Larger studies are required to identify additional common SNPs, and to explore the role of rare or structural variants and gene-gene interactions in the heritability of circulating 25-hydroxyvitamin D levels.

Genome-Wide Association Trans-Ethnic Meta-Analyses Identifies Novel Associations Regulating Coagulation Factor VIII and von Willebrand Factor Plasma Levels. - Sabater-Lleal, Maria; Huffman, Jennifer E; de Vries, Paul S; Marten, Jonathan; Mastrangelo, Michael A; Song, Ci; Pankratz, Nathan; Ward-Caviness, Cavin K; Yanek, Lisa R; Trompet, Stella; Delgado, Graciela E; Guo, Xiuqing; et al. (Circulation, 2018)
BACKGROUND: Factor VIII (FVIII) and its carrier protein von Willebrand factor (VWF) are associated with risk of arterial and venous thrombosis and with hemorrhagic disorders. We aimed to identify and functionally test novel genetic associations regulating plasma FVIII and VWF. METHODS: We meta-analyzed genome-wide association results from 46,354 individuals of European, African, East Asian, and Hispanic ancestry. All studies performed linear regression analysis using an additive genetic model and associated approximately 35 million imputed variants with natural-log transformed phenotype levels. In vitro gene silencing in cultured endothelial cells was performed for candidate genes to provide additional evidence on association and function. Two-sample Mendelian randomization (MR) analyses were applied to test the causal role of FVIII and VWF plasma levels on the risk of arterial and venous thrombotic events. RESULTS: We identified 13 novel genome-wide significant (p≤2.5x10) associations; 7 with FVIII levels ( FCHO2/TMEM171/TNPO1, HLA, SOX17/RP1, LINC00583/NFIB, RAB5C-KAT2A, RPL3/TAB1/SYNGR1, and ARSA) and 11 with VWF levels ( PDHB/PXK/KCTD6, SLC39A8, FCHO2/TMEM171/TNPO1, HLA, GIMAP7/GIMAP4, OR13C5/NIPSNAP, DAB2IP, C2CD4B, RAB5C-KAT2A, TAB1/SYNGR1, and ARSA), beyond 10 previously reported associations with these phenotypes. Functional validation provided further evidence of association for all loci on VWF except ARSA and DAB2IP. MR suggested causal effects of plasma FVIII activity levels on venous thrombosis and coronary artery disease risk and plasma VWF levels on ischemic stroke risk. CONCLUSIONS: The meta-analysis identified 13 novel genetic loci regulating FVIII and VWF plasma levels, 10 of which we validated functionally. We provide some evidence for a causal role of these proteins in thrombotic events.

Genome-wide meta-analysis of 158,000 individuals of European ancestry identifies three loci associated with chronic back pain. - Suri, Pradeep; Palmer, Melody R; Tsepilov, Yakov A; Freidin, Maxim B; Boer, Cindy G; Yau, Michelle S; Evans, Daniel S; Gelemanovic, Andrea; Bartz, Traci M; Nethander, Maria; Arbeeva, Liubov; Karssen, Lennart; et al. (PLoS Genet, 2018)
Back pain is the #1 cause of years lived with disability worldwide, yet surprisingly little is known regarding the biology underlying this symptom. We conducted a genome-wide association study (GWAS) meta-analysis of chronic back pain (CBP). Adults of European ancestry were included from 15 cohorts in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, and from the UK Biobank interim data release. CBP cases were defined as those reporting back pain present for ≥3-6 months; non-cases were included as comparisons ("controls"). Each cohort conducted genotyping using commercially available arrays followed by imputation. GWAS used logistic regression models with additive genetic effects, adjusting for age, sex, study-specific covariates, and population substructure. The threshold for genome-wide significance in the fixed-effect inverse-variance weighted meta-analysis was p<5×10-8. Suggestive (p<5×10-7) and genome-wide significant (p<5×10-8) variants were carried forward for replication or further investigation in the remaining UK Biobank participants not included in the discovery sample. The discovery sample comprised 158,025 individuals, including 29,531 CBP cases. A genome-wide significant association was found for the intronic variant rs12310519 in SOX5 (OR 1.08, p = 7.2×10-10). This was subsequently replicated in 283,752 UK Biobank participants not included in the discovery sample, including 50,915 cases (OR 1.06, p = 5.3×10-11), and exceeded genome-wide significance in joint meta-analysis (OR 1.07, p = 4.5×10-19). We found suggestive associations at three other loci in the discovery sample, two of which exceeded genome-wide significance in joint meta-analysis: an intergenic variant, rs7833174, located between CCDC26 and GSDMC (OR 1.05, p = 4.4×10-13), and an intronic variant, rs4384683, in DCC (OR 0.97, p = 2.4×10-10). In this first reported meta-analysis of GWAS for CBP, we identified and replicated a genetic locus associated with CBP (SOX5). We also identified 2 other loci that reached genome-wide significance in a 2-stage joint meta-analysis (CCDC26/GSDMC and DCC).

GWAS and colocalization analyses implicate carotid intima-media thickness and carotid plaque loci in cardiovascular outcomes. - Franceschini, Nora; Giambartolomei, Claudia; de Vries, Paul S; Finan, Chris; Bis, Joshua C; Huntley, Rachael P; Lovering, Ruth C; Tajuddin, Salman M; Winkler, Thomas W; Graff, Misa; Kavousi, Maryam; Dale, Caroline; et al. (Nat Commun, 2018)
Carotid artery intima media thickness (cIMT) and carotid plaque are measures of subclinical atherosclerosis associated with ischemic stroke and coronary heart disease (CHD). Here, we undertake meta-analyses of genome-wide association studies (GWAS) in 71,128 individuals for cIMT, and 48,434 individuals for carotid plaque traits. We identify eight novel susceptibility loci for cIMT, one independent association at the previously-identified PINX1 locus, and one novel locus for carotid plaque. Colocalization analysis with nearby vascular expression quantitative loci (cis-eQTLs) derived from arterial wall and metabolic tissues obtained from patients with CHD identifies candidate genes at two potentially additional loci, ADAMTS9 and LOXL4. LD score regression reveals significant genetic correlations between cIMT and plaque traits, and both cIMT and plaque with CHD, any stroke subtype and ischemic stroke. Our study provides insights into genes and tissue-specific regulatory mechanisms linking atherosclerosis both to its functional genomic origins and its clinical consequences in humans.
Keywords: ADAMTS9 Protein; Amino Acid Oxidoreductases; Carotid Intima-Media Thickness; Coronary Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lod Score; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

Harmonization of Respiratory Data From 9 US Population-Based Cohorts: The NHLBI Pooled Cohorts Study. - Oelsner, Elizabeth C; Balte, Pallavi P; Cassano, Patricia A; Couper, David; Enright, Paul L; Folsom, Aaron R; Hankinson, John; Jacobs, David R; Kalhan, Ravi; Kaplan, Robert; Kronmal, Richard; Lange, Leslie; et al. (Am J Epidemiol, 2018)
Chronic lower respiratory diseases (CLRDs) are the fourth leading cause of death in the United States. To support investigations into CLRD risk determinants and new approaches to primary prevention, we aimed to harmonize and pool respiratory data from US general population-based cohorts. Data were obtained from prospective cohorts that performed prebronchodilator spirometry and were harmonized following 2005 ATS/ERS standards. In cohorts conducting follow-up for noncardiovascular events, CLRD events were defined as hospitalizations/deaths adjudicated as CLRD-related or assigned relevant administrative codes. Coding and variable names were applied uniformly. The pooled sample included 65,251 adults in 9 cohorts followed-up for CLRD-related mortality over 653,380 person-years during 1983-2016. Average baseline age was 52 years; 56% were female; 49% were never-smokers; and racial/ethnic composition was 44% white, 22% black, 28% Hispanic/Latino, and 5% American Indian. Over 96% had complete data on smoking, clinical CLRD diagnoses, and dyspnea. After excluding invalid spirometry examinations (13%), there were 105,696 valid examinations (median, 2 per participant). Of 29,351 participants followed for CLRD hospitalizations, median follow-up was 14 years; only 5% were lost to follow-up at 10 years. The NHLBI Pooled Cohorts Study provides a harmonization standard applied to a large, US population-based sample that may be used to advance epidemiologic research on CLRD.

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).

Left atrial diameter and vascular brain injury on MRI: The Cardiovascular Health Study. - Yaghi, Shadi; Bartz, Traci M; Kronmal, Richard; Kamel, Hooman; Gottdiener, John; Longstreth, W T; Elkind, Mitchell S V (Neurology, 2018)
OBJECTIVE: To determine the association left atrial diameter (LAD) and vascular brain injury on brain MRI. METHODS: We analyzed data from the Cardiovascular Health Study (CHS), a prospective cohort of community-dwelling adults ≥65 years old. LAD was measured from 2-dimensional transthoracic echocardiograms. Among CHS participants who underwent brain MRI, we examined associations of LAD with brain infarcts and leukoaraiosis. Primary outcomes (number for analysis) were prevalent infarcts (2,327) and degree of leukoaraiosis on initial MRI (2,315). Secondary outcomes were prevalent nonlacunar infarcts (2,327), incident infarcts (939), incident nonlacunar infarcts (1,185), and degree of leukoaraiosis on follow-up MRI adjusted for initial MRI (1,158). Relative risk (RR) and linear regression models were adjusted for demographics, vascular risk factors, and potential confounders. RESULTS: Mean age of the 2,335 participants with initial brain MRI was 72.0 ± 4.8 years; 38.7% were men; and 29.0% participants had prevalent infarcts. In multivariable, fully adjusted models, LAD was associated with prevalent infarcts (RR 1.20, 95% confidence interval [CI] 1.08-1.34) and prevalent nonlacunar infarcts (RR 1.28, 95% CI 1.06-1.54) but not with leukoaraiosis (-0.08, 95% CI -0.17 to 0.07), incident infarcts (RR 1.00, 95% CI 0.78-1.29), nonlacunar infarcts (RR 0.98, 95% CI 0.67-1.42), or worsening leukoaraiosis (-0.04, 95% CI -0.10 to 0.02). CONCLUSION: LAD is independently associated with prevalent brain infarcts, particularly nonlacunar infarcts, but not leukoaraiosis. Larger studies are needed to determine associations with incident infarct risk and whether this risk in patients with left atrial enlargement can be reduced with anticoagulant agents.

{Life-Course Genome-wide Association Study Meta-analysis of Total Body BMD and Assessment of Age-Specific Effects - Medina-Gomez, C.; Kemp, J. P.; Trajanoska, K.; Luan, J.; Chesi, A.; Ahluwalia, T. S.; Mook-Kanamori, D. O.; Ham, A.; Hartwig, F. P.; Evans, D. S.; Joro, R.; Nedeljkovic, I.; et al. (Am J Hum Genet, 2018)
Bone mineral density (BMD) assessed by DXA is used to evaluate bone health. In children, total body (TB) measurements are commonly used; in older individuals, BMD at the lumbar spine (LS) and femoral neck (FN) is used to diagnose osteoporosis. To date, genetic variants in more than 60 loci have been identified as associated with BMD. To investigate the genetic determinants of TB-BMD variation along the life course and test for age-specific effects, we performed a meta-analysis of 30 genome-wide association studies (GWASs) of TB-BMD including 66,628 individuals overall and divided across five age strata, each spanning 15 years. We identified variants associated with TB-BMD at 80 loci, of which 36 have not been previously identified; overall, they explain approximately 10% of the TB-BMD variance when combining all age groups and influence the risk of fracture. Pathway and enrichment analysis of the association signals showed clustering within gene sets implicated in the regulation of cell growth and SMAD proteins, overexpressed in the musculoskeletal system, and enriched in enhancer and promoter regions. These findings reveal TB-BMD as a relevant trait for genetic studies of osteoporosis, enabling the identification of variants and pathways influencing different bone compartments. Only variants in ESR1 and close proximity to RANKL showed a clear effect dependency on age. This most likely indicates that the majority of genetic variants identified influence BMD early in life and that their effect can be captured throughout the life course.

Low thyroid function is not associated with an accelerated deterioration in renal function. - Meuwese, Christiaan L; van Diepen, Merel; Cappola, Anne R; Sarnak, Mark J; Shlipak, Michael G; Bauer, Douglas C; Fried, Linda P; Iacoviello, Massimo; Vaes, Bert; Degryse, Jean; Khaw, Kay-Tee; Luben, Robert N; et al. (Nephrol Dial Transplant, 2018)
Background: Chronic kidney disease (CKD) is frequently accompanied by thyroid hormone dysfunction. It is currently unclear whether these alterations are the cause or consequence of CKD. This study aimed at studying the effect of thyroid hormone alterations on renal function in cross-sectional and longitudinal analyses in individuals from all adult age groups. Methods: Individual participant data (IPD) from 16 independent cohorts having measured thyroid stimulating hormone, free thyroxine levels and creatinine levels were included. Thyroid hormone status was defined using clinical cut-off values. Estimated glomerular filtration rates (eGFR) were calculated by means of the four-variable Modification of Diet in Renal Disease (MDRD) formula. For this IPD meta-analysis, eGFR at baseline and eGFR change during follow-up were computed by fitting linear regression models and linear mixed models in each cohort separately. Effect estimates were pooled using random effects models. Results: A total of 72 856 individuals from 16 different cohorts were included. At baseline, individuals with overt hypothyroidism (n = 704) and subclinical hypothyroidism (n = 3356) had a average (95% confidence interval) -4.07 (-6.37 to -1.78) and -2.40 (-3.78 to -1.02) mL/min/1.73 m2 lower eGFR as compared with euthyroid subjects (n = 66 542). In (subclinical) hyperthyroid subjects (n = 2254), average eGFR was 3.01 (1.50-4.52) mL/min/1.73 m2 higher. During 329 713 patient years of follow-up, eGFR did not decline more rapidly in individuals with low thyroid function compared with individuals with normal thyroid function. Conclusions: Low thyroid function is not associated with a deterioration of renal function. The cross-sectional association may be explained by renal dysfunction causing thyroid hormone alterations.

Meta-analysis across Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium provides evidence for an association of serum vitamin D with pulmonary function. - Xu, Jiayi; Bartz, Traci M; Chittoor, Geetha; Eiriksdottir, Gudny; Manichaikul, Ani W; Sun, Fangui; Terzikhan, Natalie; Zhou, Xia; Booth, Sarah L; Brusselle, Guy G; de Boer, Ian H; Fornage, Myriam; et al. (Br J Nutr, 2018)
The role that vitamin D plays in pulmonary function remains uncertain. Epidemiological studies reported mixed findings for serum 25-hydroxyvitamin D (25(OH)D)-pulmonary function association. We conducted the largest cross-sectional meta-analysis of the 25(OH)D-pulmonary function association to date, based on nine European ancestry (EA) cohorts (n 22 838) and five African ancestry (AA) cohorts (n 4290) in the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. Data were analysed using linear models by cohort and ancestry. Effect modification by smoking status (current/former/never) was tested. Results were combined using fixed-effects meta-analysis. Mean serum 25(OH)D was 68 (sd 29) nmol/l for EA and 49 (sd 21) nmol/l for AA. For each 1 nmol/l higher 25(OH)D, forced expiratory volume in the 1st second (FEV1) was higher by 1·1 ml in EA (95 % CI 0·9, 1·3; P<0·0001) and 1·8 ml (95 % CI 1·1, 2·5; P<0·0001) in AA (P race difference=0·06), and forced vital capacity (FVC) was higher by 1·3 ml in EA (95 % CI 1·0, 1·6; P<0·0001) and 1·5 ml (95 % CI 0·8, 2·3; P=0·0001) in AA (P race difference=0·56). Among EA, the 25(OH)D-FVC association was stronger in smokers: per 1 nmol/l higher 25(OH)D, FVC was higher by 1·7 ml (95 % CI 1·1, 2·3) for current smokers and 1·7 ml (95 % CI 1·2, 2·1) for former smokers, compared with 0·8 ml (95 % CI 0·4, 1·2) for never smokers. In summary, the 25(OH)D associations with FEV1 and FVC were positive in both ancestries. In EA, a stronger association was observed for smokers compared with never smokers, which supports the importance of vitamin D in vulnerable populations.

Meta-analysis of exome array data identifies six novel genetic loci for lung function. - Jackson, Victoria E; Latourelle, Jeanne C; Wain, Louise V; Smith, Albert V; Grove, Megan L; Bartz, Traci M; Obeidat, Ma'en; Province, Michael A; Gao, Wei; Qaiser, Beenish; Porteous, David J; Cassano, Patricia A; et al. (Wellcome Open Res, 2018)
Over 90 regions of the genome have been associated with lung function to date, many of which have also been implicated in chronic obstructive pulmonary disease. We carried out meta-analyses of exome array data and three lung function measures: forced expiratory volume in one second (FEV ), forced vital capacity (FVC) and the ratio of FEV to FVC (FEV /FVC). These analyses by the SpiroMeta and CHARGE consortia included 60,749 individuals of European ancestry from 23 studies, and 7,721 individuals of African Ancestry from 5 studies in the discovery stage, with follow-up in up to 111,556 independent individuals. We identified significant (P<2·8x10 ) associations with six SNPs: a nonsynonymous variant in , which is predicted to be damaging, three intronic SNPs ( and ) and two intergenic SNPs near to and Expression quantitative trait loci analyses found evidence for regulation of gene expression at three signals and implicated several genes, including and . Further interrogation of these loci could provide greater understanding of the determinants of lung function and pulmonary disease.

Multiancestry association study identifies new asthma risk loci that colocalize with immune-cell enhancer marks. - Demenais, Florence; Margaritte-Jeannin, Patricia; Barnes, Kathleen C; Cookson, William O C; Altmüller, Janine; Ang, Wei; Barr, R Graham; Beaty, Terri H; Becker, Allan B; Beilby, John; Bisgaard, Hans; Bjornsdottir, Unnur Steina; et al. (Nat Genet, 2018)
We examined common variation in asthma risk by conducting a meta-analysis of worldwide asthma genome-wide association studies (23,948 asthma cases, 118,538 controls) of individuals from ethnically diverse populations. We identified five new asthma loci, found two new associations at two known asthma loci, established asthma associations at two loci previously implicated in the comorbidity of asthma plus hay fever, and confirmed nine known loci. Investigation of pleiotropy showed large overlaps in genetic variants with autoimmune and inflammatory diseases. The enrichment in enhancer marks at asthma risk loci, especially in immune cells, suggested a major role of these loci in the regulation of immunologically related mechanisms.

Multiancestry genome-wide association study of 520,000 subjects identifies 32 loci associated with stroke and stroke subtypes. - Malik, Rainer; Chauhan, Ganesh; Traylor, Matthew; Sargurupremraj, Muralidharan; Okada, Yukinori; Mishra, Aniket; Rutten-Jacobs, Loes; Giese, Anne-Katrin; van der Laan, Sander W; Gretarsdottir, Solveig; Anderson, Christopher D; Chong, Michael; et al. (Nat Genet, 2018)
Stroke has multiple etiologies, but the underlying genes and pathways are largely unknown. We conducted a multiancestry genome-wide-association meta-analysis in 521,612 individuals (67,162 cases and 454,450 controls) and discovered 22 new stroke risk loci, bringing the total to 32. We further found shared genetic variation with related vascular traits, including blood pressure, cardiac traits, and venous thromboembolism, at individual loci (n = 18), and using genetic risk scores and linkage-disequilibrium-score regression. Several loci exhibited distinct association and pleiotropy patterns for etiological stroke subtypes. Eleven new susceptibility loci indicate mechanisms not previously implicated in stroke pathophysiology, with prioritization of risk variants and genes accomplished through bioinformatics analyses using extensive functional datasets. Stroke risk loci were significantly enriched in drug targets for antithrombotic therapy.

Multi-ethnic genome-wide association study for atrial fibrillation. - Roselli, Carolina; Chaffin, Mark D; Weng, Lu-Chen; Aeschbacher, Stefanie; Ahlberg, Gustav; Albert, Christine M; Almgren, Peter; Alonso, Alvaro; Anderson, Christopher D; Aragam, Krishna G; Arking, Dan E; Barnard, John; et al. (Nat Genet, 2018)
Atrial fibrillation (AF) affects more than 33 million individuals worldwide and has a complex heritability. We conducted the largest meta-analysis of genome-wide association studies (GWAS) for AF to date, consisting of more than half a million individuals, including 65,446 with AF. In total, we identified 97 loci significantly associated with AF, including 67 that were novel in a combined-ancestry analysis, and 3 that were novel in a European-specific analysis. We sought to identify AF-associated genes at the GWAS loci by performing RNA-sequencing and expression quantitative trait locus analyses in 101 left atrial samples, the most relevant tissue for AF. We also performed transcriptome-wide analyses that identified 57 AF-associated genes, 42 of which overlap with GWAS loci. The identified loci implicate genes enriched within cardiac developmental, electrophysiological, contractile and structural pathways. These results extend our understanding of the biological pathways underlying AF and may facilitate the development of therapeutics for AF.

Multiethnic Meta-Analysis Identifies RAI1 as a Possible Obstructive Sleep Apnea-related Quantitative Trait Locus in Men. - Chen, Han; Cade, Brian E; Gleason, Kevin J; Bjonnes, Andrew C; Stilp, Adrienne M; Sofer, Tamar; Conomos, Matthew P; Ancoli-Israel, Sonia; Arens, Raanan; Azarbarzin, Ali; Bell, Graeme I; Below, Jennifer E; et al. (Am J Respir Cell Mol Biol, 2018)
Obstructive sleep apnea (OSA) is a common heritable disorder displaying marked sexual dimorphism in disease prevalence and progression. Previous genetic association studies have identified a few genetic loci associated with OSA and related quantitative traits, but they have only focused on single ethnic groups, and a large proportion of the heritability remains unexplained. The apnea-hypopnea index (AHI) is a commonly used quantitative measure characterizing OSA severity. Because OSA differs by sex, and the pathophysiology of obstructive events differ in rapid eye movement (REM) and non-REM (NREM) sleep, we hypothesized that additional genetic association signals would be identified by analyzing the NREM/REM-specific AHI and by conducting sex-specific analyses in multiethnic samples. We performed genome-wide association tests for up to 19,733 participants of African, Asian, European, and Hispanic/Latino American ancestry in 7 studies. We identified rs12936587 on chromosome 17 as a possible quantitative trait locus for NREM AHI in men (N = 6,737; P = 1.7 × 10) but not in women (P = 0.77). The association with NREM AHI was replicated in a physiological research study (N = 67; P = 0.047). This locus overlapping the RAI1 gene and encompassing genes PEMT1, SREBF1, and RASD1 was previously reported to be associated with coronary artery disease, lipid metabolism, and implicated in Potocki-Lupski syndrome and Smith-Magenis syndrome, which are characterized by abnormal sleep phenotypes. We also identified gene-by-sex interactions in suggestive association regions, suggesting that genetic variants for AHI appear to vary by sex, consistent with the clinical observations of strong sexual dimorphism.

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.

Omega-3 Fatty Acids and Genome-wide Interaction Analyses Reveal DPP10-Pulmonary Function Association. - Xu, Jiayi; Gaddis, Nathan C; Bartz, Traci M; Hou, Ruixue; Manichaikul, Ani W; Pankratz, Nathan; Smith, Albert V; Sun, Fangui; Terzikhan, Natalie; Markunas, Christina A; Patchen, Bonnie K; Schu, Matthew; et al. (Am J Respir Crit Care Med, 2018)
RATIONALE: Omega-3 poly-unsaturated fatty acids (n-3 PUFAs) have anti-inflammatory properties that could benefit adults with comprised pulmonary health. OBJECTIVE: To investigate n-3 PUFA associations with spirometric measures of pulmonary function tests (PFTs) and determine underlying genetic susceptibility. METHODS: Associations of n-3 PUFA biomarkers (alpha-linolenic acid, eicosapentaenoic acid, docosapentaenoic acid [DPA], and docosahexaenoic acid [DHA]) were evaluated with PFTs (forced expiratory volume in the first second [FEV], forced vital capacity [FVC], and [FEV/FVC]) in meta-analyses across seven cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium (N=16,134 of European or African ancestry). PFT-associated n-3 PUFAs were carried forward to genome-wide interaction analyses in the four largest cohorts (N=11,962) and replicated in one cohort (N=1,687). Cohort-specific results were combined using joint 2 degree-of-freedom (2df) meta-analyses of single nucleotide polymorphism (SNP) associations and their interactions with n-3 PUFAs. RESULTS: DPA and DHA were positively associated with FEV1 and FVC (P<0.025), with evidence for effect modification by smoking and by sex. Genome-wide analyses identified a novel association of rs11693320-an intronic DPP10 SNP-with FVC when incorporating an interaction with DHA, and the finding was replicated (P=9.4×10 across discovery and replication cohorts). The rs11693320-A allele (frequency~80%) was associated with lower FVC (P=2.1×10; β= -161.0mL), and the association was attenuated by higher DHA levels (P=2.1×10; β=36.2mL). CONCLUSIONS: We corroborated beneficial effects of n-3 PUFAs on pulmonary function. By modeling genome-wide n-3 PUFA interactions, we identified a novel DPP10 SNP association with FVC that was not detectable in much larger studies ignoring this interaction.

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.

Predictive value for cardiovascular events of common carotid intima media thickness and its rate of change in individuals at high cardiovascular risk - Results from the PROG-IMT collaboration. - Lorenz, Matthias W; Gao, Lu; Ziegelbauer, Kathrin; Norata, Giuseppe Danilo; Empana, Jean Philippe; Schmidtmann, Irene; Lin, Hung-Ju; McLachlan, Stela; Bokemark, Lena; Ronkainen, Kimmo; Amato, Mauro; Schminke, Ulf; et al. (PLoS One, 2018)
AIMS: Carotid intima media thickness (CIMT) predicts cardiovascular (CVD) events, but the predictive value of CIMT change is debated. We assessed the relation between CIMT change and events in individuals at high cardiovascular risk. METHODS AND RESULTS: From 31 cohorts with two CIMT scans (total n = 89070) on average 3.6 years apart and clinical follow-up, subcohorts were drawn: (A) individuals with at least 3 cardiovascular risk factors without previous CVD events, (B) individuals with carotid plaques without previous CVD events, and (C) individuals with previous CVD events. Cox regression models were fit to estimate the hazard ratio (HR) of the combined endpoint (myocardial infarction, stroke or vascular death) per standard deviation (SD) of CIMT change, adjusted for CVD risk factors. These HRs were pooled across studies. In groups A, B and C we observed 3483, 2845 and 1165 endpoint events, respectively. Average common CIMT was 0.79mm (SD 0.16mm), and annual common CIMT change was 0.01mm (SD 0.07mm), both in group A. The pooled HR per SD of annual common CIMT change (0.02 to 0.43mm) was 0.99 (95% confidence interval: 0.95-1.02) in group A, 0.98 (0.93-1.04) in group B, and 0.95 (0.89-1.04) in group C. The HR per SD of common CIMT (average of the first and the second CIMT scan, 0.09 to 0.75mm) was 1.15 (1.07-1.23) in group A, 1.13 (1.05-1.22) in group B, and 1.12 (1.05-1.20) in group C. CONCLUSIONS: We confirm that common CIMT is associated with future CVD events in individuals at high risk. CIMT change does not relate to future event risk in high-risk individuals.
Keywords: Aged; Cardiovascular Diseases; Carotid Intima-Media Thickness; Female; Humans; Intersectoral Collaboration; Male; Middle Aged; Prognosis; Risk Factors

Refining the accuracy of validated target identification through coding variant fine-mapping in type 2 diabetes. - Mahajan, Anubha; Wessel, Jennifer; Willems, Sara M; Zhao, Wei; Robertson, Neil R; Chu, Audrey Y; Gan, Wei; Kitajima, Hidetoshi; Taliun, Daniel; Rayner, N William; Guo, Xiuqing; Lu, Yingchang; et al. (Nat Genet, 2018)
We aggregated coding variant data for 81,412 type 2 diabetes cases and 370,832 controls of diverse ancestry, identifying 40 coding variant association signals (P < 2.2 × 10); of these, 16 map outside known risk-associated loci. We make two important observations. First, only five of these signals are driven by low-frequency variants: even for these, effect sizes are modest (odds ratio ≤1.29). Second, when we used large-scale genome-wide association data to fine-map the associated variants in their regional context, accounting for the global enrichment of complex trait associations in coding sequence, compelling evidence for coding variant causality was obtained for only 16 signals. At 13 others, the associated coding variants clearly represent 'false leads' with potential to generate erroneous mechanistic inference. Coding variant associations offer a direct route to biological insight for complex diseases and identification of validated therapeutic targets; however, appropriate mechanistic inference requires careful specification of their causal contribution to disease predisposition.

The relation between thyroid function and anemia: a pooled analysis of individual participant data. - Wopereis, Daisy M; Du Puy, Robert S; van Heemst, Diana; Walsh, John P; Bremner, Alexandra; Bakker, Stephan J L; Bauer, Douglas C; Cappola, Anne R; Ceresini, Graziano; Degryse, Jean; Dullaart, Robin P F; Feller, Martin; et al. (J Clin Endocrinol Metab, 2018)
Context: Anemia and thyroid dysfunction often co-occur and both increase with age. Human data on the relationship between thyroid disease and anemia are scarce. Objective: To investigate the cross-sectional and longitudinal associations between clinical thyroid status and anemia. Design: Individual participant data meta-analysis. Setting: Sixteen cohorts participating in the Thyroid Studies Collaboration (n=42 162). Main outcome measures: Primary outcome measure was anemia (hemoglobin <130 g/L in men and <120 g/L in women). Results: Cross-sectionally, participants with abnormal thyroid status had an increased risk of having anemia compared with euthyroid participants (overt hypothyroidism, pooled odds ratio 1.84 [95% CI: 1.35-2.50], subclinical hypothyroidism 1.21 [1.02-1.43], subclinical hyperthyroidism 1.27 [1.03-1.57], overt hyperthyroidism 1.69 [1.00-2.87]). Hemoglobin levels were lower in all groups compared to participants with euthyroidism. In the longitudinal analyses (n=25,466 from 14 cohorts), the pooled hazard ratio for the risk of development of anemia was 1.38 [95% CI: 0.86-2.20] for overt hypothyroidism, 1.18 [1.00-1.38] for subclinical hypothyroidism, 1.15 [0.94-1.42] for subclinical hyperthyroidism and 1.47 [0.91-2.38] for overt hyperthyroidism. Sensitivity analyses excluding thyroid medication or high levels of C-reactive protein yielded similar results. No differences in mean annual change in hemoglobin levels were observed between the thyroid hormone status groups. Conclusion: Higher odds of having anemia were observed in both participants with hypothyroid function and hyperthyroid function. In addition, reduced thyroid function at baseline showed a trend of increased risk of developing anemia during follow-up. It remains to be assessed in a randomized controlled trial whether treatment is effective in reducing anemia.

Risk thresholds for alcohol consumption: combined analysis of individual-participant data for 599 912 current drinkers in 83 prospective studies. - Wood, Angela M; Kaptoge, Stephen; Butterworth, Adam S; Willeit, Peter; Warnakula, Samantha; Bolton, Thomas; Paige, Ellie; Paul, Dirk S; Sweeting, Michael; Burgess, Stephen; Bell, Steven; Astle, William; et al. (Lancet, 2018)
BACKGROUND: Low-risk limits recommended for alcohol consumption vary substantially across different national guidelines. To define thresholds associated with lowest risk for all-cause mortality and cardiovascular disease, we studied individual-participant data from 599 912 current drinkers without previous cardiovascular disease. METHODS: We did a combined analysis of individual-participant data from three large-scale data sources in 19 high-income countries (the Emerging Risk Factors Collaboration, EPIC-CVD, and the UK Biobank). We characterised dose-response associations and calculated hazard ratios (HRs) per 100 g per week of alcohol (12·5 units per week) across 83 prospective studies, adjusting at least for study or centre, age, sex, smoking, and diabetes. To be eligible for the analysis, participants had to have information recorded about their alcohol consumption amount and status (ie, non-drinker vs current drinker), plus age, sex, history of diabetes and smoking status, at least 1 year of follow-up after baseline, and no baseline history of cardiovascular disease. The main analyses focused on current drinkers, whose baseline alcohol consumption was categorised into eight predefined groups according to the amount in grams consumed per week. We assessed alcohol consumption in relation to all-cause mortality, total cardiovascular disease, and several cardiovascular disease subtypes. We corrected HRs for estimated long-term variability in alcohol consumption using 152 640 serial alcohol assessments obtained some years apart (median interval 5·6 years [5th-95th percentile 1·04-13·5]) from 71 011 participants from 37 studies. FINDINGS: In the 599 912 current drinkers included in the analysis, we recorded 40 310 deaths and 39 018 incident cardiovascular disease events during 5·4 million person-years of follow-up. For all-cause mortality, we recorded a positive and curvilinear association with the level of alcohol consumption, with the minimum mortality risk around or below 100 g per week. Alcohol consumption was roughly linearly associated with a higher risk of stroke (HR per 100 g per week higher consumption 1·14, 95% CI, 1·10-1·17), coronary disease excluding myocardial infarction (1·06, 1·00-1·11), heart failure (1·09, 1·03-1·15), fatal hypertensive disease (1·24, 1·15-1·33); and fatal aortic aneurysm (1·15, 1·03-1·28). By contrast, increased alcohol consumption was log-linearly associated with a lower risk of myocardial infarction (HR 0·94, 0·91-0·97). In comparison to those who reported drinking >0-≤100 g per week, those who reported drinking >100-≤200 g per week, >200-≤350 g per week, or >350 g per week had lower life expectancy at age 40 years of approximately 6 months, 1-2 years, or 4-5 years, respectively. INTERPRETATION: In current drinkers of alcohol in high-income countries, the threshold for lowest risk of all-cause mortality was about 100 g/week. For cardiovascular disease subtypes other than myocardial infarction, there were no clear risk thresholds below which lower alcohol consumption stopped being associated with lower disease risk. These data support limits for alcohol consumption that are lower than those recommended in most current guidelines. FUNDING: UK Medical Research Council, British Heart Foundation, National Institute for Health Research, European Union Framework 7, and European Research Council.

Sex and Race Differences in Lifetime Risk of Heart Failure With Preserved Ejection Fraction and Heart Failure With Reduced Ejection Fraction. - Pandey, Ambarish; Omar, Wally; Ayers, Colby; LaMonte, Michael; Klein, Liviu; Allen, Norrina B; Kuller, Lewis H; Greenland, Philip; Eaton, Charles B; Gottdiener, John S; Lloyd-Jones, Donald M; Berry, Jarett D (Circulation, 2018)
BACKGROUND: Lifetime risk of heart failure has been estimated to range from 20% to 46% in diverse sex and race groups. However, lifetime risk estimates for the 2 HF phenotypes, HF with preserved ejection fraction (HFpEF) and HF with reduced ejection fraction (HFrEF), are not known. METHODS: Participant-level data from 2 large prospective cohort studies, the CHS (Cardiovascular Health Study) and MESA (Multiethnic Study of Atherosclerosis), were pooled, excluding individuals with prevalent HF at baseline. Remaining lifetime risk estimates for HFpEF (EF ≥45%) and HFrEF (EF <45%) were determined at different index ages with the use of a modified Kaplan-Meier method with mortality and the other HF subtype as competing risks. RESULTS: We included 12 417 participants >45 years of age (22.2% blacks, 44.8% men) who were followed up for median duration of 11.6 years with 2178 overall incident HF events with 561 HFrEF events and 726 HFpEF events. At the index age of 45 years, the lifetime risk for any HF through 90 years of age was higher in men than women (27.4% versus 23.8%). Among HF subtypes, the lifetime risk for HFrEF was higher in men than women (10.6% versus 5.8%). In contrast, the lifetime risk for HFpEF was similar in men and women. In race-stratified analyses, lifetime risk for overall HF was higher in nonblacks than blacks (25.9% versus 22.4%). Among HF subtypes, the lifetime risk for HFpEF was higher in nonblacks than blacks (11.2% versus 7.7%), whereas that for HFrEF was similar across the 2 groups. Among participants with antecedent myocardial infarction before HF diagnosis, the remaining lifetime risks for HFpEF and HFrEF were up to 2.5-fold and 4-fold higher, respectively, compared with those without antecedent myocardial infarction. CONCLUSIONS: Lifetime risks for HFpEF and HFrEF vary by sex, race, and history of antecedent myocardial infarction. These insights into the distribution of HF risk and its subtypes could inform the development of targeted strategies to improve population-level HF prevention and control.

Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Davies, Gail; Lam, Max; Harris, Sarah E; Trampush, Joey W; Luciano, Michelle; Hill, W David; Hagenaars, Saskia P; Ritchie, Stuart J; Marioni, Riccardo E; Fawns-Ritchie, Chloe; Liewald, David C M; Okely, Judith A; et al. (Nat Commun, 2018)
General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16-102) and find 148 genome-wide significant independent loci (P < 5 × 10) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, and brain structure. Gene-based analyses find 709 genes associated with general cognitive function. Expression levels across the cortex are associated with general cognitive function. Using polygenic scores, up to 4.3% of variance in general cognitive function is predicted in independent samples. We detect significant genetic overlap between general cognitive function, reaction time, and many health variables including eyesight, hypertension, and longevity. In conclusion we identify novel genetic loci and pathways contributing to the heritability of general cognitive function.

Sugar-sweetened beverage intake associations with fasting glucose and insulin concentrations are not modified by selected genetic variants in a ChREBP-FGF21 pathway: a meta-analysis. - McKeown, Nicola M; Dashti, Hassan S; Ma, Jiantao; Haslam, Danielle E; Kiefte-de Jong, Jessica C; Smith, Caren E; Tanaka, Toshiko; Graff, Mariaelisa; Lemaitre, Rozenn N; Rybin, Denis; Sonestedt, Emily; Frazier-Wood, Alexis C; et al. (Diabetologia, 2018)
AIMS/HYPOTHESIS: Sugar-sweetened beverages (SSBs) are a major dietary contributor to fructose intake. A molecular pathway involving the carbohydrate responsive element-binding protein (ChREBP) and the metabolic hormone fibroblast growth factor 21 (FGF21) may influence sugar metabolism and, thereby, contribute to fructose-induced metabolic disease. We hypothesise that common variants in 11 genes involved in fructose metabolism and the ChREBP-FGF21 pathway may interact with SSB intake to exacerbate positive associations between higher SSB intake and glycaemic traits. METHODS: Data from 11 cohorts (six discovery and five replication) in the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium provided association and interaction results from 34,748 adults of European descent. SSB intake (soft drinks, fruit punches, lemonades or other fruit drinks) was derived from food-frequency questionnaires and food diaries. In fixed-effects meta-analyses, we quantified: (1) the associations between SSBs and glycaemic traits (fasting glucose and fasting insulin); and (2) the interactions between SSBs and 18 independent SNPs related to the ChREBP-FGF21 pathway. RESULTS: In our combined meta-analyses of discovery and replication cohorts, after adjustment for age, sex, energy intake, BMI and other dietary covariates, each additional serving of SSB intake was associated with higher fasting glucose (β ± SE 0.014 ± 0.004 [mmol/l], p = 1.5 × 10-3) and higher fasting insulin (0.030 ± 0.005 [log e pmol/l], p = 2.0 × 10-10). No significant interactions on glycaemic traits were observed between SSB intake and selected SNPs. While a suggestive interaction was observed in the discovery cohorts with a SNP (rs1542423) in the β-Klotho (KLB) locus on fasting insulin (0.030 ± 0.011 log e pmol/l, uncorrected p = 0.006), results in the replication cohorts and combined meta-analyses were non-significant. CONCLUSIONS/INTERPRETATION: In this large meta-analysis, we observed that SSB intake was associated with higher fasting glucose and insulin. Although a suggestive interaction with a genetic variant in the ChREBP-FGF21 pathway was observed in the discovery cohorts, this observation was not confirmed in the replication analysis. TRIAL REGISTRATION: Trials related to this study were registered at clinicaltrials.gov as NCT00005131 (Atherosclerosis Risk in Communities), NCT00005133 (Cardiovascular Health Study), NCT00005121 (Framingham Offspring Study), NCT00005487 (Multi-Ethnic Study of Atherosclerosis) and NCT00005152 (Nurses' Health Study).

Temporal Trends in the Incidence of and Mortality Associated With Heart Failure With Preserved and Reduced Ejection Fraction. - Tsao, Connie W; Lyass, Asya; Enserro, Danielle; Larson, Martin G; Ho, Jennifer E; Kizer, Jorge R; Gottdiener, John S; Psaty, Bruce M; Vasan, Ramachandran S (JACC Heart Fail, 2018)
OBJECTIVES: This study aimed to determine temporal trends in the incidence of and mortality associated with heart failure (HF) and its subtypes (heart failure with reduced ejection fraction [HFrEF] and heart rate with preserved ejection fraction [HFpEF]) in the community. BACKGROUND: Major shifts in cardiovascular disease risk factor prevalence and advances in therapies may have influenced HF incidence and mortality. METHODS: In the FHS (Framingham Heart Study) and CHS (Cardiovascular Health Study), for participants who were ≥60 years of age and free of HF (n = 15,217; 60% women; 2,524 incident HF cases; 115,703 person-years of follow-up), we estimated adjusted incidence rate ratios of HF, HFrEF, and HFpEF from 1990 to 1999 and 2000 to 2009. We compared the cumulative incidence of and mortality associated with HFrEF versus HFpEF within and between decades. RESULTS: Across the 2 decades, HF incidence rate ratio was similar (p = 0.13). The incidence rate ratio of HFrEF declined (p = 0.0029), whereas HFpEF increased (p < 0.001). Although HFrEF incidence declined more in men than in women, men had a higher incidence of HFrEF than women in each decade (p < 0.001). The incidence of HFpEF significantly increased over time in both men and women (p < 0.001 and p = 0.02, respectively). During follow-up after HF, 1,701 individuals died (67.4%; HFrEF, n = 557 [33%]; HFpEF, n = 474 [29%]). There were no significant differences in mortality rates (overall, cardiovascular disease, and noncardiovascular disease) across decades within HF subtypes or between HFrEF and HFpEF within decade. CONCLUSIONS: In several U.S. community-based samples from 1990 to 2009, we observed divergent trends of decreasing HFrEF and increasing HFpEF incidence, with stable overall HF incidence and high risk for mortality. Our findings highlight the need to elucidate factors contributing to these observations.

Trans-ethnic analysis of metabochip data identifies two new loci associated with BMI. - Gong, J; Nishimura, K K; Fernandez-Rhodes, L; Haessler, J; Bien, S; Graff, M; Lim, U; Lu, Y; Gross, M; Fornage, M; Yoneyama, S; Isasi, C R; et al. (Int J Obes (Lond), 2018)
OBJECTIVE: Body mass index (BMI) is commonly used to assess obesity, which is associated with numerous diseases and negative health outcomes. BMI has been shown to be a heritable, polygenic trait, with close to 100 loci previously identified and replicated in multiple populations. We aim to replicate known BMI loci and identify novel associations in a trans-ethnic study population. SUBJECTS: Using eligible participants from the Population Architecture using Genomics and Epidemiology consortium, we conducted a trans-ethnic meta-analysis of 102 514 African Americans, Hispanics, Asian/Native Hawaiian, Native Americans and European Americans. Participants were genotyped on over 200 000 SNPs on the Illumina Metabochip custom array, or imputed into the 1000 Genomes Project (Phase I). Linear regression of the natural log of BMI, adjusting for age, sex, study site (if applicable), and ancestry principal components, was conducted for each race/ethnicity within each study cohort. Race/ethnicity-specific, and combined meta-analyses used fixed-effects models. RESULTS: We replicated 15 of 21 BMI loci included on the Metabochip, and identified two novel BMI loci at 1q41 (rs2820436) and 2q31.1 (rs10930502) at the Metabochip-wide significance threshold (P<2.5 × 10). Bioinformatic functional investigation of SNPs at these loci suggests a possible impact on pathways that regulate metabolism and adipose tissue. CONCLUSION: Conducting studies in genetically diverse populations continues to be a valuable strategy for replicating known loci and uncovering novel BMI associations.

Trans-ethnic Evaluation Identifies Novel Low Frequency Loci Associated with 25-Hydroxyvitamin D Concentrations. - Hong, Jaeyoung; Hatchell, Kathryn E; Bradfield, Jonathan P; Andrew, Bjonnes; Alessandra, Chesi; Chao-Qiang, Lai; Langefeld, Carl D; Lu, Lingyi; Lu, Yingchang; Lutsey, Pamela L; Musani, Solomon K; Nalls, Mike A; et al. (J Clin Endocrinol Metab, 2018)
Context: Vitamin D inadequacy is common in the adult population of the United States. While the genetic determinants underlying vitamin D inadequacy have been studied in people of European ancestry, less is known in Hispanic or African ancestry populations. Objective: The TRANSCEN-D (TRANS-ethniC Evaluation of vitamiN D GWAS) consortium was assembled to replicate genetic associations with 25-hydroxyvitamin D (25(OH)D) concentrations from the meta-analyses of European ancestry (SUNLIGHT) and to identify novel genetic variants related to vitamin D concentrations in African and Hispanic ancestries. Design: Ancestry-specific (Hispanic and African) and trans-ethnic (Hispanic, African and European) meta-analyses were performed using the METAL software. Patients or Other Participants: In total, 8,541 African-American and 3,485 Hispanic-American (from North America) participants from twelve cohorts, and 16,124 European participants from SUNLIGHT were included in the study. Main Outcome Measure(s): Blood concentrations of 25(OH)D were measured for all participants. Results: Ancestry-specific analyses in African and Hispanic Americans replicated SNPs in GC (2 and 4 SNPs, respectively). A potentially novel SNP (rs79666294) near the KIF4B gene was identified in the African-American cohort. Trans-ethnic evaluation replicated GC and DHCR7 region SNPs. Additionally, the trans-ethnic analyses revealed novel SNPs rs719700 and rs1410656 near the ANO6/ARID2 and HTR2A genes, respectively. Conclusions: Ancestry-specific and trans-ethnic GWAS of 25(OH)D confirmed findings in GC and DHCR7 for African and Hispanic American samples and revealed novel findings near KIF4B, ANO6/ARID2, and HTR2A. The biological mechanisms that link these regions with 25(OH)D metabolism require further investigation.

Admixture mapping identifies novel loci for obstructive sleep apnea in Hispanic/Latino Americans. - Wang, Heming; Cade, Brian E; Sofer, Tamar; Sands, Scott A; Chen, Han; Browning, Sharon R; Stilp, Adrienne M; Louie, Tin L; Thornton, Timothy A; Johnson, W Craig; Below, Jennifer E; Conomos, Matthew P; et al. (Hum Mol Genet, 2019)
Obstructive sleep apnea (OSA) is a common disorder associated with increased risk of cardiovascular disease and mortality. Its prevalence and severity vary across ancestral background. Although OSA traits are heritable, few genetic associations have been identified. To identify genetic regions associated with OSA and improve statistical power, we applied admixture mapping on three primary OSA traits [the apnea hypopnea index (AHI), overnight average oxyhemoglobin saturation (SaO2) and percentage time SaO2 < 90%] and a secondary trait (respiratory event duration) in a Hispanic/Latino American population study of 11 575 individuals with significant variation in ancestral background. Linear mixed models were performed using previously inferred African, European and Amerindian local genetic ancestry markers. Global African ancestry was associated with a lower AHI, higher SaO2 and shorter event duration. Admixture mapping analysis of the primary OSA traits identified local African ancestry at the chromosomal region 2q37 as genome-wide significantly associated with AHI (P < 5.7 × 10-5), and European and Amerindian ancestries at 18q21 suggestively associated with both AHI and percentage time SaO2 < 90% (P < 10-3). Follow-up joint ancestry-SNP association analyses identified novel variants in ferrochelatase (FECH), significantly associated with AHI and percentage time SaO2 < 90% after adjusting for multiple tests (P < 8 × 10-6). These signals contributed to the admixture mapping associations and were replicated in independent cohorts. In this first admixture mapping study of OSA, novel associations with variants in the iron/heme metabolism pathway suggest a role for iron in influencing respiratory traits underlying OSA.

{Alzheimer's disease progression and risk factors: A standardized comparison between six large data sets - Evans, S.; McRae-McKee, K.; Hadjichrysanthou, C.; Wong, M. M.; Ames, D.; Lopez, O.; de Wolf, F.; Anderson, R. M. (Alzheimers Dement (N Y), 2019)
There exist a large number of cohort studies that have been used to identify genetic and biological risk factors for developing Alzheimer's disease (AD). However, there is a disagreement between studies as to how strongly these risk factors affect the rate of progression through diagnostic groups toward AD. We have calculated the probability of transitioning through diagnostic groups in six studies and considered how uncertainty around the strength of the effect of these risk factors affects estimates of the distribution of individuals in each diagnostic group in an AD clinical trial simulator. In this work, we identify the optimal choice of widely collected variables for comparing data sets and calculating probabilities of progression toward AD. We use the estimated transition probabilities to inform stochastic simulations of AD progression that are based on a Markov model and compare predicted incidence rates to those in a community-based study, the Cardiovascular Health Study.

Assessment of the Relationship Between Genetic Determinants of Thyroid Function and Atrial Fibrillation: A Mendelian Randomization Study. - Ellervik, Christina; Roselli, Carolina; Christophersen, Ingrid E; Alonso, Alvaro; Pietzner, Maik; Sitlani, Collen M; Trompet, Stella; Arking, Dan E; Geelhoed, Bastiaan; Guo, Xiuqing; Kleber, Marcus E; Lin, Henry J; et al. (JAMA Cardiol, 2019)
Importance: Increased free thyroxine (FT4) and decreased thyrotropin are associated with increased risk of atrial fibrillation (AF) in observational studies, but direct involvement is unclear. Objective: To evaluate the potential direct involvement of thyroid traits on AF. Design, Setting, and Participants: Study-level mendelian randomization (MR) included 11 studies, and summary-level MR included 55 114 AF cases and 482 295 referents, all of European ancestry. Exposures: Genomewide significant variants were used as instruments for standardized FT4 and thyrotropin levels within the reference range, standardized triiodothyronine (FT3):FT4 ratio, hypothyroidism, standardized thyroid peroxidase antibody levels, and hyperthyroidism. Mendelian randomization used genetic risk scores in study-level analysis or individual single-nucleotide polymorphisms in 2-sample MR for the summary-level data. Main Outcomes and Measures: Prevalent and incident AF. Results: The study-level analysis included 7679 individuals with AF and 49 233 referents (mean age [standard error], 62 [3] years; 15 859 men [29.7%]). In study-level random-effects meta-analysis, the pooled hazard ratio of FT4 levels (nanograms per deciliter) for incident AF was 1.55 (95% CI, 1.09-2.20; P = .02; I2 = 76%) and the pooled odds ratio (OR) for prevalent AF was 2.80 (95% CI, 1.41-5.54; P = .003; I2 = 64%) in multivariable-adjusted analyses. The FT4 genetic risk score was associated with an increase in FT4 by 0.082 SD (standard error, 0.007; P < .001) but not with incident AF (risk ratio, 0.84; 95% CI, 0.62-1.14; P = .27) or prevalent AF (OR, 1.32; 95% CI, 0.64-2.73; P = .46). Similarly, in summary-level inverse-variance weighted random-effects MR, gene-based FT4 within the reference range was not associated with AF (OR, 1.01; 95% CI, 0.89-1.14; P = .88). However, gene-based increased FT3:FT4 ratio, increased thyrotropin within the reference range, and hypothyroidism were associated with AF with inverse-variance weighted random-effects OR of 1.33 (95% CI, 1.08-1.63; P = .006), 0.88 (95% CI, 0.84-0.92; P < .001), and 0.94 (95% CI, 0.90-0.99; P = .009), respectively, and robust to tests of horizontal pleiotropy. However, the subset of hypothyroidism single-nucleotide polymorphisms involved in autoimmunity and thyroid peroxidase antibodies levels were not associated with AF. Gene-based hyperthyroidism was associated with AF with MR-Egger OR of 1.31 (95% CI, 1.05-1.63; P = .02) with evidence of horizontal pleiotropy (P = .045). Conclusions and Relevance: Genetically increased FT3:FT4 ratio and hyperthyroidism, but not FT4 within the reference range, were associated with increased AF, and increased thyrotropin within the reference range and hypothyroidism were associated with decreased AF, supporting a pathway involving the pituitary-thyroid-cardiac axis.

Associations of autozygosity with a broad range of human phenotypes. - Clark, David W; Okada, Yukinori; Moore, Kristjan H S; Mason, Dan; Pirastu, Nicola; Gandin, Ilaria; Mattsson, Hannele; Barnes, Catriona L K; Lin, Kuang; Zhao, Jing Hua; Deelen, Patrick; Rohde, Rebecca; et al. (Nat Commun, 2019)
In many species, the offspring of related parents suffer reduced reproductive success, a phenomenon known as inbreeding depression. In humans, the importance of this effect has remained unclear, partly because reproduction between close relatives is both rare and frequently associated with confounding social factors. Here, using genomic inbreeding coefficients (F) for >1.4 million individuals, we show that F is significantly associated (p < 0.0005) with apparently deleterious changes in 32 out of 100 traits analysed. These changes are associated with runs of homozygosity (ROH), but not with common variant homozygosity, suggesting that genetic variants associated with inbreeding depression are predominantly rare. The effect on fertility is striking: F equivalent to the offspring of first cousins is associated with a 55% decrease [95% CI 44-66%] in the odds of having children. Finally, the effects of F are confirmed within full-sibling pairs, where the variation in F is independent of all environmental confounding.

Associations of variants In the hexokinase 1 and interleukin 18 receptor regions with oxyhemoglobin saturation during sleep. - Cade, Brian E; Chen, Han; Stilp, Adrienne M; Louie, Tin; Ancoli-Israel, Sonia; Arens, Raanan; Barfield, Richard; Below, Jennifer E; Cai, Jianwen; Conomos, Matthew P; Evans, Daniel S; Frazier-Wood, Alexis C; et al. (PLoS Genet, 2019)
Sleep disordered breathing (SDB)-related overnight hypoxemia is associated with cardiometabolic disease and other comorbidities. Understanding the genetic bases for variations in nocturnal hypoxemia may help understand mechanisms influencing oxygenation and SDB-related mortality. We conducted genome-wide association tests across 10 cohorts and 4 populations to identify genetic variants associated with three correlated measures of overnight oxyhemoglobin saturation: average and minimum oxyhemoglobin saturation during sleep and the percent of sleep with oxyhemoglobin saturation under 90%. The discovery sample consisted of 8,326 individuals. Variants with p < 1 × 10(-6) were analyzed in a replication group of 14,410 individuals. We identified 3 significantly associated regions, including 2 regions in multi-ethnic analyses (2q12, 10q22). SNPs in the 2q12 region associated with minimum SpO2 (rs78136548 p = 2.70 × 10(-10)). SNPs at 10q22 were associated with all three traits including average SpO2 (rs72805692 p = 4.58 × 10(-8)). SNPs in both regions were associated in over 20,000 individuals and are supported by prior associations or functional evidence. Four additional significant regions were detected in secondary sex-stratified and combined discovery and replication analyses, including a region overlapping Reelin, a known marker of respiratory complex neurons.These are the first genome-wide significant findings reported for oxyhemoglobin saturation during sleep, a phenotype of high clinical interest. Our replicated associations with HK1 and IL18R1 suggest that variants in inflammatory pathways, such as the biologically-plausible NLRP3 inflammasome, may contribute to nocturnal hypoxemia.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cell Adhesion Molecules, Neuronal; Computational Biology; Extracellular Matrix Proteins; Female; Gene Regulatory Networks; Genetic Variation; Genome-Wide Association Study; Hexokinase; Humans; Hypoxia; Interleukin-18 Receptor alpha Subunit; Male; Middle Aged; Nerve Tissue Proteins; NLR Family, Pyrin Domain-Containing 3 Protein; Oxygen; Oxyhemoglobins; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Serine Endopeptidases; Sleep; Sleep Apnea Syndromes; Young Adult

Biomarkers of Dietary Omega-6 Fatty Acids and Incident Cardiovascular Disease and Mortality. - Marklund, Matti; Wu, Jason H Y; Imamura, Fumiaki; Del Gobbo, Liana C; Fretts, Amanda; de Goede, Janette; Shi, Peilin; Tintle, Nathan; Wennberg, Maria; Aslibekyan, Stella; Chen, Tzu-An; de Oliveira Otto, Marcia C; et al. (Circulation, 2019)
BACKGROUND: Global dietary recommendations for and cardiovascular effects of linoleic acid, the major dietary omega-6 fatty acid, and its major metabolite, arachidonic acid, remain controversial. To address this uncertainty and inform international recommendations, we evaluated how in vivo circulating and tissue levels of linoleic acid (LA) and arachidonic acid (AA) relate to incident cardiovascular disease (CVD) across multiple international studies. METHODS: We performed harmonized, de novo, individual-level analyses in a global consortium of 30 prospective observational studies from 13 countries. Multivariable-adjusted associations of circulating and adipose tissue LA and AA biomarkers with incident total CVD and subtypes (coronary heart disease, ischemic stroke, cardiovascular mortality) were investigated according to a prespecified analytic plan. Levels of LA and AA, measured as the percentage of total fatty acids, were evaluated linearly according to their interquintile range (ie, the range between the midpoint of the first and fifth quintiles), and categorically by quintiles. Study-specific results were pooled using inverse-variance-weighted meta-analysis. Heterogeneity was explored by age, sex, race, diabetes mellitus, statin use, aspirin use, omega-3 levels, and fatty acid desaturase 1 genotype (when available). RESULTS: In 30 prospective studies with medians of follow-up ranging 2.5 to 31.9 years, 15 198 incident cardiovascular events occurred among 68 659 participants. Higher levels of LA were significantly associated with lower risks of total CVD, cardiovascular mortality, and ischemic stroke, with hazard ratios per interquintile range of 0.93 (95% CI, 0.88-0.99), 0.78 (0.70-0.85), and 0.88 (0.79-0.98), respectively, and nonsignificantly with lower coronary heart disease risk (0.94; 0.88-1.00). Relationships were similar for LA evaluated across quintiles. AA levels were not associated with higher risk of cardiovascular outcomes; in a comparison of extreme quintiles, higher levels were associated with lower risk of total CVD (0.92; 0.86-0.99). No consistent heterogeneity by population subgroups was identified in the observed relationships. CONCLUSIONS: In pooled global analyses, higher in vivo circulating and tissue levels of LA and possibly AA were associated with lower risk of major cardiovascular events. These results support a favorable role for LA in CVD prevention.

A catalog of genetic loci associated with kidney function from analyses of a million individuals. - Wuttke, Matthias; Li, Yong; Li, Man; Sieber, Karsten B; Feitosa, Mary F; Gorski, Mathias; Tin, Adrienne; Wang, Lihua; Chu, Audrey Y; Hoppmann, Anselm; Kirsten, Holger; Giri, Ayush; et al. (Nat Genet, 2019)
Chronic kidney disease (CKD) is responsible for a public health burden with multi-systemic complications. Through trans-ancestry meta-analysis of genome-wide association studies of estimated glomerular filtration rate (eGFR) and independent replication (n = 1,046,070), we identified 264 associated loci (166 new). Of these, 147 were likely to be relevant for kidney function on the basis of associations with the alternative kidney function marker blood urea nitrogen (n = 416,178). Pathway and enrichment analyses, including mouse models with renal phenotypes, support the kidney as the main target organ. A genetic risk score for lower eGFR was associated with clinically diagnosed CKD in 452,264 independent individuals. Colocalization analyses of associations with eGFR among 783,978 European-ancestry individuals and gene expression across 46 human tissues, including tubulo-interstitial and glomerular kidney compartments, identified 17 genes differentially expressed in kidney. Fine-mapping highlighted missense driver variants in 11 genes and kidney-specific regulatory variants. These results provide a comprehensive priority list of molecular targets for translational research.
Keywords: Chromosome Mapping; European Continental Ancestry Group; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inheritance Patterns; Kidney Function Tests; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Renal Insufficiency, Chronic; Uromodulin

Disentangling the genetics of lean mass. - Karasik, David; Zillikens, M Carola; Hsu, Yi-Hsiang; Aghdassi, Ali; Åkesson, Kristina; Amin, Najaf; Barroso, Inês; Bennett, David A; Bertram, Lars; Bochud, Murielle; Borecki, Ingrid B; Broer, Linda; et al. (Am J Clin Nutr, 2019)
Background: Lean body mass (LM) plays an important role in mobility and metabolic function. We previously identified five loci associated with LM adjusted for fat mass in kilograms. Such an adjustment may reduce the power to identify genetic signals having an association with both lean mass and fat mass. Objectives: To determine the impact of different fat mass adjustments on genetic architecture of LM and identify additional LM loci. Methods: We performed genome-wide association analyses for whole-body LM (20 cohorts of European ancestry with n = 38,292) measured using dual-energy X-ray absorptiometry) or bioelectrical impedance analysis, adjusted for sex, age, age2, and height with or without fat mass adjustments (Model 1 no fat adjustment; Model 2 adjustment for fat mass as a percentage of body mass; Model 3 adjustment for fat mass in kilograms). Results: Seven single-nucleotide polymorphisms (SNPs) in separate loci, including one novel LM locus (TNRC6B), were successfully replicated in an additional 47,227 individuals from 29 cohorts. Based on the strengths of the associations in Model 1 vs Model 3, we divided the LM loci into those with an effect on both lean mass and fat mass in the same direction and refer to those as "sumo wrestler" loci (FTO and MC4R). In contrast, loci with an impact specifically on LM were termed "body builder" loci (VCAN and ADAMTSL3). Using existing available genome-wide association study databases, LM increasing alleles of SNPs in sumo wrestler loci were associated with an adverse metabolic profile, whereas LM increasing alleles of SNPs in "body builder" loci were associated with metabolic protection. Conclusions: In conclusion, we identified one novel LM locus (TNRC6B). Our results suggest that a genetically determined increase in lean mass might exert either harmful or protective effects on metabolic traits, depending on its relation to fat mass.

{Equalization of four cardiovascular risk algorithms after systematic recalibration: individual-participant meta-analysis of 86 prospective studies - Pennells, L.; Kaptoge, S.; Wood, A.; Sweeting, M.; Zhao, X.; White, I.; Burgess, S.; Willeit, P.; Bolton, T.; Moons, K. G. M.; van der Schouw, Y. T.; Selmer, R.; et al. (Eur Heart J, 2019)
There is debate about the optimum algorithm for cardiovascular disease (CVD) risk estimation. We conducted head-to-head comparisons of four algorithms recommended by primary prevention guidelines, before and after 'recalibration', a method that adapts risk algorithms to take account of differences in the risk characteristics of the populations being studied.\ Using individual-participant data on 360 737 participants without CVD at baseline in 86 prospective studies from 22 countries, we compared the Framingham risk score (FRS), Systematic COronary Risk Evaluation (SCORE), pooled cohort equations (PCE), and Reynolds risk score (RRS). We calculated measures of risk discrimination and calibration, and modelled clinical implications of initiating statin therapy in people judged to be at 'high' 10 year CVD risk. Original risk algorithms were recalibrated using the risk factor profile and CVD incidence of target populations. The four algorithms had similar risk discrimination. Before recalibration, FRS, SCORE, and PCE over-predicted CVD risk on average by 10%, 52%, and 41%, respectively, whereas RRS under-predicted by 10%. Original versions of algorithms classified 29-39% of individuals aged â‰¥40 years as high risk. By contrast, recalibration reduced this proportion to 22-24% for every algorithm. We estimated that to prevent one CVD event, it would be necessary to initiate statin therapy in 44-51 such individuals using original algorithms, in contrast to 37-39 individuals with recalibrated algorithms.\ Before recalibration, the clinical performance of four widely used CVD risk algorithms varied substantially. By contrast, simple recalibration nearly equalized their performance and improved modelled targeting of preventive action to clinical need.

{Exome sequencing of 20,791 cases of type 2 diabetes and 24,440 controls - Flannick, J.; Mercader, J. M.; Fuchsberger, C.; Udler, M. S.; Mahajan, A.; Wessel, J.; Teslovich, T. M.; Caulkins, L.; Koesterer, R.; Barajas-Olmos, F.; Blackwell, T. W.; Boerwinkle, E.; et al. (Nature, 2019)
Protein-coding genetic variants that strongly affect disease risk can yield relevant clues to disease pathogenesis. Here we report exome-sequencing analyses of 20,791 individuals with type 2 diabetes (T2D) and 24,440 non-diabetic control participants from 5 ancestries. We identify gene-level associations of rare variants (with minor allele frequencies of less than 0.5%) in 4 genes at exome-wide significance, including a series of more than 30 SLC30A8 alleles that conveys protection against T2D, and in 12 gene sets, including those corresponding to T2D drug targets (P = 6.1 Ã— 10-3) and candidate genes from knockout mice (P = 5.2 Ã— 10-3). Within our study, the strongest T2D gene-level signals for rare variants explain at most 25% of the heritability of the strongest common single-variant signals, and the gene-level effect sizes of the rare variants that we observed in established T2D drug targets will require 75,000-185,000 sequenced cases to achieve exome-wide significance. We propose a method to interpret these modest rare-variant associations and to incorporate these associations into future target or gene prioritization efforts.

Genetic architecture of subcortical brain structures in 38,851 individuals. - Satizabal, Claudia L; Adams, Hieab H H; Hibar, Derrek P; White, Charles C; Knol, Maria J; Stein, Jason L; Scholz, Markus; Sargurupremraj, Muralidharan; Jahanshad, Neda; Roshchupkin, Gennady V; Smith, Albert V; Bis, Joshua C; et al. (Nat Genet, 2019)
Subcortical brain structures are integral to motion, consciousness, emotions and learning. We identified common genetic variation related to the volumes of the nucleus accumbens, amygdala, brainstem, caudate nucleus, globus pallidus, putamen and thalamus, using genome-wide association analyses in almost 40,000 individuals from CHARGE, ENIGMA and UK Biobank. We show that variability in subcortical volumes is heritable, and identify 48 significantly associated loci (40 novel at the time of analysis). Annotation of these loci by utilizing gene expression, methylation and neuropathological data identified 199 genes putatively implicated in neurodevelopment, synaptic signaling, axonal transport, apoptosis, inflammation/infection and susceptibility to neurological disorders. This set of genes is significantly enriched for Drosophila orthologs associated with neurodevelopmental phenotypes, suggesting evolutionarily conserved mechanisms. Our findings uncover novel biology and potential drug targets underlying brain development and disease.

Genetic meta-analysis of diagnosed Alzheimer's disease identifies new risk loci and implicates Aβ, tau, immunity and lipid processing. - Kunkle, Brian W; Grenier-Boley, Benjamin; Sims, Rebecca; Bis, Joshua C; Damotte, Vincent; Naj, Adam C; Boland, Anne; Vronskaya, Maria; van der Lee, Sven J; Amlie-Wolf, Alexandre; Bellenguez, Céline; Frizatti, Aura; et al. (Nat Genet, 2019)
Risk for late-onset Alzheimer's disease (LOAD), the most prevalent dementia, is partially driven by genetics. To identify LOAD risk loci, we performed a large genome-wide association meta-analysis of clinically diagnosed LOAD (94,437 individuals). We confirm 20 previous LOAD risk loci and identify five new genome-wide loci (IQCK, ACE, ADAM10, ADAMTS1, and WWOX), two of which (ADAM10, ACE) were identified in a recent genome-wide association (GWAS)-by-familial-proxy of Alzheimer's or dementia. Fine-mapping of the human leukocyte antigen (HLA) region confirms the neurological and immune-mediated disease haplotype HLA-DR15 as a risk factor for LOAD. Pathway analysis implicates immunity, lipid metabolism, tau binding proteins, and amyloid precursor protein (APP) metabolism, showing that genetic variants affecting APP and Aβ processing are associated not only with early-onset autosomal dominant Alzheimer's disease but also with LOAD. Analyses of risk genes and pathways show enrichment for rare variants (P = 1.32 × 10), indicating that additional rare variants remain to be identified. We also identify important genetic correlations between LOAD and traits such as family history of dementia and education.

{Genome-wide association meta-analyses and fine-mapping elucidate pathways influencing albuminuria - Teumer, A.; Li, Y.; Ghasemi, S.; Prins, B. P.; Wuttke, M.; Hermle, T.; Giri, A.; Sieber, K. B.; Qiu, C.; Kirsten, H.; Tin, A.; Chu, A. Y.; et al. (Nat Commun, 2019)
Increased levels of the urinary albumin-to-creatinine ratio (UACR) are associated with higher risk of kidney disease progression and cardiovascular events, but underlying mechanisms are incompletely understood. Here, we conduct trans-ethnic (n = 564,257) and European-ancestry specific meta-analyses of genome-wide association studies of UACR, including ancestry- and diabetes-specific analyses, and identify 68 UACR-associated loci. Genetic correlation analyses and risk score associations in an independent electronic medical records database (n = 192,868) reveal connections with proteinuria, hyperlipidemia, gout, and hypertension. Fine-mapping and trans-Omics analyses with gene expression in 47 tissues and plasma protein levels implicate genes potentially operating through differential expression in kidney (including TGFB1, MUC1, PRKCI, and OAF), and allow coupling of UACR associations to altered plasma OAF concentrations. Knockdown of OAF and PRKCI orthologs in Drosophila nephrocytes reduces albumin endocytosis. Silencing fly PRKCI further impairs slit diaphragm formation. These results generate a priority list of genes and pathways for translational research to reduce albuminuria.

A genome-wide association study identifies new loci for factor VII and implicates factor VII in ischemic stroke etiology. - de Vries, Paul S; Sabater-Lleal, Maria; Huffman, Jennifer E; Marten, Jonathan; Song, Ci; Pankratz, Nathan; Bartz, Traci M; de Haan, Hugoline G; Delgado, Graciela E; Eicher, John D; Martinez-Perez, Angel; Ward-Caviness, Cavin K; et al. (Blood, 2019)
Factor VII (FVII) is an important component of the coagulation cascade. Few genetic loci regulating FVII activity and/or levels have been discovered to date. We conducted a meta-analysis of 9 genome-wide association studies of plasma FVII levels (7 FVII activity and 2 FVII antigen) among 27 495 participants of European and African ancestry. Each study performed ancestry-specific association analyses. Inverse variance weighted meta-analysis was performed within each ancestry group and then combined for a -ancestry meta-analysis. Our primary analysis included the 7 studies that measured FVII activity, and a secondary analysis included all 9 studies. We provided functional genomic validation for newly identified significant loci by silencing candidate genes in a human liver cell line (HuH7) using small-interfering RNA and then measuring messenger RNA and FVII protein expression. Lastly, we used meta-analysis results to perform Mendelian randomization analysis to estimate the causal effect of FVII activity on coronary artery disease, ischemic stroke (IS), and venous thromboembolism. We identified 2 novel ( and ) and 6 known loci associated with FVII activity, explaining 19.0% of the phenotypic variance. Adding FVII antigen data to the meta-analysis did not result in the discovery of further loci. Silencing in HuH7 cells upregulated FVII, whereas silencing downregulated FVII. Mendelian randomization analyses suggest that FVII activity has a positive causal effect on the risk of IS. Variants at and contribute to FVII activity by regulating expression levels. FVII activity appears to contribute to the etiology of IS in the general population.

{Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group - Irvin, M. R.; Sitlani, C. M.; Floyd, J. S.; Psaty, B. M.; Bis, J. C.; Wiggins, K. L.; Whitsel, E. A.; Sturmer, T.; Stewart, J.; Raffield, L.; Sun, F.; Liu, C. T.; et al. (Am J Hypertens, 2019)
{Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described.\ We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP â‰¥ 140 mm Hg and/or diastolic BP â‰¥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931

Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group. - Irvin, Marguerite R; Sitlani, Colleen M; Floyd, James S; Psaty, Bruce M; Bis, Joshua C; Wiggins, Kerri L; Whitsel, Eric A; Stürmer, Til; Stewart, James; Raffield, Laura; Sun, Fangui; Liu, Ching-Ti; et al. (Am J Hypertens, 2019)
BACKGROUND: Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described. METHODS: We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP ≥ 140 mm Hg and/or diastolic BP ≥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931, nAA = 228). Both a normotensive control group and a treatment-responsive control group were considered in separate analyses. Normotensive controls were untreated (nEA = 14,210, nAA = 2,480) and had systolic BP/diastolic BP < 140/90 mm Hg. Treatment-responsive controls (nEA = 5,266, nAA = 1,817) had BP at goal (<140/90 mm Hg), while treated with one antihypertensive medication class. Individual cohorts used logistic regression with adjustment for age, sex, study site, and principal components for ancestry to examine the association of single-nucleotide polymorphisms with case-control status. Inverse variance-weighted fixed-effects meta-analyses were carried out using METAL. RESULTS: The known hypertension locus, CASZ1, was a top finding among EAs (P = 1.1 × 10-8) and in the race-combined analysis (P = 1.5 × 10-9) using the normotensive control group (rs12046278, odds ratio = 0.71 (95% confidence interval: 0.6-0.8)). Single-nucleotide polymorphisms in this locus were robustly replicated in the Million Veterans Program (MVP) study in consideration of a treatment-responsive control group. There were no statistically significant findings for the discovery analyses including treatment-responsive controls. CONCLUSION: This genomic discovery effort for aTRH identified CASZ1 as an aTRH risk locus.
Keywords: Aged; Antihypertensive Agents; Black or African American; Blood Pressure; Case-Control Studies; DNA (Cytosine-5-)-Methyltransferases; DNA Methyltransferase 3A; DNA-Binding Proteins; Drug Resistance; Dystrophin-Associated Proteins; Europe; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Myosin Heavy Chains; Myosin Type V; Neuropeptides; Pharmacogenetics; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors; Transcription Factors; United States; White People

{Genome-Wide Association Transethnic Meta-Analyses Identifies Novel Associations Regulating Coagulation Factor VIII and von Willebrand Factor Plasma Levels - Sabater-Lleal, M.; Huffman, J. E.; de Vries, P. S.; Marten, J.; Mastrangelo, M. A.; Song, C.; Pankratz, N.; Ward-Caviness, C. K.; Yanek, L. R.; Trompet, S.; Delgado, G. E.; Guo, X.; et al. (Circulation, 2019)
Factor VIII (FVIII) and its carrier protein von Willebrand factor (VWF) are associated with risk of arterial and venous thrombosis and with hemorrhagic disorders. We aimed to identify and functionally test novel genetic associations regulating plasma FVIII and VWF.\ We meta-analyzed genome-wide association results from 46 354 individuals of European, African, East Asian, and Hispanic ancestry. All studies performed linear regression analysis using an additive genetic model and associated ≈35 million imputed variants with natural log-transformed phenotype levels. In vitro gene silencing in cultured endothelial cells was performed for candidate genes to provide additional evidence on association and function. Two-sample Mendelian randomization analyses were applied to test the causal role of FVIII and VWF plasma levels on the risk of arterial and venous thrombotic events.\ We identified 13 novel genome-wide significant ( P≤2.5×10-8) associations, 7 with FVIII levels ( FCHO2/TMEM171/TNPO1, HLA, SOX17/RP1, LINC00583/NFIB, RAB5C-KAT2A, RPL3/TAB1/SYNGR1, and ARSA) and 11 with VWF levels ( PDHB/PXK/KCTD6, SLC39A8, FCHO2/TMEM171/TNPO1, HLA, GIMAP7/GIMAP4, OR13C5/NIPSNAP, DAB2IP, C2CD4B, RAB5C-KAT2A, TAB1/SYNGR1, and ARSA), beyond 10 previously reported associations with these phenotypes. Functional validation provided further evidence of association for all loci on VWF except ARSA and DAB2IP. Mendelian randomization suggested causal effects of plasma FVIII activity levels on venous thrombosis and coronary artery disease risk and plasma VWF levels on ischemic stroke risk.\ The meta-analysis identified 13 novel genetic loci regulating FVIII and VWF plasma levels, 10 of which we validated functionally. We provide some evidence for a causal role of these proteins in thrombotic events.

Genome-wide meta-analysis of variant-by-diuretic interactions as modulators of lipid traits in persons of European and African ancestry. - de Las Fuentes, L; Sung, Y J; Sitlani, C M; Avery, C L; Bartz, T M; Keyser, C de; Evans, D S; Li, X; Musani, S K; Ruiter, R; Smith, A V; Sun, F; et al. (Pharmacogenomics J, 2019)
Hypertension (HTN) is a significant risk factor for cardiovascular morbidity and mortality. Metabolic abnormalities, including adverse cholesterol and triglycerides (TG) profiles, are frequent comorbid findings with HTN and contribute to cardiovascular disease. Diuretics, which are used to treat HTN and heart failure, have been associated with worsening of fasting lipid concentrations. Genome-wide meta-analyses with 39,710 European-ancestry (EA) individuals and 9925 African-ancestry (AA) individuals were performed to identify genetic variants that modify the effect of loop or thiazide diuretic use on blood lipid concentrations. Both longitudinal and cross sectional data were used to compute cohort-specific interaction results, which were then combined through meta-analysis in each ancestry. These ancestry-specific results were further combined through trans-ancestry meta-analysis. Analysis of EA data identified two genome-wide significant (p < 5 × 10) loci with single nucleotide variant (SNV)-loop diuretic interaction on TG concentrations (including COL11A1). Analysis of AA data identified one genome-wide significant locus adjacent to BMP2 with SNV-loop diuretic interaction on TG concentrations. Trans-ancestry analysis strengthened evidence of association for SNV-loop diuretic interaction at two loci (KIAA1217 and BAALC). There were few significant SNV-thiazide diuretic interaction associations on TG concentrations and for either diuretic on cholesterol concentrations. Several promising loci were identified that may implicate biologic pathways that contribute to adverse metabolic side effects from diuretic therapy.

Genomics of 1 million parent lifespans implicates novel pathways and common diseases and distinguishes survival chances. - Timmers, Paul Rhj; Mounier, Ninon; Läll, Kristi; Fischer, Krista; Ning, Zheng; Feng, Xiao; Bretherick, Andrew D; Clark, David W; Agbessi, M; Ahsan, H; Alves, I; Andiappan, A; et al. (Elife, 2019)
We use a genome-wide association of 1 million parental lifespans of genotyped subjects and data on mortality risk factors to validate previously unreplicated findings near , , , , , and 13q21.31, and identify and replicate novel findings near , , and . We also validate previous findings near 5q33.3/ and , whilst finding contradictory evidence at other loci. Gene set and cell-specific analyses show that expression in foetal brain cells and adult dorsolateral prefrontal cortex is enriched for lifespan variation, as are gene pathways involving lipid proteins and homeostasis, vesicle-mediated transport, and synaptic function. Individual genetic variants that increase dementia, cardiovascular disease, and lung cancer - but not other cancers - explain the most variance. Resulting polygenic scores show a mean lifespan difference of around five years of life across the deciles. Editorial note: This article has been through an editorial process in which the authors decide how to respond to the issues raised during peer review. The Reviewing Editor's assessment is that all the issues have been addressed (see decision letter).

{The impact of APOE genotype on survival: Results of 38,537 participants from six population-based cohorts (E2-CHARGE) - Wolters, F. J.; Yang, Q.; Biggs, M. L.; Jakobsdottir, J.; Li, S.; Evans, D. S.; Bis, J. C.; Harris, T. B.; Vasan, R. S.; Zilhao, N. R.; Ghanbari, M.; Ikram, M. A.; et al. (PLoS One, 2019)
Apolipoprotein E is a glycoprotein best known as a mediator and regulator of lipid transport and uptake. The APOE-Îµ4 allele has long been associated with increased risks of Alzheimer's disease and mortality, but the effect of the less prevalent APOE-Îµ2 allele on diseases in the elderly and survival remains elusive.\ We aggregated data of 38,537 individuals of European ancestry (mean age 65.5 years; 55.6% women) from six population-based cohort studies (Rotterdam Study, AGES-Reykjavik Study, Cardiovascular Health Study, Health-ABC Study, and the family-based Framingham Heart Study and Long Life Family Study) to determine the association of APOE, and in particular APOE-Îµ2, with survival in the population.\ During a mean follow-up of 11.7 years, 17,021 individuals died. Compared with homozygous APOE-Îµ3 carriers, APOE-Îµ2 carriers were at lower risk of death (hazard ratio,95% confidence interval: 0.94,0.90-0.99; P = 1.1*10-2), whereas APOE-Îµ4 carriers were at increased risk of death (HR 1.17,1.12-1.21; P = 2.8*10-16). APOE was associated with mortality risk in a dose-dependent manner, with risk estimates lowest for homozygous APOE-Îµ2 (HR 0.89,0.74-1.08), and highest for homozygous APOE-Îµ4 (HR 1.52,1.37-1.70). After censoring for dementia, effect estimates remained similar for APOE-Îµ2 (HR 0.95,0.90-1.01), but attenuated for APOE-Îµ4 (HR 1.07,1.01-1.12). Results were broadly similar across cohorts, and did not differ by age or sex. APOE genotype was associated with baseline lipid fractions (e.g. mean difference(95%CI) in LDL(mg/dL) for Îµ2 versus Îµ33: -17.1(-18.1-16.0), and Îµ4 versus Îµ33: +5.7(4.8;6.5)), but the association between APOE and mortality was unaltered after adjustment for baseline LDL or cardiovascular disease. Given the European ancestry of the study population, results may not apply to other ethnicities.\ Compared with APOE-Îµ3, APOE-Îµ2 is associated with prolonged survival, whereas mortality risk is increased for APOE-Îµ4 carriers. Further collaborative efforts are needed to unravel the role of APOE and in particular APOE-Îµ2 in health and disease.

A large-scale exome array analysis of venous thromboembolism. - Lindström, Sara; Brody, Jennifer A; Turman, Constance; Germain, Marine; Bartz, Traci M; Smith, Erin N; Chen, Ming-Huei; Puurunen, Marja; Chasman, Daniel; Hassler, Jeffrey; Pankratz, Nathan; Basu, Saonli; et al. (Genet Epidemiol, 2019)
Although recent Genome-Wide Association Studies have identified novel associations for common variants, there has been no comprehensive exome-wide search for low-frequency variants that affect the risk of venous thromboembolism (VTE). We conducted a meta-analysis of 11 studies comprising 8,332 cases and 16,087 controls of European ancestry and 382 cases and 1,476 controls of African American ancestry genotyped with the Illumina HumanExome BeadChip. We used the seqMeta package in R to conduct single variant and gene-based rare variant tests. In the single variant analysis, we limited our analysis to the 64,794 variants with at least 40 minor alleles across studies (minor allele frequency [MAF] ~0.08%). We confirmed associations with previously identified VTE loci, including ABO, F5, F11, and FGA. After adjusting for multiple testing, we observed no novel significant findings in single variant or gene-based analysis. Given our sample size, we had greater than 80% power to detect minimum odds ratios greater than 1.5 and 1.8 for a single variant with MAF of 0.01 and 0.005, respectively. Larger studies and sequence data may be needed to identify novel low-frequency and rare variants associated with VTE risk.

{Low thyroid function is not associated with an accelerated deterioration in renal function - Meuwese, C. L.; van Diepen, M.; Cappola, A. R.; Sarnak, M. J.; Shlipak, M. G.; Bauer, D. C.; Fried, L. P.; Iacoviello, M.; Vaes, B.; Degryse, J.; Khaw, K. T.; Luben, R. N.; et al. (Nephrol Dial Transplant, 2019)
Chronic kidney disease (CKD) is frequently accompanied by thyroid hormone dysfunction. It is currently unclear whether these alterations are the cause or consequence of CKD. This study aimed at studying the effect of thyroid hormone alterations on renal function in cross-sectional and longitudinal analyses in individuals from all adult age groups.\ Individual participant data (IPD) from 16 independent cohorts having measured thyroid stimulating hormone, free thyroxine levels and creatinine levels were included. Thyroid hormone status was defined using clinical cut-off values. Estimated glomerular filtration rates (eGFR) were calculated by means of the four-variable Modification of Diet in Renal Disease (MDRD) formula. For this IPD meta-analysis, eGFR at baseline and eGFR change during follow-up were computed by fitting linear regression models and linear mixed models in each cohort separately. Effect estimates were pooled using random effects models.\ A total of 72 856 individuals from 16 different cohorts were included. At baseline, individuals with overt hypothyroidism (n = 704) and subclinical hypothyroidism (n = 3356) had a average (95% confidence interval) -4.07 (-6.37 to -1.78) and -2.40 (-3.78 to -1.02) mL/min/1.73 m2 lower eGFR as compared with euthyroid subjects (n = 66 542). In (subclinical) hyperthyroid subjects (n = 2254), average eGFR was 3.01 (1.50-4.52) mL/min/1.73 m2 higher. During 329 713 patient years of follow-up, eGFR did not decline more rapidly in individuals with low thyroid function compared with individuals with normal thyroid function.\ Low thyroid function is not associated with a deterioration of renal function. The cross-sectional association may be explained by renal dysfunction causing thyroid hormone alterations.

{A meta-analysis of genome-wide association studies identifies multiple longevity genes - Deelen, J.; Evans, D. S.; Arking, D. E.; Tesi, N.; Nygaard, M.; Liu, X.; Wojczynski, M. K.; Biggs, M. L.; van der Spek, A.; Atzmon, G.; Ware, E. B.; Sarnowski, C.; et al. (Nat Commun, 2019)
Human longevity is heritable, but genome-wide association (GWA) studies have had limited success. Here, we perform two meta-analyses of GWA studies of a rigorous longevity phenotype definition including 11,262/3484 cases surviving at or beyond the age corresponding to the 90th/99th survival percentile, respectively, and 25,483 controls whose age at death or at last contact was at or below the age corresponding to the 60th survival percentile. Consistent with previous reports, rs429358 (apolipoprotein E (ApoE) Îµ4) is associated with lower odds of surviving to the 90th and 99th percentile age, while rs7412 (ApoE Îµ2) shows the opposite. Moreover, rs7676745, located near GPR78, associates with lower odds of surviving to the 90th percentile age. Gene-level association analysis reveals a role for tissue-specific expression of multiple genes in longevity. Finally, genetic correlation of the longevity GWA results with that of several disease-related phenotypes points to a shared genetic architecture between health and longevity.

{A meta-analysis of genome-wide association studies identifies multiple longevity genes - Deelen, J.; Evans, D. S.; Arking, D. E.; Tesi, N.; Nygaard, M.; Liu, X.; Wojczynski, M. K.; Biggs, M. L.; van der Spek, A.; Atzmon, G.; Ware, E. B.; Sarnowski, C.; et al. (Nat Commun, 2019)
2) shows the opposite. Moreover, rs7676745, located near GPR78, associates with lower odds of surviving to the 90th percentile age. Gene-level association analysis reveals a role for tissue-specific expression of multiple genes in longevity. Finally, genetic correlation of the longevity GWA results with that of several disease-related phenotypes points to a shared genetic architecture between health and longevity.

{Meta-Analysis of Genomewide Association Studies Reveals Genetic Variants for Hip Bone Geometry - Hsu, Y. H.; Estrada, K.; Evangelou, E.; Ackert-Bicknell, C.; Akesson, K.; Beck, T.; Brown, S. J.; Capellini, T.; Carbone, L.; Cauley, J.; Cheung, C. L.; Cummings, S. R.; et al. (J Bone Miner Res, 2019)
Hip geometry is an important predictor of fracture. We performed a meta-analysis of GWAS studies in adults to identify genetic variants that are associated with proximal femur geometry phenotypes. We analyzed four phenotypes: (i) femoral neck length; (ii) neck-shaft angle; (iii) femoral neck width, and (iv) femoral neck section modulus, estimated from DXA scans using algorithms of hip structure analysis. In the Discovery stage, 10 cohort studies were included in the fixed-effect meta-analysis, with up to 18,719 men and women ages 16 to 93 years. Association analyses were performed with ∼2.5 million polymorphisms under an additive model adjusted for age, body mass index, and height. Replication analyses of meta-GWAS significant loci (at adjusted genomewide significance [GWS], threshold p ≤ 2.6 × 10-8 ) were performed in seven additional cohorts in silico. We looked up SNPs associated in our analysis, for association with height, bone mineral density (BMD), and fracture. In meta-analysis (combined Discovery and Replication stages), GWS associations were found at 5p15 (IRX1 and ADAMTS16); 5q35 near FGFR4; at 12p11 (in CCDC91); 11q13 (near LRP5 and PPP6R3 (rs7102273)). Several hip geometry signals overlapped with BMD, including LRP5 (chr. 11). Chr. 11 SNP rs7102273 was associated with any-type fracture (p = 7.5 × 10-5 ). We used bone transcriptome data and discovered several significant eQTLs, including rs7102273 and PPP6R3 expression (p = 0.0007), and rs6556301 (intergenic, chr.5 near FGFR4) and PDLIM7 expression (p = 0.005). In conclusion, we found associations between several genes and hip geometry measures that explained 12% to 22% of heritability at different sites. The results provide a defined set of genes related to biological pathways relevant to BMD and etiology of bone fragility. © 2019 American Society for Bone and Mineral Research.

Multi-Ancestry Genome-Wide Association Study of Lipid Levels Incorporating Gene-Alcohol Interactions. - de Vries, Paul S; Brown, Michael R; Bentley, Amy R; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Schwander, Karen; Kraja, Aldi T; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; et al. (Am J Epidemiol, 2019)
An individual's lipid profile is influenced by genetic variants and alcohol consumption, but the contribution of interactions between these exposures has not been studied. We therefore incorporated gene-alcohol interactions into a multi-ancestry genome-wide association study of levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides. We included 45 studies in Stage 1 (genome-wide discovery) and 66 studies in Stage 2 (focused follow-up), for a total of 394,584 individuals from five ancestry groups. Genetic main and interaction effects were jointly assessed by a 2 degrees of freedom (DF) test, and a 1 DF test was used to assess the interaction effects alone. Variants at 495 loci were at least suggestively associated (P < 1 × 10-6) with lipid levels in Stage 1 and were evaluated in Stage 2, followed by combined analyses of Stage 1 and Stage 2. In the combined analysis of Stage 1 and Stage 2, 147 independent loci were associated with lipid levels at P < 5 × 10-8 using 2 DF tests, of which 18 were novel. No genome-wide significant associations were found testing the interaction effect alone. The novel loci included several genes (PCSK5, VEGFB, and A1CF) with a putative role in lipid metabolism based on existing evidence from cellular and experimental models.

Multi-ancestry genome-wide gene-smoking interaction study of 387,272 individuals identifies new loci associated with serum lipids. - Bentley, Amy R; Sung, Yun J; Brown, Michael R; Winkler, Thomas W; Kraja, Aldi T; Ntalla, Ioanna; Schwander, Karen; Chasman, Daniel I; Lim, Elise; Deng, Xuan; Guo, Xiuqing; Liu, Jingmin; et al. (Nat Genet, 2019)
The concentrations of high- and low-density-lipoprotein cholesterol and triglycerides are influenced by smoking, but it is unknown whether genetic associations with lipids may be modified by smoking. We conducted a multi-ancestry genome-wide gene-smoking interaction study in 133,805 individuals with follow-up in an additional 253,467 individuals. Combined meta-analyses identified 13 new loci associated with lipids, some of which were detected only because association differed by smoking status. Additionally, we demonstrate the importance of including diverse populations, particularly in studies of interactions with lifestyle factors, where genomic and lifestyle differences by ancestry may contribute to novel findings.

{A multi-ancestry genome-wide study incorporating gene-smoking interactions identifies multiple new loci for pulse pressure and mean arterial pressure - Sung, Y. J.; de Las Fuentes, L.; Winkler, T. W.; Chasman, D. I.; Bentley, A. R.; Kraja, A. T.; Ntalla, I.; Warren, H. R.; Guo, X.; Schwander, K.; Manning, A. K.; Brown, M. R.; et al. (Hum. Mol. Genet., 2019)
Elevated blood pressure (BP), a leading cause of global morbidity and mortality, is influenced by both genetic and lifestyle factors. Cigarette smoking is one such lifestyle factor. Across five ancestries, we performed a genome-wide gene-smoking interaction study of mean arterial pressure (MAP) and pulse pressure (PP) in 129 913 individuals in stage 1 and follow-up analysis in 480 178 additional individuals in stage 2. We report here 136 loci significantly associated with MAP and/or PP. Of these, 61 were previously published through main-effect analysis of BP traits, 37 were recently reported by us for systolic BP and/or diastolic BP through gene-smoking interaction analysis and 38 were newly identified (P < 5 Ã— 10-8, false discovery rate < 0.05). We also identified nine new signals near known loci. Of the 136 loci, 8 showed significant interaction with smoking status. They include CSMD1 previously reported for insulin resistance and BP in the spontaneously hypertensive rats. Many of the 38 new loci show biologic plausibility for a role in BP regulation. SLC26A7 encodes a chloride/bicarbonate exchanger expressed in the renal outer medullary collecting duct. AVPR1A is widely expressed, including in vascular smooth muscle cells, kidney, myocardium and brain. FHAD1 is a long non-coding RNA overexpressed in heart failure. TMEM51 was associated with contractile function in cardiomyocytes. CASP9 plays a central role in cardiomyocyte apoptosis. Identified only in African ancestry were 30 novel loci. Our findings highlight the value of multi-ancestry investigations, particularly in studies of interaction with lifestyle factors, where genomic and lifestyle differences may contribute to novel findings.

Multi-ancestry sleep-by-SNP interaction analysis in 126,926 individuals reveals lipid loci stratified by sleep duration. - Noordam, Raymond; Bos, Maxime M; Wang, Heming; Winkler, Thomas W; Bentley, Amy R; Kilpeläinen, Tuomas O; de Vries, Paul S; Sung, Yun Ju; Schwander, Karen; Cade, Brian E; Manning, Alisa; Aschard, Hugues; et al. (Nat Commun, 2019)
Both short and long sleep are associated with an adverse lipid profile, likely through different biological pathways. To elucidate the biology of sleep-associated adverse lipid profile, we conduct multi-ancestry genome-wide sleep-SNP interaction analyses on three lipid traits (HDL-c, LDL-c and triglycerides). In the total study sample (discovery + replication) of 126,926 individuals from 5 different ancestry groups, when considering either long or short total sleep time interactions in joint analyses, we identify 49 previously unreported lipid loci, and 10 additional previously unreported lipid loci in a restricted sample of European-ancestry cohorts. In addition, we identify new gene-sleep interactions for known lipid loci such as LPL and PCSK9. The previously unreported lipid loci have a modest explained variance in lipid levels: most notable, gene-short-sleep interactions explain 4.25% of the variance in triglyceride level. Collectively, these findings contribute to our understanding of the biological mechanisms involved in sleep-associated adverse lipid profiles.

Multi-ancestry study of blood lipid levels identifies four loci interacting with physical activity. - Kilpeläinen, Tuomas O; Bentley, Amy R; Noordam, Raymond; Sung, Yun Ju; Schwander, Karen; Winkler, Thomas W; Jakupović, Hermina; Chasman, Daniel I; Manning, Alisa; Ntalla, Ioanna; Aschard, Hugues; Brown, Michael R; et al. (Nat Commun, 2019)
Many genetic loci affect circulating lipid levels, but it remains unknown whether lifestyle factors, such as physical activity, modify these genetic effects. To identify lipid loci interacting with physical activity, we performed genome-wide analyses of circulating HDL cholesterol, LDL cholesterol, and triglyceride levels in up to 120,979 individuals of European, African, Asian, Hispanic, and Brazilian ancestry, with follow-up of suggestive associations in an additional 131,012 individuals. We find four loci, in/near CLASP1, LHX1, SNTA1, and CNTNAP2, that are associated with circulating lipid levels through interaction with physical activity; higher levels of physical activity enhance the HDL cholesterol-increasing effects of the CLASP1, LHX1, and SNTA1 loci and attenuate the LDL cholesterol-increasing effect of the CNTNAP2 locus. The CLASP1, LHX1, and SNTA1 regions harbor genes linked to muscle function and lipid metabolism. Our results elucidate the role of physical activity interactions in the genetic contribution to blood lipid levels.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Brazil; Calcium-Binding Proteins; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Exercise; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Hispanic Americans; Humans; LIM-Homeodomain Proteins; Lipid Metabolism; Lipids; Male; Membrane Proteins; Microtubule-Associated Proteins; Middle Aged; Muscle Proteins; Nerve Tissue Proteins; Transcription Factors; Triglycerides; Young Adult

{New alcohol-related genes suggest shared genetic mechanisms with neuropsychiatric disorders - Evangelou, E.; Gao, H.; Chu, C.; Ntritsos, G.; Blakeley, P.; Butts, A. R.; Pazoki, R.; Suzuki, H.; Koskeridis, F.; Yiorkas, A. M.; Karaman, I.; Elliott, J.; et al. (Nat Hum Behav, 2019)
Excessive alcohol consumption is one of the main causes of death and disability worldwide. Alcohol consumption is a heritable complex trait. Here we conducted a meta-analysis of genome-wide association studies of alcohol consumption (g d-1) from the UK Biobank, the Alcohol Genome-Wide Consortium and the Cohorts for Heart and Aging Research in Genomic Epidemiology Plus consortia, collecting data from 480,842 people of European descent to decipher the genetic architecture of alcohol intake. We identified 46 new common loci and investigated their potential functional importance using magnetic resonance imaging data and gene expression studies. We identify genetic pathways associated with alcohol consumption and suggest genetic mechanisms that are shared with neuropsychiatric disorders such as schizophrenia.

{Omega-3 Fatty Acids and Genome-Wide Interaction Analyses Reveal DPP10-Pulmonary Function Association - Xu, J.; Gaddis, N. C.; Bartz, T. M.; Hou, R.; Manichaikul, A. W.; Pankratz, N.; Smith, A. V.; Sun, F.; Terzikhan, N.; Markunas, C. A.; Patchen, B. K.; Schu, M.; et al. (Am J Respir Crit Care Med, 2019)
Omega-3 polyunsaturated fatty acids (n-3 PUFAs) have anti-inflammatory properties that could benefit adults with comprised pulmonary health.\ To investigate n-3 PUFA associations with spirometric measures of pulmonary function tests (PFTs) and determine underlying genetic susceptibility.\ Associations of n-3 PUFA biomarkers (α-linolenic acid, eicosapentaenoic acid, docosapentaenoic acid [DPA], and docosahexaenoic acid [DHA]) were evaluated with PFTs (FEV1, FVC, and FEV1/FVC) in meta-analyses across seven cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium (N = 16,134 of European or African ancestry). PFT-associated n-3 PUFAs were carried forward to genome-wide interaction analyses in the four largest cohorts (N = 11,962) and replicated in one cohort (N = 1,687). Cohort-specific results were combined using joint 2 degree-of-freedom (2df) meta-analyses of SNP associations and their interactions with n-3 PUFAs.\ DPA and DHA were positively associated with FEV1 and FVC (P < 0.025), with evidence for effect modification by smoking and by sex. Genome-wide analyses identified a novel association of rs11693320-an intronic DPP10 SNP-with FVC when incorporating an interaction with DHA, and the finding was replicated (P2df = 9.4 × 10-9 across discovery and replication cohorts). The rs11693320-A allele (frequency, ∼80%) was associated with lower FVC (PSNP = 2.1 × 10-9; βSNP = -161.0 ml), and the association was attenuated by higher DHA levels (PSNP×DHA interaction = 2.1 × 10-7; βSNP×DHA interaction = 36.2 ml).\ We corroborated beneficial effects of n-3 PUFAs on pulmonary function. By modeling genome-wide n-3 PUFA interactions, we identified a novel DPP10 SNP association with FVC that was not detectable in much larger studies ignoring this interaction.

{Quality of dietary fat and genetic risk of type 2 diabetes: individual participant data meta-analysis - Merino, J.; Guasch-Ferr?, M.; Ellervik, C.; Dashti, H. S.; Sharp, S. J.; Wu, P.; Overvad, K.; Sarnowski, C.; Kuokkanen, M.; Lemaitre, R. N.; Justice, A. E.; Ericson, U.; et al. (BMJ, 2019)
{To investigate whether the genetic burden of type 2 diabetes modifies the association between the quality of dietary fat and the incidence of type 2 diabetes.\ Individual participant data meta-analysis.\ Eligible prospective cohort studies were systematically sourced from studies published between January 1970 and February 2017 through electronic searches in major medical databases (Medline, Embase, and Scopus) and discussion with investigators.\ Data from cohort studies or multicohort consortia with available genome-wide genetic data and information about the quality of dietary fat and the incidence of type 2 diabetes in participants of European descent was sought. Prospective cohorts that had accrued five or more years of follow-up were included. The type 2 diabetes genetic risk profile was characterized by a 68-variant polygenic risk score weighted by published effect sizes. Diet was recorded by using validated cohort-specific dietary assessment tools. Outcome measures were summary adjusted hazard ratios of incident type 2 diabetes for polygenic risk score, isocaloric replacement of carbohydrate (refined starch and sugars) with types of fat, and the interaction of types of fat with polygenic risk score.\ Of 102 305 participants from 15 prospective cohort studies, 20 015 type 2 diabetes cases were documented after a median follow-up of 12 years (interquartile range 9.4-14.2). The hazard ratio of type 2 diabetes per increment of 10 risk alleles in the polygenic risk score was 1.64 (95% confidence interval 1.54 to 1.75

{Relationship of Estimated GFR and Albuminuria to Concurrent Laboratory Abnormalities: An Individual Participant Data Meta-analysis in a Global Consortium - Inker, L. A.; Grams, M. E.; Levey, A. S.; Coresh, J.; Cirillo, M.; Collins, J. F.; Gansevoort, R. T.; Gutierrez, O. M.; Hamano, T.; Heine, G. H.; Ishikawa, S.; Jee, S. H.; et al. (Am J Kidney Dis, 2019)
Chronic kidney disease (CKD) is complicated by abnormalities that reflect disruption in filtration, tubular, and endocrine functions of the kidney. Our aim was to explore the relationship of specific laboratory result abnormalities and hypertension with the estimated glomerular filtration rate (eGFR) and albuminuria CKD staging framework.\ Cross-sectional individual participant-level analyses in a global consortium.\ 17 CKD and 38 general population and high-risk cohorts.\ Cohorts in the CKD Prognosis Consortium with data for eGFR and albuminuria, as well as a measurement of hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, or calcium, or hypertension.\ Data were obtained and analyzed between July 2015 and January 2018.\ We modeled the association of eGFR and albuminuria with hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, and calcium values using linear regression and with hypertension and categorical definitions of each abnormality using logistic regression. Results were pooled using random-effects meta-analyses.\ The CKD cohorts (n=254,666 participants) were 27% women and 10% black, with a mean age of 69 (SD, 12) years. The general population/high-risk cohorts (n=1,758,334) were 50% women and 2% black, with a mean age of 50 (16) years. There was a strong graded association between lower eGFR and all laboratory result abnormalities (ORs ranging from 3.27 [95% CI, 2.68-3.97] to 8.91 [95% CI, 7.22-10.99] comparing eGFRs of 15 to 29 with eGFRs of 45 to 59mL/min/1.73m2), whereas albuminuria had equivocal or weak associations with abnormalities (ORs ranging from 0.77 [95% CI, 0.60-0.99] to 1.92 [95% CI, 1.65-2.24] comparing urinary albumin-creatinine ratio > 300 vs < 30mg/g).\ Variations in study era, health care delivery system, typical diet, and laboratory assays.\ Lower eGFR was strongly associated with higher odds of multiple laboratory result abnormalities. Knowledge of risk associations might help guide management in the heterogeneous group of patients with CKD.

Sequencing Analysis at 8p23 Identifies Multiple Rare Variants in DLC1 Associated with Sleep-Related Oxyhemoglobin Saturation Level. - Liang, Jingjing; Cade, Brian E; He, Karen Y; Wang, Heming; Lee, Jiwon; Sofer, Tamar; Williams, Stephanie; Li, Ruitong; Chen, Han; Gottlieb, Daniel J; Evans, Daniel S; Guo, Xiuqing; et al. (Am J Hum Genet, 2019)
Average arterial oxyhemoglobin saturation during sleep (AvSpOS) is a clinically relevant measure of physiological stress associated with sleep-disordered breathing, and this measure predicts incident cardiovascular disease and mortality. Using high-depth whole-genome sequencing data from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) project and focusing on genes with linkage evidence on chromosome 8p23, we observed that six coding and 51 noncoding variants in a gene that encodes the GTPase-activating protein (DLC1) are significantly associated with AvSpOS and replicated in independent subjects. The combined DLC1 association evidence of discovery and replication cohorts reaches genome-wide significance in European Americans (p = 7.9 × 10). A risk score for these variants, built on an independent dataset, explains 0.97% of the AvSpOS variation and contributes to the linkage evidence. The 51 noncoding variants are enriched in regulatory features in a human lung fibroblast cell line and contribute to DLC1 expression variation. Mendelian randomization analysis using these variants indicates a significant causal effect of DLC1 expression in fibroblasts on AvSpOS. Multiple sources of information, including genetic variants, gene expression, and methylation, consistently suggest that DLC1 is a gene associated with AvSpOS.

Systematic analysis of dark and camouflaged genes reveals disease-relevant genes hiding in plain sight. - Ebbert, Mark T W; Jensen, Tanner D; Jansen-West, Karen; Sens, Jonathon P; Reddy, Joseph S; Ridge, Perry G; Kauwe, John S K; Belzil, Veronique; Pregent, Luc; Carrasquillo, Minerva M; Keene, Dirk; Larson, Eric; et al. (Genome Biol, 2019)
BACKGROUND: The human genome contains "dark" gene regions that cannot be adequately assembled or aligned using standard short-read sequencing technologies, preventing researchers from identifying mutations within these gene regions that may be relevant to human disease. Here, we identify regions with few mappable reads that we call dark by depth, and others that have ambiguous alignment, called camouflaged. We assess how well long-read or linked-read technologies resolve these regions. RESULTS: Based on standard whole-genome Illumina sequencing data, we identify 36,794 dark regions in 6054 gene bodies from pathways important to human health, development, and reproduction. Of these gene bodies, 8.7% are completely dark and 35.2% are ≥ 5% dark. We identify dark regions that are present in protein-coding exons across 748 genes. Linked-read or long-read sequencing technologies from 10x Genomics, PacBio, and Oxford Nanopore Technologies reduce dark protein-coding regions to approximately 50.5%, 35.6%, and 9.6%, respectively. We present an algorithm to resolve most camouflaged regions and apply it to the Alzheimer's Disease Sequencing Project. We rescue a rare ten-nucleotide frameshift deletion in CR1, a top Alzheimer's disease gene, found in disease cases but not in controls. CONCLUSIONS: While we could not formally assess the association of the CR1 frameshift mutation with Alzheimer's disease due to insufficient sample-size, we believe it merits investigating in a larger cohort. There remain thousands of potentially important genomic regions overlooked by short-read sequencing that are largely resolved by long-read technologies.
Keywords: Genetic Predisposition to Disease; Genome, Human; Humans; Mutation

Target genes, variants, tissues and transcriptional pathways influencing human serum urate levels. - Tin, Adrienne; Marten, Jonathan; Halperin Kuhns, Victoria L; Li, Yong; Wuttke, Matthias; Kirsten, Holger; Sieber, Karsten B; Qiu, Chengxiang; Gorski, Mathias; Yu, Zhi; Giri, Ayush; Sveinbjornsson, Gardar; et al. (Nat Genet, 2019)
Elevated serum urate levels cause gout and correlate with cardiometabolic diseases via poorly understood mechanisms. We performed a trans-ancestry genome-wide association study of serum urate in 457,690 individuals, identifying 183 loci (147 previously unknown) that improve the prediction of gout in an independent cohort of 334,880 individuals. Serum urate showed significant genetic correlations with many cardiometabolic traits, with genetic causality analyses supporting a substantial role for pleiotropy. Enrichment analysis, fine-mapping of urate-associated loci and colocalization with gene expression in 47 tissues implicated the kidney and liver as the main target organs and prioritized potentially causal genes and variants, including the transcriptional master regulators in the liver and kidney, HNF1A and HNF4A. Experimental validation showed that HNF4A transactivated the promoter of ABCG2, encoding a major urate transporter, in kidney cells, and that HNF4A p.Thr139Ile is a functional variant. Transcriptional coregulation within and across organs may be a general mechanism underlying the observed pleiotropy between urate and cardiometabolic traits.

Trans-ethnic association study of blood pressure determinants in over 750,000 individuals. - Giri, Ayush; Hellwege, Jacklyn N; Keaton, Jacob M; Park, Jihwan; Qiu, Chengxiang; Warren, Helen R; Torstenson, Eric S; Kovesdy, Csaba P; Sun, Yan V; Wilson, Otis D; Robinson-Cohen, Cassianne; Roumie, Christianne L; et al. (Nat Genet, 2019)
In this trans-ethnic multi-omic study, we reinterpret the genetic architecture of blood pressure to identify genes, tissues, phenomes and medication contexts of blood pressure homeostasis. We discovered 208 novel common blood pressure SNPs and 53 rare variants in genome-wide association studies of systolic, diastolic and pulse pressure in up to 776,078 participants from the Million Veteran Program (MVP) and collaborating studies, with analysis of the blood pressure clinical phenome in MVP. Our transcriptome-wide association study detected 4,043 blood pressure associations with genetically predicted gene expression of 840 genes in 45 tissues, and mouse renal single-cell RNA sequencing identified upregulated blood pressure genes in kidney tubule cells.

Translating Alzheimer's disease-associated polymorphisms into functional candidates: a survey of IGAP genes and SNPs. - Katsumata, Yuriko; Nelson, Peter T; Estus, Steven; Fardo, David W (Neurobiol Aging, 2019)
The International Genomics of Alzheimer's Project (IGAP) is a consortium for characterizing the genetic landscape of Alzheimer's disease (AD). The identified and/or confirmed 19 single-nucleotide polymorphisms (SNPs) associated with AD are located on non-coding DNA regions, and their functional impacts on AD are as yet poorly understood. We evaluated the roles of the IGAP SNPs by integrating data from many resources, based on whether the IGAP SNP was (1) a proxy for a coding SNP or (2) associated with altered mRNA transcript levels. For (1), we confirmed that 12 AD-associated coding common SNPs and five nonsynonymous rare variants are in linkage disequilibrium with the IGAP SNPs. For (2), the IGAP SNPs in CELF1 and MS4A6A were associated with expression of their neighboring genes, MYBPC3 and MS4A6A, respectively, in blood. The IGAP SNP in DSG2 was an expression quantitative trait loci (eQTL) for DLGAP1 and NETO1 in the human frontal cortex. The IGAP SNPs in ABCA7, CD2AP, and CD33 each acted as eQTL for AD-associated genes in brain. Our approach for identifying proxies and examining eQTL highlighted potentially impactful, novel gene regulatory phenomena pertinent to the AD phenotype.

{Variants Associated with the Ankle Brachial Index Differ by Hispanic/Latino Ethnic Group: a genome-wide association study in the Hispanic Community Health Study/Study of Latinos - Sofer, T.; Emery, L.; Jain, D.; Ellis, A. M.; Laurie, C. C.; Allison, M. A.; Lee, J.; Kurniansyah, N.; Kerr, K. F.; Gonz?lez, H. M.; Tarraf, W.; Criqui, M. H.; et al. (Sci Rep, 2019)
Lower extremity peripheral artery disease (PAD) burden differs by race/ethnicity. Although familial aggregation and heritability studies suggest a genetic basis, little is known about the genetic susceptibility to PAD, especially in non-European descent populations. Genome-wide association studies (GWAS) of the ankle brachial index (ABI) and PAD (defined as an ABI < 0.90) have not been conducted in Hispanics/Latinos. We performed a GWAS of PAD and the ABI in 7,589 participants aged >45 years from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). We also performed GWAS for ABI stratified by Hispanic/Latino ethnic subgroups: Central American, Mexican, and South American (Mainland group), and Cuban, Dominican, and Puerto Rican (Caribbean group). We detected two genome-wide significant associations for the ABI in COMMD10 in Puerto Ricans, and at SYBU in the Caribbean group. The lead SNP rs4466200 in the COMMD10 gene had a replication p = 0.02 for the ABI in Multi-Ethnic Study of Atherosclerosis (MESA) African Americans, but it did not replicate in African Americans from the Cardiovascular Health Study (CHS). In a regional look-up, a nearby SNP rs12520838 had Bonferroni adjusted p = 0.05 (unadjusted p = 7.5 Ã— 10-5) for PAD in MESA Hispanics. Among three suggestive associations (p < 10-7) in subgroup-specific analyses, DMD on chromosome X, identified in Central Americans, replicated in MESA Hispanics (p = 2.2 Ã— 10-4). None of the previously reported ABI and PAD associations in whites generalized to Hispanics/Latinos.

Alzheimer Disease Pathology-Associated Polymorphism in a Complex Variable Number of Tandem Repeat Region Within the MUC6 Gene, Near the AP2A2 Gene. - Katsumata, Yuriko; Fardo, David W; Bachstetter, Adam D; Artiushin, Sergey C; Wang, Wang-Xia; Wei, Angela; Brzezinski, Lena J; Nelson, Bela G; Huang, Qingwei; Abner, Erin L; Anderson, Sonya; Patel, Indumati; et al. (J Neuropathol Exp Neurol, 2020)
We found evidence of late-onset Alzheimer disease (LOAD)-associated genetic polymorphism within an exon of Mucin 6 (MUC6) and immediately downstream from another gene: Adaptor Related Protein Complex 2 Subunit Alpha 2 (AP2A2). PCR analyses on genomic DNA samples confirmed that the size of the MUC6 variable number tandem repeat (VNTR) region was highly polymorphic. In a cohort of autopsied subjects with quantitative digital pathology data (n = 119), the size of the polymorphic region was associated with the severity of pTau pathology in neocortex. In a separate replication cohort of autopsied subjects (n = 173), more pTau pathology was again observed in subjects with longer VNTR regions (p = 0.031). Unlike MUC6, AP2A2 is highly expressed in human brain. AP2A2 expression was lower in a subset analysis of brain samples from persons with longer versus shorter VNTR regions (p = 0.014 normalizing with AP2B1 expression). Double-label immunofluorescence studies showed that AP2A2 protein often colocalized with neurofibrillary tangles in LOAD but was not colocalized with pTau proteinopathy in progressive supranuclear palsy, or with TDP-43 proteinopathy. In summary, polymorphism in a repeat-rich region near AP2A2 was associated with neocortical pTau proteinopathy (because of the unique repeats, prior genome-wide association studies were probably unable to detect this association), and AP2A2 was often colocalized with neurofibrillary tangles in LOAD.
Keywords: Adaptor Protein Complex 2; Adaptor Protein Complex alpha Subunits; Aged; Aged, 80 and over; Alzheimer Disease; Autopsy; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Minisatellite Repeats; Mucin-6; Neurofibrillary Tangles; Polymorphism, Genetic; Polymorphism, Single Nucleotide; TDP-43 Proteinopathies

Association Between Blood Pressure and Later-Life Cognition Among Black and White Individuals. - Levine, Deborah A; Gross, Alden L; Briceño, Emily M; Tilton, Nicholas; Kabeto, Mohammed U; Hingtgen, Stephanie M; Giordani, Bruno J; Sussman, Jeremy B; Hayward, Rodney A; Burke, James F; Elkind, Mitchell S V; Manly, Jennifer J; et al. (JAMA Neurol, 2020)
Importance: Black individuals are more likely than white individuals to develop dementia. Whether higher blood pressure (BP) levels in black individuals explain differences between black and white individuals in dementia risk is uncertain. Objective: To determine whether cumulative BP levels explain racial differences in cognitive decline. Design, Setting, and Participants: Individual participant data from 5 cohorts (January 1971 to December 2017) were pooled from the Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, and Northern Manhattan Study. Outcomes were standardized as t scores (mean [SD], 50 [10]); a 1-point difference represented a 0.1-SD difference in cognition. The median (interquartile range) follow-up was 12.4 (5.9-21.0) years. Analysis began September 2018. Main Outcomes and Measures: The primary outcome was change in global cognition, and secondary outcomes were change in memory and executive function. Exposures: Race (black vs white). Results: Among 34 349 participants, 19 378 individuals who were free of stroke and dementia and had longitudinal BP, cognitive, and covariate data were included in the analysis. The mean (SD) age at first cognitive assessment was 59.8 (10.4) years and ranged from 5 to 95 years. Of 19 378 individuals, 10 724 (55.3%) were female and 15 526 (80.1%) were white. Compared with white individuals, black individuals had significantly faster declines in global cognition (-0.03 points per year faster [95% CI, -0.05 to -0.01]; P = .004) and memory (-0.08 points per year faster [95% CI, -0.11 to -0.06]; P < .001) but significantly slower declines in executive function (0.09 points per year slower [95% CI, 0.08-0.10]; P < .001). Time-dependent cumulative mean systolic BP level was associated with significantly faster declines in global cognition (-0.018 points per year faster per each 10-mm Hg increase [95% CI, -0.023 to -0.014]; P < .001), memory (-0.028 points per year faster per each 10-mm Hg increase [95% CI, -0.035 to -0.021]; P < .001), and executive function (-0.01 points per year faster per each 10-mm Hg increase [95% CI, -0.014 to -0.007]; P < .001). After adjusting for cumulative mean systolic BP, differences between black and white individuals in cognitive slopes were attenuated for global cognition (-0.01 points per year [95% CI, -0.03 to 0.01]; P = .56) and memory (-0.06 points per year [95% CI, -0.08 to -0.03]; P < .001) but not executive function (0.10 points per year [95% CI, 0.09-0.11]; P < .001). Conclusions and Relevance: These results suggest that black individuals' higher cumulative BP levels may contribute to racial differences in later-life cognitive decline.

Association of Nonobstructive Chronic Bronchitis With Respiratory Health Outcomes in Adults. - Balte, Pallavi P; Chaves, Paulo H M; Couper, David J; Enright, Paul; Jacobs, David R; Kalhan, Ravi; Kronmal, Richard A; Loehr, Laura R; London, Stephanie J; Newman, Anne B; O'Connor, George T; Schwartz, Joseph E; et al. (JAMA Intern Med, 2020)
Importance: Chronic bronchitis has been associated with cigarette smoking as well as with e-cigarette use among young adults, but the association of chronic bronchitis in persons without airflow obstruction or clinical asthma, described as nonobstructive chronic bronchitis, with respiratory health outcomes remains uncertain. Objective: To assess whether nonobstructive chronic bronchitis is associated with adverse respiratory health outcomes in adult ever smokers and never smokers. Design, Setting, and Participants: This prospective cohort study included 22 325 adults without initial airflow obstruction (defined as the ratio of forced expiratory volume in the first second [FEV1] to forced vital capacity [FVC] of <0.70) or clinical asthma at baseline. The National Heart, Lung, and Blood Institute (NHLBI) Pooled Cohorts Study harmonized and pooled data from 9 US general population-based cohorts. Thus present study is based on data from 5 of these cohorts. Participants were enrolled from August 1971 through May 2007 and were followed up through December 2018. Exposures: Nonobstructive chronic bronchitis was defined by questionnaire at baseline as both cough and phlegm for at least 3 months for at least 2 consecutive years. Main Outcomes and Measures: Lung function was measured by prebronchodilator spirometry. Hospitalizations and deaths due to chronic lower respiratory disease and respiratory disease-related mortality were defined by events adjudication and administrative criteria. Models were stratified by smoking status and adjusted for anthropometric, sociodemographic, and smoking-related factors. The comparison group was participants without nonobstructive chronic bronchitis. Results: Among 22 325 adults included in the analysis, mean (SD) age was 53.0 (16.3) years (range, 18.0-95.0 years), 58.2% were female, 65.9% were non-Hispanic white, and 49.6% were ever smokers. Among 11 082 ever smokers with 99 869 person-years of follow-up, participants with nonobstructive chronic bronchitis (300 [2.7%]) had accelerated decreases in FEV1 (4.1 mL/y; 95% CI, 2.1-6.1 mL/y) and FVC (4.7 mL/y; 95% CI, 2.2-7.2 mL/y), increased risks of chronic lower respiratory disease-related hospitalization or mortality (hazard ratio [HR], 2.2; 95% CI, 1.7-2.7), and greater respiratory disease-related (HR, 2.0; 95% CI, 1.1-3.8) and all-cause mortality (HR, 1.5; 95% CI, 1.3-1.8) compared with ever smokers without nonobstructive chronic bronchitis. Among 11 243 never smokers with 120 004 person-years of follow-up, participants with nonobstructive chronic bronchitis (151 [1.3%]) had greater rates of chronic lower respiratory disease-related hospitalization or mortality (HR, 3.1; 95% CI, 2.1-4.5) compared with never smokers without nonobstructive chronic bronchitis. Nonobstructive chronic bronchitis was not associated with FEV1:FVC decline or incident airflow obstruction. The presence of at least 1 of the component symptoms of nonobstructive chronic bronchitis (ie, chronic cough or phlegm), which was common in both ever smokers (11.0%) and never smokers (6.7%), was associated with adverse respiratory health outcomes. Conclusions and Relevance: The findings suggest that nonobstructive chronic bronchitis is associated with adverse respiratory health outcomes, particularly in ever smokers, and may be a high-risk phenotype suitable for risk stratification and targeted therapies.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asthma; Bronchitis, Chronic; Female; Humans; Lung; Male; Middle Aged; Prospective Studies; Respiratory Function Tests; Smokers; Smoking; Young Adult

{Cerebral small vessel disease genomics and its implications across the lifespan - Sargurupremraj, M.; Suzuki, H.; Jian, X.; Sarnowski, C.; Evans, T. E.; Bis, J. C.; Eiriksdottir, G.; Sakaue, S.; Terzikhan, N.; Habes, M.; Zhao, W.; Armstrong, N. J.; et al. (Nat Commun, 2020)
White matter hyperintensities (WMH) are the most common brain-imaging feature of cerebral small vessel disease (SVD), hypertension being the main known risk factor. Here, we identify 27 genome-wide loci for WMH-volume in a cohort of 50,970 older individuals, accounting for modification/confounding by hypertension. Aggregated WMH risk variants were associated with altered white matter integrity (p = 2.5Ã—10-7) in brain images from 1,738 young healthy adults, providing insight into the lifetime impact of SVD genetic risk. Mendelian randomization suggested causal association of increasing WMH-volume with stroke, Alzheimer-type dementia, and of increasing blood pressure (BP) with larger WMH-volume, notably also in persons without clinical hypertension. Transcriptome-wide colocalization analyses showed association of WMH-volume with expression of 39 genes, of which four encode known drug targets. Finally, we provide insight into BP-independent biological pathways underlying SVD and suggest potential for genetic stratification of high-risk individuals and for genetically-informed prioritization of drug targets for prevention trials.

Cholesterol Variability and Cranial Magnetic Resonance Imaging Findings in Older Adults: The Cardiovascular Health Study. - Kalani, Rizwan; Bartz, Traci M; Suchy-Dicey, Astrid; Elkind, Mitchell S V; Psaty, Bruce M; Leung, Lester Y; Rice, Kenneth; Tirschwell, David; Longstreth, W T (Stroke, 2020)
Background and Purpose- Serum cholesterol variability, independent of mean, has been associated with stroke, white matter hyperintensities on cranial magnetic resonance imaging (MRI), and other cardiovascular events. We sought to assess the relationship between total serum cholesterol (TC) variability and cranial MRI findings of subclinical or covert vascular brain injury in a longitudinal, population-based cohort study of older adults. Methods- In the Cardiovascular Health Study, we assessed associations between intraindividual TC mean, trend, and variability over ≈5 years with covert brain infarction (CBI) and white matter grade (WMG) on cranial MRI. Mean TC was calculated for each study participant from 4 annual TC measurements between 2 MRI scans. TC trend was calculated as the slope of the linear regression of the TC measurements, and TC variability was calculated as the SD of the residuals from the linear regression. We evaluated the association of intraindividual TC variability with incident CBI and worsening WMG between 2 MRI scans in primary analyses and with prevalent CBI number and WMG on the follow-up MRI scan in secondary analyses. Results- Among participants who were eligible for the study and free of clinical stroke before the follow-up MRI, 17.9% of 1098 had incident CBI, and 27.8% of 1351 had worsening WMG on the follow-up MRI. Mean, trend, and variability of TC were not associated with these outcomes. TC variability, independent of mean and trend, was significantly associated with the number of CBI (β=0.009 [95% CI, 0.003-0.016] =0.004; N=1604) and was associated with WMG (β, 0.009 [95% CI, -0.0002 to 0.019] =0.055; N=1602) on the follow-up MRI. Conclusions- Among older adults, TC variability was not associated with incident CBI or worsening WMG but was associated with the number of prevalent CBI on cranial MRI. More work is needed to validate and to clarify the mechanisms underlying such associations.

{Discovery of rare variants associated with blood pressure regulation through meta-analysis of 1.3 million individuals - Surendran, P.; Feofanova, E. V.; Lahrouchi, N.; Ntalla, I.; Karthikeyan, S.; Cook, J.; Chen, L.; Mifsud, B.; Yao, C.; Kraja, A. T.; Cartwright, J. H.; Hellwege, J. N.; et al. (Nat Genet, 2020)
Genetic studies of blood pressure (BP) to date have mainly analyzed common variants (minor allele frequency > 0.05). In a meta-analysis of up to 1.3 million participants, we discovered 106 new BP-associated genomic regions and 87 rare (minor allele frequency â‰¤ 0.01) variant BP associations (P < 5 Ã— 10-8), of which 32 were in new BP-associated loci and 55 were independent BP-associated single-nucleotide variants within known BP-associated regions. Average effects of rare variants (44% coding) were 8 times larger than common variant effects and indicate potential candidate causal genes at new and known loci (for example, GATA5 and PLCB3). BP-associated variants (including rare and common) were enriched in regions of active chromatin in fetal tissues, potentially linking fetal development with BP regulation in later life. Multivariable Mendelian randomization suggested possible inverse effects of elevated systolic and diastolic BP on large artery stroke. Our study demonstrates the utility of rare-variant analyses for identifying candidate genes and the results highlight potential therapeutic targets.

{Dynamic incorporation of multiple in silico functional annotations empowers rare variant association analysis of large whole-genome sequencing studies at scale - Li, X.; Li, Z.; Zhou, H.; Gaynor, S. M.; Liu, Y.; Chen, H.; Sun, R.; Dey, R.; Arnett, D. K.; Aslibekyan, S.; Ballantyne, C. M.; Bielak, L. F.; et al. (Nat Genet, 2020)
Large-scale whole-genome sequencing studies have enabled the analysis of rare variants (RVs) associated with complex phenotypes. Commonly used RV association tests have limited scope to leverage variant functions. We propose STAAR (variant-set test for association using annotation information), a scalable and powerful RV association test method that effectively incorporates both variant categories and multiple complementary annotations using a dynamic weighting scheme. For the latter, we introduce 'annotation principal components', multidimensional summaries of in silico variant annotations. STAAR accounts for population structure and relatedness and is scalable for analyzing very large cohort and biobank whole-genome sequencing studies of continuous and dichotomous traits. We applied STAAR to identify RVs associated with four lipid traits in 12,316 discovery and 17,822 replication samples from the Trans-Omics for Precision Medicine Program. We discovered and replicated new RV associations, including disruptive missense RVs of NPC1L1 and an intergenic region near APOC1P1 associated with low-density lipoprotein cholesterol.

Estrogen, brain structure, and cognition in postmenopausal women. - Boyle, Christina P; Raji, Cyrus A; Erickson, Kirk I; Lopez, Oscar L; Becker, James T; Gach, H Michael; Kuller, Lewis H; Longstreth, William; Carmichael, Owen T; Riedel, Brandalyn C; Thompson, Paul M (Hum Brain Mapp, 2020)
Declining estrogen levels before, during, and after menopause can affect memory and risk for Alzheimer's disease. Undesirable side effects of hormone variations emphasize a role for hormone therapy (HT) where possible benefits include a delay in the onset of dementia-yet findings are inconsistent. Effects of HT may be mediated by estrogen receptors found throughout the brain. Effects may also depend on lifestyle factors, timing of use, and genetic risk. We studied the impact of self-reported HT use on brain volume in 562 elderly women (71-94 years) with mixed cognitive status while adjusting for aforementioned factors. Covariate-adjusted voxelwise linear regression analyses using a model with 16 predictors showed HT use as positively associated with regional brain volumes, regardless of cognitive status. Examinations of other factors related to menopause, oophorectomy and hysterectomy status independently yielded positive effects on brain volume when added to our model. One interaction term, HTxBMI, out of several examined, revealed significant negative association with overall brain volume, suggesting a greater reduction in brain volume than BMI alone. Our main findings relating HT to regional brain volume were as hypothesized, but some exploratory analyses were not in line with existing hypotheses. Studies suggest lower levels of estrogen resulting from oophorectomy and hysterectomy affect brain volume negatively, and the addition of HT modifies the relation between BMI and brain volume positively. Effects of HT may depend on the age range assessed, motivating studies with a wider age range as well as a randomized design.

Fatty Acid Binding Protein-4 and Risk of Cardiovascular Disease: The Cardiovascular Health Study. - Egbuche, Obiora; Biggs, Mary L; Ix, Joachim H; Kizer, Jorge R; Lyles, Mary F; Siscovick, David S; Djoussé, Luc; Mukamal, Kenneth J (J Am Heart Assoc, 2020)
Background FABP-4 (fatty acid binding protein-4) is a lipid chaperone in adipocytes and has been associated with prognosis in selected clinical populations. We investigated the associations between circulating FABP-4, risk of incident cardiovascular disease (CVD), and risk of CVD mortality among older adults with and without established CVD. Methods and Results In the Cardiovascular Health Study, we measured FABP4 levels in stored specimens from the 1992-993 visit and followed participants for incident CVD if they were free of prevalent CVD at baseline and for CVD mortality through June 2015. We used Cox regression to estimate hazard ratios for incident CVD and CVD mortality per doubling in serum FABP-4 adjusted for age, sex, race, field center, waist circumference, blood pressure, lipids, fasting glucose, and C-reactive protein. Among 4026 participants free of CVD and 681 with prevalent CVD, we documented 1878 cases of incident CVD and 331 CVD deaths, respectively. In adjusted analyses, FABP-4 was modestly associated with risk of incident CVD (mean, 34.24; SD, 18.90; HR, 1.10 per doubling in FABP-4, 95% CI, 1.00-1.21). In contrast, FABP-4 was more clearly associated with risk of CVD mortality among participants without (HR hazard ratio 1.24, 95% CI, 1.10-1.40) or with prevalent CVD (HR hazard ratio 1.57, 95% CI, 1.24-1.98). These associations were not significantly modified by sex, age, and waist circumference. Conclusions Serum FABP-4 is modestly associated with risk of incident CVD even after adjustment for standard risk factors, but more strongly associated with CVD mortality among older adults with and without established CVD.

Gene-educational attainment interactions in a multi-ancestry genome-wide meta-analysis identify novel blood pressure loci. - de Las Fuentes, Lisa; Sung, Yun Ju; Noordam, Raymond; Winkler, Thomas; Feitosa, Mary F; Schwander, Karen; Bentley, Amy R; Brown, Michael R; Guo, Xiuqing; Manning, Alisa; Chasman, Daniel I; Aschard, Hugues; et al. (Mol Psychiatry, 2020)
Educational attainment is widely used as a surrogate for socioeconomic status (SES). Low SES is a risk factor for hypertension and high blood pressure (BP). To identify novel BP loci, we performed multi-ancestry meta-analyses accounting for gene-educational attainment interactions using two variables, "Some College" (yes/no) and "Graduated College" (yes/no). Interactions were evaluated using both a 1 degree of freedom (DF) interaction term and a 2DF joint test of genetic and interaction effects. Analyses were performed for systolic BP, diastolic BP, mean arterial pressure, and pulse pressure. We pursued genome-wide interrogation in Stage 1 studies (N = 117 438) and follow-up on promising variants in Stage 2 studies (N = 293 787) in five ancestry groups. Through combined meta-analyses of Stages 1 and 2, we identified 84 known and 18 novel BP loci at genome-wide significance level (P < 5 × 10). Two novel loci were identified based on the 1DF test of interaction with educational attainment, while the remaining 16 loci were identified through the 2DF joint test of genetic and interaction effects. Ten novel loci were identified in individuals of African ancestry. Several novel loci show strong biological plausibility since they involve physiologic systems implicated in BP regulation. They include genes involved in the central nervous system-adrenal signaling axis (ZDHHC17, CADPS, PIK3C2G), vascular structure and function (GNB3, CDON), and renal function (HAS2 and HAS2-AS1, SLIT3). Collectively, these findings suggest a role of educational attainment or SES in further dissection of the genetic architecture of BP.

The genetic architecture of the human cerebral cortex - Grasby, Katrina L.; Jahanshad, Neda; Painter, Jodie N.; Colodro-Conde, Lucía; Bralten, Janita; Hibar, Derrek P.; Lind, Penelope A.; Pizzagalli, Fabrizio; Ching, Christopher R. K.; McMahon, Mary Agnes B.; Shatokhina, Natalia; Zsembik, Leo C. P.; et al. (Science, 2020)

{Genetic correlations and genome-wide associations of cortical structure in general population samples of 22,824 adults - Hofer, E.; Roshchupkin, G. V.; Adams, H. H. H.; Knol, M. J.; Lin, H.; Li, S.; Zare, H.; Ahmad, S.; Armstrong, N. J.; Satizabal, C. L.; Bernard, M.; Bis, J. C.; et al. (Nat Commun, 2020)
Cortical thickness, surface area and volumes vary with age and cognitive function, and in neurological and psychiatric diseases. Here we report heritability, genetic correlations and genome-wide associations of these cortical measures across the whole cortex, and in 34 anatomically predefined regions. Our discovery sample comprises 22,824 individuals from 20 cohorts within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank. We identify genetic heterogeneity between cortical measures and brain regions, and 160 genome-wide significant associations pointing to wnt/Î²-catenin, TGF-Î² and sonic hedgehog pathways. There is enrichment for genes involved in anthropometric traits, hindbrain development, vascular and neurodegenerative disease and psychiatric conditions. These data are a rich resource for studies of the biological mechanisms behind cortical development and aging.

{Genetic Determinants of Electrocardiographic P-wave Duration and Relation to Atrial Fibrillation - Weng, L. C.; Hall, A. W.; Choi, S. H.; Jurgens, S. J.; Haessler, J.; Bihlmeyer, N. A.; Grarup, N.; Lin, H.; Teumer, A.; Li-Gao, R.; Yao, J.; Guo, X.; et al. (Circ Genom Precis Med, 2020)
Background - The P-wave duration (PWD) is an electrocardiographic (ECG) measurement that represents cardiac conduction in the atria. Shortened or prolonged PWD is associated with atrial fibrillation (AF). We used exome chip data to examine the associations between common and rare variants with PWD. Methods - Fifteen studies comprising 64,440 individuals (56,943 European, 5,681 African, 1,186 Hispanic, 630 Asian), and 230,000 variants were used to examine associations with maximum PWD across the 12-lead ECG. Meta-analyses summarized association results for common variants; gene-based burden and SKAT tests examined low-frequency variant-PWD associations. Additionally, we examined the associations between PWD loci and AF using previous AF GWAS. Results - We identified 21 common and low-frequency genetic loci (14 novel) associated with maximum PWD, including several AF loci (TTN, CAND2, SCN10A, PITX2, CAV1, SYNPO2L, SOX5, TBX5, MYH6, RPL3L). The top variants at known sarcomere genes (TTN, MYH6) were associated with longer PWD and increased AF risk. However, top variants at other loci (e.g., PITX2 and SCN10A) were associated with longer PWD but lower AF risk. Conclusions - Our results highlight multiple novel genetic loci associated with PWD, and underscore the shared mechanisms of atrial conduction and AF. Prolonged PWD may be an endophenotype for several different genetic mechanisms of AF.

{Genome-wide association and Mendelian randomisation analysis provide insights into the pathogenesis of heart failure - Shah, S.; Henry, A.; Roselli, C.; Lin, H.; Sveinbj?rnsson, G.; Fatemifar, G.; Hedman, ?. K.; Wilk, J. B.; Morley, M. P.; Chaffin, M. D.; Helgadottir, A.; Verweij, N.; et al. (Nat Commun, 2020)
Heart failure (HF) is a leading cause of morbidity and mortality worldwide. A small proportion of HF cases are attributable to monogenic cardiomyopathies and existing genome-wide association studies (GWAS) have yielded only limited insights, leaving the observed heritability of HF largely unexplained. We report results from a GWAS meta-analysis of HF comprising 47,309 cases and 930,014 controls. Twelve independent variants at 11 genomic loci are associated with HF, all of which demonstrate one or more associations with coronary artery disease (CAD), atrial fibrillation, or reduced left ventricular function, suggesting shared genetic aetiology. Functional analysis of non-CAD-associated loci implicate genes involved in cardiac development (MYOZ1, SYNPO2L), protein homoeostasis (BAG3), and cellular senescence (CDKN1A). Mendelian randomisation analysis supports causal roles for several HF risk factors, and demonstrates CAD-independent effects for atrial fibrillation, body mass index, and hypertension. These findings extend our knowledge of the pathways underlying HF and may inform new therapeutic strategies.

{Genome-Wide Association Study Meta-Analysis of Stroke in 22 000 Individuals of African Descent Identifies Novel Associations With Stroke - Keene, K. L.; Hyacinth, H. I.; Bis, J. C.; Kittner, S. J.; Mitchell, B. D.; Cheng, Y. C.; Pare, G.; Chong, M.; O'Donnell, M.; Meschia, J. F.; Chen, W. M.; Sale, M. M.; et al. (Stroke, 2020)
Stroke is a complex disease with multiple genetic and environmental risk factors. Blacks endure a nearly 2-fold greater risk of stroke and are 2× to 3× more likely to die from stroke than European Americans.\ The COMPASS (Consortium of Minority Population Genome-Wide Association Studies of Stroke) has conducted a genome-wide association meta-analysis of stroke in >22 000 individuals of African ancestry (3734 cases, 18 317 controls) from 13 cohorts.\ In meta-analyses, we identified one single nucleotide polymorphism (rs55931441) near the HNF1A gene that reached genome-wide significance (P=4.62×10-8) and an additional 29 variants with suggestive evidence of association (P<1×10-6), representing 24 unique loci. For validation, a look-up analysis for a 100 kb region flanking the COMPASS single nucleotide polymorphism was performed in SiGN (Stroke Genetics Network) Europeans, SiGN Hispanics, and METASTROKE (Europeans). Using a stringent Bonferroni correction P value of 2.08×10-3 (0.05/24 unique loci), we were able to validate associations at the HNF1A locus in both SiGN (P=8.18×10-4) and METASTROKE (P=1.72×10-3) European populations. Overall, 16 of 24 loci showed evidence for validation across multiple populations. Previous studies have reported associations between variants in the HNF1A gene and lipids, C-reactive protein, and risk of coronary artery disease and stroke. Suggestive associations with variants in the SFXN4 and TMEM108 genes represent potential novel ischemic stroke loci.\ These findings represent the most thorough investigation of genetic determinants of stroke in individuals of African descent, to date.

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.

Mendelian randomization analysis does not support causal associations of birth weight with hypertension risk and blood pressure in adulthood. - Zheng, Yan; Huang, Tao; Wang, Tiange; Mei, Zhendong; Sun, Zhonghan; Zhang, Tao; Ellervik, Christina; Chai, Jin-Fang; Sim, Xueling; van Dam, Rob M; Tai, E-Shyong; Koh, Woon-Puay; et al. (Eur J Epidemiol, 2020)
Epidemiology studies suggested that low birthweight was associated with a higher risk of hypertension in later life. However, little is known about the causality of such associations. In our study, we evaluated the causal association of low birthweight with adulthood hypertension following a standard analytic protocol using the study-level data of 183,433 participants from 60 studies (CHARGE-BIG consortium), as well as that with blood pressure using publicly available summary-level genome-wide association data from EGG consortium of 153,781 participants, ICBP consortium and UK Biobank cohort together of 757,601 participants. We used seven SNPs as the instrumental variable in the study-level analysis and 47 SNPs in the summary-level analysis. In the study-level analyses, decreased birthweight was associated with a higher risk of hypertension in adults (the odds ratio per 1 standard deviation (SD) lower birthweight, 1.22; 95% CI 1.16 to 1.28), while no association was found between genetically instrumented birthweight and hypertension risk (instrumental odds ratio for causal effect per 1 SD lower birthweight, 0.97; 95% CI 0.68 to 1.41). Such results were consistent with that from the summary-level analyses, where the genetically determined low birthweight was not associated with blood pressure measurements either. One SD lower genetically determined birthweight was not associated with systolic blood pressure (β = - 0.76, 95% CI - 2.45 to 1.08 mmHg), 0.06 mmHg lower diastolic blood pressure (β = - 0.06, 95% CI - 0.93 to 0.87 mmHg), or pulse pressure (β = - 0.65, 95% CI - 1.38 to 0.69 mmHg, all p > 0.05). Our findings suggest that the inverse association of birthweight with hypertension risk from observational studies was not supported by large Mendelian randomization analyses.

Meta-analysis uncovers genome-wide significant variants for rapid kidney function decline. - Gorski, Mathias; Jung, Bettina; Li, Yong; Matias-Garcia, Pamela R; Wuttke, Matthias; Coassin, Stefan; Thio, Chris H L; Kleber, Marcus E; Winkler, Thomas W; Wanner, Veronika; Chai, Jin-Fang; Chu, Audrey Y; et al. (Kidney Int, 2020)
Rapid decline of glomerular filtration rate estimated from creatinine (eGFRcrea) is associated with severe clinical endpoints. In contrast to cross-sectionally assessed eGFRcrea, the genetic basis for rapid eGFRcrea decline is largely unknown. To help define this, we meta-analyzed 42 genome-wide association studies from the Chronic Kidney Diseases Genetics Consortium and United Kingdom Biobank to identify genetic loci for rapid eGFRcrea decline. Two definitions of eGFRcrea decline were used: 3 mL/min/1.73m/year or more ("Rapid3"; encompassing 34,874 cases, 107,090 controls) and eGFRcrea decline 25% or more and eGFRcrea under 60 mL/min/1.73m at follow-up among those with eGFRcrea 60 mL/min/1.73m or more at baseline ("CKDi25"; encompassing 19,901 cases, 175,244 controls). Seven independent variants were identified across six loci for Rapid3 and/or CKDi25: consisting of five variants at four loci with genome-wide significance (near UMOD-PDILT (2), PRKAG2, WDR72, OR2S2) and two variants among 265 known eGFRcrea variants (near GATM, LARP4B). All these loci were novel for Rapid3 and/or CKDi25 and our bioinformatic follow-up prioritized variants and genes underneath these loci. The OR2S2 locus is novel for any eGFRcrea trait including interesting candidates. For the five genome-wide significant lead variants, we found supporting effects for annual change in blood urea nitrogen or cystatin-based eGFR, but not for GATM or LARP4B. Individuals at high compared to those at low genetic risk (8-14 vs 0-5 adverse alleles) had a 1.20-fold increased risk of acute kidney injury (95% confidence interval 1.08-1.33). Thus, our identified loci for rapid kidney function decline may help prioritize therapeutic targets and identify mechanisms and individuals at risk for sustained deterioration of kidney function.

Multi-ancestry GWAS of the electrocardiographic PR interval identifies 202 loci underlying cardiac conduction. - Ntalla, Ioanna; Weng, Lu-Chen; Cartwright, James H; Hall, Amelia Weber; Sveinbjornsson, Gardar; Tucker, Nathan R; Choi, Seung Hoan; Chaffin, Mark D; Roselli, Carolina; Barnes, Michael R; Mifsud, Borbala; Warren, Helen R; et al. (Nat Commun, 2020)
The electrocardiographic PR interval reflects atrioventricular conduction, and is associated with conduction abnormalities, pacemaker implantation, atrial fibrillation (AF), and cardiovascular mortality. Here we report a multi-ancestry (N = 293,051) genome-wide association meta-analysis for the PR interval, discovering 202 loci of which 141 have not previously been reported. Variants at identified loci increase the percentage of heritability explained, from 33.5% to 62.6%. We observe enrichment for cardiac muscle developmental/contractile and cytoskeletal genes, highlighting key regulation processes for atrioventricular conduction. Additionally, 8 loci not previously reported harbor genes underlying inherited arrhythmic syndromes and/or cardiomyopathies suggesting a role for these genes in cardiovascular pathology in the general population. We show that polygenic predisposition to PR interval duration is an endophenotype for cardiovascular disease, including distal conduction disease, AF, and atrioventricular pre-excitation. These findings advance our understanding of the polygenic basis of cardiac conduction, and the genetic relationship between PR interval duration and cardiovascular disease.

The Polygenic and Monogenic Basis of Blood Traits and Diseases. - Vuckovic, Dragana; Bao, Erik L; Akbari, Parsa; Lareau, Caleb A; Mousas, Abdou; Jiang, Tao; Chen, Ming-Huei; Raffield, Laura M; Tardaguila, Manuel; Huffman, Jennifer E; Ritchie, Scott C; Megy, Karyn; et al. (Cell, 2020)
Blood cells play essential roles in human health, underpinning physiological processes such as immunity, oxygen transport, and clotting, which when perturbed cause a significant global health burden. Here we integrate data from UK Biobank and a large-scale international collaborative effort, including data for 563,085 European ancestry participants, and discover 5,106 new genetic variants independently associated with 29 blood cell phenotypes covering a range of variation impacting hematopoiesis. We holistically characterize the genetic architecture of hematopoiesis, assess the relevance of the omnigenic model to blood cell phenotypes, delineate relevant hematopoietic cell states influenced by regulatory genetic variants and gene networks, identify novel splice-altering variants mediating the associations, and assess the polygenic prediction potential for blood traits and clinical disorders at the interface of complex and Mendelian genetics. These results show the power of large-scale blood cell trait GWAS to interrogate clinically meaningful variants across a wide allelic spectrum of human variation.

Putative Cut-Points in Sarcopenia Components and Incident Adverse Health Outcomes: An SDOC Analysis. - Cawthon, Peggy M; Manini, Todd; Patel, Sheena M; Newman, Anne; Travison, Thomas; Kiel, Douglas P; Santanasto, Adam J; Ensrud, Kristine E; Xue, Qian-Li; Shardell, Michelle; Duchowny, Kate; Erlandson, Kristine M; et al. (J Am Geriatr Soc, 2020)
OBJECTIVES: Analyses performed by the Sarcopenia Definitions and Outcomes Consortium (SDOC) identified cut-points in several metrics of grip strength for consideration in a definition of sarcopenia. We describe the associations between the SDOC-identified metrics of low grip strength (absolute or standardized to body size/composition); low dual-energy x-ray absorptiometry (DXA) lean mass as previously defined in the literature (appendicular lean mass [ALM]/ht ); and slowness (walking speed <.8 m/s) with subsequent adverse outcomes (falls, hip fractures, mobility limitation, and mortality). DESIGN: Individual-level, sex-stratified pooled analysis. We calculated odds ratios (ORs) or hazard ratios (HRs) for incident falls, mobility limitation, hip fractures, and mortality. Follow-up time ranged from 1 year for falls to 8.8 ± 2.3 years for mortality. SETTING: Eight prospective observational cohort studies. PARTICIPANTS: A total of 13,421 community-dwelling men and 4,828 community-dwelling women. MEASUREMENTS Grip strength by hand dynamometry, gait speed, and lean mass by DXA. RESULTS: Low grip strength (absolute or standardized to body size/composition) was associated with incident outcomes, usually independently of slowness, in both men and women. ORs and HRs generally ranged from 1.2 to 3.0 for those below vs above the cut-point. DXA lean mass was not consistently associated with these outcomes. When considered together, those who had both muscle weakness by absolute grip strength (<35.5 kg in men and <20 kg in women) and slowness were consistently more likely to have a fall, hip fracture, mobility limitation, or die than those without either slowness or muscle weakness. CONCLUSION: Older men and women with both muscle weakness and slowness have a higher likelihood of adverse health outcomes. These results support the inclusion of grip strength and walking speed as components in a summary definition of sarcopenia. J Am Geriatr Soc 68:1429-1437, 2020.

Trans-ethnic and Ancestry-Specific Blood-Cell Genetics in 746,667 Individuals from 5 Global Populations. - Chen, Ming-Huei; Raffield, Laura M; Mousas, Abdou; Sakaue, Saori; Huffman, Jennifer E; Moscati, Arden; Trivedi, Bhavi; Jiang, Tao; Akbari, Parsa; Vuckovic, Dragana; Bao, Erik L; Zhong, Xue; et al. (Cell, 2020)
Most loci identified by GWASs have been found in populations of European ancestry (EUR). In trans-ethnic meta-analyses for 15 hematological traits in 746,667 participants, including 184,535 non-EUR individuals, we identified 5,552 trait-variant associations at p < 5 × 10, including 71 novel associations not found in EUR populations. We also identified 28 additional novel variants in ancestry-specific, non-EUR meta-analyses, including an IL7 missense variant in South Asians associated with lymphocyte count in vivo and IL-7 secretion levels in vitro. Fine-mapping prioritized variants annotated as functional and generated 95% credible sets that were 30% smaller when using the trans-ethnic as opposed to the EUR-only results. We explored the clinical significance and predictive value of trans-ethnic variants in multiple populations and compared genetic architecture and the effect of natural selection on these blood phenotypes between populations. Altogether, our results for hematological traits highlight the value of a more global representation of populations in genetic studies.

Whole Blood DNA Methylation Signatures of Diet Are Associated With Cardiovascular Disease Risk Factors and All-Cause Mortality. - Ma, Jiantao; Rebholz, Casey M; Braun, Kim V E; Reynolds, Lindsay M; Aslibekyan, Stella; Xia, Rui; Biligowda, Niranjan G; Huan, Tianxiao; Liu, Chunyu; Mendelson, Michael M; Joehanes, Roby; Hu, Emily A; et al. (Circ Genom Precis Med, 2020)
BACKGROUND: DNA methylation patterns associated with habitual diet have not been well studied. METHODS: Diet quality was characterized using a Mediterranean-style diet score and the Alternative Healthy Eating Index score. We conducted ethnicity-specific and trans-ethnic epigenome-wide association analyses for diet quality and leukocyte-derived DNA methylation at over 400 000 CpGs (cytosine-guanine dinucleotides) in 5 population-based cohorts including 6662 European ancestry, 2702 African ancestry, and 360 Hispanic ancestry participants. For diet-associated CpGs identified in epigenome-wide analyses, we conducted Mendelian randomization (MR) analysis to examine their relations to cardiovascular disease risk factors and examined their longitudinal associations with all-cause mortality. RESULTS: We identified 30 CpGs associated with either Mediterranean-style diet score or Alternative Healthy Eating Index, or both, in European ancestry participants. Among these CpGs, 12 CpGs were significantly associated with all-cause mortality (Bonferroni corrected <1.6×10). Hypermethylation of cg18181703 () was associated with higher scores of both Mediterranean-style diet score and Alternative Healthy Eating Index and lower risk for all-cause mortality (=5.7×10). Ten additional diet-associated CpGs were nominally associated with all-cause mortality (<0.05). MR analysis revealed 8 putatively causal associations for 6 CpGs with 4 cardiovascular disease risk factors (body mass index, triglycerides, high-density lipoprotein cholesterol concentrations, and type 2 diabetes mellitus; Bonferroni corrected MR <4.5×10). For example, hypermethylation of cg11250194 () was associated with lower triglyceride concentrations (MR, =1.5×10).and hypermethylation of cg02079413 (; ) was associated with body mass index (corrected MR, =1×10). CONCLUSIONS: Habitual diet quality was associated with differential peripheral leukocyte DNA methylation levels of 30 CpGs, most of which were also associated with multiple health outcomes, in European ancestry individuals. These findings demonstrate that integrative genomic analysis of dietary information may reveal molecular targets for disease prevention and treatment.

Association Between Intracerebral Hemorrhage and Subsequent Arterial Ischemic Events in Participants From 4 Population-Based Cohort Studies. - Murthy, Santosh B; Zhang, Cenai; Diaz, Ivan; Levitan, Emily B; Koton, Silvia; Bartz, Traci M; DeRosa, Janet T; Strobino, Kevin; Colantonio, Lisandro D; Iadecola, Costantino; Safford, Monika M; Howard, Virginia J; et al. (JAMA Neurol, 2021)
Importance: Intracerebral hemorrhage and arterial ischemic disease share risk factors, to our knowledge, but the association between the 2 conditions remains unknown. Objective: To evaluate whether intracerebral hemorrhage was associated with an increased risk of incident ischemic stroke and myocardial infarction. Design, Setting, and Participants: An analysis was conducted of pooled longitudinal participant-level data from 4 population-based cohort studies in the United States: the Atherosclerosis Risk in Communities (ARIC) study, the Cardiovascular Health Study (CHS), the Northern Manhattan Study (NOMAS), and the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study. Patients were enrolled from 1987 to 2007, and the last available follow-up was December 31, 2018. Data were analyzed from September 1, 2019, to March 31, 2020. Exposure: Intracerebral hemorrhage, as assessed by an adjudication committee based on predefined clinical and radiologic criteria. Main Outcomes and Measures: The primary outcome was an arterial ischemic event, defined as a composite of ischemic stroke or myocardial infarction, centrally adjudicated within each study. Secondary outcomes were ischemic stroke and myocardial infarction. Participants with prevalent intracerebral hemorrhage, ischemic stroke, or myocardial infarction at their baseline study visit were excluded. Cox proportional hazards regression was used to examine the association between intracerebral hemorrhage and subsequent arterial ischemic events after adjustment for baseline age, sex, race/ethnicity, vascular comorbidities, and antithrombotic medications. Results: Of 55 131 participants, 47 866 (27 639 women [57.7%]; mean [SD] age, 62.2 [10.2] years) were eligible for analysis. During a median follow-up of 12.7 years (interquartile range, 7.7-19.5 years), there were 318 intracerebral hemorrhages and 7648 arterial ischemic events. The incidence of an arterial ischemic event was 3.6 events per 100 person-years (95% CI, 2.7-5.0 events per 100 person-years) after intracerebral hemorrhage vs 1.1 events per 100 person-years (95% CI, 1.1-1.2 events per 100 person-years) among those without intracerebral hemorrhage. In adjusted models, intracerebral hemorrhage was associated with arterial ischemic events (hazard ratio [HR], 2.3; 95% CI, 1.7-3.1), ischemic stroke (HR, 3.1; 95% CI, 2.1-4.5), and myocardial infarction (HR, 1.9; 95% CI, 1.2-2.9). In sensitivity analyses, intracerebral hemorrhage was associated with arterial ischemic events when updating covariates in a time-varying manner (HR, 2.2; 95% CI, 1.6-3.0); when using incidence density matching (odds ratio, 2.3; 95% CI, 1.3-4.2); when including participants with prevalent intracerebral hemorrhage, ischemic stroke, or myocardial infarction (HR, 2.2; 95% CI, 1.6-2.9); and when using death as a competing risk (subdistribution HR, 1.6; 95% CI, 1.1-2.1). Conclusions and Relevance: This study found that intracerebral hemorrhage was associated with an increased risk of ischemic stroke and myocardial infarction. These findings suggest that intracerebral hemorrhage may be a novel risk marker for arterial ischemic events.

Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2021)
Measures of information processing speed vary between individuals and decline with age. Studies of aging twins suggest heritability may be as high as 67%. The Illumina HumanExome Bead Chip genotyping array was used to examine the association of rare coding variants with performance on the Digit-Symbol Substitution Test (DSST) in community-dwelling adults participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. DSST scores were available for 30,576 individuals of European ancestry from nine cohorts and for 5758 individuals of African ancestry from four cohorts who were older than 45 years and free of dementia and clinical stroke. Linear regression models adjusted for age and gender were used for analysis of single genetic variants, and the T5, T1, and T01 burden tests that aggregate the number of rare alleles by gene were also applied. Secondary analyses included further adjustment for education. Meta-analyses to combine cohort-specific results were carried out separately for each ancestry group. Variants in RNF19A reached the threshold for statistical significance (p = 2.01 × 10) using the T01 test in individuals of European descent. RNF19A belongs to the class of E3 ubiquitin ligases that confer substrate specificity when proteins are ubiquitinated and targeted for degradation through the 26S proteasome. Variants in SLC22A7 and OR51A7 were suggestively associated with DSST scores after adjustment for education for African-American participants and in the European cohorts, respectively. Further functional characterization of its substrates will be required to confirm the role of RNF19A in cognitive function.
Keywords: Adult; Aging; Cognition; Genome-Wide Association Study; Geroscience; Humans; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Blood n-3 fatty acid levels and total and cause-specific mortality from 17 prospective studies. - Harris, William S; Tintle, Nathan L; Imamura, Fumiaki; Qian, Frank; Korat, Andres V Ardisson; Marklund, Matti; Djoussé, Luc; Bassett, Julie K; Carmichael, Pierre-Hugues; Chen, Yun-Yu; Hirakawa, Yoichiro; Küpers, Leanne K; et al. (Nat Commun, 2021)
The health effects of omega-3 fatty acids have been controversial. Here we report the results of a de novo pooled analysis conducted with data from 17 prospective cohort studies examining the associations between blood omega-3 fatty acid levels and risk for all-cause mortality. Over a median of 16 years of follow-up, 15,720 deaths occurred among 42,466 individuals. We found that, after multivariable adjustment for relevant risk factors, risk for death from all causes was significantly lower (by 15-18%, at least p < 0.003) in the highest vs the lowest quintile for circulating long chain (20-22 carbon) omega-3 fatty acids (eicosapentaenoic, docosapentaenoic, and docosahexaenoic acids). Similar relationships were seen for death from cardiovascular disease, cancer and other causes. No associations were seen with the 18-carbon omega-3, alpha-linolenic acid. These findings suggest that higher circulating levels of marine n-3 PUFA are associated with a lower risk of premature death.
Keywords: Aged; Aged, 80 and over; Cause of Death; Fatty Acids, Omega-3; Female; Follow-Up Studies; Humans; Male; Middle Aged; Mortality, Premature; Prospective Studies; Protective Factors; Risk Factors

Cardiovascular autonomic nervous system function and hip fracture risk: the Cardiovascular Health Study. - Stein, Phyllis K; Bůzková, Petra; Fink, Howard A; Robbins, John A; Mukamal, Kenneth J; Cauley, Jane A; Carbone, Laura; Elam, Rachel; McMillan, David W; Valderrabano, Rodrigo; Barzilay, Joshua I (Arch Osteoporos, 2021)
Among 1299 older adults with 24-h Holter monitoring data at baseline, followed for approximately 15 years, 190 incident hip fractures occurred. Increased heart rate variability was independently associated with reduced risk of hip fracture among female participants. PURPOSE: Autonomic nervous system function modulates bone remodeling in rodent osteoporosis models. We tested whether cardiovascular autonomic function is associated with hip fracture risk in humans. METHODS: Participants were 1299 subjects from the Cardiovascular Health Study (mean age 72.8 years). Eight heart rate variability (HRV) measures (time and frequency domains, detrended fluctuation analysis variables, and heart rate turbulence) were derived from 24-h Holter monitor scans in sinus rhythm. Median follow-up for incident hip fracture was 14.7 years [IQR 9.1, 20.2]. Cox proportional hazards models were used to calculate hazard ratios (95% confidence intervals, CI). RESULTS: There were 144 hip fractures among 714 women (1.31 [1.06, 1.61] per 100-person years) and 46 among 585 men (0.62 [0.43, 0.90] per 100 person-years). From among HRV variables examined, a one standard deviation (SD) higher variation between normal heart beats over 24 h (the SD of NN intervals [SDNN]) was associated with a multivariable-adjusted lower hip fracture risk (HR [Formula: see text] 0.80; 95% CI 0.65-0.99; p = 0.04) in women. The adjusted association between very low frequency power, and hip fracture was borderline statistically significant in women (HR [Formula: see text] 0.82; 95% CI, 0.66-1.00; p = 0.06). When the 8 HRV variables were considered conjointly and adjusted for each other's association with hip fracture risk, a 1 SD higher SDNN value was significantly associated with reduced hip fracture risk in women (HR 0.74; 95% CI, 0.50-0.99; p = 0.05). No HRV variables were associated with hip fracture in men. CONCLUSIONS: In older women, increased heart rate variation is associated with hip fracture risk.
Keywords: Aged; Autonomic Nervous System; Female; Heart Rate; Hip Fractures; Humans; Osteoporosis; Proportional Hazards Models

Chromosome Xq23 is associated with lower atherogenic lipid concentrations and favorable cardiometabolic indices. - Natarajan, Pradeep; Pampana, Akhil; Graham, Sarah E; Ruotsalainen, Sanni E; Perry, James A; de Vries, Paul S; Broome, Jai G; Pirruccello, James P; Honigberg, Michael C; Aragam, Krishna; Wolford, Brooke; Brody, Jennifer A; et al. (Nat Commun, 2021)
Autosomal genetic analyses of blood lipids have yielded key insights for coronary heart disease (CHD). However, X chromosome genetic variation is understudied for blood lipids in large sample sizes. We now analyze genetic and blood lipid data in a high-coverage whole X chromosome sequencing study of 65,322 multi-ancestry participants and perform replication among 456,893 European participants. Common alleles on chromosome Xq23 are strongly associated with reduced total cholesterol, LDL cholesterol, and triglycerides (min P = 8.5 × 10), with similar effects for males and females. Chromosome Xq23 lipid-lowering alleles are associated with reduced odds for CHD among 42,545 cases and 591,247 controls (P = 1.7 × 10), and reduced odds for diabetes mellitus type 2 among 54,095 cases and 573,885 controls (P = 1.4 × 10). Although we observe an association with increased BMI, waist-to-hip ratio adjusted for BMI is reduced, bioimpedance analyses indicate increased gluteofemoral fat, and abdominal MRI analyses indicate reduced visceral adiposity. Co-localization analyses strongly correlate increased CHRDL1 gene expression, particularly in adipose tissue, with reduced concentrations of blood lipids.

Cognitive decline in older adults with epilepsy: The Cardiovascular Health Study. - Choi, Hyunmi; Thacker, Evan L; Longstreth, William T; Elkind, Mitchell S V; Boehme, Amelia K (Epilepsia, 2021)
OBJECTIVE: Cognitive decline is a major concern for older adults with epilepsy. Whether and how much faster older adults with epilepsy experience cognitive decline beyond expected age-related cognitive change remain unclear. We sought to estimate and compare rates of cognitive decline in older adults with and without epilepsy. METHODS: The Cardiovascular Health Study is a population-based longitudinal cohort study of 5888 US adults aged 65+. Cognitive function was assessed annually with Modified Mini-Mental State Exam (3MS) and Digit Symbol Substitution Test (DSST). We used linear mixed models to estimate average rates of decline in 3MS and DSST scores by epilepsy status (prevalent, incident, or no epilepsy), adjusted for risk factors associated with cognitive decline. RESULTS: The rate of decline in 3MS was significantly faster in prevalent epilepsy (P < .001) and after incident epilepsy (P = .002) compared with no epilepsy. Prevalent epilepsy and apolipoprotein E gene (APOE) ε4 (ApoE4) had a synergistic interaction, whereby prevalent epilepsy and ApoE4 together were associated with 1.51 points faster annual decline in 3MS than would be expected if prevalent epilepsy and ApoE4 did not interact (P < .001). Older adults with prevalent epilepsy had a significantly lower initial DSST score and faster rate of decline compared to those with no epilepsy (P < .001). SIGNIFICANCE: Faster decline in global cognitive ability seen in this study validates concerns of patients. ApoE4 allele status was an effect modifier of the relationship between cognitive decline and prevalent epilepsy. Further research is warranted to explore biological mechanisms and possible interventions to mitigate cognitive decline.

Determinants of penetrance and variable expressivity in monogenic metabolic conditions across 77,184 exomes. - Goodrich, Julia K; Singer-Berk, Moriel; Son, Rachel; Sveden, Abigail; Wood, Jordan; England, Eleina; Cole, Joanne B; Weisburd, Ben; Watts, Nick; Caulkins, Lizz; Dornbos, Peter; Koesterer, Ryan; et al. (Nat Commun, 2021)
Hundreds of thousands of genetic variants have been reported to cause severe monogenic diseases, but the probability that a variant carrier develops the disease (termed penetrance) is unknown for virtually all of them. Additionally, the clinical utility of common polygenetic variation remains uncertain. Using exome sequencing from 77,184 adult individuals (38,618 multi-ancestral individuals from a type 2 diabetes case-control study and 38,566 participants from the UK Biobank, for whom genotype array data were also available), we apply clinical standard-of-care gene variant curation for eight monogenic metabolic conditions. Rare variants causing monogenic diabetes and dyslipidemias display effect sizes significantly larger than the top 1% of the corresponding polygenic scores. Nevertheless, penetrance estimates for monogenic variant carriers average 60% or lower for most conditions. We assess epidemiologic and genetic factors contributing to risk prediction in monogenic variant carriers, demonstrating that inclusion of polygenic variation significantly improves biomarker estimation for two monogenic dyslipidemias.
Keywords: Adult; Biological Variation, Population; Biomarkers; Diabetes Mellitus, Type 2; Dyslipidemias; Exome; Genetic Predisposition to Disease; Genotype; Humans; Multifactorial Inheritance; Penetrance; Risk Assessment

Discovery and fine-mapping of height loci via high-density imputation of GWASs in individuals of African ancestry. - Graff, Mariaelisa; Justice, Anne E; Young, Kristin L; Marouli, Eirini; Zhang, Xinruo; Fine, Rebecca S; Lim, Elise; Buchanan, Victoria; Rand, Kristin; Feitosa, Mary F; Wojczynski, Mary K; Yanek, Lisa R; et al. (Am J Hum Genet, 2021)
Although many loci have been associated with height in European ancestry populations, very few have been identified in African ancestry individuals. Furthermore, many of the known loci have yet to be generalized to and fine-mapped within a large-scale African ancestry sample. We performed sex-combined and sex-stratified meta-analyses in up to 52,764 individuals with height and genome-wide genotyping data from the African Ancestry Anthropometry Genetics Consortium (AAAGC). We additionally combined our African ancestry meta-analysis results with published European genome-wide association study (GWAS) data. In the African ancestry analyses, we identified three novel loci (SLC4A3, NCOA2, ECD/FAM149B1) in sex-combined results and two loci (CRB1, KLF6) in women only. In the African plus European sex-combined GWAS, we identified an additional three novel loci (RCCD1, G6PC3, CEP95) which were equally driven by AAAGC and European results. Among 39 genome-wide significant signals at known loci, conditioning index SNPs from European studies identified 20 secondary signals. Two of the 20 new secondary signals and none of the 8 novel loci had minor allele frequencies (MAF) < 5%. Of 802 known European height signals, 643 displayed directionally consistent associations with height, of which 205 were nominally significant (p < 0.05) in the African ancestry sex-combined sample. Furthermore, 148 of 241 loci contained ≤20 variants in the credible sets that jointly account for 99% of the posterior probability of driving the associations. In summary, trans-ethnic meta-analyses revealed novel signals and further improved fine-mapping of putative causal variants in loci shared between African and European ancestry populations.

Epigenetic Age and the Risk of Incident Atrial Fibrillation. - Roberts, Jason D; Vittinghoff, Eric; Lu, Ake T; Alonso, Alvaro; Wang, Biqi; Sitlani, Colleen M; Mohammadi-Shemirani, Pedrum; Fornage, Myriam; Kornej, Jelena; Brody, Jennifer A; Arking, Dan E; Lin, Honghuang; et al. (Circulation, 2021)
BACKGROUND: The most prominent risk factor for atrial fibrillation (AF) is chronological age; however, underlying mechanisms are unexplained. Algorithms using epigenetic modifications to the human genome effectively predict chronological age. Chronological and epigenetic predicted ages may diverge in a phenomenon referred to as epigenetic age acceleration (EAA), which may reflect accelerated biological aging. We sought to evaluate for associations between epigenetic age measures and incident AF. METHODS: Measures for 4 epigenetic clocks (Horvath, Hannum, DNA methylation [DNAm] PhenoAge, and DNAm GrimAge) and an epigenetic predictor of PAI-1 (plasminogen activator inhibitor-1) levels (ie, DNAm PAI-1) were determined for study participants from 3 population-based cohort studies. Cox models evaluated for associations with incident AF and results were combined via random-effects meta-analyses. Two-sample summary-level Mendelian randomization analyses evaluated for associations between genetic instruments of the EAA measures and AF. RESULTS: Among 5600 participants (mean age, 65.5 years; female, 60.1%; Black, 50.7%), there were 905 incident AF cases during a mean follow-up of 12.9 years. Unadjusted analyses revealed all 4 epigenetic clocks and the DNAm PAI-1 predictor were associated with statistically significant higher hazards of incident AF, though the magnitudes of their point estimates were smaller relative to the associations observed for chronological age. The pooled EAA estimates for each epigenetic measure, with the exception of Horvath EAA, were associated with incident AF in models adjusted for chronological age, race, sex, and smoking variables. After multivariable adjustment for additional known AF risk factors that could also potentially function as mediators, pooled EAA measures for 2 clocks remained statistically significant. Five-year increases in EAA measures for DNAm GrimAge and DNAm PhenoAge were associated with 19% (adjusted hazard ratio [HR], 1.19 [95% CI, 1.09-1.31]; <0.01) and 15% (adjusted HR, 1.15 [95% CI, 1.05-1.25]; <0.01) higher hazards of incident AF, respectively. Mendelian randomization analyses for the 5 EAA measures did not reveal statistically significant associations with AF. CONCLUSIONS: Our study identified adjusted associations between EAA measures and incident AF, suggesting that biological aging plays an important role independent of chronological age, though a potential underlying causal relationship remains unclear. These aging processes may be modifiable and not constrained by the immutable factor of time.
Keywords: Aged; Aging; Atrial Fibrillation; DNA Methylation; Epigenesis, Genetic; Epigenomics; Female; Follow-Up Studies; Humans; Incidence; Male; Mendelian Randomization Analysis; Middle Aged; Models, Cardiovascular; Models, Genetic

{Epigenome-wide association meta-analysis of DNA methylation with coffee and tea consumption - Karabegović, I.; Portilla-Fernandez, E.; Li, Y.; Ma, J.; Maas, S. C. E.; Sun, D.; Hu, E. A.; Kühnel, B.; Zhang, Y.; Ambatipudi, S.; Fiorito, G.; Huang, J.; et al. (Nat Commun, 2021)
10.1038/s41467-021-22752-6Coffee and tea are extensively consumed beverages worldwide which have received considerable attention regarding health. Intake of these beverages is consistently linked to, among others, reduced risk of diabetes and liver diseases; however, the mechanisms of action remain elusive. Epigenetics is suggested as a mechanism mediating the effects of dietary and lifestyle factors on disease onset. Here we report the results from epigenome-wide association studies (EWAS) on coffee and tea consumption in 15,789 participants of European and African-American ancestries from 15 cohorts. EWAS meta-analysis of coffee consumption reveals 11 CpGs surpassing the epigenome-wide significance threshold (P-value <1.1×10-7), which annotated to the AHRR, F2RL3, FLJ43663, HDAC4, GFI1 and PHGDH genes. Among them, cg14476101 is significantly associated with expression of the PHGDH and risk of fatty liver disease. Knockdown of PHGDH expression in liver cells shows a correlation with expression levels of genes associated with circulating lipids, suggesting a role of PHGDH in hepatic-lipid metabolism. EWAS meta-analysis on tea consumption reveals no significant association, only two CpGs annotated to CACNA1A and PRDM16 genes show suggestive association (P-value <5.0×10-6). These findings indicate that coffee-associated changes in DNA methylation levels may explain the mechanism of action of coffee consumption in conferring risk of diseases.

Epigenome-wide association study of serum urate reveals insights into urate co-regulation and the SLC2A9 locus. - Tin, Adrienne; Schlosser, Pascal; Matias-Garcia, Pamela R; Thio, Chris H L; Joehanes, Roby; Liu, Hongbo; Yu, Zhi; Weihs, Antoine; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L; Kuhns, Victoria L Halperin; et al. (Nat Commun, 2021)
Elevated serum urate levels, a complex trait and major risk factor for incident gout, are correlated with cardiometabolic traits via incompletely understood mechanisms. DNA methylation in whole blood captures genetic and environmental influences and is assessed in transethnic meta-analysis of epigenome-wide association studies (EWAS) of serum urate (discovery, n = 12,474, replication, n = 5522). The 100 replicated, epigenome-wide significant (p < 1.1E-7) CpGs explain 11.6% of the serum urate variance. At SLC2A9, the serum urate locus with the largest effect in genome-wide association studies (GWAS), five CpGs are associated with SLC2A9 gene expression. Four CpGs at SLC2A9 have significant causal effects on serum urate levels and/or gout, and two of these partly mediate the effects of urate-associated GWAS variants. In other genes, including SLC7A11 and PHGDH, 17 urate-associated CpGs are associated with conditions defining metabolic syndrome, suggesting that these CpGs may represent a blood DNA methylation signature of cardiometabolic risk factors. This study demonstrates that EWAS can provide new insights into GWAS loci and the correlation of serum urate with other complex traits.
Keywords: Amino Acid Transport System y+; Cohort Studies; CpG Islands; DNA Methylation; Epigenome; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Transport Proteins, Facilitative; Gout; Humans; Male; Uric Acid

Genetic insights into biological mechanisms governing human ovarian ageing. - Ruth, Katherine S; Day, Felix R; Hussain, Jazib; Martínez-Marchal, Ana; Aiken, Catherine E; Azad, Ajuna; Thompson, Deborah J; Knoblochova, Lucie; Abe, Hironori; Tarry-Adkins, Jane L; Gonzalez, Javier Martin; Fontanillas, Pierre; et al. (Nature, 2021)
Reproductive longevity is essential for fertility and influences healthy ageing in women, but insights into its underlying biological mechanisms and treatments to preserve it are limited. Here we identify 290 genetic determinants of ovarian ageing, assessed using normal variation in age at natural menopause (ANM) in about 200,000 women of European ancestry. These common alleles were associated with clinical extremes of ANM; women in the top 1% of genetic susceptibility have an equivalent risk of premature ovarian insufficiency to those carrying monogenic FMR1 premutations. The identified loci implicate a broad range of DNA damage response (DDR) processes and include loss-of-function variants in key DDR-associated genes. Integration with experimental models demonstrates that these DDR processes act across the life-course to shape the ovarian reserve and its rate of depletion. Furthermore, we demonstrate that experimental manipulation of DDR pathways highlighted by human genetics increases fertility and extends reproductive life in mice. Causal inference analyses using the identified genetic variants indicate that extending reproductive life in women improves bone health and reduces risk of type 2 diabetes, but increases the risk of hormone-sensitive cancers. These findings provide insight into the mechanisms that govern ovarian ageing, when they act, and how they might be targeted by therapeutic approaches to extend fertility and prevent disease.

{Genome-Wide Association Study of Circulating Interleukin 6 Levels Identifies Novel Loci - Ahluwalia, T. S.; Prins, B. P.; Abdollahi, M.; Armstrong, N. J.; Aslibekyan, S.; Bain, L.; Jefferis, B.; Baumert, J.; Beekman, M.; Ben-Shlomo, Y.; Bis, J. C.; Mitchell, B. D.; et al. (Hum Mol Genet, 2021)
Interleukin-6 (IL-6) is a multifunctional cytokine with both pro- and anti-inflammatory properties with a heritability estimate of up to 61%. The circulating levels of IL-6 in blood have been associated with an increased risk of complex disease pathogenesis. We conducted a two-staged, discovery, and replication meta genome-wide association study (GWAS) of circulating serum IL-6 levels comprising up to 67 428 (ndiscovery = 52 654 and nreplication = 14 774) individuals of European ancestry. The inverse variance fixed-effects based discovery meta-analysis, followed by replication led to the identification of two independent loci, IL1F10/IL1RN rs6734238 on Chromosome (Chr) 2q14, (pcombined = 1.8 × 10-11), HLA-DRB1/DRB5 rs660895 on Chr6p21 (pcombined = 1.5 × 10-10) in the combined meta-analyses of all samples. We also replicated the IL6R rs4537545 locus on Chr1q21 (pcombined = 1.2 × 10-122). Our study identifies novel loci for circulating IL-6 levels uncovering new immunological and inflammatory pathways that may influence IL-6 pathobiology.

{The genomics of heart failure: design and rationale of the HERMES consortium - Lumbers, R. T.; Shah, S.; Lin, H.; Czuba, T.; Henry, A.; Swerdlow, D. I.; Malarstig, A.; Andersson, C.; Verweij, N.; Holmes, M. V.; Ärnlöv, J.; Svensson, P.; et al. (ESC Heart Fail, 2021)
The HERMES (HEart failure Molecular Epidemiology for Therapeutic targetS) consortium aims to identify the genomic and molecular basis of heart failure.\ under an additive genetic model.\ HERMES is a global collaboration aiming to (i) identify the genetic determinants of heart failure; (ii) generate insights into the causal pathways leading to heart failure and enable genetic approaches to target prioritization; and (iii) develop genomic tools for disease stratification and risk prediction.

Hemostatic factor levels and cognitive decline in older adults: The Cardiovascular Health Study. - Harrington, Laura B; Ehlert, Alexa N; Thacker, Evan L; Jenny, Nancy S; Lopez, Oscar; Cushman, Mary; Fitzpatrick, Annette; Mukamal, Kenneth J; Jensen, Majken K (J Thromb Haemost, 2021)
BACKGROUND: Hemostasis is a key factor in cerebrovascular disease, but the association of hemostatic factors with cognitive decline is unclear. OBJECTIVE: To prospectively evaluate associations of 20 hemostatic factor levels with changes in cognition during ≥8 years of follow-up in the Cardiovascular Health Study (CHS) of older adults. METHODS: We included participants of an existing CHS cross-sectional substudy (n = 400) with hemostatic factors measured in 1989-1990. Between 1989-1990 and 1998-1999, cognitive function was measured using the Modified Mini-Mental State Examination (3MSE) and Digit Symbol Substitution Tests. Mixed-effects linear regression models estimated change in cognitive function over time, adjusting for sociodemographic and clinical factors and APOE genotype, using Bonferroni adjustment. We also derived principal components to account for the interrelationship among factors. RESULTS: Of 20 factors evaluated individually, only higher levels of plasmin-α -antiplasmin complex (PAP), tissue factor pathway inhibitor (TFPI), and lower factor X (FXc) levels were associated with faster cognitive decline, estimated by annual change in 3MSE points (1 standard deviation PAP β = -0.65, 95% confidence interval [CI]: -1.08 to -0.21; TFPI β = -0.55, 95% CI: -0.90 to -0.19; FXc β = 0.52, 95% CI: 0.21-0.84). One of four principal components, loading positively on D-dimer, prothrombin fragment 1.2 (F1.2), and PAP was significantly associated with change in 3MSE. CONCLUSIONS: Levels of PAP, TPFI, and FXc and a combination of factors driven by PAP, D-dimer, and F1.2 were associated with cognitive decline. Whether these findings can be used to improve dementia prevention or prediction requires further study.

Meta-analyses identify DNA methylation associated with kidney function and damage. - Schlosser, Pascal; Tin, Adrienne; Matias-Garcia, Pamela R; Thio, Chris H L; Joehanes, Roby; Liu, Hongbo; Weihs, Antoine; Yu, Zhi; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L; Adeyemo, Adebowale A; et al. (Nat Commun, 2021)
Chronic kidney disease is a major public health burden. Elevated urinary albumin-to-creatinine ratio is a measure of kidney damage, and used to diagnose and stage chronic kidney disease. To extend the knowledge on regulatory mechanisms related to kidney function and disease, we conducted a blood-based epigenome-wide association study for estimated glomerular filtration rate (n = 33,605) and urinary albumin-to-creatinine ratio (n = 15,068) and detected 69 and seven CpG sites where DNA methylation was associated with the respective trait. The majority of these findings showed directionally consistent associations with the respective clinical outcomes chronic kidney disease and moderately increased albuminuria. Associations of DNA methylation with kidney function, such as CpGs at JAZF1, PELI1 and CHD2 were validated in kidney tissue. Methylation at PHRF1, LDB2, CSRNP1 and IRF5 indicated causal effects on kidney function. Enrichment analyses revealed pathways related to hemostasis and blood cell migration for estimated glomerular filtration rate, and immune cell activation and response for urinary albumin-to-creatinineratio-associated CpGs.
Keywords: Adult; Aged; CpG Islands; DNA Methylation; Female; Glomerular Filtration Rate; Humans; Interferon Regulatory Factors; Kidney; Kidney Function Tests; LIM Domain Proteins; Male; Membrane Proteins; Middle Aged; Renal Insufficiency, Chronic; Transcription Factors

Multi-Ancestry Genome-wide Association Study Accounting for Gene-Psychosocial Factor Interactions Identifies Novel Loci for Blood Pressure Traits. - Sun, Daokun; Richard, Melissa; Musani, Solomon K; Sung, Yun Ju; Winkler, Thomas W; Schwander, Karen; Chai, Jin Fang; Guo, Xiuqing; Kilpeläinen, Tuomas O; Vojinovic, Dina; Aschard, Hugues; Bartz, Traci M; et al. (HGG Adv, 2021)
Psychological and social factors are known to influence blood pressure (BP) and risk of hypertension and associated cardiovascular diseases. To identify novel BP loci, we carried out genome-wide association meta-analyses of systolic, diastolic, pulse, and mean arterial BP taking into account the interaction effects of genetic variants with three psychosocial factors: depressive symptoms, anxiety symptoms, and social support. Analyses were performed using a two-stage design in a sample of up to 128,894 adults from 5 ancestry groups. In the combined meta-analyses of Stages 1 and 2, we identified 59 loci (p value <5e-8), including nine novel BP loci. The novel associations were observed mostly with pulse pressure, with fewer observed with mean arterial pressure. Five novel loci were identified in African ancestry, and all but one showed patterns of interaction with at least one psychosocial factor. Functional annotation of the novel loci supports a major role for genes implicated in the immune response (), synaptic function and neurotransmission (), as well as genes previously implicated in neuropsychiatric or stress-related disorders (). These findings underscore the importance of considering psychological and social factors in gene discovery for BP, especially in non-European populations.

Multi-ancestry genome-wide gene-sleep interactions identify novel loci for blood pressure. - Wang, Heming; Noordam, Raymond; Cade, Brian E; Schwander, Karen; Winkler, Thomas W; Lee, Jiwon; Sung, Yun Ju; Bentley, Amy R; Manning, Alisa K; Aschard, Hugues; Kilpeläinen, Tuomas O; Ilkov, Marjan; et al. (Mol Psychiatry, 2021)
Long and short sleep duration are associated with elevated blood pressure (BP), possibly through effects on molecular pathways that influence neuroendocrine and vascular systems. To gain new insights into the genetic basis of sleep-related BP variation, we performed genome-wide gene by short or long sleep duration interaction analyses on four BP traits (systolic BP, diastolic BP, mean arterial pressure, and pulse pressure) across five ancestry groups in two stages using 2 degree of freedom (df) joint test followed by 1df test of interaction effects. Primary multi-ancestry analysis in 62,969 individuals in stage 1 identified three novel gene by sleep interactions that were replicated in an additional 59,296 individuals in stage 2 (stage 1 + 2 P < 5 × 10), including rs7955964 (FIGNL2/ANKRD33) that increases BP among long sleepers, and rs73493041 (SNORA26/C9orf170) and rs10406644 (KCTD15/LSM14A) that increase BP among short sleepers (P < 5 × 10). Secondary ancestry-specific analysis identified another novel gene by long sleep interaction at rs111887471 (TRPC3/KIAA1109) in individuals of African ancestry (P = 2 × 10). Combined stage 1 and 2 analyses additionally identified significant gene by long sleep interactions at 10 loci including MKLN1 and RGL3/ELAVL3 previously associated with BP, and significant gene by short sleep interactions at 10 loci including C2orf43 previously associated with BP (P < 10). 2df test also identified novel loci for BP after modeling sleep that has known functions in sleep-wake regulation, nervous and cardiometabolic systems. This study indicates that sleep and primary mechanisms regulating BP may interact to elevate BP level, suggesting novel insights into sleep-related BP regulation.

is mutated in clonal hematopoiesis and myelodysplastic syndromes and impacts RNA splicing. - Beauchamp, Ellen M; Leventhal, Matthew; Bernard, Elsa; Hoppe, Emma R; Todisco, Gabriele; Creignou, Maria; Gallì, Anna; Castellano, Cecilia A; McConkey, Marie; Tarun, Akansha; Wong, Waihay; Schenone, Monica; et al. (Blood Cancer Discov, 2021)
Clonal hematopoiesis results from somatic mutations in cancer driver genes in hematopoietic stem cells. We sought to identify novel drivers of clonal expansion using an unbiased analysis of sequencing data from 84,683 persons and identified common mutations in the 5-methylcytosine reader, , as well as in , , and . We also identified these mutations at low frequency in myelodysplastic syndrome patients. edited mouse hematopoietic stem and progenitor cells exhibited a competitive advantage and increased genome-wide intron retention. mutations potentially link DNA methylation and RNA splicing, the two most commonly mutated pathways in clonal hematopoiesis and MDS.

{The power of genetic diversity in genome-wide association studies of lipids - Graham, S. E.; Clarke, S. L.; Wu, K. H.; Kanoni, S.; Zajac, G. J. M.; Ramdas, S.; Surakka, I.; Ntalla, I.; Vedantam, S.; Winkler, T. W.; Locke, A. E.; Marouli, E.; et al. (Nature, 2021)
application of polygenic scores in clinical practice.

Pre-Statistical Considerations for Harmonization of Cognitive Instruments: Harmonization of ARIC, CARDIA, CHS, FHS, MESA, and NOMAS. - Briceño, Emily M; Gross, Alden L; Giordani, Bruno J; Manly, Jennifer J; Gottesman, Rebecca F; Elkind, Mitchell S V; Sidney, Stephen; Hingtgen, Stephanie; Sacco, Ralph L; Wright, Clinton B; Fitzpatrick, Annette; Fohner, Alison E; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Meta-analyses of individuals' cognitive data are increasing to investigate the biomedical, lifestyle, and sociocultural factors that influence cognitive decline and dementia risk. Pre-statistical harmonization of cognitive instruments is a critical methodological step for accurate cognitive data harmonization, yet specific approaches for this process are unclear. OBJECTIVE: To describe pre-statistical harmonization of cognitive instruments for an individual-level meta-analysis in the blood pressure and cognition (BP COG) study. METHODS: We identified cognitive instruments from six cohorts (the Atherosclerosis Risk in Communities Study, Cardiovascular Health Study, Coronary Artery Risk Development in Young Adults study, Framingham Offspring Study, Multi-Ethnic Study of Atherosclerosis, and Northern Manhattan Study) and conducted an extensive review of each item's administration and scoring procedures, and score distributions. RESULTS: We included 153 cognitive instrument items from 34 instruments across the six cohorts. Of these items, 42%were common across ≥2 cohorts. 86%of common items showed differences across cohorts. We found administration, scoring, and coding differences for seemingly equivalent items. These differences corresponded to variability across cohorts in score distributions and ranges. We performed data augmentation to adjust for differences. CONCLUSION: Cross-cohort administration, scoring, and procedural differences for cognitive instruments are frequent and need to be assessed to address potential impact on meta-analyses and cognitive data interpretation. Detecting and accounting for these differences is critical for accurate attributions of cognitive health across cohort studies.

{Rare and low-frequency exonic variants and gene-by-smoking interactions in pulmonary function - Yang, T.; Jackson, V. E.; Smith, A. V.; Chen, H.; Bartz, T. M.; Sitlani, C. M.; Psaty, B. M.; Gharib, S. A.; O'Connor, G. T.; Dupuis, J.; Xu, J.; Lohman, K.; et al. (Sci Rep, 2021)
. This study investigates the utility of assessing gene-by-smoking interactions and underscores their effects on potential pulmonary function.

{Rare Coding Variants Associated With Electrocardiographic Intervals Identify Monogenic Arrhythmia Susceptibility Genes: A Multi-Ancestry Analysis - Choi, S. H.; Jurgens, S. J.; Haggerty, C. M.; Hall, A. W.; Halford, J. L.; Morrill, V. N.; Weng, L. C.; Lagerman, B.; Mirshahi, T.; Pettinger, M.; Guo, X.; Lin, H. J.; et al. (Circ Genom Precis Med, 2021)
Alterations in electrocardiographic (ECG) intervals are well-known markers for arrhythmia and sudden cardiac death (SCD) risk. While the genetics of arrhythmia syndromes have been studied, relations between electrocardiographic intervals and rare genetic variation at a population level are poorly understood.\ Using a discovery sample of 29 000 individuals with whole-genome sequencing from Trans-Omics in Precision Medicine and replication in nearly 100 000 with whole-exome sequencing from the UK Biobank and MyCode, we examined associations between low-frequency and rare coding variants with 5 routinely measured electrocardiographic traits (RR, P-wave, PR, and QRS intervals and corrected QT interval).\ ), a marker of SCD risk. Incomplete penetrance of such deleterious variation was common as over 70% of carriers had normal electrocardiographic intervals.\ Our findings indicate that large-scale high-depth sequence data and electrocardiographic analysis identifies monogenic arrhythmia susceptibility genes and rare variants with large effects. Known pathogenic variation in conventional arrhythmia and SCD genes exhibited incomplete penetrance and accounted for only a small fraction of marked electrocardiographic interval prolongation.

Sequencing of 53,831 diverse genomes from the NHLBI TOPMed Program. - Taliun, Daniel; Harris, Daniel N; Kessler, Michael D; Carlson, Jedidiah; Szpiech, Zachary A; Torres, Raul; Taliun, Sarah A Gagliano; Corvelo, André; Gogarten, Stephanie M; Kang, Hyun Min; Pitsillides, Achilleas N; LeFaive, Jonathon; et al. (Nature, 2021)
The Trans-Omics for Precision Medicine (TOPMed) programme seeks to elucidate the genetic architecture and biology of heart, lung, blood and sleep disorders, with the ultimate goal of improving diagnosis, treatment and prevention of these diseases. The initial phases of the programme focused on whole-genome sequencing of individuals with rich phenotypic data and diverse backgrounds. Here we describe the TOPMed goals and design as well as the available resources and early insights obtained from the sequence data. The resources include a variant browser, a genotype imputation server, and genomic and phenotypic data that are available through dbGaP (Database of Genotypes and Phenotypes). In the first 53,831 TOPMed samples, we detected more than 400 million single-nucleotide and insertion or deletion variants after alignment with the reference genome. Additional previously undescribed variants were detected through assembly of unmapped reads and customized analysis in highly variable loci. Among the more than 400 million detected variants, 97% have frequencies of less than 1% and 46% are singletons that are present in only one individual (53% among unrelated individuals). These rare variants provide insights into mutational processes and recent human evolutionary history. The extensive catalogue of genetic variation in TOPMed studies provides unique opportunities for exploring the contributions of rare and noncoding sequence variants to phenotypic variation. Furthermore, combining TOPMed haplotypes with modern imputation methods improves the power and reach of genome-wide association studies to include variants down to a frequency of approximately 0.01%.

Sex Differences in Cognitive Decline Among US Adults. - Levine, Deborah A; Gross, Alden L; Briceño, Emily M; Tilton, Nicholas; Giordani, Bruno J; Sussman, Jeremy B; Hayward, Rodney A; Burke, James F; Hingtgen, Stephanie; Elkind, Mitchell S V; Manly, Jennifer J; Gottesman, Rebecca F; et al. (JAMA Netw Open, 2021)
Importance: Sex differences in dementia risk are unclear, but some studies have found greater risk for women. Objective: To determine associations between sex and cognitive decline in order to better understand sex differences in dementia risk. Design, Setting, and Participants: This cohort study used pooled analysis of individual participant data from 5 cohort studies for years 1971 to 2017: Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, and Northern Manhattan Study. Linear mixed-effects models were used to estimate changes in each continuous cognitive outcome over time by sex. Data analysis was completed from March 2019 to October 2020. Exposure: Sex. Main Outcomes and Measures: The primary outcome was change in global cognition. Secondary outcomes were change in memory and executive function. Outcomes were standardized as t scores (mean [SD], 50 [10]); a 1-point difference represents a 0.1-SD difference in cognition. Results: Among 34 349 participants, 26 088 who self-reported Black or White race, were free of stroke and dementia, and had covariate data at or before the first cognitive assessment were included for analysis. Median (interquartile range) follow-up was 7.9 (5.3-20.5) years. There were 11 775 (44.7%) men (median [interquartile range] age, 58 [51-66] years at first cognitive assessment; 2229 [18.9%] Black) and 14 313 women (median [interquartile range] age, 58 [51-67] years at first cognitive assessment; 3636 [25.4%] Black). Women had significantly higher baseline performance than men in global cognition (2.20 points higher; 95% CI, 2.04 to 2.35 points; P < .001), executive function (2.13 points higher; 95% CI, 1.98 to 2.29 points; P < .001), and memory (1.89 points higher; 95% CI, 1.72 to 2.06 points; P < .001). Compared with men, women had significantly faster declines in global cognition (-0.07 points/y faster; 95% CI, -0.08 to -0.05 points/y; P < .001) and executive function (-0.06 points/y faster; 95% CI, -0.07 to -0.05 points/y; P < .001). Men and women had similar declines in memory (-0.004 points/y faster; 95% CI, -0.023 to 0.014; P = .61). Conclusions and Relevance: The results of this cohort study suggest that women may have greater cognitive reserve but faster cognitive decline than men, which could contribute to sex differences in late-life dementia.
Keywords: Aged; Cognitive Dysfunction; Cognitive Reserve; Cohort Studies; Executive Function; Humans; Memory; Middle Aged; Risk; Sex Factors; Time Factors; United States

{Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Lagou, V.; Mägi, R.; Hottenga, J. J.; Grallert, H.; Perry, J. R. B.; Bouatia-Naji, N.; Marullo, L.; Rybin, D.; Jansen, R.; Min, J. L.; Dimas, A. S.; Ulrich, A.; et al. (Nat Commun, 2021)
Differences between sexes contribute to variation in the levels of fasting glucose and insulin. Epidemiological studies established a higher prevalence of impaired fasting glucose in men and impaired glucose tolerance in women, however, the genetic component underlying this phenomenon is not established. We assess sex-dimorphic (73,089/50,404 women and 67,506/47,806 men) and sex-combined (151,188/105,056 individuals) fasting glucose/fasting insulin genetic effects via genome-wide association study meta-analyses in individuals of European descent without diabetes. Here we report sex dimorphism in allelic effects on fasting insulin at IRS1 and ZNF12 loci, the latter showing higher RNA expression in whole blood in women compared to men. We also observe sex-homogeneous effects on fasting glucose at seven novel loci. Fasting insulin in women shows stronger genetic correlations than in men with waist-to-hip ratio and anorexia nervosa. Furthermore, waist-to-hip ratio is causally related to insulin resistance in women, but not in men. These results position dissection of metabolic and glycemic health sex dimorphism as a steppingstone for understanding differences in genetic effects between women and men in related phenotypes.

{Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Lagou, V.; M?gi, R.; Hottenga, J. J.; Grallert, H.; Perry, J. R. B.; Bouatia-Naji, N.; Marullo, L.; Rybin, D.; Jansen, R.; Min, J. L.; Dimas, A. S.; Ulrich, A.; et al. (Nat Commun, 2021)
Differences between sexes contribute to variation in the levels of fasting glucose and insulin. Epidemiological studies established a higher prevalence of impaired fasting glucose in men and impaired glucose tolerance in women, however, the genetic component underlying this phenomenon is not established. We assess sex-dimorphic (73,089/50,404 women and 67,506/47,806 men) and sex-combined (151,188/105,056 individuals) fasting glucose/fasting insulin genetic effects via genome-wide association study meta-analyses in individuals of European descent without diabetes. Here we report sex dimorphism in allelic effects on fasting insulin at IRS1 and ZNF12 loci, the latter showing higher RNA expression in whole blood in women compared to men. We also observe sex-homogeneous effects on fasting glucose at seven novel loci. Fasting insulin in women shows stronger genetic correlations than in men with waist-to-hip ratio and anorexia nervosa. Furthermore, waist-to-hip ratio is causally related to insulin resistance in women, but not in men. These results position dissection of metabolic and glycemic health sex dimorphism as a steppingstone for understanding differences in genetic effects between women and men in related phenotypes.

Silent Myocardial Infarction and Subsequent Ischemic Stroke in the Cardiovascular Health Study. - Merkler, Alexander E; Bartz, Traci M; Kamel, Hooman; Soliman, Elsayed Z; Howard, Virginia; Psaty, Bruce M; Okin, Peter M; Safford, Monika M; Elkind, Mitchell S V; Longstreth, W T (Neurology, 2021)
OBJECTIVE: To test the hypothesis that silent MI is a risk factor for ischemic stroke, we evaluated the association between silent MI and subsequent ischemic stroke in the Cardiovascular Health Study. METHODS: The Cardiovascular Health Study prospectively enrolled community-dwelling individuals ≥65 years of age. We included participants without prevalent stroke or baseline evidence of MI. Our exposures were silent and clinically apparent, overt MI. Silent MI was defined as new evidence of Q-wave MI, without clinical symptoms of MI, on ECGs performed during annual study visits from 1989-1999. The primary outcome was incident ischemic stroke. Secondary outcomes were ischemic stroke subtypes: non-lacunar, lacunar, and other/unknown. Cox proportional hazards analysis was used to model the association between time-varying MI status (silent, overt, or no MI) and stroke after adjustment for baseline demographics and vascular risk factors. RESULTS: Among 4,224 participants, 362 (8.6%) had an incident silent MI, 421 (10.0%) an incident overt MI, and 377 (8.9%) an incident ischemic stroke during a median follow-up of 9.8 years. After adjustment for demographics and comorbidities, silent MI was independently associated with subsequent ischemic stroke (HR, 1.51; 95% CI, 1.03-2.21). Overt MI was associated with ischemic stroke both in the short term (HR, 80; 95% CI, 53-119) and long term (HR, 1.60; 95% CI, 1.04-2.44). In secondary analyses, the association between silent MI and stroke was limited to non-lacunar ischemic stroke (HR 2.40; 95% CI, 1.36-4.22). CONCLUSION: In a community-based sample, we found an association between silent MI and ischemic stroke.

Supplemental Association of Clonal Hematopoiesis With Incident Heart Failure. - Yu, Bing; Roberts, Mary B; Raffield, Laura M; Zekavat, Seyedeh Maryam; Nguyen, Ngoc Quynh H; Biggs, Mary L; Brown, Michael R; Griffin, Gabriel; Desai, Pinkal; Correa, Adolfo; Morrison, Alanna C; Shah, Amil M; et al. (J Am Coll Cardiol, 2021)
BACKGROUND: Age-related clonal hematopoiesis of indeterminate potential (CHIP), defined as clonally expanded leukemogenic sequence variations (particularly in DNMT3A, TET2, ASXL1, and JAK2) in asymptomatic individuals, is associated with cardiovascular events, including recurrent heart failure (HF). OBJECTIVES: This study sought to evaluate whether CHIP is associated with incident HF. METHODS: CHIP status was obtained from whole exome or genome sequencing of blood DNA in participants without prevalent HF or hematological malignancy from 5 cohorts. Cox proportional hazards models were performed within each cohort, adjusting for demographic and clinical risk factors, followed by fixed-effect meta-analyses. Large CHIP clones (defined as variant allele frequency >10%), HF with or without baseline coronary heart disease, and left ventricular ejection fraction were evaluated in secondary analyses. RESULTS: Of 56,597 individuals (59% women, mean age 58 years at baseline), 3,406 (6%) had CHIP, and 4,694 developed HF (8.3%) over up to 20 years of follow-up. CHIP was prospectively associated with a 25% increased risk of HF in meta-analysis (hazard ratio: 1.25; 95% confidence interval: 1.13-1.38) with consistent associations across cohorts. ASXL1, TET2, and JAK2 sequence variations were each associated with an increased risk of HF, whereas DNMT3A sequence variations were not associated with HF. Secondary analyses suggested large CHIP was associated with a greater risk of HF (hazard ratio: 1.29; 95% confidence interval: 1.15-1.44), and the associations for CHIP on HF with and without prior coronary heart disease were homogenous. ASXL1 sequence variations were associated with reduced left ventricular ejection fraction. CONCLUSIONS: CHIP, particularly sequence variations in ASXL1, TET2, and JAK2, represents a new risk factor for HF.
Keywords: Aged; Clonal Hematopoiesis; Correlation of Data; Demography; DNA-Binding Proteins; Female; Heart Failure; Humans; Janus Kinase 2; Male; Middle Aged; Mutation; Proportional Hazards Models; Proto-Oncogene Proteins; Repressor Proteins; Risk Factors; Stroke Volume; Ventricular Dysfunction, Left; Whole Exome Sequencing

A System for Phenotype Harmonization in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. - Stilp, Adrienne M; Emery, Leslie S; Broome, Jai G; Buth, Erin J; Khan, Alyna T; Laurie, Cecelia A; Wang, Fei Fei; Wong, Quenna; Chen, Dongquan; D'Augustine, Catherine M; Heard-Costa, Nancy L; Hohensee, Chancellor R; et al. (Am J Epidemiol, 2021)
Genotype-phenotype association studies often combine phenotype data from multiple studies to increase power. Harmonization of the data usually requires substantial effort due to heterogeneity in phenotype definitions, study design, data collection procedures, and data set organization. Here we describe a centralized system for phenotype harmonization that includes input from phenotype domain and study experts, quality control, documentation, reproducible results, and data sharing mechanisms. This system was developed for the National Heart, Lung and Blood Institute's Trans-Omics for Precision Medicine program, which is generating genomic and other omics data for >80 studies with extensive phenotype data. To date, 63 phenotypes have been harmonized across thousands of participants from up to 17 studies per phenotype (participants recruited 1948-2012). We discuss challenges in this undertaking and how they were addressed. The harmonized phenotype data and associated documentation have been submitted to National Institutes of Health data repositories for controlled-access by the scientific community. We also provide materials to facilitate future harmonization efforts by the community, which include (1) the code used to generate the 63 harmonized phenotypes, enabling others to reproduce, modify or extend these harmonizations to additional studies; and (2) results of labeling thousands of phenotype variables with controlled vocabulary terms.

{The trans-ancestral genomic architecture of glycemic traits - Chen, J.; Spracklen, C. N.; Marenne, G.; Varshney, A.; Corbin, L. J.; Luan, J.; Willems, S. M.; Wu, Y.; Zhang, X.; Horikoshi, M.; Boutin, T. S.; Mägi, R.; et al. (Nat Genet, 2021)
10.1038/s41588-021-00852-9Glycemic traits are used to diagnose and monitor type 2 diabetes and cardiometabolic health. To date, most genetic studies of glycemic traits have focused on individuals of European ancestry. Here we aggregated genome-wide association studies comprising up to 281,416 individuals without diabetes (30% non-European ancestry) for whom fasting glucose, 2-h glucose after an oral glucose challenge, glycated hemoglobin and fasting insulin data were available. Trans-ancestry and single-ancestry meta-analyses identified 242 loci (99 novel; P < 5 × 10-8), 80% of which had no significant evidence of between-ancestry heterogeneity. Analyses restricted to individuals of European ancestry with equivalent sample size would have led to 24 fewer new loci. Compared with single-ancestry analyses, equivalent-sized trans-ancestry fine-mapping reduced the number of estimated variants in 99% credible sets by a median of 37.5%. Genomic-feature, gene-expression and gene-set analyses revealed distinct biological signatures for each trait, highlighting different underlying biological pathways. Our results increase our understanding of diabetes pathophysiology by using trans-ancestry studies for improved power and resolution.

Whole genome sequence analysis of platelet traits in the NHLBI trans-omics for precision medicine initiative. - Little, Amarise; Hu, Yao; Sun, Quan; Jain, Deepti; Broome, Jai; Chen, Ming-Huei; Thibord, Florian; McHugh, Caitlin; Surendran, Praveen; Blackwell, Thomas W; Brody, Jennifer A; Bhan, Arunoday; et al. (Hum Mol Genet, 2021)
Platelets play a key role in thrombosis and hemostasis. Platelet count (PLT) and mean platelet volume (MPV) are highly heritable quantitative traits, with hundreds of genetic signals previously identified, mostly in European ancestry populations. We here utilize whole genome sequencing from NHLBI's Trans-Omics for Precision Medicine Initiative (TOPMed) in a large multi-ethnic sample to further explore common and rare variation contributing to PLT (n = 61 200) and MPV (n = 23 485). We identified and replicated secondary signals at MPL (rs532784633) and PECAM1 (rs73345162), both more common in African ancestry populations. We also observed rare variation in Mendelian platelet related disorder genes influencing variation in platelet traits in TOPMed cohorts (not enriched for blood disorders). For example, association of GP9 with lower PLT and higher MPV was partly driven by a pathogenic Bernard-Soulier syndrome variant (rs5030764, p.Asn61Ser), and the signals at TUBB1 and CD36 were partly driven by loss of function variants not annotated as pathogenic in ClinVar (rs199948010 and rs571975065). However, residual signal remained for these gene-based signals after adjusting for lead variants, suggesting that additional variants in Mendelian genes with impacts in general population cohorts remain to be identified. Gene-based signals were also identified at several GWAS identified loci for genes not annotated for Mendelian platelet disorders (PTPRH, TET2, CHEK2), with somatic variation driving the result at TET2. These results highlight the value of whole genome sequencing in populations of diverse genetic ancestry to identify novel regulatory and coding signals, even for well-studied traits like platelet traits.

Whole-genome association analyses of sleep-disordered breathing phenotypes in the NHLBI TOPMed program. - Cade, Brian E; Lee, Jiwon; Sofer, Tamar; Wang, Heming; Zhang, Man; Chen, Han; Gharib, Sina A; Gottlieb, Daniel J; Guo, Xiuqing; Lane, Jacqueline M; Liang, Jingjing; Lin, Xihong; et al. (Genome Med, 2021)
BACKGROUND: Sleep-disordered breathing is a common disorder associated with significant morbidity. The genetic architecture of sleep-disordered breathing remains poorly understood. Through the NHLBI Trans-Omics for Precision Medicine (TOPMed) program, we performed the first whole-genome sequence analysis of sleep-disordered breathing. METHODS: The study sample was comprised of 7988 individuals of diverse ancestry. Common-variant and pathway analyses included an additional 13,257 individuals. We examined five complementary traits describing different aspects of sleep-disordered breathing: the apnea-hypopnea index, average oxyhemoglobin desaturation per event, average and minimum oxyhemoglobin saturation across the sleep episode, and the percentage of sleep with oxyhemoglobin saturation < 90%. We adjusted for age, sex, BMI, study, and family structure using MMSKAT and EMMAX mixed linear model approaches. Additional bioinformatics analyses were performed with MetaXcan, GIGSEA, and ReMap. RESULTS: We identified a multi-ethnic set-based rare-variant association (p = 3.48 × 10) on chromosome X with ARMCX3. Additional rare-variant associations include ARMCX3-AS1, MRPS33, and C16orf90. Novel common-variant loci were identified in the NRG1 and SLC45A2 regions, and previously associated loci in the IL18RAP and ATP2B4 regions were associated with novel phenotypes. Transcription factor binding site enrichment identified associations with genes implicated with respiratory and craniofacial traits. Additional analyses identified significantly associated pathways. CONCLUSIONS: We have identified the first gene-based rare-variant associations with objectively measured sleep-disordered breathing traits. Our results increase the understanding of the genetic architecture of sleep-disordered breathing and highlight associations in genes that modulate lung development, inflammation, respiratory rhythmogenesis, and HIF1A-mediated hypoxic response.

Whole-genome sequencing association analysis of quantitative red blood cell phenotypes: The NHLBI TOPMed program. - Hu, Yao; Stilp, Adrienne M; McHugh, Caitlin P; Rao, Shuquan; Jain, Deepti; Zheng, Xiuwen; Lane, John; Méric de Bellefon, Sébastian; Raffield, Laura M; Chen, Ming-Huei; Yanek, Lisa R; Wheeler, Marsha; et al. (Am J Hum Genet, 2021)
Whole-genome sequencing (WGS), a powerful tool for detecting novel coding and non-coding disease-causing variants, has largely been applied to clinical diagnosis of inherited disorders. Here we leveraged WGS data in up to 62,653 ethnically diverse participants from the NHLBI Trans-Omics for Precision Medicine (TOPMed) program and assessed statistical association of variants with seven red blood cell (RBC) quantitative traits. We discovered 14 single variant-RBC trait associations at 12 genomic loci, which have not been reported previously. Several of the RBC trait-variant associations (RPN1, ELL2, MIDN, HBB, HBA1, PIEZO1, and G6PD) were replicated in independent GWAS datasets imputed to the TOPMed reference panel. Most of these discovered variants are rare/low frequency, and several are observed disproportionately among non-European Ancestry (African, Hispanic/Latino, or East Asian) populations. We identified a 3 bp indel p.Lys2169del (g.88717175_88717177TCT[4]) (common only in the Ashkenazi Jewish population) of PIEZO1, a gene responsible for the Mendelian red cell disorder hereditary xerocytosis (MIM: 194380), associated with higher mean corpuscular hemoglobin concentration (MCHC). In stepwise conditional analysis and in gene-based rare variant aggregated association analysis, we identified several of the variants in HBB, HBA1, TMPRSS6, and G6PD that represent the carrier state for known coding, promoter, or splice site loss-of-function variants that cause inherited RBC disorders. Finally, we applied base and nuclease editing to demonstrate that the sentinel variant rs112097551 (nearest gene RPN1) acts through a cis-regulatory element that exerts long-range control of the gene RUVBL1 which is essential for hematopoiesis. Together, these results demonstrate the utility of WGS in ethnically diverse population-based samples and gene editing for expanding knowledge of the genetic architecture of quantitative hematologic traits and suggest a continuum between complex trait and Mendelian red cell disorders.
Keywords: Adult; Aged; Chromosomes, Human, Pair 16; Datasets as Topic; Erythrocytes; Female; Gene Editing; Genetic Variation; Genome-Wide Association Study; HEK293 Cells; Humans; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Quality Control; Reproducibility of Results; United States

Whole-genome sequencing in diverse subjects identifies genetic correlates of leukocyte traits: The NHLBI TOPMed program. - Mikhaylova, Anna V; McHugh, Caitlin P; Polfus, Linda M; Raffield, Laura M; Boorgula, Meher Preethi; Blackwell, Thomas W; Brody, Jennifer A; Broome, Jai; Chami, Nathalie; Chen, Ming-Huei; Conomos, Matthew P; Cox, Corey; et al. (Am J Hum Genet, 2021)
Many common and rare variants associated with hematologic traits have been discovered through imputation on large-scale reference panels. However, the majority of genome-wide association studies (GWASs) have been conducted in Europeans, and determining causal variants has proved challenging. We performed a GWAS of total leukocyte, neutrophil, lymphocyte, monocyte, eosinophil, and basophil counts generated from 109,563,748 variants in the autosomes and the X chromosome in the Trans-Omics for Precision Medicine (TOPMed) program, which included data from 61,802 individuals of diverse ancestry. We discovered and replicated 7 leukocyte trait associations, including (1) the association between a chromosome X, pseudo-autosomal region (PAR), noncoding variant located between cytokine receptor genes (CSF2RA and CLRF2) and lower eosinophil count; and (2) associations between single variants found predominantly among African Americans at the S1PR3 (9q22.1) and HBB (11p15.4) loci and monocyte and lymphocyte counts, respectively. We further provide evidence indicating that the newly discovered eosinophil-lowering chromosome X PAR variant might be associated with reduced susceptibility to common allergic diseases such as atopic dermatitis and asthma. Additionally, we found a burden of very rare FLT3 (13q12.2) variants associated with monocyte counts. Together, these results emphasize the utility of whole-genome sequencing in diverse samples in identifying associations missed by European-ancestry-driven GWASs.
Keywords: Asthma; Biomarkers; Dermatitis, Atopic; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Leukocytes; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Polymorphism, Single Nucleotide; Prognosis; Proteome; Pulmonary Disease, Chronic Obstructive; Quantitative Trait Loci; United Kingdom; United States; Whole Genome Sequencing

Assessing the contribution of rare variants to complex trait heritability from whole-genome sequence data. - Wainschtein, Pierrick; Jain, Deepti; Zheng, Zhili; Cupples, L Adrienne; Shadyab, Aladdin H; McKnight, Barbara; Shoemaker, Benjamin M; Mitchell, Braxton D; Psaty, Bruce M; Kooperberg, Charles; Liu, Ching-Ti; Albert, Christine M; et al. (Nat Genet, 2022)
Analyses of data from genome-wide association studies on unrelated individuals have shown that, for human traits and diseases, approximately one-third to two-thirds of heritability is captured by common SNPs. However, it is not known whether the remaining heritability is due to the imperfect tagging of causal variants by common SNPs, in particular whether the causal variants are rare, or whether it is overestimated due to bias in inference from pedigree data. Here we estimated heritability for height and body mass index (BMI) from whole-genome sequence data on 25,465 unrelated individuals of European ancestry. The estimated heritability was 0.68 (standard error 0.10) for height and 0.30 (standard error 0.10) for body mass index. Low minor allele frequency variants in low linkage disequilibrium (LD) with neighboring variants were enriched for heritability, to a greater extent for protein-altering variants, consistent with negative selection. Our results imply that rare variants, in particular those in regions of low linkage disequilibrium, are a major source of the still missing heritability of complex traits and disease.

The Association of Lipids and Lipoproteins with Hip Fracture Risk the Cardiovascular Health Study. - Barzilay, Joshua I; Bůzková, Petra; Kuller, Lewis H; Cauley, Jane A; Fink, Howard A; Sheets, Kerry; Robbins, John A; Carbone, Laura D; Elam, Rachel E; Mukamal, Kenneth J (Am J Med, 2022)
BACKGROUND: It is uncertain if lipids or lipoproteins are associated with osteoporotic fractures. In this study, incident hip fracture risk according to conventional lipid levels and lipoprotein levels and sizes was examined. METHODS: We followed 5832 participants aged ≥65 years from the Cardiovascular Health Study for hip fracture for a mean of 13.5 (SD 5.7) years. Standard enzymatic methods were used to determine lipid levels (HDL-c, LDL-c, triglycerides). Nuclear magnetic resonance spectroscopy was used to measure lipoprotein fractions (VLDL-P, LDL-P, HDL-P) in a subset of 1849 participants. RESULTS: We documented 755 incident hip fractures among women (1.19 fractures per 100 participant years [95% CI, 1.04, 1.35]) and 197 among men (0.67 fractures per 100 participant years [95% CI, 0.41, 1.10]) over an average follow-up. HDL-c and LDL-c levels had statistically significant non-linear U-shaped relationships with hip fracture risk (HDL-c, p=0.009; LDL-c, p=0.02). Triglyceride levels were not significantly associated with hip fracture risk. In fully adjusted conjoint models, higher VLDL-P concentration [HR per 1-standard (SD) increment 1.47 (1.13, 1.91)] and size [HR per 1-SD increment 1.24 [1.05, 1.46]) and higher HDL-P size (HR per 1-SD increment 1.81 [1.25, 2.62]) were all associated with higher hip fracture risk. CONCLUSIONS: Lipids and lipoproteins are associated with hip fracture risk in older adults. The associations are complex. Mechanistic studies are needed to understand these findings.

Associations of Pulmonary Function with MRI Brain Volumes: A Coordinated Multi-Study Analysis. - Frenzel, Stefan; Bis, Josh C; Gudmundsson, Elias F; O'Donnell, Adrienne; Simino, Jeannette; Yaqub, Amber; Bartz, Traci M; Brusselle, Guy G O; Bülow, Robin; DeCarli, Charles S; Ewert, Ralf; Gharib, Sina A; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Previous studies suggest poor pulmonary function is associated with increased burden of cerebral white matter hyperintensities and brain atrophy among elderly individuals, but the results are inconsistent. OBJECTIVE: To study the cross-sectional associations of pulmonary function with structural brain variables. METHODS: Data from six large community-based samples (N = 11,091) were analyzed. Spirometric measurements were standardized with respect to age, sex, height, and ethnicity using reference equations of the Global Lung Function Initiative. Associations of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and their ratio FEV1/FVC with brain volume, gray matter volume, hippocampal volume, and volume of white matter hyperintensities were investigated using multivariable linear regressions for each study separately and then combined using random-effect meta-analyses. RESULTS: FEV1 and FVC were positively associated with brain volume, gray matter volume, and hippocampal volume, and negatively associated with white matter hyperintensities volume after multiple testing correction, with little heterogeneity present between the studies. For instance, an increase of FVC by one unit was associated with 3.5 ml higher brain volume (95% CI: [2.2, 4.9]). In contrast, results for FEV1/FVC were more heterogeneous across studies, with significant positive associations with brain volume, gray matter volume, and hippocampal volume, but not white matter hyperintensities volume. Associations of brain variables with both FEV1 and FVC were consistently stronger than with FEV1/FVC, specifically with brain volume and white matter hyperintensities volume. CONCLUSION: In cross-sectional analyses, worse pulmonary function is associated with smaller brain volumes and higher white matter hyperintensities burden.

Clonal Hematopoiesis Is Associated With Higher Risk of Stroke. - Bhattacharya, Romit; Zekavat, Seyedeh M; Haessler, Jeffrey; Fornage, Myriam; Raffield, Laura; Uddin, Md Mesbah; Bick, Alexander G; Niroula, Abhishek; Yu, Bing; Gibson, Christopher; Griffin, Gabriel; Morrison, Alanna C; et al. (Stroke, 2022)
BACKGROUND AND PURPOSE: Clonal hematopoiesis of indeterminate potential (CHIP) is a novel age-related risk factor for cardiovascular disease-related morbidity and mortality. The association of CHIP with risk of incident ischemic stroke was reported previously in an exploratory analysis including a small number of incident stroke cases without replication and lack of stroke subphenotyping. The purpose of this study was to discover whether CHIP is a risk factor for ischemic or hemorrhagic stroke. METHODS: We utilized plasma genome sequence data of blood DNA to identify CHIP in 78 752 individuals from 8 prospective cohorts and biobanks. We then assessed the association of CHIP and commonly mutated individual CHIP driver genes (, , and ) with any stroke, ischemic stroke, and hemorrhagic stroke. RESULTS: CHIP was associated with an increased risk of total stroke (hazard ratio, 1.14 [95% CI, 1.03-1.27]; =0.01) after adjustment for age, sex, and race. We observed associations with CHIP with risk of hemorrhagic stroke (hazard ratio, 1.24 [95% CI, 1.01-1.51]; =0.04) and with small vessel ischemic stroke subtypes. In gene-specific association results, showed the strongest association with total stroke and ischemic stroke, whereas and were each associated with increased risk of hemorrhagic stroke. CONCLUSIONS: CHIP is associated with an increased risk of stroke, particularly with hemorrhagic and small vessel ischemic stroke. Future studies clarifying the relationship between CHIP and subtypes of stroke are needed.

{Clonal hematopoiesis of indeterminate potential, DNA methylation, and risk for coronary artery disease - Uddin, M. D. M.; Nguyen, N. Q. H.; Yu, B.; Brody, J. A.; Pampana, A.; Nakao, T.; Fornage, M.; Bressler, J.; Sotoodehnia, N.; Weinstock, J. S.; Honigberg, M. C.; Nachun, D.; et al. (Nat Commun, 2022)
Age-related changes to the genome-wide DNA methylation (DNAm) pattern observed in blood are well-documented. Clonal hematopoiesis of indeterminate potential (CHIP), characterized by the age-related acquisition and expansion of leukemogenic mutations in hematopoietic stem cells (HSCs), is associated with blood cancer and coronary artery disease (CAD). Epigenetic regulators DNMT3A and TET2 are the two most frequently mutated CHIP genes. Here, we present results from an epigenome-wide association study for CHIP in 582 Cardiovascular Health Study (CHS) participants, with replication in 2655 Atherosclerosis Risk in Communities (ARIC) Study participants. We show that DNMT3A and TET2 CHIP have distinct and directionally opposing genome-wide DNAm association patterns consistent with their regulatory roles, albeit both promoting self-renewal of HSCs. Mendelian randomization analyses indicate that a subset of DNAm alterations associated with these two leading CHIP genes may promote the risk for CAD.

Correlations between complex human phenotypes vary by genetic background, gender, and environment. - Elgart, Michael; Goodman, Matthew O; Isasi, Carmen; Chen, Han; Morrison, Alanna C; de Vries, Paul S; Xu, Huichun; Manichaikul, Ani W; Guo, Xiuqing; Franceschini, Nora; Psaty, Bruce M; Rich, Stephen S; et al. (Cell Rep Med, 2022)
We develop a closed-form Haseman-Elston estimator for genetic and environmental correlation coefficients between complex phenotypes, which we term HEc, that is as precise as GCTA yet ∼20× faster. We estimate genetic and environmental correlations between over 7,000 phenotype pairs in subgroups from the Trans-Omics in Precision Medicine (TOPMed) program. We demonstrate substantial differences in both heritabilities and genetic correlations for multiple phenotypes and phenotype pairs between individuals of self-reported Black, Hispanic/Latino, and White backgrounds. We similarly observe differences in many of the genetic and environmental correlations between genders. To estimate the contribution of genetics to the observed phenotypic correlation, we introduce "fractional genetic correlation" as the fraction of phenotypic correlation explained by genetics. Finally, we quantify the enrichment of correlations between phenotypic domains, each of which is comprised of multiple phenotypes. Altogether, we demonstrate that the observed correlations between complex human phenotypes depend on the genetic background of the individuals, their gender, and their environment.
Keywords: Female; Genetic Background; Humans; Male; Phenotype

Cross-Ancestry Investigation of Venous Thromboembolism Genomic Predictors. - Thibord, Florian; Klarin, Derek; Brody, Jennifer A; Chen, Ming-Huei; Levin, Michael G; Chasman, Daniel I; Goode, Ellen L; Hveem, Kristian; Teder-Laving, Maris; Martinez-Perez, Angel; Aïssi, Dylan; Daian-Bacq, Delphine; et al. (Circulation, 2022)
BACKGROUND: Venous thromboembolism (VTE) is a life-threatening vascular event with environmental and genetic determinants. Recent VTE genome-wide association studies (GWAS) meta-analyses involved nearly 30 000 VTE cases and identified up to 40 genetic loci associated with VTE risk, including loci not previously suspected to play a role in hemostasis. The aim of our research was to expand discovery of new genetic loci associated with VTE by using cross-ancestry genomic resources. METHODS: We present new cross-ancestry meta-analyzed GWAS results involving up to 81 669 VTE cases from 30 studies, with replication of novel loci in independent populations and loci characterization through in silico genomic interrogations. RESULTS: In our genetic discovery effort that included 55 330 participants with VTE (47 822 European, 6320 African, and 1188 Hispanic ancestry), we identified 48 novel associations, of which 34 were replicated after correction for multiple testing. In our combined discovery-replication analysis (81 669 VTE participants) and ancestry-stratified meta-analyses (European, African, and Hispanic), we identified another 44 novel associations, which are new candidate VTE-associated loci requiring replication. In total, across all GWAS meta-analyses, we identified 135 independent genomic loci significantly associated with VTE risk. A genetic risk score of the significantly associated loci in Europeans identified a 6-fold increase in risk for those in the top 1% of scores compared with those with average scores. We also identified 31 novel transcript associations in transcriptome-wide association studies and 8 novel candidate genes with protein quantitative-trait locus Mendelian randomization analyses. In silico interrogations of hemostasis and hematology traits and a large phenome-wide association analysis of the 135 GWAS loci provided insights to biological pathways contributing to VTE, with some loci contributing to VTE through well-characterized coagulation pathways and others providing new data on the role of hematology traits, particularly platelet function. Many of the replicated loci are outside of known or currently hypothesized pathways to thrombosis. CONCLUSIONS: Our cross-ancestry GWAS meta-analyses identified new loci associated with VTE. These findings highlight new pathways to thrombosis and provide novel molecules that may be useful in the development of improved antithrombosis treatments.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Thrombosis; Venous Thromboembolism

Differential and shared genetic effects on kidney function between diabetic and non-diabetic individuals. - Winkler, Thomas W; Rasheed, Humaira; Teumer, Alexander; Gorski, Mathias; Rowan, Bryce X; Stanzick, Kira J; Thomas, Laurent F; Tin, Adrienne; Hoppmann, Anselm; Chu, Audrey Y; Tayo, Bamidele; Thio, Chris H L; et al. (Commun Biol, 2022)
Reduced glomerular filtration rate (GFR) can progress to kidney failure. Risk factors include genetics and diabetes mellitus (DM), but little is known about their interaction. We conducted genome-wide association meta-analyses for estimated GFR based on serum creatinine (eGFR), separately for individuals with or without DM (n = 178,691, n = 1,296,113). Our genome-wide searches identified (i) seven eGFR loci with significant DM/noDM-difference, (ii) four additional novel loci with suggestive difference and (iii) 28 further novel loci (including CUBN) by allowing for potential difference. GWAS on eGFR among DM individuals identified 2 known and 27 potentially responsible loci for diabetic kidney disease. Gene prioritization highlighted 18 genes that may inform reno-protective drug development. We highlight the existence of DM-only and noDM-only effects, which can inform about the target group, if respective genes are advanced as drug targets. Largely shared effects suggest that most drug interventions to alter eGFR should be effective in DM and noDM.
Keywords: Creatinine; Diabetes Mellitus; Diabetic Nephropathies; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney

{DNA methylation signature of chronic low-grade inflammation and its role in cardio-respiratory diseases - Wielscher, M.; Mandaviya, P. R.; Kuehnel, B.; Joehanes, R.; Mustafa, R.; Robinson, O.; Zhang, Y.; Bodinier, B.; Walton, E.; Mishra, P. P.; Schlosser, P.; Wilson, R.; et al. (Nat Commun, 2022)
We performed a multi-ethnic Epigenome Wide Association study on 22,774 individuals to describe the DNA methylation signature of chronic low-grade inflammation as measured by C-Reactive protein (CRP). We find 1,511 independent differentially methylated loci associated with CRP. These CpG sites show correlation structures across chromosomes, and are primarily situated in euchromatin, depleted in CpG islands. These genomic loci are predominantly situated in transcription factor binding sites and genomic enhancer regions. Mendelian randomization analysis suggests altered CpG methylation is a consequence of increased blood CRP levels. Mediation analysis reveals obesity and smoking as important underlying driving factors for changed CpG methylation. Finally, we find that an activated CpG signature significantly increases the risk for cardiometabolic diseases and COPD.

Endophenotype effect sizes support variant pathogenicity in monogenic disease susceptibility genes. - Halford, Jennifer L; Morrill, Valerie N; Choi, Seung Hoan; Jurgens, Sean J; Melloni, Giorgio; Marston, Nicholas A; Weng, Lu-Chen; Nauffal, Victor; Hall, Amelia W; Gunn, Sophia; Austin-Tse, Christina A; Pirruccello, James P; et al. (Nat Commun, 2022)
Accurate and efficient classification of variant pathogenicity is critical for research and clinical care. Using data from three large studies, we demonstrate that population-based associations between rare variants and quantitative endophenotypes for three monogenic diseases (low-density-lipoprotein cholesterol for familial hypercholesterolemia, electrocardiographic QTc interval for long QT syndrome, and glycosylated hemoglobin for maturity-onset diabetes of the young) provide evidence for variant pathogenicity. Effect sizes are associated with pathogenic ClinVar assertions (P < 0.001 for each trait) and discriminate pathogenic from non-pathogenic variants (area under the curve 0.82-0.84 across endophenotypes). An effect size threshold of ≥ 0.5 times the endophenotype standard deviation nominates up to 35% of rare variants of uncertain significance or not in ClinVar in disease susceptibility genes with pathogenic potential. We propose that variant associations with quantitative endophenotypes for monogenic diseases can provide evidence supporting pathogenicity.
Keywords: Disease Susceptibility; Endophenotypes; Humans; Long QT Syndrome; Virulence

Epilepsy, Vascular Risk Factors, and Cognitive Decline in Older Adults: The Cardiovascular Health Study. - Choi, Hyunmi; Elkind, Mitchell S V; Longstreth, W T; Boehme, Amelia K; Hafen, Rebekah; Hoyt, Emma J; Thacker, Evan L (Neurology, 2022)
BACKGROUND AND OBJECTIVES: Recent studies have shown that global cognitive ability tends to decline faster over time in older adults (≥65 years) with epilepsy compared with older adults without epilepsy. Scarce data exist about the role of vascular risk factors (VRFs) on cognitive course in epilepsy. We assessed whether the associations of individual VRFs with cognitive trajectory differed depending on the presence of prevalent epilepsy. METHODS: The Cardiovascular Health Study is a population-based longitudinal cohort study of 5,888 US adults aged ≥65 years. Cognitive function was assessed annually with modified Mini-Mental State Examination (3MS; global cognitive ability) and Digit Symbol Substitution Test (DSST; information processing speed). We used linear mixed models to estimate the individual and joint associations of epilepsy and VRFs with cognitive decline by modeling epilepsy × VRF interactions one by one, each adjusted for all other VRFs considered, including demographics, health behaviors, clinical characteristics, and comorbid diagnoses. From these models, we estimated excess mean cognitive decline due to interaction of epilepsy with each VRF. RESULTS: We observed excess mean decline in global cognitive ability (3MS) due to interactions of epilepsy with hypertension (6.6 points greater mean 8-year decline than expected if no interaction; 95% CI 1.3-12.0) and with abstaining from alcohol (5.8 points greater than expected; 95% CI 0.3-11.3). We also observed excess mean decline in information processing speed (DSST) due to interactions of epilepsy with prior stroke (18.1 points greater mean 9-year decline than expected; 95% CI 7.6-28.5), with abstaining from alcohol (6.1 points greater than expected; 95% CI 2.5-9.8), and with higher triglyceride levels (2.4 points greater than expected per SD; 95% CI 0.4-4.3). DISCUSSION: Associations of some VRFs with cognitive decline in older adults are stronger in the presence of epilepsy, suggesting a need for greater attention to vascular protection for preserving brain health in older adults with epilepsy.
Keywords: Aged; Cognition; Cognitive Dysfunction; Epilepsy; Humans; Longitudinal Studies; Neuropsychological Tests; Risk Factors

{Genetic analyses of the electrocardiographic QT interval and its components identify additional loci and pathways - Young, W. J.; Lahrouchi, N.; Isaacs, A.; Duong, T.; Foco, L.; Ahmed, F.; Brody, J. A.; Salman, R.; Noordam, R.; Benjamins, J. W.; Haessler, J.; Lyytikäinen, L. P.; et al. (Nat Commun, 2022)
250,000 individuals) we identify 177, 156 and 121 independent loci for QT, JT and QRS, respectively, including a male-specific X-chromosome locus. Using gene-based rare-variant methods, we identify associations with Mendelian disease genes. Enrichments are observed in established pathways for QT and JT, and previously unreported genes indicated in insulin-receptor signalling and cardiac energy metabolism. In contrast for QRS, connective tissue components and processes for cell growth and extracellular matrix interactions are significantly enriched. We demonstrate polygenic risk score associations with atrial fibrillation, conduction disease and sudden cardiac death. Prioritization of druggable genes highlight potential therapeutic targets for arrhythmia. Together, these results substantially advance our understanding of the genetic architecture of ventricular depolarization and repolarization.

{Genetic and clinical determinants of abdominal aortic diameter: genome-wide association studies, exome array data and Mendelian randomization study - Portilla-Fernandez, E.; Klarin, D.; Hwang, S. J.; Biggs, M. L.; Bis, J. C.; Weiss, S.; Rospleszcz, S.; Natarajan, P.; Hoffmann, U.; Rogers, I. S.; Truong, Q. A.; lker, U.; et al. (Hum Mol Genet, 2022)
0.0001), known risk factors for AAA, consistent with a causal association with AAD. Our findings point to new biology as well as highlighting gene regions in mechanisms that have previously been implicated in the genetics of other vascular diseases.

Genetic loci and prioritization of genes for kidney function decline derived from a meta-analysis of 62 longitudinal genome-wide association studies. - Gorski, Mathias; Rasheed, Humaira; Teumer, Alexander; Thomas, Laurent F; Graham, Sarah E; Sveinbjornsson, Gardar; Winkler, Thomas W; Günther, Felix; Stark, Klaus J; Chai, Jin-Fang; Tayo, Bamidele O; Wuttke, Matthias; et al. (Kidney Int, 2022)
Estimated glomerular filtration rate (eGFR) reflects kidney function. Progressive eGFR-decline can lead to kidney failure, necessitating dialysis or transplantation. Hundreds of loci from genome-wide association studies (GWAS) for eGFR help explain population cross section variability. Since the contribution of these or other loci to eGFR-decline remains largely unknown, we derived GWAS for annual eGFR-decline and meta-analyzed 62 longitudinal studies with eGFR assessed twice over time in all 343,339 individuals and in high-risk groups. We also explored different covariate adjustment. Twelve genome-wide significant independent variants for eGFR-decline unadjusted or adjusted for eGFR-baseline (11 novel, one known for this phenotype), including nine variants robustly associated across models were identified. All loci for eGFR-decline were known for cross-sectional eGFR and thus distinguished a subgroup of eGFR loci. Seven of the nine variants showed variant-by-age interaction on eGFR cross section (further about 350,000 individuals), which linked genetic associations for eGFR-decline with age-dependency of genetic cross-section associations. Clinically important were two to four-fold greater genetic effects on eGFR-decline in high-risk subgroups. Five variants associated also with chronic kidney disease progression mapped to genes with functional in-silico evidence (UMOD, SPATA7, GALNTL5, TPPP). An unfavorable versus favorable nine-variant genetic profile showed increased risk odds ratios of 1.35 for kidney failure (95% confidence intervals 1.03-1.77) and 1.27 for acute kidney injury (95% confidence intervals 1.08-1.50) in over 2000 cases each, with matched controls). Thus, we provide a large data resource, genetic loci, and prioritized genes for kidney function decline, which help inform drug development pipelines revealing important insights into the age-dependency of kidney function genetics.

Genome-wide meta-analyses reveal novel loci for verbal short-term memory and learning. - Lahti, Jari; Tuominen, Samuli; Yang, Qiong; Pergola, Giulio; Ahmad, Shahzad; Amin, Najaf; Armstrong, Nicola J; Beiser, Alexa; Bey, Katharina; Bis, Joshua C; Boerwinkle, Eric; Bressler, Jan; et al. (Mol Psychiatry, 2022)
Understanding the genomic basis of memory processes may help in combating neurodegenerative disorders. Hence, we examined the associations of common genetic variants with verbal short-term memory and verbal learning in adults without dementia or stroke (N = 53,637). We identified novel loci in the intronic region of CDH18, and at 13q21 and 3p21.1, as well as an expected signal in the APOE/APOC1/TOMM40 region. These results replicated in an independent sample. Functional and bioinformatic analyses supported many of these loci and further implicated POC1. We showed that polygenic score for verbal learning associated with brain activation in right parieto-occipital region during working memory task. Finally, we showed genetic correlations of these memory traits with several neurocognitive and health outcomes. Our findings suggest a role of several genomic loci in verbal memory processes.

{Genome-wide studies reveal factors associated with circulating uromodulin and its relationships to complex diseases - Li, Y.; Cheng, Y.; Consolato, F.; Schiano, G.; Chong, M. R.; Pietzner, M.; Nguyen, N. Q. H.; Scherer, N.; Biggs, M. L.; Kleber, M. E.; Haug, S.; Göçmen, B.; et al. (JCI Insight, 2022)
Uromodulin (UMOD) is a major risk gene for monogenic and complex forms of kidney disease. The encoded kidney-specific protein uromodulin is highly abundant in urine and related to chronic kidney disease, hypertension, and pathogen defense. To gain insights into potential systemic roles, we performed genome-wide screens of circulating uromodulin using complementary antibody-based and aptamer-based assays. We detected 3 and 10 distinct significant loci, respectively. Integration of antibody-based results at the UMOD locus with functional genomics data (RNA-Seq, ATAC-Seq, Hi-C) of primary human kidney tissue highlighted an upstream variant with differential accessibility and transcription in uromodulin-synthesizing kidney cells as underlying the observed cis effect. Shared association patterns with complex traits, including chronic kidney disease and blood pressure, placed the PRKAG2 locus in the same pathway as UMOD. Experimental validation of the third antibody-based locus, B4GALNT2, showed that the p.Cys466Arg variant of the encoded N-acetylgalactosaminyltransferase had a loss-of-function effect leading to higher serum uromodulin levels. Aptamer-based results pointed to enzymes writing glycan marks present on uromodulin and to their receptors in the circulation, suggesting that this assay permits investigating uromodulin's complex glycosylation rather than its quantitative levels. Overall, our study provides insights into circulating uromodulin and its emerging functions.

{Implicating genes, pleiotropy, and sexual dimorphism at blood lipid loci through multi-ancestry meta-analysis - Kanoni, S.; Graham, S. E.; Wang, Y.; Surakka, I.; Ramdas, S.; Zhu, X.; Clarke, S. L.; Bhatti, K. F.; Vedantam, S.; Winkler, T. W.; Locke, A. E.; Marouli, E.; et al. (Genome Biol, 2022)
Genetic variants within nearly 1000 loci are known to contribute to modulation of blood lipid levels. However, the biological pathways underlying these associations are frequently unknown, limiting understanding of these findings and hindering downstream translational efforts such as drug target discovery.\ 1,654,960) of blood lipids to prioritize putative causal genes for 2286 lipid associations using six gene prediction approaches. Using phenome-wide association (PheWAS) scans, we identify relationships of genetically predicted lipid levels to other diseases and conditions. We confirm known pleiotropic associations with cardiovascular phenotypes and determine novel associations, notably with cholelithiasis risk. We perform sex-stratified GWAS meta-analysis of lipid levels and show that 3-5% of autosomal lipid-associated loci demonstrate sex-biased effects. Finally, we report 21 novel lipid loci identified on the X chromosome. Many of the sex-biased autosomal and X chromosome lipid loci show pleiotropic associations with sex hormones, emphasizing the role of hormone regulation in lipid metabolism.\ Taken together, our findings provide insights into the biological mechanisms through which associated variants lead to altered lipid levels and potentially cardiovascular disease risk.

Insights From a Large-Scale Whole-Genome Sequencing Study of Systolic Blood Pressure, Diastolic Blood Pressure, and Hypertension. - Kelly, Tanika N; Sun, Xiao; He, Karen Y; Brown, Michael R; Taliun, Sarah A Gagliano; Hellwege, Jacklyn N; Irvin, Marguerite R; Mi, Xuenan; Brody, Jennifer A; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; et al. (Hypertension, 2022)
BACKGROUND: The availability of whole-genome sequencing data in large studies has enabled the assessment of coding and noncoding variants across the allele frequency spectrum for their associations with blood pressure. METHODS: We conducted a multiancestry whole-genome sequencing analysis of blood pressure among 51 456 Trans-Omics for Precision Medicine and Centers for Common Disease Genomics program participants (stage-1). Stage-2 analyses leveraged array data from UK Biobank (N=383 145), Million Veteran Program (N=318 891), and Reasons for Geographic and Racial Differences in Stroke (N=10 643) participants, along with whole-exome sequencing data from UK Biobank (N=199 631) participants. RESULTS: Two blood pressure signals achieved genome-wide significance in meta-analyses of stage-1 and stage-2 single variant findings (<5×10). Among them, a rare intergenic variant at novel locus, , was associated with lower systolic blood pressure in stage-1 (beta [SE]=-32.6 [6.0]; =4.99×10) but not stage-2 analysis (=0.11). Furthermore, a novel common variant at the known locus was suggestively associated with diastolic blood pressure in stage-1 (beta [SE]=-0.36 [0.07]; =4.18×10) and attained genome-wide significance in stage-2 (beta [SE]=-0.29 [0.03]; =7.28×10). Nineteen additional signals suggestively associated with blood pressure in meta-analysis of single and aggregate rare variant findings (<1×10 and <1×10, respectively). DISCUSSION: We report one promising but unconfirmed rare variant for blood pressure and, more importantly, contribute insights for future blood pressure sequencing studies. Our findings suggest promise of aggregate analyses to complement single variant analysis strategies and the need for larger, diverse samples, and family studies to enable robust rare variant identification.

Integrative analysis of clinical and epigenetic biomarkers of mortality. - Huan, Tianxiao; Nguyen, Steve; Colicino, Elena; Ochoa-Rosales, Carolina; Hill, W David; Brody, Jennifer A; Soerensen, Mette; Zhang, Yan; Baldassari, Antoine; Elhadad, Mohamed Ahmed; Toshiko, Tanaka; Zheng, Yinan; et al. (Aging Cell, 2022)
DNA methylation (DNAm) has been reported to be associated with many diseases and with mortality. We hypothesized that the integration of DNAm with clinical risk factors would improve mortality prediction. We performed an epigenome-wide association study of whole blood DNAm in relation to mortality in 15 cohorts (n = 15,013). During a mean follow-up of 10 years, there were 4314 deaths from all causes including 1235 cardiovascular disease (CVD) deaths and 868 cancer deaths. Ancestry-stratified meta-analysis of all-cause mortality identified 163 CpGs in European ancestry (EA) and 17 in African ancestry (AA) participants at p < 1 × 10 , of which 41 (EA) and 16 (AA) were also associated with CVD death, and 15 (EA) and 9 (AA) with cancer death. We built DNAm-based prediction models for all-cause mortality that predicted mortality risk after adjusting for clinical risk factors. The mortality prediction model trained by integrating DNAm with clinical risk factors showed an improvement in prediction of cancer death with 5% increase in the C-index in a replication cohort, compared with the model including clinical risk factors alone. Mendelian randomization identified 15 putatively causal CpGs in relation to longevity, CVD, or cancer risk. For example, cg06885782 (in KCNQ4) was positively associated with risk for prostate cancer (Beta = 1.2, P  = 4.1 × 10 ) and negatively associated with longevity (Beta = -1.9, P  = 0.02). Pathway analysis revealed that genes associated with mortality-related CpGs are enriched for immune- and cancer-related pathways. We identified replicable DNAm signatures of mortality and demonstrated the potential utility of CpGs as informative biomarkers for prediction of mortality risk.
Keywords: Biomarkers; Cardiovascular Diseases; DNA Methylation; Epigenesis, Genetic; Epigenomics; Humans; Male; Neoplasms

Lung function impairment and risk of incident heart failure: the NHLBI Pooled Cohorts Study. - Eckhardt, Christina M; Balte, Pallavi P; Barr, Robert Graham; Bertoni, Alain G; Bhatt, Surya P; Cuttica, Michael; Cassano, Patricia A; Chaves, Paolo; Couper, David; Jacobs, David R; Kalhan, Ravi; Kronmal, Richard; et al. (Eur Heart J, 2022)
AIMS: The aim is to evaluate associations of lung function impairment with risk of incident heart failure (HF). METHODS AND RESULTS: Data were pooled across eight US population-based cohorts that enrolled participants from 1987 to 2004. Participants with self-reported baseline cardiovascular disease were excluded. Spirometry was used to define obstructive [forced expiratory volume in 1 s/forced vital capacity (FEV1/FVC) <0.70] or restrictive (FEV1/FVC ≥0.70, FVC <80%) lung physiology. The incident HF was defined as hospitalization or death caused by HF. In a sub-set, HF events were sub-classified as HF with reduced ejection fraction (HFrEF; EF <50%) or preserved EF (HFpEF; EF ≥50%). The Fine-Gray proportional sub-distribution hazards models were adjusted for sociodemographic factors, smoking, and cardiovascular risk factors. In models of incident HF sub-types, HFrEF, HFpEF, and non-HF mortality were treated as competing risks. Among 31 677 adults, there were 3344 incident HF events over a median follow-up of 21.0 years. Of 2066 classifiable HF events, 1030 were classified as HFrEF and 1036 as HFpEF. Obstructive [adjusted hazard ratio (HR) 1.17, 95% confidence interval (CI) 1.07-1.27] and restrictive physiology (adjusted HR 1.43, 95% CI 1.27-1.62) were associated with incident HF. Obstructive and restrictive ventilatory defects were associated with HFpEF but not HFrEF. The magnitude of the association between restrictive physiology and HFpEF was similar to associations with hypertension, diabetes, and smoking. CONCLUSION: Lung function impairment was associated with increased risk of incident HF, and particularly incident HFpEF, independent of and to a similar extent as major known cardiovascular risk factors.
Keywords: Adult; Heart Failure; Hospitalization; Humans; Lung; National Heart, Lung, and Blood Institute (U.S.); Prognosis; Risk Factors; Stroke Volume; United States

Monogenic and Polygenic Contributions to QTc Prolongation in the Population. - Nauffal, Victor; Morrill, Valerie N; Jurgens, Sean J; Choi, Seung Hoan; Hall, Amelia W; Weng, Lu-Chen; Halford, Jennifer L; Austin-Tse, Christina; Haggerty, Christopher M; Harris, Stephanie L; Wong, Eugene K; Alonso, Alvaro; et al. (Circulation, 2022)
Rare sequence variation in genes underlying cardiac repolarization and common polygenic variation influence QT interval duration. However, current clinical genetic testing of individuals with unexplained QT prolongation is restricted to examination of monogenic rare variants. The recent emergence of large-scale biorepositories with sequence data enables examination of the joint contribution of rare and common variation to the QT interval in the population. We performed a genome wide association study (GWAS) of the QTc in 84,630 United Kingdom Biobank (UKB) participants and created a polygenic risk score (PRS). Among 26,976 participants with whole genome sequencing and electrocardiogram data in the Trans-Omics for Precision Medicine (TOPMed) program, we identified 160 carriers of putative pathogenic rare variants in 10 genes known to be associated with the QT interval. We examined QTc associations with the PRS and with rare variants in TOPMed. Fifty-four independent loci were identified by GWAS in the UKB. Twenty-one loci were novel, of which 12 were replicated in TOPMed. The PRS comprising 1,110,494 common variants was significantly associated with the QTc in TOPMed (ΔQTc/ = 1.4 ms, 95% CI 1.3 -1.5; p-value=1.1×10). Carriers of putative pathogenic rare variants had longer QTc than non-carriers (ΔQTc=10.9 ms [7.4-14.4]). 23.7% of individuals with QTc>480 ms carried either a monogenic rare variant or had a PRS in the top decile (3.4% monogenic, 21% top decile of PRS). QTc duration in the population is influenced by both rare variants in genes underlying cardiac repolarization and polygenic risk, with a sizeable contribution from polygenic risk. Comprehensive assessment of the genetic determinants of QTc prolongation includes incorporation of both polygenic and monogenic risk.

Multi-ancestry genetic study of type 2 diabetes highlights the power of diverse populations for discovery and translation. - Mahajan, Anubha; Spracklen, Cassandra N; Zhang, Weihua; Ng, Maggie C Y; Petty, Lauren E; Kitajima, Hidetoshi; Yu, Grace Z; Rüeger, Sina; Speidel, Leo; Kim, Young Jin; Horikoshi, Momoko; Mercader, Josep M; et al. (Nat Genet, 2022)
We assembled an ancestrally diverse collection of genome-wide association studies (GWAS) of type 2 diabetes (T2D) in 180,834 affected individuals and 1,159,055 controls (48.9% non-European descent) through the Diabetes Meta-Analysis of Trans-Ethnic association studies (DIAMANTE) Consortium. Multi-ancestry GWAS meta-analysis identified 237 loci attaining stringent genome-wide significance (P < 5 × 10), which were delineated to 338 distinct association signals. Fine-mapping of these signals was enhanced by the increased sample size and expanded population diversity of the multi-ancestry meta-analysis, which localized 54.4% of T2D associations to a single variant with >50% posterior probability. This improved fine-mapping enabled systematic assessment of candidate causal genes and molecular mechanisms through which T2D associations are mediated, laying the foundations for functional investigations. Multi-ancestry genetic risk scores enhanced transferability of T2D prediction across diverse populations. Our study provides a step toward more effective clinical translation of T2D GWAS to improve global health for all, irrespective of genetic background.
Keywords: Diabetes Mellitus, Type 2; Ethnicity; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

A multi-ethnic polygenic risk score is associated with hypertension prevalence and progression throughout adulthood. - Kurniansyah, Nuzulul; Goodman, Matthew O; Kelly, Tanika N; Elfassy, Tali; Wiggins, Kerri L; Bis, Joshua C; Guo, Xiuqing; Palmas, Walter; Taylor, Kent D; Lin, Henry J; Haessler, Jeffrey; Gao, Yan; et al. (Nat Commun, 2022)
In a multi-stage analysis of 52,436 individuals aged 17-90 across diverse cohorts and biobanks, we train, test, and evaluate a polygenic risk score (PRS) for hypertension risk and progression. The PRS is trained using genome-wide association studies (GWAS) for systolic, diastolic blood pressure, and hypertension, respectively. For each trait, PRS is selected by optimizing the coefficient of variation (CV) across estimated effect sizes from multiple potential PRS using the same GWAS, after which the 3 trait-specific PRSs are combined via an unweighted sum called "PRSsum", forming the HTN-PRS. The HTN-PRS is associated with both prevalent and incident hypertension at 4-6 years of follow up. This association is further confirmed in age-stratified analysis. In an independent biobank of 40,201 individuals, the HTN-PRS is confirmed to be predictive of increased risk for coronary artery disease, ischemic stroke, type 2 diabetes, and chronic kidney disease.
Keywords: Adult; Diabetes Mellitus, Type 2; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Multifactorial Inheritance; Prevalence; Risk Factors

Multi-Scalar Data Integration Links Glomerular Angiopoietin-Tie Signaling Pathway Activation With Progression of Diabetic Kidney Disease. - Liu, Jiahao; Nair, Viji; Zhao, Yi-Yang; Chang, Dong-Yuan; Limonte, Christine; Bansal, Nisha; Fermin, Damian; Eichinger, Felix; Tanner, Emily C; Bellovich, Keith A; Steigerwalt, Susan; Bhat, Zeenat; et al. (Diabetes, 2022)
Diabetic kidney disease (DKD) is the leading cause of end-stage kidney disease (ESKD). Prognostic biomarkers reflective of underlying molecular mechanisms are critically needed for effective management of DKD. A three-marker panel was derived from a proteomics analysis of plasma samples by an unbiased machine learning approach from participants (N = 58) in the Clinical Phenotyping and Resource Biobank study. In combination with standard clinical parameters, this panel improved prediction of the composite outcome of ESKD or a 40% decline in glomerular filtration rate. The panel was validated in an independent group (N = 68), who also had kidney transcriptomic profiles. One marker, plasma angiopoietin 2 (ANGPT2), was significantly associated with outcomes in cohorts from the Cardiovascular Health Study (N = 3,183) and the Chinese Cohort Study of Chronic Kidney Disease (N = 210). Glomerular transcriptional angiopoietin/Tie (ANG-TIE) pathway scores, derived from the expression of 154 ANG-TIE signaling mediators, correlated positively with plasma ANGPT2 levels and kidney outcomes. Higher receptor expression in glomeruli and higher ANG-TIE pathway scores in endothelial cells corroborated potential functional effects in the kidney from elevated plasma ANGPT2 levels. Our work suggests that ANGPT2 is a promising prognostic endothelial biomarker with likely functional impact on glomerular pathogenesis in DKD.
Keywords: Angiopoietin-1; Angiopoietin-2; Angiopoietins; Biomarkers; Cohort Studies; Diabetes Mellitus; Diabetic Nephropathies; Disease Progression; Endothelial Cells; Humans; Kidney Failure, Chronic; Receptor, TIE-2; Signal Transduction

New insights into the genetic etiology of Alzheimer's disease and related dementias. - Bellenguez, Céline; Küçükali, Fahri; Jansen, Iris E; Kleineidam, Luca; Moreno-Grau, Sonia; Amin, Najaf; Naj, Adam C; Campos-Martin, Rafael; Grenier-Boley, Benjamin; Andrade, Victor; Holmans, Peter A; Boland, Anne; et al. (Nat Genet, 2022)
Characterization of the genetic landscape of Alzheimer's disease (AD) and related dementias (ADD) provides a unique opportunity for a better understanding of the associated pathophysiological processes. We performed a two-stage genome-wide association study totaling 111,326 clinically diagnosed/'proxy' AD cases and 677,663 controls. We found 75 risk loci, of which 42 were new at the time of analysis. Pathway enrichment analyses confirmed the involvement of amyloid/tau pathways and highlighted microglia implication. Gene prioritization in the new loci identified 31 genes that were suggestive of new genetically associated processes, including the tumor necrosis factor alpha pathway through the linear ubiquitin chain assembly complex. We also built a new genetic risk score associated with the risk of future AD/dementia or progression from mild cognitive impairment to AD/dementia. The improvement in prediction led to a 1.6- to 1.9-fold increase in AD risk from the lowest to the highest decile, in addition to effects of age and the APOE ε4 allele.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Genome-Wide Association Study; Humans; tau Proteins

Non-linear machine learning models incorporating SNPs and PRS improve polygenic prediction in diverse human populations. - Elgart, Michael; Lyons, Genevieve; Romero-Brufau, Santiago; Kurniansyah, Nuzulul; Brody, Jennifer A; Guo, Xiuqing; Lin, Henry J; Raffield, Laura; Gao, Yan; Chen, Han; de Vries, Paul; Lloyd-Jones, Donald M; et al. (Commun Biol, 2022)
Polygenic risk scores (PRS) are commonly used to quantify the inherited susceptibility for a trait, yet they fail to account for non-linear and interaction effects between single nucleotide polymorphisms (SNPs). We address this via a machine learning approach, validated in nine complex phenotypes in a multi-ancestry population. We use an ensemble method of SNP selection followed by gradient boosted trees (XGBoost) to allow for non-linearities and interaction effects. We compare our results to the standard, linear PRS model developed using PRSice, LDpred2, and lassosum2. Combining a PRS as a feature in an XGBoost model results in a relative increase in the percentage variance explained compared to the standard linear PRS model by 22% for height, 27% for HDL cholesterol, 43% for body mass index, 50% for sleep duration, 58% for systolic blood pressure, 64% for total cholesterol, 66% for triglycerides, 77% for LDL cholesterol, and 100% for diastolic blood pressure. Multi-ancestry trained models perform similarly to specific racial/ethnic group trained models and are consistently superior to the standard linear PRS models. This work demonstrates an effective method to account for non-linearities and interaction effects in genetics-based prediction models.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Machine Learning; Multifactorial Inheritance; Polymorphism, Single Nucleotide

{Obesity Partially Mediates the Diabetogenic Effect of Lowering LDL Cholesterol - Wu, P.; Moon, J. Y.; Daghlas, I.; Franco, G.; Porneala, B. C.; Ahmadizar, F.; Richardson, T. G.; Isaksen, J. L.; Hindy, G.; Yao, J.; Sitlani, C. M.; Raffield, L. M.; et al. (Diabetes Care, 2022)
LDL cholesterol (LDLc)-lowering drugs modestly increase body weight and type 2 diabetes risk, but the extent to which the diabetogenic effect of lowering LDLc is mediated through increased BMI is unknown.\ We conducted summary-level univariable and multivariable Mendelian randomization (MR) analyses in 921,908 participants to investigate the effect of lowering LDLc on type 2 diabetes risk and the proportion of this effect mediated through BMI. We used data from 92,532 participants from 14 observational studies to replicate findings in individual-level MR analyses.\ A 1-SD decrease in genetically predicted LDLc was associated with increased type 2 diabetes odds (odds ratio [OR] 1.12 [95% CI 1.01, 1.24]) and BMI (β = 0.07 SD units [95% CI 0.02, 0.12]) in univariable MR analyses. The multivariable MR analysis showed evidence of an indirect effect of lowering LDLc on type 2 diabetes through BMI (OR 1.04 [95% CI 1.01, 1.08]) with a proportion mediated of 38% of the total effect (P = 0.03). Total and indirect effect estimates were similar across a number of sensitivity analyses. Individual-level MR analyses confirmed the indirect effect of lowering LDLc on type 2 diabetes through BMI with an estimated proportion mediated of 8% (P = 0.04).\ These findings suggest that the diabetogenic effect attributed to lowering LDLc is partially mediated through increased BMI. Our results could help advance understanding of adipose tissue and lipids in type 2 diabetes pathophysiology and inform strategies to reduce diabetes risk among individuals taking LDLc-lowering medications.

Proteomics and Population Biology in the Cardiovascular Health Study (CHS): design of a study with mentored access and active data sharing. - Austin, Thomas R; McHugh, Caitlin P; Brody, Jennifer A; Bis, Joshua C; Sitlani, Colleen M; Bartz, Traci M; Biggs, Mary L; Bansal, Nisha; Bůzková, Petra; Carr, Steven A; deFilippi, Christopher R; Elkind, Mitchell S V; et al. (Eur J Epidemiol, 2022)
BACKGROUND: In the last decade, genomic studies have identified and replicated thousands of genetic associations with measures of health and disease and contributed to the understanding of the etiology of a variety of health conditions. Proteins are key biomarkers in clinical medicine and often drug-therapy targets. Like genomics, proteomics can advance our understanding of biology. METHODS AND RESULTS: In the setting of the Cardiovascular Health Study (CHS), a cohort study of older adults, an aptamer-based method that has high sensitivity for low-abundance proteins was used to assay 4979 proteins in frozen, stored plasma from 3188 participants (61% women, mean age 74 years). CHS provides active support, including central analysis, for seven phenotype-specific working groups (WGs). Each CHS WG is led by one or two senior investigators and includes 10 to 20 early or mid-career scientists. In this setting of mentored access, the proteomic data and analytic methods are widely shared with the WGs and investigators so that they may evaluate associations between baseline levels of circulating proteins and the incidence of a variety of health outcomes in prospective cohort analyses. We describe the design of CHS, the CHS Proteomics Study, characteristics of participants, quality control measures, and structural characteristics of the data provided to CHS WGs. We additionally highlight plans for validation and replication of novel proteomic associations. CONCLUSION: The CHS Proteomics Study offers an opportunity for collaborative data sharing to improve our understanding of the etiology of a variety of health conditions in older adults.

PUFA ω-3 and ω-6 biomarkers and sleep: a pooled analysis of cohort studies on behalf of the Fatty Acids and Outcomes Research Consortium (FORCE). - Murphy, Rachel A; Tintle, Nathan; Harris, William S; Darvishian, Maryam; Marklund, Matti; Virtanen, Jyrki K; Hantunen, Sari; de Mello, Vanessa D; Tuomilehto, Jaakko; Lindström, Jaana; Bolt, Matthew A; Brouwer, Ingeborg A; et al. (Am J Clin Nutr, 2022)
BACKGROUND: n-3 and n-6 PUFAs have physiologic roles in sleep processes, but little is known regarding circulating n-3 and n-6 PUFA and sleep parameters. OBJECTIVES: We sought to assess associations between biomarkers of n-3 and n-6 PUFA intake with self-reported sleep duration and difficulty falling sleeping in the Fatty Acids and Outcome Research Consortium. METHODS: Harmonized, de novo, individual-level analyses were performed and pooled across 12 cohorts. Participants were 35-96 y old and from 5 nations. Circulating measures included α-linolenic acid (ALA), EPA, docosapentaenoic acid (DPA), DHA, EPA + DPA + DHA, linoleic acid, and arachidonic acid. Sleep duration (10 cohorts, n = 18,791) was categorized as short (≤6 h), 7-8 h (reference), or long (≥9 h). Difficulty falling asleep (8 cohorts, n = 12,500) was categorized as yes or no. Associations between PUFAs, sleep duration, and difficulty falling sleeping were assessed by cross-sectional multinomial logistic regression using standardized protocols and covariates. Cohort-specific multivariable-adjusted ORs per quintile of PUFAs were pooled with inverse-variance weighted meta-analysis. RESULTS: In pooled analysis adjusted for sociodemographic characteristics and health status, participants with higher very long-chain n-3 PUFAs were less likely to have long sleep duration. In the top compared with the bottom quintiles, the multivariable-adjusted ORs (95% CIs) for long sleep were 0.78 (95% CI: 0.65, 0.95) for DHA and 0.76 (95% CI: 0.63, 0.93) for EPA + DPA + DHA. Significant associations for ALA and n-6 PUFA with short sleep duration or difficulty falling sleeping were not identified. CONCLUSIONS: Participants with higher concentrations of very long-chain n-3 PUFAs were less likely to have long sleep duration. While objective biomarkers reduce recall bias and misclassification, the cross-sectional design limits assessment of the temporal nature of this relation. These novel findings across 12 cohorts highlight the need for experimental and biological assessments of very long-chain n-3 PUFAs and sleep duration.
Keywords: Biomarkers; Cohort Studies; Cross-Sectional Studies; Fatty Acids; Fatty Acids, Omega-3; Humans; Outcome Assessment, Health Care; Sleep

Rare coding variants in 35 genes associate with circulating lipid levels-A multi-ancestry analysis of 170,000 exomes. - Hindy, George; Dornbos, Peter; Chaffin, Mark D; Liu, Dajiang J; Wang, Minxian; Selvaraj, Margaret Sunitha; Zhang, David; Park, Joseph; Aguilar-Salinas, Carlos A; Antonacci-Fulton, Lucinda; Ardissino, Diego; Arnett, Donna K; et al. (Am J Hum Genet, 2022)
Large-scale gene sequencing studies for complex traits have the potential to identify causal genes with therapeutic implications. We performed gene-based association testing of blood lipid levels with rare (minor allele frequency < 1%) predicted damaging coding variation by using sequence data from >170,000 individuals from multiple ancestries: 97,493 European, 30,025 South Asian, 16,507 African, 16,440 Hispanic/Latino, 10,420 East Asian, and 1,182 Samoan. We identified 35 genes associated with circulating lipid levels; some of these genes have not been previously associated with lipid levels when using rare coding variation from population-based samples. We prioritize 32 genes in array-based genome-wide association study (GWAS) loci based on aggregations of rare coding variants; three (EVI5, SH2B3, and PLIN1) had no prior association of rare coding variants with lipid levels. Most of our associated genes showed evidence of association among multiple ancestries. Finally, we observed an enrichment of gene-based associations for low-density lipoprotein cholesterol drug target genes and for genes closest to GWAS index single-nucleotide polymorphisms (SNPs). Our results demonstrate that gene-based associations can be beneficial for drug target development and provide evidence that the gene closest to the array-based GWAS index SNP is often the functional gene for blood lipid levels.
Keywords: Alleles; Blood Glucose; Case-Control Studies; Computational Biology; Databases, Genetic; Diabetes Mellitus, Type 2; Exome; Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Lipids; Liver; Molecular Sequence Annotation; Multifactorial Inheritance; Open Reading Frames; Phenotype; Polymorphism, Single Nucleotide

Rare genetic variants explain missing heritability in smoking. - Jang, Seon-Kyeong; Evans, Luke; Fialkowski, Allison; Arnett, Donna K; Ashley-Koch, Allison E; Barnes, Kathleen C; Becker, Diane M; Bis, Joshua C; Blangero, John; Bleecker, Eugene R; Boorgula, Meher Preethi; Bowden, Donald W; et al. (Nat Hum Behav, 2022)
Common genetic variants explain less variation in complex phenotypes than inferred from family-based studies, and there is a debate on the source of this 'missing heritability'. We investigated the contribution of rare genetic variants to tobacco use with whole-genome sequences from up to 26,257 unrelated individuals of European ancestries and 11,743 individuals of African ancestries. Across four smoking traits, single-nucleotide-polymorphism-based heritability ([Formula: see text]) was estimated from 0.13 to 0.28 (s.e., 0.10-0.13) in European ancestries, with 35-74% of it attributable to rare variants with minor allele frequencies between 0.01% and 1%. These heritability estimates are 1.5-4 times higher than past estimates based on common variants alone and accounted for 60% to 100% of our pedigree-based estimates of narrow-sense heritability ([Formula: see text], 0.18-0.34). In the African ancestry samples, [Formula: see text] was estimated from 0.03 to 0.33 (s.e., 0.09-0.14) across the four smoking traits. These results suggest that rare variants are important contributors to the heritability of smoking.

{A saturated map of common genetic variants associated with human height - Yengo, L.; Vedantam, S.; Marouli, E.; Sidorenko, J.; Bartell, E.; Sakaue, S.; Graff, M.; Eliasen, A. U.; Jiang, Y.; Raghavan, S.; Miao, J.; Arias, J. D.; et al. (Nature, 2022)
) account for 40% (45%) of phenotypic variance in populations of European ancestry but only around 10-20% (14-24%) in populations of other ancestries. Effect sizes, associated regions and gene prioritization are similar across ancestries, indicating that reduced prediction accuracy is likely to be explained by linkage disequilibrium and differences in allele frequency within associated regions. Finally, we show that the relevant biological pathways are detectable with smaller sample sizes than are needed to implicate causal genes and variants. Overall, this study provides a comprehensive map of specific genomic regions that contain the vast majority of common height-associated variants. Although this map is saturated for populations of European ancestry, further research is needed to achieve equivalent saturation in other ancestries.

Stroke genetics informs drug discovery and risk prediction across ancestries. - Mishra, Aniket; Malik, Rainer; Hachiya, Tsuyoshi; Jürgenson, Tuuli; Namba, Shinichi; Posner, Daniel C; Kamanu, Frederick K; Koido, Masaru; Le Grand, Quentin; Shi, Mingyang; He, Yunye; Georgakis, Marios K; et al. (Nature, 2022)
Previous genome-wide association studies (GWASs) of stroke - the second leading cause of death worldwide - were conducted predominantly in populations of European ancestry. Here, in cross-ancestry GWAS meta-analyses of 110,182 patients who have had a stroke (five ancestries, 33% non-European) and 1,503,898 control individuals, we identify association signals for stroke and its subtypes at 89 (61 new) independent loci: 60 in primary inverse-variance-weighted analyses and 29 in secondary meta-regression and multitrait analyses. On the basis of internal cross-ancestry validation and an independent follow-up in 89,084 additional cases of stroke (30% non-European) and 1,013,843 control individuals, 87% of the primary stroke risk loci and 60% of the secondary stroke risk loci were replicated (P < 0.05). Effect sizes were highly correlated across ancestries. Cross-ancestry fine-mapping, in silico mutagenesis analysis, and transcriptome-wide and proteome-wide association analyses revealed putative causal genes (such as SH3PXD2A and FURIN) and variants (such as at GRK5 and NOS3). Using a three-pronged approach, we provide genetic evidence for putative drug effects, highlighting F11, KLKB1, PROC, GP1BA, LAMC2 and VCAM1 as possible targets, with drugs already under investigation for stroke for F11 and PROC. A polygenic score integrating cross-ancestry and ancestry-specific stroke GWASs with vascular-risk factor GWASs (integrative polygenic scores) strongly predicted ischaemic stroke in populations of European, East Asian and African ancestry. Stroke genetic risk scores were predictive of ischaemic stroke independent of clinical risk factors in 52,600 clinical-trial participants with cardiometabolic disease. Our results provide insights to inform biology, reveal potential drug targets and derive genetic risk prediction tools across ancestries.

Targeted Genome Sequencing Identifies Multiple Rare Variants in Caveolin-1 Associated with Obstructive Sleep Apnea. - Liang, Jingjing; Wang, Heming; Cade, Brian E; Kurniansyah, Nuzulul; He, Karen Y; Lee, Jiwon; Sands, Scott A; Brody, Jennifer; Chen, Han; Gottlieb, Daniel J; Evans, Daniel S; Guo, Xiuqing; et al. (Am J Respir Crit Care Med, 2022)
INTRODUCTION: Obstructive sleep apnea (OSA) is a common disorder associated with increased risk for cardiovascular disease, diabetes, and premature mortality. There is strong clinical and epi-demiologic evidence supporting the importance of genetic factors influencing OSA, but limited data implicating specific genes. METHODS: Leveraging high depth genomic sequencing data from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program and imputed genotype data from multiple population-based studies, we performed linkage analysis in the Cleve-land Family Study (CFS) followed by multi-stage gene-based association analyses in independent cohorts to search for rare variants contributing to OSA severity as assessed by the apnea-hypopnea index (AHI) in a total of 7,708 individuals of European ancestry. RESULTS: Linkage analysis in CFS identified a suggestive linkage peak on chromosome 7q31 (LOD=2.31). Gene-based analysis identified 21 non-coding rare variants in Caveolin-1 (CAV1) associated with lower AHI after accounting for multiple comparisons (p=7.4×10-8). These non-coding variants together significantly contributed to the linkage evidence (p<10-3). Follow-up anal-ysis revealed significant associations between these variants and increased CAV1 expression, and increased CAV1 expression in peripheral monocytes was associated with lower AHI (p=0.024) and higher minimum overnight oxygen saturation (p=0.007). CONCLUSION: Rare variants in CAV1, a membrane scaffolding protein essential in multiple cellular and metabolic functions, are associated with higher CAV1 gene expression and lower OSA severity, suggesting a novel target for modulating OSA severity.

Trimethylamine N-oxide and hip fracture and bone mineral density in older adults: The cardiovascular health study. - Elam, Rachel E; Bůzková, Petra; Barzilay, Joshua I; Wang, Zeneng; Nemet, Ina; Budoff, Matthew J; Cauley, Jane A; Fink, Howard A; Lee, Yujin; Robbins, John A; Wang, Meng; Hazen, Stanley L; et al. (Bone, 2022)
CONTEXT: Gut microbiota-derived metabolite trimethylamine N-oxide (TMAO) may adversely affect bone by inducing oxidative stress. Whether this translates into increased fracture risk in older adults is uncertain. OBJECTIVE: Determine the associations of plasma TMAO with hip fracture and bone mineral density (BMD) in older adults. DESIGN AND SETTING: Cox hazard models and linear regression stratified by sex examined the associations of TMAO with hip fracture and BMD in the longitudinal cohort of the Cardiovascular Health Study. PARTICIPANTS: 5019 U.S. adults aged ≥65 years. EXPOSURE: Plasma TMAO. MAIN OUTCOME MEASURES: Incident hip fractures; total hip BMD dual x-ray absorptiometry in a subset (n = 1400). RESULTS: Six hundred sixty-six incident hip fractures occurred during up to 26 years of follow-up (67,574 person-years). After multivariable adjustment, TMAO was not significantly associated with hip fracture (women: hazard ratio (HR) [95% confidence interval (CI)] of 1.00[0.92,1.09] per TMAO doubling; men: 1.12[0.95,1.33]). TMAO was also not associated with total hip BMD (women: BMD difference [95% CI] of 0.42 g/cm*100 [-0.34,1.17] per TMAO doubling; men: 0.19[-1.04,1.42]). In exploratory analyses, we found an interaction between body mass index (BMI) and the association of TMAO with hip fracture (P < 0.01). Higher TMAO was significantly associated with risk of hip fracture in adults with overweight or obesity (BMI ≥ 25) (HR [95% CI]:1.17[1.05,1.31]), but not normal or underweight. CONCLUSIONS: Among older US men and women, TMAO was not significantly associated with risk of hip fracture or BMD overall. Exploratory analyses suggested a significant association between higher TMAO and hip fracture when BMI was elevated, which merits further study.
Keywords: Absorptiometry, Photon; Aged; Bone Density; Female; Hip Fractures; Humans; Male; Methylamines; Risk Factors

The Value of Rare Genetic Variation in the Prediction of Common Obesity in European Ancestry Populations. - Wang, Zhe; Choi, Shing Wan; Chami, Nathalie; Boerwinkle, Eric; Fornage, Myriam; Redline, Susan; Bis, Joshua C; Brody, Jennifer A; Psaty, Bruce M; Kim, Wonji; McDonald, Merry-Lynn N; Regan, Elizabeth A; et al. (Front Endocrinol (Lausanne), 2022)
Polygenic risk scores (PRSs) aggregate the effects of genetic variants across the genome and are used to predict risk of complex diseases, such as obesity. Current PRSs only include common variants (minor allele frequency (MAF) ≥1%), whereas the contribution of rare variants in PRSs to predict disease remains unknown. Here, we examine whether augmenting the standard common variant PRS (PRS) with a rare variant PRS (PRS) improves prediction of obesity. We used genome-wide genotyped and imputed data on 451,145 European-ancestry participants of the UK Biobank, as well as whole exome sequencing (WES) data on 184,385 participants. We performed single variant analyses (for both common and rare variants) and gene-based analyses (for rare variants) for association with BMI (kg/m), obesity (BMI ≥ 30 kg/m), and extreme obesity (BMI ≥ 40 kg/m). We built PRSs and PRSs using a range of methods (Clumping+Thresholding [C+T], PRS-CS, lassosum, gene-burden test). We selected the best-performing PRSs and assessed their performance in 36,757 European-ancestry unrelated participants with whole genome sequencing (WGS) data from the Trans-Omics for Precision Medicine (TOPMed) program. The best-performing PRS explained 10.1% of variation in BMI, and 18.3% and 22.5% of the susceptibility to obesity and extreme obesity, respectively, whereas the best-performing PRS explained 1.49%, and 2.97% and 3.68%, respectively. The PRS was associated with an increased risk of obesity and extreme obesity (OR = 1.37 per SD, = 1.7x10; OR = 1.55 per SD, = 3.8x10), which was attenuated, after adjusting for PRS (OR = 1.08 per SD, = 9.8x10; OR= 1.09 per SD, = 0.02). When PRS and PRS are combined, the increase in explained variance attributed to PRS was small (incremental Nagelkerke R = 0.24% for obesity and 0.51% for extreme obesity). Consistently, combining PRS to PRS provided little improvement to the prediction of obesity (PRS AUC = 0.591; PRS AUC = 0.708; PRS AUC = 0.710). In summary, while rare variants show convincing association with BMI, obesity and extreme obesity, the PRS provides limited improvement over PRS in the prediction of obesity risk, based on these large populations.
Keywords: Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Obesity; Whole Genome Sequencing

Association Between Acute Myocardial Infarction and Cognition. - Johansen, Michelle C; Ye, Wen; Gross, Alden; Gottesman, Rebecca F; Han, Dehua; Whitney, Rachael; Briceño, Emily M; Giordani, Bruno J; Shore, Supriya; Elkind, Mitchell S V; Manly, Jennifer J; Sacco, Ralph L; et al. (JAMA Neurol, 2023)
IMPORTANCE: The magnitude of cognitive change after incident myocardial infarction (MI) is unclear. OBJECTIVE: To assess whether incident MI is associated with changes in cognitive function after adjusting for pre-MI cognitive trajectories. DESIGN, SETTING, AND PARTICIPANTS: This cohort study included adults without MI, dementia, or stroke and with complete covariates from the following US population-based cohort studies conducted from 1971 to 2019: Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, Multi-Ethnic Study of Atherosclerosis, and Northern Manhattan Study. Data were analyzed from July 2021 to January 2022. EXPOSURES: Incident MI. MAIN OUTCOMES AND MEASURES: The main outcome was change in global cognition. Secondary outcomes were changes in memory and executive function. Outcomes were standardized as mean (SD) T scores of 50 (10); a 1-point difference represented a 0.1-SD difference in cognition. Linear mixed-effects models estimated changes in cognition at the time of MI (change in the intercept) and the rate of cognitive change over the years after MI (change in the slope), controlling for pre-MI cognitive trajectories and participant factors, with interaction terms for race and sex. RESULTS: The study included 30 465 adults (mean [SD] age, 64 [10] years; 56% female), of whom 1033 had 1 or more MI event, and 29 432 did not have an MI event. Median follow-up was 6.4 years (IQR, 4.9-19.7 years). Overall, incident MI was not associated with an acute decrease in global cognition (-0.18 points; 95% CI, -0.52 to 0.17 points), executive function (-0.17 points; 95% CI, -0.53 to 0.18 points), or memory (0.62 points; 95% CI, -0.07 to 1.31 points). However, individuals with incident MI vs those without MI demonstrated faster declines in global cognition (-0.15 points per year; 95% CI, -0.21 to -0.10 points per year), memory (-0.13 points per year; 95% CI, -0.22 to -0.04 points per year), and executive function (-0.14 points per year; 95% CI, -0.20 to -0.08 points per year) over the years after MI compared with pre-MI slopes. The interaction analysis suggested that race and sex modified the degree of change in the decline in global cognition after MI (race × post-MI slope interaction term, P = .02; sex × post-MI slope interaction term, P = .04), with a smaller change in the decline over the years after MI in Black individuals than in White individuals (difference in slope change, 0.22 points per year; 95% CI, 0.04-0.40 points per year) and in females than in males (difference in slope change, 0.12 points per year; 95% CI, 0.01-0.23 points per year). CONCLUSIONS: This cohort study using pooled data from 6 cohort studies found that incident MI was not associated with a decrease in global cognition, memory, or executive function at the time of the event compared with no MI but was associated with faster declines in global cognition, memory, and executive function over time. These findings suggest that prevention of MI may be important for long-term brain health.

Association of a blood-based aging biomarker index with death and chronic disease: Cardiovascular Health Study. - Zhang, Xiao; Sanders, Jason L; Boudreau, Robert M; Arnold, Alice M; Justice, Jamie N; Espeland, Mark A; Kuchel, George A; Barzilai, Nir; Kuller, Lewis H; Lopez, Oscar L; Kritchevsky, Stephen B; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2023)
BACKGROUND: A goal of gerontology is to discover phenotypes that reflect biological aging distinct from disease pathogenesis. Biomarkers that are strongly associated with mortality could be used to define such a phenotype. However, the relation of such an index with multiple chronic conditions warrants further exploration. METHODS: A Biomarker Index (BI) was constructed in the Cardiovascular Health Study (N=3197), with a mean age of 74 years. The BI incorporated circulating levels of new biomarkers, including insulin-like growth factor-1, interleukin-6, amino-terminal pro-B-type natriuretic peptide, cystatin-C, C-reactive protein, tumor necrosis factor-alpha soluble receptor 1, fasting insulin, and fasting glucose, and was built based on their relationships with mortality. Cox proportional hazards models predicting a composite of death and chronic disease involving cardiovascular disease, dementia, and cancer were calculated with 6 years of follow-up. RESULTS: The hazard ratio (HR, 95% CI) for the composite outcome of death or chronic disease per category of BI was 1.65 (1.52, 1.80) and 1.75 (1.58, 1.94) in women and men, respectively. The HR (95% CI) per 5 years of age was 1.57 (1.48, 1.67) and 1.55 (1.44, 1.67) in women and men, respectively. Moreover, BI could attenuate the effect of age on the composite outcome by 16.7% and 22.0% in women and men, respectively. CONCLUSIONS: BI was significantly and independently associated with a composite outcome of death and chronic disease, and attenuated the effect of age. The BI that is composed of plasma biomarkers may be a practical intermediate phenotype for interventions aiming to modify the course of aging.

Association of Immune Cell Subsets with Incident Hip Fracture: The Cardiovascular Health Study. - Elam, Rachel E; Bůzková, Petra; Delaney, Joseph A C; Fink, Howard A; Barzilay, Joshua I; Carbone, Laura D; Saha, Rick; Robbins, John A; Mukamal, Kenneth J; Valderrábano, Rodrigo J; Psaty, Bruce M; Tracy, Russell P; et al. (Calcif Tissue Int, 2023)
In this study, we aimed to evaluate the association of innate and adaptive immune cell subsets in peripheral blood mononuclear cells (PBMCs) with hip fracture. To conduct this study, we used data from the Cardiovascular Health Study (CHS), a U.S. multicenter observational cohort of community-dwelling men and women aged ≥ 65 years. Twenty-five immune cell phenotypes were measured by flow cytometry from cryopreserved PBMCs of CHS participants collected in 1998-1999. The natural killer (NK), γδ T, T helper 17 (Th17), and differentiated/senescent CD4CD28 T cell subsets were pre-specified as primary subsets of interest. Hip fracture incidence was assessed prospectively by review of hospitalization records. Multivariable Cox hazard models evaluated associations of immune cell phenotypes with incident hip fracture in sex-stratified and combined analyses. Among 1928 persons, 259 hip fractures occurred over a median 9.7 years of follow-up. In women, NK cells were inversely associated with hip fracture [hazard ratio (HR) 0.77, 95% confidence interval (CI) 0.60-0.99 per one standard deviation higher value] and Th17 cells were positively associated with hip fracture [HR 1.18, 95% CI 1.01-1.39]. In men, γδ T cells were inversely associated with hip fracture [HR 0.60, 95% CI 0.37-0.98]. None of the measured immune cell phenotypes were significantly associated with hip fracture incidence in combined analyses. In this large prospective cohort of older adults, potentially important sex differences in the associations of immune cell phenotypes and hip fracture were identified. However, immune cell phenotypes had no association with hip fracture in analyses combining men and women.

Association of Obesity With Cognitive Decline in Black and White Americans. - Quaye, Emmanuel; Galecki, Andrzej T; Tilton, Nicholas; Whitney, Rachael; Briceño, Emily M; Elkind, Mitchell S V; Fitzpatrick, Annette L; Gottesman, Rebecca F; Griswold, Michael; Gross, Alden L; Heckbert, Susan R; Hughes, Timothy M; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: There are disparities in the prevalence of obesity by race, and the relationship between obesity and cognitive decline is unclear. The objective of this study was to determine whether obesity is independently associated with cognitive decline and whether the association between obesity and cognitive decline differs in Black and White adults. We hypothesized that obesity is associated with greater cognitive decline compared with normal weight and that the effect of obesity on cognitive decline is more pronounced in Black adults compared with their White counterparts. METHODS: We pooled data from 28,867 participants free of stroke and dementia (mean, SD: age 61 [10.7] years at the first cognitive assessment, 55% female, 24% Black, and 29% obese) from 6 cohorts. The primary outcome was the annual change in global cognition. We performed linear mixed-effects models with and without time-varying cumulative mean systolic blood pressure (SBP) and fasting plasma glucose (FPG). Global cognition was set to a t-score metric (mean 50, SD 10) at a participant's first cognitive assessment; a 1-point difference represents a 0.1 SD difference in global cognition across the 6 cohorts. The median follow-up was 6.5 years (25th percentile, 75th percentile: 5.03, 20.15). RESULTS: Obese participants had lower baseline global cognition than normal-weight participants (difference in intercepts, -0.36 [95% CI, -0.46 to -0.17]; < 0.001). This difference in baseline global cognition was attenuated but was borderline significant after accounting for SBP and FPG (adjusted differences in intercepts, -0.19 [95% CI, -0.39 to 0.002]; = 0.05). There was no difference in the rate of decline in global cognition between obese and normal-weight participants (difference in slope, 0.009 points/year [95% CI, -0.009 to 0.03]; = 0.32). After accounting for SBP and FPG, obese participants had a slower decline in global cognition (adjusted difference in slope, 0.03 points/year slower [95% CI, 0.01 to 0.05]; < 0.001). There was no evidence that race modified the association between body mass index and global cognitive decline ( = 0.34). DISCUSSION: These results suggest that obesity is associated with lower initial cognitive scores and may potentially attenuate declines in cognition after accounting for BP and FPG.
Keywords: Aged; Black or African American; Cognition; Cognitive Dysfunction; Female; Humans; Male; Middle Aged; Obesity; Risk Factors; United States; White

The Association of Tryptophan and Its Metabolites With Incident Hip Fractures, Mortality, and Prevalent Frailty in Older Adults: The Cardiovascular Health Study. - Carbone, Laura; Bůzková, Petra; Fink, Howard A; Robbins, John A; Barzilay, Joshua I; Elam, Rachel E; Isales, Carlos (JBMR Plus, 2023)
Amino acids are the building blocks of proteins, and sufficient protein intake is important for skeletal health. We utilized stored serum from the Cardiovascular Health Study in 1992-1993 to examine the relationship between levels of the essential amino acid tryptophan (trp) and its oxidized and nonoxidized metabolites to risk for incident hip fractures and mortality over 12 years of follow-up. We included 131 persons who sustained a hip fracture during this time period and 131 without a hip fracture over these same 12 years of follow-up; 58% female and 95% White. Weighted multivariable Cox hazards models were used to estimate the hazard ratios (HR) and 95% confidence intervals (CI) of incident hip fracture associated with a one standard deviation (SD) higher trp or its metabolites exposure. Relative risk regression was used to evaluate the cross-sectional association of trp and its metabolites with frailty. Higher serum levels of trp were significantly associated with lower risk of incident hip fractures (HR = 0.75 per SD of trp (95% CI 0.57-0.99) but were not significantly associated with mortality or frailty status by Freid's frailty index. There were no statistically significant associations between any of the oxidized or nonoxidized products of trp with incident hip fractures ( ≥ 0.64), mortality ( ≥ 0.20), or cross-sectional frailty status ( ≥ 0.13) after multiple testing adjustment. Randomized clinical trials examining whether increasing trp intake is beneficial for osteoporosis are needed. © 2023 The Authors. published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research. This article has been contributed to by U.S. Government employees and their work is in the public domain in the USA.

{Associations Between Vascular Risk Factor Levels and Cognitive Decline Among Stroke Survivors - Levine, D. A.; Chen, B.; Galecki, A. T.; Gross, A. L.; o, E. M.; Whitney, R. T.; Ploutz-Snyder, R. J.; Giordani, B. J.; Sussman, J. B.; Burke, J. F.; Lazar, R. M.; Howard, V. J.; et al. (JAMA Netw Open, 2023)
Incident stroke is associated with accelerated cognitive decline. Whether poststroke vascular risk factor levels are associated with faster cognitive decline is uncertain.\ To evaluate associations of poststroke systolic blood pressure (SBP), glucose, and low-density lipoprotein (LDL) cholesterol levels with cognitive decline.\ Individual participant data meta-analysis of 4 US cohort studies (conducted 1971-2019). Linear mixed-effects models estimated changes in cognition after incident stroke. Median (IQR) follow-up was 4.7 (2.6-7.9) years. Analysis began August 2021 and was completed March 2023.\ Time-dependent cumulative mean poststroke SBP, glucose, and LDL cholesterol levels.\ The primary outcome was change in global cognition. Secondary outcomes were change in executive function and memory. Outcomes were standardized as t scores (mean [SD], 50 [10]); a 1-point difference represents a 0.1-SD difference in cognition.\ .002) but not executive function or memory declines.\ In this cohort study, higher poststroke glucose levels were associated with faster global cognitive decline. We found no evidence that poststroke LDL cholesterol and SBP levels were associated with cognitive decline.

The associations of markers of endothelial dysfunction with hip fracture risk. - Barzilay, Joshua I; Bůzková, Petra; Fink, Howard A; Cauley, Jane A; Carbone, Laura; Elam, Rachel; Robbins, John A; Stein, Phyllis; Sheets, Kerry; Jalal, Diana; Mukamal, Kenneth J (Arch Osteoporos, 2023)
UNLABELLED: Endothelial dysfunction underlies the development of atherosclerotic vascular disease, which in turn is associated with osteoporotic fractures. Here, we examined the association of two markers of endothelial dysfunction with incident hip fracture risk in older adults but found no statistically significant associations between them. PURPOSE/INTRODUCTION: Endothelial dysfunction underlies the development of atherosclerotic vascular disease. Vascular disease, in turn, is associated with the risk of osteoporotic fractures, such as hip fractures. Here, we examine whether two measures of endothelial dysfunction are related to hip fracture risk. METHODS: Participants for this study were 2792 individuals (mean age 78.6 years) who had flow-mediated dilation (FMD) measured after ischemia in the forearm and 2255 adults (mean age 73.3 years) with measured soluble intercellular adhesion molecule (siCAM) levels, a constitutive endothelial cell membrane protein associated with the initiation of atherosclerosis. Mean follow-up was 9.7 and 11.7 years, respectively. There were 375 and 265 incident hip fractures, respectively, in each group. RESULTS: In Cox proportional hazards models, there was no significant association between FMD response and incident hip fracture (HR per 1% higher FMD was 0.98 [0.93, 1.04]; p = 0.44). In exploratory analyses, when data were examined dichotomously, participants in the lowest 80% of FMD (≤ 4.5%) had an adjusted 1.29 (0.98, 1.68; p = 0.067) higher hazard of hip fracture compared to participants in the upper 20% of FMD change. There were no significant associations between siCAM and incident hip fracture whether examined as a continuous or dichotomized variable. CONCLUSIONS: Among older adults, two measures of endothelial dysfunction were not significantly associated with hip fracture risk. There was a trend for higher fracture risk with lower FMD.
Keywords: Aged; Forearm; Hip Fractures; Humans; Osteoporotic Fractures; Vascular Diseases

CogDrisk, ANU-ADRI, CAIDE, and LIBRA Risk Scores for Estimating Dementia Risk. - Huque, Md Hamidul; Kootar, Scherazad; Eramudugolla, Ranmalee; Han, S Duke; Carlson, Michelle C; Lopez, Oscar L; Bennett, David A; Peters, Ruth; Anstey, Kaarin J (JAMA Netw Open, 2023)
IMPORTANCE: While the Australian National University-Alzheimer Disease Risk Index (ANU-ADRI), Cardiovascular Risk Factors, Aging, and Dementia (CAIDE), and Lifestyle for Brain Health (LIBRA) dementia risk tools have been widely used, a large body of new evidence has emerged since their publication. Recently, Cognitive Health and Dementia Risk Index (CogDrisk) and CogDrisk for Alzheimer disease (CogDrisk-AD) risk tools have been developed for the assessment of dementia and AD risk, respectively, using contemporary evidence; comparison of the relative performance of these risk tools is limited. OBJECTIVE: To evaluate the performance of CogDrisk, ANU-ADRI, CAIDE, LIBRA, and modified LIBRA (LIBRA with age and sex estimates from ANU-ADRI) in estimating dementia and AD risks (with CogDrisk-AD and ANU-ADRI). DESIGN, SETTING, AND PARTICIPANTS: This population-based cohort study obtained data from the Rush Memory and Aging Project (MAP), the Cardiovascular Health Study Cognition Study (CHS-CS), and the Health and Retirement Study-Aging, Demographics and Memory Study (HRS-ADAMS). Participants who were free of dementia at baseline were included. The factors were component variables in the risk tools that included self-reported baseline demographics, medical risk factors, and lifestyle habits. The study was conducted between November 2021 and March 2023, and statistical analysis was performed from January to June 2023. MAIN OUTCOMES AND MEASURES: Risk scores were calculated based on available factors in each of these cohorts. Area under the receiver operating characteristic curve (AUC) was calculated to measure the performance of each risk score. Multiple imputation was used to assess whether missing data may have affected estimates for dementia risk. RESULTS: Among the 6107 participants in 3 validation cohorts included for this study, 2184 participants without dementia at baseline were available from MAP (mean [SD] age, 80.0 [7.6] years; 1606 [73.5%] female), 548 participants without dementia at baseline were available from HRS-ADAMS (mean [SD] age, 79.5 [6.3] years; 288 [52.5%] female), and 3375 participants without dementia at baseline were available from CHS-CS (mean [SD] age, 74.8 [4.9] years; 1994 [59.1%] female). In all 3 cohorts, a similar AUC for dementia was obtained using CogDrisk, ANU-ADRI, and modified LIBRA (MAP cohort: CogDrisk AUC, 0.65 [95% CI, 0.61-0.69]; ANU-ADRI AUC, 0.65 [95% CI, 0.61-0.69]; modified LIBRA AUC, 0.65 [95% CI, 0.61-0.69]; HRS-ADAMS cohort: CogDrisk AUC, 0.75 [95% CI, 0.71-0.79]; ANU-ADRI AUC, 0.74 [95% CI, 0.70-0.78]; modified LIBRA AUC, 0.75 [95% CI, 0.71-0.79]; CHS-CS cohort: CogDrisk AUC, 0.70 [95% CI, 0.67-0.72]; ANU-ADRI AUC, 0.69 [95% CI, 0.66-0.72]; modified LIBRA AUC, 0.70 [95% CI, 0.68-0.73]). The CAIDE and LIBRA also provided similar but lower AUCs than the 3 aforementioned tools (eg, MAP cohort: CAIDE AUC, 0.50 [95% CI, 0.46-0.54]; LIBRA AUC, 0.53 [95% CI, 0.48-0.57]). The performance of CogDrisk-AD and ANU-ADRI in estimating AD risks was also similar. CONCLUSIONS AND RELEVANCE: CogDrisk and CogDrisk-AD performed similarly to ANU-ADRI in estimating dementia and AD risks. These results suggest that CogDrisk and CogDrisk-AD, with a greater range of modifiable risk factors compared with other risk tools in this study, may be more informative for risk reduction.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Australia; Cohort Studies; Female; Heart Disease Risk Factors; Humans; Male; Risk Factors

{Early-onset Alzheimer's disease explained by polygenic risk of late-onset disease? - Mantyh, W. G.; Cochran, J. N.; Taylor, J. W.; Broce, I. J.; Geier, E. G.; Bonham, L. W.; Anderson, A. G.; Sirkis, D. W.; Joie, R.; Iaccarino, L.; Chaudhary, K.; Edwards, L.; et al. (Alzheimers Dement (Amst), 2023)
There is a unique genetic architecture of early- versus late-onset Alzheimer's disease (AD).Late-onset AD polygenic risk is not an explanation for early-onset AD.Polygenic risk of late-onset AD does not predict early-onset AD biology.Unique genetic architecture of early- versus late-onset AD parallels AD heterogeneity.

Evaluating the use of blood pressure polygenic risk scores across race/ethnic background groups. - Kurniansyah, Nuzulul; Goodman, Matthew O; Khan, Alyna T; Wang, Jiongming; Feofanova, Elena; Bis, Joshua C; Wiggins, Kerri L; Huffman, Jennifer E; Kelly, Tanika; Elfassy, Tali; Guo, Xiuqing; Palmas, Walter; et al. (Nat Commun, 2023)
We assess performance and limitations of polygenic risk scores (PRSs) for multiple blood pressure (BP) phenotypes in diverse population groups. We compare "clumping-and-thresholding" (PRSice2) and LD-based (LDPred2) methods to construct PRSs from each of multiple GWAS, as well as multi-PRS approaches that sum PRSs with and without weights, including PRS-CSx. We use datasets from the MGB Biobank, TOPMed study, UK biobank, and from All of Us to train, assess, and validate PRSs in groups defined by self-reported race/ethnic background (Asian, Black, Hispanic/Latino, and White). For both SBP and DBP, the PRS-CSx based PRS, constructed as a weighted sum of PRSs developed from multiple independent GWAS, perform best across all race/ethnic backgrounds. Stratified analysis in All of Us shows that PRSs are better predictive of BP in females compared to males, individuals without obesity, and middle-aged (40-60 years) compared to older and younger individuals.
Keywords: Blood Pressure; Ethnicity; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Multifactorial Inheritance; Population Health; Risk Factors

Gene-educational attainment interactions in a multi-population genome-wide meta-analysis identify novel lipid loci. - de Las Fuentes, Lisa; Schwander, Karen L; Brown, Michael R; Bentley, Amy R; Winkler, Thomas W; Sung, Yun Ju; Munroe, Patricia B; Miller, Clint L; Aschard, Hugo; Aslibekyan, Stella; Bartz, Traci M; Bielak, Lawrence F; et al. (Front Genet, 2023)
Educational attainment, widely used in epidemiologic studies as a surrogate for socioeconomic status, is a predictor of cardiovascular health outcomes. A two-stage genome-wide meta-analysis of low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglyceride (TG) levels was performed while accounting for gene-educational attainment interactions in up to 226,315 individuals from five population groups. We considered two educational attainment variables: "Some College" (yes/no, for any education beyond high school) and "Graduated College" (yes/no, for completing a 4-year college degree). Genome-wide significant ( < 5 × 10) and suggestive ( < 1 × 10) variants were identified in Stage 1 (in up to 108,784 individuals) through genome-wide analysis, and those variants were followed up in Stage 2 studies (in up to 117,531 individuals). In combined analysis of Stages 1 and 2, we identified 18 novel lipid loci (nine for LDL, seven for HDL, and two for TG) by two degree-of-freedom (2 DF) joint tests of main and interaction effects. Four loci showed significant interaction with educational attainment. Two loci were significant only in cross-population analyses. Several loci include genes with known or suggested roles in adipose (), brain (), and liver () biology, highlighting the potential importance of brain-adipose-liver communication in the regulation of lipid metabolism. An investigation of the potential druggability of genes in identified loci resulted in five gene targets shown to interact with drugs approved by the Food and Drug Administration, including genes with roles in adipose and brain tissue. Genome-wide interaction analysis of educational attainment identified novel lipid loci not previously detected by analyses limited to main genetic effects.

Genetic architecture of spatial electrical biomarkers for cardiac arrhythmia and relationship with cardiovascular disease. - Young, William J; Haessler, Jeffrey; Benjamins, Jan-Walter; Repetto, Linda; Yao, Jie; Isaacs, Aaron; Harper, Andrew R; Ramirez, Julia; Garnier, Sophie; Van Duijvenboden, Stefan; Baldassari, Antoine R; Concas, Maria Pina; et al. (Nat Commun, 2023)
The 3-dimensional spatial and 2-dimensional frontal QRS-T angles are measures derived from the vectorcardiogram. They are independent risk predictors for arrhythmia, but the underlying biology is unknown. Using multi-ancestry genome-wide association studies we identify 61 (58 previously unreported) loci for the spatial QRS-T angle (N = 118,780) and 11 for the frontal QRS-T angle (N = 159,715). Seven out of the 61 spatial QRS-T angle loci have not been reported for other electrocardiographic measures. Enrichments are observed in pathways related to cardiac and vascular development, muscle contraction, and hypertrophy. Pairwise genome-wide association studies with classical ECG traits identify shared genetic influences with PR interval and QRS duration. Phenome-wide scanning indicate associations with atrial fibrillation, atrioventricular block and arterial embolism and genetically determined QRS-T angle measures are associated with fascicular and bundle branch block (and also atrioventricular block for the frontal QRS-T angle). We identify potential biology involved in the QRS-T angle and their genetic relationships with cardiovascular traits and diseases, may inform future research and risk prediction.
Keywords: Arrhythmias, Cardiac; Atrioventricular Block; Biomarkers; Cardiovascular Diseases; Electrocardiography; Genome-Wide Association Study; Humans; Risk Factors

Genetic control of mRNA splicing as a potential mechanism for incomplete penetrance of rare coding variants. - Einson, Jonah; Glinos, Dafni; Boerwinkle, Eric; Castaldi, Peter; Darbar, Dawood; de Andrade, Mariza; Ellinor, Patrick; Fornage, Myriam; Gabriel, Stacey; Germer, Soren; Gibbs, Richard; Hersh, Craig P; et al. (bioRxiv, 2023)
Exonic variants present some of the strongest links between genotype and phenotype. However, these variants can have significant inter-individual pathogenicity differences, known as variable penetrance. In this study, we propose a model where genetically controlled mRNA splicing modulates the pathogenicity of exonic variants. By first cataloging exonic inclusion from RNA-seq data in GTEx v8, we find that pathogenic alleles are depleted on highly included exons. Using a large-scale phased WGS data from the TOPMed consortium, we observe that this effect may be driven by common splice-regulatory genetic variants, and that natural selection acts on haplotype configurations that reduce the transcript inclusion of putatively pathogenic variants, especially when limiting to haploinsufficient genes. Finally, we test if this effect may be relevant for autism risk using families from the Simons Simplex Collection, but find that splicing of pathogenic alleles has a penetrance reducing effect here as well. Overall, our results indicate that common splice-regulatory variants may play a role in reducing the damaging effects of rare exonic variants.

Hospital-Acquired Infection at Time of Stroke and Cognitive Decline: The Cardiovascular Health Study. - Cole, Kyril L; Boehme, Amelia K; Thacker, Evan L; Longstreth, W T; Brown, Bruce L; Gale, Shawn D; Hedges, Dawson W; Anderson, Jacqueline K; Elkind, Mitchell S V (Cerebrovasc Dis, 2023)
Introduction Hospital-acquired infections (HAIs) after stroke are associated with additional morbidity and mortality, but whether HAIs increase long-term cognitive decline in stroke patients is unknown. We hypothesized that older adults with incident stroke with HAI experience faster cognitive decline than those having stroke without HAI and those without stroke. Methods We performed a longitudinal analysis in the population-based prospective Cardiovascular Health Study. Medicare-eligible participants aged >65 years with and without incident stroke had cognition assessed annually. HAIs were assessed by hospital discharge codes. Global cognitive function was assessed annually by Modified Mini-Mental State Examination (3MSE) and executive function by Digit Symbol Substitution Test (DSST). We used linear mixed models to estimate the mean decline and 95% confidence intervals (95% CI) for 3MSE and DSST scores by incident stroke and HAI status, adjusted for demographics and vascular risk factors. Results Among 5,443 participants >65 years without previous history of stroke, 393 participants had stroke with HAI (SI), 766 had a stroke only (SO), and 4,284 had no stroke (NS) throughout a maximum 9-year follow-up. For 3MSE, compared with NS participants, SO participants had a similar adjusted mean decline (additional 0.08 points/year, 95%CI -0.15, 0.31), while SI participants had a more rapid decline (additional 0.28 points/year, 95%CI 0.16, 0.40). Adjusted mean decline was 0.20 points/year faster (95%CI -0.05, 0.45) among SI than SO participants. For DSST, compared with NS participants, SO participants had a faster adjusted mean decline (additional 0.17 points/year (95%CI 0.003, 0.33), as did SI participants (additional 0.27 points/year (95%CI 0.19, 0.35). Conclusion Stroke, when accompanied by HAI, leads to a faster long-term decline in cognitive ability than in those without stroke. The clinical and public health implications of the effect of infection on post-stroke cognitive decline warrant further attention.

{Identification of circulating proteins associated with general cognitive function among middle-aged and older adults - Tin, A.; Fohner, A. E.; Yang, Q.; Brody, J. A.; Davies, G.; Yao, J.; Liu, D.; Caro, I.; Lindbohm, J. V.; Duggan, M. R.; Meirelles, O.; Harris, S. E.; et al. (Commun Biol, 2023)
2.0E-4). Proteins implicated as causes or consequences of AD susceptibility may provide new insight into the potential relationship between immunity and AD susceptibility as well as potential therapeutic targets.

Machine learning models for blood pressure phenotypes combining multiple polygenic risk scores. - Hrytsenko, Yana; Shea, Benjamin; Elgart, Michael; Kurniansyah, Nuzulul; Lyons, Genevieve; Morrison, Alanna C; Carson, April P; Haring, Bernhard; Mitchel, Braxton D; Psaty, Bruce M; Jaeger, Byron C; Gu, C Charles; et al. (medRxiv, 2023)
We construct non-linear machine learning (ML) prediction models for systolic and diastolic blood pressure (SBP, DBP) using demographic and clinical variables and polygenic risk scores (PRSs). We developed a two-model ensemble, consisting of a baseline model, where prediction is based on demographic and clinical variables only, and a genetic model, where we also include PRSs. We evaluate the use of a linear versus a non-linear model at both the baseline and the genetic model levels and assess the improvement in performance when incorporating multiple PRSs. We report the ensemble model's performance as percentage variance explained (PVE) on a held-out test dataset. A non-linear baseline model improved the PVEs from 28.1% to 30.1% (SBP) and 14.3% to 17.4% (DBP) compared with a linear baseline model. Including seven PRSs in the genetic model computed based on the largest available GWAS of SBP/DBP improved the genetic model PVE from 4.8% to 5.1% (SBP) and 4.7% to 5% (DBP) compared to using a single PRS. Adding additional 14 PRSs computed based on two independent GWASs further increased the genetic model PVE to 6.3% (SBP) and 5.7% (DBP). PVE differed across self-reported race/ethnicity groups, with primarily all non-White groups benefitting from the inclusion of additional PRSs.

Mortality Following Hip Fracture in Older Adults With and Without Coronary Heart Disease. - Robbins, John A; Bůzková, Petra; Barzilay, Joshua I; Cauley, Jane A; Fink, Howard A; Carbone, Laura D; Chen, Zhao; Stein, Phyllis K; Elam, Rachel; Sheets, Kerry; Mukamal, Kenneth J (Am J Med, 2023)
BACKGROUND: Comorbidities like coronary heart disease are common among older people who sustain an osteoporotic hip fracture. However, their impact on short- and long-term mortality post-hip fracture is not well quantified. METHODS: We examined 4092 and 1173 older adults without and with prevalent coronary heart disease, respectively. Post-hip fracture mortality rates were computed with Poisson models and hazard ratios with Cox regression. For perspective, we compared mortality rates among participants with prevalent coronary heart disease who had either a hip fracture or incident heart failure (but no hip fracture). RESULTS: Among participants without prevalent coronary heart disease, the mortality rate post-hip fracture was 21.83 per 100 participant years, including 49.27 per 100 participant years in the first 6 months following hip fracture. Among participants with prevalent coronary heart disease, the corresponding mortality rates were 32.52 and 79.44 per 100 participant years, respectively. Participants with prevalent coronary heart disease and incident heart failure (but no hip fracture) had corresponding post-incident heart failure mortality rates per 100 participant years of 25.62 overall and 46.4 in the first 6 months. In all 3 groups, the hazard ratio for mortality was similarly elevated: 5- to 7-fold at 6 months and 1.7- to 2.5-fold beyond 5 years. CONCLUSION: As a case study in the absolute effects of a comorbidity on post-hip fracture mortality, hip fracture in a person with coronary heart disease carries an exceedingly high mortality rate, even higher than that following incident heart failure in individuals with coronary heart disease.

Multi-ancestry genome-wide study in >2.5 million individuals reveals heterogeneity in mechanistic pathways of type 2 diabetes and complications. - Suzuki, Ken; Hatzikotoulas, Konstantinos; Southam, Lorraine; Taylor, Henry J; Yin, Xianyong; Lorenz, Kim M; Mandla, Ravi; Huerta-Chagoya, Alicia; Rayner, Nigel W; Bocher, Ozvan; Ana Luiza de, S V Arruda; Sonehara, Kyuto; et al. (medRxiv, 2023)
Type 2 diabetes (T2D) is a heterogeneous disease that develops through diverse pathophysiological processes. To characterise the genetic contribution to these processes across ancestry groups, we aggregate genome-wide association study (GWAS) data from 2,535,601 individuals (39.7% non-European ancestry), including 428,452 T2D cases. We identify 1,289 independent association signals at genome-wide significance (P<5×10 ) that map to 611 loci, of which 145 loci are previously unreported. We define eight non-overlapping clusters of T2D signals characterised by distinct profiles of cardiometabolic trait associations. These clusters are differentially enriched for cell-type specific regions of open chromatin, including pancreatic islets, adipocytes, endothelial, and enteroendocrine cells. We build cluster-specific partitioned genetic risk scores (GRS) in an additional 137,559 individuals of diverse ancestry, including 10,159 T2D cases, and test their association with T2D-related vascular outcomes. Cluster-specific partitioned GRS are more strongly associated with coronary artery disease and end-stage diabetic nephropathy than an overall T2D GRS across ancestry groups, highlighting the importance of obesity-related processes in the development of vascular outcomes. Our findings demonstrate the value of integrating multi-ancestry GWAS with single-cell epigenomics to disentangle the aetiological heterogeneity driving the development and progression of T2D, which may offer a route to optimise global access to genetically-informed diabetes care.

Plasma Levels of Branched Chain Amino Acids, Incident Hip Fractures and Bone Mineral Density of the Hip and Spine. - Carbone, Laura; Bůzková, Petra; Fink, Howard A; Robbins, John A; Barzilay, Joshua I; Elam, Rachel E; Isales, Carlos; Connelly, Margery A; Mukamal, Kenneth J (J Clin Endocrinol Metab, 2023)
OBJECTIVE: Branched chain amino acids (BCAA) are building blocks for protein, an essential component of bone. However, the association of plasma levels of BCAA with fractures in populations outside of Hong Kong or with hip fractures in particular is not known. The purpose of these analyses was to determine the relationship of BCAA including valine, leucine and isoleucine and total BCAA (standard deviation of the sum of Z-scores for each BCAA) with incident hip fractures and bone mineral density (BMD) of the hip and lumbar spine in older African American and Caucasian men and women in the Cardiovascular Health Study (CHS). DESIGN: Longitudinal analyses of association of plasma levels of BCAA with incident hip fractures and cross-sectional BMD of the hip and lumbar spine from the CHS. SETTING: Community. PARTICIPANTS: 1850 men (38% of cohort) and women; mean age 73. MAIN OUTCOME MEASURES: Incident hip fractures and cross-sectional BMD of the total hip, femoral neck and lumbar spine. RESULTS: In fully adjusted models, over 12 years of follow-up, we observed no significant association between incident hip fracture and plasma values of valine, leucine, isoleucine or total BCAA per 1 standard deviation higher of each BCAA. Plasma values of leucine but not valine, isoleucine or total BCAA, were positively and significantly associated with BMD of the total hip (p = 0.03) and femoral neck (p = 0.02), but not the lumbar spine (p = 0.07). CONCLUSIONS: Plasma levels of the BCAA leucine may be associated with higher BMD in older men and women. However, given lack of a significant association with hip fracture risk, further information is needed to determine whether BCAAs would be novel targets for osteoporosis therapies.

Plasma Proteomic Associations With Incident Ischemic Stroke in Older Adults: The Cardiovascular Health Study. - Kalani, Rizwan; Bartz, Traci M; Psaty, Bruce M; Elkind, Mitchell S V; Floyd, James S; Gerszten, Robert E; Shojaie, Ali; Heckbert, Susan R; Bis, Joshua C; Austin, Thomas R; Tirschwell, David L; Delaney, Joseph A C; et al. (Neurology, 2023)
BACKGROUND: Plasma proteomics may elucidate novel insights into the pathophysiology of ischemic stroke (IS), identify biomarkers of IS risk, and guide development of nascent prevention strategies. We evaluated the relationship between the plasma proteome and IS risk in the population-based Cardiovascular Health Study (CHS). METHODS: Eligible CHS participants were free of prevalent stroke and underwent quantification of 1298 plasma proteins using the aptamer-based SOMAScan assay platform from the 1992-1993 study visit. Multivariable Cox proportional hazards regression was used to evaluate associations between a 1-standard deviation increase in the log-2 transformed estimated plasma protein concentrations and incident IS, adjusting for demographics, IS risk factors, and estimated glomerular filtration rate. For proteins independently associated with incident IS, a secondary stratified analysis evaluated associations in subgroups defined by sex and race. Exploratory analyses evaluated plasma proteomic associations with cardioembolic and non-cardioembolic IS as well as proteins associated with IS risk in participants with left atrial dysfunction but without atrial fibrillation. RESULTS: Of 2983 eligible participants, the mean age was 74.3 (± 4.8) years, 61.2% were women, and 15.4% were Black. Over a median follow-up of 12.6 years, 450 participants experienced an incident IS. N-terminal pro-brain natriuretic peptide (NTproBNP, adjusted HR 1.37, 95% CI 1.23-1.53, P=2.08x10) and macrophage metalloelastase (MMP12, adjusted HR 1.30, 95% CI 1.16-1.45, P=4.55x10) were independently associated with IS risk. These two associations were similar in men and women and in Black and non-Black participants. In exploratory analyses, NTproBNP was independently associated with incident cardioembolic IS, E-selectin with incident non-cardioembolic IS, and secreted frizzled-related protein 1 with IS risk in participants with left atrial dysfunction. CONCLUSIONS: In a cohort of older adults, NTproBNP and MMP12 were independently associated with IS risk. We identified plasma proteomic determinants of incident cardioembolic and non-cardioembolic IS and found a novel protein associated with IS risk in those with left atrial dysfunction.

Prediction of Multiple Individual Primary Cardiovascular Events Using Pooled Cohorts. - Sussman, Jeremy B; Whitney, Rachael T; Burke, James F; Hayward, Rodney A; Galecki, Andrzej; Sidney, Stephen; Allen, Norrina Bai; Gottesman, Rebecca F; Heckbert, Susan R; Longstreth, William T; Psaty, Bruce M; Elkind, Mitchell S V; et al. (medRxiv, 2023)
INTRODUCTION: Most current clinical risk prediction scores for cardiovascular disease prevention use a composite outcome. Risk prediction scores for specific cardiovascular events could identify people who are at higher risk for some events than others informing personalized care and trial recruitment. We sought to predict risk for multiple different events, describe how those risks differ, and examine if these differences could improve treatment priorities. METHODS: We used participant-level data from five cohort studies. We included participants between 40 and 79 years old who had no history of myocardial infarction (MI), stroke, or heart failure (HF). We made separate models to predict 10-year rates of first atherosclerotic cardiovascular disease (ASCVD), first fatal or nonfatal MI, first fatal or nonfatal stroke, new-onset HF, fatal ASCVD, fatal MI, fatal stroke, and all-cause mortality using established ASCVD risk factors. To limit overfitting, we used elastic net regularization with alpha = 0.75. We assessed the models for calibration, discrimination, and for correlations between predicted risks for different events. We also estimated the potential impact of varying treatment based on patients who are high risk for some ASCVD events, but not others. RESULTS: Our study included 24,505 people; 55.6% were women, and 20.7% were non-Hispanic Black. Our models had C-statistics between 0.75 for MI and 0.85 for HF, good calibration, and minimal overfitting. The models were least similar for fatal stroke and all MI (0.58). In 1,840 participants whose risk of MI but not stroke or all-cause mortality was in the top quartile, we estimate one blood pressure-lowering medication would have a 2.4% chance of preventing any ASCVD event per 10 years. A moderate-strength statin would have a 2.1% chance. In 1,039 participants who had top quartile risk of stroke but not MI or mortality, a blood pressure-lowering medication would have a 2.5% chance of preventing an event, but a moderate-strength statin, 1.6%. CONCLUSION: We developed risk scores for eight key clinical events and found that cardiovascular risk varies somewhat for different clinical events. Future work could determine if tailoring decisions by risk of separate events can improve care.

A proteomic analysis of atrial fibrillation in a prospective longitudinal cohort (AGES-Reykjavik study). - Jonmundsson, Thorarinn; Steindorsdottir, Anna E; Austin, Thomas R; Frick, Elisabet A; Axelsson, Gisli T; Launer, Lenore; Psaty, Bruce M; Loureiro, Joseph; Orth, Anthony P; Aspelund, Thor; Emilsson, Valur; Floyd, James S; et al. (Europace, 2023)
AIMS: Atrial fibrillation (AF) is associated with high risk of comorbidities and mortality. Our aim was to examine causal and predictive relationships between 4137 serum proteins and incident AF in the prospective population-based Age, Gene/Environment Susceptibility-Reykjavik (AGES-Reykjavik) study. METHODS AND RESULTS: The study included 4765 participants, of whom 1172 developed AF. Cox proportional hazards regression models were fitted for 4137 baseline protein measurements adjusting for known risk factors. Protein associations were tested for replication in the Cardiovascular Health Study (CHS). Causal relationships were examined in a bidirectional, two-sample Mendelian randomization analysis. The time-dependent area under the receiver operating characteristic curve (AUC)-statistic was examined as protein levels and an AF-polygenic risk score (PRS) were added to clinical risk models. The proteomic signature of incident AF consisted of 76 proteins, of which 63 (83%) were novel and 29 (38%) were replicated in CHS. The signature included both N-terminal prohormone of brain natriuretic peptide (NT-proBNP)-dependent (e.g. CHST15, ATP1B1, and SVEP1) and independent components (e.g. ASPN, AKR1B, and LAMA1/LAMB1/LAMC1). Nine causal candidates were identified (TAGLN, WARS, CHST15, CHMP3, COL15A1, DUSP13, MANBA, QSOX2, and SRL). The reverse causal analysis suggested that most AF-associated proteins were affected by the genetic liability to AF. N-terminal prohormone of brain natriuretic peptide improved the prediction of incident AF events close to baseline with further improvements gained by the AF-PRS at all time points. CONCLUSION: The AF proteomic signature includes biologically relevant proteins, some of which may be causal. It mainly reflects an NT-proBNP-dependent consequence of the genetic liability to AF. N-terminal prohormone of brain natriuretic peptide is a promising marker for incident AF in the short term, but risk assessment incorporating a PRS may improve long-term risk assessment.
Keywords: Atrial Fibrillation; Biomarkers; Endosomal Sorting Complexes Required for Transport; Humans; Natriuretic Peptide, Brain; Oxidoreductases Acting on Sulfur Group Donors; Peptide Fragments; Prognosis; Prospective Studies; Proteomics; Risk Factors

Proteomic prediction of incident heart failure and its main subtypes. - Emilsson, Valur; Jonsson, Brynjolfur G; Austin, Thomas R; Gudmundsdottir, Valborg; Axelsson, Gisli T; Frick, Elisabet A; Jonmundsson, Thorarinn; Steindorsdottir, Anna E; Loureiro, Joseph; Brody, Jennifer A; Aspelund, Thor; Launer, Lenore J; et al. (Eur J Heart Fail, 2023)
AIM: To examine the ability of serum proteins in predicting future heart failure (HF) events, including HF with reduced or preserved ejection fraction (HFrEF or HFpEF), in relation to event time, and with or without considering established HF-associated clinical variables. METHODS AND RESULTS: In the prospective population-based Age, Gene/Environment Susceptibility Reykjavik Study (AGES-RS), 440 individuals developed HF after their first visit with a median follow-up of 5.45 years. Among them, 167 were diagnosed with HFrEF and 188 with HFpEF. A least absolute shrinkage and selection operator regression model with nonparametric bootstrap were used to select predictors from an analysis of 4782 serum proteins, and several pre-established clinical parameters linked to HF. A subset of 8-10 distinct or overlapping serum proteins predicted different future HF outcomes, and C-statistics were used to assess discrimination, revealing proteins combined with a C-index of 0.80 for all incident HF, 0.78 and 0.80 for incident HFpEF or HFrEF, respectively. In the AGES-RS, protein panels alone encompassed the risk contained in the clinical information and improved the performance characteristics of prediction models based on NT-proBNP and clinical risk factors. Finally, the protein predictors performed particularly well close to the time of an HF event, an outcome that was replicated in the Cardiovascular Health Study (CHS). CONCLUSION: A small number of circulating proteins accurately predicted future HF in the AGES-RS cohort of older adults, and they alone encompass the risk information found in a collection of clinical data. Incident HF events were predicted up to eight years, with predictor performance significantly improving for events occurring less than one year ahead, a finding replicated in an external cohort study. This article is protected by copyright. All rights reserved.

Rare variants in long non-coding RNAs are associated with blood lipid levels in the TOPMed Whole Genome Sequencing Study. - Wang, Yuxuan; Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Holdcraft, Jacob A; Arnett, Donna K; Bis, Joshua C; Blangero, John; Boerwinkle, Eric; Bowden, Donald W; Cade, Brian E; Carlson, Jenna C; et al. (medRxiv, 2023)
Long non-coding RNAs (lncRNAs) are known to perform important regulatory functions. Large-scale whole genome sequencing (WGS) studies and new statistical methods for variant set tests now provide an opportunity to assess the associations between rare variants in lncRNA genes and complex traits across the genome. In this study, we used high-coverage WGS from 66,329 participants of diverse ancestries with blood lipid levels (LDL-C, HDL-C, TC, and TG) in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program to investigate the role of lncRNAs in lipid variability. We aggregated rare variants for 165,375 lncRNA genes based on their genomic locations and conducted rare variant aggregate association tests using the STAAR (variant-Set Test for Association using Annotation infoRmation) framework. We performed STAAR conditional analysis adjusting for common variants in known lipid GWAS loci and rare coding variants in nearby protein coding genes. Our analyses revealed 83 rare lncRNA variant sets significantly associated with blood lipid levels, all of which were located in known lipid GWAS loci (in a ±500 kb window of a Global Lipids Genetics Consortium index variant). Notably, 61 out of 83 signals (73%) were conditionally independent of common regulatory variations and rare protein coding variations at the same loci. We replicated 34 out of 61 (56%) conditionally independent associations using the independent UK Biobank WGS data. Our results expand the genetic architecture of blood lipids to rare variants in lncRNA, implicating new therapeutic opportunities.

{Serum NfL and GFAP are associated with incident dementia and dementia mortality in older adults: The cardiovascular health study - é, H. T.; Liu, X.; Odden, M. C.; Moseholm, K. F.; Seshadri, S.; Satizabal, C. L.; Lopez, O. L.; Bis, J. C.; é, L.; Fohner, A. E.; Psaty, B. M.; Tracy, R. P.; et al. (Alzheimers Dement, 2023)
Circulating neurofilament light chain (NfL) and glial fibrillary acidic protein (GFAP) have been independently associated with dementia risk. Their additive association, and their associations with dementia-specific mortality, have not been investigated.\ We associated serum NfL, GFAP, total tau ,and ubiquitin carboxyl-terminal hydrolase-L1, measured in 1712 dementia-free adults, with 19-year incident dementia and dementia-specific mortality risk, and with 3-year cognitive decline.\ 2.06 (1.60-2.67) and 9.22 (4.48-18.9). NfL was independently associated with accelerated cognitive decline.\ Circulating NfL and GFAP may, independently and jointly, provide useful clinical insight regarding dementia risk and prognosis.

Validation of the CogDrisk Instrument as Predictive of Dementia in Four General Community-Dwelling Populations. - Kootar, S; Huque, M H; Eramudugolla, R; Rizzuto, D; Carlson, M C; Odden, M C; Lopez, O L; Qiu, C; Fratiglioni, L; Han, S D; Bennett, D A; Peters, R; et al. (J Prev Alzheimers Dis, 2023)
BACKGROUND: Lack of external validation of dementia risk tools is a major limitation for generalizability and translatability of prediction scores in clinical practice and research. OBJECTIVES: We aimed to validate a new dementia prediction risk tool called CogDrisk and a version, CogDrisk-AD for predicting Alzheimer's disease (AD) using cohort studies. DESIGN, SETTING, PARTICIPANTS AND MEASUREMENTS: Four cohort studies were identified that included majority of the dementia risk factors from the CogDrisk tool. Participants who were free of dementia at baseline were included. The predictors were component variables in the CogDrisk tool that include self-reported demographics, medical risk factors and lifestyle habits. Risk scores for Any Dementia and AD were computed and Area Under the Curve (AUC) was assessed. To examine modifiable risk factors for dementia, the CogDrisk tool was tested by excluding age and sex estimates from the model. RESULTS: The performance of the tool varied between studies. The overall AUC and 95% CI for predicting dementia was 0.77 (0.57, 0.97) for the Swedish National study on Aging and Care in Kungsholmen, 0.76 (0.70, 0.83) for the Health and Retirement Study - Aging, Demographics and Memory Study, 0.70 (0.67,0.72) for the Cardiovascular Health Study Cognition Study, and 0.66 (0.62,0.70) for the Rush Memory and Aging Project. CONCLUSIONS: The CogDrisk and CogDrisk-AD performed well in the four studies. Overall, this tool can be used to assess individualized risk factors of dementia and AD in various population settings.
Keywords: Aging; Alzheimer Disease; Cohort Studies; Dementia; Humans; Independent Living

Whole genome analysis of plasma fibrinogen reveals population-differentiated genetic regulators with putative liver roles. - Huffman, Jennifer E; Nicolas, Jayna; Hahn, Julie; Heath, Adam S; Raffield, Laura M; Yanek, Lisa R; Brody, Jennifer A; Thibord, Florian; Almasy, Laura; Bartz, Traci M; Bielak, Lawrence F; Bowler, Russell P; et al. (medRxiv, 2023)
UNLABELLED: Genetic studies have identified numerous regions associated with plasma fibrinogen levels in Europeans, yet missing heritability and limited inclusion of non-Europeans necessitates further studies with improved power and sensitivity. Compared with array-based genotyping, whole genome sequencing (WGS) data provides better coverage of the genome and better representation of non-European variants. To better understand the genetic landscape regulating plasma fibrinogen levels, we meta-analyzed WGS data from the NHLBI's Trans-Omics for Precision Medicine (TOPMed) program (n=32,572), with array-based genotype data from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium (n=131,340) imputed to the TOPMed or Haplotype Reference Consortium panel. We identified 18 loci that have not been identified in prior genetic studies of fibrinogen. Of these, four are driven by common variants of small effect with reported MAF at least 10% higher in African populations. Three ( , and signals contain predicted deleterious missense variants. Two loci, and , each harbor two conditionally distinct, non-coding variants. The gene region encoding the protein chain subunits ( ), contains 7 distinct signals, including one novel signal driven by rs28577061, a variant common (MAF=0.180) in African reference panels but extremely rare (MAF=0.008) in Europeans. Through phenome-wide association studies in the VA Million Veteran Program, we found associations between fibrinogen polygenic risk scores and thrombotic and inflammatory disease phenotypes, including an association with gout. Our findings demonstrate the utility of WGS to augment genetic discovery in diverse populations and offer new insights for putative mechanisms of fibrinogen regulation. KEY POINTS: Largest and most diverse genetic study of plasma fibrinogen identifies 54 regions (18 novel), housing 69 conditionally distinct variants (20 novel).Sufficient power achieved to identify signal driven by African population variant.Links to (1) liver enzyme, blood cell and lipid genetic signals, (2) liver regulatory elements, and (3) thrombotic and inflammatory disease.

Whole genome sequence analysis of apparent treatment resistant hypertension status in participants from the Trans-Omics for Precision Medicine program. - Armstrong, Nicole D; Srinivasasainagendra, Vinodh; Ammous, Farah; Assimes, Themistocles L; Beitelshees, Amber L; Brody, Jennifer; Cade, Brian E; Ida Chen, Yii-Der; Chen, Han; de Vries, Paul S; Floyd, James S; Franceschini, Nora; et al. (Front Genet, 2023)
Apparent treatment-resistant hypertension (aTRH) is characterized by the use of four or more antihypertensive (AHT) classes to achieve blood pressure (BP) control. In the current study, we conducted single-variant and gene-based analyses of aTRH among individuals from 12 Trans-Omics for Precision Medicine cohorts with whole-genome sequencing data. Cases were defined as individuals treated for hypertension (HTN) taking three different AHT classes, with average systolic BP ≥ 140 or diastolic BP ≥ 90 mmHg, or four or more medications regardless of BP ( = 1,705). A normotensive control group was defined as individuals with BP < 140/90 mmHg ( = 22,079), not on AHT medication. A second control group comprised individuals who were treatment responsive on one AHT medication with BP < 140/ 90 mmHg ( = 5,424). Logistic regression with kinship adjustment using the Scalable and Accurate Implementation of Generalized mixed models (SAIGE) was performed, adjusting for age, sex, and genetic ancestry. We assessed variants using SKAT-O in rare-variant analyses. Single-variant and gene-based tests were conducted in a pooled multi-ethnicity stratum, as well as self-reported ethnic/racial strata (European and African American). One variant in the known HTN locus, , was a top finding in the multi-ethnic analysis ( = 8.23E-07) for the normotensive control group [rs12476527, odds ratio (95% confidence interval) = 0.80 (0.74-0.88)]. This variant was replicated in the Vanderbilt University Medical Center's DNA repository data. Aggregate gene-based signals included the genes and . Additional work validating these loci in larger, more diverse populations, is warranted to determine whether these regions influence the pathobiology of aTRH.

WHOLE GENOME SEQUENCING ANALYSIS OF BODY MASS INDEX IDENTIFIES NOVEL AFRICAN ANCESTRY-SPECIFIC RISK ALLELE. - Zhang, Xinruo; Brody, Jennifer A; Graff, Mariaelisa; Highland, Heather M; Chami, Nathalie; Xu, Hanfei; Wang, Zhe; Ferrier, Kendra; Chittoor, Geetha; Josyula, Navya S; Li, Xihao; Li, Zilin; et al. (medRxiv, 2023)
Obesity is a major public health crisis associated with high mortality rates. Previous genome-wide association studies (GWAS) investigating body mass index (BMI) have largely relied on imputed data from European individuals. This study leveraged whole-genome sequencing (WGS) data from 88,873 participants from the Trans-Omics for Precision Medicine (TOPMed) Program, of which 51% were of non-European population groups. We discovered 18 BMI-associated signals ( < 5 × 10 ). Notably, we identified and replicated a novel low frequency single nucleotide polymorphism (SNP) in that was common in individuals of African descent. Using a diverse study population, we further identified two novel secondary signals in known BMI loci and pinpointed two likely causal variants in the and loci. Our work demonstrates the benefits of combining WGS and diverse cohorts in expanding current catalog of variants and genes confer risk for obesity, bringing us one step closer to personalized medicine.

{A genetic association study of circulating coagulation Factor VIII and von Willebrand Factor levels - de Vries, P. S.; Reventun, P.; Brown, M. R.; Heath, A. S.; Huffman, J. E.; Le, N. Q.; Bebo, A.; Brody, J. A.; Temprano-Sagrera, G.; Raffield, L. M.; Ozel, A. B.; Thibord, F.; et al. (Blood, 2024)
10-9) at seven new loci for FVIII (ST3GAL4, CLEC4M, B3GNT2, ASGR1, F12, KNG1, and TREM1/NCR2) and one for VWF (B3GNT2). VWF, ABO, and STAB2 were associated with FVIII and VWF in gene-based analyses. Multi-phenotype analysis of FVIII and VWF identified another three new loci, including PDIA3. Silencing of B3GNT2 and the previously reported CD36 gene decreased release of FVIII by HLECs, while silencing of B3GNT2, CD36, and PDIA3 decreased release of VWF by HVECs. Mendelian randomization supports causal association of higher FVIII and VWF with increased risk of thrombotic outcomes. Seven new loci were identified for FVIII and one for VWF, with evidence supporting causal associations of FVIII and VWF with thrombotic outcomes. B3GNT2, CD36, and PDIA3 modulate the release of FVIII and/or VWF in vitro.

Genetic drivers of heterogeneity in type 2 diabetes pathophysiology. - Suzuki, Ken; Hatzikotoulas, Konstantinos; Southam, Lorraine; Taylor, Henry J; Yin, Xianyong; Lorenz, Kim M; Mandla, Ravi; Huerta-Chagoya, Alicia; Melloni, Giorgio E M; Kanoni, Stavroula; Rayner, Nigel W; Bocher, Ozvan; et al. (Nature, 2024)
Type 2 diabetes (T2D) is a heterogeneous disease that develops through diverse pathophysiological processes and molecular mechanisms that are often specific to cell type. Here, to characterize the genetic contribution to these processes across ancestry groups, we aggregate genome-wide association study data from 2,535,601 individuals (39.7% not of European ancestry), including 428,452 cases of T2D. We identify 1,289 independent association signals at genome-wide significance (P < 5 × 10) that map to 611 loci, of which 145 loci are, to our knowledge, previously unreported. We define eight non-overlapping clusters of T2D signals that are characterized by distinct profiles of cardiometabolic trait associations. These clusters are differentially enriched for cell-type-specific regions of open chromatin, including pancreatic islets, adipocytes, endothelial cells and enteroendocrine cells. We build cluster-specific partitioned polygenic scores in a further 279,552 individuals of diverse ancestry, including 30,288 cases of T2D, and test their association with T2D-related vascular outcomes. Cluster-specific partitioned polygenic scores are associated with coronary artery disease, peripheral artery disease and end-stage diabetic nephropathy across ancestry groups, highlighting the importance of obesity-related processes in the development of vascular outcomes. Our findings show the value of integrating multi-ancestry genome-wide association study data with single-cell epigenomics to disentangle the aetiological heterogeneity that drives the development and progression of T2D. This might offer a route to optimize global access to genetically informed diabetes care.

A Large-Scale Genome-Wide Study of Gene-Sleep Duration Interactions for Blood Pressure in 811,405 Individuals from Diverse Populations. - Nagarajan, Pavithra; Winkler, Thomas W; Bentley, Amy R; Miller, Clint L; Kraja, Aldi T; Schwander, Karen; Lee, Songmi; Wang, Wenyi; Brown, Michael R; Morrison, John L; Giri, Ayush; O'Connell, Jeffrey R; et al. (medRxiv, 2024)
Although both short and long sleep duration are associated with elevated hypertension risk, our understanding of their interplay with biological pathways governing blood pressure remains limited. To address this, we carried out genome-wide cross-population gene-by-short-sleep and long-sleep duration interaction analyses for three blood pressure traits (systolic, diastolic, and pulse pressure) in 811,405 individuals from diverse population groups. We discover 22 novel gene-sleep duration interaction loci for blood pressure, mapped to genes involved in neurological, thyroidal, bone metabolism, and hematopoietic pathways. Non-overlap between short sleep (12) and long sleep (10) interactions underscores the plausibility of distinct influences of both sleep duration extremes in cardiovascular health. With several of our loci reflecting specificity towards population background or sex, our discovery sheds light on the importance of embracing granularity when addressing heterogeneity entangled in gene-environment interactions, and in therapeutic design approaches for blood pressure management.

Large-Scale Proteomics Identifies Novel Biomarkers and Circulating Risk Factors for Aortic Stenosis. - Shelbaya, Khaled; Arthur, Victoria; Yang, Yimin; Dorbala, Pranav; Buckley, Leo; Claggett, Brian; Skali, Hicham; Dufresne, Line; Yang, Ta-Yu; Engert, James C; Thanassoulis, George; Floyd, James; et al. (J Am Coll Cardiol, 2024)
BACKGROUND: Limited data exist regarding risk factors for aortic stenosis (AS). The plasma proteome is a promising phenotype for discovery of novel biomarkers and potentially causative mechanisms. OBJECTIVES: The aim of this study was to discover novel biomarkers with potentially causal associations with AS. METHODS: We measured 4,877 plasma proteins (SomaScan aptamer-affinity assay) among ARIC (Atherosclerosis Risk In Communities) study participants in mid-life (visit 3 [V3]; n = 11,430; age 60 ± 6 years) and in late-life (V5; n = 4,899; age 76 ± 5 years). We identified proteins cross-sectionally associated with aortic valve (AV) peak velocity (AVmax) and dimensionless index by echocardiography at V5 and with incident AV-related hospitalization after V3 with the use of multivariable linear and Cox proportional hazard regression. We assessed associations of candidate proteins with changes in AVmax over 6 years and with AV calcification with the use of cardiac computed tomography, replicated analysis in an independent sample, performed Mendelian randomization, and evaluated gene expression in explanted human AV tissue. RESULTS: Fifty-two proteins cross-sectionally were associated with AVmax and dimensionless index at V5 and with risk of incident AV-related hospitalization after V3. Among 3,413 participants in the Cardiovascular Health Study, 6 of those proteins were significantly associated with adjudicated moderate or severe AS, including matrix metalloproteinase 12 (MMP12), complement C1q tumor necrosis factor-related protein 1 (C1QTNF1), and growth differentiation factor-15. MMP12 was also associated with greater increase in AVmax over 6 years, greater degree of AV calcification, and greater expression in calcific compared with normal or fibrotic AV tissue. C1QTNF1 had consistent potential causal effects on both AS and AVmax according to Mendelian randomization analysis. CONCLUSIONS: These findings identify MMP12 as a potential novel circulating biomarker of AS risk and C1QTNF1 as a new putative target to prevent AS progression.
Keywords: Aged; Aged, 80 and over; Aortic Valve; Aortic Valve Stenosis; Biomarkers; Calcinosis; Humans; Matrix Metalloproteinase 12; Middle Aged; Proteomics; Risk Factors

Levels of procoagulant factors and peak thrombin generation in relation to dementia risk in older adults: The Cardiovascular Health Study. - Harrington, Laura B; Ehlert, Alexa N; Thacker, Evan L; Jenny, Nancy S; Lopez, Oscar; Cushman, Mary; Olson, Nels C; Fitzpatrick, Annette; Mukamal, Kenneth J; Jensen, Majken K (Thromb Res, 2024)
INTRODUCTION: Markers of hemostasis such as procoagulant factors and peak thrombin generation are associated with cardiovascular outcomes, but their associations with dementia risk are unclear. We aimed to evaluate prospective associations of selected procoagulant factors and peak thrombin generation with dementia risk. METHODS: We measured levels of 7 hemostatic factors (fibrinogen, factor VII coagulant activity [FVIIc], activated factor VII [FVIIa], factor VIIa-antithrombin [FVIIa-AT], factor XI antigen [FXI], peak thrombin generation, and platelet count) among participants in the Cardiovascular Health Study, a cohort of older adults free of dementia in 1992/1993 (n = 3185). Dementia was adjudicated and classified by DSM-IV criteria through 1998/1999. Cox proportional hazards models estimated hazard ratios (HRs) for any dementia associated with 1-standard deviation (SD) differences, adjusting for sociodemographic and clinical factors and APOE genotype. Secondary analyses separately evaluated the risk of vascular dementia, Alzheimer's disease, and mixed dementia. RESULTS: At baseline, participants had a median age of 73 years. Over 5.4 years of follow-up, we identified 448 dementia cases. There was no evidence of linear associations between levels of these hemostatic factors with any dementia risk (HRs per 1-SD difference ranged from 1.0 to 1.1; 95 % confidence intervals included 1.0). Results of secondary analyses by dementia subtype were similar. CONCLUSIONS: In this prospective study, there was no strong evidence of linear associations between levels of fibrinogen, FVIIc, FVIIa, FVIIa-AT, FXI, peak thrombin generation, or platelet count with dementia risk. Despite their associations with cardiovascular disease, higher levels of these biomarkers measured among older adults may not reflect dementia risk.
Keywords: Aged; Anticoagulants; Antithrombin III; Antithrombins; Dementia; Factor VIIa; Fibrinogen; Hemostatics; Humans; Prospective Studies; Thrombin

Multi-omics and pathway analyses of genome-wide associations implicate regulation and immunity in verbal declarative memory performance. - Mei, Hao; Simino, Jeannette; Li, Lianna; Jiang, Fan; Bis, Joshua C; Davies, Gail; Hill, W David; Xia, Charley; Gudnason, Vilmundur; Yang, Qiong; Lahti, Jari; Smith, Jennifer A; et al. (Alzheimers Res Ther, 2024)
BACKGROUND: Uncovering the functional relevance underlying verbal declarative memory (VDM) genome-wide association study (GWAS) results may facilitate the development of interventions to reduce age-related memory decline and dementia. METHODS: We performed multi-omics and pathway enrichment analyses of paragraph (PAR-dr) and word list (WL-dr) delayed recall GWAS from 29,076 older non-demented individuals of European descent. We assessed the relationship between single-variant associations and expression quantitative trait loci (eQTLs) in 44 tissues and methylation quantitative trait loci (meQTLs) in the hippocampus. We determined the relationship between gene associations and transcript levels in 53 tissues, annotation as immune genes, and regulation by transcription factors (TFs) and microRNAs. To identify significant pathways, gene set enrichment was tested in each cohort and meta-analyzed across cohorts. Analyses of differential expression in brain tissues were conducted for pathway component genes. RESULTS: The single-variant associations of VDM showed significant linkage disequilibrium (LD) with eQTLs across all tissues and meQTLs within the hippocampus. Stronger WL-dr gene associations correlated with reduced expression in four brain tissues, including the hippocampus. More robust PAR-dr and/or WL-dr gene associations were intricately linked with immunity and were influenced by 31 TFs and 2 microRNAs. Six pathways, including type I diabetes, exhibited significant associations with both PAR-dr and WL-dr. These pathways included fifteen MHC genes intricately linked to VDM performance, showing diverse expression patterns based on cognitive status in brain tissues. CONCLUSIONS: VDM genetic associations influence expression regulation via eQTLs and meQTLs. The involvement of TFs, microRNAs, MHC genes, and immune-related pathways contributes to VDM performance in older individuals.
Keywords: Aged; Cognition; Genome-Wide Association Study; Humans; Memory; MicroRNAs; Multiomics; Polymorphism, Single Nucleotide

{Multi-trait analysis characterizes the genetics of thyroid function and identifies causal associations with clinical implications - Sterenborg, R. B. T. M.; Steinbrenner, I.; Li, Y.; Bujnis, M. N.; Naito, T.; Marouli, E.; Galesloot, T. E.; Babajide, O.; Andreasen, L.; Astrup, A.; svold, B. O.; Bandinelli, S.; et al. (Nat Commun, 2024)
T3, whereas the FT4 associations represent the thyroid hormone metabolism. Polygenic risk score and Mendelian randomization analyses showed the effects of genetically determined variation in thyroid function on various clinical outcomes, including cardiovascular risk factors and diseases, autoimmune diseases, and cancer. In conclusion, our results improve the understanding of thyroid hormone physiology and highlight the pleiotropic effects of thyroid function on various diseases.

Role of Polyunsaturated Fat in Modifying Cardiovascular Risk Associated With Family History of Cardiovascular Disease: Pooled De Novo Results From 15 Observational Studies. - Laguzzi, Federica; Åkesson, Agneta; Marklund, Matti; Qian, Frank; Gigante, Bruna; Bartz, Traci M; Bassett, Julie K; Birukov, Anna; Campos, Hannia; Hirakawa, Yoichiro; Imamura, Fumiaki; Jäger, Susanne; et al. (Circulation, 2024)
BACKGROUND: It is unknown whether dietary intake of polyunsaturated fatty acids (PUFA) modifies the cardiovascular disease (CVD) risk associated with a family history of CVD. We assessed interactions between biomarkers of low PUFA intake and a family history in relation to long-term CVD risk in a large consortium. METHODS: Blood and tissue PUFA data from 40 885 CVD-free adults were assessed. PUFA levels ≤25th percentile were considered to reflect low intake of linoleic, alpha-linolenic, and eicosapentaenoic/docosahexaenoic acids (EPA/DHA). Family history was defined as having ≥1 first-degree relative who experienced a CVD event. Relative risks with 95% CI of CVD were estimated using Cox regression and meta-analyzed. Interactions were assessed by analyzing product terms and calculating relative excess risk due to interaction. RESULTS: After multivariable adjustments, a significant interaction between low EPA/DHA and family history was observed (product term pooled RR, 1.09 [95% CI, 1.02-1.16]; =0.01). The pooled relative risk of CVD associated with the combined exposure to low EPA/DHA, and family history was 1.41 (95% CI, 1.30-1.54), whereas it was 1.25 (95% CI, 1.16-1.33) for family history alone and 1.06 (95% CI, 0.98-1.14) for EPA/DHA alone, compared with those with neither exposure. The relative excess risk due to interaction results indicated no interactions. CONCLUSIONS: A significant interaction between biomarkers of low EPA/DHA intake, but not the other PUFA, and a family history was observed. This novel finding might suggest a need to emphasize the benefit of consuming oily fish for individuals with a family history of CVD.
Keywords: Animals; Biomarkers; Cardiovascular Diseases; Docosahexaenoic Acids; Fatty Acids, Omega-3; Risk Factors

X-chromosome and kidney function: evidence from a multi-trait genetic analysis of 908,697 individuals reveals sex-specific and sex-differential findings in genes regulated by androgen response elements. - Scholz, Markus; Horn, Katrin; Pott, Janne; Wuttke, Matthias; Kühnapfel, Andreas; Nasr, M Kamal; Kirsten, Holger; Li, Yong; Hoppmann, Anselm; Gorski, Mathias; Ghasemi, Sahar; Li, Man; et al. (Nat Commun, 2024)
X-chromosomal genetic variants are understudied but can yield valuable insights into sexually dimorphic human traits and diseases. We performed a sex-stratified cross-ancestry X-chromosome-wide association meta-analysis of seven kidney-related traits (n = 908,697), identifying 23 loci genome-wide significantly associated with two of the traits: 7 for uric acid and 16 for estimated glomerular filtration rate (eGFR), including four novel eGFR loci containing the functionally plausible prioritized genes ACSL4, CLDN2, TSPAN6 and the female-specific DRP2. Further, we identified five novel sex-interactions, comprising male-specific effects at FAM9B and AR/EDA2R, and three sex-differential findings with larger genetic effect sizes in males at DCAF12L1 and MST4 and larger effect sizes in females at HPRT1. All prioritized genes in loci showing significant sex-interactions were located next to androgen response elements (ARE). Five ARE genes showed sex-differential expressions. This study contributes new insights into sex-dimorphisms of kidney traits along with new prioritized gene targets for further molecular research.
Keywords: Androgens; Chromosomes, Human, X; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Kidney; Male; Polymorphism, Single Nucleotide; Response Elements; Tetraspanins